2.5% efficient organic plastic solar cells - Shaheen, Sean E.; Brabec, Christoph; Sariciftci, N. Serdar; et al. (Applied Physics Letters, 2001)
We show that the power conversion efficiency of organic photovoltaic devices based on a conjugated polymer/methanofullerene blend is dramatically affected by molecular morphology. By structuring the blend to be a more intimate mixture that contains less phase segregation of methanofullerenes, and simultaneously increasing the degree of interactions between conjugated polymer chains, we have fabricated a device with a power conversion efficiency of 2.5% under AM1.5 illumination. This is a nearly threefold enhancement over previously reported values for such a device, and it approaches what is needed for the practical use of these devices for harvesting energy from sunlight. © 2001 American Institute of Physics.

2D-3D heterostructure enables scalable coating of efficient low-bandgap Sn–Pb mixed perovskite solar cells - Zeng, Linxiang; Chen, Zongao; Qiu, Shudi; Hu, Jinlong; Li, Chaohui; Liu, Xianhu; Liang, Guangxing; Brabec, Christoph; Mai, Yaohua; Guo, Fei (Nano Energy, 2019)
Low-bandgap photovoltaic absorbers based on mixed tin-lead (Sn–Pb) halide perovskites offer promising opportunities to fabricate efficient multi-junction solar cells. However, the current Sn–Pb mixed perovskite solar cells (PSCs) were mainly prepared using lab-scale spin-coating, greatly hindering their application for large-area device fabrication. Here, we report a simple and robust methodology for scalable deposition of dense and uniform Sn–Pb mixed perovskite films by one-step blade coating. High quality perovskite films with different Sn–Pb ratios are readily prepared by vacuuming the freshly coated precursor films followed by an anneal process. Solar cells based on these bladed Sn–Pb mixed perovskite absorbers showed decent photovoltaic behaviors. Further enhancement of device performance was realized via surface defects passivation using phenethylammonium bromide (PEABr). It was found that the formation of a thin layer of 2D Ruddlesden-Popper perovskite on top of 3D bulk perovskite significantly suppressed charge recombination. As a consequence, the open-circuit voltage (VOC) of the solar cells (Eg = 1.35 eV) was dramatically lifted from 0.71 V to 0.78 V, yielding high efficiencies of over 15%. Moreover, notable improvement in shelf and moisture stability was observed due to the protection barrier of the 2D perovskite capping layer.
CRIS-Team Scopus Importer:2019-09-24
Keywords: 2D-3D heterostructure; Blade coating; Low bandgap; Perovskite solar cells; Sn–Pb mixed perovskite; Vacuum-assisted crystallization

4H-1,2,6-Thiadiazin-4-one-containing small molecule donors and additive effects on their performance in solution-processed organic solar cells - Hermerschmidt, Felix; Kalogirou, Andreas S.; Min, Jie; Zissimou, Georgia A.; Tuladhar, Sachetan M.; Ameri, Tayebeh; Faber, Hendrik; Itskos, Grigorios; Choulis, Stelios A.; Anthopoulos, Thomas D.; Bradley, Donal D. C.; Nelson, Jenny; et al. (Journal of Materials Chemistry C, 2015)
The optical, electrochemical, morphological and transport properties of a series of thiadiazinone (acceptor) and (thienyl)carbazoles (donor) containing π-extended donor-acceptor-donors (D-A-D) are presented. Systematic variations in the number of the thienyl units, the choice of branched or straight alkyl side chains and the use of a processing additive demonstrate their use as electron donors in bulk heterojunction solar cells blended with fullerene acceptors. The best power conversion efficiency (PCE) of 2.7% is achieved by adding to the D-A-D 3:fullerene blend a polydimethylsiloxane (PDMS) additive, that improves the morphology and doubles the hole mobility within the D-A-D:fullerene blend.

A Bayesian Approach to Predict Solubility Parameters - Sanchez-Lengeling, Benjamin; Roch, Loïc; Perea Ospina, Jose Dario; Langner, Stefan; Brabec, Christoph; Aspuru-Guzik, Alan (Advanced Theory and Simulations, 2019)
Solubility is a ubiquitous phenomenon in many aspects of material science. While solubility can be determined by considering the cohesive forces in a liquid via the Hansen solubility parameters (HSP), quantitative structure-property relationship models are often used for prediction, notably due to their low computational cost. Here, gpHSP, an interpretable and versatile probabilistic approach to determining HSP, is reported. Our model is based on Gaussian processes, a Bayesian machine learning approach that provides uncertainty bounds to prediction. gpHSP achieves its flexibility by leveraging a variety of input data, such as SMILES strings, COSMOtherm simulations, and quantum chemistry calculations. gpHSP is built on experimentally determined HSP, including a general solvents set aggregated from the literature, and a polymer set experimentally characterized by this group of authors. In all sets, a high degree of agreement is obtained, surpassing well-established machine learning methods. The general applicability of gpHSP to miscibility of organic semiconductors, drug compounds, and in general solvents is demonstrated, which can be further extended to other domains. gpHSP is a fast and accurate toolbox, which could be applied to molecular design for solution processing technologies.
Keywords: machine learning; miscibility; organic materials; polymers; solubility

A Benchmark for Visual Identification of Defective Solar Cells in Electroluminescence Imagery - Buerhop-Lutz, Claudia; Deitsch, Sergiu; Maier, Andreas; Gallwitz, Florian; Berger, Stephan; Doll, Bernd; Hauch, Jens; Camus, Christian; Brabec, Christoph (35th European Photovoltaic Solar Energy Conference and Exhibition, 2018)
In this paper a dataset consisting of 2,426 solar cells extracted from high-resolution electroluminescence (EL) images is used for automated defect probability recognition. The collected images contain both functional and defective solar cells with varying degrees of degradation both in monocrystalline and polycrystalline solar modules. The images were labeled by expert who categorized the solar cells by the likelihood of a defect within each image. The labeled images can be used for development of computer vision and machine learning methods for automatic detection of different defects, like cracks, fracture interconnects, PID, and cell quality and for the purpose of predicting the power efficiency los
Keywords: EL Imaging; Machine Learning; Visual Inspection

A bilayer conducting polymer structure for planar perovskite solar cells with over 1,400 hours operational stability at elevated temperatures - Zhao, Yicheng; Heumueller, Thomas; Zhang, Jiyun; Luo, Junsheng; Kasian, Olga; Langner, Stefan; Kupfer, Christian; Liu, Bowen; Zhong, Yu; Elia, Jack; Osvet, Andres; Wu, Jianchang; et al. (Nature Energy, 2021)
The long-term stability of perovskite solar cells remains a challenge. Both the perovskite layer and the device architecture need to endure long-term operation. Here we first use a self-constructed high-throughput screening platform to find perovskite compositions stable under heat and light. Then, we use the most stable perovskite composition to investigate the stability of contact layers in solar cells. We report on the thermal degradation mechanism of transition metal oxide contact (for example, Ta-WOx/NiOx) and propose a bilayer structure consisting of acid-doped polymer stacked on dopant-free polymer as an alternative. The dopant-free polymer provides an acid barrier between the perovskite and the acid-doped polymer. The bilayer structure exhibits stable ohmic contact at elevated temperatures and buffers iodine vapours. The unencapsulated device based on the bilayer contact (with a MgF2 capping layer) retains 99% of its peak efficiency after 1,450 h of continuous operation at 65 degrees C in a N-2 atmosphere under metal-halide lamps. The device also shows negligible hysteresis during the entire ageing period.
CRIS-Team WoS Importer:2021-12-24

Abnormal strong burn-in degradation of highly efficient polymer solar cells caused by spinodal donor-acceptor demixing - Li, Ning; Perea, José Darío; Kassar, Thaer; Richter, Moses; Heumüller, Thomas; Matt, Gebhard; Hou, Yi; Güldal, Nusret Sena; Chen, Haiwei; Chen, Shi; Langner, Stefan; Berlinghof, Marvin; et al. (Nature Communications, 2017)
The performance of organic solar cells is determined by the delicate, meticulously optimized bulk-heterojunction microstructure, which consists of finely mixed and relatively separated donor/acceptor regions. Here we demonstrate an abnormal strong burn-in degradation in highly efficient polymer solar cells caused by spinodal demixing of the donor and acceptor phases, which dramatically reduces charge generation and can be attributed to the inherently low miscibility of both materials. Even though the microstructure can be kinetically tuned for achieving high-performance, the inherently low miscibility of donor and acceptor leads to spontaneous phase separation in the solid state, even at room temperature and in the dark. A theoretical calculation of the molecular parameters and construction of the spinodal phase diagrams highlight molecular incompatibilities between the donor and acceptor as a dominant mechanism for burn-in degradation, which is to date the major short-time loss reducing the performance and stability of organic solar cells.

Absence of Charge Transfer State Enables Very Low V-OC Losses in SWCNT:Fullerene Solar Cells - Classen, Andrej; Einsiedler, Lukas; Heumuelier, Thomas; Graf, Arko; Brohmann, Maximilian; Berger, Felix; Kahmann, Simon; Richter, Moses; Matt, Gebhard; Forberich, Karen; Zaumseil, Jana; Brabec, Christoph (Advanced Energy Materials, 2019)
Current state-of-the-art organic solar cells (OSCs) still suffer from high losses of open-circuit voltage (V-OC). Conventional polymer:fullerene solar cells usually exhibit bandgap to V-OC losses greater than 0.8 V. Here a detailed investigation of V-OC is presented for solution-processed OSCs based on (6,5) single-walled carbon nanotube (SWCNT): [6,6]-phenyl-C-71-butyric acid methyl ester active layers. Considering the very small optical bandgap of only 1.22 eV of (6,5) SWCNTs, a high V-OC of 0.59 V leading to a low E-gap/q - V-OC = 0.63 V loss is observed. The low voltage losses are partly due to the lack of a measurable charge transfer state and partly due to the narrow absorption edge of SWCNTs. Consequently, V-OC losses attributed to a broadening of the band edge are very small, resulting in V-OC,V-SQ - V-OC,V-rad = 0.12 V. Interestingly, this loss is mainly caused by minor amounts of SWCNTs with smaller bandgaps as well as (6,5) SWCNT trions, all of which are experimentally well resolved employing Fourier transform photocurrent spectroscopy. In addition, the low losses due to band edge broadening, a very low voltage loss are also found due to nonradiative recombination, Delta V-OC,V-nonrad = 0.26 V, which is exceptional for fullerene-based OSCs.
Keywords: all-carbon absorbers; charge transfer state; organic photovoltaics; single-walled carbon nanotubes; V-OC loss analysis

Accelerated degradation of Al3+ doped ZnO thin films using damp heat test - Litzov, Ivan; Azimi, Seyed Hamed; Matt, Gebhard; Kubis, Peter; Stubhan, Tobias; Popov, Georgi; Brabec, Christoph (Organic Electronics, 2014)
Two different types of aluminum-doped zinc oxide (AZO) thin films were fabricated using low cost sol-gel technique. By applying damp heat testing, the optical and electrical properties of those films were investigated under the influence of accelerated degradation from moisture or moisture vapor. Complementary measurements of optical transmittance, work function, and conductivity allowed exploring the degradation of AZO thin films and the corresponding OPV devices. We found that optical properties like transmittance, absorption coefficient, and band gap are not influenced by temperature and moisture. However, an increase in the work function, and a decrease in the conductivity of AZO films were observed upon damp heat exposure indicating the formation of a barrier or depletion layer at the metal oxide semiconductor interface. © 2013 Elsevier B.V. All rights reserved.
Keywords: Aluminum-doped zinc oxide; Conductivity; Damp heat test; Work function

Accelerated lifetime testing of thin-film solar cells at high irradiances and controlled temperatures - Burlafinger, Klaus; Strohm, Sebastian; Joisten, Christoph; Woiton, Michael; Classen, Andrej; Hepp, Johannes; Heumüller, Thomas; Brabec, Christoph; Vetter, Andreas (Progress in Photovoltaics, 2021)
Within this study, we investigate the intrinsic photostability of thin-film solar cells, here organic photovoltaic cells. Since degradation under natural sun light proceeds within the timeframe of months and years, the process needs to be speeded up for fast material analysis and screening, using high-concentration accelerated lifetime testing (high-C ALT). For this purpose, we established setups allowing irradiances of up to 730 sun equivalents (SE). One key finding of our study is that accelerating the testing procedure by such large intensities is possible but a precise measurement and control of the solar cell temperature is absolutely essential. Accordingly, we developed an innovative method of determining the temperature of the active layer which offers significant advantages over commonly used measurement methods. Furthermore, it was found that the degradation process under high illumination densities can be well described by a stretched exponential law. We demonstrate that the temperature kinetics of P3HT:PCBM was found to be Arrhenius governed with an activation energy of 27.2 kJ/mol under continuous illumination of 300 SE. Finally, it was shown that the velocity of light-induced degradation of short-circuit current depends linearly on the used irradiance dose at a given temperature starting from normal illumination conditions up to at least 300 SE. This makes high-C ALT a very valuable tool for swift screening of the lifetime of novel thin-film solar cells and materials.
CRIS-Team Scopus Importer:2021-11-26
Keywords: accelerated degradation; high irradiances; temperature check

Accelerating Photostability Evaluation of Perovskite Films through Intelligent Spectral Learning-Based Early Diagnosis - Liu, Ziyi; Zhang, Jiyun; Rao, Gaofeng; Peng, Zijian; Huang, Yixing; Arnold, Simon; Liu, Bowen; Deng, Can; Li, Chen; Li, Heng; Zhi, Hanxiang; Zhang, Zhi; et al. (ACS Energy Letters, 2024)
Obtaining highly stable metal-halide perovskites is crucial for the commercialization of perovskite solar cells. However, current methods for evaluating perovskite stability mainly rely on a time-consuming and resource-intensive aging process. Here, we demonstrate a spectral learning-based methodology that enables the prediction of perovskite stability by leveraging the features in photoluminescence and absorption spectra of fresh perovskite films. This methodology circumvents the long-term aging process by combining a custom-developed spectral feature extraction algorithm and an integrated voting machine learning model. By integration of the early diagnosis program with high-throughput experiments, the prediction accuracy for stable perovskites exceeds 86% in 160 fresh samples. The universality is further examined by another batch of 224 fresh samples fabricated through different processing conditions. Finally, the early diagnosis of perovskite films is successfully translated to enhanced stability in perovskite solar cells. Our work provides a new pathway to accelerate the discovery and development of stable perovskite films.
Created from Fastlane, Scopus look-up

Accelerating the discovery of materials for clean energy in the era of smart automation - Tabor, Daniel P.; Roch, Loic M.; Saikin, Semion K.; Kreisbeck, Christoph; Sheberla, Dennis; Montoya, Joseph H.; Dwaraknath, Shyam; Aykol, Muratahan; Ortiz, Carlos; Tribukait, Hermann; Amador-Bedolla, Carlos; Brabec, Christoph; et al. (NATURE REVIEWS MATERIALS, 2018)
The discovery and development of novel materials in the field of energy are essential to accelerate the transition to a low-carbon economy. Bringing recent technological innovations in automation, robotics and computer science together with current approaches in chemistry, materials synthesis and characterization will act as a catalyst for revolutionizing traditional research and development in both industry and academia. This Perspective provides a vision for an integrated artificial intelligence approach towards autonomous materials discovery, which, in our opinion, will emerge within the next 5 to 10 years. The approach we discuss requires the integration of the following tools, which have already seen substantial development to date: high-throughput virtual screening, automated synthesis planning, automated laboratories and machine learning algorithms. In addition to reducing the time to deployment of new materials by an order of magnitude, this integrated approach is expected to lower the cost associated with the initial discovery. Thus, the price of the final products (for example, solar panels, batteries and electric vehicles) will also decrease. This in turn will enable industries and governments to meet more ambitious targets in terms of reducing greenhouse gas emissions at a faster pace.

Acenequinocumulenes: Lateral and vertical π-extended analogs of tetracyanoquinodimethane (TCNQ) - Gruber, Marco; Padberg, Kevin; Min, Jie; Waterloo, Andreas; Hampel, Frank; Maid, Harald; Ameri, Tayebeh; Brabec, Christoph; Tykwinski, Rik (Chemistry - A European Journal, 2017)
We have designed a series of molecules and developed synthetic methodology that allows for the inclusion of structural diversity along both the lateral and vertical axes of the basic TCNQ skeleton. In the lateral direction, benzoannulation extends the π-system through (hetero)acene formation, while incorporation of a [3]cumulene increases delocalization vertically. The potential of these new molecules as semiconductors is explored through UV-vis spectroscopy, cyclic voltammetry, X-ray crystallography, thin film formation, and mobility measurements (via space charge limited current measurements
Keywords: pentacenes; donor-acceptor; organic materials; cumulenes; synthetic methodology

Achieving efficient and stabilized organic solar cells by precisely controlling the proportion of copolymerized units in electron-rich polymers - Xie, Qian; Cui, Yongjie; Chen, Zeng; Zhang, Ming; Liu, Chao; Zhu, Haiming; Liu, Feng; Brabec, Christoph; Liao, Xunfan; Chen, Yiwang (Nanoscale, 2022)
A series of random polymers based on the donor polymer PM6 were designed from the perspective of regulating the surface electrostatic potential (ESP) distribution of the polymers and applied in organic solar cells (OSCs). Random polymers with different ESPs were obtained by introducing structural units of polymer PM6 into the polymer structure as the third unit. The simulation results showed that the random polymers feature a wider electron-donating region after the introduction of BDT units, indicating a more efficient charge generation probability. Benefiting from the optimized morphology of the active layer and the stronger interaction between the donor and the acceptor in the active layer, the device exhibited the best charge transport efficiency and lower charge recombination after the introduction of 5% BDT units, and a high power conversion efficiency (PCE) of 16.76% was achieved. In addition, OSC devices based on random polymers incorporating 5% BDT units exhibit excellent device stability. In contrast, the devices based on random polymers after the introduction of BDD units showed a much lower PCE of around 13% due to the inferior charge generation and charge transport. This work not only provides a new perspective for the molecular design of efficient random polymers, but also demonstrates that the OSC devices based on random polymers can still achieve better stability.
CRIS-Team WoS Importer:2022-12-09

Achieving High External Quantum Efficiency for ITIC-Based Organic Solar Cells with Negligible Homo Energy Offsets - Du, Huijun; An, Kang; Wang, Rong; Yin, Zhipeng; Peng, Feng; Lüer, Larry; Brabec, Christoph; Ying, Lei; Li, Ning (Advanced Energy Materials, 2024)
Minimizing energy loss in organic solar cells (OSCS) is critical for attaining high photovoltaic performance. Among the parameters that correlated to photovoltaic performance, the energy offsets between donor–acceptor pairs play a vital role in photoelectric conversion processes. For so far reported a large number of non-fullerene acceptors (NFAs), only Y6 and its derivatives can achieve external quantum efficiencies (EQEs) over 80% with negligible energy offsets when combined with polymeric donors. Thus, understanding the relationship between energy offsets and energy losses in representative NFAs is the key to further enhancing the efficiency of OSCs. In this study, a series of wide-bandgap polymer donors based on pyrrolo[3,4-f]benzotriazole-5,7(6H)-dione (TzBI) and benzo[1,2-c:4,5-c′] dithiophene-4,8-dione building blocks are combined with representative NFAs, including ITIC and Y6, to gain deep insights into their photovoltaic performances and related energy losses. Outstanding EQEs (≈70%) and suppressed non-radiative recombination are achieved at negligible energy offsets. Moreover, it is noted that a prolonged exciton lifetime of acceptor is not essential to obtain high EQEs in OSCs with negligible energy offsets. Eventually, ITIC derivatives with high electroluminescence efficiencies and near-infrared absorptions have the potential to be assembled to obtain high-efficiency OSCs.
CRIS-Team Scopus Importer:2024-02-16
Keywords: energy offsets; external quantum efficiency; non-fullerene acceptors; non-radiative energy loss

Achieving over 17% efficiency of ternary all-polymer solar cells with two well-compatible polymer acceptors - Sun, Rui; Wang, Wei; Yu, Han; Chen, Zeng; Xia, Xinxin; Shen, Hao; Guo, Jing; Shi, Mumin; Zheng, Yina; Wu, Yao; Yang, Wenyan; Wang, Tao; et al. (Joule, 2021)
The field of all-polymer solar cells (all-PSCs) has experienced rapid development during the past few years, mainly driven by the design of efficient polymer acceptors (PAs). However, the polymer/polymer blend systems still lag far behind polymer/small molecule acceptor counterparts in power conversion efficiencies (PCEs). Here, we designed a near-infrared PA PY2F-T and paired it with polymer donor PM6 to fabricate all-PSCs with 15.0% PCE. Afterwards, PYT as the third component was introduced into the PM6:PY2F-T host system. Because of the complementary absorption bands and finely tuned microstructures of the ternary blend, the PCE is improved up to 17.2%, with the external quantum efficiency over 80% in visible and near-infrared spectral regions. Impressively, the ternary blend exhibited less energy loss, better light-soaking and photo-thermal stabilities than did the corresponding binary systems. This work promotes the development of high-performance ternary all-polymer systems and heralds a brighter future for accelerating the possible applications of all-PSCs.
CRIS-Team Scopus Importer:2021-07-09
Keywords: absorption coefficient; all-polymer solar cells; energy loss; polymer acceptor; stability

A combination of Al-doped ZnO and a conjugated polyelectrolyte interlayer for small molecule solution-processed solar cells with an inverted structure - Min, Jie; Zhang, Hong; Stubhan, Tobias; Luponosov, Yuriy N.; Kraft, Mario; Ponomarenko, Sergei A.; Ameri, Tayebeh; Scherf, Ullrich; Brabec, Christoph (Journal of Materials Chemistry A, 2013)
We successfully demonstrate a smart strategy to use aluminum doped ZnO (AZO) and the thiophene-based conjugated polyelectrolyte P3TMAHT as an interfacial layer in small molecule solution-processed inverted solar cells. Modification of AZO with a thin P3TMAHT layer increases the photovoltaic properties of the inverted cell as a result of reduction in the work function of the cathode with well aligned frontier orbital energy levels for efficient charge transport and reduced surface recombination. The inverted device achieved 16% performance improvement dominantly by recapturing part of the Voc losses when going from conventional to the inverted architecture. In addition, the inverted device using the AZO/P3TMAHT interlayer shows improved device stability in air compared to conventional devices.
Keywords: Aluminum-doped ZnO; Conjugated polyelectrolytes; Frontier orbital energies; Inverted architectures; Inverted solar cells; Photovoltaic property; Solution-processed; Surface recombinations Engineering controlled terms: Molecules; Polyelectrolytes; Zinc oxide Engineering main heading: Solar cells

A comparison between state-of-the-art 'gilch' and 'sulphinyl' synthesised MDMO-PPV/PCBM bulk hetero-junction solar cells - Munters, T.; Martens, T.; Goris, L.; Vrindts, V.; Manca, J.; Lutsen, L.; De Ceuninck, W.; Vanderzande, D.; De Schepper, L.; Gelan, J.; Sariciftci, Niyazi Serdar; Brabec, Christoph (Thin Solid Films, 2002)
To obtain photovoltaic devices based on electron donating conjugated polymers with a higher efficiency, a major breakthrough was realised by mixing the polymers with a suitable electron acceptor, thereby enhancing the rate for photo-induced charge generation by several orders. State-of-the-art organic bulk hetero-junction photovoltaic cells are based on an interpenetrating donor-acceptor network in the bulk to form efficient nanostructured p-n junctions in the organic materials. Devices made with 'Gilch' poly(2-methoxy-5-(3′,7′-dimethyl-octyloxy))-p-phenylene vinylene, (MDMO-PPV), as an electron donor and (6,6)-phenyl-C-butyric-acid (PCBM) (a soluble C60 derivative) as an electron acceptor yielded the highest efficiency until now in this class of devices. A power conversion efficiency of approximately η≥2.5% (electrical power out/incident light power) under AM 1.5 illumination was reported. The 'gilch' route is a direct synthetic route. The 'sulphinyl' route is a promising, indirect precursor-route towards MDMO-PPV. Due to the non-symmetric monomer, so-called 'head-to-head' and 'tail-to-tail' additions are excluded to a higher level in comparison to the 'gilch' route. This difference between both materials makes them interesting candidates to compare them in the state-of-the-art photovoltaic devices. Preliminary results indicate that the 'sulphinyl' MDMO-PPV/PCBM bulk hetero-junction solar cells attain a power conversion efficiency of nearly η=3% (electrical power out/incident light power), have a higher fill factor, incident photon per converted electron value (IPCE) and short circuit current. It is indicated that the observed solar cell characteristics are related to the defect level of the conjugated polymer used. © 2002 Elsevier Science B.V. All rights reserved.
Keywords: Gilch; Hetero-junction solar cells; MDMO-PPV; OCICIO; Organic photovoltaics; Organic solar cell; PCBM; PPV; Sulphinyl

A conformally bonded molecular interface retarded iodine migration for durable perovskite solar cells - Yuan, Ligang; Zhu, Weiya; Zhang, Yiheng; Li, Yuan; Chan, Christopher C. S.; Qin, Minchao; Qiu, Jianhang; Zhang, Kaicheng; Huang, Jiaxing; Wang, Jiarong; Luo, Huiming; Zhang, Zheng; et al. (Energy and Environmental Science, 2023)
State-of-the-art n-i-p perovskite solar cells (PSCs) suffer from stability issues due to ionic interdiffusion. Herein, by enlarging the indacenodithiophene π-bridge donor (D′) to combine with the methoxy triphenylamine donor (D) and benzothiadiazole acceptor (A), three linear molecules termed L1, L2 and L3 with a D-A-D′-A-D structure are developed as dopant-free hole transport materials (HTMs). The π-bridge extension with active sites for coordination leverages the intramolecular dipole effect and intermolecular packing effect, resulting in a conformally bonded ultrathin interface with compact and uniform coverage (∼60 nm) to retard iodine migration and protect the buried perovskite. The unencapsulated L3-PSC (ITO/SnO2/perovskite/L3/MoO3/Au) achieved an impressive PCE of 22.61% (certified 21.79%, 0.0525 cm2). Ultrafast laser spectroscopy reveals that L-series molecules have a sequential reduction of photoexcited energy disorder to illustrate the structure-performance-stability relationship. L3-PSC maintains over 85% of the initial efficiency after 500 h at 85 °C maximum power point tracking (MPP) and enables the possibility of using small molecules to stabilize n-i-p PSCs.
CRIS-Team Scopus Importer:2023-05-05

A Cost-Effective, Aqueous-Solution-Processed Cathode Interlayer Based on Organosilica Nanodots for Highly Efficient and Stable Organic Solar Cells - Cui, Mengqi; Li, Dan; Du, Xiaoyan; Li, Na; Rong, Qikun; Li, Ning; Shui, Lingling; Zhou, Guofu; Wang, Xinghua; Brabec, Christoph; Nian, Li (Advanced Materials, 2020)
The performance and industrial viability of organic photovoltaics are strongly influenced by the functionality and stability of interface layers. Many of the interface materials most commonly used in the lab are limited in their operational stability or their materials cost and are frequently not transferred toward large-scale production and industrial applications. In this work, an advanced aqueous-solution-processed cathode interface layer is demonstrated based on cost-effective organosilica nanodots (OSiNDs) synthesized via a simple one-step hydrothermal reaction. Compared to the interface layers optimized for inverted organic solar cells (i-OSCs), the OSiNDs cathode interlayer shows improved charge carrier extraction and excellent operational stability for various model photoactive systems, achieving a remarkably high power conversion efficiency up to 17.15%. More importantly, the OSiNDs’ interlayer is extremely stable under thermal stress or photoillumination (UV and AM 1.5G) and undergoes no photochemical reaction with the photoactive materials used. As a result, the operational stability of inverted OSCs under continuous 1 sun illumination (AM 1.5G, 100 mW cm−2) is significantly improved by replacing the commonly used ZnO interlayer with OSiND-based interfaces.
CRIS-Team Scopus Importer:2020-08-21
Keywords: cathode interlayers; device stability; organic photovoltaics; organosilica nanodots; photostability

A Cross-Linked Interconnecting Layer Enabling Reliable and Reproducible Solution-Processing of Organic Tandem Solar Cells - Liu, Chao; Du, Xiaoyan; Gao, Shuai; Classen, Andrej; Osvet, Andres; He, Yakun; Mayrhofer, Karl; Li, Ning; Brabec, Christoph (Advanced Energy Materials, 2020)
The performance of tandem organic solar cells (OSCs) is directly related to the functionality and reliability of the interconnecting layer (ICL). However, it is a challenge to develop a fully functional ICL for reliable and reproducible fabrication of solution-processed tandem OSCs with minimized optical and electrical losses, in particular for being compatible with various state-of-the-art photoactive materials. Although various ICLs have been developed to realize tandem OSCs with impressively high performance, their reliability, reproducibility, and generic applicability are rarely analyzed and reported so far, which restricts the progress and widespread adoption of tandem OSCs. In this work, a robust and fully functional ICL is developed by incorporating a hydrolyzed silane crosslinker, (3-glycidyloxypropyl)trimethoxysilane (GOPS), into poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), and its functionality for reliable and reproducible fabrication of tandem OSCs based on various photoactive materials is validated. The cross-linked ICL can successfully protect the bottom active layer against penetration of high boiling point solvents during device fabrication, which widely broadens the solvent selection for processing photoactive materials with high quality and reliability, providing a great opportunity to continuously develop the tandem OSCs towards future large-scale production and commercialization.
CRIS-Team Scopus Importer:2020-02-25
Keywords: (3-glycidyloxypropyl)trimethoxysilane; cross-linking; interconnecting layer; organic tandem solar cells; solution-processing

A data fusion approach to optimize compositional stability of halide perovskites - Sun, Shijing; Tiihonen, Armi; Oviedo, Felipe; Liu, Zhe; Thapa, Janak; Zhao, Yicheng; Hartono, Noor Titan P.; Goyal, Anuj; Heumüller, Thomas; Batali, Clio; Encinas, Alex; Yoo, Jason J.; et al. (Matter, 2021)
Search for resource-efficient materials in vast compositional spaces is an outstanding challenge in creating environmentally stable perovskite semiconductors. We demonstrate a physics-constrained sequential learning framework to subsequently identify the most stable alloyed organic-inorganic perovskites. We fuse data from high-throughput degradation tests and first-principle calculations of phase thermodynamics into an end-to-end Bayesian optimization algorithm using probabilistic constraints. By sampling just 1.8% of the discretized CsxMAyFA1−x−yPbI3 (MA, methylammonium; FA, formamidinium) compositional space, perovskites centered at Cs0.17MA0.03FA0.80PbI3 show minimal optical change under increased temperature, moisture, and illumination with >17-fold stability improvement over MAPbI3. The thin films have 3-fold improved stability compared with state-of-the-art multi-halide Cs0.05(MA0.17FA0.83)0.95Pb(I0.83Br0.17)3, translating into enhanced solar cell stability without compromising conversion efficiency. Synchrotron-based X-ray scattering validates the suppression of chemical decomposition and minority phase formation achieved using fewer elements and a maximum of 8% MA. We anticipate that this data fusion approach can be extended to guide materials discovery for a wide range of multinary systems. Despite recent intensive efforts to improve the environmental stability of halide perovskite materials for energy harvesting and conversion, traditional trial-and-error explorations face bottlenecks in the navigation of vast chemical and compositional spaces. We develop a closed-loop optimization framework that seamlessly marries data from first-principle calculations and high-throughput experimentation into a single machine learning algorithm. This framework enables us to achieve rapid optimization of compositional stability for CsxMAyFA1−x−yPbI3 perovskites while taking the human out of the decision-making loop. We envision that this data fusion approach is generalizable to directly tackle challenges in designing multinary materials, and we hope that our successful showcase on perovskites will encourage researchers in other fields to incorporate knowledge of physics into the search algorithms, applying hybrid machine learning models to guide discovery of materials in high-dimensional spaces. Data fusion combines first-principle calculations and high-throughput experimentation into an end-to-end closed-loop optimization framework, allowing an accelerated search of alloyed halide perovskites in a combinatorial space without human intervention.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Bayesian optimization; data fusion; density-functional theory; energy materials; high-throughput experimentation; machine learning; MAP4: Demonstrate; perovskite stability

A digital twin to overcome long-time challenges in photovoltaics - Lüer, Larry; Peters, Ian Marius; Smith, Ana-Suncana; Dorschky, Eva; Eskofier, Björn; Liers-Bergmann, Frauke; Franke, Jörg; Sjarov, Martin; Brossog, Matthias; Guldi, Dirk Michael; Maier, Andreas; Brabec, Christoph (Joule, 2024)
The recent successes of emerging photovoltaics (PVs) are largely driven by innovations in material science. However, closing the gap to commercialization still requires significant progress to match contradicting requirements, such as performance, longevity, and recyclability. In this perspective, we envision the layout of a digital twin for PV materials able to provide the necessary acceleration of innovation. The layout combines machine learning approaches, as performed in materials acceleration platforms (MAPs), with physical models and digital twin concepts used in engineering. This layout will allow the use of high-throughput (HT) experimentation in MAPs to improve the parametrization of quantum chemical and solid-state models. In turn, the improved and generalized models can be used to obtain the crucial structural parameters. HT experimentation will thus yield a detailed understanding of generally valid structure-property relationships. We discuss the current state of the enabling technologies, namely fast scale-bridging surrogate models and large-scale optimization under uncertainty, and identify promising approaches for further development.<br
Keywords: digital twin; emerging photovoltaics; artificial intelligence; multi-scale simulations; optimization; high-throughput methods; materials acceleration platforms

Adjusting the energy of interfacial states in organic photovoltaics for maximum efficiency - Gasparini, Nicola; Camargo, Franco V.A.; Frühwald, Stefan; Nagahara, Tetsuhiko; Classen, Andrej; Roland, Steffen; Wadsworth, Andrew; Gregoriou, Vasilis G.; Chochos, Christos L.; Neher, Dieter; Salvador, Michael; Baran, Derya; et al. (Nature Communications, 2021)
A critical bottleneck for improving the performance of organic solar cells (OSC) is minimising non-radiative losses in the interfacial charge-transfer (CT) state via the formation of hybrid energetic states. This requires small energetic offsets often detrimental for high external quantum efficiency (EQE). Here, we obtain OSC with both non-radiative voltage losses (0.24 V) and photocurrent losses (EQE > 80%) simultaneously minimised. The interfacial CT states separate into free carriers with ≈40-ps time constant. We combine device and spectroscopic data to model the thermodynamics of charge separation and extraction, revealing that the relatively high performance of the devices arises from an optimal adjustment of the CT state energy, which determines how the available overall driving force is efficiently used to maximize both exciton splitting and charge separation. The model proposed is universal for donor:acceptor (D:A) with low driving forces and predicts which D:A will benefit from a morphology optimization for highly efficient OSC.
CRIS-Team Scopus Importer:2021-04-02

Advances in Lead-Free Perovskite Single Crystals: Fundamentals and Applications - Tailor, Naveen Kumar; Kar, Shaoni; Mishra, Pranjal; These, Albert; Kupfer, Christian; Hu, Hanlin; Awais, Muhammad; Saidaminov, Makhsud; Dar, M. Ibrahim; Brabec, Christoph; Satapathi, Soumitra (ACS Materials Letters, 2021)
With rapid progress in the deployment of metal halide perovskites in various device applications such as solar cells, light-emitting devices, field-effect transistors, photodetectors, etc., the next eminent focus is on the single crystals of these materials. With a lack of grain boundaries and low trap densities, remarkably long charge carrier diffusion lengths, and high ambient and operational stabilities, this class of materials seems greatly promising. Yet, the growing concern for lead toxicity in commercial semiconductor devices has entailed a thrust in the research of alternative lead-free perovskites, including their single crystalline forms. However, there is still no consolidated account of the state-of-the-art in this domain and accordingly, countless feasible systems still remain unexplored. To bridge this gap, we attempt to provide here, an up-to-date overview of lead-free perovskite single crystals with respect to their synthesis methods, structural diversity, stability, photophysical and electrical properties, and device applications. We discuss various approaches to designing, modeling, fabricating, and characterizing new single-crystal systems and conclude with some critical insights for further investigating this field of research.
CRIS-Team Scopus Importer:2021-07-16

Aerial Photoluminescence Imaging of Photovoltaic Modules - Doll, Bernd; Wittmann, Ernst; Lüer, Larry; Hepp, Johannes; Buerhop-Lutz, Claudia; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (Physica Status Solidi-Rapid Research Letters, 2023)
On-site imaging of modules in photovoltaic (PV) systems requires contact-free techniques with high throughput and low cost for commercial relevance. Photoluminescence imaging satisfies these requirements, but it has so far not been used for aerial imaging. Such a system faces unique engineering and operating challenges, including the need to mount a light source on the drone and identifying module defects from images taken under low- and nonuniform irradiance. Herein, in-house developed photoluminescence aerial imaging (PLAI) setup is presented and it is demonstrated that it can be used to identify defects even with a difference of excitation intensity of up to 50%. The setup consists of a hexacopter aerial drone equipped with an illumination unit and a near-infrared camera. The unit is capable of partially illuminating full-sized modules at night and capturing the photoluminescence response. In the maiden flight, a throughput of 13.6 PV modules per minute is achieved, and a throughput of 300 PV modules per minute is feasible. It is shown that the setup can be used to detect and identify cracks and potential induced degradation with high levels of confidence. These findings are verified by cross correlation and comparing captured photoluminescence images to electroluminescence images taken indoors.
CRIS-Team Scopus Importer:2023-05-26
Keywords: aerial inspection; photoluminescence; photovoltaic

Aerosol jet printed AgNW electrode and PEDOT:PSS layers for organic light-emitting diode devices fabrication - Hamjah, Mohd Khairulamzari; Steinberger, Marc; Tam, Kai Cheong; Egelhaaf, Hans Joachim; Brabec, Christoph; Franke, Jörg (2021 14th International Congress: Molded Interconnect Devices, MID 2021 - Proceedings, 2021)
Aerosol jet printing is a cutting-edge technology offering a plethora of advantages in organic optoelectronics fabrication. In this work, we fabricated organic light-emitting diodes on glass substrates. Silver nanowires (AgNWs) and poly (3,4-ethylene dioxythiophene) polystyrene sulfonate (PEDOT:PSS) were aerosol-jet printed as the bottom electrode and hole transport layer, respectively. The other remaining layer materials were blade coated to form a multi-layered structure of the devices. The results show that the organic lightemitting diode device with 40 mm2 active areas was successfully obtained. A comparison study of blade-coated organic light-emitting diode devices on indium tin oxide based electrode is also discussed. The results of this work show that aerosol jet printing technology enables fully solution-based fabrication of organic light-emitting diode devices.
CRIS-Team Scopus Importer:2021-04-02
Keywords: 4-ethylene dioxythiophene) polystyrene sulfonate; aerosol jet printing; organic light-emitting diode; poly(3; silver nanowires

Aerosol-Jet-Printed Encapsulation of Organic Photovoltaics - Basu, Robin; Siah, Kok Siong; Distler, Andreas; Häußler, Felix; Franke, Jörg; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Engineering Materials, 2023)
Organic electronic devices (OEDs) are prone to oxygen- and water-induced degradation and therefore need to be encapsulated with barrier materials. In this work, an aerosol jet (AJ)-printing process is developed to coat perhydropolysilazane (PHPS) directly onto OEDs by adapting the print setup and systematically optimizing the process parameters. Furthermore, a novel curing process that converts PHPS to silica barrier layers is developed by combining damp heat (DH) exposure with subsequent vacuum–UV irradiation. This two-step treatment is shown to be considerably faster and gentler than the state-of-the-art curing processes and also yields a quantitatively higher conversion. Both the printing and the conversion process are fully compatible with OED devices, which is demonstrated by a damage-free direct encapsulation of organic solar cells. The encapsulated cells show a significant reduction of degradation in DH conditions (65 °C/85% r.h.), maintaining >95% of their initial performance for >100 h. Complementary electroluminescence measurements reveal that the AJ-printed barrier layers effectively prevent lateral water ingress into the devices. Herein, the proof of principle is provided that AJ printing can be used to print barrier layers directly onto OEDs and is thus an industrially highly relevant technology to precisely encapsulate such devices even on 3D objects.
CRIS-Team Scopus Importer:2023-07-07
Keywords: aerosol jet printing; organic solar cells; perhydropolysilazane; printed barriers; solution-processed encapsulation

A facile one-step method to reduce surface impurities in solution-processed CuInS2 nanocrystal solar cells - Stahl, Melissa S.; Azimi, Seyed Hamed; Brabec, Christoph (Journal of Materials Chemistry A, 2015)
The presence of impurities and disorders presents a potential barrier for the success of solution processed inorganic nanocrystalline devices. The removal of impurities typically requires harsh conditions and complex procedures that limit utility. This paper demonstrates the successful use of a set of solvents, which can efficaciously remove the surface impurities formed during in situ deposition of CuInS2 nanocrystals. These impurities include a hard-to-remove byproduct melamine that is formed by the decomposition of thiourea at elevated temperatures, and other organic residues like amines, conjugated organic systems, as well as ketones, aldehydes or esters. This work provides some design rules for the selection of solvents for removal purposes that could potentially be used for other absorber materials as well.

Afterglow Effects as a Tool to Screen Emissive Nongeminate Charge Recombination Processes in Organic Photovoltaic Composites. - Keivanidis, Panagiotis E.; Itskos, Grigorios; Kan, Zhipeng; Aluicio-Sarduy, Eduardo; Goudarzi, Hossein; Kamm, Valentin; Laquai, Frédéric; Zhang, Weimin; Brabec, Christoph; Floudas, George; McCulloch, Iain (ACS Applied Materials and Interfaces, 2020)
Disentangling temporally overlapping charge carrier recombination events in organic bulk heterojunctions by optical spectroscopy is challenging. Here, a new methodology for employing delayed luminescence spectroscopy is presented. The proposed method is capable of distinguishing between recombination of spatially separated charge carriers and trap-assisted charge recombination simply by monitoring the delayed luminescence (afterglow) of bulk heterojunctions with a quasi time-integrated detection scheme. Applied on the model composite of the donor poly(6,12-dihydro-6,6,12,12- tetraoctyl-indeno[1,2-b]fluorene-alt-benzothiadiazole) (PIF8BT) polymer and the acceptor ethyl-propyl perylene diimide (PDI) derivative, that is, PIF8BT:PDI, the luminescence of charge-transfer (CT) states created by nongeminate charge recombination on the ns to μs timescale is observed. Fluence-dependent, quasi time-integrated detection of the CT luminescence monitors exclusively emissive charge recombination events, while rejecting the contribution of other early-time emissive processes. Trap-assisted and bimolecular charge recombination channels are identified based on their distinct dependence on fluence. The importance of the two recombination channels is correlated with the layer's order and electrical properties of the corresponding devices. Four different microstructures of the PIF8BT:PDI composite obtained by thermal annealing are investigated. Thermal annealing of PIF8BT:PDI shrinks the PDI domains in parallel with the growth of the PIF8BT domains in the blend. Common to all states studied, the delayed CT luminescence signal is dominated by trap-assisted recombination. Yet, the minor fraction of fully separated charge recombination in the overall CT emission increases as the difference in the size of the donor and acceptor domains in the PIF8BT:PDI blend becomes larger. Electric field-induced quenching measurements on complete PIF8BT:PDI devices confirm quantitatively the dominance of emissive trap-limited charge recombination and demonstrates that only 40% of the PIF8BT/PDI CT luminescence comes from the recombination of fully-separated charges, taking place within 200 ns after photoexcitation. The method is applicable to other nonfullerene acceptor blends beyond the system discussed here, if their CT state luminescence can be monitored.
Keywords: solar cell; photodetector; perylene diimides; fill factor; charge trapping; delayed luminescence; multiple-diode equivalent circuit; nonfullerene acceptors

A fulleropyrrolidine-phthalocyanine dyad for photovoltaic applications - Loi, M.A.; Denk, Patrick; Hoppe, H.; Neugebauer, H.; Meissner, Dieter; Winder, C.; Brabec, Christoph; Sariciftci, N. Serdar; Gouloumis, Andreas; Vazquez, Purificacion; Torres, Tomas (Synthetic Metals, 2003)
We report on photophysical properties of a novel dyad molecule having as antenna/donor a Zn-phthalocyanine derivative and as acceptor a C derivative covalently attached. We found evidences for long living photoinduced electron transfer in solid state. Photovoltaic action of thin film devices of the dyad is demonstrated.
Keywords: Fullerene; Photoinduced charge transfer; Phthalocyanines; Solar cells

A General Guideline for Vertically Resolved Imaging of Manufacturing Defects in Organic Tandem Solar Cells - Karl, André; Osvet, Andres; Li, Ning; Brabec, Christoph (Advanced Materials Interfaces, 2020)
Organic tandem solar cells recently made great improvements with power conversion efficiencies (PCEs) over 15%, making them attractive for further large-scale production and industrial applications. However, compared to their single-junction counterparts, the complicated device architectures of organic tandem solar cells strongly restrict their processing and upscaling to larger scales. Therefore, fast and reliable quality control measures are crucial for developing organic tandem photovoltaic technologies towards commercialization. Some of the most widely used means for quality control are luminescence imaging and lock-in thermography respectively. While effective techniques, they are limited in some respects. For example, determining the lateral position of a defect is easily possible, while the exact resolution in which layer of a thin film stack a defect is located, is challenging. This is particularly the case for tandem cells with complicated multi-layer cell architectures. This approach to overcome this challenge is the introduction of well-defined artificial defects into certain layers of an organic tandem cell stack and subsequently performing imaging analysis of the defected cells with several complementary methods. The unique response from cells with artificial defects using different imaging techniques and excitation sources can then be transferred to the imaging of devices with naturally occurring manufacturing defects.
CRIS-Team Scopus Importer:2020-05-22
Keywords: defects; imaging; organic tandem solar cells; quality control

A Generalized Crystallization Protocol for Scalable Deposition of High-Quality Perovskite Thin Films for Photovoltaic Applications - Guo, Fei; Qiu, Shudi; Hu, Jinlong; Wang, Huahua; Cai, Boyuan; Li, Jianjun; Yuan, Xiaocong; Liu, Xianhu; Forberich, Karen; Brabec, Christoph; Mai, Yaohua (Advanced Science, 2019)
Metal halide perovskite solar cells (PSCs) have raised considerable scientific interest due to their high cost-efficiency potential for photovoltaic solar energy conversion. As PSCs already are meeting the efficiency requirements for renewable power generation, more attention is given to further technological barriers as environmental stability and reliability. However, the most major obstacle limiting commercialization of PSCs is the lack of a reliable and scalable process for thin film production. Here, a generic crystallization strategy that allows the controlled growth of highly qualitative perovskite films via a one-step blade coating is reported. Through rational ink formulation in combination with a facile vacuum-assisted precrystallization strategy, it is possible to produce dense and uniform perovskite films with high crystallinity on large areas. The universal application of the method is demonstrated at the hand of three typical perovskite compositions with different band gaps. P-i-n perovskite solar cells show fill factors up to 80%, underpinning the statement of the importance of controlling crystallization dynamics. The methodology provides important progress toward the realization of cost-effective large-area perovskite solar cells for practical applications.
CRIS-Team Scopus Importer:2019-07-09
Keywords: blade coating; one-step; perovskites

A generic concept to overcome bandgap limitations for designing highly efficient multi-junction photovoltaic cells - Guo, Fei; Li, Ning; Fecher, Frank W.; Gasparini, Nicola; Ramírez Quiroz, César Omar; Bronnbauer, Carina; Hou, Yi; Radmilovic, Vuk V.; Radmilovic, Velimir R.; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (Nature Communications, 2015)
The multi-junction concept is the most relevant approach to overcome the Shockley-Queisser limit for single-junction photovoltaic cells. The record efficiencies of several types of solar technologies are held by series-connected tandem configurations. However, the stringent current-matching criterion presents primarily a material challenge and permanently requires developing and processing novel semiconductors with desired bandgaps and thicknesses. Here we report a generic concept to alleviate this limitation. By integrating series- and parallel-interconnections into a triple-junction configuration, we find significantly relaxed material selection and current-matching constraints. To illustrate the versatile applicability of the proposed triple-junction concept, organic and organic-inorganic hybrid triple-junction solar cells are constructed by printing methods. High fill factors up to 68% without resistive losses are achieved for both organic and hybrid triple-junction devices. Series/parallel triple-junction cells with organic, as well as perovskite-based subcells may become a key technology to further advance the efficiency roadmap of the existing photovoltaic technologies.
Keywords: GEOBASE Subject Index: fuel cell; photovoltaic system; solar power EMTREE medical terms: Article; electric current; electric potential; electrical equipment; multi junction photovoltaic cell

A generic interface to reduce the efficiency-stability-cost gap of perovskite solar cells - Hou, Yi; Du, Xiaoyan; Scheiner, Simon; McMeekin, David P.; Wang, Zhiping; Li, Ning; Killian, Manuela; Chen, Haiwei; Richter, Moses; Levchuk, Ievgen; Schrenker, Nadine; Spiecker, Erdmann; et al. (Science, 2017)
A major bottleneck delaying the further commercialization of thin-film solar cells based on hybrid organohalide lead perovskites is the interface losses in state-of-the-art devices. We present a generic interface architecture that combines solution-processed, reliable, and cost-efficient hole-transporting materials, without compromising efficiency, stability or scalability of perovskite solar cells. Tantalum doped tungsten oxide (Ta-WOx)/conjugated polymer multilayers offer a surprisingly small interface barrier and form quasi-ohmic contacts universally with various scalable conjugated polymers. Using a simple regular planar architecture device, Ta-WOx doped interface-based perovskite solar cells achieve maximum efficiencies of 21.2% and combined with over 1000 hours of light stability based on a self-assembled monolayer. By eliminating additional ionic dopants, these findings open up the whole class of organics as scalable hole-transporting materials for perovskite solar cell

A generic surfactant-free approach to overcome wetting limitations and its application to improve inkjet-printed P3HT:non-fullerene acceptor PV - Maisch, Philipp; Eisenhofer, Lena M.; Tam, Kai Cheong; Distler, Andreas; Voigt, Monika M.; Brabec, Christoph; Egelhaaf, Hans-Joachim (Journal of Materials Chemistry A, 2019)
Solution based thin film technology often implies challenging wetting behaviour which has to be improved in order to achieve good printing or coating qualities. A common way of solving such problems is the use of wetting agents but they often show undesired side effects. In this work, we introduce a generic strategy to overcome this problem. We demonstrate inkjet printed arrays of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate (PEDOT:PSS) dots to efficiently pin the three-phase contact line of wet films, thereby enforcing homogenous wetting and subsequent drying on low energetic surfaces. By printing and drying single droplets of ink, a matrix of anchoring points is created which pins the subsequently printed continuous wet layer and thus enables the coating of large surface areas with homogeneous, defect free films. This method also allows convenient patterning of surfaces by combining inkjet-printing of anchoring points with subsequent large area flood coating, e.g., by doctor blading. Furthermore, the defined placement of each anchoring point allows full thermodynamic control of the film formation by quantitative calculation of the processing windows and patterning precision. The beneficial application of this new strategy to printed electronics is demonstrated by fabricating organic solar cells with power conversion efficiencies of 5%. This is achieved by printing a hydrophilic PEDOT:PSS electron blocking layer without addition of surfactants at unprecedented quality onto an otherwise non-wettable hydrophobic active layer consisting of poly(3-hexylthiophene) (P3HT) and the indacenodithiophene-based non-fullerene acceptor O-IDTBR.
CRIS-Team Scopus Importer:2019-06-18

AgIn5S8/ZnS Quantum Dots for Luminescent Down-Shifting and Anti-Reflective Layer in Enhancing Photovoltaic Performance - Kong, Mengqin; Osvet, Andres; Barabash, Anastasiia; Zhang, Kaicheng; Hu, Huiying; Elia, Jack; Erban, Christof; Yokosawa, Tadahiro; Spiecker, Erdmann; Batentschuk, Miroslaw; Brabec, Christoph (ACS Applied Materials and Interfaces, 2023)

A History and Perspective of Non-Fullerene Electron Acceptors for Organic Solar Cells - Armin, Ardalan; Li, Wei; Sandberg, Oskar J.; Xiao, Zuo; Ding, Liming; Nelson, Jenny; Neher, Dieter; Vandewal, Koen; Shoaee, Safa; Wang, Tao; Ade, Harald; Heumüller, Thomas; et al. (Advanced Energy Materials, 2021)
Organic solar cells are composed of electron donating and accepting organic semiconductors. Whilst a significant palette of donors has been developed over three decades, until recently only a small number of acceptors have proven capable of delivering high power conversion efficiencies. In particular the fullerenes have dominated the landscape. In this perspective, the emergence of a family of materials–the non-fullerene acceptors (NFAs) is described. These have delivered a discontinuous advance in cell efficiencies, with the significant milestone of 20% now in sight. Intensive international efforts in synthetic chemistry have established clear design rules for molecular engineering enabling an ever-expanding number of high efficiency candidates. However, these materials challenge the accepted wisdom of how organic solar cells work and force new thinking in areas such as morphology, charge generation and recombination. This perspective provides a historical context for the development of NFAs, and also addresses current thinking in these areas plus considers important manufacturability criteria. There is no doubt that the NFAs have propelled organic solar cell technology to the efficiencies necessary for a viable commercial technology–but how far can they be pushed, and will they also deliver on equally important metrics such as stability?.
CRIS-Team Scopus Importer:2021-01-22
Keywords: non-fullerene electron acceptors; organic solar cells; review and perspective

Air-processed organic tandem solar cells on glass: Toward competitive operating lifetimes - Adams, Jens; Spyropoulos, Georgios; Salvador, Michael Filipe; Li, Ning; Strohm, Sebastian; Lucera, Luca; Langner, Stefan; Machui, Florian; Zhang, Hong; Ameri, Tayebeh; Voigt, Monika M.; Krebs, Frederik C.; et al. (Energy and Environmental Science, 2015)
Photovoltaic devices based on organic semiconductors (OPVs) hold great promise as a cost-effective renewable energy platform because they can be processed from solution and deposited on flexible plastics using roll-to-roll processing. Despite important progress and reported power conversion efficiencies of more than 10% the rather limited stability of this type of devices raises concerns towards future commercialization. The tandem concept allows for both absorbing a broader range of the solar spectrum and reducing thermalization losses. We designed an organic tandem solar cell with an inverted device geometry comprising environmentally stable active and charge-selecting layers. Under continuous white light irradiation, we demonstrate an extrapolated, operating lifetime in excess of one decade. We elucidate that for the current generation of organic tandem cells one critical requirement for long operating lifetimes consists of periodic UV light treatment. These results suggest that new material approaches towards UV-resilient active and interfacial layers may enable efficient organic tandem solar cells with lifetimes competitive with traditional inorganic photovoltaics.

Air-processed polymer tandem solar cells with power conversion efficiency exceeding 10% - Li, Ning; Brabec, Christoph (Energy and Environmental Science, 2015)
The power conversion efficiencies (PCEs) of the state-of-the-art organic tandem solar cells are steadily improved in the range of 10-12%, which can be mainly attributed to the design and development of highly efficient absorbers with complementary absorption spectra. However, the impressive recorded efficiencies are only achieved for devices spin-coated in an inert atmosphere, which does not directly contribute to the commercialization of the organic photovoltaic technology. Herein, we perform a systematic study of PTB7-Th-based single-junction solar cells fabricated under various conditions. The relatively low photovoltaic performance and poor environmental stability of the air-processed devices are successfully improved by a post-treatment with alcohol-based solvents. The effect of solvent treatment is valid for both regular and inverted device architecture. Tandem devices fabricated by doctor-blading in air achieve a high PCE of 10.03% along with an unprecedentedly high FF of 76.6%.
Keywords: Engineering controlled terms: Conversion efficiency; Efficiency; Photovoltaic cells; Solar absorbers Design and Development; Efficient absorbers; Environmental stability; Organic photovoltaics; Photovoltaic performance; Polymer tandem solar cells; Power conversion efficiencies; Single junction solar cells Engineering main heading: Solar cells

aIR-PV-check: A quality inspection of PV-power plants without operation interruption - Buerhop, Claudia; Pickel, Tobias; Dalsass, Manuel; Scheuerpflug, Hans; Camus, Christian; Brabec, Christoph (43rd IEEE Photovoltaic Specialists Conference, PVSC 2016, 2016)
aIR-PV-check is a method using an unmanned aerial vehicles (UAV) with an infrared (IR)-camera for the quality inspection of PV-plants under real operating conditions. It enables the fast and 100%-control of PV-plants. Defective modules are detected by their temperature distribution. Besides the meteorological conditions, the interaction of defective modules within a string influences the module performance significantly as the measured and simulated data show. Thus, modules with extremely high temperatures are predominantly expected / detected in strings with only one single defective module. Consequently, string configurations and constellations of defective modules have to be considered for evaluating the quality of modules, strings and generator
Keywords: aerial thermography; monitoring; PV module defects; system performance

aIR-PV-check: A quality inspection of PV-power plants without operation interruption - Buerhop, Claudia; Pickel, Tobias; Dalsass, Manuel; Scheuerpflug, Hans; Camus, Christian; Brabec, Christoph; Brabec, Christoph J. (2017 IEEE 44th Photovoltaic Specialist Conference, PVSC 2017; Category numberCFP17PSC-ART; Code 136737, 2018)
AIR-PV-check is a method using an unmanned aerial vehicles (UAV) with an infrared (IR)-camera for the quality inspection of PV-plants under real operating conditions. It enables the fast and 100%-control of PV-plants. Defective modules are detected by their temperature distribution. Besides the meteorological conditions, the interaction of defective modules within a string influences the module performance significantly as the measured and simulated data show. Thus, modules with extremely high temperatures are predominantly expected / detected in strings with only one single defective module. Consequently, string configurations and constellations of defective modules have to be considered for evaluating the quality of modules, strings and generator
Keywords: Aerial thermography; Monitoring; PV module defects; System performance

Algorithmus zur IR-Panoramabilderstellung aus IR-Luftaufnahmen von PV-Freiflächenanlagen - Dalsaß, Manuel; Deitsch, Sergiu; Moerman, Daniil; Gallwitz, Florian; Brabec, Christoph (32. Symposium Photovoltaische Solarenergie, 2017)

Alkyl Chain Engineering of Solution-Processable Star-Shaped Molecules for High-Performance Organic Solar Cells - Min, Jie; Luponosov, Yuriy N.; Gerl, Andreas; Polinskaya, Marina S.; Peregudova, Svetlana M.; Dmitryakov, Petr V.; Bakirov, Artem V.; Shcherbina, Maxim A.; Chvalun, Sergei N.; Grigorian, Souren; Kaush-Busies, Nina; Ponomarenko, Sergei A.; et al. (Advanced Energy Materials, 2014)
The impact of alkyl side-chain substituents on conjugated polymers on the photovoltaic properties of bulk heterojunction (BHJ) solar cells has been studied extensively, but their impact on small molecules has not received adequate attention. To reveal the effect of side chains, a series of star-shaped molecules based on a triphenylamine (TPA) core, bithiophene, and dicyanovinyl units derivatized with various alkyl end-capping groups of methyl, ethyl, hexyl and dodecyl is synthesiyed and studied to comprehensively investigate structure-properties relationships. UV-vis absorption and cyclic voltammetry data show that variations of alkyl chain length have little infl uence on the absorption and highest occupied molecular orbital (HOMO)-lowest unoccupied molecular orbital (LUMO) levels. However, these seemingly negligible changes have a pronounced impact on the morphology of BHJ thin films as well as their charge carrier separation and transportation, which in turn influences the photovoltaic properties of these small-molecule-based BHJ devices. Solution-processed organic solar cells (OSCs) based on the small molecule with the shortest methyl end groups exhibit high short circuit current (Jsc) and fill factor (FF), with an efficiency as high as 4.76% without any post-treatments; these are among the highest reported for solution-processed OSCs based on star-shaped molecules.
Keywords: Engineering controlled terms: Charge carriers; Heterojunctions; Molecules; Solar cells; Stars Carrier separation; Highest occupied molecular orbital; Lowest unoccupied molecular orbital; Power conversion efficiencies; Side-chains; Star-shaped molecules; Structure property relationships; Structure-properties relationships Engineering main heading: Synthesis (chemical)

All inkjet-printed organic solar cells on 3D objects - Steinberger, Marc; Distler, Andreas; Hörber, Johannes; Tam, Kai Cheong; Brabec, Christoph; Egelhaaf, Hans-Joachim (Flexible and Printed Electronics, 2024)
Drop-on-demand inkjet printing is a promising and commercially relevant technology for producing organic electronic devices of arbitrary shape on a wide variety of different substrates. In this work we transfer the inkjet printing process of organic photovoltaic devices from 2D to 3D substrates, using a 5-axis robot system equipped with a multi-nozzle inkjet printing unit. We present a ready-to-use 3D printing system for industrial application, using a 5-axis motion system controlled by commercial 3D motion software, combined with a commonly used multi-nozzle inkjet print head controlled by the corresponding printing software. The very first time inkjet-printed solar cells on glass/ITO with power conversion efficiencies (PCEs) of up to 7% are realized on a 3D object with surfaces tilted by angles of up to 60° against the horizontal direction. Undesired ink flow during deposition of the inkjet-printed layers was avoided by proper ink formulation. In order to be able to print organic (opto-)electronic devices also on substrates without sputtered indium tin oxide bottom electrode, the bottom electrode was inkjet-printed from silver nanoparticle (AgNP) ink, resulting in the first all inkjet-printed (i.e. including bottom electrode) solar cell on a 3D object ever with a record PCE of 2.5%. This work paves the way for functionalizing even complex objects, such as cars, mobile phones, or ‘Internet of Things’ applications with inkjet-printed (opto-)electronic devices.
CRIS-Team Scopus Importer:2024-07-05
Keywords: 3D functionalization; 3D printing; inkjet printing; organic solar cells; silver nanoparticles

All Printed Photoanode/Photovoltaic Mini-Module for Water Splitting - Xu, Zhenhua; Chen, Lang; Brabec, Christoph; Guo, Fei (Small Methods, 2023)
Printing a large-area bismuth vanadate photoanode offers a promising approach for cost-effective photoelectrochemical (PEC) water splitting. However, the light absorption trade-off with charge transfer, as well as stability issues always lead to poor PEC efficiency. Here, the solution-processed recipe is advanced with BiI3 dopant for the printed deposition with controllable crystal growth. The resultant BiVO4 films prefer (001) orientation with nanorod feature on substrate, allowing a faster charge transfer and improved photocurrent. The BiVO4 photoanode in tandem with perovskite solar module delivers an operating photocurrent density of 5.88 mA cm−2 at zero bias in 3.11 cm2 active area under AM 1.5 G illumination, yielding a solar-to-hydrogen efficiency as high as 7.02% for unbiased water splitting. Equally important, the stability of the aged BiVO4 rods has been addressed to distinguish phase segregation at surface. The photocatalysis degradation composes of vanadium loss and Bi2O3 enriching at the surface, opening a lid on the long-term stability of BiVO4 photoanodes.
CRIS-Team Scopus Importer:2023-09-29
Keywords: BiVO; large area; tandem devices; water splitting

All sub-nanosecond laser monolithic interconnection of OPV modules - Kubis, Peter; Winter, Jan; Gavrilova, Anna; Hennel, Markus; Schlosser, Susanne; Richter, Isabel; Distler, Andreas; Heyder, Madeleine; Kery, Stefan; Lenk, Peter; Geiger, Stephan; Brabec, Christoph; et al. (Progress in Photovoltaics, 2019)
Although green femtosecond lasers provide outstanding quality and wide processing windows for monolithic interconnection of the individual cells in organic photovoltaic (OPV) modules, they are hardly used in commercial applications, due to cost reasons. In this work, a process has been developed that allows the monolithic interconnection in OPV modules with an infrared sub‐nanosecond laser exclusively, without compromising the performance of the modules. While the photoactive layer is removed easily by green femtosecond pulses without damaging the bottom electrode, this is not possible for infrared nanosecond pulses, due to their much larger optical penetration length, which significantly exceeds the thickness of the active layer and is well absorbed by the indium tin oxide (ITO) layer. This leads to damage of the ITO bottom electrode, which in turn compromises the functionality of the module. By systematically varying single‐pulse laser fluence and spatial pulse overlap, the laser parameters are optimized in such a way that the contact area between the residues of the metal oxide bottom electrode and the silver nanowire top electrode is maximized so that the electrical resistances of the contacts are sufficiently small not to affect device performance. This is demonstrated by presenting large‐area OPV modules based on the well‐characterized reference system P3HT:PCBM that show efficiencies of up to 2.4%. This achievement opens up the way towards reliable roll‐to‐roll (R2R) laser patterning processes with sub‐nanosecond lasers and thus represents a breakthrough with respect to cost‐effective R2R manufacturing of OPV modules, due to grossly reduced investment and maintenance costs for laser sources.<br
Keywords: sub-nanosecond pulses; flexible organic photovoltaic module; laser patterning

A low-bandgap semiconducting polymer for photovoltaic devices and infrared emitting diodes - Brabec, Christoph; Winder, C.; Sariciftci, Niyazi Serdar; Hummelen, J.C.; Dhanabalan, Anantharaman; van Hal, P.A.; Janssen, Rene A. J. (Advanced Functional Materials, 2002)
A novel low-bandgap conjugated polymer (PTPTB, E = ∼1.6 eV), consisting of alternating electron-rich N-dodecyl-2,5-bis(2′-thienyl)pyrrole (TPT) and electron-deficient 2,1,3-benzothiadiazole (B) units, is introduced for thin-film optoelectronic devices working in the near infrared (NIR). Bulk heterojunction photovoltaic cells from solid-state composite films of PTPTB with the soluble fullerene derivative [6,6]-phenyl C butyric acid methyl ester (PCBM) as an active layer shows promising power conversion efficiencies up to 1% under AM1.5 illumination. Furthermore, electroluminescent devices (light-emitting diodes) from thin films of pristine PTPTB show near infrared emission peaking at 800 nm with a turn on voltage below 4 V. The electroluminescence can be significantly enhanced by sensitization of this material with a wide bandgap material such as the poly(p-phenylene vinylene) derivative MDMO-PPV.

Alternating quinoxaline/oligothiophene copolymers - Synthesis and unexpected absorption properties - Tsami, Argiri; Bünnagel, Thorsten W.; Farrell, Tony; Scharber, Markus; Chalois, Stelios A.; Brabec, Christoph; Scherf, Ullrich (Journal of Materials Chemistry, 2007)
The optical and electronic properties of novel, alternating quinoxaline/oligothiophene donor-acceptor copolymers show an unexpected independence of absorption and photoluminescence, as well as of the HOMO/LUMO energy levels, on the length of the oligothiophene segments in the copolymer main chain. © The Royal Society of Chemistry.

Alternative device concepts for future requirements of organic photovoltaic cells - Waldauf, Christoph; Morana, Mauro; Denk, Patrick; Brabec, Christoph J.; Brabec, Christoph; Coakley, Kevin; Schilinsky, Pavel; Choulis, Stelios A. (Organic Photovoltaics VII, 2006)
The challenge to reversing the layer sequence of organic photovoltaics (OPVs) is to prepare a selective contact bottom cathode and to achieve a suitable morphology for carrier collection in the inverted structure. We report the creation of an efficient electron selective bottom contact based on a solution-processed Titania layer on top of Indium Tin Oxide. The use of o-xylene as the casting solvent creates an efficient carrier collection network with little vertical phase segregation, providing sufficient performance for both regular as well as inverted solar cells. We demonstrate inverted layer sequence OPVs with AM 1.5-calibrated power conversion efficiencies of over 3%.
Keywords: Electrode; Inverted cell; Organic; Photovoltaic; Titania

A multi-objective optimization-based layer-by-layer blade-coating approach for organic solar cells: rational control of vertical stratification for high performance - Sun, Rui; Guo, Jie; Wu, Qiang; Zhang, Zhuohan; Yang, Wenyan; Guo, Jing; Shi, Mumin; Zhang, Yaohong; Kahmann, Simon; Ye, Long; Jiao, Xuechen; Loi, Maria A.; et al. (Energy and Environmental Science, 2019)
A major breakthrough in organic solar cells (OSCs) in the last thirty years was the development of the bulk heterojunction (BHJ) solution processing strategy, which effectively provided a nanoscale phase-separated morphology, aiding in the separation of Coulombically bound excitons and facilitating charge transport and extraction. Compared with the application of the layer-by-layer (LbL) approach proposed in the same period, the BHJ spin-coating technology shows overwhelming advantages for evaluating the performance of photovoltaic materials and achieving more-efficient photoelectric conversion. Thus, in this study, we have further compared the BHJ and LbL processing strategies via the doctor-blade coating technology because it is a roll-to-roll compatible high-throughput thin film fabrication route. We systematically evaluated multiple target parameters, including morphological characteristics, optical simulation, physical kinetics, device efficiency, and blend stability issues. It is worth emphasizing that our findings disprove the old stereotypes such as the BHJ processing method is superior to the LbL technology for the preparation of high-performance OSCs and the LbL approach requires an orthogonal solvent and donor/acceptor materials with special solubility. Our studies demonstrate that the LbL blade-coating approach is a promising strategy to effectively reduce the efficiency-stability gap of OSCs and even a superior alternative to the BHJ method in commercial applications.
CRIS-Team WoS Importer:2019-10-25

An alcohol-dispersed conducting polymer complex for fully printable organic solar cells with improved stability - Jiang, Youyu; Dong, Xinyun; Sun, Lulu; Liu, Tiefeng; Qin, Fei; Xie, Cong; Jiang, Pei; Hu, Lu; Lu, Xin; Zhou, Xianmin; Meng, Wei; Li, Ning; et al. (Nature Energy, 2022)
Efficient and stable organic solar cells via full coating are highly desirable. Poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) is a classic conducting polymer complex and widely used for hole collection in fully printable devices. However, PEDOT:PSS is typically dispersed in water and exhibits strong acidity that deteriorates device efficiency and stability. Here we report an alcohol-dispersed formulation (denoted as PEDOT:F) by adopting perfluorinated sulfonic acid ionomers as counterions. The ionomers have a special advantage of having two solubility parameters and can be dispersed in water or alcohols, which enables us to prepare PEDOT:F formulations dispersed in alcohols. The alcohol-dispersed formulation has good wetting properties and low acidity, which avoids the drawbacks of aqueous PEDOT:PSS. Fully printable organic photovoltaics (from bottom electrode to top electrode) based on PEDOT:F were obtained with a power conversion efficiency of 15% and could retain 83% of the initial efficiency under continuous illumination at maximum power point tracking for 1,330 h.
CRIS-Team Scopus Importer:2022-04-22

An Alternative Strategy to Adjust the Recombination Mechanism of Organic Photovoltaics by Implementing Ternary Compounds - Gasparini, Nicola; Salvador, Michael Filipe; Fladischer, Stefanie; Katsouras, Athanasios; Avgeropoulos, Apostolos; Spiecker, Erdmann; Chochos, Christos L.; Brabec, Christoph; Ameri, Tayebeh (Advanced Energy Materials, 2015)
Trap-assisted recombination is one of the main loss mechanisms in bulk-heterojunction (BHJ) solar cells. Results suggest that introducing a near infrared (NIR) polymer into the 2,3-bis(3-(octyloxy)phenyl)quinoxaline (PIDTTQ):[6,6]-phenyl C butyric acid methyl ester (PCBM) host system suppresses trap-assisted recombination in the binary blend, leading to a significant improvement of ≈60% in power conversion efficiency for ternary organic solar cells at low light intensity.
Keywords: IR sensitization; low light intensity; organic solar cells; recombination; ternary blends

Analysis of Digitized PV-Module/System Data for Failure Diagnosis - Buerhop, Claudia; Pickel, Tobias; Teubner, Janine; Doll, Bernd; Hauch, Jens; Brabec, Christoph (36th EU PVSEC 2019 Conference, 2019)
EL-images disclose many failures in PV-modules, e. g. cell cracks. Their impact and the relevance of certain defect features on the performance during operation is not known. This study focused on the identification of defective power-relevant cells, their impact on the performance and the degradation. Therefore, pre-cracked, low-performing modules are integrated in a string and monitored on module level. As a result, a statistical analysis of EL-images identified the power-relevant cells. The power of defective modules is extremely sensitive to changing measurement conditions. Historical monitoring data and actual EL-images give evidence that so far no changes of the crack structures of fractured cells occurred. Strong seasonal impact is observed. However, the yield is rather stable during the inspection peri

Analysis of inhomogeneous local distribution of Potential induced degradation at a rooftop photovoltaic installation - Buerhop, Claudia; Pickel, Tobias; Patel, Tirth; Fecher, Frank W.; Zetzmann, Cornelia; Camus, Christian; Hauch, Jens; Brabec, Christoph (IET Renewable Power Generation, 2017)
Potential induced degradation (PID) of photovoltaic (PV) modules is one of the frequently observed failures in PV installations nowadays. This study investigates the inhomogeneous and complex PID generation on rooftop installations on industrial buildings as well as its impact on the module performance. The PID development is exemplarily presented for a 314kWp PV-plant installed in the Atlantic coastal climate. Due to the complex plant geometry and resulting irradiation situation the existence of PID could not be identified based on the annual yield data. By Infrared imaging PID was clearly identified. Evaluating historic monitoring data, the impact of PID on the string and plant performance could be quantified. A linear correlation between the defect ratio and the performance rate as well as the degradation loss rate could be formulated. © The Institution of Engineering and Technology 2017.
Keywords: Engineering controlled terms: Infrared imagingOffice buildings Compendex keywords Induced degradationIndustrial buildingsLinear correlationLocal distributionsModule performancePhotovoltaic installationPhotovoltaic modulesPlant performance Engineering main heading: Thermography (imaging)

Analytical Model for Light Modulating Impedance Spectroscopy (LIMIS) in All-Solid-State p-n Junction Solar Cells at Open-Circuit - Almora Rodriguez, Osbel; Miravet, Daniel; Matt, Gebhard; Garcia-Belmonte, Germà; Brabec, Christoph (Applied Physics Letters, 2020)
Potentiostatic impedance spectroscopy (IS) is a well-known tool for characterization of materials and electronic devices. It can be complemented by numerical simulation strategies relying on drift-diffusion equations without any equivalent circuit-based assumptions. This implies the time-dependent solutions of the transport equations under small perturbation of the external bias applied as a boundary condition at the electrodes. However, in the case of photosensitive devices, a small light perturbation modulates the generation rate along the absorber bulk. This work then approaches a set of analytical solutions for the signals of IS and intensity modulated photocurrent and photovoltage spectroscopies, intensity modulated photocurrent spectroscopy (IMPS) and intensity modulated photovoltage spectroscopy (IMVS), respectively, from one-sided p-n junction solar cells at the open-circuit. Subsequently, a photoimpedance signal named “light intensity modulated impedance spectroscopy” (LIMIS = IMVS/IMPS) is analytically simulated, and its difference with respect to IS suggests a correlation with the surface charge carrier recombination velocity. This is an illustrative result and the starting point for future more realistic numerical simulations.<br

Analyzing the degradation of pre-damaged PV-modules - Buerhop, Claudia; Winkler, Thilo; Wirsching, Sven; Pickel, Tobias; Bemm, Andreas; Camus, Christian; Hauch, Jens; Brabec, Christoph (Proc. SPIE 10370, Reliability of Photovoltaic Cells, Modules, Components, and Systems X, 2017)
Cracked PV-modules are frequently detected in PV-systems. The impact of cracked cells on the energy yield and module performance under real operating conditions is not yet understood but of great relevance. Standard tests cannot reveal the relevant information conclusively. Therefore, we conducted a twofold analysis. 1) field exposure (global analysis on string level as well as detailed analysis on module level), and 2) load testing in the lab. Here, we present comparative electroluminescence (EL-) images recorded in an outdoor test stand and during load testing. Additionally, infrared (IR-) images as well as power data obtained from loaded and operating (field) conditions are discusse
Keywords: pre-cracked modules; field tests; loading tests; power measurements; IR-imaging; performance loss

Analyzing the efficiency, stability and cost potential for fullerene-free organic photovoltaics in one figure of merit - Li, Ning; Mcculloch, Iain; Brabec, Christoph (Energy and Environmental Science, 2018)
The power conversion efficiencies (PCEs) of solution-processed organic photovoltaic (OPV) devices continue increasing towards the 15% milestone. Recently-emerging non-fullerene acceptors (NFAs) have significantly accelerated this development. Most of the efficiency analyses performed previously are based on a fullerene acceptor without considering its contribution to the enhancement of photo-absorption and PCE. Moreover, the stability and cost potential of OPV devices are usually not discussed, which sometimes makes the efficiency prediction less representative for broad interest. In this work, we effectively combine the prediction of efficiencies with experimentally determined stability data to analyze and predict the commercial potential of a NFA-based OPV product. Assuming that NFAs dominate the blend near IR absorption, the efficiency limit of OPV devices is predicted to be close to 20% and is found to be insensitive to the donor bandgap. With the excellent photo-stability observed for state-of-the-art NFA-based OPV devices, it is suggested that the corresponding customized donors with promising processing properties, excellent environmental stability and low synthesis complexity be designed as realistic material pairs for large-scale production and commercializatio
Keywords: Engineering controlled terms: ForecastingFullerenesImage enhancementNanostructured materialsStability Engineering uncontrolled terms Commercial potentialEfficiency predictionsEnvironmental stabilityLarge scale productionsOrganic photovoltaic devicesOrganic photovoltaicsPower conversion efficienciesProcessing properties Engineering main heading: Efficiency

Analyzing the outdoor degradation behavior of organic solar modules in North China - Liu, Shaopeng; Zhang, Dawei; Egelhaaf, Hans-Joachim; Wang, Gaoyuan; Li, Xiaogang; Heumüller, Thomas; Brabec, Christoph; Li, Ning (Journal of Materials Chemistry A, 2024)
The outdoor stability of organic solar modules (OSMs) directly determines the success of the organic photovoltaic (OPV) technology, which is critically important but insufficiently studied so far. Here, we perform a systematic study on the long-term outdoor exposure of OSMs according to the ISOS-O-2 standard lasting over two years. OSMs featuring a large active area (108 cm2), lightweight design (∼22 g), and typical PCE value (4.2%) were utilized in this study. The environmental data and OSMs' property data are synchronously collected to investigate the relationship between the outdoor properties of OSMs and environmental factors with the aid of machine learning and traditional mathematical methods. Based on the experimental results, we quantify the OSMs' degradation process and evaluate the long-term stability of OSMs. Encouragingly, we find that the long-term operational stability of OSMs is quite impressive under the outdoor aging conditions in North China. The initial outdoor PCE value was around 4%, maintaining over 3.3% even after two years of outdoor exposure. The extrapolated degradation rate remained below 2% per year, despite the burn-in process. The observed burn-in process during outdoor degradation suggests that mitigating burn-in loss could enhance the field stability of OSMs, and that the outdoor environment can be effectively simulated in a well-designed laboratory setting for stability studies. All of this suggests a bright future for further development of OPV technology towards commercialization and practical outdoor applications.
CRIS-Team Scopus Importer:2024-05-31

An efficient solution-processed intermediate layer for facilitating fabrication of organic multi-junction solar cells - Li, Ning; Baran, Derya; Forberich, Karen; Turbiez, Mathieu; Ameri, Tayebeh; Krebs, Frederik C.; Brabec, Christoph (Advanced Energy Materials, 2013)
Photovoltaic tandem technology has the potential to boost the power conversion efficiency of organic photovoltaic devices. Here, a reliable and efficient fully solution-processed intermediate layer (IML) consisting of ZnO and neutralized poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) is demonstrated for series-connected multi-junction organic solar cells (OSCs). Drying at 80°C in air is sufficient for this solution-processed IML to obtain excellent functionality and reliability, which allow the use of most of high performance donor materials in the tandem structure. An open circuit voltage (V) of 0.56 V is obtained for single-junction OSCs based on a low band-gap polymer, while multi-junction OSCs based on the same absorber material deliver promising fill factor values along with fully additive V as the number of junctions increase. Optical and electrical simulations, which are reliable and promising guidelines for the design and investigation of multi-junction OSCs, are discussed. The outcome of optical and electrical simulations is in excellent agreement with the experimental data, indicating the outstanding efficiency and functionality of this solution-processed IML. The demonstration of this efficient, solution-processed IML represents a convenient way for facilitating fabrication of multi-junction OSCs to achieve high power conversion efficiency. An efficient solution-processed intermediate layer is introduced for facilitating fabrication of multi-junction organic solar cells (OSCs). The multi-junction OSCs that incorporate this intermediate layer deliver promising fill factor values along with the fully additive open circuit voltage (V) as the number of junctions increase. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: electrical simulation; low temperature treatment; optical stimulation; organic tandem solar cells; solution-processed intermediate layers; ZnO-nanoparticles

A New Crystal Phase Molybdate Yb2Mo4O15: The Synthesis and Upconversion Properties - Wang, Hai-Qiao; Mackovic, Mirza; Osvet, Andres; Litzov, Ivan; Epelbaum, Elena; Stiegelschmitt, Alfons; Batentschuk, Miroslaw; Spiecker, Erdmann; Brabec, Christoph (Particle & Particle Systems Characterization, 2015)
A new upconversion nanocrystal phase Yb2Mo4O15:Er is developed by using a facile aqueous-precipitation procedure combined with thermal annealing. Nanocrystals of Yb2Mo4O15 are exclusively synthesized, with particle sizes ranging from 1 to 20 nm. The optical properties are characterized and a high upconversion quantum yield is determined to be approximate to 1.3% at room temperature, under excitation of approximate to 500 mW cm(-2) IR (975 nm). To the best of our knowledge, this is the first work concerning the synthesis of nanocrystalline Yb2Mo4O15 and the characterization of its upconversion properties, which possesses the potential to be utilized in bio-probing and thin-film optoelectronic device applications.
Keywords: upconversion; Yb2Mo4O15:Er; nanocrystals; characterization

A new dithienosilole-based oligothiophene with methyldicyanovinyl groups for high performance solution-processed organic solar cells - Luponosov, Yuriy N.; Min, Jie; Ameri, Tayebeh; Brabec, Christoph; Ponomarenko, Sergei A. (Organic Electronics, 2014)
A new linear dithienosilole-based oligothiophene end-capped with methyl and electron-withdrawing dicyanovinyl groups, DTS(Oct)-(2T-DCV-Me), was prepared in good yield. This oligomer exhibited broad absorption spectra in bulk down to the near-IR region with the optical edge at 900 nm, resulting in an initially high power conversion efficiency of 5.44% in solution-processed organic solar cells using PCBM as an acceptor.
Keywords: Dicyanovinyl groups; Donor-acceptor oligomer; Oligothiophene; Organic solar cell; Small molecule

A New Metric for Assessing Local Mechanical Load Scenarios for PV Modules at Specific Locations - Camus, Christian; Offermann, Pascal; Weissmann, Martin; Buerhop-Lutz, Claudia; Hauch, Jens; Brabec, Christoph (33rd EUPVSEC, 2017)
In this paper, a new metric for assessing the location-specific mechanical loads imposed by snow or wind gusts which a photovoltaic module can be expected to be exposed to at a given location is introduced. For demonstrating this general approach, two locations of moderate distance ( 110km) in Northern Bavaria are compared. It is shown that even on moderate distances the expected loads differ by a factor of four or more highlighting the importance of location-specific requirements for PV modules. For assessing the loads, the historical weather data of the closest surrounding weather station is evaluated in order to deduce an expectation value for the site of interest. This data is analyzed with respect to the frequency and severity of the relevant weather events such that the annuality of a weather event of a given severity can be determined. Finally, the severity of an event corresponding to a single occurrence in 20 years, i.e. a standard product warranty, is chosen to represent the requirements of a location with respect to a certain parameter.
Keywords: Photovoltaic; Forecast; Reliability; Weather

A new two-dimensional oligothiophene end-capped with alkyl cyanoacetate groups for highly efficient solution-processed organic solar cells - Cui, Chaohua; Min, Jie; Ho, Cheuk-Lam; Ameri, Tayebeh; Yang, Pei; Zhao, Jianzhang; Brabec, Christoph; Wong, Wai-Yeung (Chemical Communications, 2013)
A new two-dimensional small molecule (DCA3T(VT)BDT) with an acceptor-donor-acceptor framework showed a high power conversion efficiency of 4% with a high fill factor of up to 0.63 in solution-processed organic solar cells. © 2013 The Royal Society of Chemistry.
Keywords: EMTREE drug terms: alkyl cyanoacetate; alkyl group; oligothiophene; thiophene derivative; unclassified drug EMTREE medical terms: article; electric potential; energy resource; organic solar cell; synthesis

Angle dependence of external and internal quantum efficiencies in bulk-heterojunction organic solar cells - Dennler, Gilles; Forberich, Karen; Scharber, Markus; Brabec, Christoph; Tomis, Igor; Hingerl, Kurt; Fromherz, Thomas (Journal of Applied Physics, 2007)
The realization of highly efficient organic solar cells requires the understanding and the optimization of the light path in the photoactive layer. We present in this article our approach to measure and model the optical properties of our bulk-heterojunction devices, and to control them in order to enhance the photovoltaic performances. We report our recent observations on the dependence of the external quantum efficiency (EQE) on the incidence angle of the light, and our results on the determination of internal quantum efficiency based on EQE measurement and optical modeling cross-checked by reflection measurements. We investigate poly(3-hexylthiophene): 1-(3-methoxy-carbonyl) propyl-1- phenyl [6,6] C61 based solar cells with two different thicknesses of the active layer (170 and 880 nm), and show that in the thin ones the absorption is enhanced for oblique incident radiation. © 2007 American Institute of Physics.

An improved algorithm for calculating relaxation time spectra from material functions of polymers with monodisperse and bimodal molar mass distributions - Brabec, Christoph; Schausberger, Alois (Rheologica Acta, 1995)
Using the basic concept of Emri and Tschoegl, the algorithm for calculating relaxation time spectra has been improved such that excellent results are provided in the difficult case of polymers with narrow molar mass distributions. These spectra can be compared with those calculated by nonlinear regularization (Weese 1992), which we regard as a very exact method, and show equally good results with even less mathematical effort. Examples of dense relaxation time spectra (up to eight points per decade) are given for nearly monodisperse polystyrene melts and for mixtures of these up to four components. The relaxation time spectra describe the dynamic mechanical experimental data in each case with an overall error of less than 3%. The filtering method used to avoid physically senseless oscillations has been proven to resolve the characteristic peaks contributed by monodisperse polymers accurately. © 1995 Steinkopff Verlag.
Keywords: dynamic moduli; iterative filtering method; molar mass distribution; Relaxation time spectra

An Innovative Anode Interface Combination for Perovskite Solar Cells with Improved Efficiency, Stability, and Reproducibility - Meng, Wei; Xu, Junyi; Dong, Lirong; Zhang, Jiyun; Xie, Zhiqiang; Luo, Junsheng; Zhao, Baolin; Zhang, Kaicheng; Osvet, Andres; Heumüller, Thomas; Forberich, Karen; Halik, Marcus; et al. (Solar RRL, 2022)
Rational design and engineering of top interface layers with combined properties of effective passivation, high thermal- and photo-stability are effective methods to advance the commercialization of perovskite photovoltaics. Here, an innovative anode interface combination is developed based on alcohol-dispersed poly (3-hexylthiophene-2,5-diyl) (P3HT) nanoparticles as the hole transport material and chlorobenzene-dissolved trioctylphosphine oxide (TO PO) as the passivation agent. It is shown that instead of the commonly used 2D passivation ligands, TOPO-passivated perovskite films exhibit greatly improved thermal stability. Furthermore, the passivation contributes to an enhanced carrier lifetime and reduced surface trap density, yielding an improvement in the quasi-fermi-level splitting of 57 meV. To maintain surface passivation during solution processing of further layers, it is necessary to develop a hole transport layer that can be processed from orthogonal solvents. P3HT nanoparticles formulated in alcoholic media fully meet this requirement, clearly benefitting from their high vertical conductivity and extremely low contact resistance with carbon electrodes. Based on this configuration, device efficiency of up to 18.4% is demonstrated for perovskite solar cells with fully solution-processed carbon electrodes, along with significantly improved device stability and reproducibility.
CRIS-Team WoS Importer:2022-06-17

An insight into the temperature dependence of photoluminescence of a highly-emissive Cs-Ag(Na)Bi(In)Cl-6 perovskite - Stroyuk, Oleksandr; Raievska, Oleksandra; Osvet, Andres; Hauch, Jens; Brabec, Christoph (Journal of Materials Chemistry C, 2023)
The temperature-dependent evolution of the photoluminescence (PL) properties of a highly emissive Cs2Ag0.35Na0.65Bi0.02In0.98Cl6 perovskite was examined in the range of 80-340 K. The PL maximum exhibited a shift to higher energies with an increase in T, while the bandgap decreased with elevated T. This behavior can be explained by a thermal distribution of the self-trapped exciton states.
CRIS-Team WoS Importer:2023-03-17

An inter-laboratory stability study of roll-to-roll coated flexible polymer solar modules - Gevorgyan, Suren A.; Medford, Andrew J.; Bundgaard, Eva; Sapkota, Subarna B.; Schleiermacher, Hans-Frieder; Zimmermann, Birger; Wuerfel, Uli; Chafiq, Amine; Lira-Cantu, Monica; Swonke, Thomas; Wagner, Michael; Haillant, Olivier O.; et al. (Solar Energy Materials and Solar Cells, 2011)
A large number of flexible polymer solar modules comprising 16 serially connected individual cells was prepared at the experimental workshop at Risø DTU. The photoactive layer was prepared from several varieties of P3HT (Merck, Plextronics, BASF and Risø DTU) and two varieties of ZnO (nanoparticulate, thin film) were employed as electron transport layers. The devices were all tested at Risø DTU and the functional devices were subjected to an inter-laboratory study involving the performance and the stability of modules over time in the dark, under light soaking and outdoor conditions. 24 laboratories from 10 countries and across four different continents were involved in the studies. The reported results allowed for analysis of the variability between different groups in performing lifetime studies as well as performing a comparison of different testing procedures. These studies constitute the first steps toward establishing standard procedures for an OPV lifetime characterization. © 2011 Elsevier B.V. All rights reserve
Keywords: Flexible modules; Inter-laboratory study; Outdoor testing; Polymer solar cells; R2R manufactured OPV; Round robin

Anomaly detection in IR images of PV modules using supervised contrastive learning - Bommes, Lukas; Hoffmann, Mathis; Buerhop-Lutz, Claudia; Pickel, Tobias; Hauch, Jens; Brabec, Christoph; Maier, Andreas; Peters, Ian Marius (Progress in Photovoltaics, 2022)
Increasing deployment of photovoltaic (PV) plants requires methods for automatic detection of faulty PV modules in modalities, such as infrared (IR) images. Recently, deep learning has become popular for this. However, related works typically sample train and test data from the same distribution ignoring the presence of domain shift between data of different PV plants. Instead, we frame fault detection as more realistic unsupervised domain adaptation problem where we train on labeled data of one source PV plant and make predictions on another target plant. We train a ResNet-34 convolutional neural network with a supervised contrastive loss, on top of which we employ a k-nearest neighbor classifier to detect anomalies. Our method achieves a satisfactory area under the receiver operating characteristic (AUROC) of 73.3% to 96.6% on nine combinations of four source and target datasets with 2.92 million IR images of which 8.5% are anomalous. It even outperforms a binary cross-entropy classifier in some cases. With a fixed decision threshold, this results in 79.4% and 77.1% correctly classified normal and anomalous images, respectively. Most misclassified anomalies are of low severity, such as hot diodes and small hot spots. Our method is insensitive to hyperparameter settings, converges quickly, and reliably detects unknown types of anomalies making it well suited for practice. Possible uses are in automatic PV plant inspection systems or to streamline manual labeling of IR datasets by filtering out normal images. Furthermore, our work serves the community with a more realistic view on PV module fault detection using unsupervised domain adaptation to develop more performant methods with favorable generalization capabilities.
CRIS-Team WoS Importer:2022-04-08

An Operando Study on the Photostability of Nonfullerene Organic Solar Cells - Xiao, Jingyang; Ren, Minrun; Zhang, Guichuan; Wang, Jianbin; Zhang, Donglian; Liu, Linlin; Li, Ning; Brabec, Christoph; Yip, Hin-Lap; Cao, Yong (Solar RRL, 2019)
Nonfullerene organic solar cells (OSCs) have achieved an impressive power conversion efficiency (PCE) over the past few years, showing a great potential for real applications. However, the study on the photostability and degradation mechanism of nonfullerene OSCs is far behind than that of fullerene-based solar cells, which is crucial for the commercial applications of the technology. Herein, an efficient and stable nonfullerene OSC based on PCE10:rhodanine-benzothiadiazole-coupled indacenodithiophene with branched 2-ethylhexyl side chains (EH-IDT) is fabricated from environmentally benign solvent. The PCE10:EH-IDT solar cell shows a high PCE of 9.17% and a long operational lifetime (T-80) of 2132 h, compared with other two OSCs based on 3,9-bis(2-methylene-(3-(1,1-dicyanomethylene)-indanone)-5,5,11,11-tetrakis(4-hexylphenyl)-dithieno[2,3-d:2',3'-d']-s-indaceno[1,2-b:5,6-b']-dithiophene (ITIC) and another fuse ring acceptor with withdrawing units of 1,1-dicyanomethylene-3-indanone and hexyl side chains (IDIC) nonfullerene acceptors, with tested lifetimes of only 221 and 558 h, respectively. As indicated by the Flory-Huggins interaction parameters, ITIC and IDIC have poor miscibility with PCE10, which leads to morphology degradation, suppressed charge generation, increased trap states, and charge recombination in the photoaging test, which accounts for the significant loss of short-circuit current density and fill factor during operation. The improved miscibility of the donor and the acceptor results in a more stable morphology, and the PCE10:EH-IDT solar cells thus achieve an outstanding overall performance that combines high efficiency and superior photostability and paves the way for the potential practical applications of OSCs.
CRIS-Team WoS Importer:2019-07-26
Keywords: miscibility; nonfullerene organic solar cells; operational lifetime; photostability

A paradigmatic change: Linking fullerenes to electron acceptors - Feng, Lai; Rudolf, Marc; Wolfrum, Silke; Troeger, Anna; Slanina, Zdenek; Akasaka, Takeshi; Nagase, Shigeru; Martin, Nazario; Ameri, Tayebeh; Brabec, Christoph; Guldi, Dirk Michael (Journal of the American Chemical Society, 2012)
The potential of Lu N@C and its analogues as electron acceptors in the areas of photovoltaics and artificial photosynthesis is tremendous. To this date, their electron-donating properties have never been explored, despite the facile oxidations that they reveal when compared to those of C . Herein, we report on the synthesis and physicochemical studies of a covalently linked Lu N@C -perylenebisimide (PDI) conjugate, in which PDI acts as the light harvester and the electron acceptor. Most important is the unambiguous evidence-in terms of spectroscopy and kinetics-that corroborates a photoinduced electron transfer evolving from the ground state of Lu N@C to the singlet excited state of PDI. In stark contrast, the photoreactivity of a C -PDI conjugate is exclusively governed by a cascade of energy-transfer processes. Also, the electron-donating property of the Lu N@C moiety was confirmed through constructing and testing a bilayer heterojunction solar cell device with a PDI and Lu N@C derivative as electron acceptor and electron donor, respectively. In particular, a positive photovoltage of 0.46 V and a negative short circuit current density of 0.38 mA are observed with PDI/Ca as anode and ITO/Lu N@C as cathode. Although the devices were not optimized, the sign of the V and the flow direction of J clearly underline the unique oxidative role of Lu N@C within electron donor-acceptor conjugates toward the construction of novel optoelectronic devices. © 2012 American Chemical Society.

A phase-field model for the evaporation of thin film mixtures - Ronsin, Olivier; Jang, DongJu; Egelhaaf, Hans-Joachim; Brabec, Christoph; Harting, Jens (Physical Chemistry Chemical Physics, 2020)

Application of optical absorbance for the investigation of electronic and structural properties of sol-gel processed TiO2 films - Welte, Andrea; Waldauf, Christoph; Brabec, Christoph J.; Wellmann, Peter (Thin Solid Films, 2008)
In this paper we report on optical absorbance as characterization technique to determine the electronic nature and, to a certain extend, also the structural properties of sol-gel deposited thin films in the 10 nm to 100 nm thickness range. In particular we have addressed the band structure of the TiO2 layers using band edge optical absorbance measurements; the crystallographic structure (i.e. amorphous, anatase, rutile, and brookite) after heat treatment in wet atmosphere was verified using X-ray diffraction (XRD) and Raman spectroscopy. In the case of structural properties we found that - after heat treatment at 200 degrees C - amorphous structural properties dominate while at higher temperatures (e.g. 500 degrees C) the anatase polytype is dominant. While XRD and Raman spectroscopy fail for 10 nm thin layers, optical absorbance proved to be a valid tool. The latter being of particular interest for the function of TiOx layers in electronic devices like sensors and solar cells. The aim of the paper is to discuss appropriate optical characterization tools for thin sol-gel processed TiO2 films. (c) 2007 Elsevier B.V. All rights reserve
Keywords: TiO2; Absorbance; Raman spectroscopy; XRD

A pressure process for efficient and stable perovskite solar cells - Luo, Junsheng; Xia, Jianxing; Yang, Hua; Sun, Chunlin; Li, Ning; Malik, Haseeb Ashraf; Shu, Hongyu; Wan, Zhongquan; Zhang, Haoli; Brabec, Christoph; Jia, Chunyang (Nano Energy, 2020)
The grain boundaries of organic-inorganic halide perovskite films not only function as defect centers, but also behave as intrinsic ion migrating channels and extrinsic moisture-induced degradation initiators, which are detrimental to the efficiency and stability of perovskite solar cells (PSCs). Here, an effective methodology for fabrication of high-quality perovskite layers with reduced non-radiative recombination, suppressed ion migration and increased moisture stability is reported for the first time, referred as the pressure-assisted solution processing (PASP). Through PASP strategy, the nucleation and growth of perovskite crystals can be controlled, leading to the micron-sized grains and microsecond-range carrier lifetimes. The resultant PSC shows champion power conversion efficiency (PCE) as high as 20.74% and a stabilized efficiency exceeding 20%, with superior long-term stability, maintaining above 90% of initial PCE even aging 60 days and continuous 1-sun illumination for 200 h in ambient environment without encapsulation. We unambiguously believe that the control of perovskite crystal nucleation and growth with high quality will be an important direction to improve the efficiency of PSCs to the theoretical limit, as well as to stabilize perovskite-based materials and devices.
CRIS-Team Scopus Importer:2020-07-24
Keywords: High-efficiency; Micron-sized grains; Microsecond-range carrier lifetimes; Perovskite solar cells; Pressure; Stability

A Series of Pyrene-Substituted Silicon Phthalocyanines as Near-IR Sensitizers in Organic Ternary Solar Cells - Ke, Lili; Min, Jie; Adam, Matthias; Gasparini, Nicola; Hou, Yi; Perea, Jose Dario; Chen, Wei; Zhang, Hong; Fladischer, Stefanie; Sale, Anna Chiara; Spiecker, Erdmann; Tykwinski, Rik; et al. (Advanced Energy Materials, 2016)
An attractive method to broaden the absorption bandwidth of polymer/fullerene-based bulk heterojunction (BHJ) solar cells is to blend near infrared (near-IR) sensitizers into the host system. Axial substitution of silicon phthalocyanines (Pcs) opens a possibility to modify the chemical, thermodynamic, electronic, and optical properties. Different axial substitutions are already designed to modify the thermodynamic properties of Pcs, but the impact of extending the π-conjugation of the axial ligand on the opto-electronic properties, as a function of the length of the alkyl spacer, has not been investigated yet. For this purpose, a novel series of pyrene-substituted silicon phthalocyanines (SiPc-Pys) with varying lengths of alkyl chain tethers are synthesized. The UV-vis and external quantum efficiency (EQE) results exhibit an efficient near IR sensitization up to 800 nm, clearly establishing the impact of the pyrene substitution. This yields an increase of over 20% in the short circuit current density (J ) and over 50% in the power conversion efficiency (PCE) for the dye-sensitized ternary device. Charge generation, transport properties, and microstructure are studied using different advanced technologies. Remarkably, these results provide guidance for the diverse and judicious selection of dye sensitizers to overcome the absorption limitation and achieve high efficiency ternary solar cells.
Keywords: Absorption limitations; Charge transport; Near-IR sensitizers; Silicon phthalocyanine; Ternary solar cells

A Soluble Donor-Acceptor Double-Cable Polymer: Polythiophene with Pendant Fullerenes - Cravino, Antonio; Zerza, Gerald; Maggini, Michele; Bucella, Stefania; Svensson, Mattias; Andersson, Mats R.; Neugebauer, Helmut; Brabec, Christoph; Sariciftci, Niyazi Serdar (Monatshefte für Chemie, 2003)
We report the synthesis and the spectroscopic properties of a novel soluble thiophene-based copolymer carrying pendant fullerene moieties (donor-acceptor double-cable polymer). Photoinduced absorption (PIA) experiments on spin cast films reveal a photoinduced electron transfer from the polythiophene chain onto the fullerene moieties. The performance of photovoltaic devices produced with this copolymer is also discussed.
Keywords: Double-cable polymers; Fullerenes; Organic photovoltaics; Photoinduced spectroscopy; Polythiophenes

A solution-processable star-shaped molecule for high-performance organic solar cells via alkyl chain engineering and solvent additive - Min, Jie; Luponosov, Yuriy N.; Ameri, Tayebeh; Elschner, Andreas; Peregudova, Svetlana M.; Baran, Derya; Heumüller, Thomas; Li, Ning; Machui, Florian; Ponomarenko, Sergei; Brabec, Christoph (Organic Electronics, 2013)
A new star-shaped D-π-A molecule, tris4-[5′′-(1,1- dicyanobut-1-en-2-yl)-2,2′-bithiophen-5-yl]phenylamine N(Ph-2T-DCN-Et), with high efficiency potential for photovoltaic applications was synthesized. As compared to its analogue S(TPA-bT-DCN), it showed stronger absorption in the region of 350-450 nm and a lower lying highest occupied molecular energy level (HOMO). Solution-processed organic solar cells (OSCs) based on a blend of N(Ph-2T-DCN-Et) and PCBM resulted in a high PCE of 3.1% without any post-treatment. The PCE of N(Ph-2T-DCN-Et) based solar cells was further improved to 3.6% under simulated AM 1.5 by addition of a new additive 4-bromoanisole (BrAni). © 2012 Elsevier B.V. All rights reserved.
Keywords: 4-Bromoanisole (BrAni); D-π-A molecule; Highest occupied molecular energy level; Organic solar cells (OSCs)

A solution-processed barium hydroxide modified aluminum doped zinc oxide layer for highly efficient inverted organic solar cells - Zhang, Hong; Stubhan, Tobias; Li, Ning; Turbiez, Mathieu; Matt, Gebhard; Ameri, Tayebeh; Brabec, Christoph (Journal of Materials Chemistry A, 2014)
Inverted organic solar cells (iOSCs) with air stable interface materials and top electrodes and an efficiency of 6.01% are achieved by inserting a barium hydroxide (Ba(OH)) layer between the aluminum doped zinc oxide (AZO) electron extraction layer and the active layer. A low bandgap diketopyrrolopyrrole-quinquethiophene alternating copolymer (pDPP5T-2) and phenyl-C61-butyric acid methyl ester (PCBM) were chosen as the active layer compounds. Compared to the control device without Ba(OH), insertion of a few nm thick Ba(OH) layer results in an enhanced V of 10%, J of 28%, FF of 28% and PCE of 80%. Modification of AZO with a solution processed low-cost Ba(OH) layer increased the efficiency of the inverted device by dominantly reducing the energy barrier for electron extraction from PCBM, and consequently, reduced charge recombination is observed. The drastic improvement in device efficiency and the simplicity of fabrication by solution processing suggest Ba(OH) as a promising and practical route to reduce interface induced recombination losses at the cathode of organic solar cells.
Keywords: Aluminum doped zinc oxide layers; Barium hydroxide; Inverted organic solar cells; Solution-processed

Assembling Mesoscale-Structured Organic Interfaces in Perovskite Photovoltaics - Hou, Yi; Xie, Chen; Radmilovic, Vuk V.; Puscher, Bianka; Wu, Mingjian; Heumüller, Thomas; Karl, André; Li, Ning; Tang, Xiaofeng; Meng, Wei; Chen, Shi; Osvet, Andres; et al. (Advanced Materials, 2019)
Mesoscale-structured materials offer broad opportunities in extremely diverse applications owing to their high surface areas, tunable surface energy, and large pore volume. These benefits may improve the performance of materials in terms of carrier density, charge transport, and stability. Although metal oxides–based mesoscale-structured materials, such as TiO2, predominantly hold the record efficiency in perovskite solar cells, high temperatures (above 400 °C) and limited materials choices still challenge the community. A novel route to fabricate organic-based mesoscale-structured interfaces (OMI) for perovskite solar cells using a low-temperature and green solvent–based process is presented here. The efficient infiltration of organic porous structures based on crystalline nanoparticles allows engineering efficient “n-i-p” and “p-i-n” perovskite solar cells with enhanced thermal stability, good performance, and excellent lateral homogeneity. The results show that this method is universal for multiple organic electronic materials, which opens the door to transform a wide variety of organic-based semiconductors into scalable n- or p-type porous interfaces for diverse advanced applications.<br

Assessing Temperature Dependence of Drift Mobility in Methylammonium Lead Iodide Perovskite Single Crystals - Shrestha, Shreetu; Matt, Gebhard; Osvet, Andres; Niesner, Daniel; Hock, Rainer; Brabec, Christoph (Journal of Physical Chemistry C, 2018)
Hybrid organic-inorganic perovskites have emerged as cost-effective and high-performance semiconductors for optoelectronic applications. Precise knowledge of charge carrier mobility and especially the temperature dependence of mobility is therefore of utmost relevance for advancing high-performance materials. Here, the charge carrier mobility in methylammonium lead iodide single crystals is investigated with time of flight technique from 290 to 100 K. A nondispersive transport with an electron mobility of 135 (+/- 20) cm(2)/V s and a hole mobility of 90 (+/- 20) cm(2)/V s is obtained at room temperature. A power-law temperature dependence of mobility, mu alpha T-m, with an exponent m = -2.8 and -2.0, is measured for electrons and holes in the tetragonal phase. The highest electron and hole mobilities measured are 635 (+/- 70) and 415 (+/- 20) cm(2)/V s, respectively. Our results indicate that the scattering of charge carriers with phonons is the limiting factor for carrier mobilities at room temperature.

Assessing the accuracy of imaging techniques for defect characterization on thin film solar cells - Vetter, Andreas; Hofbeck, Bernhard; Kubis, Peter; Brabec, Christoph (42nd IEEE Photovoltaic Specialist Conference, PVSC 2015, 2015)
Imaging methods are an essential tool for improving processing of solar cells. Unfortunately, it is difficult to validate the imaging methods in detail. One focus of our work was to establish an approach by which one can assess the accuracy of the determination of the influence of defects via imaging on CIGS solar cells. The method is, however, not restricted to CIGS and should be easily transferable to other solar cell types, in particular other thin film technologies. The benefit of such a method is the possibility to validate and optimize imaging techniques and, in turn, improving tools to optimize solar cell material and processing of solar cells.
Keywords: accuracy; CIGS; defects; ILIT; imaging; performance loss; quality control

Assessment of Technology- and Weather-Specific Temperature Losses of Various Photovoltaic Technologies - Brabec, Christoph (35th European Photovoltaic Solar Energy Conference and Exhibition, 2018)
In this paper, the temperature-induced performance losses of eight different photovoltaic (PV) module technologies under various real weather conditions are analyzed. Therefore, the electrical performance data of one year gathered at the ZAE Bayern’s PV test plant in Arzberg, Germany was correlated to on-site weather data and module temperature measurements. By classifying the measurement days into distinct weather categories an in-depth analysis of the weather- and technology-dependent performance is realized in this study. For each weather category, the different PV technologies are ranked with respect to their electrical yield. Subsequently, the temperature behavior of the technologies is analyzed for each of the categories in order to investigate, in how far the temperature-related yield losses are responsible for the weather-dependent performance differences that are observed for the different technologies. This analysis shows that the performance behavior is one of the main causes for the performance differences that are observed. However, it also becomes clear that further losses due to differences in spectral and / or angular sensitivity or weak light performance also influence the performance significantly. In the future, the results of this study will support system designers in choosing the appropriate PV technology for a given site based on the local climate conditio
Keywords: PV Technologies; Outdoor Performance; Yield Analysis; Temperature Behavior

A star-shaped D-π-A small molecule based on a tris(2-methoxyphenyl)amine core for highly efficient solution-processed organic solar cells - Min, Jie; Luponosov, Yuriy N.; Solodukhin, Alexander N.; Kausch-Busies, Nina; Ponomarenko, Sergei A.; Ameri, Tayebeh; Brabec, Christoph (Journal of Materials Chemistry C, 2014)
A new star-shaped D-π-A small molecule, 2,2′,2′- nitrilotris[(3-methoxy-4,1-phenylene)-2,2′-bithiene-5′, 5-diyleth-1-yl-1-ylidene]trimalononitrile N(Ph(OMe)-2T-DCN-Me), with high efficiency potential for photovoltaic applications was synthesized. Introducing a soluble tris(2-methoxyphenyl)amine (TPA-MeO) core unit can significantly improve the solubility of star-shaped small molecules without negatively impacting intramolecular conjugation and intermolecular solid state arrangements. Solution-processed organic solar cells based on a blend of N(Ph(OMe)-2T-DCN-Me) and PCBM show an initially high power conversion efficiency of over 4% under simulated AM 1.5. © the Partner Organisations 201
Keywords: Engineering controlled terms: Molecules; Stars; Synthesis (chemical) High power conversion; Organic solar cell; Photovoltaic applications; Small molecules; Solution-processed; Star-shaped Engineering main heading: Solar cells

A top-down strategy identifying molecular phase stabilizers to overcome microstructure instabilities in organic solar cells - Zhang, Chaohong; Heumüller, Thomas; Leon, Salvador; Gruber, Wolfgang; Burlafinger, Klaus; Tang, Xiaofeng; Perea, Jose Dario; Wabra, Isabell; Hirsch, Andreas; Unruh, Tobias; Li, Ning; Brabec, Christoph (Energy and Environmental Science, 2019)
The operational stability of organic solar cells (OSCs) is the essential barrier to commercialization. Compared to thermally-induced degradation, photo-stability of OSCs is far away from being resolved. Here, we demonstrate that the thermal- and photo-degradation of metastable bulk-heterojunction OSCs are governed by the same mechanism. Understanding the fundamental principles behind this mechanism is of significant importance to fully address the instability issues. Structural incompatibilities between the donor and acceptor molecules are identified as the main origin of the instability. Further, we introduce a top-down approach mainly based on their melting temperature and interaction parameters to rationally screen molecular phase stabilizers from a database with more than 10000 small molecules. Eventually, five chemicals were selected to validate our concept and tested in unstable organic solar cells. 1,4-Piperazine, which possesses a high melting point, good miscibility with polymers and the capability of forming inter-molecular hydrogen bonding, can indeed stabilize the mixed amorphous phases, leading to significantly improved stability of otherwise metastable OSCs.<br

A universal interface layer based on an amine-functionalized fullerene derivative with dual functionality for efficient solution processed organic and perovskite solar cells - Azimi, Seyed Hamed; Ameri, Tayebeh; Ameri, Tayebeh; Zhang, Hong; Hou, Yi; Ramírez Quiroz, César Omar; Min, Jie; Hu, Mengyao; Zhang, Zhi-Guo; Przybilla, Thomas; Matt, Gebhard; Spiecker, Erdmann; et al. (Advanced Energy Materials, 2015)
The successful application of an effective dipolar interface layer based on an amine functionalized fullerene derivative (DMAPA-C60) is reported for the perovskite and organic photovoltaic devices. The incorporation of DMAPA-C60 facilitates a favorable energy level alignment, and results in enhanced mobility-lifetime (μt) produc
Keywords: energy level alignment; mobility-lifetime products; organic photovoltaic devices; perovskite solar cells

A universal method to form the equivalent ohmic contact for efficient solution-processed organic tandem solar cells - Li, Ning; Stubhan, Tobias; Krantz, Johannes; Machui, Florian; Turbiez, Mathieu; Ameri, Tayebeh; Brabec, Christoph (Journal of Materials Chemistry A, 2014)
The highly transparent, conductive and robust intermediate layer (IML) is the primary challenge for constructing efficient organic tandem solar cells. In this work, we demonstrate an easy but generic approach to realize the fully functional, solution-processed IMLs. In detail, solution-processed silver-nanowires are packed at low concentration between hole- and electron-transporting layers to convert an otherwise rectifying interface into an ohmic interface. The IMLs are proven to be of ohmic nature under applied bias, despite the unipolar charge selectivity of the single layers. Ohmic recombination within IMLs is further proven in organic tandem solar cells fabricated by doctor-blading under ambient conditions. The tandem solar cells based on PCDTBT:[70]PCBM as the bottom cell and pDPP5T-2:[60]PCBM as the top cell give a power conversion efficiency of 7.25%, which is among the highest values for solution-processed organic tandem solar cells fabricated by using a roll-to-roll compatible deposition method in air. © the Partner Organisations 2014.
Keywords: Engineering controlled terms: Hole concentration; Nanowires; Ohmic contacts Ambient conditions; Deposition methods; Electron-transporting layers; Intermediate layers; Low concentrations; Power conversion efficiencies; Solution-processed; Tandem solar cells Engineering main heading: Solar cells

Author Correction: Traps and transport resistance are the next frontiers for stable non-fullerene acceptor solar cells (Nature Communications, (2022), 13, 1, (3786), 10.1038/s41467-022-31326-z) - Wöpke, Christopher; Göhler, Clemens; Saladina, Maria; Du, Xiaoyan; Nian, Li; Greve, Christopher; Zhu, Chenhui; Yallum, Kaila M.; Hofstetter, Yvonne J.; Becker-Koch, David; Li, Ning; Heumüller, Thomas; et al. (Nature Communications, 2022)
The original version of this Article contained an error in Fig. 2, in which three data sets (represented by circles, squares and triangles, respectively)were shifted along the x-axis by one data point, leadin g to an incorrect representation of the “Exp. suns-Voc” data (the symbols) in Fig. 2a and 2b. The correct version of Fig. 2 is:(Figure Presented.).This has been corrected in both the PDF andHTMLversions of the Article.
CRIS-Team Scopus Importer:2022-08-12

Automated Synthesis of 1-Tetradecylphosphonic Acid-Capped FAPbBr3 Nanocrystals for Light Conversion in Display Applications - Hu, Huiying; Shi, Hongyang; Zhang, Jiyun; Hauch, Jens; Osvet, Andres; Brabec, Christoph (ACS Applied Nano Materials, 2024)
Perovskite nanocrystals (NCs) have garnered increasing attention as light-emitting materials owing to their high photoluminescence quantum yields (PLQY) and narrow full width at half-maximum (fwhm). However, the poor stability hinders their practical application in displays. In this work, we investigate the photostability of FAPbBr3 NCs with the modification of 1-tetradecylphosphonic acid (TDPA). Employing a high-throughput approach, the optimized FAPbBr3/TDPA NCs reached a sufficiently high PLQY of 76% with a narrow band emission of 20 nm, as opposed to 45% PLQY for FAPbBr3/oleic acid NCs. Due to the strong passivation of TDPA on the perovskite surface, NC-filled polymeric binder layers exhibit excellent photostability under environmental conditions. The optimal samples maintained 95% of the initial PL intensity after continuous intense irradiation.
CRIS-Team Scopus Importer:2024-04-26
Keywords: ligand; light conversion; perovskite nanocrystal; PLQY; stability

Automated synthesis of quantum dot nanocrystals by hot injection: Mixing induced self-focusing - Salaheldin, Ahmed M.; Walter, Johannes; Herre, Patrick; Levchuk, Ievgen; Jabbari, Yasaman; Kolle, Joel; Brabec, Christoph; Peukert, Wolfgang; Segets, Doris (Chemical Engineering Journal, 2017)
The hot injection technique for the synthesis of quantum dots (QDs) is a well-established and widely used method in the lab. However, scale-up rules do not exist. One reason is that in particular the role of process parameters like mixing on particle formation is largely unknown, as systematic examination of the latter is impossible for the laborious and complex manual synthesis. Herein we studied the mixing induced self-focusing of particle size distributions (PSDs) of CdSe QDs using automation in combination with a defined stirrer geometry. Basis for our study is a platform that allows parallelization with inline temperature monitoring, defined injection rate, accurate sampling times as well as controlled stirring. Reproducibility in terms of optical product properties was analyzed by absorption and emission whereas reproducibility in terms of the PSD was verified by deconvolution of UV/Vis absorbance spectra and especially by analytical ultracentrifugation (AUC) complemented by transmission electron microscopy (TEM). In line with previous results, AUC confirmed that even QDs made by hot injection in an automated setup are polydisperse with multimodal size distributions. Finally, reproducibility in combination with early stage sampling and controlled mixing allowed us for the first time to analyze the influence of stirring on focusing and defocusing of PSDs, that has been expressed in terms of the evolution of the relative standard deviation (RSD). Our work paves the way to gain in-depth understanding of often forgotten process-structure relationships of colloidal nanoparticles which eventually is a first step in the direction of the development of scalable synthesis and reliable application of high-quality QDs in technical application

Automatic Detection and Analysis of Photovoltaic Modules in Aerial Infrared Imagery - Dotenco, Sergiu; Dalsaß, Manuel; Winkler, Ludwig; Wurzner, Tobias; Brabec, Christoph; Maier, Andreas; Gallwitz, Florian (IEEE Winter Conference on Applications of Computer Vision, 2016)
Drone-based aerial thermography has become a convenient quality assessment tool for the precise localization of defective modules and cells in large photovoltaic-power plants. However, manual evaluation of aerial infrared recordings can be extremely time-consuming. Therefore, we propose an approach for automatic detection and analysis of photovoltaic modules in aerial infrared images. Significant temperature abnormalities such as hot spots and hot areas can be identified using our processing pipeline. To identify such defects, we first detect the individual modules in infrared images, and then use statistical tests to detect the defective modules. A quantitative evaluation of the detection and analysis pipeline on real-world, infrared recordings shows the applicability of our approac

Automatized analysis of IR-images of photovoltaic modules and its use for quality control of solar cells - Hepp, Johannes; Machui, Florian; Egelhaaf, Hans-J.; Brabec, Christoph; Vetter, Andreas (Energy Science and Engineering, 2016)
It is well known that the performance of solar cells may significantly suffer from local electric defects. Accordingly, infrared thermography (i.p. lock-in thermography) has been intensely applied to identify such defects as hot spots. As an imaging method, this is a fast way of module characterization. However, imaging leads to a huge amount of data, which needs to be investigated. An automatized image analysis would be a very beneficial tool but has not been suggested so far for lock-in thermography images. In this manuscript, we describe such an automatized analysis of solar cells. We first established a robust algorithm for segmentation (or recognition) for both, the PV-module and the defects (hot spots). With this information, we then calculated a parameter from the IR-images, which could be well correlated with the maximal power (Pmpp) of the modules. The proposed automatized method serves as a very useful foundation for faster and more thorough analyses of IR-images and stimulates the further development of quality control on solar modules. © 2016 The Authors. Energy Science & Engineering published by the Society of Chemical Industry and John Wiley & Sons Ltd.
Keywords: Imaging; IR-thermography; PV; quality control; segmentation; solar cell

Automatized segmentation of photovoltaic modules in IR-images with extreme noise - Vetter, Andreas; Hepp, Johannes; Brabec, Christoph (Infrared Physics & Technology, 2016)
Local electric defects may result in considerable performance losses in solar cells. Infrared thermography is an essential tool to detect these defects on photovoltaic modules. Accordingly, IR-thermography is frequently used in R&D labs of PV manufactures and, furthermore, outdoors in order to identify faulty modules in PV-power plants. Massive amount of data is acquired which needs to be analyzed. An automatized method for detecting solar modules in IR-images would enable a faster and automatized analysis of the data. However, IR-images tend to suffer from rather large noise, which makes an automatized segmentation challenging. The aim of this study was to establish a reliable segmentation algorithm for R&D labs. We propose an algorithm, which detects a solar cell or module within an IR-image with large noise. We tested the algorithm on images of 10 PV-samples characterized by highly sensitive dark lock-in thermography (DLIT). The algorithm proved to be very reliable in detecting correctly the solar module. In our study, we focused on thin film solar cells, however, a transfer of the algorithm to other cell types is straight forward.
Keywords: DLIT; IR-thermography; Segmentation; Solar module

Autonomous optimization of an organic solar cell in a 4-dimensional parameter space - Osterrieder, Tobias; Schmitt, Frederik; Lüer, Larry; Wagner, Jerrit; Heumüller, Thomas; Hauch, Jens; Brabec, Christoph J. (Energy and Environmental Science, 2023)
Optimizing solution-processed organic solar cells is a complex and challenging task due to the vast parameter space in organic photovoltaics (OPV). Classical Edisonian or one-variable-at-a-time (OVAT) optimization approaches are laborious, time-consuming, and may not find the optimal parameter set in multidimensional design spaces. To tackle this problem, we demonstrate here for the first time artificial intelligence (AI) guided closed-loop autonomous optimization for fully functional organic solar cells. We empower our LineOne, an automated materials and device acceleration platform with a Bayesian Optimizer (BO) to enable autonomous operation for solving complex optimization problems without human interference. The system is able to fabricate and characterize complete OPV devices and navigate efficiently through the design space spanned by composition and processing parameters. In addition, a Gaussian Progress Regression (GPR) based early prediction model is employed to predict the efficiency of the cells from cheap proxy measurements, in our case, thin film absorption spectra, which are analyzed using a spectral model based on physical properties to generate microstructure features as input for the GPR. We demonstrate our generic and complete autonomous approach by optimizing composition and processing conditions of a ternary OPV system (PM6:Y12:PC70BM) in a four-dimensional parameter space. We identify the best parameter set for our system and obtain a precise objective function over the whole parameter space with a minimal number of samples. We demonstrate autonomous optimization of a complex opto-electronic device within 40 samples only, whereas an Edisonian approach would have required about 1000 samples. Even larger acceleration factors are expected for higher dimensional parameter spaces. This raises an important discussion on the necessity of autonomous platforms to accelerate Material science.
CRIS-Team Scopus Importer:2023-10-13

Axisymmetric and Asymmetric Naphthalene-Bisthienothiophene Based Nonfullerene Acceptors: On Constitutional Isomerization and Photovoltaic Performance - Hu, Wei; Du, Xiaoyan; Zhuang, Wenliu; Su, Wenyan; Cao, Jiamin; Pourrahimi, Amir Masoud; Li, Ning; Shen, Xingxing; Zhang, Maojie; Yu, Donghong; Gruber, Wolfgang; Unruh, Tobias; et al. (ACS Applied Energy Materials, 2020)
Two pairs of constitutional isomers of fused-octacyclic nonfullerene acceptors (NFAs) based on a naphthalene-bisthienothiophene core with or without fluorination at the ending groups have been developed. Compared with the axisymmetric NFAs N66-IC and N66-2FIC with two six-member-ring bridges, their asymmetric constitutional isomers N65-IC and N65-2FIC both with one six-member-ring bridge and one five-member-ring bridge exhibit remarkable red-shifted absorption, higher crystallinity, and slightly down-shifted LUMO energy levels. Organic solar cells based on PBDB-T-2F:N65-2FIC achieved a promising power conversion efficiency of 10.19%, which is three times higher than that of its counterpart PBDB-T-2F:N66-2FIC cell (3.46%). While being blended with PBDB-T as the donor material, the asymmetric acceptor analogue N65-IC based solar cell pronounces a PCE of 9.03%, being significantly improved from that of 5.45% for the PBDB-T:N66-IC based cell, which is in consistency with the results from those cells from their both fluorinated donor and acceptor counterparts. Design rules on either both fluorinated, both nonfluorinated, or cross-combined donor/acceptors for device fabrication has been explored. In addition, PBDB-T-2F:N65-2FIC possesses very promising device stability with 85% of its initial PCE after an exposure time of 1500 h under one sun illumination, which is meaningful for their future commercial devices.<br
Keywords: asymmetry; axisymmetry; isomerization

Balancing electrical and optical losses for efficient 4-terminal Si–perovskite solar cells with solution processed percolation electrodes - Ramírez Quiroz, César Omar; Shen, Yilei; Salvador, Michael Filipe; Forberich, Karen; Schrenker, Nadine; Spyropoulos, Georgios; Heumüller, Thomas; Wilkinson, Benjamin; Kirchartz, Thomas; Spiecker, Erdmann; Verlinden, Pierre J.; Zhang, Xueling; et al. (Journal of Materials Chemistry A, 2018)
The unprecedented rise in efficiency of perovskite-based photovoltaics has sparked interest in semitransparent devices, particularly for tandem structures. Despite promising reports regarding efficiency and reduced parasitic absorption, many devices still rely on processes from the gas phase, compromising both applicability and cost factors. Here, we report all-solution perovskite solar cells with improved infrared transparency ideally suited as top-cells for efficient multi-junction device configurations. We demonstrate the functionality of copper(I) thiocyanate as antireflective layer and as selective contact between the transparent conductive oxide and the perovskite. This concept allows us to fabricate an opaque device with steady state efficiency as high as 20.1%. By employing silver nanowires with robust environmental stability as the bottom electrode, we demonstrate different regimes of device performance that can be described through a classical percolation model, leading to semi-transparent solar cells with efficiencies of up to 17.1%. In conjunction with the implementation of an infrared-tuned transparent conductive oxide contact deposited on UV-fused silica, we show a full device average transmittance surpassing 84% between 800 and 1100 nm (as opposed to 77% with PEDOT:PSS as the selective contact). Finally, we mechanically stacked optimized perovskite devices on top of high performing PERL and IBC silicon architectures. The measured imputed output efficiency of the 4-terminal perovskite–silicon solar cell was 26.7% and 25.2% for the PERL–perovskite and IBC–perovskite, respectivel

Balancing the efficiency, stability, and cost potential for organic solar cells via a new figure of merit - Yang, Wenyan; Wang, Wei; Wang, Yuheng; Sun, Rui; Guo, Jie; Li, Hongneng; Shi, Mumin; Guo, Jing; Wu, Yao; Wang, Tao; Lu, Guanghao; Brabec, Christoph; et al. (Joule, 2021)
In spite of the great success in device efficiency resulting from the excessive design of photovoltaic materials, the stability and cost issues concerning basic commercial requirements of organic solar cells (OSCs) remain unresolved or controversial, slowing down the introduction of market-ready applications. We proposed an exciting discovery that as the active layer thickness decreases, the thermal stability increases gradually, even exceeding 100% of the initial efficiency under 150°C thermal stress. This trend was further confirmed by investigating thermodynamics and kinetics of morphology evolution for PM6:Y6 as a reference example. Extended research found that there is a similar correlation between photo-thermal stability and blend thickness. Consequently, a new reliable industrial figure of merit (i-FOM2.0), including four main factors: efficiency, photo-thermal stability, synthesis complexity, and active layer thickness, is presented here. Our work provides a promising trade-off strategy for reducing efficiency-stability-cost gap and accelerates the commercialization of OSCs.
CRIS-Team Scopus Importer:2021-06-04
Keywords: active layer thickness; figure of merit; organic solar cells; photo-thermal stability; thermal stability

Bandgap and Photoluminescence Tunability of Lead-Free Cs3Bi2(Br,I)9 Solid Solution Compounds - Hashimoto, Haruto; Oka, Ryohei; Hayakawa, Tomokatsu; Brabec, Christoph (Physica Status Solidi-Rapid Research Letters, 2023)
Herein, lead-free, mixed-halide perovskites of cesium bismuth bromide/iodide are synthesized by a hydrothermal method, and their structures and optical properties of the solid solution compounds are examined. The synthesized compounds exhibit X-ray diffraction patterns similar to that of trigonal Cs3Bi2Br9 (CBB), whose reflections are shifted to lower angles depending on the experimental iodine content. Very interestingly, even with the excessive introduction of iodine content in nominal, the symmetry of the crystals is kept to be trigonal, indicating that bromide CBB and iodide Cs3Bi2I9 (CBI) are crystallographically mixed in a facile way, although the stable crystal form of CBI is hexagonal. The optical properties of bandgap energy Eg and photoluminescence (PL) for the synthesized crystals are also examined. It is found that Eg decreases and PL peak position is correspondingly shifted to a longer wavelength with an increase in the experimental iodine content due to their band-to-band transitions. Moreover, first-principles calculation suggests the reduction of Eg with iodine content and the varied nature of band structure from direct (trigonal CBB) to indirect (trigonal CBI) transition. These novel findings can make the proposed strategy successful for developing lead-free, mixed-halide Bi-based perovskite crystals with the tunability of their optical properties.
CRIS-Team Scopus Importer:2023-09-22
Keywords: bandgap tunability; Bi-based halide perovskites; electronic structures; hydrothermal synthesis; photoluminescence; solid solution compounds; trigonal

Barix multilayer barrier technology for organic solar cells - Moro, Lorenza; Rutherford, Nicole M.; Visser, Robert Jan; Hauch, Jens A.; Klepek, Claudia; Denk, Patrick; Schilinsky, Pavel; Brabec, Christoph (Proc. of SPIE Vol. 6334, 2006)
The effect of multilayer barrier materials on the lifetime of organic photovoltaic cells has been investigated. For thin film encapsulated cells a protective layer was used to prevent damage during barrier layer deposition. No post deposition effects developed after dry box storage. In accelerated temperature and humidity lifetime testing the degradation of the encapsulated cells can be related to the loss of effective cell area. An extrapolation of the lifetime at room conditions has been quantitatively determined by comparing the cell degradation with the loss of Ca in a Caoxidation test. The results indicate a barrier permeation rate of 10 gr /[m* day] for these samples, corresponding to a lifetime of greater than 5000 hours. Routes to improvement of the OPV cell lifetime are discussed.
Keywords: Barrier films; Barrier layers; Bulk heterojunction; Conjugated polymers; Degradation; Encapsulation; Organic solar cells

Beginner's Guide to Visual Analysis of Perovskite and Organic Solar Cell Current Density–Voltage Characteristics - These, Albert; Koster, L. Jan Anton; Brabec, Christoph; Le Corre, Vincent Marc (Advanced Energy Materials, 2024)
The current density–voltage characteristic (J–V) is a critical tool for understanding the behavior of solar cells. This study presents an overview of the key aspects of J–V analysis and introduces a user-friendly flowchart that facilitates the swift identification of the most probable limiting process in a solar cell, based mainly on the outcomes of light-intensity-dependent J–V measurements. The flowchart is developed through extensive drift-diffusion simulations and a rigorous review of the literature, with a specific focus on perovskite and organic solar cells. Moreover, the flowchart proposes supplementary experiments that can be conducted to obtain a more precise prediction of the primary performance losses. It therefore serves as an optimal starting point to analyse performance losses of solar cells.
CRIS-Team Scopus Importer:2024-04-19
Keywords: current-voltage characteristic; drift-diffusion simulation; organic solar cell; perovskite solar cell; photovoltaics

Beyond Donor-Acceptor (D-A) Approach: Structure-Optoelectronic Properties-Organic Photovoltaic Performance Correlation in New D-A1-D-A2 Low-Bandgap Conjugated Polymers - Chochos, Christos L.; Drakopoulou, Sofia; Katsouras, Athanasios; Squeo, Benedetta M.; Sprau, Christian; Colsmann, Alexander; Gregoriou, Vasilis G.; Cando, Alex Palma; Allard, Sybille; Scherf, Ullrich; Gasparini, Nicola; Kazerouni, Negar; et al. (Macromolecular Rapid Communications, 2017)
Low-bandgap near-infrared polymers are usually synthesized using the common donor-acceptor (D-A) approach. However, recently polymer chemists are introducing more complex chemical concepts for better fine tuning of their optoelectronic properties. Usually these studies are limited to one or two polymer examples in each case study so far, though. In this study, the dependence of optoelectronic and macroscopic (device performance) properties in a series of six new D-A-D-A low bandgap semiconducting polymers is reported for the first time. Correlation between the chemical structure of single-component polymer films and their optoelectronic properties has been achieved in terms of absorption maxima, optical bandgap, ionization potential, and electron affinity. Preliminary organic photovoltaic results based on blends of the D-A-D-A polymers as the electron donor mixed with the fullerene derivative [6,6]-phenyl-C-butyric acid methyl ester demonstrate power conversion efficiencies close to 4% with short-circuit current densities (J ) of around 11 mA cm, high fill factors up to 0.70, and high open-circuit voltages (V s) of 0.70 V. All the devices are fabricated in an inverted architecture with the photoactive layer processed in air with doctor blade technique, showing the compatibility with roll-to-roll large-scale manufacturing processes.
Keywords: Conjugated polymers; Donor-acceptor; Low bandgap; Near-infrared; Organic photovoltaics

Beyond Ternary OPV: High-Throughput Experimentation and Self-Driving Laboratories Optimize Multicomponent Systems - Langner, Stefan; Häse, Florian; Perea, Jose Dario; Stubhan, Tobias; Hauch, Jens; Roch, Loïc M.; Heumüller, Thomas; Aspuru-Guzik, Alán; Brabec, Christoph (Advanced Materials, 2020)
Fundamental advances to increase the efficiency as well as stability of organic photovoltaics (OPVs) are achieved by designing ternary blends, which represents a clear trend toward multicomponent active layer blends. The development of high-throughput and autonomous experimentation methods is reported for the effective optimization of multicomponent polymer blends for OPVs. A method for automated film formation enabling the fabrication of up to 6048 films per day is introduced. Equipping this automated experimentation platform with a Bayesian optimization, a self-driving laboratory is constructed that autonomously evaluates measurements to design and execute the next experiments. To demonstrate the potential of these methods, a 4D parameter space of quaternary OPV blends is mapped and optimized for photostability. While with conventional approaches, roughly 100 mg of material would be necessary, the robot-based platform can screen 2000 combinations with less than 10 mg, and machine-learning-enabled autonomous experimentation identifies stable compositions with less than 1 mg.
CRIS-Team Scopus Importer:2020-02-25
Keywords: high-throughput experimentation; machine learning; organic photovoltaics; photostability; solar energy

Bimolecular crystals of fullerenes in conjugated polymers and the implications of molecular mixing for solar cells - Mayer, A.C.; Toney, M.F.; Scully, S.R.; Rivnay, J.; Brabec, Christoph; Scharber, Markus C.; Koppe, Markus; Heeney, Martin; Mcculloch, Iain; Mcgehee, Michael D. (Advanced Functional Materials, 2009)
The performance of polymerfullerene bulk heterojunction solar cells is heavily influenced by the interpenetrating nanostructure formed by the two semiconductors because the size of the phases, the nature of the interface, and molecular packing affect exciton dissociation, recombination, and charge transport. Here, X-ray diffraction is used to demonstrate the formation of stable, well-ordered bimolecular crystals offullerene intercalated between the side-chains of the semiconducting polymer poly(2,5-bis(3-tetradecylthiophen- 2-yl)thieno[3,2-b]thiophene. It is shown that fullerene intercalation is general and is likely to occur in blends with both amorphous and semicrystalline polymers when there is enough free volume between the side-chains to accommodate the fullerene molecule. These findings offer explanations for why luminescence is completely quenched in crystals much larger than exciton diffusion lengths, how the hole mobility of poly(2-methoxy-5-(3',7'- dimethyloxy)-p-phylene vinylene) increases by over 2 orders of magnitude when blended with fullerene derivatives, and why large-scale phase separation occurs in some polymer:fullerene blend ratios while thermodynamically stable mixing on the molecular scale occurs for others. Furthermore, it is shown that intercalation offullerenes between side chains mostly determines the optimum polymer:fullerene blending ratios. These discoveries suggest a method ofintentionally designing bimolecular crystals and tuning their properties to create novel materials for photovoltaic and other applications. © 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Bipolar charge transport in PCPDTBT-PCBM bulk-heterojunctions for photovoltaic applications - Morana, Mauro; Wegscheider, Matthias; Bonanni, Alberta; Kopidakis, Nikos; Shaheen, Sean; Scharber, Markus; Zhu, Zhengguo; Waller, David; Gaudiana, Russell; Brabec, Christoph (Advanced Functional Materials, 2008)
An experimental study of the transport properties of a low-bandgap conjugated polymer giving high photovoltaic quantum efficiencies in the near infrared spectral region (Eg-opt similar to 1.35 eV) is presented. Using a organic thin film transistor geometry, we demonstrate a relatively high in-plane hole mobility, up to 1.5. x 10(-2) cm(2) V-1 s(-1) and quantify the electron mobility at 3 x .10(-5) cm(2) V-1 s(-1) on a SiO2 dielectric. In addition, singular contact behavior results in bipolar quasi-Ohmic injection both from low and high workfunction metals like LiF/Al and An. X-ray investigations revealed a degree of interchain pi-stacking that is probably embedded in a disordered matrix. Disorder also manifests itself in a strong positive field dependence of the hole mobility from the electric field. In blends made with the electron acceptor methanofullerene [6,6]-phenyl C-61 butyric acid methyl ester (PCBM), the transistor characteristics suggest a relatively unfavorable intermixing of the two components for the application to photovoltaic devices. We attribute this to a too fine dispersion of [C60]-PCBM in the polymer matrix, that is also confirmed by the quenching of the photoluminescence signal measured in PCPDTBT [C60]-PCBM films with various composition. We show that a higher degree of phase separation can be induced during the film formation by using 1,8-octanedithiol (ODT), which leads to a more efficient electron percolation in the [C60]-PCBM. In addition, the experimental results, in combination with those of solar cells seem to support the correlation between the blend morphology and charge recombination. We tentatively propose that the drift length, and similarly the electrical fill factor, can be limited by the recombination of holes with electrons trapped on isolated [C60]-PCBM clusters. Ionized and isolated [C60]-PCBM molecules can modify the local electric field in the solar cell by build-up of a space-charge. The results also suggest that further improvements of the fill factor may also be limited by a strong electrical-field dependence of the hole transport.

Branched side chains improve molecular packing of non-fullerene acceptors - Li, Ning; Brabec, Christoph (Science China-Chemistry, 2021)
CRIS-Team Scopus Importer:2021-06-25

Brightly Luminescent and Color-Tunable CsPbBr3 Nanocrystals with Enhanced Stability and Room Temperature Cubic Structure through Codoping with MnCl2 - Darwish, Elshaimaa; Elia, Jack; Fehn, Dominik; Köllner, David; Pourjafar, Amir; Christiansen, Silke; Meyer, Karsten; Webber, Kyle Grant; Brabec, Christoph; Batentschuk, Miroslaw; Osvet, Andres (Advanced Engineering Materials, 2024)
Lead halide perovskites have attracted much attention from the scientific community in recent years due to their attractive properties and their proven potential in many applications. Nevertheless, their stability and lead toxicity have remained a problem. Herein, the potential of manganese as a divalent dopant to offer better stability and replace a fraction of the toxic lead ions is investigated. Moreover, the reverse microemulsion method is used to obtain tunability in emission and bandgap by doping cesium lead bromide. Furthermore, cubic cesium lead bromide particles are managed to obtain at room temperature as a result of doping.
CRIS-Team Scopus Importer:2024-05-24
Keywords: light conversion; perovskite nanoparticle; semiconductor quantum dots

Brightly Luminescent and Color-Tunable Formamidinium Lead Halide Perovskite FAPbX3 (X = Cl, Br, I) Colloidal Nanocrystals - Levchuk, Ievgen; Osvet, Andres; Tang, Xiaofeng; Brandl, Marco; Perea, Jose Dario; Högl, Florian; Matt, Gebhard; Hock, Rainer; Batentschuk, Miroslaw; Brabec, Christoph (Nano Letters, 2017)
In the past few years, hybrid organic-inorganic and all-inorganic metal halide perovskite nanocrystals have become one of the most interesting materials for optoelectronic applications. Here, we report a facile and rapid room temperature synthesis of 15-25 nm formamidinium CH(NH2)2PbX3 (X = Cl, Br, I, or mixed Cl/Br and Br/I) colloidal nanocrystals by ligand-assisted reprecipitation (LARP). The cubic and platelet-like nanocrystals with their emission in the range of 415-740 nm, full width at half-maximum (fwhm) of 20-44 nm, and radiative lifetimes of 5-166 ns enable band gap tuning by halide composition as well as by their thickness tailoring; they have a high photoluminescence quantum yield (up to 85%), colloidal and thermodynamic stability. Combined with surface modification that prevents degradation by water, this nanocrystalline material is an ideal candidate for optoelectronic devices and applications. In addition, optoelectronic measurements verify that the photodetector based on FAPbI3 nanocrystals paves the way for perovskite quantum dot photovoltaics. © 2017 American Chemical Society.
Keywords: Chelation; Energy gap; Hybrid materials; Ligands; Metal halides; Nanocrystalline materials; Optoelectronic devices; Perovskite; Photoluminescence; Semiconductor quantum dots; Surface treatment; Colloidal nanocrystals; Formamidinium; Hybrid organic-inorganic; Optoelectronic applications; Optoelectronic measurements; Photoluminescence quantum yields; Re-precipitation; Room temperature synthesis; Nanocrystals

Building process design rules for microstructure control in wide-bandgap mixed halide perovskite solar cells by a high-throughput approach - Akhundova, Fatima; Lüer, Larry; Osvet, Andres; Hauch, Jens; Peters, Ian Marius; Forberich, Karen; Li, Ning; Brabec, Christoph (Applied Physics Letters, 2021)
Wide bandgap mixed halide perovskites ABX3, in which X can be I, Br, or Cl, are promising materials to form highly efficient optoelectronic devices, because the optical bandgap can be controlled over a wide range by variation of the halogen composition. However, significant nonradiative losses must be overcome to approach the efficiency limit of single-junction solar cells. Here, we present a high throughput-based investigation of the influence of processing parameters on nonradiative losses in the perovskite bulk. We perform antisolvent crystallization during spin coating and vary the solvent type, its volume, and the temperature of the subsequent annealing step. We use the photoluminescence quantum yield (PLQY) as a proxy to the presence of nonradiative losses and PL spectra as a qualitative probe for sample morphology. Using Gaussian process regression, we find that we can reliably predict PLQY from the PL spectral shape. This means that the PL spectral shape conveys the essential photophysics controlling PL quenching and thus nonradiative charge recombination. In comparison with scanning electron micrographs and x-ray diffraction data, we find that nonradiative losses in polycrystalline perovskite films are caused by increased domain size dispersion. Our method provides a simple and fast structure-sensitive in-line probe for fast morphology optimization in a high-throughput fashion.
CRIS-Team Scopus Importer:2021-06-25

Burn-in Free Nonfullerene-Based Organic Solar Cells - Gasparini, Nicola; Salvador, Michael Filipe; Strohm, Sebastian; Heumüller, Thomas; Levchuk, Ievgen; Wadsworth, Andrew; Bannock, James H.; de Mello, John C.; Egelhaaf, Hans Joachim; Baran, Derya; Mcculloch, Iain; Brabec, Christoph (Advanced Energy Materials, 2017)
Organic solar cells that are free of burn-in, the commonly observed rapid performance loss under light, are presented. The solar cells are based on poly(3-hexylthiophene) (P3HT) with varying molecular weights and a nonfullerene acceptor (rhodanine-benzothiadiazole-coupled indacenodithiophene, IDTBR) and are fabricated in air. P3HT:IDTBR solar cells light-soaked over the course of 2000 h lose about 5% of power conversion efficiency (PCE), in stark contrast to [6,6]-Phenyl C61 butyric acid methyl ester (PCBM)-based solar cells whose PCE shows a burn-in that extends over several hundreds of hours and levels off at a loss of ≈34%. Replacing PCBM with IDTBR prevents short-circuit current losses due to fullerene dimerization and inhibits disorder-induced open-circuit voltage losses, indicating a very robust device operation that is insensitive to defect states. Small losses in fill factor over time are proposed to originate from polymer or interface defects. Finally, the combination of enhanced efficiency and stability in P3HT:IDTBR increases the lifetime energy yield by more than a factor of 10 when compared with the same type of devices using a fullerene-based acceptor instead. © 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Butyric acid; Defects; Degradation; Fullerenes; Open circuit voltage; Organic solar cells; Enhanced efficiency; Light soaking; Nonfullerene acceptor; Open circuit voltage loss; P3HT; Poly-3-hexylthiophene; Power conversion efficiencies; [6; 6]-phenyl-C61-butyric acid methyl esters; Solar cells

Bypassing the Single Junction Limit with Advanced Photovoltaic Architectures - Lüer, Larry; Peters, Ian Marius; Le Corre, Vincent Marc; Forberich, Karen; Guldi, Dirk Michael; Brabec, Christoph (Advanced Materials, 2023)
Multijunction devices and photon up- and down-conversion are prominent concepts aimed at increasing photovoltaic efficiencies beyond the single junction limit. Integrating these concepts into advanced architectures may address long-standing issues such as processing complexity, microstructure control, and resilience against spectral changes of the incoming radiation. However, so far, no models have been established to predict the performance of such integrated architectures. Here, a simulation environment based on Bayesian optimization is presented, that can predict and virtually optimize the electrical performance of multi-junction architectures, both vertical and lateral, in combination with up- and down-conversion materials. Microstructure effects on performance are explicitly considered using machine-learned predictive models from high throughput experimentation on simpler architectures. Two architectures that would surpass the single junction limit of photovoltaic energy conversion at reasonable complexity are identified: a vertical “staggered half octave system,” where selective absorption allows the use of 6 different bandgaps, and the lateral “overlapping rainbow system” where selective irradiation allows the use of a narrowband energy acceptor with reduced voltage losses, according to the energy gap law. Both architectures would be highly resilient against spectral changes, in contrast with two terminal multi-junction architectures which are limited by Kirchhoff's law.<br

Cage Molecules Stabilize Lead Halide Perovskite Thin Films - Sun, Shijing; Liu, Ming; Thapa, Janak; Hartono, Noor Titan Putri; Zhao, Yicheng; He, Donglin; Wieghold, Sarah; Chua, Matthew; Wu, Yue; Bulović, Vladimir; Ling, Sanliang; Brabec, Christoph; et al. (Chemistry of Materials, 2022)
The environmental stability of hybrid organic-inorganic perovskite (HOIP) materials needs to increase to enable their widespread adoption in thin-film solar and optoelectronic devices. Molecular additives have recently emerged as an effective strategy for regulating HOIP crystal growth and passivating defects. However, to date the choice of additives is largely limited to a dozen or so materials under the design philosophy that high crystallinity is a prerequisite for stable HOIP thin films. In this study, we incorporate porous organic cages (POCs) as functional additives into perovskite thin films for the first time and investigate the HOIP-POC interaction via a combined experimental and computational approach. POCs are significantly larger than the small-molecule additives explored for HOIP synthesis to date but much smaller than polymeric sealants. Partially amorphized composites of MAPbI3 (methylammonium lead iodide, HOIP) and RCC3 (an amine POC) form a network-like surface topography and lead to an increase in the optical bandgap from 1.60 to 1.63 eV. Further in situ optical imaging suggests that RCC3 can delay the MAPbI3 film degradation onset up to 50× under heat and humidity stresses, showing promise for improving reliability in HOIP-based solar-cell and light-emitting applications. Furthermore, there is evidence of molecular interactions between RCC3 and MAPbI3, as fingerprinted by the suppressed N-H stretching mode in MA+ from Fourier transform infrared (FTIR) spectra and density functional theory (DFT) simulations that suggest strong hydrogen bonding between MA+ and RCC3. Given the diversity of POCs and HOIPs, our work opens a new avenue to stabilize HOIPs via tailored molecular interactions with functional organic materials.
CRIS-Team Scopus Importer:2022-11-11

Carbon Photodetectors: The Versatility of Carbon Allotropes - Richter, Moses; Heumüller, Thomas; Matt, Gebhard; Heiß, Wolfgang; Brabec, Christoph; Heiß, Wolfgang (Advanced Energy Materials, 2016)
Carbon-based organic electronics are a technology, with the potential of complementing and substituting opto-electronic devices based on inorganic semiconductors and metals. In the group of organic semiconductors, carbon allotropes come with outstanding opto-electric properties and are remarkable candidates for novel applications like printed electronics via solution-processing on mechanically flexible, robust and light weight substrates, while reducing the environmental impact. Carbon allotropes like fullerenes, graphene quantum dots (GQD), carbon nanotubes (CNT), graphene and also diamond are especially interesting for photodetectors due to their tunable bandgap, high absorption coefficients and high charge carrier mobilites. These unique opto-electric properties of the allotropes, which strongly depend on their molecular dimensionality (0D, 1D, 2D and 3D), allow each allotrope to be used in a preferential range. Hence, relying on the intrinsic properties of carbon allotropes or by hybridization, carbon-based photodetectors are built for a spectral bandwidth, reaching from gamma-rays to THz radiation. This review highlights the recent advances in photodetectors based on fullerenes, GQDs, CNTs, graphene and diamond, with the focus on room temperature-operated devices. The versatility of multi-dimensional carbon allotropes is outstanding, and promising results outline the maturing of all carbon-based photodetection across the technologically relevant wavelengths.
Keywords: Carbon nanotubes; Fullerenes; Graphene; Graphene quantum dots; Organic photodetectors

Characterization of Aerosol Deposited Cesium Lead Tribromide Perovskite Films on Interdigited ITO Electrodes - These, Albert; Khansur, Neamul Hayet; Almora, Osbel; Luer, Larry; Matt, Gebhard; Eckstein, Udo; Barabash, Anastasiia; Osvet, Andres; Webber, Kyle Grant; Brabec, Christoph (Advanced Electronic Materials, 2021)
Aerosol deposition (AD) is a promising additive manufacturing method to fabricate low-cost, scalable films at room temperature, but has not been considered for semiconductor processing, so far. The successful preparation of cesium lead tribromide (CsPbBr3) perovskite films on interdigitated indium tin oxide (ITO) electrodes by means of AD is reported here. The 20–35 µm thick layers are dense and have good adhesion to the substrate. The orthorhombic Pnma crystal structure of the precursor powder was retained during the deposition process with no signs of defect formation. The formation of electronic defects by photoluminescence spectroscopy is investigated and found slightly increased carrier recombination from defect sites for AD films compared to the powder. A nonuniform defect distribution across the layer, presumably induced by the impact of the semiconducting grains on the hard substrate surface, is revealed. The opto-electronic properties of AD processed semiconducting films is further tested by electrical measurements and confirmed good semiconducting properties and high responsivity for the films. These results demonstrate that AD processing of metal halide perovskites is possible for opto-electronic device manufacturing on 3D surfaces. It is believed that this work paves the way for the fabrication of previously unimaginable opto-electronic devices by additive manufacturing.
CRIS-Team Scopus Importer:2021-01-22
Keywords: aerosol deposition; hysteresis; impedance spectroscopy; inorganic perovskites; photoluminescence spectroscopy

Characterization of ZnO Interlayers for Organic Solar Cells: Correlation of Electrochemical Properties with Thin-Film Morphology and Device Performance - Ou, Kai-Lin; Ehamparam, Ramanan; Macdonald, Gordon; Stubhan, Tobias; Wu, Xin; Shallcross, R. Clayton; Richards, Robin; Brabec, Christoph; Saavedra, S. Scott; Armstrong, Neal R. (ACS Applied Materials and Interfaces, 2016)
This report focuses on the evaluation of the electrochemical properties of both solution-deposited sol-gel (sg-ZnO) and sputtered (sp-ZnO) zinc oxide thin films, intended for use as electron-collecting interlayers in organic solar cells (OPVs). In the electrochemical studies (voltammetric and impedance studies), we used indium-tin oxide (ITO) over coated with either sg-ZnO or sp-ZnO interlayers, in contact with either plain electrolyte solutions, or solutions with probe redox couples. The electroactive area of exposed ITO under the ZnO interlayer was estimated by characterizing the electrochemical response of just the oxide interlayer and the charge transfer resistance from solutions with the probe redox couples. Compared to bare ITO, the effective electroactive area of ITO under sg-ZnO films was ca. 70%, 10%, and 0.3% for 40, 80, and 120 nm sg-ZnO films. More compact sp-ZnO films required only 30 nm thicknesses to achieve an effective electroactive ITO area of ca. 0.02%. We also examined the electrochemical responses of these same ITO/ZnO heterojunctions overcoated with device thickness pure poly(3-hexylthiophehe) (P3HT), and donor/acceptor blended active layers (P3HT:PCBM). Voltammetric oxidation/reduction of pure P3HT thin films on ZnO/ITO contacts showed that pinhole pathways exist in ZnO films that permit dark oxidation (ITO hole injection into P3HT). In P3HT:PCBM active layers, however, the electrochemical activity for P3HT oxidation is greatly attenuated, suggesting PCBM enrichment near the ZnO interface, effectively blocking P3HT interaction with the ITO contact. The shunt resistance, obtained from dark current-voltage behavior in full P3HT/PCBM OPVs, was dependent on both (i) the porosity of the sg-ZnO or sp-ZnO films (as revealed by probe molecule electrochemistry) and (ii) the apparent enrichment of PCBM at ZnO/P3HT:PCBM interfaces, both effects conveniently revealed by electrochemical characterization. We anticipate that these approaches will be applicable to a wider array of solution-processed interlayers for "printable" solar cells.
Keywords: charge selective interlayers; impedance spectroscopy; organic solar cells; phase separation; voltammetry; zinc oxide

Charge carrier dynamics in a ternary bulk heterojunction system consisting of P3HT, fullerene, and a low bandgap polymer - Koppe, Markus; Egelhaaf, Hans-Joachim; Clodic, Ewan; Morana, Mauro; Lueer, Larry; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Ameri, Tayebeh; Brabec, Christoph (Advanced Energy Materials, 2013)
The photoresponse of P3HT:PC BM based organic solar cells can be enhanced by blending the bulk heterojunction with the low band gap polymer Si-PCPDTBT. Organic solar cells containing the resulting ternary blend as the photoactive layer deliver short circuit currents of up to 15.5 mA cm. Morphological studies show modest phase separation without the perturbation of the crystallinity of the P3HT:PC BM matrix, in accordance with the measured acceptable fill factors. Picosecond time-resolved pump-probe spectroscopy reveals that the sensitization of P3HT:PC BM with Si-PCPDTBT involves the transfer of photogenerated positive polarons from the low band gap polymer to P3HT within few hundreds of picoseconds. Intensity dependent experiments in combination with global fitting show that the charge transfer from Si-PCPDTBT to P3HT competes with non-geminate charge carrier recombination of the holes in the Si-PCPDTBT phase with electrons in the PC BM phase, both processes being of diffusive nature. At excitation densities corresponding to steady state conditions under one sun, modelling predicts hole transfer efficiencies exceeding 90%, in accordance with IQE measurements. At higher pump intensities, bimolecular recombination suppresses the hole transfer process effectively. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Charge transport and recombination in low-bandgap bulk heterojunction solar cell using bis-adduct fullerene - Azimi, Hamed; Senes, Alessia; Scharber, Markus C.; Hingerl, Kurt; Brabec, Christoph (Advanced Energy Materials, 2011)
Charge transport and recombination are studied for organic solar cells fabricated using blends of polymer poly[(4,4′-bis(2-ethylhexyl)dithieno[3, 2-b:2′,3′ -d]silole)-2,6-diyl-alt-(4,7-bis(2-thienyl)-2,1,3- benzothiadiazole)-5,5′-diyl] (Si-PCPDTBT) with [6,6]-phenyl-C -butyric acid methyl ester (mono-PCBM) and the bis-adduct analogue of mono-PCBM (bis-PCBM). The photocurrent of Si-PCPDTBT:bis-PCBM devices shows a strong square root dependence on the effective applied voltage. From the relationship between the photocurrent and the light intensity, we found that the square-root dependence of the photocurrent is governed by the mobility-lifetime ( ) product of charge carriers while space-charge field effects are insignificant. The fill factor (FF) and short circuit current density ( J ) of bis-PCBM solar cells show a considerable increase with temperature as compared to mono-PCBM solar cells. SCLC analysis of single carrier devices proofs that the mobility of both electrons and holes is significantly lowered when replacing mono-PCBM with bis-PCBM. The increased recombination in Si-PCPDTBT:bis-PCBM solar cells is therefore attributed to the low carrier mobilities, as the transient photovoltage measurements show that the carrier lifetime of devices are not significantly altered by using bis-PCBM instead of mono-PCBM. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Applied voltages; Benzothiadiazoles; Bis-adducts; Bulk heterojunction solar cells; Charge transport and recombination; Electrons and holes; Fill factor; Light intensity; Methyl esters; Organic solar cell; Single carrier; Space charge field; Square-root dependence; Transient photovoltage measurements Engineering controlled terms: Heterojunctions; Photocurrents; Polymer blends; Silicon Engineering main heading: Solar cells

Charge transport in nanoparticular thin films of zinc oxide and aluminum-doped zinc oxide - Lenz, Thomas; Richter, Moses; Matt, Gebhard; Luechinger, N.A.; Halim, S.C.; Heiß, Wolfgang; Brabec, Christoph (Journal of Materials Chemistry C, 2015)
In this work, we report on the electrical characterization of nanoparticular thin films of zinc oxide (ZnO) and aluminum-doped ZnO (AZO). Temperature-dependent current-voltage measurements revealed that charge transport for both, ZnO and AZO, is well described by the Poole-Frenkel model and excellent agreement between the experimental data and the theoretical predictions is demonstrated. For the first time it is shown that the nature of the charge-transport is not affected by the doping of the nanoparticles and it is proposed that the Poole-Frenkel effect is an intrinsic and universally limiting mechanism for the charge transport in nanoparticular thin films with defect states within the bandgap. © The Royal Society of Chemistry 2015.
Keywords: Engineering controlled terms: Aluminum; Carrier transport; Optical films; Semiconductor doping; Thin films; Zinc; Zinc oxide Aluminum-doped zinc oxide; Aluminum-doped ZnO; Current voltage measurement; Electrical characterization; Poole-Frenkel effect; Poole-Frenkel model; Temperature dependent; Zinc oxide (ZnO) Engineering main heading: Oxide films

Classification of Additives for Organic Photovoltaic Devices - Machui, Florian; Maisch, Philipp; Burgues-Ceballos, Ignasi; Langner, Stefan; Krantz, Johannes; Ameri, Tayebeh; Brabec, Christoph (ChemPhysChem, 2015)
The use of additives to improve the performance of organic photovoltaic cells has been intensely researched in recent years. However, so far, no system has been reported for the classification of additives and their functions. In this report, a system for classifying additives according to the fundamental mechanism by which they influence microstructure formation for P3HT:PCBM is suggested. The major parameters used for their classification are solubility and drying kinetics. Both are discussed in detail and their consequences on processing are analyzed. Furthermore, a general mechanism to classify the impact of additives on structure formation is suggested and discussed for different materials relevant to organic photovoltaic devices.
Keywords: additives; fullerenes; ink formulation; organic photovoltaics; polymers

CO2 snow jet cleaning as a roll-to-roll compatible method for deburring IMI substrates after laser patterning - Wagner, Michael; Distler, Andreas; Schmidt, Hans-Dieter; Classen, A.; Stubhan, T.; Koegl, M.; Illg, J.; Brabec, Christoph; Egelhaaf, Hans-Joachim (Flexible and Printed Electronics, 2023)
Burring is commonly encountered upon patterning of dielectric-metal-dielectric (DMD) transparent electrodes by laser ablation. These burrs are conductive and thus lead to shunting of the (opto-)electronic devices built upon these electrodes. In this work, CO2 snow jet blasting is presented as a convenient and reliable method for deburring laser-patterned DMD electrodes during roll-to-roll manufacturing of organic solar modules. As CO2 snow jet blasting significantly reduces the extent of shunting and concomitantly avoids scratching the electrode, the photoelectrical conversion efficiencies of the solar modules thus produced are higher than those obtained for traditional deburring techniques.
CRIS-Team Scopus Importer:2023-02-10
Keywords: carbon dioxide snow jet; deburring; laser patterning; printed photovoltaics; transparent electrode

Coloring Semitransparent Perovskite Solar Cells via Dielectric Mirrors - Ramírez Quiroz, César Omar; Bronnbauer, Carina; Levchuk, Ievgen; Hou, Yi; Brabec, Christoph; Forberich, Karen (ACS nano, 2016)
While perovskite-based semitransparent solar cells for window applications show competitive levels of transparency and efficiency compared to organic photovoltaics, the color perception of the perovskite films is highly restricted because band gap engineering results in losses in power conversion efficiencies. To overcome the limitation in visual aesthetics, we combined semitransparent perovskite solar cells with dielectric mirrors. This approach enables one to tailor the device appearance to almost any desired color and simultaneously offers additional light harvesting for the solar cell. In the present work, opto-electrical effects are investigated through quantum efficiency and UV-to-visible spectroscopic measurements. Likewise, a detailed chromaticity analysis, featuring the transmissive and reflective color perception of the device including the mirror, from both sides and in different illumination conditions, is presented and analyzed. Photocurrent density enhancement of up to 21% along with overall device transparency values of up to 31% (4.2% efficiency) is demonstrated for cells showing a colored aesthetic appeal. Finally, a series of simulations emulating the device chromaticity, transparency, and increased photocurrent density as a function of the photoactive layer thickness and the design wavelength of the dielectric mirror are presented. Our simulations and their experimental validation enabled us to establish the design rules that consider the color efficiency/transparency interplay for real applications.
Keywords: Bragg mirror; dielectric mirror; perovskite photovoltaics; room temperature crystallization; semitransparent

Combinatorial screening of polymer: Fullerene blends for organic solar cells by inkjet printing - Teichler, Anke; Eckardt, Rebecca; Hoeppener, Stephanie; Friebe, Christian; Perelaer, Jolke; Senes, Alessia; Morana, Mauro; Brabec, Christoph; Schubert, Ulrich S. (Advanced Energy Materials, 2011)
Polymer: fullerene blends were screened in a combinatorial approach using inkjet printing thin film libraries for photovoltaic devices. The application of inkjet printing enabled a fast and simple experimental workflow from film preparation to the study of structure-property-relationships with a very high material efficiency. Inkjet printing requires less material for the preparation of thin film libraries in comparison to other dispensing techniques, like spin-coating. Two polymers (PCPDTBT, PSBTBT) and two fullerene derivatives (mono-PCBM, bis-PCBM) were investigated in various blend ratios, concentrations, solvent ratios, and film thicknesses. Morphological and optical properties of the inkjet printed films were investigated and compared with spin-coated films. This study shows the principle of an experimental setup from solution preparation to film characterization for the combinatorial investigation of large polymer: fullerene libraries. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Blend ratios; Combinatorial approach; Combinatorial screenings; Experimental setup; Film characterizations; Fullerene derivative; Material efficiency; Organic solar cell; Photovoltaic devices; Spin-coated films; Thin film libraries Engineering controlled terms: Fullerenes; Ink jet printing; Libraries; Optical properties; Polymer blends; Polymers; Thin films Engineering main heading: Film preparation

Combined Computational Approach Based on Density Functional Theory and Artificial Neural Networks for Predicting the Solubility Parameters of Fullerenes - Perea Ospina, Jose Dario; Langner, Stefan; Salvador, Michael Filipe; Kontos, Janos; Jarvas, Gabor; Winkler, Florian; Machui, Florian; Görling, Andreas; Dallos, Andras; Ameri, Tayebeh; Brabec, Christoph (Journal of Physical Chemistry B, 2016)
The solubility of organic semiconductors in environmentally benign solvents is an important prerequisite for the widespread adoption of organic electronic appliances. Solubility can be determined by considering the cohesive forces in a liquid via Hansen solubility parameters (HSP). We report a numerical approach to determine the HSP of fullerenes using a mathematical tool based on artificial neural networks (ANN). ANN transforms the molecular surface charge density distribution (σ-profile) as determined by density functional theory (DFT) calculations within the framework of a continuum solvation model into solubility parameters. We validate our model with experimentally determined HSP of the fullerenes C, PCBM, bisPCBM, ICMA, ICBA, and PCBM and through comparison with previously reported molecular dynamics calculations. Most excitingly, the ANN is able to correctly predict the dispersive contributions to the solubility parameters of the fullerenes although no explicit information on the van der Waals forces is present in the σ-profile. The presented theoretical DFT calculation in combination with the ANN mathematical tool can be easily extended to other π-conjugated, electronic material classes and offers a fast and reliable toolbox for future pathways that may include the design of green ink formulations for solution-processed optoelectronic devices.
Keywords: Engineering controlled terms: Computation theory; Design for testability; Fullerenes; Molecular dynamics; Neural networks; Optoelectronic devices; Solubility; Van der Waals forces Computational approach; Continuum solvation models; Electronic materials; Environmentally benign; Hansen solubility parameters; Molecular dynamics calculation; Numerical approaches; Solubility parameters Engineering main heading: Density functional theory

Comparative analysis of outdoor energy harvest of organic and silicon solar modules for applications in BIPV systems - Feroze, Sarmad; Distler, Andreas; Forberich, Karen; Ahmed Channa, Iftikhar; Doll, Bernd; Brabec, Christoph; Egelhaaf, Hans-Joachim (Solar Energy, 2023)
Organic photovoltaics (OPV) have the potential to fill niches that traditional silicon photovoltaics (Si-PV) have left open so far. Building-integrated photovoltaics (BIPV) is one key area where OPV modules can play a vital role due to their functional attributes of semitransparency, flexibility, and lightweight. However, the architectural constraints and physical layout of buildings often do not allow the installation of photovoltaic (PV) modules at their optimal angles. Herein, we report the outdoor energy harvest of commercial OPV, and monocrystalline silicon (m-Si) modules mounted at inclinations of 45° and 90°, using the ISOS-O2 protocol as a test standard. The semitransparent OPV modules incorporating a P3HT:PCBM bulk heterojunction absorbing layer were found to offer daily specific energy yields (YF) that are 10–15% higher than those of the m-Si modules at 45° inclination. For vertical (90°) mounting, the YF of the OPV modules is even 24–30% higher than that of their inorganic counterparts, thus making them ideally suited for façade integrated BIPV. Laboratory investigations reveal that the superior performance of OPV modules in the vertical position is mainly due to a strongly enhanced fill factor (FF) at reduced in-plane irradiance. At a 45° inclination, the positive temperature coefficient of the OPV modules also plays an important role during high-irradiance hours.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Building-integrated photovoltaics; Energy harvest; Organic photovoltaics; Outdoor monitoring

Comparison of Drone-based IR-imaging with Module Resolved Monitoring Power Data - Teubner, Janine; Kruse, Ingmar; Scheuerpflug, Hans; Buerhop-Lutz, Claudia; Hauch, Jens; Camus, Christian; Brabec, Christoph (Energy Procedia, 2017)
Two testing methods for photovoltaic (PV) plants, an infrared (IR)-measurement aerial system and a monitoring system on module level, are compared with respect to their capabilities for identifying irregularities of PV panels in a PV plant. For the first method, a hypothesis is tested that infrared temperature and module power can be correlated with an empirical linear correlation using the raw measurement data of the second method. A workaround is proposed how to quantify power losses for unknown PV plants showing at the same time how power losses depend on ambient conditions. Also, the data is used to improve results from the IR-measurements. The second method is explained to compare the two methods. It is shown that each method offers different advantages, helping to properly assess and schedule O&M measures.
Keywords: Engineering controlled terms: DronesElectric lossesFlight dynamicsInfrared imagingInspectionPhotovoltaic cellsReliabilitySiliconTestingThermography (imaging)Unmanned aerial vehicles (UAV) Compendex keywords Ambient conditionsInfrared measurementsIR thermographyLinear correlationMonitoring systemPhotovoltaicsPower-lossesRaw measurements Engineering main heading: Monitoring

Comparison of electroluminescence intensity and photocurrent of polymer based solar cells - Hoyer, Ulrich; Pinna, Luigi; Swonke, Thomas; Auer, Richard; Brabec, Christoph; Stubhan, Tobias; Li, Ning (Advanced Energy Materials, 2011)
The reciprocity theorem for solar cell predicts a linear relation between electroluminescence emission and photovoltaic quantum efficiency and an exponential dependence of the electroluminescence signal on the applied voltage. Both dependencies are experimentally verified for polymer based solar cells in this paper. Furthermore it is shown, that electroluminescence imaging of organic solar cells has the potential to visualize the photocurrent distribution significantly faster than standard laser beam induced current mapping (LBIC) techniques.

Comparison of the sputtered TiO2 anatase and rutile thin films as electron transporting layers in perovskite solar cells - Shahvaranfard, Fahimeh; Li, Ning; Hosseinpour, Saman; Hejazi, Seyedsina; Zhang, Kaicheng; Altomare, Marco; Schmuki, Patrik; Brabec, Christoph (Nano Select, 2021)
We examine comparatively the performance of sputtered TiO2 rutile and anatase thin films as an electron transport layer (ETL) inMAPbI3-based perovskite solar cells. Both anatase and rutile TiO2 ETLs are deposited (on fluorine-doped tin oxide [FTO] substrates) by magnetron sputtering in the form of nanocrystalline thin films. We systematically investigate the role of crystallographic phase composition of TiO2 ETLs on the photovoltaic performance of perovskite solar cells. The champion power conversion efficiencies (PCEs) of 18.4% and 17.7% under reverse scan mode are obtained for perovskite solar cells based on TiO2 anatase and TiO2 rutile ETL, respectively. The results show that the magnetron sputtering deposited ETLs differ from each other only in their phase composition while the overall performance of the devices is not greatly affected by the crystallographic phase of the TiO2 ETLs. Our results point to an important fact that for a proper and reliable comparison between the performance of TiO2 anatase and rutile ETLs, it is crucial to investigate films of similar morphology and structure that are synthesize under similar condition
Keywords: magnetron sputtering; perovskite solar cell; TiO2 anatase; TiO2 rutile

Comparison of various sol-gel derived metal oxide layers for inverted organic solar cells - Oh, Hyunchul; Krantz, Johannes; Litzov, Ivan; Stubhan, Tobias; Pinna, Luigi; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2011)
Inverted bulk-heterojunction solar cells have recently captured high interest due to their environmental stability as well as compatibility to mass production. This has been enabled by the development of solution processable n-type semiconductors, mainly TiO and ZnO. However, the device performance is strongly correlated to the electronic properties of the interfacial materials, and here specifically to their work function, surface states as well as conductivity and mobility. It is noteworthy to say that these properties are massively determined by the crystallinity and stoichiometry of the metal oxides. In this study, we investigated aluminum-doped zinc oxide (AZO) as charge selective extraction layer for inverted BHJ solar cells. Thin AZO films were characterized with respect to their structural, optical and electrical properties. The performance of organic solar cells with an AZO electron extraction layer (EEL) is compared to the performance of intrinsic ZnO or TiO EELs. We determined the transmittance, absorbance, conductivity and optical band gap of all these different metal oxides. Furthermore, we also built the correlations between doping level of AZO and device performance, and between annealing temperature of AZO and device performance. © 2011 Elsevier B.V.
Keywords: Al doped ZnO (AZO); Charge selective extraction layer; Inverted Organic Solar cells; Sol-Gel synthesis; TiOx; ZnO

Composition-Dependent Optical Band Bowing, Vibrational, and Photochemical Behavior of Aqueous Glutathione-Capped (Cu, Ag)-In-S Quantum Dots - Raievska, Oleksandra; Stroyuk, Oleksandr; Azhniuk, Yuriy; Solonenko, Dmytro; Barabash, Anastasiia; Brabec, Christoph; Zahn, Dietrich R. T. (Journal of Physical Chemistry C, 2020)
A mild aqueous synthesis of colloidal 2-4 nm (Cu, Ag)-In-S (CAIS) quantum dots (QDs) stabilized by surface metal complexes with glutathione was introduced. Linear variations of the interplanar distances as well as of the characteristic Ag(Cu)-S-related Raman vibrational frequencies of CAIS QDs with the increasing copper content show such QDs to be solid solutions rather than a mixture of AIS and CIS phases. At the same time, the band gaps and the energies of the photoluminescence (PL) band maxima of CAIS QDs show nonmonotonous changes decreasing from AIS to CAIS QDs (50 mol % Cu) and then increasing back for Cu-richer CAIS compositions and pure CIS. This behavior was interpreted as a result of the band bowing phenomenon. The bowing parameters of CAIS QDs determined from both absorption spectra (1.10 eV) and PL spectra (0.38 eV) are close to the range typically reported for ternary bulk MI-MIII-S compounds with the MI sites occupied by a mixture of copper and silver cations. The PL intensity of CAIS QDs was found to decrease during PL registration due to the photochemical decomposition of QDs, and the efficiency of this process increases with the increasing copper content. A similar trend was found in the photocatalytic reduction of methylviologen cations by hydrosulfide anions in the presence of CAIS. The initial rate of this reaction increased monotonously from AIS to CAIS to CIS QDs, with the activity of the CAIS QDs (50 mol % Cu) and pure CIS QDs being, respectively, 1.5 and 2.7 times higher than the photoactivity of pure AIS QDs. This trend is compliant with a strong decrease in the PL emission efficiency observed from AIS to CAIS to CIS QDs. Similar optical and photochemical properties were revealed for core/shell CAIS/ZnS QDs. The band bowing effect and photochemical activity of mixed CAIS (CAIS/ZnS) QDs open good perspectives for light-conversion applications in the photon energy range down to 1.8 eV.
CRIS-Team Scopus Importer:2020-10-23

Composition Engineering of All-Inorganic Perovskite Film for Efficient and Operationally Stable Solar Cells - Tian, Jingjing; Wang, Jing; Xue, Qifan; Niu, Tianqi; Yan, Lei; Zhu, Zonglong; Li, Ning; Brabec, Christoph; Yip, Hin Lap; Cao, Yong (Advanced Functional Materials, 2020)
Cesium-based inorganic perovskites have recently attracted great research focus due to their excellent optoelectronic properties and thermal stability. However, the operational instability of all-inorganic perovskites is still a main hindrance for the commercialization. Herein, a facile approach is reported to simultaneously enhance both the efficiency and long-term stability for all-inorganic CsPbI2.5Br0.5 perovskite solar cells via inducing excess lead iodide (PbI2) into the precursors. Comprehensive film and device characterizations are conducted to study the influences of excess PbI2 on the crystal quality, passivation effect, charge dynamics, and photovoltaic performance. It is found that excess PbI2 improves the crystallization process, producing high-quality CsPbI2.5Br0.5 films with enlarged grain sizes, enhanced crystal orientation, and unchanged phase composition. The residual PbI2 at the grain boundaries also provides a passivation effect, which improves the optoelectronic properties and charge collection property in optimized devices, leading to a power conversion efficiency up to 17.1% with a high open-circuit voltage of 1.25 V. More importantly, a remarkable long-term operational stability is also achieved for the optimized CsPbI2.5Br0.5 solar cells, with less than 24% degradation drop at the maximum power point under continuous illumination for 420 h.
CRIS-Team Scopus Importer:2020-06-09
Keywords: composition engineering; CsPbI; defect passivation; operationally stable; PbI

Comprehensive Investigation and Analysis of Bulk-Heterojunction Microstructure of High-Performance PCE11:PCBM Solar Cells - Zhang, Chaohong; Heumüller, Thomas; Gruber, Wolfgang; Almora, Osbel; Du, Xiaoyan; Ying, Lei; Chen, Junwu; Unruh, Tobias; Cao, Yong; Li, Ning; Brabec, Christoph (ACS Applied Materials and Interfaces, 2019)
Worldwide research efforts have been devoted to organic photovoltaics in the hope of a large-scale commercial application in the near future. To meet the industrial production requirements, organic photovoltaics that can reach power conversion efficiency (PCE) of over 10% along with promising operational device stability are of utmost interest. In the study, we take PCE11:PCBM as a model system, which can achieve over 11% PCE when processed from nonhalogen solvents, to deeply investigate the morphology− performance−stability correlation. We demonstrate that four batches of PCE11 with varying crystalline properties can achieve similar high performance in combination with PCBM. Careful device optimization is necessary in each case to properly address the requirements for the quite distinct microstructures. The bulk-heterojunction (BHJ) microstructure is comprehensively investigated as a function of the macromolecular weight and crystallinity. It is demonstrated that small differences in morphology significantly affect the kinetics and thermodynamic equilibrium of the BHJ microstructure as well as the photostability and thermal stability of the PCE11:PCBM solar cells<br
Keywords: in situ capacitance spectroscopy; organic photovoltaics; bulk-heterojunction microstructures; film morphology; PCE11:PCBM solar cells

Computational optimization and solution-processing of thick and efficient luminescent down-shifting layers for photovoltaics - Solodovnyk, Anastasiia; Kick, Christopher; Osvet, Andres; Egelhaaf, Hans-Joachim; Stern, Edda; Batentschuk, Miroslaw; Forberich, Karen; Brabec, Christoph (Physics, Simulation, and Photonic Engineering of Photovoltaic Devices V, 2016)
Luminescent down-shifting (LDS) is a simple, powerful tool for increasing the range of solar irradiance that can be efficiently utilized by photovoltaic devices. We developed an optical model to simulate the ideal optical properties (absorbance, transmittance, luminescence quantum yield, etc.) of LDS layers for solar cells. We evaluated which quantum efficiencies and which optical densities are necessary to achieve an improvement in solar cell performance. In particular we considered copper indium gallium diselenide (CIGS) devices. Our model relies on experimentally measured data for the transmission and emission spectra as well as for the external quantum efficiency (EQE) of the solar cell. By combining experimental work with this optical model, we aim to propose an environmentally friendly technology for coating thick (300-500 μm), efficient luminescent down-shifting layers. These layers consist of polyvinyl butyral (PVB) and organic UV-converting fluorescent dyes. The absorption coefficients and luminescence quantum yields of the dyes were determined both in a solution of the solvent benzyl alcohol and in the solid polymer layers. This data shows that the dyes retain luminescence quantum yields of approximately 90% after solution-processing. The produced layers were then applied to CIGS solar cells, thereby improving the EQE of the devices in the UV region. At a wavelength of 390 nm, for instance, the EQE increased from 18% to 53%. These values closely agree with the theoretically calculated ones. The proposed technology, thus, provides a pathway toward efficient, fully solutionprocessable encapsulated photovoltaic modules.
Keywords: Absorbance; EQE; Luminescence; Organic dye; Photovoltaics; Quantum yield

Computer vision tool for detection, mapping, and fault classification of photovoltaics modules in aerial IR videos - Bommes, Lukas; Pickel, Tobias; Buerhop-Lutz, Claudia; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (Progress in Photovoltaics, 2021)
Increasing deployment of photovoltaics (PV) plants demands for cheap and fast inspection. A viable tool for this task is thermographic imaging by unmanned aerial vehicles (UAV). In this work, we develop a computer vision tool for the semi-automatic extraction of PV modules from thermographic UAV videos. We use it to curate a dataset containing 4.3 million IR images of 107,842 PV modules from thermographic videos of seven different PV plants. To demonstrate its use for automated PV plant inspection, we train a ResNet-50 to classify ten common module anomalies with more than 90% test accuracy. Experiments show that our tool generalizes well to different PV plants. It successfully extracts PV modules from 512 out of 561 plant rows. Failures are mostly due to an inappropriate UAV trajectory and erroneous module segmentation. Including all manual steps our tool enables inspection of 3.5 MWp to 9 MWp of PV installations per day, potentially scaling to multi-gigawatt plants due to its parallel nature. While we present an effective method for automated PV plant inspection, we are also confident that our approach helps to meet the growing demand for large thermographic datasets for machine learning tasks, such as power prediction or unsupervised defect identification.
CRIS-Team WoS Importer:2021-07-16

Consensus statement for stability assessment and reporting for perovskite photovoltaics based on ISOS procedures - Khenkin, Mark V.; Katz, Eugene A.; Abate, Antonio; Bardizza, Giorgio; Berry, Joseph J.; Brabec, Christoph; Brunetti, Francesca; Bulovic, Vladimir; Burlingame, Quinn; Di Carlo, Aldo; Cheacharoen, Rongrong; Cheng, Yi-Bing; et al. (Nature Energy, 2020)
Improving the long-term stability of perovskite solar cells is critical to the deployment of this technology. Despite the great emphasis laid on stability-related investigations, publications lack consistency in experimental procedures and parameters reported. It is therefore challenging to reproduce and compare results and thereby develop a deep understanding of degradation mechanisms. Here, we report a consensus between researchers in the field on procedures for testing perovskite solar cell stability, which are based on the International Summit on Organic Photovoltaic Stability (ISOS) protocols. We propose additional procedures to account for properties specific to PSCs such as ion redistribution under electric fields, reversible degradation and to distinguish ambient-induced degradation from other stress factors. These protocols are not intended as a replacement of the existing qualification standards, but rather they aim to unify the stability assessment and to understand failure modes. Finally, we identify key procedural information which we suggest reporting in publications to improve reproducibility and enable large data set analysis.
CRIS-Team Scopus Importer:2020-02-04

Consensus statement: Standardized reporting of power-producing luminescent solar concentrator performance - Yang, Chenchen; Atwater, Harry A.; Baldo, Marc A.; Baran, Derya; Barile, Christopher J.; Barr, Miles C.; Bates, Matthew; Bawendi, Moungi G.; Bergren, Matthew R.; Borhan, Babak; Brabec, Christoph; Brovelli, Sergio; et al. (Joule, 2022)
Fair and meaningful device performance comparison among luminescent solar concentrator-photovoltaic (LSC-PV) reports cannot be realized without a general consensus on reporting standards in LSC-PV research. Therefore, it is imperative to adopt standardized characterization protocols for these emerging types of PV devices that are consistent with other PV devices. This commentary highlights several common limitations in LSC literature and summarizes the best practices moving forward to harmonize with standard PV reporting, considering the greater nuances present with LSC-PV. Based on these practices, a checklist of actionable items is provided to help standardize the characterization/reporting protocols and offer a set of baseline expectations for authors, reviewers, and editors. The general consensus combined with the checklist will ultimately guide LSC-PV research towards reliable and meaningful advances.
CRIS-Team WoS Importer:2022-02-11

Contactless temperature determination using dual-channel lock-in phosphor thermometry - Hashemi, Amir; Jovicic, Gordana; Batentschuk, Miroslaw; Brabec, Christoph; Vetter, Andreas (Measurement Science and Technology, 2017)
In this paper, we present dual-channel lock-in phosphor thermometry, which offers an option of accurate and contactless temperature determination under high environmental noise. We studied YAG:Dy as thermographic phosphor at an excitation wavelength of 405 nm. We tested our approach under different experimental conditions with noise levels of about 550, 1060 and 2190 times larger than the excitation signal. With the dual-channel lock-in setup, we were able to suppress the strong noise in all cases and to reliably determine surface temperature using our optical measurements (error < 10 K). Additionally, the effect of signal to noise ratio, lock-in frequency and lock-in bandwidth on temperature determination accuracy was studied in this work.
Keywords: dual-channel; lock-in; luminescence; phosphor thermometry; temperature

Controlling additive behavior to reveal an alternative morphology formation mechanism in polymer: Fullerene bulk-heterojunctions - Güldal, Nusret Sena; Berlinghof, Marvin; Kassar, Thaer; Du, Xiaoyan; Jiao, Xuechen; Meyer, Markus; Ameri, Tayebeh; Osvet, Andres; Li, Ning; Destri, Giovanni Li; Fink, Rainer; Ade, Harald; et al. (Journal of Materials Chemistry A, 2016)
One of the most employed morphology optimization methods to design better performing organic photovoltaic devices is ink formulation engineering with additives. In this work, by employing a suboptimal host solvent mixture and 1,8-diiodooctane (DIO) as a very optimal solvent for both components in poly-thieno[3,2b]thiophene-diketopyrrolopyrrole-co-thiophene (DPP-TT-T)-based bulk-heterojunctions (BHJ), an alternative, previously unknown mechanism of additive behavior on BHJ microstructure formation is presented. In situ characterization methods involving grazing incidence X-ray diffraction, white-light reflectometry, laser light scattering and photoluminescence during film drying reveal that the microstructure formation under the influence of DIO is led towards thermodynamic equilibrium during host solvent drying, and the kinetics of morphology formation (i.e. polymer crystallization, fullerene aggregation...) are controlled dominantly by the additive during its evaporation. Ex situ X-ray-based characterization methods, such as scanning transmission X-ray microspectroscopy (STXM) and resonant soft X-ray scattering (R-SoXS), additionally reveal that the microstructure of dried films favors smaller domain sizes with purer domains, smaller fullerene aggregates, bimodal polymer crystallization relative to the substrate and more face-on molecular orientation relative to the donor/acceptor interface, which at the end lead to better performing devices with power conversion efficiencies ranging from 1.25% to 4.68%.
Keywords: Engineering controlled terms: Additives; Fullerenes; Heterojunctions; Interfaces (materials); Light scattering; Microstructure; Molecular orientation; Morphology; Polymers; Solvents; Thiophene; X ray diffraction; X ray scattering Bulk heterojunction (BHJ); Characterization methods; Donor/acceptor interface; Grazing incidence X-ray diffraction; In-situ characterization; Microstructure formation; Organic photovoltaic devices; Power conversion efficiencies Engineering main heading: Polymer films

Controlling the crystallization dynamics of photovoltaic perovskite layers on larger-area coatings - Zeng, Linxiang; Chen, Shi; Forberich, Karen; Brabec, Christoph; Mai, Yaohua; Guo, Fei (Energy and Environmental Science, 2020)
As perovskite solar cells are highly efficient and already meet the efficiency requirement for renewable power generation, more attention is given to technological barriers such as scalability and stability. In particular, the large efficiency losses associated with upscaling lab-scale devices to large-area modules represents one of the major hurdles for commercialization. Given the essential role of the perovskite films in the device performance, it is of critical importance to develop reliable crystallization protocols to deposit high-quality perovskite layers via scalable methods. This review summarizes recent advances in emerging crystallization protocols for the large-scale deposition of perovskite thin films. The unique merits of the well-developed crystallization strategies, including antisolvent, gas quenching, vacuum quenching, etc., are carefully analyzed and discussed. We highlight that, independent of the coating method, creating intermediate phases to decouple the otherwise overlapped solution coating and crystal growth is essential to realize homogeneous coatings of perovskite thin films. Strategies for enhancing the crystal morphology of perovskite films are presented as well, which is vitally important to realize reproducible manufacturing of large-area modules. This tutorial review assists the screening and development of robust crystallization strategies for scalable deposition of high-quality perovskite films for photovoltaic applications.<br

Controlling the electronic interface properties in polymer–fullerene bulk heterojunction solar cells - Wolf, Nadine; Manara, Jochen; Stubhan, Tobias; Dyakonov, Vladimir; Brabec, Christoph (Springer New York LLC, 2016)
This work covers the use of solution-processed metal oxides as interface layers for organic solar cells. To study the interface properties, intrinsic and Al-doped ZnO were chosen as reference systems. From the class of n-type metal oxides, ZnO was chosen because it can be doped when it is solution processed. Furthermore, the influence of thin modification layers applied on top of the metal oxides is investigate
Keywords: Aluminum-doped zinc oxide; Barium hydroxide; Charge transport in nanoparticular films; Conjugated polyelectrolyte; Device structure; Diketopyrrolopyrrole-quinquethiophene; Doped zinc oxide; Electronic surface properties; Energy diagram; Energy-level diagrams; EQE spectra; Inferface layers for organic solar cells; Interface layers; Interface modification layers; Inverted organic solar cells; J-V characteristics; Low temperature; Molybdenum oxide; Mott–Schottky capacitance; Oxygen; P3HT; PCDTBT; Phosphonic acid anchored fullerene SAM; Polyvinylpyrrolidone; Poole–Frenkel effect; Reference solar cells; SAM modification; Stability of interface materials; Stabilization of AZO nanoparticles; Summary; Thickness dependence; Trioxadecanoic acid; Water; Zinc oxide

Correction: A star-shaped D-π-A small molecule based on a tris(2-methoxyphenyl)amine core for highly efficient solution-processed organic solar cells - Min, Jie; Luponosov, Yuriy N.; Solodukhin, Alexander N.; Kausch-Busies, Nina; Ponomarenko, Sergei A.; Ameri, Tayebeh; Brabec, Christoph (Journal of Materials Chemistry C, 2014)
Correction for 'A star-shaped D-π-A small molecule based on a tris(2-methoxyphenyl)amine core for highly efficient solution-processed organic solar cells' by Jie Min et al., J. Mater. Chem. C, 2014, 2, 7614-7620. This journal is

Correction: Balancing electrical and optical losses for efficient 4-terminal Si-perovskite solar cells with solution processed percolation electrodes (Journal of Materials Chemistry A (2018) 6 (3583-3592) DOI: 10.1039/C7TA10945H) - Ramírez Quiroz, César Omar; Shen, Yilei; Salvador, Michael Filipe; Forberich, Karen; Schrenker, Nadine; Spyropoulos, Georgios; Heumüller, Thomas; Wilkinson, Benjamin; Kirchartz, Thomas; Spiecker, Erdmann; Verlinden, Pierre J.; Zhang, Xueling; et al. (Journal of Materials Chemistry A, 2018)
The authors regret inconsistent labelling of the Jsc column in Table 1 of the original manuscript. The experimental conditions are now described correctly in the caption of the updated Table 1, shown below, as indicated by superscripts "b" and "c". (Table Presented). The Royal Society of Chemistry apologises for these errors and any consequent inconvenience to authors and readers

Correction to: Polymer-acid-metal quasi-ohmic contact for stable perovskite solar cells beyond a 20,000-hour extrapolated lifetime (Nature Communications, (2024), 15, 1, (2002), 10.1038/s41467-024-46145-7) - Luo, Junsheng; Liu, Bowen; Yin, Haomiao; Zhou, Xin; Wu, Mingjian; Shi, Hongyang; Zhang, Jiyun; Elia, Jack; Zhang, Kaicheng; Wu, Jianchang; Xie, Zhiqiang; Liu, Chao; et al. (Nature Communications, 2024)
Correction to: Nature Communicationshttps://doi.org/10.1038/s41467-024-46145-7, published online 05 March 2024 In this article, Junsheng Luo and Bowen Liu should have been denoted as equally contributing authors. The original article has been corrected.
CRIS-Team Scopus Importer:2024-05-17

Correlation between the generated string powers of a photovoltaic: Power plant and module defects detected by aerial thermography - Dalsass, Manuel; Scheuerpflug, Hans; Fecher, Frank W.; Buerhop-Lutz, Claudia; Camus, Christian; Brabec, Christoph (43rd IEEE Photovoltaic Specialists Conference, PVSC 2016, 2016)
Drone-based aerial thermography has become a convenient quality assessment tool for photovoltaic power plants. Often caused by defective photovoltaic modules and cells, thermal abnormalities can be localized and classified. So far, infrared images cannot be utilized for the quantitative estimation of the generated power of a solar park yet. In this context, three photovoltaic power plants with an overall nominal power of approximately 9.4 MW are evaluated. The analysis of both the radiometric data and the monitoring data of the inverters indicate a strong correlation between defective modules and the power of the associated string.
Keywords: aerial thermography; monitoring; PV module defects; system performance

Correlation between the generated string powers of a photovoltaic power plant and module defects detected by aerial thermography - Dalsass, Manuel; Scheuerpflug, Hans; Fecher, Frank W.; Buerhop-Lutz, Claudia; Camus, Christian; Brabec, Christoph (44th IEEE Photovoltaic Specialist Conference, PVSC 2017, 2018)
Drone-based aerial thermography has become a convenient quality assessment tool for photovoltaic power plants. Often caused by defective photovoltaic modules and cells, thermal abnormalities can be localized and classified. So far, infrared images cannot be utilized for the quantitative estimation of the generated power of a solar park yet. In this context, three photovoltaic power plants with an overall nominal power of approximately 9.4 MWp are evaluated. The analysis of both the radiometric data and the monitoring data of the inverters indicate a strong correlation between defective modules and the power of the associated stri
Keywords: Aerial thermography; PV module defects; Monitoring; System performance

Correlative relationship between nanomorphology, crystallinity, texture and device efficiency of organic BHJ solar cells studied by energy-filtered TEM - Harreiß, Christina; Wu, Mingjian; Langner, Stefan; Rechberger, Stefanie; Will, Johannes; Brabec, Christoph; Spiecker, Erdmann (Microscopy and Microanalysis, 2021)

Cost analysis of roll-to-roll fabricated ITO free single and tandem organic solar modules based on data from manufacture - Machui, Florian; Hosel, Markus; Li, Ning; Spyropoulos, Georgios; Ameri, Tayebeh; Sondergaard, Roar R.; Jorgensen, Mikkel; Scheel, Arnulf; Gaiser, Detlef; Kreul, Kilian; Lenssen, Daniel; Legros, Mathilde; et al. (Energy and Environmental Science, 2014)
We present a cost analysis based on state of the art printing and coating processes to fully encapsulated, flexible ITO- and vacuum-free polymer solar cell modules. Manufacturing data for both single junctions and tandem junctions are presented and analyzed. Within this calculation the most expensive layers and processing steps are identified. Based on large roll-to-roll coating experiments the exact material consumptions were determined. In addition to the data for the pilot scale experiment presented here, projections to medium and large scale scenarios serve as a guide to achieve cost targets of 5 €ct per W in a detailed material and cost analysis. These scenarios include the replacement of cost intensive layers, as well as process optimization steps. Furthermore, the cost structures for single and tandem devices are listed in detail and discussed. In an optimized model the material costs drop below 10 € per m which proves that OPV is a competitive alternative to established power generation technologies. This journal is © the Partner Organisations 2014.
Keywords: Engineering controlled terms: Coatings; Costs; Experiments; Manufacture; Optimization; Rolls (machine components); Solar cells Coating process; Optimized models; Pilot-scale experiments; Polymer Solar Cells; Power generation technology; Processing steps; Single junction; Tandem junction Engineering main heading: Cost accounting GEOBASE Subject Index: coating; cost-benefit analysis; numerical model; photovoltaic system; solar power

Cost-efficient recycling of organic photovoltaic devices - Sun, Rui; Yuan, Xinxin; Yang, Xinrong; Wu, Yao; Shao, Yiming; Wu, Xiaohei; Brabec, Christoph; Min, Jie (Joule, 2024)
The vast majority of research on organic photovoltaics (OPVs) has focused on improving device efficiency and stability and reducing material costs. However, if one could refurbish OPVs, their stability might not be so demanding, and the reuse of valuable OPV components can reduce the price per watt of solar modules. Herein, we present a dismantling procedure for reusing the active-layer materials without causing performance losses and for recovering the silver electrode and indium tin oxide (ITO)-electrode substrate via chemical and physical processes. Combined with the developed physical mixing methodology, the OPVs fabricated from recycled components also show comparable performance to that of fresh devices. The potential economic analysis points out that this recycling protocol can save 14.24 m−2 in industrial scenarios, strongly demonstrating the possibility of recycling OPVs. This work represents a significant step toward cost-effective, high-yield recycling of waste OPVs while also demonstrating the prospects of no material supply constraints for OPV manufacturing shortly.
CRIS-Team Scopus Importer:2024-07-19
Keywords: economic feasibility; organic photovoltaics; recycling protocol; reuse of materials; sustainability

Critical review of the molecular design progress in non-fullerene electron acceptors towards commercially viable organic solar cells. - Wadsworth, Andrew; Moser, Maximilian; Marks, Adam; Little, Mark S.; Gasparini, Nicola; Brabec, Christoph; Baran, Derya; Mcculloch, Iain (Chemical Society Reviews, 2018)
Fullerenes have formed an integral part of high performance organic solar cells over the last 20 years, however their inherent limitations in terms of synthetic flexibility, cost and stability have acted as a motivation to develop replacements; the so-called non-fullerene electron acceptors. A rapid evolution of such materials has taken place over the last few years, yielding a number of promising candidates that can exceed the device performance of fullerenes and provide opportunities to improve upon the stability and processability of organic solar cells. In this review we explore the structure-property relationships of a library of non-fullerene acceptors, highlighting the important chemical modifications that have led to progress in the field and provide an outlook for future innovations in electron acceptors for use in organic photovoltaics.

Crystallization of sensitizers controls morphology and performance in Si-/C-PCPDTBT-sensitized P3HT: ICBA ternary blends - Du, Xiaoyan; Jiao, Xuechen; Rechberger, Stefanie; Perea Ospina, Jose Dario; Meyer, Markus; Kazerouni, Negar; Spiecker, Erdmann; Ade, Harald; Brabec, Christoph; Fink, Rainer; Ameri, Tayebeh (Macromolecules, 2017)
Organic solar cells based on multinary components are promising to further boost the device performance. The complex interplay of the morphology and functionality needs further investigations. Here, we report on a systematic study on the morphology evolution of prototype ternary systems upon adding sensitizers featuring similar chemical structures but dramatically different crystallinity, namely poly(3-hexylthiophene) (P3HT) and indene-C-bis-adduct (ICBA) blends with poly[(4,4′-bis(2-ethylhexyl)dithieno[3,2-b:2′,3′-d]silole)-2,6-diyl-alt-(4,7-bis(2-thienyl)-2,1,3-benzothiadi-azole)-5,5′-diyl] (Si-PCPDTBT) and poly[2,6-(4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b′]-dithiophene)-alt-4,7-(2,1,3-benzothiadiazole)] (C-PCPDTBT), employing energy-filtered transmission electron microscopy (EFTEM) and resonant soft X-ray scattering (RSoXS). In addition, a combined density functional theory (DFT) and artificial neuronal network (ANN) computational approach has been utilized to calculate the solubility parameters and Flory-Huggins intermolecular parameters to evaluate the influence of miscibility on the final morphology. Our experiments reveal that the domain spacing and purity of ICBA-rich domains are retained in Si-PCPDTBT-based systems but are strongly reduced in C-PCPDTBT-based ternary systems. The P3HT fiber structure are retained at low sensitizer content but dramatically reduced at high sensitizer content. The theoretical calculations reveal very similar miscibility/compatibility between the two sensitizers and ICBA as well as P3HT. Thus, we conclude that mainly the crystallization of Si-PCPDTBT drives the nanostructure evolution in the ternary systems, while this driving force is absent in C-PCPDTBT-based ternary blends.
Keywords: Computation theoryDeep neural networksHigh resolution transmission electron microscopyMorphologyNeuronsOrganic solar cellsSiliconSolar cellsSolubilityTernary systemsTransmission electron microscopyX ray scattering

Crystal-structure of active layers of small molecule organic photovoltaics before and after solvent vapor annealing - Berlinghof, Marvin; Langner, Stefan; Harreiß, Christina; Schmidt, Ella; Siris, Rita; Bertram, Florian; Shen, Chen; Will, Johannes; Schindler, Torben; Prihoda, Annemarie; Rechberger, Stefanie; Duesberg, Georg; et al. (Zeitschrift fur Kristallographie - Crystalline Materials, 2020)
It is demonstrated by a detailed structural analysis that the crystallinity and the efficiency of small molecule based organic photovoltaics can be tuned by solvent vapor annealing (SVA). Blends made of the small molecule donor 2,2′-[(3,3′″,3″″,4′-tetraoctyl[2,2′:5′,2″:5″,2′″:5′″,2″″-quinquethiophene]-5,5″″-diyl)bis[(Z)-methylidyne(3-ethyl-4-oxo-5,2-thiazolidinediylidene)]]bis-propanedinitrile (DRCN5T) and the acceptor [6,6]-phenyl C71 butyric acid methyl ester (PC 71 BM) were annealed using solvent vapors with either a high solubility for the donor (tetrahydrofuran), the acceptor (carbon disulfide) or both (chloroform). The samples were analyzed by grazing-incidence wide-angle X-ray scattering (GIWAXS), electron diffraction, X-ray pole figures, and time-of-flight secondary ion mass spectrometry (ToF-SIMS). A phase separation of DRCN5T and PC 71 BM is induced by SVA leading to a crystallization of DRCN5T and the formation of a DRCN5T enriched layer. The DRCN5T crystallites possess the two dimensional oblique crystal system with the lattice parameters a = 19.2 Å, c = 27.1 Å, and β = 111.1° for the chloroform case. No major differences in the crystal structure for the other solvent vapors were observed. However, the solvent choice strongly influences the size of the DRCN5T enriched layer. Missing periodicity in the [010]-direction leads to the extinction of all Bragg reflections with k ≠ 0. The annealed samples are randomly orientated with respect to the normal of the substrate (fiber texture

Cs2AgxNa1-xBiyIn1-yCl6 perovskites approaching photoluminescence quantum yields of 100% - Stroyuk, Oleksandr; Raievska, Oleksandra; Barabash, Anastasiia; Kupfer, Christian; Osvet, Andres; Dzhagan, Volodymyr; Zahn, Dietrich R. T.; Hauch, Jens; Brabec, Christoph J. (Materials Advances, 2022)
A new single-step and green approach for the synthesis of microcrystalline Cs2AgxNa1-xBiyIn1-yCl6 (CANBIC) perovskites in ambient conditions is introduced. The CANBIC powders emit broadband self-trapped excitonic photoluminescence (PL) with a champion PL quantum yield (QY) of 98 +/- 2% and a PL lifetime of ca. 2 mu s observed for x = 0.40 and y = 0.01-0.02. The study focuses on the dependence of structural, spectral, and photophysical properties of CANBICs on Bi content. CANBICs are solid solutions with isomorphous In-to-Bi substitution with the bandgap and valence band edge energy decreasing gradually with increasing y. The PL QY and the rate constant of the radiative recombination showed volcano-shaped dependences on the Bi content, while the rate of the non-radiative recombination revealed a drastic growth by three orders of magnitude as the Bi fraction y was elevated from 0.01 to 1.0 indicating that BiCl6 units are responsible for non-radiative recombination.
CRIS-Team WoS Importer:2022-09-09

Cutting “lab-to-fab” short: high throughput optimization and process assessment in roll-to-roll slot die coating of printed photovoltaics - Wagner, Michael; Distler, Andreas; Le Corre, Vincent Marc; Zapf, Simon; Baydar, Burak; Schmidt, Hans-Dieter; Heyder, Madeleine; Forberich, Karen; Lüer, Larry; Brabec, Christoph; Egelhaaf, Hans-Joachim (Energy and Environmental Science, 2023)
Commercialization of printed photovoltaics requires knowledge of the optimal composition and microstructure of the single layers, and the ability to control these properties over large areas under industrial conditions. While microstructure optimization can be readily achieved by lab scale methods, the transfer from laboratory scale to a pilot production line (“lab to fab”) is a slow and cumbersome process: first, the difficulty of operating structure-sensitive methods in-line impedes proper microstructure characterization, and second, the processing-functionality relationship must be redetermined for every material combination as the results obtained by typical lab-scale spin-coating cannot be directly transferred to other coating methods. Here, we show how we can optimize the performance of organic solar cells and at the same time assess process performance in a 2D combinatorial approach directly on an industrially relevant slot die coating line. This is enabled by a multi-nozzle slot die coating head allowing parameter variations along and across the web. This modification allows us to generate and analyze 3750 devices in a single coating run, varying the active layer donor : acceptor ratio and the thickness of the electron transport layer (ETL). We use Gaussian Process Regression (GPR) to exploit the whole dataset for precise determination of the optimal parameter combination. Performance-relevant features of the active layer morphology are inferred from UV-Vis absorption spectra. By mapping morphology in this way, small undesired gradients of process conditions (extrusion rates, annealing temperatures) are detected and their effect on device performance is quantified. The correlation between process parameters, morphology and performance obtained by GPR provides hints to the underlying physics, which are finally quantified by automated high-throughput drift-diffusion simulations. This leads to the conclusion that voltage losses which are observed for very thin ETL coatings are due to incomplete coverage of the electrode by the ETL, which causes enhanced surface recombination.
CRIS-Team Scopus Importer:2023-11-10

Data-Filtering-Dependent Variability of Long-Term Degradation Rates of MW-Scale Photovoltaic Power Plants from “Non-Ideal” Monitoring and Weather Data - Camus, Christian; Huettner, Maximilian; Lassahn, D.; Kurz, C.; Hauch, Jens; Brabec, Christoph (35th European Photovoltaic Solar Energy Conference and Exhibition, 2018)
In contrast to research photovoltaic (PV) systems, commercial PV systems are usually not equipped with sophisticated weather metrology and quite frequently even lack an irradiance sensor. Still, the determination of their degradation rate is of paramount importance for the plant owners. This paper compares various approaches to determine the degradation rates of commercial MW-scale PV systems from such “non-ideal” data sets as they are frequently obtained from monitoring data. In particular, the use of model-based irradiance and temperature data is evaluated and several novel methods for data filtering are introduced. It is investigated, for which weather conditions the use of externally weather station data is superior to on-site data. By reducing the data set to mostly sunny conditions, reliable DRs can be determined. Furthermore, the data scattering can be reduced significantly so that sudden performance drops or changes in the DRs become visible, which were previously masked by scattering and data drifts. These results demonstrate that significantly different DRs and uncertainties are obtained depending on the method of data filtering. Hence, care must be taken, when deriving DRs from “non-ideal” monitoring and weather data and when comparing DRs determined by different metho
Keywords: PV Technologies; Outdoor Performance; Yield Analysis; Temperature Behavior

Deciphering the Origins of P1-Induced Power Losses in CIGS Modules Through Hyperspectral Luminescence - Quiroz, César Omar Ramírez; Dion-Bertrand, Laura Isabelle; Brabec, Christoph; Müller, Joachim; Orgassa, Kay (Engineering, 2020)
In this report, we show that hyperspectral high-resolution photoluminescence mapping is a powerful tool for the selection and optimization of the laser ablation processes used for the patterning interconnections of subcells on Cu(Inx,Ga1−x)Se2 (CIGS) modules. In this way, we show that in-depth monitoring of material degradation in the vicinity of the ablation region and the identification of the underlying mechanisms can be accomplished. Specifically, by analyzing the standard P1 patterning line ablated before the CIGS deposition, we reveal an anomalous emission-quenching effect that follows the edge of the molybdenum groove underneath. We further rationalize the origins of this effect by comparing the topography of the P1 edge through a scanning electron microscope (SEM) cross-section, where a reduction of the photoemission cannot be explained by a thickness variation. We also investigate the laser-induced damage on P1 patterning lines performed after the deposition of CIGS. We then document, for the first time, the existence of a short-range damaged area, which is independent of the application of an optical aperture on the laser path. Our findings pave the way for a better understanding of P1-induced power losses and introduce new insights into the improvement of current strategies for industry-relevant module interconnection schemes.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Cell-to-module efficiency gap; CIGS; Hyperspectral photoluminescence; Laser ablation short-range heat effect; P1-induced power losses

Deciphering the Role of Impurities in Methylammonium Iodide and Their Impact on the Performance of Perovskite Solar Cells - Levchuk, Ievgen; Hou, Yi; Gruber, Marco; Brandl, Marco; Herre, Patrick; Tang, Xiaofeng; Högl, Florian; Batentschuk, Miroslaw; Osvet, Andres; Hock, Rainer; Peukert, Wolfgang; Tykwinski, Rik; et al. (Advanced Materials Interfaces, 2016)
Solution-based perovskite solar cell fabrication typically involves rather complex processing sequences to yield highest performance. While most studies concentrate on the exploration of processing conditions, the purity levels of common perovskite precursor solutions have been investigated and a number of impurities that are critically important toward controlling the crystallization of perovskites are found. In this study, an in-depth chemical study of the possible impurities formed during CHNHI preparation is presented and their relevance on solar cell processing is revealed. A primary consideration is the chemical transformation of hypophosphorous acid, which plays the role of the stabilizer for HI. The detrimental role of the impurities is best demonstrated by comparing perovskite solar cell devices fabricated from impurity-free precursors versus precursors containing different concentrations of impurities. Most interestingly, it is revealed that a certain concentration of impurities is detrimental to the growth of large-grained crystals. PbHPO nanoparticles, which are formed after hypophosphorous acid transformation, actually cause crystal domain growth through serving as a nucleation center. This study gives valuable insight into the rate determining steps of perovskite crystal growth and further provides the basis for developing reliable and reproducible high-performance recipes for perovskite solar cell processing.
Keywords: Grain size; Impurities; Perovskites; Seed growth; Solar cells

DeepDeg: Forecasting and explaining degradation in novel photovoltaics - Oviedo, Felipe; Hayden, David S.; Heumüller, Thomas; Wortmann, Jonas; Perea, Jose Dario; Naik, Richa; Xue, Hansong; Lavista, Juan; Fisher, John; Brabec, Christoph; Buonassisi, Tonio (2025)
Degradation is a technical and market hurdle in the development of novel photovoltaics and other energy devices. Understanding and addressing degradation requires complex, time-consuming measurements on multiple samples. To address this challenge, we present DeepDeg, a machine learning model that combines deep learning, explainable machine learning, and physical modeling to: 1) forecast hundreds of hours of degradation, and 2) explain degradation in novel photovoltaics. Using a large and diverse dataset of over 785 stability tests of organic solar cells, totaling 230,000 measurement hours, DeepDeg is able to accurately predict degradation dynamics and explain the physiochemical factors driving them using few initial hours of degradation. We use cross-validation and a held-out dataset of over 9,000 hours of degradation of PCE10:OIDTBR to evaluate our model. We demonstrate that by using DeepDeg, degradation characterization and screening can be accelerated by 5-20x.<br
https://cris.fau.de/converis/publicweb/Publication/320695955
Keywords: solar; degradation; stability; machine learning; photovoltaics; energy

Deep Learning-based Pipeline for Module Power Prediction from EL Measurements - Hoffmann, Mathis; Buerhop-Lutz, Claudia; Reeb, Luca; Pickel, Tobias; Winkler, Thilo; Doll, Bernd; Würfl, Tobias; Peters, Ian Marius; Brabec, Christoph; Maier, Andreas; Christlein, Vincent (Progress in Photovoltaics: Research and Applications, 2021)
Automated inspection plays an important role in monitoring large-scale photovoltaic power plants. Commonly, electroluminescense measurements are used to identify various types of defects on solar modules but have not been used to determine the power of a module. However, knowledge of the power at maximum power point is important as well, since drops in the power of a single module can affect the performance of an entire string. By now, this is commonly determined by measurements that require to discontact or even dismount the module, rendering a regular inspection of individual modules infeasible. In this work, we bridge the gap between electroluminescense measurements and the power determination of a module. We compile a large dataset of 719 electroluminescense measurementsof modules at various stages of degradation, especially cell cracks and fractures, and the corresponding power at maximum power point. Here,we focus on inactive regions and cracks as the predominant type of defect. We set up a baseline regression model to predict the power from electroluminescense measurements with a mean absolute error of 9.0+/-3.7W (4.0+/-8.4%). Then, we show that deep-learning can be used to train a model that performs significantly better (7.3+/-2.7W or 3.2+/-6.5%). With this work, we aim to open a new research topic. Therefore, we publicly release the dataset, the code and trained models to empower other researchers to compare against our results. Finally, we present a thorough evaluation of certain boundary conditions like the dataset size and an automated preprocessing pipeline for on-site measurements showing multiple modules at once.

Defect recognition in crystalline silicon solar cells by X-ray tomosynthesis with layer resolution - Voland, Virginia; Hoyer, Ulrich; Auer, Richard; Salamon, Michael; Uhlmann, Norman; Brabec, Christoph (Progress in Photovoltaics: Research and Applications, 2015)
The increasing demand for higher quality in solar cell production led to the development of several inline control methods. Beneath the image-guided methods, X-ray is not yet very well investigated for the application in photovoltaic research but shows high potential. In contrast to the ordinary X-ray radioscopic method, the tomosynthesis technique exhibits additional depth information of the solar cells and modules. In this article, several applications of tomosynthesis for the investigation of solar cells and modules are studied. It will be shown what potential the application of X-ray and especially tomosynthesis has as quality control tool for photovoltaics.
Keywords: Defect recognition; Metrology; Tomosynthesis; X-ray

Defects and performance of Si PV modules in the field - an analysis - Denz, J.; Hepp, Johannes; Buerhop, C.; Doll, Bernd; Hauch, J.; Brabec, Christoph; Peters, I. M. (Energy and Environmental Science, 2022)
Photovoltaic installations will likely become one of the major power sources in the 21st century and we need photovoltaic modules to operate reliably. In this review, we explore what is known today about the status of installed crystalline silicon photovoltaic modules in the world, how different sources classify module defects, and what we might deduce for future installations. Looking at more than 200 results from 132 installations and 79 reports, we find that PV modules in general are robust in outdoor operation, with about one in 250 modules failing completely each year. About one in ten modules will develop a defect resulting in greater than expected power loss throughout their lifetime, and practically every module will develop visually perceivable alterations. We observe no trends of changes over time in these findings, hence there is no indication that future performance will deviate dramatically. We note though that more information is needed. Available studies represent a module fleet with greater age than current installations, and are over-representing multicrystalline - compared to monocrystalline silicon, and AL-BSF - compared to PERC cell architectures. Studies from Asia and Africa and from tropical climates are underrepresented. A major challenge in the analysis was the variety of metrics used. To facilitate easier comparison, we propose reporting guidelines.
CRIS-Team WoS Importer:2022-05-13

Degradation through Directional Self-Doping and Homogeneous Density of Recombination Centers Hindered by 1,8-Diiodooctane Additive in Non-Fullerene Organic Solar Cells - Almora, Osbel; Wiegand, Julius; Lopez-Varo, Pilar; Matt, Gebhard J.; Brabec, Christoph (Solar RRL, 2021)
Non-fullerene-based organic solar cells (OSCs) have recently proven to perform with efficiencies above 18%. This is an important milestone for one of the most promising technologies in the fields of flexible and transparent/semitransparent photovoltaics. However, the stability of OSCs is still a challenging issue to meet the industry requirements. Herein, several devices with IT-4F:PM6 as the active layer with and without 1,8-Diiodooctane (DIO) additive are characterized before and after a 1400 h degradation test under 1 sun white light-emitting diode (LED) illumination intensity. The optoelectronic study via impedance spectroscopy under illumination at quasi-open-circuit correlates the use of DIO as an additive with a retarded degradation behavior and an overall improved device performance. In dark conditions, the Mott-Schottky analysis suggests that samples without DIO develop self-doping during degradation, changing the p-i-n doping profile into a p-n type, most likely related to the evolution of the blend demixing. These mechanisms are further confirmed by drift-diffusion simulations. Space-oriented redistribution of shallow trap levels (self-doping) and homogeneous increase in deep-trap levels (nonradiative recombination) are shown to be hindered by the use of the DIO additive.
CRIS-Team WoS Importer:2021-03-19

Delocalisation softens polaron electronic transitions and vibrational modes in conjugated polymers - Kahmann, Simon; Loi, Maria A.; Brabec, Christoph (Journal of Materials Chemistry C, 2018)
In this work we study the photoinduced signatures of polarons in conjugated polymers and the impact of charge carrier delocalisation on their spectra. The variation of film crystallinity for two prototypical systems – blends of the homopolymer P3HT or the donor–acceptor polymer PCPDTBT with PCBM – allows probing changes of the polaron absorption in the mid infrared spectral region. Increased polaron delocalisation entails a shift of the electronic transition to lower energy in both cases. Also, infrared active vibrations soften due to a higher polymer chain order. Our findings help in providing a more complete understanding of polaron properties in conjugated materials and bring the application of the polaron absorption spectrum as an indicator for the environment on a more thoroughly studied foundatio

Delocalization of exciton and electron wavefunction in non-fullerene acceptor molecules enables efficient organic solar cells - Zhang, Guichuan; Chen, Xian Kai; Xiao, Jingyang; Chow, Philip C.Y.; Ren, Minrun; Kupgan, Grit; Jiao, Xuechen; Chan, Christopher C.S.; Du, Xiaoyan; Xia, Ruoxi; Chen, Ziming; Yuan, Jun; et al. (Nature Communications, 2020)
A major challenge for organic solar cell (OSC) research is how to minimize the tradeoff between voltage loss and charge generation. In early 2019, we reported a non-fullerene acceptor (named Y6) that can simultaneously achieve high external quantum efficiency and low voltage loss for OSC. Here, we use a combination of experimental and theoretical modeling to reveal the structure-property-performance relationships of this state-of-the-art OSC system. We find that the distinctive π–π molecular packing of Y6 not only exists in molecular single crystals but also in thin films. Importantly, such molecular packing leads to (i) the formation of delocalized and emissive excitons that enable small non-radiative voltage loss, and (ii) delocalization of electron wavefunctions at donor/acceptor interfaces that significantly reduces the Coulomb attraction between interfacial electron-hole pairs. These properties are critical in enabling highly efficient charge generation in OSC systems with negligible donor-acceptor energy offset.
CRIS-Team Scopus Importer:2020-08-14

Designing ternary blend bulk heterojunction solar cells with reduced carrier recombination and a fill factor of 77% - Gasparini, Nicola; Jiao, Xuechen; Heumüller, Thomas; Baran, Derya; Matt, Gebhard; Fladischer, Stefanie; Spiecker, Erdmann; Ade, Harald; Brabec, Christoph; Ameri, Tayebeh (Nature Energy, 2016)
In recent years the concept of ternary blend bulk heterojunction (BHJ) solar cells based on organic semiconductors has been widely used to achieve a better match to the solar irradiance spectrum, and power conversion effciencies beyond 10% have been reported. However, the fill factor of organic solar cells is still limited by the competition between recombination and extraction of free charges. Here, we design advanced material composites leading to a high fill factor of 77% in ternary blends, thus demonstrating how the recombination thresholds can be overcome. Extending beyond the typical sensitization concept, we add a highly ordered polymer that, in addition to enhanced absorption, overcomes limits predicted by classical recombination models. An effective charge transfer from the disordered host system onto the highly ordered sensitizer effectively avoids traps of the host matrix and features an almost ideal recombination behaviour.

Design of donor-acceptor star-shaped oligomers for efficient solution-processible organic photovoltaics - Ponomarenko, S. A.; Luponosov, Y. N.; Min, Jie; Solodukhin, A. N.; Surin, N. M.; Shcherbina, M. A.; Chvalun, S. N.; Ameri, Tayebeh; Brabec, Christoph (Faraday Discussions, 2014)
This contribution describes recent progress in the design, synthesis and properties of solution-processible star-shaped oligomers and their application in organic photovoltaics. Even though alternative chemistry has been used to design such oligomers, the most successful approach is based on a triphenylamine donor branching center, (oligo)thiophene conjugated spacers and dicyanovinyl acceptor groups. These are mainly amorphous low band-gap organic semiconductors, though crystalline or liquid crystalline ordering can sometimes be realized. It was shown that the solubility, thermal behavior and structure of such molecules in the bulk strongly depend on the presence and position of alkyl groups, as well as on their length. The photovoltaic properties of solution-processed molecules of this type are now approaching 5% which exceeds those of vacuum-sublimed devices. The design rules and future perspectives of this class of organic photovoltaic molecules are discussed.

Design of Highly Efficient Semitransparent Perovskite/Organic Tandem Solar Cells - Rossi, Daniele; Forberich, Karen; Matteocci, Fabio; Der Maur, Matthias Auf; Egelhaaf, Hans-Joachim; Brabec, Christoph; Di Carlo, Aldo (Solar RRL, 2022)
Solar cells transparent in the visible range are highly requested for integration in see-through photovoltaic (PV) applications such as building glass façades or greenhouse roofs. The development of advanced transparent PV can fully exploit the tandem technology where the top cell absorbs the near-ultraviolet solar spectrum while the bottom one absorbs the near-infrared part. Herein, a possible implementation of this tandem PV paradigm, namely, the tandem structure composed of a high-bandgap halide perovskite solar cell and a low-bandgap organic solar cell, is considered. Electro-optical simulation results based on parameters calibrated on experimental data show that an efficiency of 15% can be achieved with an average visible transmittance above 50%. This can be obtained considering the halide perovskite with mixed chlorine and bromine anions, a nonfullerene-based bulk heterojunction, a well-calibrated light management, and a three-terminal configuration of the tandem.
CRIS-Team Scopus Importer:2022-07-08
Keywords: organic solar cells; pervoskite solar cells; solar cell simulations; tandem perovskite/organic solar cells; transparent solar cells

Design of low band gap small molecules with alkyldicyanovinyl acceptor and different donor groups for efficient bulk heterojunction organic solar cells - Luponosov, Yuriy N.; Min, Jie; Solodukhin, Alexander N.; Chvalun, Sergei N.; Ameri, Tayebeh; Brabec, Christoph; Ponomarenko, Sergey A. (2015 Organic Photovoltaics XVI, 2015)
A library of low band gap small molecules with alkyldicyanovinyl acceptor and triphenylamine, tris(2-methoxyphenyl)amine or dithienosilole donor groups linked through (oligo)thiophene conjugated spacers was designed and successfully synthesized. Systematic variations of the alkyl chain length and the number of conjugated thiophene rings in the molecules allowed to elucidate the structure-properties relationships for their solubility, absorption spectra, phase behavior, morphology and structure in thin films, as well as photovoltaic properties. Bulk heterojunction organic solar cells prepared from these molecules as donors and PCBM[70] as acceptor by solution processing showed power conversion efficiency up to 5.4-6.4%.
Keywords: bulk heterojunction; dicyanovinyl; dithienosilole; donor-acceptor oligomers; oligothiophenes; Organic photovoltaics; solution processing; triphenylamine

Design of the solution-processed intermediate layer by engineering for inverted organic multi junction solar cells - Li, Ning; Stubhan, Tobias; Baran, Derya; Min, Jie; Wang, Haiqiao; Ameri, Tayebeh; Brabec, Christoph (Advanced Energy Materials, 2013)
An equivalent ohmic contact is successfully formed between low-conductivity poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate)(PEDOT:PSS) and solution-processed aluminum-doped ZnO (AZO). Because of its promising optical and electrical properties, this combination can serve as an efficient interconnection layer as well as an optical spacer in inverted-structure organic tandem devices. © 2013 WILEY-VCH Verlag GmbH & Co.
Keywords: Aluminum-doped ZnO; Interconnection layers; Intermediate layers; Multi junction solar cells; Optical and electrical properties; Poly(3; 4-ethylenedioxythiophene):poly(styrenesulfonate); Solution-processed; Tandem devices Engineering controlled terms: Conducting polymers; Ohmic contacts; Zinc oxide Engineering main heading: Electric properties

Detailed optical modelling and light-management of thin-film organic solar cells with consideration of small-area effects - Lipovšek, Benjamin; Čampa, Andrej; Guo, Fei; Brabec, Christoph; Forberich, Karen; Krč, Janez; Topič, Marko (Optics Express, 2017)
We present detailed numerical and experimental investigation of thin-film organic solar cells with a micro-textured light management foil applied on top of the front glass substrate. We first demonstrate that measurements of small-area laboratory solar cells are susceptible to a significant amount of optical losses that could lead to false interpretation of the measurement results. Using the combined optical model CROWM calibrated with realistic optical properties of organic films and other layers, we identify the origins of these losses and quantify the extent of their influence. Further on, we identify the most important light management mechanisms of the micro-textured foil, among which the prevention of light escaping at the front side of the cell is revealed as the dominant one. Detailed three-dimensional simulations show that the light-management foil applied on top of a large-area organic solar cell can reduce the total reflection losses by nearly 60% and improve the short-circuit current density by almost 20%. Finally, by assuming realistic open-circuit voltage and especially the realistic fill factor that deteriorates as the absorber layer thickness is increased, we determine the optimal absorber layer thickness that would result in the highest power conversion efficiency of the investigated organic solar cells.
Keywords: Engineering controlled terms: Open circuit voltage; Optical films; Optical properties; Organic solar cells; Substrates; Thin film solar cells; Thin films Experimental investigations; Glass substrates; Light management; Optical modeling; Optical modelling; Power conversion efficiencies; Three dimensional simulations; Total reflection Engineering main heading: Solar cells

Detection of X-ray photons by solution-processed lead halide perovskites - Yakunin, Sergii; Sytnyk, Mykhailo; Kriegner, Dominik; Shrestha, Shreetu; Richter, Moses; Matt, Gebhard; Azimi, Hamed; Brabec, Christoph; Stangl, Julian; Kovalenko, Maksym V.; Heiß, Wolfgang (Nature Photonics, 2015)
The evolution of real-time medical diagnostic tools such as angiography and computer tomography from radiography based on photographic plates was enabled by the development of integrated solid-state X-ray photon detectors made from conventional solid-state semiconductors. Recently, for optoelectronic devices operating in the visible and near-infrared spectral regions, solution-processed organic and inorganic semiconductors have also attracted a great deal of attention. Here, we demonstrate a possibility to use such inexpensive semiconductors for the sensitive detection of X-ray photons by direct photon-to-current conversion. In particular, methylammonium lead iodide perovskite (CH3NH3PbI3) offers a compelling combination of fast photoresponse and a high absorption cross-section for X-rays, owing to the heavy Pb and I atoms. Solution-processed photodiodes as well as photoconductors are presented, exhibiting high values of X-ray sensitivity (up to 25 μC mGyair-1 cm-3) and responsivity (1.9 × 104 carriers/photon), which are commensurate with those obtained by the current solid-state technology.
Keywords: Engineering controlled terms: Chemical detection; Diagnosis; Diagnostic radiography; Infrared devices; Lead; Optoelectronic devices; Perovskite; Photons; Single crystals; Solid state device structures Absorption cross sections; Inorganic semiconductors; Medical diagnostic tools; Sensitive detection; Solid state semiconductors; Solid state technology; Solution-processed; Visible and near infrared Engineering main heading: X ray radiography

Determination of phase diagrams of binary and ternary organic semiconductor blends for organic photovoltaic devices - Li, Ning; Machui, Florian; Waller, David; Koppe, Markus; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2011)
Ternary blends were recently suggested as a sound approach to increase the short circuit current density of organic solar cells by sensitizing the bulk heterojunction (BHJ) with a further absorber, i.e., a low band gap polymer. Poly[2,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b́]dithiophene) -alt-4,7(2,1,3-benzothiadiazole)] (PCPDTBT) is a suitable candidate as low band gap polymer for ternary blends with poly(3-hexylthiophene) (P3HT) and [6,6]-pheny-C-butyric acid methyl ester ([60]PCBM) due to its ideal energy level and charge carrier properties. Phase diagrams are common in polymer science to visualize the mixing behavior of multicomponent systems as a function of temperature. In this study, we have used differential scanning calorimetry (DSC) to extract phase diagrams for binary and ternary organic semiconductor blends, and built the corresponding solar cells to analyze correlations between the thermal and the electrical properties of such semiconductor blends. © 2011 Elsevier B.V. All rights reserved.
Keywords: Differential scanning calorimetry (DSC); Organic photovoltaic devices; P3HT/PCBM/PCPDTBT; Phase diagram; Ternary blends

Determination of solubility parameters for organic semiconductor formulations - Machui, Florian; Abbott, Steven; Waller, David; Koppe, Markus; Brabec, Christoph (Macromolecular Chemistry and Physics, 2011)
The concept of Hansen solubility parameters (HSP) is applied to organic semiconductors in order to determine and predict their solubility behavior, which is essential for the design of functional and environmentally friendly ink formulations for organic photovoltaics. Two different conjugated polymers, one semicrystalline and one dominantly amorphous, and one fullerene derivative are selected as prototype candidates to evaluate the applicability of the HSP concept for organic semiconductors. The method for determining the solubility parameters is described and the quality of the HSP fits as well as their suitability for designing of organic electronic inks are discussed in detail. The applicability of Hansen solubility parameters in designing organic semiconductor ink formulations is analyzed by determining and predicting the solubility behavior of three different organic semiconductors. A large number of solvents are studied and temperature-dependent solubility is examined to enhance the practical relevance of this work. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: conjugated polymers; fullerenes; Hansen solubility parameters (HSP); ink formulations; organic photovoltaics

Determination of the complex refractive index of powder phosphors - Solodovnyk, Anastasiia; Riedel, Daniel; Lipovšek, Benjamin; Osvet, Andres; Gast, Jessica; Stern, Edda; Forberich, Karen; Batentschuk, Miroslaw; Krč, Janez; Topič, Marko; Brabec, Christoph (Optical Materials Express, 2017)
We demonstrate a novel 2-step method to precisely determine both n and k of phosphors, luminescent inorganic particles, in the visible spectrum. To measure n we modified the Becke Line immersion method and verified its applicability in the absorption/ emission regions of phosphor particles (step 1). Particles were then embedded into a transparent binder and coated in thick layers (100-500 μm) on glass. Absorptance of the layers was measured with a novel approach: spectral angular resolved measurements. This method delivers accurate results by avoiding any errors from intense scattering inside the layers. A computational model was employed to extract k of particles from the measured absorptance data taking into account luminescence, scattering and re-absorption (step 2). The entire method was verified on reference materials. Finally, based on the proposed method, we determined in a broad wavelength range the n and k parameters for a variety of commonly used phosphors with few or no earlier reports on their n and k values (the complete set of numerical data is fully disclosed in the supplementary materials). © 2017 Optical Society of America.
Keywords: Light emission; Luminescence; Phosphors; Refractive index; Complex refractive index; Computational model; Immersion method; Inorganic particles; Phosphor particles; Powder phosphors; Reference material; Wavelength ranges; Numerical methods

Determination of the P3HT:PCBM solubility parameters via a binary solvent gradient method: Impact of solubility on the photovoltaic performance - Machui, Florian; Langner, Stefan; Zhu, Xiangdong; Abbott, Steven; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2012)
We discuss an alternative route to determine the solubility parameters of two prototype organic semiconductors, namely the semi-crystalline polymer poly-(3-hexylthiophene-2,5-diyl) (P3HT) and the methano-fullerene derivative [6,6]-phenyl-C -butyric acid methyl ester (PCBM). The HSP (Hansen solubility Parameters) derived by this novel method are compared to the findings derived from the classical multi-solvent method to determine the HSP, and significantly higher accuracy is found. For this novel approach we designed two component solvent blend systems, being composed by mixing a solvent with a non-solvent. Varying the composition of the solvent non-solvent blends from 0% to 100% gradually converts a solvent into a non-solvent. This very accurate control of the dispersive, polar and hydrogen contributions to the overall solubility now allows determining the Hansen sphere for P3HT and PCBM with much higher accuracy. The transition from a solvent into a non-solvent was further followed by solar cell investigations. Comparing the solubility studies with device investigations allows identifying the processing limits of solvent systems. © 2012 Elsevier B.V. All rights reserved.
Keywords: Conjugated polymers; Fullerenes; Hansen solubility parameters; Ink formulations; Organic photovoltaics; Solvent blends

Determining the coating speed limitations for organic photovoltaic inks - Jakubka, Florian; Heyder, Madeleine; Kaschta, Joachim; Machui, Florian; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2013)
To determine the output capability of present organic photovoltaic (OPV) materials, it is important to know the theoretical maximum coating speeds of the used semiconductor formulations. Here, we present a comprehensive investigation of the coating stability window of several prototype organic semiconductor inks relevant for organic solar cells. The coating stability window was first determined experimentally by a sheet to sheet coater at velocities of up to 10 m/min. A numerical simulation model based on the "Coating Window Suite 2010" software was established to give insight into the coating stability limitations at higher coating velocities. An analysis of PEDOT:PSS [poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate)] in a water/isopropyl alcohol mixture as well as P3HT:PCBM [poly(3-hexylthiophene-2,5-diyl):Phenyl-C61-butyric acid methyl ester] in chlorobenzene, o-xylene and tetrahydronaphthalene showed the possibility of coating speeds up to 60 m/min. The simulation further revealed the maximum coating head distances for a given wet film thickness. Finally, we show a solar-cell with slot-die coated PEDOT:PSS and P3HT:PCBM-layer based on the parameters obtained by the simulated data, which exhibits reasonable performance. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: OPV solar cell; Slot-die coating; Coating speed

Determining the internal quantum efficiency of organic Bulk Heterojunctions based on mono and bisadduct fullerenes as acceptor - Azimi, Hamed; Morana, Mauro; Ameri, Tayebeh; Dastmalchi, Babak; Scharber, Markus; Hingerl, Kurt; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2011)
With the aid of optical modeling, the internal quantum efficiencies of organic Bulk Heterojunction (oBHJ) photovoltaic devices based on low band gap polymer of poly[(4,4′-bis(2-ethylhexyl)dithieno[3,2-b:2′,3′-d] silole)-2,6-diyl-alt-(4,7-bis(2-thienyl)-2,1,3-benzothiadiazole)-5, 5′-diyl] (Si-PCPDTBT) blended with the acceptors of 1-(3-Methoxycarbonyl) propyl-1-phenyl [6,6] C61 (PCBM) and bisadduct (bisPCBM) are determined. The Si-PCPDTBT:bisPCBM devices show considerably lower short circuit current density (J) as compared to the Si-PCPDTBT:PCBM devices. The results show that 30% of this smaller J is due to the lower optical absorption of bisPCBM, while the major losses originate from the electrical losses. It is found that for the best Si-PCPDTBT:bisPCBM devices with an active layer thickness in the range of 70100 nm, the inefficient charge generation within the bisPCBM domains is the major contribution to the whole losses. Increasing the active layer thickness of Si-PCPDTBT:bisPCBM device significantly enhances recombination losses in polymer/bisfullerene matrix. © 2011 Elsevier B.V. All rights reserved.
Keywords: Charge generation; Fullerene bisadduct; Internal quantum efficiency; Organic solar cell; Recombination

Development of efficient and stable inverted bulk heterojunction (BHJ) solar cells using different metal oxide interfaces - Litzov, Ivan; Brabec, Christoph (Materials, 2013)
Solution-processed inverted bulk heterojunction (BHJ) solar cells have gained much more attention during the last decade, because of their significantly better environmental stability compared to the normal architecture BHJ solar cells. Transparent metal oxides (MeO) play an important role as the dominant class for solution-processed interface materials in this development, due to their excellent optical transparency, their relatively high electrical conductivity and their tunable work function. This article reviews the advantages and disadvantages of the most common synthesis methods used for the wet chemical preparation of the most relevant n-type- and p-type-like MeO interface materials consisting of binary compounds AB. Their performance for applications as electron transport/extraction layers (ETL/EEL) and as hole transport/extraction layers (HTL/HEL) in inverted BHJ solar cells will be reviewed and discussed. © copy 2013 by the authors; licensee MDPI, Basel, Switzerland.
Keywords: Device stability; Inverted structure; Metal oxide interfaces; Sol-gel methods

Device Performance of Emerging Photovoltaic Materials (Version 1) - Almora, Osbel; Baran, Derya; Bazan, Guillermo C.; Berger, Christian; Cabrera, Carlos I.; Catchpole, Kylie R.; Erten-Ela, Sule; Guo, Fei; Hauch, Jens; Ho-Baillie, Anita W.Y.; Jacobsson, T. Jesper; Janssen, Rene A.J.; et al. (Advanced Energy Materials, 2020)
Emerging photovoltaics (PVs) focus on a variety of applications complementing large scale electricity generation. Organic, dye-sensitized, and some perovskite solar cells are considered in building integration, greenhouses, wearable, and indoor applications, thereby motivating research on flexible, transparent, semitransparent, and multi-junction PVs. Nevertheless, it can be very time consuming to find or develop an up-to-date overview of the state-of-the-art performance for these systems and applications. Two important resources for recording research cells efficiencies are the National Renewable Energy Laboratory chart and the efficiency tables compiled biannually by Martin Green and colleagues. Both publications provide an effective coverage over the established technologies, bridging research and industry. An alternative approach is proposed here summarizing the best reports in the diverse research subjects for emerging PVs. Best performance parameters are provided as a function of the photovoltaic bandgap energy for each technology and application, and are put into perspective using, e.g., the Shockley–Queisser limit. In all cases, the reported data correspond to published and/or properly described certified results, with enough details provided for prospective data reproduction. Additionally, the stability test energy yield is included as an analysis parameter among state-of-the-art emerging PVs.
CRIS-Team Scopus Importer:2020-12-11
Keywords: bandgap energy; emerging photovoltaics; flexible photovoltaics; photovoltaic device photostability; transparent and semitransparent solar cells

Discerning recombination mechanisms and ideality factors through impedance analysis of high-efficiency perovskite solar cells - Almora, Osbel; Cho, Kyung Taek; Aghazada, Sadig; Zimmermann, Iwan; Matt, Gebhard; Brabec, Christoph; Nazeeruddin, Mohammad Khaja; Garcia-Belmonte, Germa (Nano Energy, 2018)
The ubiquitous hysteresis in the current-voltage characteristic of perovskite solar cells (PSCs) interferes in a proper determination of the diode ideality factor (n), a key parameter commonly adopted to analyze recombination mechanisms. An alternative way of determining n is by measuring the voltage variation of the ac resistances in conditions of negligible steady-state dc currents. A reliable analysis of n based on the determination of the resistive response, free of hysteretic influences, reveals two separated voltage exponential dependences using different perovskite absorbers (3D perovskites layer based on CH3NH3PbI3 or mixed Cs(0.1)FA(0.74)MA(0.13)PbI(2.48)Br(0.39)) and a variety of interlayers (2D perovskite thin capping). The dominant resistive element always exhibits an exponential dependence with factor n approximate to 2, irrespective of the type of perovskite and capping layers. In addition, a non-negligible resistive mechanism occurs at low-frequencies (with voltage-independent time constant similar to 1 s) which is related to the kinetic properties of the outer interfaces, with varying ideality factor (n = 2 for CH3NH3PbI3, and n = 1.5 for Cs(0.1)FA(0.74)MA(0.13)PbI(2.48)Br(0.39)). Our work identifies common features in the carrier recombination mechanisms among different types of high-efficiency PSCs, and simultaneously signals particularities on specific architectures, mostly in the carrier dynamics at outer interfaces.
Keywords: Perovskites solar cells; Recombination; Impedance spectroscopy; Capacitance; 2D capping

Discovering hidden relations in organic semiconductor composites – a concept to accelerate the development of organic photovoltaics - Brabec, Christoph (13th Conference on Hybrid and Organic Photovoltaics (HOPV21), 2021)
While c-Si appears untouchable as leading PV main stream technology for a longer time, many of the new applications which rely on flexibility, transparency, colour management, integrability or simply elegant appearance require novel photovoltaic materials and technologies. Organic photovoltaics (OPV), like other emerging thin film PV technologies, are not yet part of this global TW scenario. The first printed PV products were launched in 2008/2009 for portable chargers at an efficiency of about 2 %. Despite the rather low performance at that time, these first products already showed the characteristic “OPV features” like flexibility, transparency and colour variability. Since then, the printed PV community has concentrated on developing novel material systems for higher efficiency – a development which was outstandingly successful. In the last 10 years. Organic solar modules with close to 13 % efficiency were certified in 2020, while single junction cells already reach 18 % power conversion efficiency. Despite the great process, OPV is still facing multiple challenges, from lifetime to cost and to environmental aspects. The most urgent question therefore is – how can we accelerate the development of organic solar cells towards a market ready product. In this talk I will discuss concepts and strategies to speed-up the development of OPV technologies towards an earlier deployment on the market. Automated, robot-based research lines with shared interfaces to multi-objective machine learning based optimization routines are introduced as a powerful concept to accelerate the development of new materials towards markets. Despite the commonly accepted understanding that machine learning algorithms can accelerate optimization, we demonstrate that physical model-based AI is superior in discovering hidden relations. We will demonstrate that in specific cases it is becoming possible to predict efficiency or even stability of organic solar cells based on a simple absorption measurement.

Discovery of temperature-induced stability reversal in perovskites using high-throughput robotic learning - Zhao, Yicheng; Hauch, Jens; Zhang, Jiyun; Xu, Zhengwei; Sun, Shijing; Langner, Stefan; Hartono, Noor Titan Putri; Heumüller, Thomas; Hou, Yi; Elia, Jack; Li, Ning; Matt, Gebhard; et al. (Nature Communications, 2021)
Stability of perovskite-based photovoltaics remains a topic requiring further attention. Cation engineering influences perovskite stability, with the present-day understanding of the impact of cations based on accelerated ageing tests at higher-than-operating temperatures (e.g. 140°C). By coupling high-throughput experimentation with machine learning, we discover a weak correlation between high/low-temperature stability with a stability-reversal behavior. At high ageing temperatures, increasing organic cation (e.g. methylammonium) or decreasing inorganic cation (e.g. cesium) in multi-cation perovskites has detrimental impact on photo/thermal-stability; but below 100°C, the impact is reversed. The underlying mechanism is revealed by calculating the kinetic activation energy in perovskite decomposition. We further identify that incorporating at least 10 mol.% MA and up to 5 mol.% Cs/Rb to maximize the device stability at device-operating temperature (<100°C). We close by demonstrating the methylammonium-containing perovskite solar cells showing negligible efficiency loss compared to its initial efficiency after 1800 hours of working under illumination at 30°C.
CRIS-Team Scopus Importer:2021-05-21

Discriminating bulk versus interface shunts in organic solar cells by advanced imaging techniques - Karl, André; Osvet, Andres; Vetter, Andreas; Maisch, Philipp; Li, Ning; Egelhaaf, Hans Joachim; Brabec, Christoph (Progress in Photovoltaics: Research and Applications, 2019)
An important aspect when upscaling organic photovoltaics from laboratory to industrial scale is quality control. Established imaging techniques like lock‐in thermography or luminescence imaging are frequently used for this purpose. While these techniques allow for the lateral detection of defects, they cannot provide information on the vertical position of the defect in the OPV stack. Here, we present an approach to overcome this limitation. A femtosecond‐laser is deployed to introduce well‐defined artificial calibration defects selectively into both the interface and the bulk active layer of inverted P3HT:PCBM bulk heterojunction cells during device fabrication. The defective cells are then characterized using J‐V analysis and several nondestructive imaging methods (dark lock‐in thermography, photoluminescence, and electroluminescence imaging). The distinct response for each defect in the different imaging methods enables us to uniquely distinguish between bulk and interface defects. This allows to study surface recombination under most controlled conditions.
Keywords: imaging; organic solar cells; dark lock-in thermography; electroluminescence; photoluminescence; quality control

Disorder-Induced Open-Circuit Voltage Losses in Organic Solar Cells during Photoinduced Burn-In - Heumueller, Thomas; Burke, Timothy M.; Mateker, William R.; Sachs-Quintana, Isaac T.; Vandewal, Koen; Brabec, Christoph; Mcgehee, Michael D. (Advanced Energy Materials, 2015)
The photoinduced open-circuit voltage (Voc) loss commonly observed in bulk heterojunction organic solar cells made from amorphous polymers is investigated. It is observed that the total charge carrier density and, importantly, the recombination dynamics are unchanged by photoinduced burn-in. Charge extraction is used to monitor changes in the density of states (DOS) during degradation of the solar cells, and a broadening over time is observed. It is proposed that the Voc losses observed during burn-in are caused by a redistribution of charge carriers in a broader DOS. The temperature and light intensity dependence of the Voc losses can be described with an analytical model that contains the amount of disorder broadening in a Gaussian DOS as the only fit parameter. Finally, the Voc loss in solar cells made from amorphous and crystalline polymers is compared and an increased stability observed in crystalline polymer solar cells is investigated. It is found that solar cells made from crystalline materials have a considerably higher charge carrier density than those with amorphous materials. The effects of a DOS broadening upon aging are suppressed in solar cells with crystalline materials due to their higher carrier density, making crystalline materials more stable against Voc losses during burn-in.
Keywords: charge carrier densities; disorders; morphology; organic photovoltaics; solar cells; stabilities

Distinguishing between different types of multi-layered PET-based backsheets of PV modules with near-infrared spectroscopy - Stroyuk, Oleksandr; Buerhop-Lutz, Claudia; Vetter, Andreas; Hepp, Johannes; Hauch, Jens; Peters, Ian Marius; Brabec, Christoph J. (Progress in Photovoltaics, 2021)
Degradation of backsheets (BSs) of commercial silicon PV modules is currently recognized as a source of reduced module performance and module failure. Monitoring of the BS state in the field is possible by using non-destructive and highly informative near-infrared absorption (NIRA) spectroscopy. Application of NIRA for the analysis of multi-layer polyethylene terephtalate (PET) based BSs, which dominate the PV module market, is challenging due to a large variety of possible BS configurations that show only small differences in NIRA spectra. In the present work, a spectroscopic tool for the structural identification of PET-based BSs is introduced. The method is based on a principal component analysis of a database of 250 representative NIRA spectra of BSs of different types. It allows a BS with an unknown structure to be assigned to one of 12 different types based solely on its NIRA spectrum. The identification was successfully validated on a test collection of 45 selected BSs and shown to be feasible for the field deployment. Further automation of NIRA measurements and spectral analysis are expected to elevate the proposed tool to the level of a non-intrusive high-throughput field analysis of the BS composition and state in operating PV module grids.
CRIS-Team Scopus Importer:2021-11-19
Keywords: multispectral Raman imaging; polyethylene terephtalate; principal component analysis; PV module backsheets; spectral characterization

Does Covid-19 Impact Photovoltaics? - Peters, Ian Marius; Brabec, Christoph; Buonassisi, Tonio; Hauch, Jens; Nobre, Andre M. (2020 47TH IEEE PHOTOVOLTAIC SPECIALISTS CONFERENCE (PVSC), 2020)
CRIS-Team WoS Importer:2021-06-25

Dopant-Free Bithiophene-Imide-Based Polymeric Hole-Transporting Materials for Efficient and Stable Perovskite Solar Cells - Bai, Yuanqing; Zhou, Zhisheng; Xue, Qifan; Liu, Chunchen; Li, Ning; Tang, Haoran; Zhang, Jiabin; Xia, Xinxin; Zhang, Jie; Lu, Xinhui; Brabec, Christoph; Huang, Fei (Advanced Materials, 2022)
The development of hole-transport materials (HTMs) with high mobility, long-term stability, and comprehensive passivation is significant for simultaneously improving the efficiency and stability of perovskite solar cells (PVSCs). Herein, two donor-acceptor (D-A) conjugated polymers PBTI and PFBTI with alternating benzodithiophene (BDT) and bithiophene imide (BTI) units are successfully developed with desirable hole mobilities due to the good planarity and extended conjugation of molecular backbone. Both copolymers can be employed as HTMs with suitable energy levels and efficient defect passivation. Shortening the alkyl chain of the BTI unit and introducing fluorine atoms on the BDT moiety effectively enhances hole mobility and hydrophobicity of the HTMs, leading to improved efficiency and stability of PVSCs. As a result, the organic-inorganic hybrid PVSCs with PFBTI as the HTM deliver a power conversion efficiency (PCE) of 23.1% with enhanced long-term operational and ambient stability, which is one of the best efficiencies reported for PVSCs with dopant-free polymeric HTMs to date. Moreover, PFBTI can be applied in inorganic PVSCs and perovskite/organic tandem solar cells, achieving a high PCE of 17.4% and 22.2%, respectively. These results illustrate the great potential of PFBTI as an efficient and widely applicable HTM for cost-effective and stable PVSCs.
CRIS-Team WoS Importer:2022-11-11

Dopant mapping in highly p-doped silicon by micro-Raman spectroscopy at various injection levels - Kunz, Thomas; Hessmann, Maik T.; Seren, S.; Meidel, B.; Terheiden, B.; Brabec, Christoph (Journal of Applied Physics, 2013)
Micro-Raman spectroscopy has been used to investigate the acceptor distribution in highly p-doped silicon. As an example, the dopant distribution in crystalline thin-film layers, as developed for solar cells, was mapped. The method is based on the analysis of the Fano-type Raman peak shape which is caused by free charge carriers. For calibration of the Raman acceptor measurements (excitation at a wavelength of 532 nm), we used mono-crystalline reference samples whose acceptor concentration was determined by electrochemical capacitance voltage. We find a significant influence of light induced free charge carriers on the peak shape which results from typical Raman excitation. Thus, the selection of a suitable intensity is important to avoid a too low signal-to-noise ratio on the one hand and systematic errors due to light induced carriers on the other hand. Different evaluation methods, i.e., peak asymmetry versus peak width analysis, are compared in respect to interference caused by random noise of the spectra or else by internal stress in the sample. While the width analysis method is more robust to a low signal-to-noise ratio, the symmetry analysis is more reliable in case of high intrinsic stress. © 2013 American Institute of Physics.
Keywords: Acceptor concentrations; Analysis method; Dopant distribution; Electrochemical capacitance voltage; Evaluation methods; Free charge carriers; Injection levels; Intrinsic stress; Low signal-to-noise ratio; Micro Raman Spectroscopy; Peak asymmetry; Peak shapes; Peak widths; Raman excitation; Raman peak; Random noise; Symmetry analysis; Thin film layers Engineering controlled terms: Charge carriers; Crystalline materials; Phosphorus; Raman spectroscopy; Signal to noise ratio Engineering main heading: Silicon

Doping/Alloying Pathways to Lead-Free Halide Perovskites with Ultimate Photoluminescence Quantum Yields - Stroyuk, Oleksandr; Raievska, Oleksandra; Hauch, Jens; Brabec, Christoph (Angewandte Chemie International Edition, 2022)
Tailored modifications of halide lead-free perovskites (LFPs) via doping/alloying with metal cations have been recognized as a promising pathway to highly efficient inorganic phosphors with photoluminescence (PL) quantum yields of up to 100%. Such materials typically reveal selective sensitivity to UV light, a broad PL range, large PL lifetimes as well as a unique compositional variability and stability – an ideal combination for many light-harvesting applications. The minireview presents the state-of-the-art in doped LFPs, focusing on the reports published mostly in the last 2-3 years. We discuss the factors determining the efficiency and spectral parameters of the broadband PL of doped LFPs depending on the dopant and host matrix, both in micro- and nanocrystalline states, address the most relevant challenges this rapidly developing research area is facing, and outline the most promising concepts to further progress in this field to be achieved.
CRIS-Team Scopus Importer:2022-12-16
Keywords: elpasolites; inorganic perovskites; light conversion; light emission; photophysical properties

Doping of Mesoscopic Charge Extraction Layers Enables the Design of Long-Time Stable Organic Solar Cells - Xu, Junyi; Luo, Junsheng; Gubanov, Kirill; Barabash, Anastasiia; Fink, Rainer; Heumüller, Thomas; Brabec, Christoph (ACS Energy Letters, 2024)
Realizing efficient and stable organic solar cells (OSCs) via all-solution processing requires the design of tailored charge extraction interfaces. Herein, we demonstrate a substantially different interface concept for OSC that is based on a low-temperature processed mesoscopic hole transporting layer (HTL) derived from partially covered organic nanoparticles (NPs) in the n-i-p structure. The mesoscopic interface is further doped in a second coating step with an organic salt dopant, BCF-Li. The interactions among the dopant, the solvent for sequential doping, and the semiconductor layer are surprisingly complex. The mesoscopic interface is necessary to evenly wet the semiconductor and prevent the aggregation of the dopant. At the same time, the sequential process reduces the excess acceptor at the interface. Both processes together are necessary to generate an efficiently doped interface for low-Ohmic-charge extraction and stable contacts. Devices with fully solution-processed mesoscopic interfaces show a superb shelf lifetime of over 22000 h without encapsulation and a long-term operational stability under 1 sun illumination for 2000 h (T80). Flexible devices bypass 1000 bending cycles with negligible degradation. Mesoscopic doped interfaces are demonstrated as an alternative to PEDOT:PSS as well as PEDOT related interface concepts for nonfullerene acceptors (NFA) in the n-i-p architecture.
CRIS-Team Scopus Importer:2024-01-12

Double-Cable Conjugated Polymers Based on Simple Non-Fused Electron Acceptors for Single-Component Organic Solar Cells - Liu, Baiqiao; Liang, Shijie; Karuthedath, Safakath; He, Yakun; Wang, Jing; Tan, Wen Liang; Li, Hao; Xu, Yunhua; Laquai, Frederic; Brabec, Christoph; Mcneill, Christopher R.; Xiao, Chengyi; et al. (Macromolecules, 2023)
In this work, a non-fused electron acceptor with near-infrared absorption was introduced into double-cable conjugated polymers for single-component organic solar cells (SCOSCs). The non-fused electron acceptor contains a simple thienyl-phenyl-thienyl core with 2-(3-oxo-2,3-dihydroinden-1ylidene)malononitrile (IC) as the end group, which was used as the side unit to create double-cable conjugated polymers. In addition, poly(benzodithiophene) was selected as the conjugated backbone, in which the number of chlorine (Cl) atoms was varied to tune the optical and electronic properties. The new double-cable polymers were successfully applied in SCOSCs, providing an efficiency of over 8% with a broad photoresponse from 300 to 800 nm. When the number of Cl atoms on the repeat unit was increased from 2 to 3, the open-circuit voltage was enhanced to 1.01 V, yielding a low voltage loss of 0.59 eV, while the efficiency was reduced to 5.28%. The reduced performance is explained by the increased charge recombination in this polymer, as observed by transient absorption spectroscopy. This work reports a set of IC-based NIR double-cable conjugated polymers, which inspire material design toward more efficient SCOSCs.
CRIS-Team WoS Importer:2023-02-24

Double-Cable Conjugated Polymers with Pendent Near-Infrared Electron Acceptors for Single-Component Organic Solar Cells - Liang, Shijie; Liu, Baiqiao; Karuthedath, Safakath; Wang, Jing; He, Yakun; Tan, Wen Liang; Li, Hao; Xu, Yunhua; Li, Ning; Hou, Jianhui; Tang, Zheng; Laquai, Frederic; et al. (Angewandte Chemie International Edition, 2022)
Double-cable conjugated polymers with near-infrared (NIR) electron acceptors are synthesized for use in single-component organic solar cells (SCOSCs). Through the development of a judicious synthetic pathway, the highly sensitive nature of the 2-(3-oxo-2,3-dihydroinden-1-ylidene)malononitrile (IC)-based electron acceptors in basic and protonic solvents is overcome. In addition, an asymmetric design motif is adopted to optimize the packing of donor and acceptor segments, enhancing charge separation efficiency. As such, the new double-cable polymers are successfully applied in SCOSCs, providing an efficiency of over 10 % with a broad photo response from 300 to 850 nm and exhibiting excellent thermal/light stability. These results demonstrate the powerful design of NIR-acceptor-based double-cable polymers and will enable SCOSCs to enter a new stage.
CRIS-Team WoS Importer:2022-07-29

Dual Interfacial Design for Efficient CsPbI2Br Perovskite Solar Cells with Improved Photostability - Tian, Jingjing; Xue, Qifan; Tang, Xiaofeng; Chen, Yuxuan; Li, Ning; Hu, Zhicheng; Shi, Tingting; Wang, Xin; Huang, Fei; Brabec, Christoph; Yip, Hin Lap; Cao, Yong (Advanced Materials, 2019)
A synergic interface design is demonstrated for photostable inorganic mixed‐halide perovskite solar cells (PVSCs) by applying an amino‐functionalized polymer (PN4N) as cathode interlayer and a dopant‐free hole‐transporting polymer poly[5,5′‐bis(2‐butyloctyl)‐(2,2′‐bithiophene)‐4,4′‐dicarboxylate‐alt‐5,5′‐2,2′‐bithiophene] (PDCBT) as anode interlayer. First, the interfacial dipole formed at the cathode interface reduces the workfunction of SnO2, while PDCBT with deeper‐lying highest occupied molecular orbital (HOMO) level provides a better energy‐level matching at the anode, leading to a significant enhancement in open‐circuit voltage (Voc) of the PVSCs. Second, the PN4N layer can also tune the surface wetting property to promote the growth of high‐quality all‐inorganic perovskite films with larger grain size and higher crystallinity. Most importantly, both theoretical and experimental results reveal that PN4N and PDCBT can interact strongly with the perovskite crystal, which effectively passivates the electronic surface trap states and suppresses the photoinduced halide segregation of CsPbI2Br films. Therefore, the optimized CsPbI2Br PVSCs exhibit reduced interfacial recombination with efficiency over 16%, which is one of the highest efficiencies reported for all‐inorganic PVSCs. A high photostability with a less than 10% efficiency drop is demonstrated for the CsPbI2Br PVSCs with dual interfacial modifications under continuous 1 sun equivalent illumination for 400 h.
CRIS-Team Scopus Importer:2019-05-02
Keywords: all-inorganic perovskite solar cells; high efficiency; interface modification; photoinduced halide segregation; surface passivation

Effective Ligand Engineering of the Cu2ZnSnS4 Nanocrystal Surface for Increasing Hole Transport Efficiency in Perovskite Solar Cells - Khanzada, Laraib Sarfraz; Levchuk, Ievgen; Hou, Yi; Azimi, Seyed Hamed; Osvet, Andres; Ahmad, Rameez; Brandl, Marco; Herre, Patrick; Distaso, Monica; Hock, Rainer; Peukert, Wolfgang; Batentschuk, Miroslaw; et al. (Advanced Functional Materials, 2016)
Effective engineering of surface ligands in semiconductor nanocrystals can facilitate the electronic interaction between the individual nanocrystals, making them promising for low-cost optoelectronic applications. Here, the use of high purity CuZnSnS (CZTS) nanocrystals as the photoactive layer and hole-transporting material is reported in low-temperature solution-processed solar cells. The high purity CZTS nanocrystals are prepared by engineering the surface ligands of CZTS nanocrystals, capped originally with the long-chain organic ligand oleylamine. After ligand removal, CZTS nanocrystals show substantial improvement in photoconductivity and mobility, displaying also an appreciable photoresponse in a simple heterojunction solar cell architecture. More notably, CZTS nanocrystals exhibit excellent hole-transporting properties as interface layer in perovskite solar cells, yielding power conversion efficiency (PCE) of 15.4% with excellent fill factor (FF) of 81%. These findings underscore the importance of removing undesired surface ligands in nanocrystalline optoelectronic devices, and demonstrate the great potential of CZTS nanocrystals as both active and passive material for the realization of low-cost efficient solar cells.
Keywords: CZTS solar cells; HTM; Inorganic nanocrystals; Ligand exchange; Perovskite

Effective Ligand Passivation of Cu2O Nanoparticles through Solid-State Treatment with Mercaptopropionic Acid - Azimi, Seyed Hamed; Kuhri, Susanne; Osvet, Andres; Matt, Gebhard; Khanzada, Laraib Sarfraz; Lemmer, Mario; Luechinger, Norman A.; Larsson, Mats I.; Zeira, Eitan; Guldi, Dirk Michael; Brabec, Christoph (Journal of the American Chemical Society, 2014)
In colloidal nanoparticle (NPs) devices, trap state densities at their surface exert a profound impact on the rate of charge carrier recombination and, consequently, on the deterioration of the device performance. Here, we report on the successful application of a ligand exchange strategy to effectively passivate the surface of cuprite (Cu2O) NPs. Cu2O NPs were prepared by means of a novel synthetic route based on flame spray pyrolysis. FTIR, XRD, XPS, and HRTEM measurements corroborate the formation of cubic cuprite Cu2O nanocrystals, excluding the possible presence of undesired CuO or Cu phases. Most importantly, steady-state emission and transient absorption assays document that surface passivation results in substantial changes in the intensity of emissive excitonic states-centered at copper and oxygen vacancies-and in the lifetime of excitons near the band edge. To shed light onto ultrafast processes in Cu2O nanocrystals additional pump probe experiments on the femtosecond and nanosecond time scales were carried out. Two discernible species were observed: on one hand, an ultrafast component ( ps) that relates to the excitons; on the other hand, a long-lived component ( μs) that originates from the defects/trap states.
Keywords: Engineering controlled terms: Nanocrystals; Spray pyrolysis Charge carrier recombination; Colloidal nanoparticles; Ligand passivation; Mercaptopropionic acid; Pump-probe experiments; Steady-state emissions; Surface passivation; Transient absorption Engineering main heading: Excitons EMTREE drug terms: 3 mercaptopropionic acid; copper; copper nanoparticle; nanocrystal; oxygen EMTREE medical terms: article; assay; infrared spectroscopy; pyrolysis; solid; steady state; surface property; transient absorption assay; transmission electron microscopy; X ray photoelectron spectroscopy

Effect of the Precursor Chemistry on the Crystallization of Triple Cation Mixed Halide Perovskites - Singh, Mriganka; Abdelsamie, Maged; Li, Qihua; Kodalle, Tim; Lee, Do Kyoung; Arnold, Simon; Ceratti, Davide R.; Slack, Jonathan L.; Schwartz, Craig P.; Brabec, Christoph; Tao, Shuxia; Sutter-Fella, Carolin M. (Chemistry of Materials, 2023)
Triple cation, mixed halide perovskite compositions have been reported to be more thermally stable, exhibit fewer phase impurities, and show higher power conversion efficiency and better reproducibility than single cation perovskites. In this work, we explain the formation of Cs0.05FA0.81MA0.14Pb(I0.85Br0.15)3 via a multimodal in situ study combining structural information from synchrotron grazing-incidence wide-angle X-ray scattering (GIWAXS) and optical properties from photoluminescence (PL) spectroscopy with density functional theory calculations (DFT). The focus here is on the effects of the solvent and antisolvent during crystallization. The predominantly used solvents N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), and the antisolvent chlorobenzene (CB) as well as the solvent-antisolvent-precursor interactions are investigated. Given the high elemental complexity and mutual interdependencies between solvent, antisolvent, and perovskite precursors, we found significant differences in the crystallization pathways. DMF-pure precursors show the formation of the DMF-containing intermediate phase and the nucleation of compositionally distinct perovskite phases, while when DMSO is added, only crystalline α- and δ-phases were found. In addition, the presence of DMSO helps the formation of α-perovskite. Coordination energy and bond order (BO) calculations support our experimental findings. Dripping of CB induces nucleation at room temperature, slows the α-phase formation rate, and appears to reduce the nucleation radius. These findings provide novel insights into solvent, antisolvent, and perovskite precursor interactions and their formation pathways. The complexity of interactions between solvents and reagents highlights the importance of understanding these effects to further improve the reproducibility and optimize processing conditions.
CRIS-Team Scopus Importer:2023-10-27

Effect of water vapor content during the solid state synthesis of manganese-doped magnesium fluoro-germanate phosphor on its chemistry and photoluminescent properties - Ali, Amjad; Chepyga, Liudmyla; Khanzada, Laraib Sarfraz; Osvet, Andres; Brabec, Christoph; Batentschuk, Miroslaw (Optical Materials, 2020)
Several samples of magnesium fluoro-germanate doped with Mn4+ were prepared by solid state synthesis with a different water vapor content in the synthesis atmosphere. A significant decrease in quantum yield and emission intensity was observed with the increase in water vapor content during synthesis. Although there was little effect on the emission spectra, the changes in excitation spectra indicate the dominance of magnesium germanate instead of magnesium fluoro-germanate at high water vapor content. X-ray diffraction (XRD) results show that the pure phase was only achieved with the least amount of water vapor. Refinement of XRD data estimates the quantities of different phases present. The effect on the grain size and morphology is also remarkable, as demonstrated by scanning electron microscopy imaging. The reason behind the changes is discussed in detail. The temperature dependence of the photoluminescence spectra was measured between room temperature and 500 °C where the luminescence is quenched to nearly 3% of its initial value.
CRIS-Team Scopus Importer:2019-12-17
Keywords: Effect of humidity; Magnesium fluoro-germanate; Photoluminescence; Solid state reaction; Thermographic phosphor; Water vapor

Effects of Alkyl Terminal Chains on Morphology, Charge Generation, Transport, and Recombination Mechanisms in Solution-Processed Small Molecule Bulk Heterojunction Solar Cells - Min, Jie; Luponosov, Yuriy N.; Gasparini, Nicola; Richter, Moses; Bakirov, Artem V.; Shcherbina, Maxim A.; Chvalun, Sergei N.; Grodd, Linda; Grigorian, Souren; Ameri, Tayebeh; Ponomarenko, Sergei A.; Brabec, Christoph (Advanced Energy Materials, 2015)
Length of the terminal alkyl chains at dicyanovinyl (DCV) groups of two dithienosilole (DTS) containing small molecules (DTS(Oct)2-(2T-DCV-Me)2 and DTS(Oct)2-(2T-DCV-Hex)2) is investigated to evaluate how this affects the molecular solubility and blend morphology as well as their performance in bulk heterojunction organic solar cells (OSCs). While the DTS(Oct)2-(2T-DCV-Me)2 (a solubility of 5 mg mL-1) system exhibits both high short circuit current density (J sc) and high fill factor, the DTS(Oct)2-(2T-DCV-Hex)2 (a solubility of 24 mg mL-1) system in contrast suffers from a poor blend morphology as examined by atomic force morphology and grazing incidence X-ray scattering measurements, which limit the photovoltaic properties. The charge generation, transport, and recombination dynamics associated with the limited device performance are investigated for both systems. Nongeminate recombination losses in DTS(Oct)2-(2T-DCV-Hex)2 system are demonstrated to be significant by combining space charge limited current analysis and light intensity dependence of current-voltage characteristics in combination with photogenerated charge carrier extraction by linearly increasing voltage and transient photovoltage measurements. DTS(Oct)2-(2T-DCV-Me)2 in contrast performs nearly ideal with no evidence of nongeminate recombination, space charge effects, or mobility limitation. These results demonstrate the importance of alkyl chain engineering for solution-processed OSCs based on small molecules as an essential design tool to overcome transport limitations.
Keywords: blend morphology; molecular solubility; organic solar cells; recombination dynamics; transport limitations

Effects of bridging atom and π-bridge length on physical and photovoltaic properties of A-π-D-π-A oligomers for solution-processed organic solar cells - Luponosov, Yuriy N.; Min, Jie; Bakirov, Artem V.; Dmitryakov, Petr V.; Chvalun, Sergei N.; Peregudova, Svetlana M.; Ameri, Tayebeh; Brabec, Christoph; Ponomarenko, Sergei A. (Dyes and Pigments, 2015)
Synthesis of novel acceptor-donor-acceptor oligomers with electron-withdrawing alkyldicyanovinyl groups linked through an oligothiophene π-bridge with either dithienosilole or cyclopentadithiophene electron donor units is described. Changing the bridgehead atom from carbon to silicon in the central donor unit leads to a significant change in optical, thermal and structural properties of the oligomers. In addition, elongation of the oligothiophene π-bridge in the oligomers increases energies of HOMO and LUMO levels and leads to an unexpected hypsochromic shift of their absorption spectrum, because extension of the conjugation length cannot compensate a decrease of the intramolecular charge transfer between the dithienosilole and dicyanovinyl units. Although these minor changes in the chemical structures have a pronounced impact on the morphologies of their blends with PC70BM, the optimized solution-processed organic solar cells based on these small molecules demonstrate similar power conversion efficiencies.
EAM Import::2019-03-14
Keywords: Alkyldicyanovinyl groups; Dithienosilole; Donor-acceptor oligomers; Effect of heteroatom substitution; Oligothiophenes; Organic solar cells

Effects of bridging atom in donor units and nature of acceptor groups on physical and photovoltaic properties of A-π-D-π-A oligomers - Min, Jie; Luponosov, Yuriy N.; Khanin, Dmitry A.; Dmitryakov, Petr V.; Svidchenko, Evgeniya A.; Peregudova, Svetlana M.; Grodd, Linda; Grigorian, Souren; Chvalun, Sergei N.; Ponomarenko, Sergei A.; Brabec, Christoph (Organic Electronics, 2018)
The synthesis of a series of novel A-π-D-π-A oligomers bearing either electron-donating dithieno[3,2-b:2′,3′-d]silole (DTS) or dithieno[3,2-b:2′,3′-d]pyrrole (DTP) units linked through a bithiophene π-bridge with the electron-withdrawing methyldicyanovinyl (DCV) or N-ethylrhodanine (Rh) groups is described. In order to evaluate the effects of different donor-acceptor combinations on various physical properties of the oligomers they are comprehensively studied by UV–Vis spectroscopy, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and cyclic voltammetry (CV). Replacing the DTS by DTP as well as the DCV by Rh leads to increasing of HOMO energy levels and slight decreasing of LUMO energy levels. The DTP-based oligomers have a red shift in absorption spectra and an increased solubility as compared to the DTS-based analogs. Replacing the acceptor DCV unit by Rh also results in significantly higher solubility, but the Rh-based oligomers exhibit weaker intermolecular interactions, poorer optical absorption of sun light as well as lower charge carrier mobility in blends. Altogether, the structural improvement of the DTS-DCV and DTP-DCV blends upon annealing correlates well with the observed photovoltaic performances in organic solar cells. These results give more insight how to fine-tune and predict physical properties and photovoltaic performance of small A-π-D-π-A molecules having different donor-acceptor combinations in their chemical structures and thus providing a molecular design guideline for the next generation of high-performance photovoltaic materials
Keywords: Electron-donating; Electron-withdrawing; Oligomers; Organic solar cells; Posttreatment methods; Power conversion efficiencies; Solvent vapor annealing; Thermal annealing

Effects of electron-withdrawing group and electron-donating core combinations on physical properties and photovoltaic performance in D-π-A star-shaped small molecules - Luponosov, Yuriy N.; Min, Jie; Solodukhin, Alexander N.; Kozlov, Oleg V.; Obrezkova, Marina A.; Peregudova, Svetlana M.; Ameri, Tayebeh; Chvalun, Sergei N.; Pshenichnikov, Maxim S.; Brabec, Christoph; Ponomarenko, Sergei A. (Organic Electronics, 2016)
The first representatives of star-shaped molecules having 3-alkylrhodanine (alkyl-Rh) electron-withdrawing groups, linked through bithiophene π-spacer with electron-donating either triphenylamine (TPA) or tris(2-methoxyphenyl)amine (m-TPA) core were synthesized. The physical properties and photovoltaic performance of these novel molecules with 3-ethylrhodanine groups were comprehensively studied and compared to their full analogs having dicyanovinyl (DCV) units as the other type of well-known and frequently used acceptor groups. On one hand, the former demonstrate several advantages such as higher solubility and better photovoltaic performance in bulk-heterojunction (BHJ) organics solar cells (OSCs) as compared to the latter. Nevertheless, the former have slightly lower optical/electrochemical bandgaps and higher thermooxidation stability. On the other hand, molecules of both series based on m-TPA core along with higher solubility and higher position of HOMO energy levels have more pronounced tendency to crystalize as compared to the TPA-based molecules. Detailed investigation of the structure-property relationships for these series of molecules revealed that donor and acceptor unit combinations influence both charge generation and charge transport/recombination properties, as demonstrated by the ultrafast photoinduced absorption spectroscopy, space charge limited current measurements and transient photovoltage technique. These results give more insight how to fine-tune and predict physical properties and photovoltaic performance of small molecules having either alkyl-Rh or DCV units in their chemical structures and thus providing a molecular design guideline for the next generation of high-performance photovoltaic materials.
EAM Import::2019-03-14
Keywords: 3-Ethylrhodanine; Dicyanovinyl; Organic solar cells; Star-shaped molecules; Triphenylamine; Ultrafast charge separation

Effects of oligothiophene π-bridge length on physical and photovoltaic properties of star-shaped molecules for bulk heterojunction solar cells - Min, Jie; Luponosov, Yuriy N.; Baran, Derya; Chvalun, Sergei N.; Shcherbina, Maxim A.; Bakirov, Artem V.; Dmitryakov, Petr V.; Peregudova, Svetlana M.; Kausch-Busies, Nina; Ponomarenko, Sergei A.; Ameri, Tayebeh; Brabec, Christoph (Journal of Materials Chemistry A, 2014)
The preparation of four different star-shaped donor (D)-π-acceptor (A) small molecules (N(Ph-1T-DCN-Me)3, N(Ph-2T-DCN-Me)3, N(Ph-2T-DCN-Hex)3 and N(Ph-3T-DCN-Hex)3) possessing various oligothiophene π-bridge lengths and their use in solution-processed bulk heterojunction small molecule solar cells is reported. Optical and electrochemical data show that increasing oligothiophene π-bridge length leads to a decrease of the optical band gap due to a parallel increase of the highest occupied molecular orbital (HOMO) level. Furthermore, subtle modifications of a molecular π-bridge length strongly affect the thermal behavior, solubility, crystallization, film morphology and charge carrier mobility, which in turn significantly change the device performance. Although the moderately increasing oligothiophene π-bridge length uplifts the HOMO level, it nevertheless induces an increase of the efficiency of the resulting solar cells due to a simultaneous improvement of the short circuit current (Jsc) and fill factor (FF). The study demonstrates that such an approach can represent an interesting tool for the effective modulation of the photovoltaic properties of the organic solar cells (OSCs) at a moderate cost.
EAM Import::2019-03-14
Keywords: Bulk heterojunction solar cells; Oligothiophenes; Photovoltaic property; Star-shaped molecules

Effects on Photovoltaic Characteristics by Organic Bilayer- And Bulk-Heterojunctions: Energy Losses, Carrier Recombination and Generation - Lee, Tack Ho; Park, Song Yi; Du, Xiaoyan; Park, Sujung; Zhang, Kaicheng; Li, Ning; Cho, Shinuk; Brabec, Christoph; Kim, Jin Young (ACS Applied Materials and Interfaces, 2020)
We investigate the photovoltaic characteristics of organic solar cells (OSCs) for two distinctly different nanostructures, by comparing the charge carrier dynamics for bilayer- and bulk-heterojunction OSCs. Most interestingly, both architectures exhibit fairly similar power conversion efficiencies (PCEs), reflecting a comparable critical domain size for charge generation and charge recombination. Although this is, at first hand, surprising, a detailed analysis points out the similarity between these two concepts. A bulk-heterojunction architecture arranges the charge generating domains in a 3D ensemble across the whole bulk, while bilayer architectures arrange the specific domains on top of each other, rather than sharp bilayers. Specifically, for the polymer PBDB-T-2F, we find that the enhanced charge generation in a bulk composite is partially compensated by reduced recombination in the bilayer architecture, when nonfullerene acceptors (NFAs) are used instead of a fullerene acceptor. Overall, we demonstrate that bilayer-heterojunction OSCs with NFAs can reach competitive PCEs compared to the corresponding bulk-heterojunction OSCs because of reduced nonradiative open-circuit voltage losses, and suppressed trap-assisted recombination, as a result of a vertically separated donor-to-acceptor nanostructure. In contrast, the bilayer-heterojunction OSCs with the fullerene acceptor exhibited poor photovoltaic characteristics compared to the corresponding bulk devices because of highly aggregated acceptor molecules on top of the polymer donor. Although free carrier generation is reduced in a in a bilayer-heterojunction, because of reduced donor/acceptor interfaces and a limited exciton diffusion length, more favorable transport pathways for unipolar charge collection can partially compensate the aforementioned disadvantages. We propose that the unique properties of NFAs may open a technical venue for the bilayer-heterojunction as a great and easy alternative to the bulk heterojunction.
CRIS-Team Scopus Importer:2020-12-25
Keywords: carrier behavior; energy loss; nonfullerene small molecular acceptor; organic nanostructure; organic solar cell

Efficiency Limits and Color of Semitransparent Organic Solar Cells for Application in Building-Integrated Photovoltaics - Forberich, Karen; Guo, Fei; Bronnbauer, Carina; Brabec, Christoph (Energy Technology, 2015)
We have modified the well-known Scharber model for the efficiency limits of organic solar cells for the case of semitransparent devices, which are considered as one of the most promising applications for this photovoltaic (PV) technology. We introduce a modified external quantum efficiency (EQE) relation and derive the transparency from the convolution of the calculated transmittance spectrum with the human eye sensitivity. We find that the design guidelines for the optimum band gap of the absorber material have to be carefully adapted for the desired transparency, especially for transparency values exceeding 40%. In addition, we examine the relationship between efficiency, transmitted color, and band gap and conclude that high efficiencies can be achieved for a wide range of colors. Our model shows good agreement with experimental values from the literature and can be easily adapted to different applications (e.g., greenhouses) by using the appropriate spectrum. © 2015 WILEY-VCH Verlag GmbH & Co.
Keywords: Building-integrated photovoltaics; Organic solar cells; Photovoltaics; Scharber model; Semitransparency

Efficient Exciton Diffusion in Organic Bilayer Heterojunctions with Nonfullerene Small Molecular Acceptors - Lee, Tack Ho; Park, Song Yi; Park, Won-Woo; Du, Xiaoyan; Son, Jae Hoon; Li, Ning; Kwon, Oh-Hoon; Woo, Han Young; Brabec, Christoph; Kim, Jin Young (ACS Energy Letters, 2020)
Solution-processed bilayer organic solar cells (OSCs) with high performance are demonstrated for nonfullerene small molecular acceptors (NFAs). Unlike fullerene acceptors, NFAs show significant spectral overlap between their absorption and the photoluminescence (PL) of a polymer donor, which makes the design of an efficient exciton-harvesting bilayer heterojunction possible. Efficient exciton diffusion in the organic bilayer heterojunction is realized by long-range energy transfer between a polymer donor and NFAs. We observed efficient exciton diffusion from the polymer/NFA bilayer heterojunctions via thickness-dependent PL quenching and time-resolved PL measurements. Despite the strongly reduced donor-acceptor interface area, a substantial density of charge-transfer states is observed for the polymer/NFA bilayer heterojunctions by electroluminescence measurements. Overall, polymer/NFA bilayer heterojunction OSCs demonstrate a power conversion efficiency of 9%-10%, which is comparable to the photovoltaic performance of bulk heterojunction OSCs, with the additional advantage of simplified microstructure formation.
Created from Fastlane, WoS look-up

Efficient Organic Solar Cells with Extremely High Open-Circuit Voltages and Low Voltage Losses by Suppressing Nonradiative Recombination Losses - Liu, Xi; Du, Xiaoyan; Wang, Junyi; Duan, Chunhui; Tang, Xiaofeng; Heumüller, Thomas; Liu, Guogang; Li, Yan; Wang, Zhaohui; Wang, Jing; Liu, Feng; Li, Ning; et al. (Advanced Energy Materials, 2018)
One of the most important factors that limits the efficiencies of bulk-heterojunction organic solar cells (OSCs) is the modest open-circuit voltage (Voc) due to their large voltage loss (Vloss) caused by significant nonradiative recombination loss. To boost the performance of OSCs toward their theoretical limit, developing high-performance donor: acceptor systems featuring low Vloss with suppressed nonradiative recombination losses (<0.30 V) is desired. Herein, high performance OSCs based on a polymer donor benzodithiophene-difluorobenzoxadiazole-2-decyltetradecyl (BDT-ffBX-DT) and perylenediimide-based acceptors (PDI dimer with spirofluorene linker (SFPDI), PDI4, and PDI6) are reported which offer a high power conversion efficiency (PCE) of 7.5%, 56% external quantum efficiency associated with very high Voc (>1.10 V) and low Vloss (<0.60 V). A high Voc up to 1.23 V is achieved, which is among the highest values reported for OSCs with a PCE beyond 6%, to date. These attractive results are benefit from the suppressed nonradiative recombination voltage loss, which is as low as 0.20 V. This value is the lowest value for OSCs so far and is comparable to high performance crystalline silicon and perovskite solar cells. These results show that OSCs have the potential to achieve comparable Voc and voltage loss as inorganic photovoltaic technologies. © 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinhei
Keywords: Nonfullerene acceptors; Nonradiative recombination losses; Voltage losses; Open-circuit voltages; Organic solar cells

Efficient Polymer Solar Cells Based on Non-fullerene Acceptors with Potential Device Lifetime Approaching 10 Years - Du, Xiaoyan; Heumüller, Thomas; Gruber, Wolfgang; Classen, Andrej; Unruh, Tobias; Li, Ning; Brabec, Christoph (Joule, 2019)
Organic solar cells (OSCs) based on non-fullerene acceptors (NFAs) have developed very fast in recent years. A proper balance among power conversion efficiency (PCE), stability, and production cost needs further elaboration. Here we investigate the industrial viability of highly efficient OSCs based on several representative NFAs. The most stable OSCs exhibit PCE of ∼8% along with extrapolated T 80 lifetime (80% of the initial PCE) of over 11,000 hr under equivalent 1 sun illumination, which would lead to a very impressive operational lifetime approaching 10 years. Photo-stability is strongly dependent on the end-group and side-chain engineering of the NFAs. Breaking of conjugation during photo-aging leads to increased energetic traps. Fluorination of the end-group stabilizes molecules against light soaking, while adding methyl groups shows an opposite trend. Side-chain modification can significantly influence the morphological stability. Reducing synthetic complexity of this class of NFAs will ultimately push the organic photovoltaics technology into real-life applications. © 2018 Elsevier Inc. We investigate the industrial viability of highly efficient organic solar cells (OSCs) based on several representative non-fullerene acceptors (NFAs) by taking into consideration the three essential parameters: power conversion efficiency, photo-stability, and materials cost. End-group and side-chain modifications of NFAs strongly influence long-term photo-stability. Promising extrapolated operational lifetime approaching 10 years has been demonstrated with the most stable system. Industrial figure of merit (i-FoM) analysis highlights the importance of lowering the synthetic complexity of the NFAs for commercialization of this technology. © 2018 Elsevier Inc. Organic solar cells with non-fullerene acceptors (NFAs) have developed rapidly in recent years. Breakthroughs in power conversion efficiency (PCE) have significantly raised the confidence in the community for commercialization of this technology. In the phase of developing new materials via molecular engineering, more attention should be paid on industrial figure of merit (i-FoM), which considers the balance of PCE, stability, and production cost. Here we investigate industrial viability of highly efficient organic solar cells based on several representative NFAs. Molecular engineering on both end-groups and side chains significantly influences the long-term stability of organic solar cells by altering the intrinsic chemical stability of the molecules under light soaking as well as morphological stability. Promising lifetime approaching 10 years is demonstrated in stable candidates. Reducing synthetic complexity is highlighted in order to push this technology into real-life appli
Keywords: non-fullerene acceptors; organic photovoltaics; device operational stability; industrial figure of merit; bulk-heterojunction morphology

Efficient, stable, and fully printed carbon-electrode perovskite solar cells enabled by hole-transporting bilayers - Du, Tian; Qiu, Shudi; Zhou, Xin; Le Corre, Vincent Marc; Wu, Mingjian; Dong, Lirong; Peng, Zijian; Zhao, Yicheng; Jang, DongJu; Spiecker, Erdmann; Brabec, Christoph; Egelhaaf, Hans-Joachim (Joule, 2023)
Printable planar carbon electrodes emerge as a promising replacement for thermally evaporated metals as the rear contact for perovskite solar cells (PSCs). However, the power conversion efficiencies (PCEs) of the state-of-the-art carbon-electrode PSC (c-PSC) noticeably lag behind their metal-electrode counterparts. Here, we propose a hole-transporting bilayer (HTbL) configuration to improve the fill factor and the open-circuit voltage of c-PSCs simultaneously. The HTbL is prepared by sequentially blade coating two organic semiconductors between perovskite and carbon, with the outer HTL enhancing hole extraction to carbon, while the inner HTL mitigates perovskite surface recombination. Consequently, our fully printed c-PSCs with HTbL outperform those with single HTL, and a stabilized champion PCE of 19.2% is achieved compared with that of 17.3%. Our prototype c-PSC stably operates during 1 sun, 65°C aging test (ISOS-L-2I) for 2,500 h showing negligible PCE drop, validating its potential as a highly cost-effective photovoltaic technology.
CRIS-Team Scopus Importer:2023-08-18
Keywords: bilayer; carbon electrode; fully printed perovskite solar cells; hole transporting; stability

Efficient Surface Passivation and Electron Transport Enable Low Temperature-Processed Inverted Perovskite Solar Cells with Efficiency over 20% - Wang, Helin; Yang, Fu; Li, Ning; Kamarudin, Muhammad Akmal; Qu, Junle; Song, Jun; Hayase, Shuzi; Brabec, Christoph (ACS Sustainable Chemistry & Engineering, 2020)
PCBM is a fullerene derivative, which is commonly employed as an electron transport layer (ETL), and still has some issues to fabricate low temperature-processed perovskite solar cells (PSCs) such as surface trap states, low electron mobility, and extra recombination losses at the perovskite/PCBM interface. Herein, a novel perylene diimide dimer (2FBT2FPDI) is synthesized and employed as an ETL or intermediary layer to overcome these challenges. Owing to its suitable energy levels and high electron mobility, 2FBT2FPDI shows great potential to serve as a promising efficient ETL in the photovoltaic devices. Moreover, 2FBT2FPDI can coordinate with the lead site of the perovskite surface, which helps to heal the surface defects and suppress charge-trapped recombination. Therefore, the performance of PSCs is greatly improved from 17.3 to 20.3%, when 2FBT2FPDI was used as the intermediary layer to assist the growth of the PCBM film. This work presents a new direction through interface engineering with n-type nonfullerene small molecules for low temperature-processed stable and highly efficient inverted PSCs.<br
Keywords: perovskite solar cell; surface passivation; electron transport material; high efficiency; device stability

Electrical-Field-Driven Tunable Spectral Responses in a Broadband-Absorbing Perovskite Photodiode. - Tang, Xiaofeng; Matt, Gebhard; Gao, Shuai; Gu, Ening; Almora, Osbel; Brabec, Christoph (ACS Applied Materials and Interfaces, 2019)
Controllably manipulating the spectral response of broadband-absorbing semiconductors is crucial for developing wavelength-selective optoelectronic devices. In this article, we report for the first time, the bias-dependent spectral responses for a metal-halide perovskite photodiode. Tunable external quantum efficiencies in the short- and long-wavelength regimes, and the full spectral range (ca. 300-800 nm) are observed when the device is operated under short-circuit, and forward and reverse bias conditions, respectively. This observation is understood by the interplay of wavelength-dependent penetration depth and barrier formation within the photodiode device stack. The general applicability of this concept is confirmed by a systematic study on a series of mixed-halide perovskite devices. These results suggest that the proposed concept allows as a promising platform and should inspire further exploration of multispectral responsive optoelectronic devices.
Keywords: perovskite; optoelectronics; electrodeposition; mixed-halide perovskite; external quantum efficiency

Electrical properties of pSi/[6,6] phenyl-C61 butyric acid methyl ester/Al hybrid heterojunctions: Experimental and theoretical evaluation of diode operation - Bednorz, Mateusz; Fromherz, Thomas; Matt, Gebhard; Brabec, Christoph; Scharber, Markus; Sariciftci, N. Serdar (Journal of Applied Physics, 2012)
In this work, we analyze electrically the Al/p-Si/[6,6] phenyl-C61 butyric acid methyl ester/Al hybrid heterojunction. The barrier height at the p-Si/PCBM interface corresponding to the difference between Si valence band edge and the lowest unoccupied molecular orbital energy level of PCBM is studied with current-voltage (J-V) and capacitance-voltage (C-V) methods and determined to be ≃ 0.55eV. This value is in agreement with the onset energy of spectrally resolved photocurrent measurements presented in a previous publication [Matt, Adv. Mater. 22, 647 (2010)]. For the J-V characteristics, a thorough model based on an interface generation-recombination current is proposed. All relevant energy levels for this model are obtained experimentally. As origin of the large reverse current, the thermal generation of charge carriers throughout the Si depletion region is identified by the thermal activation measurements. © 2012 American Institute of Physics.

Electroluminescence imaging of organic photovoltaic modules - Hoyer, U.; Wagner, M.; Swonke, Th.; Bachmann, J.; Auer, R.; Osvet, Andres; Brabec, Christoph (Applied Physics Letters, 2010)
We report on electroluminescence (EL) imaging of organic photovoltaic cells and modules with poly(3-hexylthiophene)/[6,6]-phenyl C61 butyric acid methyl ester as semiconductor layer. The dominant EL emission is found in a spectral regime between 1200 and 1400 nm and is identified as the radiative decay of the charge transfer complex formed between the polymer and the fullerene. Electroluminescence emission from the pristine compounds is either much weaker or completely absent. Overall, electroluminescence imaging is shown to give valuable information on the defects but also on the performance of organic solar modules. © 2010 American Institute of Physics.

Electron barrier formation at the organic-back contact interface is the first step in thermal degradation of polymer solar cells - Sachs-Quintana, I. T.; Heumüller, Thomas; Mateker, William R.; Orozco, Darian E.; Cheacharoen, Rongrong; Sweetnam, Sean; Brabec, Christoph; Mcgehee, Michael D. (Advanced Functional Materials, 2014)
Long-term stability of polymer solar cells is determined by many factors, one of which is thermal stability. Although many thermal stability studies occur far beyond the operating temperature of a solar cell which is almost always less than 65 °C, thermal degradation is studied at temperatures that the solar cell would encounter in real-world operating conditions. At these temperatures, movement of the polymer and fullerenes, along with adhesion of the polymer to the back contact, creates a barrier for electron extraction. The polymer barrier can be removed and the performance can be restored by peeling off the electrode and depositing a new one. X-ray photoelectron spectroscopy measurements reveal a larger amount of polymer adhered to electrodes peeled from aged devices than electrodes peeled from fresh devices. The degradation caused by hole-transporting polymer adhering to the electrode can be suppressed by using an inverted device where instead of electrons, holes are extracted at the back metal electrode. The problem can be ultimately eliminated by choosing a polymer with a high glass transition temperature. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: degradation; interfaces; lifetime; organic photovoltaics; stability

Elucidating How Low Energy Offset Matters to Performance of Nonfullerene Acceptor-Based Solar Cells - Tokmoldin, Nurlan; Sun, Bowen; Moruzzi, Floriana; Patterson, Acacia; Alqahtani, Obaid; Wang, Rong; Collins, Brian A.; McCulloch, Iain; Lüer, Larry; Brabec, Christoph; Neher, Dieter; Shoaee, Safa (ACS Energy Letters, 2023)
The energetic offset between the highest occupied molecular orbitals of the donor and acceptor components of organic photovoltaic blends is well-known to affect the device efficiency. It is well-established that a decreasing offset increases the open-circuit voltage but reduces the short-circuit current, which has been explained by insufficient exciton dissociation. However, the impact of the offset on the fill factor and underlying processes is less clear. Here, we study free charge generation and recombination in three different nonfullerene acceptors, Y6, ITIC, and o-IDBTR, blended with the same donor polymer PM6. We demonstrate that a diminishing offset results in field-dependent charge generation related to field-assisted exciton dissociation. On the other hand, reformation of excitons from free charges is identified as an additional channel for charge recombination, which goes along with a substantial rise in the bimolecular recombination coefficient. In combination of these two effects, the fill factor drops considerably with a decreasing energy offset. Using the comparison between PM6:ITIC and PM6:o-IDBTR, we show that bulk properties such as morphology and carrier mobilities can not fully explain the observed difference in performance, highlighting the importance of interfacial kinetics and thermodynamics in controlling the device efficiency, both through generation and recombination of charge carriers.
CRIS-Team Scopus Importer:2023-07-14

Elucidating the Excited-State Properties of CuInS2 Nanocrystals upon Phase Transformation: Quasi-Quantum Dots Versus Bulk Behavior - Azimi, Seyed Hamed; Kuhri, Susanne; Stahl, Melissa S.; Hou, Yi; Guldi, Dirk Michael; Brabec, Christoph (Advanced Electronic Materials, 2015)
New insights into the complex relation between the thermal phase transformation and the excited state properties of chalcopyrite CuInS nanocrystals (CIS NCs) are presented. An in situ solution processing method via depositing molecular precursors is applied, offering advantages in terms of simplicity, low-temperature processability, and control over crystallite size, and optical properties. At low annealing temperatures, strong carrier quantum confinement and small crystallite sizes are realized for CIS NC films. CIS crystal growth is found to set in at higher annealing temperatures inducing a complete transformation from quasi-quantum-dot (QD) via bulk-like to bulk behavior. The transition of a near-infrared localized surface plasmon resonance (LSPR) towards a bulk-like plasmon resonance documents the crystal growth and further acts as a valuable probe to relate crystallite size with copper-deficient stoichiometries. In addition, time-resolved photophysical investigations help to shed light on the dynamics and mechanisms of exciton and charge carrier generation of CIS NC films as a function of annealing temperature. The in situ-prepared CIS NC films are further passivated by a thin CdS layer, leading to the formation of long-lived excitons and an effective CIS ground-state depletion.
Keywords: chalcopyrite; CuInS2 nanocrystals; exciton generation; localized surface plasmon resonance; transient absorption spectroscopy

Elucidating the Full Potential of OPV Materials Utilizing a High-Throughput Robot-Based Platform and Machine Learning - Du, Xiaoyan; Lüer, Larry; Heumüller, Thomas; Wagner, Jerrit; Berger, Christian; Osterrieder, Tobias; Wortmann, Jonas; Langner, Stefan; Vongsaysy, Uyxing; Bertrand, Melanie; Li, Ning; Stubhan, Tobias; et al. (Joule, 2021)
Evaluating the potential of organic photovoltaic (OPV) materials and devices for industrial production is a multidimensional optimization process with an incredibly large parameter space. Here, we demonstrate automated OPV material and device characterization in terms of efficiency and photostability. Gaussian process regression (GPR) prediction based on optical absorption features guided the optimization process with promising prediction accuracy for PV parameters and burn-in losses. With ∼100 process conditions, screening for efficiency and photostability can be finished within 70 h. The highest power conversion efficiency (PCE) of 14% was achieved by fully automated device fabrication in air with a model material system PM6:Y6. Improving molecular ordering has been identified as the most promising motif for further efficiency optimization. Thin active layers combined with medium thermal annealing temperature are favorable to simultaneously improve efficiency and suppress burn-in losses. The platform and protocol may be expanded to any solution-processed organic semiconductor and interface materials.
CRIS-Team Scopus Importer:2021-02-05
Keywords: automation; efficiency; high-throughput methods; machine learning; organic photovoltaics; photostability; processing optimization

Embedding physics domain knowledge into a Bayesian network enables layer-by-layer process innovation for photovoltaics - Ren, Zekun; Oviedo, Felipe; Thway, Maung; Tian, Siyu I. P.; Wang, Yue; Xue, Hansong; Dario Perea, Jose; Layurova, Mariya; Heumüller, Thomas; Birgersson, Erik; Aberle, Armin G.; Brabec, Christoph; et al. (npj Computational Materials, 2020)
Process optimization of photovoltaic devices is a time-intensive, trial-and-error endeavor, which lacks full transparency of the underlying physics and relies on user-imposed constraints that may or may not lead to a global optimum. Herein, we demonstrate that embedding physics domain knowledge into a Bayesian network enables an optimization approach for gallium arsenide (GaAs) solar cells that identifies the root cause(s) of underperformance with layer-by-layer resolution and reveals alternative optimal process windows beyond traditional black-box optimization. Our Bayesian network approach links a key GaAs process variable (growth temperature) to material descriptors (bulk and interface properties, e.g., bulk lifetime, doping, and surface recombination) and device performance parameters (e.g., cell efficiency). For this purpose, we combine a Bayesian inference framework with a neural network surrogate device-physics model that is 100x faster than numerical solvers. With the trained surrogate model and only a small number of experimental samples, our approach reduces significantly the time-consuming intervention and characterization required by the experimentalist. As a demonstration of our method, in only five metal organic chemical vapor depositions, we identify a superior growth temperature profile for the window, bulk, and back surface field layer of a GaAs solar cell, without any secondary measurements, and demonstrate a 6.5% relative AM1.5G efficiency improvement above traditional grid search methods.
CRIS-Team WoS Importer:2020-02-25

Engineering of the Electron Transport Layer/Perovskite Interface in Solar Cells Designed on TiO2 Rutile Nanorods - Shahvaranfard, Fahimeh; Altomare, Marco; Hou, Yi; Hejazi, Seyedsina; Meng, Wei; Osuagwu, Emeka Benedict; Li, Ning; Brabec, Christoph; Schmuki, Patrik (Advanced Functional Materials, 2020)
The engineering of the electron transport layer (ETL)/light absorber interface is explored in perovskite solar cells. Single-crystalline TiO2 nanorod (NR) arrays are used as ETL and methylammonium lead iodide (MAPI) as light absorber. A dual ETL surface modification is investigated, namely by a TiCl4 treatment combined with a subsequent PC61BM monolayer deposition, and the effects on the device photovoltaic performance were evaluated with respect to single modifications. Under optimized conditions, for the combined treatment synergistic effects are observed that lead to remarkable enhancements in cell efficiency, from 14.2% to 19.5%, and to suppression of hysteresis. The devices show J(SC), V-OC, and fill factor as high as 23.2 mA cm(-2), 1.1 V, and 77%, respectively. These results are ascribed to a more efficient charge transfer across the ETL/perovskite interface, which originates from the passivation of defects and trap states at the ETL surface. To the best of our knowledge, this is the highest cell performance ever reported for TiO2 NR-based solar cells fabricated with conventional MAPI light absorber. Perspective wise, this ETL surface functionalization approach combined with more recently developed and better performing light absorbers, such as mixed cation/anion hybrid perovskite materials, is expected to provide further performance enhancements.
Keywords: defect passivation; PC61BM; perovskite solar cells; TiCl4; TiO2 nanorods

Engineering Stable Perovskite Quantum Dot Films for High Color Purity Display Applications - Hu, Huiying; Levchuk, Ievgen; Kalkowski, Felix; Elia, Jack; Osvet, Andres; Brabec, Christoph (ACS Energy Letters, 2023)
Lead halide perovskite nanocrystals (NCs) are the most promising candidates for displays satisfying the Rec. 2020 UHDTV color standard. However, moisture sensitivity currently limits light-emitting applications requiring color stability and purity. In this study, we propose a large-area FAPbBr3-based quantum dot brightness enhancing film (QDEF) strategy developed in our group five years ago. The combination of a polymeric binder tailored to the ligands optimized perovskite NCs for light conversion and demonstrates QDEF applications with 91% coverage of Rec. 2020 standard in tablet displays, using polyhedral oligomeric silsesquioxane-capped FAPbBr3 as the green emitter and K2SiF6: Mn4+ (KSF) as a red emitter. Remarkably, our films operating in displays showed 4 year stability without lead leakage. Even without barrier protection, the unpackaged QDEF maintained 55% of its initial performance. This highlights the importance of a dual stabilization strategy for extending operational and shelf lifetimes of advanced functional perovskite composites.<br

Enhanced dissociation of charge-transfer states in narrow band gap polymer:fullerene solar cells processed with 1,8-octanedithiol - Moet, D. J. D.; Lenes, M.; Morana, M.; Azimi, H.; Brabec, Christoph; Blom, P. W. M. (Applied Physics Letters, 2010)
The improved photovoltaic performance of narrow band gap polymer:fullerene solar cells processed from solutions containing small amounts of 1,8-octanedithiol is analyzed by modeling of the experimental photocurrent. In contrast to devices that are spin coated from pristine chlorobenzene, these cells do not produce a recombination-limited photocurrent. Modeling of the experimental data reveals that a sixfold reduction in the decay rate of photogenerated bound electron-hole pairs can account for the marked increase in short-circuit current density and fill factor. At short-circuit conditions, the dissociation probability of bound pairs is found to increase from 48% to 70%. © 2010 American Institute of Physics.

Enhanced Photostability of Lead Halide Perovskite Nanocrystals with Mn3+ Incorporation - Hu, Huiying; Fehn, Dominik; Barr, Maissa; Harreiß, Christina; Zhao, Yicheng; Meyer, Karsten; Brabec, Christoph J.; Osvet, Andres; Brabec, Christoph (ACS Applied Materials and Interfaces, 2024)
Recently, lead halide perovskite nanocrystals (NCs) have shown great potential and have been widely studied in lighting and optoelectronic fields. However, the long-term stability of perovskite NCs under irradiation is an important challenge for their application in practice. Mn2+ dopants are mostly proposed as substitutes for the Pb site in perovskite NCs synthesized through the hot-injection method, with the aim of improving both photo- and thermal stability. In this work, we employed a facile ligand-assisted reprecipitate strategy to introduce Mn ions into perovskite lattice, and the results showed that Mn3+ instead of Mn2+, even with a very low level of incorporation of 0.18 mol % as interstitial dopant, can enhance the photostability of perovskite binder film under the ambient conditions without emission change, and the photoluminescent efficiency can retain 70% and be stable under intensive irradiation for 12 h. Besides, Mn3+ incorporation could prolong the photoluminescent decay time by passivating trap defects and modifying the distortion of the lattice, which underscores the significant potential for application as light emitters.
CRIS-Team Scopus Importer:2024-05-17
Keywords: interstitial doping; passivation; perovskite nanocrystal; photoluminescence; photostability

Enhanced photosynthetic activity in Spinacia oleracea by spectral modification with a photoluminescent light converting material - Xia, Qi; Batentschuk, Miroslaw; Osvet, Andres; Richter, Peter; Häder, Donat-Peter; Schneider, Juergen; Brabec, Christoph; Wondraczek, Lothar; Winnacker, Albrecht (Optics Express, 2013)
The spectral conversion of incident sunlight by appropriate photoluminescent materials has been a widely studied issue for improving the efficiency of photovoltaic solar energy harvesting. By using phosphors with suitable excitation/emission properties, also the light conditions for plants can be adjusted to match the absorption spectra of chlorophyll dyes, in this way increasing the photosynthetic activity of the plant. Here, we report on the application of this principle to a high plant, Spinacia oleracea. We employ a calcium strontium sulfide phosphor doped with divalent europium (Ca0.4Sr0.6S:Eu2+, CSSE) on a backlight conversion foil in photosynthesis experiments. We show that this phosphor can be used to effectively convert green to red light, centering at a wavelength of 650 nm which overlaps the absorption peaks of chlorophyll a/b pigments. A measurement system was developed to monitor the photosynthetic activity, expressed as the CO2 assimilation rate of spinach leaves under various controlled light conditions. Results show that under identical external light supply which is rich in green photons, the CO2 assimilation rate can be enhanced by more than 25% when the actinic light is modified by the CSSE conversion foil as compared to a purely reflecting reference foil. These results show that the phosphor could be potentially applied to modify the solar spectrum by converting the green photons into photosynthetically active red photons for improved photosynthetic activity. © 2013 Optical Society of Americ
Keywords: Engineering controlled terms: Carbon dioxide; Light emission; Phosphors; Photons; Plants (botany); Solar energy; Calcium Assimilation rate; Measurement system; Photoluminescent materials; Photosynthetic activity; Photovoltaic solar energy; Spectral conversion; Spectral modifications; Strontium sulfide phosphor; Divalent europium Engineering main heading: Light EMTREE drug terms: carbon dioxide; strontium EMTREE medical terms: article; chemistry; luminescence; metabolism; photon; photosynthesis; physiology; spectrofluorometry; spinach; time MeSH: Carbon Dioxide; Luminescence; Photons; Photosynthesis; Spectrometry; Fluorescence; Spinacia oleracea; Strontium; Time Factors Medline is the source for the MeSH terms of this document.

Enhancement of the Power Conversion Efficiency in Organic Photovoltaics by Unveiling the Appropriate Polymer Backbone Enlargement Approach - Chochos, Christos L.; Singh, Ranbir; Kim, Min; Gasparini, Nicola; Katsouras, Athanasios; Kulshreshtha, Chandramouli; Gregoriou, Vasilis G.; Keivanidis, Panagiotis E.; Ameri, Tayebeh; Brabec, Christoph; Cho, Kilwon; Avgeropoulos, Apostolos (Advanced Functional Materials, 2016)
Optoelectronic properties, supramolecular assemblies, and morphology variation of polymeric semiconductors are governed by six fundamental chemical features. These features are molecular weight, bond length alternation (BLA), planarity, aromatic resonance energy, substituents, and intermolecular interactions. Of these features the specific role of BLA in determining the performance of a polymeric semiconductor in practical technological applications is so far unknown. This study investigates this question and reports the novel finding that the optoelectronic, microscopic (supramolecular packing), and macroscopic (morphology variation and device performance) properties of model semiconducting polymers depend on the conjugated polymer backbone enlargement, which is directly related to the BLA. Extensive studies are performed in both single-component polymer films and their blends with fullerene derivatives. Understanding the specific structure-properties relations will lead to significant advancement in the area of organic electronics, since it will set new design rules toward further optimization of polymer chemical structures to enhance the device performances. An efficient way to enlarge the polymer backbone of an electron donor conjugated polymer toward higher organic photovoltaic performance is presented.
Keywords: morphology; organic electronics; polymer semiconductors; recombination dynamics; supramolecular assembly

Enhancement of up-conversion luminescence in Er,Ce doped Y3-xYbxAG single crystalline films - Zorenko, Yu.; Gorbenko, V.; Zorenko, T.; Paprocki, Kazimierz; Osvet, Andres; Batentschuk, Miroslaw; Brabec, Christoph; Fedorov, A. (Journal of Luminescence, 2016)
The paper deals with investigation of the luminescent properties of Er and Er/Ce doped solid solutions of YYbAG garnets with x values ranging from 0 to 3.0, prepared by the LPE method in the form of single crystalline films (SCF). We have found that the effective Ce→Yb energy transfer is observed in the YYbAlO:Er,Ce garnets (YYbAG:Er,Ce). Apart from that, strong enhancement of the Er upconvesion luminescence in YYbAG:Er,Ce garnets was found due to the Ce codoping. Among all the investigated samples of solid solutions of mixed YYbAG:Er,Ce garnets, the highest intensity of the up-conversion luminescence is observed for the YYbAG:Er,Ce SCF.
Keywords: Er and Ce dopant; Liquid phase luminescence; Mixed Y3-xYbxAG garnet; Single crystalline films; Up conversion luminescence

Enhancing Planar Inverted Perovskite Solar Cells with Innovative Dumbbell-Shaped HTMs: A Study of Hexabenzocoronene and Pyrene-BODIPY-Triarylamine Derivatives - Rocha-Ortiz, Juan S.; Wu, Jianchang; Wenzel, Jonas; Bornschlegl, Andreas; Perea, Jose Dario; Leon, Salvador; Barabash, Anastasiia; Wollny, Anna-Sophie; Guldi, Dirk Michael; Zhang, Jiyun; Insuasty, Alberto; Lüer, Larry; et al. (Advanced Functional Materials, 2023)
Keywords: hexabenzocoronene; donor–acceptor; BODIPY; π-conjugation; perovskite solar cells; hole-transport materials

Environmentally Printing Efficient Organic Tandem Solar Cells with High Fill Factors: A Guideline Towards 20% Power Conversion Efficiency - Li, Ning; Baran, Derya; Spyropoulos, George D.; Zhang, Hong; Berny, Stephane; Turbiez, Mathieu; Ameri, Tayebeh; Krebs, Frederik C.; Brabec, Christoph (Advanced Energy Materials, 2014)
The tandem concept involves stacking two or more cells with complementary absorption spectra in series or parallel connection, harvesting photons at the highest possible potential. It is strongly suggested that the roll-to-roll production of organic solar cells will employ the tandem concept to enhance the power conversion efficiency (PCE). However, due to the undeveloped deposition techniques, the challenges in ink formulation as well as the lack of commercially available high performance active materials, roll-to-roll fabrication of highly efficient organic tandem solar cells currently presents a major challenge. The reported high PCE values from lab-scale spin-coated devices are, of course, representative, but not helpful for commercialization. Here, organic tandem solar cells with exceptionally high fill factors and PCE values of 7.66% (on glass) and 5.56% (on flexible substrate), which are the highest values for the solution-processed tandem solar cells fabricated by a mass-production compatible coating technique under ambient conditions, are demonstrated. To predict the highest possible performance of tandem solar cells, optical simulation based on experimentally feasible values is performed. A maximum PCE of 21% is theoretically achievable for an organic tandem solar cell based on the optimized bandgaps and achieved fill factors.
Keywords: flexible electronics; large-scale production; organic photovoltaics; organic solar cells; solution processing

Environmentally safe layered crystal produced from hazardous chemical elements: TlPb2BrI4, a new promising detector material - Khyzhun, O. Y.; Vu, Tuan V.; Parasyuk, O. V.; Fedorchuk, A. O.; Fochuk, P. M.; Lavrentyev, A. A.; Gabrelian, B. V.; Levchuk, Ievgen; Matt, Gebhard; Tedde, Sandro F.; Schmidt, Oliver; Shrestha, Shreetu; et al. (Journal of Alloys and Compounds, 2022)
Exploring better Gamma, X-Ray and IR-Mid-R detectors, adequately sensitive to ambient temperatures and environmental conditions, is highly desirable. Therefore, following this path, we present detecting opportunities, based on data of experimental and theoretical investigation of the electronic and optical properties, photocurrent behavior at different bias voltages as well as the reflection for the He-Cd cw laser after irradiation by three different IR laser wavelengths, for recently grown TlPb2BrI4 single crystal with strong anisotropic, two-dimensional (2D) layered structure. The X-ray photoelectron spectroscopy brings data on binding energy values of core levels of TlPb2BrI4 for both as-grown and Ar+-ion-treated crystal surfaces as well as for elucidation of the energy distribution of the valence electronic states. In opposite to well-known IR-detector materials, TlPb2BrI4 crystal surface shows high chemical stability concerning Ar+-ion bombardment. Further, we carry out ab initio band-structure calculations to gain curves of total and partial densities of states and to elucidate the principal optical constants of TlPb2BrI4. The present studies indicate that, in spite of the fact that the TlPb2BrI4 crystal contains two very hazardous/toxic chemical elements, thallium and lead; however, it is chemically stable and reveals very low hygroscopic behavior when being exposed to environmental conditions.
CRIS-Team Scopus Importer:2022-09-02
Keywords: Electronic structure; First-principal computation; Lead; Hazardous elements; Thallium; XPS

Epitaxial Metal Halide Perovskites by Inkjet-Printing on Various Substrates - Sytnyk, Mykhailo; Yousefi-Amin, Amir Abbas; Freund, Tim; Prihoda, Annemarie; Götz, Klaus; Unruh, Tobias; Harreiß, Christina; Will, Johannes; Spiecker, Erdmann; Levchuk, Jevgen; Osvet, Andres; Brabec, Christoph; et al. (Advanced Functional Materials, 2020)
Metal-halide-perovskites revolutionized the field of thin-film semiconductor technology, due to their favorable optoelectronic properties and facile solution processing. Further improvements of perovskite thin-film devices require structural coherence on the atomic scale. Such perfection is achieved by epitaxial growth, a method that is based on the use of high-end deposition chambers. Here epitaxial growth is enabled via a approximate to 1000 times cheaper device, a single nozzle inkjet printer. By printing, single-crystal micro- and nanostructure arrays and crystalline coherent thin films are obtained on selected substrates. The hetero-epitaxial structures of methylammonium PbBr(3)grown on lattice matching substrates exhibit similar luminescence as bulk single crystals, but the crystals phase transitions are shifted to lower temperatures, indicating a structural stabilization due to interfacial lattice anchoring by the substrates. Thus, the inkjet-printing of metal-halide perovskites provides improved material characteristics in a highly economical way, as a future cheap competitor to the high-end semiconductor growth technologies.
CRIS-Team Scopus Importer:2020-09-11
Keywords: epitaxial growth; inkjet printing; metal-halide-perovskites; single-crystal-microstructures

Erratum: A multi-objective optimization-based layer-by-layer blade-coating approach for organic solar cells: Rational control of vertical stratification for high performance (Energy and Environmental Science (2019) 12 (3118-3132) DOI: 10.1039/C9EE02295C) - Sun, Rui; Guo, Jie; Wu, Qiang; Zhang, Zhuohan; Yang, Wenyan; Guo, Jing; Shi, Mumin; Zhang, Yaohong; Kahmann, Simon; Ye, Long; Jiao, Xuechen; Loi, Maria A.; et al. (Energy and Environmental Science, 2020)
The Acknowledgements section should have included the following sentence: "This work was performed in part on the SAXS/ WAXS beamline at the Australian Synchrotron, part of ANSTO". The Royal Society of Chemistry apologises for these errors and any consequent inconvenience to authors and readers.
CRIS-Team Scopus Importer:2020-02-04

Erratum: In(iii)-dictated formation of double Cs2AgxNa1−xFeyIn1−yCl6 perovskites (J. Mater. Chem. C (2023) 11 (6867–6873) DOI: 10.1039/D3TC01138) - Stroyuk, Oleksandr; Raievska, Oleksandra; Barabash, Anastasiia; Hauch, Jens; Brabec, Christoph (Journal of Materials Chemistry C, 2023)
The authors regret errors in Fig. 1(d) of the published article, in which the XRD patterns in Fig. 1(d) were incorrectly labelled with the In fraction values instead of the Fe fraction y values; in addition, the curves should have been numbered to correspond with the discussion in the main text. The corrected Fig. 1 image and caption are as shown here. (Figure Presented). The Royal Society of Chemistry apologises for these errors and any consequent inconvenience to authors and readers.
Created from Fastlane, Scopus look-up

Evaluation of Electron Donor Materials for Solution-Processed Organic Solar Cells via a Novel Figure of Merit - Min, Jie; Luponosov, Yuriy N.; Cui, Chaohua; Kan, Bin; Chen, Haiwei; Wan, Xiangjian; Chen, Yongsheng; Ponomarenko, Sergei A.; Li, Yongfang; Brabec, Christoph (Advanced Energy Materials, 2017)
Organic photovoltaic (OPV) technology offers many advantages, although no commercial applications have been achieved after more than a decade of intensive research and development. Several challenges have yet to be overcome including high power conversion efficiency (PCE), good processability, low cost, and excellent long-term stability, and so on. In this article, these fundamental challenges are significantly addressed by surveying and analyzing a new merit factor for material applied accessibility containing three parameters: synthetic complexity, device efficiency, and photostability. Thirty-five donor small molecules are introduced to assess their synthetic accessibility. Furthermore, the PCEs and device photostability of these molecules are carried out, and further measured under one sun illumination within 200 h, respectively. Combining with the characteristics of these three factors, investigated molecules are ranked according to an industrial figure of merit (i-FOM), while some guidelines for the material design and synthesis are given. It is suggested that a PCE of >14% and an i-FOM of >20% via active material engineering are realistic for possible industry future of OPV. Along with the systematic study, it is believed that this i-FOM can be taken into consideration at an early stage of molecular design and provides valuable insight for efficient evaluation of photovoltaic materials for possible commercial applications. © 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Conversion efficiency; Efficiency; Molecules; Solar cells; Synthesis (chemical); Transportation; Figure of merits; Long term stability; Low costs; Power conversion efficiencies; Processability; Organic solar cells

Evidence of Tailoring the Interfacial Chemical Composition in Normal Structure Hybrid Organohalide Perovskites by a Self-Assembled Monolayer - Will, Johannes; Hou, Yi; Scheiner, Simon; Pinkert, Ute; Hermes, Ilka M.; Weber, Stefan A.L.; Hirsch, Andreas; Halik, Marcus; Brabec, Christoph; Unruh, Tobias (ACS Applied Materials and Interfaces, 2018)
Current-voltage hysteresis is a major issue for normal architecture organo-halide perovskite solar cells. In this manuscript we reveal a several Å thick Methylammonium Iodide (MAI) rich interface between the perovskite and the metal oxide. Surface functionalization via selfassembled monolayers (SAMs) allowed us to control the composition of the interface monolayer from Pb poor to Pb rich, which in parallel suppresses hysteresis in perovskite solar cells. The bulk of the perovskite films is not affected by the interface engineering and remains highly crystalline in surface normal direction over the whole film thickness. The subnm structural modifications of the buried interface were revealed by x-ray reflectivity (XRR), which is most sensitive to monitor changes in the mass density of only several Å thin interfacial layers as a function of substrate functionalization. From Kelvin probe force microscopy (KPFM) on a solar cell cross section study, we further demonstrate local variations of the potential on different electron transporting layers (ETLs) within a solar cell. Based on these findings we present a unifying model explaining hysteresis in perovskite solar cells, giving for the first time insight into one crucial aspect of hysteresis and paving the way for new strategies in the fields of perovskite based opto-electronic devices.
Keywords: perovskite solar cell; hysteresis; buried interface; x-ray reflectivity; Kelvin probe force microscopy

Evidencing Excellent Thermal- and Photostability for Single-Component Organic Solar Cells with Inherently Built-In Microstructure - He, Yakun; Heumüller, Thomas; Lai, Wenbin; Feng, Guitao; Classen, Andrej; Du, Xiaoyan; Liu, Chao; Li, Weiwei; Li, Ning; Brabec, Christoph (Advanced Energy Materials, 2019)
Solution-processed organic solar cells (OSCs) are promising low-cost, flexible, portable renewable sources for future energy supply. The state-of-the-art OSCs are typically fabricated from a bulk-heterojunction (BHJ) active layer containing well-mixed donor and acceptor molecules in the nanometer regime. However, BHJ solar cells suffer from stability problems caused by the severe morphological changes upon thermal or illumination stress. In comparison, single-component organic solar cells (SCOSCs) based on a double-cable conjugated polymer with a covalently stabilized microstructure is suggested to be a key strategy for superior long-term stability. Here, the thermal- and photostability of SCOSCs based on a model double-cable polymer is systematically investigated. It is encouraging to find that under 90 °C & 1 sun illumination, the performance of SCOSCs remains substantially stable. Transport measurements show that charge generation and recombination (lifetime and recombination order) hardly change during the aging process. Particularly, the SCOSCs exhibit ultrahigh long-term thermal stability with 100% PCE remaining after heating at temperature up to 160 °C for over 400 h, indicating an excellent candidate for extremely rugged applicatio
Keywords: device stability; double-cable conjugated polymers; thermal- and photostability; organic photovoltaics; single-component organic solar cells

Evolution of cell cracks in PV-modules under field and laboratory conditions - Buerhop, Claudia; Wirsching, Sven; Bemm, Andreas; Pickel, Tobias; Hohmann, Philipp; Nieß, Monika; Vodermayer, Christian; Huber, Alexander; Glück, Bernhard; Mergheim, Julia; Camus, Christian; Hauch, Jens; et al. (Progress in Photovoltaics, 2017)
Damaged modules, especially with cell cracks, can be observed quite often in photovoltaicinstallations. Little knowledge exists about long‐term stability of precracked modules at real operating conditions. Previous investigations and existing standards focus on the degradation of new, defect‐free modules. This work highlights a twofold approach for life‐time study of precracked modules: (1) outdoor exposure of 54 precracked modules for 1 year and (2) artificial stressing of 20 representative precracked modules with a novel load test setup simulating snow and wind loads. The outdoor exposure reveals that at moderate weather conditions, no changes were detectable, neither in electric performance nor in EL‐images. However, the accelerated static load tests with stepwise increasing pressures point out that above a certain threshold, cracks grow. Below this threshold, formerly unseen cracks become visible at the loaded stage. In addition, modules with a smaller number of damaged cells have a stronger tendency to degrade further than modules with an already large number of cracked cells. Remarkably, the power output measured with a solar simulator after a stress test up to 2500 Pa (describing conservative proof conditions for severe snow loads according IEC 61215) remains unchanged for almost all modules.
Keywords: cracks; electroluminescence; field test; mechanically loading; performance; pre‐cracked modules

Excited-State Interaction of Semiconducting Single-Walled Carbon Nanotubes with Their Wrapping Polymers - Kahmann, Simon; Salazar Rios, Jorge M.; Zink, Matthias; Allard, Sybille; Scherf, Ullrich; Dos Santos, Maria C.; Brabec, Christoph; Loi, Maria A. (Journal of Physical Chemistry Letters, 2017)
ABSTRACT: We employ photoluminescence and pump−probe spectroscopy on films of semiconducting single-walled carbon nanotubes (CNTs) of different chirality wrapped with either a wide band gap polyfluorene derivative (PF12) or a polythiophene with narrower gap (P3DDT) to elucidate the excited states’ interplay between the two materials. Excitation above the polymer band gap gives way to an ultrafast electron transfer from both polymers toward the CNTs. By monitoring the hole polaron on the polymer via its mid infrared signature, we show that also illumination below the polymer band gap leads to the formation of this fingerprint and infer that holes are also transferred toward the polymer. As this contradicts the standard way of discussing the involved energy levels, we propose that polymer-wrapped CNTs should be considered as a single hybrid system, exhibiting states shared between the two components. This proposition is validated through quantum chemical calculations that show hybridization of the first excited states, especially for the thiophene−CNT sampl

Experimental efficiency of a low concentrating CPC PVT flat plate collector - Pröll, Markus; Osgyan, P.; Karrer, H.; Brabec, Christoph (Solar Energy, 2017)
PVT collectors aim to solar co-generation of electricity and heat. An new concept raises thermal efficiency by concentrating sunlight with CPC reflectors, in order to access a higher number of solar thermal applications. Losses in PV efficiency due to a higher operating temperature are accepted with regard to a higher overall collector efficiency. As a side effect, the concentration lowers the material usage of PV and enables a high efficient thermal coupling of the PV cell to the heat carrying fluid. The work focuses on the construction, as well as on the angle dependent electrical and thermal measurement of the real-size CPC PVT collector prototype (1460mm×600mm×150mm). In previous publications, calculations and experiments studied the influence of the CPC reflectors on the PV efficiency. Further, the thermal coupling between PV cell and heat carrier fluid has been measured in a lab experiment. These results, together with transient annual simulations, were considered in the design process of the CPC PVT prototype with an angular acceptance range of ±25°. The experiments were conducted on the outdoor solar test facility at ZAE Bayern in Garching, Germany. The thermal and PV efficiency has been measured with MPP tracking, as well as for open circuit voltage for fluid temperatures up to 107°C. It could be shown, that the thermal efficiency while MPP tracking is elevated to 34% compared to a glazed flat plate PVT with 17% for collector temperatures 60K over ambiance. At the same time, the electrical efficiency drops from 15% cell efficiency to an overall collector efficiency of 9%, due to the optical setup, temperature effects and a non-uniform flux distribution caused by the reflectors.
Keywords: Collector; Concentration; CPC; Experimental; Flat plate; Fluid; Hybrid; PV; PVT; Solar; Solar thermal

Exploring Highly Efficient Broadband Self-Trapped-Exciton Luminophors: from 0D to 3D Materials - Stroyuk, Oleksandr; Raievska, Oleksandra; Zahn, Dietrich R.T.; Brabec, Christoph J. (Chemical Record, 2023)
The review summarizes our recent reports on brightly-emitting materials with varied dimensionality (3D, 2D, 0D) synthesized using “green” chemistry and exhibiting highly efficient photoluminescence (PL) originating from self-trapped exciton (STE) states. The discussion starts with 0D emitters, in particular, ternary indium-based colloidal quantum dots, continues with 2D materials, focusing on single-layer polyheptazine carbon nitride, and further evolves to 3D luminophores, the latter exemplified by lead-free double halide perovskites. The review shows the broadband STE PL to be an inherent feature of many materials produced in mild conditions by “green” chemistry, outlining PL features general for these STE emitters and differences in their photophysical properties. The review is concluded with an outlook on the challenges in the field of STE PL emission and the most promising venues for future research.
CRIS-Team Scopus Importer:2023-09-29
Keywords: lead-free halide perovskites; photoluminescence; quantum dots; self-trapped exciton; single-layer carbon nitride

Exploring the Limiting Open-Circuit Voltage and the Voltage Loss Mechanism in Planar CH3NH3PbBr3 Perovskite Solar Cells - Chen, Shi; Hou, Yi; Chen, Haiwei; Richter, Moses; Guo, Fei; Kahmann, Simon; Tang, Xiaofeng; Stubhan, Tobias; Zhang, Hong; Li, Ning; Gasparini, Nicola; Ramírez Quiroz, César Omar; et al. (Advanced Energy Materials, 2016)
Perovskite solar cells based on CHNHPbBr with a band gap of 2.3 eV are attracting intense research interests due to their high open-circuit voltage (V) potential, which is specifically relevant for the use in tandem configuration or spectral splitting. Many efforts have been performed to optimize the V of CHNHPbBr solar cells; however, the limiting V (namely, radiative V:V) and the corresponding ΔV (the difference between V and V) mechanism are still unknown. Here, the average V of 1.50 V with the maximum value of 1.53 V at room temperature is achieved for a CHNHPbBr solar cell. External quantum efficiency measurements with electroluminescence spectroscopy determine the V of CHNHPbBr cells with 1.95 V and a ΔV of 0.45 V at 295 K. When the temperature declines from 295 to 200 K, the obtained V remains comparably stable in the vicinity of 1.5 V while the corresponding ΔV values show a more significant increase. Our findings suggest that the V of CHNHPbBr cells is primarily limited by the interface losses induced by the charge extraction layer rather than by bulk dominated recombination losses. These findings are important for developing strategies how to further enhance the V of CHNHPbBr-based solar cells.
Keywords: CH3NH3PbBr3 solar cells; interface materials based losses; nonradiative recombination losses; open-circuit voltage

Exploring the Stability of Novel Wide Bandgap Perovskites by a Robot Based High Throughput Approach - Chen, Shi; Hou, Yi; Chen, Haiwei; Tang, Xiaofeng; Langner, Stefan; Li, Ning; Stubhan, Tobias; Levchuk, Ievgen; Gu, Ening; Osvet, Andres; Brabec, Christoph (Advanced Energy Materials, 2017)
Currently, lead-based perovskites with mixed multiple cations and hybrid halides are attracting intense research interests due to their promising stability and high efficiency. A tremendous amount of 3D and 2D perovskite compositions and configurations are causing a strong demand for high throughput synthesis and characterization. Furthermore, wide bandgap (≈1.75 eV) perovskites as promising top-cell materials for perovskite–silicon tandem configurations require the screening of different compositions to overcome photoinduced halide segregation and still yielding a high opencircuit voltage (Voc). Herein, a home-made high throughput robot setup is introduced performing automatic perovskite synthesis and characterization. Subsequently, four kinds of compositions (i.e., cation mixtures of Cs–methylammonium (MA), Cs– formamidinium (FA), MA–FA, and FA–MA) with an optical bandgap of ≈1.75 eV are identified as promising device candidates. For Cs–MA and Cs–FA films it is found that the Br–I phase segregation indeed can be overcome. Moreover, Cs–MA, MA–FA, and Cs–FA based devices exhibit an average Voc of 1.17, 1.17, 1.12 V, and their maximum values approached 1.18, 1.19, 1.14 V, respectively, which are among the highest Voc (≈1.2 V) values for ≈40% Br perovskite. These findings highlight that the high throughput approach can effectively and efficiently accelerate the invention of novel perovskites for advanced applications.

Exploring the Steric Hindrance of Alkylammonium Cations in the Structural Reconfiguration of Quasi-2D Perovskite Materials Using a High-throughput Experimental Platform - Zhang, Jiyun; Wu, Jianchang; Langner, Stefan; Zhao, Baolin; Xie, Zhiqiang; Hauch, Jens; Afify, Hany A.; Barabash, Anastasiia; Luo, Junsheng; Sytnyk, Mykhailo; Meng, Wei; Zhang, Kaicheng; et al. (Advanced Functional Materials, 2022)
Reduced-dimensional (2D or quasi-2D) perovskites have recently attracted considerable interest due to their superior long-term stability. The nature of the intercalating cations plays a key role in determining the physicochemical properties and stability of the quasi-2D perovskites. Here, the thermal stability of a series of 2D Ruddlesden−Popper (RP) perovskites is studied using seven types of intercalating cations with increasing linear carbon-chain length from ethylammonium (EA) to n-dodecylammonium (DA) through a high-throughput platform. The results show that long-chain cations in quasi-2D perovskite films lead to strong steric hindrance between adjacent perovskite domains, thus suppressing Ostwald ripening during the thermal-aging process. For short-chain cations, increased-dimensional phase redistribution during the aging period is observed, which can benefit a concomitant regeneration of the 3D/3D-like perovskite phases. The impact of steric hindrance on structural reconfiguration and the subsequent phase redistribution in quasi-2D perovskites are systematically characterized by UV–vis absorption spectra, photoluminescence spectra, and X-ray diffraction patterns. Due to the steric hindrance effect, an optimal chain length is found to maximize film stability by balancing the water/oxygen resistance and increased-dimensional phase redistribution. This work provides new insight into the thermal stability of quasi-2D perovskites.
CRIS-Team Scopus Importer:2022-09-02
Keywords: 2D perovskite materials; high-throughput platform; stability performance; steric hindrance; steric structure and reconfiguration

Extending the environmental lifetime of unpackaged perovskite solar cells through interfacial design - Chen, Haiwei; Hou, Yi; Halbig, Christian Eberhard; Chen, Shi; Zhang, Hong; Li, Ning; Guo, Fei; Tang, Xiaofeng; Gasparini, Nicola; Levchuk, Ievgen; Kahmann, Simon; Ramírez Quiroz, César Omar; et al. (Journal of Materials Chemistry A, 2016)
Solution-processed oxo-functionalized graphene (oxo-G) is employed to substitute hydrophilic PEDOT:PSS as an anode interfacial layer for perovskite solar cells. The resulting devices exhibit a reasonably high power conversion efficiency (PCE) of 15.2% in the planar inverted architecture with oxo-G as a hole transporting material (HTM), and most importantly, deploy the full open-circuit voltage (V) of up to 1.1 V. Moreover, oxo-G effectively slows down the ingress of water vapor into the device stack resulting in significantly enhanced environmental stability of unpackaged cells under illumination with 80% of the initial PCE being reached after 500 h. Without encapsulation, ∼60% of the initial PCE is retained after ∼1000 h of light soaking under 0.5 sun and ambient conditions maintaining the temperature beneath 30 °C. Moreover, the unsealed perovskite device retains 92% of its initial PCE after about 1900 h under ambient conditions and in the dark. Our results underpin that controlling water diffusion into perovskite cells through advanced interface engineering is a crucial step towards prolonged environmental stability.
Keywords: Engineering controlled terms: Cell engineering; Conducting polymers; Open circuit voltage; Perovskite; Slow light; Solar cells Environmental stability; Functionalized graphene; High power conversion; Hole-transporting materials; Interface engineering; Interfacial design; Inverted architectures; Solution-processed Engineering main heading: Perovskite solar cells

Extracting and shaping the light of OLED devices - Riedel, Daniel; Dlugosch, Julian; Wehlus, Thomas; Brabec, Christoph (Proceedings of SPIE, 2015)
Before the market entry of organic light emitting diodes (OLEDs) into the field of general illumination can occur, limitations in lifetime, luminous efficacy and cost must be overcome. Additional requirements for OLEDs used for general illumination may be imposed by workplace glare reduction requirements, which demand limited luminance for high viewing angles. These requirements contrast with the typical lambertian emission characteristics of OLEDs, which result in the same luminance levels for all emission angles. As a consequence, without additional measures glare reduction could limit the maximum possible luminance of lambertian OLEDs to relatively low levels. However, high luminance levels are still desirable in order to obtain high light output. We are presenting solutions to overcome this dilemma. Therefore this work is focused on light-shaping structures for OLEDs with an internal light extraction layer. Simulations of beam-shaping structures and shapes are presented, followed by experimental measurements to verify the simulations of the most promising structures. An investigation of the loss channels has been carried out and the overall optical system efficiency was evaluated for all structures. The most promising light shaping structures achieve system efficiencies up to 80%. Finally, a general illumination application scenario has been simulated. The number of OLEDs needed to illuminate an office room has been deduced from this scenario. By using light-shaping structures for OLEDs, the number of OLEDs needed to reach the mandatory illuminance level for a workplace environment can be reduced to one third compared to lambertian OLED
Keywords: Organic light emitting diodes; Simulations; Beam shaping; Luminous efficacy; Optical systems

Fabrication, Optical Modeling, and Color Characterization of Semitransparent Bulk-Heterojunction Organic Solar Cells in an Inverted Structure - Ameri, Tayebeh; Dennler, Gilles; Waldauf, Christoph; Azimi, Hamed; Seemann, Andrea; Forberich, Karen; Hauch, Jens; Scharber, Markus; Hingerl, Kurt; Brabec, Christoph (Advanced Functional Materials, 2010)
Semitransparent inverted organic photodiodes are fabricated with a Baytron PH500 ethylene-glycol layer/silver grid as the top electrode. Reasonable performances are obtained under both rear- and front-side illumination and efficiencies up to 2% are achieved. Some light is shed on visual prospects through optical simulations for a semitransparent device of poly(3-hexylthiophene) (P3HT) and the C60 derivative 1-(3-methoxycarbonyl)propyl-1-phenyl[6,6]C71 (PC70BM) in the inverted structure. These calculations allow the maximum efficiency achievable to be predicted for semitransparent cells based on P3HT:PC70BM versus the transparency perception for a human eye. The simulations suggest that low-bandgap materials such as poly[2,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b′]dithiophene)-alt-4,7-(2,1,3-benzothiadiazole)] (PCPDTBT) have a better potential for semitransparent devices. In addition, the color range recognized by the human eye is predicted by the optical simulation for some semitransparent devices including different active layers.

Facile synthesis and photovoltaic applications of a new alkylated bismethano fullerene as electron acceptor for high open circuit voltage solar cells - Baran, Derya; Erten-Ela, Sule; Kratzer, Andreas; Ameri, Tayebeh; Brabec, Christoph; Hirsch, Andreas (RSC Advances, 2015)
It is crucial to control the lowest unoccupied molecular orbital (LUMO) of electron accepting materials for producing efficient charge transfer in bulk heterojunction (BHJ) solar cells. Due to their high LUMO level, soluble bis-adducts of C60 are of high interest for improving the Voc in BHJ solar cells. In this work, we have developed a novel bis-4-propylpentyl[6,6]methanofullerene bis-adduct, NCBA, using a alkyl solubilizing group. The optoelectronic, electrochemical and photovoltaic properties of this bis-product are investigated. NCBA is successfully applied as the electron acceptor with poly(3-hexylthiophene) (P3HT) in a BHJ solar cell showing a high Voc of 0.73 V.
Keywords: Engineering controlled terms: Charge transfer; Heterojunctions; Molecular orbitals; Open circuit voltage; Solar power generation Bulk heterojunction (BHJ); Electron acceptor; Electron-accepting; Lowest unoccupied molecular orbital; Methanofullerenes; Photovoltaic applications; Photovoltaic property; Poly-3-hexylthiophene Engineering main heading: Solar cells

Facile synthesis and post-processing of eco-friendly, highly conductive copper zinc tin sulphide nanoparticles - Ahmad, Rameez; Distaso, Monica; Azimi, Seyed Hamed; Brabec, Christoph; Peukert, Wolfgang (Journal of Nanoparticle Research, 2013)
Cu2ZnSnS4 (CZTS) nanoparticles have shown promising properties to be used as an energy harvesting material. They are usually synthesised under inert atmosphere or vacuum, whereas the subsequent step of film formation is carried out under an atmosphere of sulphur and/or Sn in order to avoid the decomposition of CZTS nanoparticles into binary and ternary species as well as the formation of the corresponding oxides. In the present paper we show that both the synthesis of CZTS nanoparticles and the film formation from the corresponding suspension can be considerably simplified. Namely, the synthesis can be carried out without controlling the atmosphere, whereas during the film annealing a nitrogen atmosphere is sufficient to avoid the depletion of the CZTS kesterite phase. Furthermore, an integrated approach including in-depth Raman analysis is developed in order to deal with the challenges associated with the characterization of CZTS nanoparticles in comparison to bulk systems. The formation of competitive compounds during the synthesis such as binary and ternary sulphides as well as metal oxides nanoparticles is discussed in detail. Finally, the as-produced films have ten times higher conductivity than the state of the art.
Keywords: By-products; Defects; Kesterite; Raman spectroscopy; Stannite CZTS nanoparticles; Thermodynamic study

Failure classification of defective PV Modules based on maximum power point analysis - Fecher, Frank; Pickel, Tobias; Buerhop-Lutz, Claudia; Camus, Christian; Brabec, Christoph (32nd European Photovoltaic Solar Energy Conference and Exhibition, 2016)
Photovoltaic (PV) modules are often affected by defects caused by transport and installation or by field degradation due to environmental conditions. If a power reduction is observed in the inverter data, a detailed error cause analysis is often very cost-intensive even when using imaging methods like thermography or electroluminescence. We present a method to classify the defect type of PV modules only by evaluating the maximum power output (Pmpp) for different irradiances. Thereby, low parallel resistance, high series resistance and broken cells can be distinguished from each other. Simulations and consistent explanations confirm the experimental findings. The method works particularly well for parallel resistance problems like potential induced degradation (PID). Thus, this failure type can easily be diagnosed in modules. The method should also be applicable to data of module strings and to thermography-based failure analysis in field which will be investigated in the future.
Keywords: Defects; Degradation; Photovoltaic; PV Module; Simulation

Fassadenelemente mit organischer Photovoltaik - Egelhaaf, Hans-Joachim; Brabec, Christoph; Neberich, Marcel; Senguttuvan, Kaushik; Hoga, Felix; Kießling, Günther; Braun, Matthias; Bordin, Susanna; Wagner, Michael; Distler, Andreas; Feroze, Sarmad; Dentel, Arno (BWK Das Energie Fachmagazin, 2021)
In dem vom Bundesministerium für Wirtschaft und Energie (BMWi) geförderten Projekt „Fassade3“ entwickelt ein Konsortium aus akademischen und industriellen Partnern ein multifunktionales Fassadenelement mit integrierter organischer Photovoltaik (OPV). Die Fassade kann aufgrund ihrer modularen Struktur vorgefertigt und sowohl in Neu- als auch Bestandsgebäude integriert werden. Sie fungiert als Energiequelle, dient der thermischen Isolation, bietet Sonnenschutz für den Innenraum und optimiert so die Energieeffizienz des Gebäudes. Mit einfachen Mitteln lässt sich somit eine voll funktionsfähige und gleichzeitig ästhetisch ansprechende Konstruktion realisieren. Ein eigens entwickeltes Messsystem erlaubt die Echtzeit-Überwachung der Energiebilanz der Fassade. Erste Ergebnisse zum Leistungsverhältnis der OPV-Module sind vielversprechend.

Fast and Robust Detection of Solar Modules in Electroluminescence Images - Hoffmann, Mathis; Doll, Bernd; Talkenberg, Florian; Brabec, Christoph; Maier, Andreas; Christlein, Vincent (Computer Analysis of Images and Patterns, 2019)

Favorable Mixing Thermodynamics in Ternary Polymer Blends for Realizing High Efficiency Plastic Solar Cells - Gasparini, Nicola; Kahmann, Simon; Salvador, Michael Filipe; Perea, Jose Dario; Sperlich, Andreas; Baumann, Andreas; Li, Ning; Rechberger, Stefanie; Spiecker, Erdmann; Dyakonov, Vladimir; Portale, Giuseppe; Loi, Maria A.; et al. (Advanced Energy Materials, 2019)
Ternary blends with broad spectral absorption have the potential to increase charge generation in organic solar cells but feature additional complexity due to limited intermixing and electronic mismatch. Here, a model system comprising the polymers poly[5,5-bis(2-butyloctyl)-(2,2-bithiophene)-4,4-dicarboxylate-alt-5,5-2,2-bithiophene] (PDCBT) and PTB7-Th and PC70BM as an electron accepting unit is presented. The power conversion efficiency (PCE) of the ternary system clearly surpasses the performance of either of the binary systems. The photophysics is governed by a fast energy transfer process from PDCBT to PTB7-Th, followed by electron transfer at the PTB7-Th:fullerene interface. The morphological motif in the ternary blend is characterized by polymer fibers. Based on a combination of photophysical analysis, GIWAXS measurements and calculation of the intermolecular parameter, the latter indicating a very favorable molecular affinity between PDCBT and PTB7-Th, it is proposed that an efficient charge generation mechanism is possible because PTB7-Th predominantly orients around PDCBT filaments, allowing energy to be effectively relayed from PDCBT to PTB7-Th. Fullerene can be replaced by a nonfullerene acceptor without sacrifices in charge generation, achieving a PCE above 11%. These results support the idea that thermodynamic mixing and energetics of the polymer–polymer interface are critical design parameter for realizing highly efficient ternary solar cells with variable electron acceptors</stron
Keywords: FRET; high efficiency; ternary organic solar cells; mixing thermodynamics; photophysics

Fine-tuning of the chemical structure of photoactive materials for highly efficient organic photovoltaics - Fan, Baobing; Du, Xiaoyan; Liu, Feng; Zhong, Wenkai; Ying, Lei; Xie, Ruihao; Tang, Xiaofeng; An, Kang; Xin, Jingming; Li, Ning; Ma, Wei; Brabec, Christoph; et al. (Nature Energy, 2018)
The performance of organic photovoltaics is largely dependent on the balance of short-circuit current density (JSC) and open-circuit voltage (VOC). For instance, the reduction of the active materials’ optical bandgap, which increases the JSC, would inevitably lead to a concomitant reduction in VOC. Here, we demonstrate that careful tuning of the chemical structure of photoactive materials can enhance both JSC and VOC simultaneously. Non-fullerene organic photovoltaics based on a well-matched materials combination exhibit a certified high power conversion efficiency of 12.25% on a device area of 1 cm2. By combining Fourier-transform photocurrent spectroscopy and electroluminescence, we show the existence of a low but non-negligible charge transfer state as the possible origin of VOC loss. This study highlights that the reduction of the bandgap to improve the efficiency requires a careful materials design to minimize non-radiative VOC losses. © 2018, The Author(s), under exclusive licence to Springer Nature Limite
Keywords: Active material; Charge transfer state; Concomitant reduction; High power conversion; Materials design; Organic photovoltaics; Photoactive materials; Photocurrent spectroscopy

First Year of Smart Metering with a High Time Resolution - Realistic Self-Sufficiency Rates for Households with Solar Batteries - Stegner, Christoph; Bogenrieder, Josef; Luchscheider, Philipp; Brabec, Christoph (Energy Procedia, 2016)
Measured data from distribution grids with a high time resolution is scarce although it is where most volatile power profiles occur. Electrical storage systems (ESS) can mitigate the imbalance of generation and demand. In this study smart meter data with a temporal resolution of 15 s is analyzed and an algorithm described, that allows identifying differently oriented generator in mixed PV plants. Various self-consumption scenarios are simulated with different setups and temporal resolution. The calculated self-sufficiency rates lead to recommendations for the dimensioning and give precise values for the correction of key parameters from simulations if data is not available in high temporal resolution. © 2016 The Authors. Published by Elsevier Ltd.
Keywords: dimensioning; PV battery systems; PV simulation; residential smart meter; self-consumption; temporal resolution

Flexible and highly segmented OLED for automotive applications - Bechert, Hermann; Wittmann, Sebastian; Brabec, Christoph; Wehlus, Thomas (Proceedings Volume 10687, Organic Electronics and Photonics: Fundamentals and Devices; 106870Q, 2018)
Today OLEDs are established light-sources for automotive rear-lights. OLEDs having a small number of segments can be found in various cars and are about to spread further. Beyond this state-of-the-art OLEDs being flexible as well as featuring a higher number of segments are desired by OEMs. Unfortunately conventional display approaches like passive and active matrix displays are struggling to deliver the high luminance and fill factor required for automotive applications and are therefore unable to fulfill the requirements by the automotive lighting industry. In this work we are going to present our approach on flexible and highly segmented OLED applications for Automotive to overcome this problem. An investigation of a novel device concept is demonstrated, as well as details on our substrate technology development, encapsulation and electronic/driving schemes. A strong focus has been put on the possibility to use standard lithography for substrate creation to have, if possible, no impact on existing supply chains and a maximum of reliability due to the use of well-known processes. The core concept for flexible and highly segmented OLED devices is derived from this processes. Challenges that occurred during the manufacturing of the substrates and devices are described in detail as well as solutions to circumvent these unexpected problems. Measurements of OLED key parameters are presented together with visual impressions of the devices. Driving schemes and electronics needed to control the OLED segments are introduced in short to complete the study of the overall concept of flexible and highly segmented OLEDs for automotive application
Keywords: segmentation; OLED; rear-light; flexible; automotive

Flexible organic tandem solar modules: A story of up-scaling - Spyropoulos, Georgios; Kubis, Peter; Li, Ning; Lucera, Luca; Salvador, Michael Filipe; Baran, Derya; Machui, Florian; Ameri, Tayebeh; Voigt, Monika; Brabec, Christoph (Organic Photovoltaics XV, 2014)
The competition in the field of solar energy between Organic Photovoltaics (OPVs) and several Inorganic Photovoltaic technologies is continuously increasing to reach the ultimate purpose of energy supply from inexpensive and easily manufactured solar cell units. Solution-processed printing techniques on flexible substrates attach a tremendous opportunity to the OPVs for the accomplishment of low-cost and large area applications. Furthermore, tandem architectures came to boost up even more OPVs by increasing the photon-harvesting properties of the device. In this work, we demonstrate the road of realizing flexible organic tandem solar modules constructed by a fully roll-to-roll compatible processing. The modules exhibit an efficiency of 5.4% with geometrical fill factors beyond 80% and minimized interconnection-resistance losses. The processing involves low temperature (<70 °C), coating methods compatible with slot die coating and high speed and precision laser patterning.
Keywords: Flexible solar cells; Laser patterning; Organic solar modules; Organic tandem solar cells; Solution-processing

Flexible organic tandem solar modules with 6% efficiency: combining roll-to-roll compatible processing with high geometric fill factors - Spyropoulos, Georgios; Kubis, Peter; Li, Ning; Baran, Derya; Lucera, Luca; Salvador, Michael Filipe; Ameri, Tayebeh; Voigt, Monika; Krebs, F. C.; Brabec, Christoph (Energy and Environmental Science, 2014)
Organic solar cell technology bears the potential for high photovoltaic performance combined with truly low-cost, high-volume processing. Here we demonstrate organic tandem solar modules on flexible substrates fabricated by fully roll-to-roll compatible processing at temperatures <70 °C. By using ultrafast laser patterning we considerably reduced the “dead area” of the modules and achieved geometric fill factors beyond 90%. The modules revealed very low interconnection-resistance compared to the single tandem cells and exhibited a power conversion efficiency of up to 5.7%. Bending tests performed on the modules suggest high mechanical resilience for this type of device. Our findings inform concrete steps towards high efficiency photovoltaic applications on curved, foldable and moving surfaces.
Keywords: Fill factor; Roll to Roll; Solar module GEOBASE Subject Index: photovoltaic system; resilience; solar power; volume

Flexible sample cell for real-time GISAXS, GIWAXS and XRR: design and construction - Berlinghof, Marvin; Bär, Christian; Haas, D.; Bertram, F.; Langner, Stefan; Osvet, Andres; Chumakov, A.; Will, Johannes; Schindler, Torben; Zech, Tobias; Brabec, Christoph; Unruh, Tobias (Journal of Synchrotron Radiation, 2018)
Since the properties of functional materials are highly dependent on their specific structure, and since the structural changes, for example during crystallization, induced by coating and annealing processes are significant, the study of structure and its formation is of interest for fundamental and applied science. However, structure analysis is often limited to ex situ determination of final states due to the lack of specialized sample cells that enable real-time investigations. The lack of such cells is mainly due to their fairly complex design and geometrical restrictions defined by the beamline setups. To overcome this obstacle, an advanced sample cell has been designed and constructed; it combines automated doctor blading, solvent vapor annealing and sample hydration with real-time grazing-incidence wide- and small-angle scattering (GIWAXS/GISAXS) and X-ray reflectivity (XRR). The sample cell has limited spatial requirements and is therefore widely usable at beamlines and laboratory-scale instruments. The cell is fully automatized and remains portable, including the necessary electronics. In addition, the cell can be used by interested scientists in cooperation with the Institute for Crystallography and Structural Physics and is expandable with regard to optical secondary probes. Exemplary research studies are presented, in the form of coating of P3HT:PC61PM thin films, solvent vapor annealing of DRCN5T:PC71BM thin films, and hydration of supported phospholipid multilayers, to demonstrate the capabilities of the in situ cell.
Keywords: in situ; GIWAXS; GISAXS; XRR; thin film

Flexible Solar Cells - Maisch, Philipp; Lucera, Luca; Egelhaaf, Hans-Joachim; Brabec, Christoph (Flexible Carbon-based Electronics, 2018)
This third volume in the Advanced Nanocarbon Materials series covers the topic of flexible electronics both from a materials and an applications perspective. Comprehensive in its scope, the monograph examines organic, inorganic and composite materials with a section devoted to carbon-based materials with a special focus on the generation and properties of 2D materials. It also presents carbon modifications and derivatives, such as carbon nanotubes, graphene oxide and diamonds. In terms of the topical applications covered these include, but are not limited to, flexible displays, organic electronics, transistors, integrated circuits, semiconductors and solar cells. These offer perspectives for today?s energy and healthcare challenges, such as electrochemical energy storage and wearable devices. Finally, a section on fundamental properties and characterization approaches of flexible electronics rounds off the book. Each contribution points out the importance of the structure-function relationship for the target-oriented fabrication of electronic devices, enabling the design of complex component

Flexible top-emitting OLEDs for lighting: Bending limits - Schwamb, Philipp; Reusch, Thilo; Brabec, Christoph (Organic Light Emitting Materials and Devices XVII, 2013)
Flexible OLED light sources have great appeal due to new design options, being unbreakable and their low weight. Top-emitting OLED device architectures offer the broadest choice of substrate materials including metals which are robust, impermeable to humidity, and good thermal conductors making them promising candidates for flexible OLED device substrates. In this study, we investigate the bending limits of flexible top-emitting OLED lighting devices with transparent metal electrode and thin film encapsulation on a variety of both metal and plastic foils. The samples were subjected to concave and convex bending and inspected by different testing methods for the onset of breakdown for example visible defects and encapsulation failures. The critical failure modes were identified as rupture of the transparent thin metal top electrode and encapsulation for convex bending and buckling of the transparent metal top electrode for concave bending. We investigated influences from substrate material and thickness and top coating thickness. The substrate thickness is found to dominate bending limits as expected by neutral layer modeling. Coating shows strong improvements for all substrates. Bending radii <15mm are achieved for both convex and concave testing without damage to devices including their encapsulation. © 2013 SPIE.
Keywords: Bending; Flexible; Organic light-emitting diode; Thin film encapsulation; Transparent metal electrode

FTIR study of the impact of PC[60]BM on the photodegradation of the low band gap polymer PCPDTBT under O2 environment - Dettinger, Ulf; Egelhaaf, Hans-Joachim; Brabec, Christoph; Latteyer, Florian; Peisert, Heiko; Chasse, Thomas (Chemistry of Materials, 2015)
The photodegradation of the low band gap polymer poly[2,6-(4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b]dithiophene)-alt-4,7(2,1,3-benzothiadiazole)] (PCPDTBT) during irradiation under white light (AM 1.5 conditions) has been studied in pristine polymer films as well as in blend films with [6,6]-phenyl C61 butyric acid methyl ester (PC[60]BM). In order to gain insight into the degradation process, FTIR spectroscopy has been used to follow the evolution of different subunits of the polymer and to probe the chemical product formation. In contrast to other polymers, not the alkyl side chains but the π-conjugated system is preferentially oxidized during the first stages of degradation. Furthermore, it has been shown that the subunits of the polymer backbone are differently affected by the degradation. Blending the polymer with PC[60]BM leads to a significantly larger impact on the stability of the cyclopentadiene group compared to the benzene ring of the benzothiadiazole group.
Keywords: Engineering controlled terms: Blending; Butyric acid; Conjugated polymers; Energy gap; Fourier transform infrared spectroscopy; Polymers 2; 1; 3-Benzothiadiazole; Alkyl side chains; Cyclopentadiene groups; Degradation process; FTIR spectroscopy; Low bandgap polymers; Pi-conjugated system; Pristine polymers Engineering main heading: Polymer films

Fullerene sensitized silicon for near- to mid-infrared light detection - Matt, Gebhard J.; Fromherz, Thomas; Bednorz, Mateusz; Zamiri, Saeid; Goncalves, Guillaume; Lungenschmied, Christoph; Meissner, Dieter; Sitter, Helmut; Sariciftci, N. Serdar; Brabec, Christoph; Bauer, Guenther (Advanced Materials, 2010)
A novel light-sensing scheme based on a silicon/fullerene-derivative heterojunction allows optoelectronic detection in the near- to mid-infrared (IR), which is fully compatible with complementary metal oxide semiconductor (CMOS) technology. Although silicon and the fullerene derivative do not absorb in the IR, a heterojunction of these materials absorbs and generates a photocurrent (PC) in the near- to mid-IR, presumably caused by an interfacial absorption mechanism. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Fully Printed and Industrially Scalable Semitransparent Organic Photovoltaic Modules: Navigating through Material and Processing Constraints - Wachsmuth, Josua; Distler, Andreas; Liu, Chao; Heumüller, Thomas; Liu, Yang; Aitchison, Catherine M.; Hauser, Alina; Rossier, Michael; Robitaille, Amélie; Llobel, Marc Antoine; Morin, Pierre Olivier; Thepaut, Anaïs; et al. (Solar RRL, 2023)
While the power conversion efficiency (PCE) of organic photovoltaics (OPV) on small-area lab cells has rapidly increased during the last few years, the performance on module level and the availability of OPV modules on the market is still limited, primarily due to specific constraints imposed by the industrial production process. This work deals with the upscaling process of latest-generation OPV from small-area lab cells to fully solution-processed modules, which are compatible to industrial roll-to-roll (R2R) printing. This transfer is demonstrated step by step from material selection and process optimization for every single layer of the stack (photoactive layer, charge transporting layers, and solution-processed top electrode)–including long-term stability investigations (thermal and light)–to scaling up the device area by a factor of >100. Thus, a semitransparent OPV module with 10.8% PCE on 10.2 cm2 active area is achieved, which is among the highest performances for semitransparent, fully solution-processed OPV modules. The individual developments all meet the requirements for industrial R2R printing (green solvents, processing in air, annealing ≤140 °C, etc.), which ensures that both the optimized layer stack and the fabrication process are fully scalable and easily transferable to large-scale production.
CRIS-Team Scopus Importer:2023-09-22
Keywords: ambient air; organic photovoltaics (OPVs); roll-to-roll (R2R)-compatibility; semitransparent modules; solution-processing; upscaling

Fully Printed Infrared Photodetectors from PbS Nanocrystals with Perovskite Ligands - Yousefiamin, Amirabbas; Killilea, Niall Andrew; Sytnyk, Mykhailo; Maisch, Philipp; Tam, Kwok-Kan; Egelhaaf, Hans-Joachim; Langner, Stefan; Stubhan, Tobias; Brabec, Christoph; Rejek, Tobias; Halik, Marcus; Poulsen, Katharina; et al. (ACS nano, 2019)
Colloidal nanocrystals from PbS are successfully applied in highly sensitive infrared photodetectors with various device architectures. Here, we demonstrate all-printed devices with high detectivity (similar to 10(12) cm Hz(1/2) /W) and a cut-off frequency of >3 kHz. The low material consumption (<0.3 mg per detector) and short processing time (14 s per detector) enabled by the automated printing promises extremely low device costs. To enable all-printed devices, an ink formulation was developed based on nanocrystals stabilized by perovskite-like methylammonium iodobismuthate ligands, which are dispersed in a ternary solvent. Fully inkjet printed devices based on this solvent were achieved with printed silver electrodes and a ZnO interlayer. Considerable improvements were obtained by the addition of small amounts of the polymer poly(vinylpyrrolidone) to the ink. The polymer improved the colloidal stability of the ink and its film-formation properties and thus enabled the scalable printing of single detectors and detector arrays. While photoconductors were shown here, the developed ink will certainly find application in a series of further electronic devices based on nanocrystals from a broad range of materials.
Keywords: colloidal nanocrystals; infrared detectors; inkjet printing; PbS; solution processing

Fully printed organic solar modules with bottom and top silver nanowire electrodes - Tam, Kai Cheong; Kubis, Peter; Maisch, Philipp; Brabec, Christoph; Egelhaaf, Hans-Joachim (Progress in Photovoltaics, 2021)
One of the advantages of organic photovoltaics (OPV) over other contemporary technologies is its relative ease of processing. There are, however, very few works that have realized fully printed devices, including the bottom electrode, let alone with a scalable process in a reasonable device size (>1 cm(2)). In this work, design steps and optimization processes towards fully printed OPV modules with scalable processes are demonstrated for the first time. An overview on issues related to upscaling with printed electrodes is first provided. The various issues are then addressed by a rational design process supported by measurements and calculations. Finally, a set of fully printed OPV modules are fabricated using these optimized parameters that have over 3.5-cm(2) active area with 5% efficiency. For the first time, this work has also demonstrated the process compatibility of fully printed device structures with non-fullerene acceptor systems, which enables more design opportunities for the current generation of high-performance OPV materials.
CRIS-Team WoS Importer:2021-12-31

Fully printed organic tandem solar cells using solution-processed silver nanowires and opaque silver as charge collecting electrodes - Guo, Fei; Li, Ning; Radmilovic, Vuk V.; Radmilovic, Velimir R.; Turbiez, Mathieu; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (Energy and Environmental Science, 2015)
We report in this work efficient, fully printed tandem organic solar cells (OSCs) using solution-processed silver as the reflective bottom electrode and silver nanowires as the transparent top electrode. Employing two different band-gap photoactive materials with complementary absorption, the tandem OSCs are fully printed under ambient conditions without the use of indium tin oxide and vacuum-based deposition. The fully printed tandem devices achieve power conversion efficiencies of 5.81% (on glass) and 4.85% (on flexible substrate) without open circuit voltage (Voc) losses. These results represent an important progress towards the realization of low-cost tandem OSCs by demonstrating the possibility of printing efficient organic tandem devices under ambient conditions onto production relevant carrier substrates.

Fully solution-processed, light-weight, and ultraflexible organic solar cells - Güler, Ezgi; Distler, Andreas; Basu, Robin; Brabec, Christoph; Egelhaaf, Hans-Joachim (Flexible and Printed Electronics, 2022)
Organic photovoltaic (OPV) devices have the potential to be superior to other PV technologies for the use in applications that require very high flexibility or maximum specific power (power-per-weight ratio), such as textile integration, wearable electronics, or outer space applications. However, OPV devices also require encapsulation by barrier films to reduce the degradation driven by extrinsic factors, which in turn limits their flexibility and leads to lower specific power values. In this work, fully solution-processed (including both electrodes) semitransparent organic solar cells (OSCs) with performance comparable with conventional indium tin oxide-based devices are processed directly onto different barrier films of varying thicknesses. Direct cell fabrication onto barrier films leads to the elimination of the additional polyethylene terephthalate substrate and one of the two adhesive layers in the final stack of an encapsulated OPV device by replacing the industrial state-of-the-art sandwich encapsulation with a top-only encapsulation process, which yields significantly thinner and lighter 'product-relevant' PV devices. In addition to the increase of the specific power to 0.38 W g(-1), which is more than four times higher than sandwich-encapsulated devices, these novel OSCs exhibit better flexibility and survive 5000 bending cycles with 4.5 mm bending radius. Moreover, the devices show comparable stability as conventionally encapsulated devices under constant illumination (1 sun) in ambient air for 1000 h. Finally, degradation under damp heat conditions (65 degrees C, 85% rh) was investigated and found to be determined by a combination of different factors, namely (UV) light soaking, intrinsic barrier properties, and potential damaging of the barriers during (laser) processing.
CRIS-Team WoS Importer:2022-05-13
Keywords: solution-processability; specific power; organic photovoltaics; silver nanowire; transparent electrodes; flexible electronics; barrier films

Fully Solution Processed Pure α-Phase Formamidinium Lead Iodide Perovskite Solar Cells for Scalable Production in Ambient Condition - Yang, Fu; Dong, Lirong; Jang, DongJu; Tam, Kai Cheong; Zhang, Kaicheng; Li, Ning; Guo, Fei; Li, Cong; Arrive, Charline; Bertrand, Mélanie; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Energy Materials, 2020)
Manufacturing commercially viable perovskite solar cells still requires appropriate low-temperature and scalable deposition processes to be developed. While α-phase FAPbI3 has higher thermal stability and broader absorption than MAPbI3, there still is no report of a pure α-phase FAPbI3 perovskite film obtained by a scalable printing method. Moreover, spontaneous conversion of the α-phase to non-perovskite δ-phase under ambient conditions poses a serious challenge for practical applications. Herein, a scalable and fully solution based printing method for the fabrication of pure α-phase FAPbI3 perovskite solar cells is reported. Through adding N-methyl pyrrolidone and methylammonium chloride to the dimethylformamide based precursor solution to control the crystallization, and vacuum or air-flow assisted film drying, pure α-FAPbI3 phase is obtained by doctor blading. The resulting α-FAPbI3 film is highly stable, with no δ-FAPbI3 phase being formed even after keeping it in an ambient atmosphere over a period of 200 days without encapsulation. In addition, a fully solution processed PSC with a PCE of 16.1% is processed by the vacuum assisted method, and 17.8% by the air-flow assisted method. Replacing silver with a printed carbon electrode provides a stable PCE up to 15% for the vacuum assisted and 16.4% for the air-flow assisted method, which is the highest performance of FAPbI3 solar cells to date. Compared with MAPbI3, the fully printed FAPbI3 perovskite devices exhibit a remarkable thermal stability in humid atmospheres which makes them a promising candidate for scalable production and commercialization.
CRIS-Team Scopus Importer:2020-10-02
Keywords: carbon electrodes; doctor blades; fully printed devices; long-term stability; α-FAPbI

Fully Solution-Processed Small Molecule Semitransparent Solar Cells: Optimization of Transparent Cathode Architecture and Four Absorbing Layers - Min, Jie; Bronnbauer, Carina; Zhang, Zhi-Guo; Cui, Chaohua; Luponosov, Yuriy N.; Ata, Ibrahim; Schweizer, Peter; Przybilla, Thomas; Guo, Fei; Ameri, Tayebeh; Forberich, Karen; Spiecker, Erdmann; et al. (Advanced Functional Materials, 2016)
Semitransparent solar cells (SSCs) can open photovoltaic applications in many commercial areas, such as power-generating windows and building integrated photovoltaics. This study successfully demonstrates solution-processed small molecule SSCs with a conventional configuration for the presently tested material systems, namely BDTT-S-TR:PCBM, N(Ph-2T-DCN-Et):PCBM, SMPV1:PCBM, and UU07:PCBM. The top transparent cathode coated through solution processes employs a highly transparent silver nanowire as electrode together with a combination interface bilayer of zinc oxide nanoparticles (ZnO) and a perylene diimide derivative (PDINO). This ZnO/PDINO bilayer not only serves as an effective cathode buffer layer but also acts as a protective film on top of the active layer. With this integrated contribution, this study achieves a power conversion efficiency (PCE) of 3.62% for fully solution-processed SSCs based on BDTT-S-TR system. Furthermore, the other three systems with various colors exhibited the PCEs close to 3% as expected from simulations, demonstrate the practicality and versatility of this printed semitransparent device architecture for small molecule systems. This work amplifies the potential of small molecule solar cells for window integration.
Keywords: building integrated photovoltaics; interface bilayer; power conversion efficiency; semitransparent solar cells; small molecule

Fully Solution-Processing Route toward Highly Transparent Polymer Solar Cells - Guo, Fei; Kubis, Peter; Stubhan, Tobias; Li, Ning; Baran, Derya; Przybilla, Thomas; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (ACS Applied Materials and Interfaces, 2014)
We report highly transparent polymer solar cells using metallic silver nanowires (AgNWs) as both the electron- and hole-collecting electrodes. The entire stack of the devices is processed from solution using a doctor blading technique. A thin layer of zinc oxide nanoparticles is introduced between photoactive layer and top AgNW electrode which plays decisive roles in device functionality: it serves as a mechanical foundation which allows the solution-deposition of top AgNWs, and more importantly it facilitates charge carriers extraction due to the better energy level alignment and the formation of ohmic contacts between the active layer/ZnO and ZnO/AgNWs. The resulting semitransparent polymer:fullerene solar cells showed a power conversion efficiency of 2.9%, which is 72% of the efficiency of an opaque reference device. Moreover, an average transmittance of 41% in the wavelength range of 400-800 nm is achieved, which is of particular interest for applications in transparent architectures.
Keywords: semitransparent polymer solar cells; fully solution processing; OPV; ITO-free

Gaining further insight into the effects of thermal annealing and solvent vapor annealing on time morphological development and degradation in small molecule solar cells - Min, Jie; Güldal, Nusret Sena; Guo, Jie; Fang, Chao; Jiao, Xuechen; Hu, Huawei; Heumüller, Thomas; Ade, Harald; Brabec, Christoph (Journal of Materials Chemistry A, 2017)
Numerous articles on thermal annealing (TA) and solvent vapor annealing (SVA) treatments have shown that both strategies effectively improve bulk morphology, reduce carrier recombination and thus improve photovoltaic performance of bulk heterojunction (BHJ) organic solar cells (OSCs). In previous work, we found that both TA and SVA treated devices based on a blend composed of a 3-ethyl-2-thioxothiazolidin-4-one containing molecule as donor (named DRCN5T) and [6,6]-phenyl-C71-butyric acid methyl ester (PC70BM) as acceptor show the similar photovoltaic performance, but their bulk microstructures are difference. Here employing in situ photoluminescence (PL) setup and X-ray scattering technologies, we found that the early stages of SVA remarkably affect the surface of film, and in contrast TA affects the whole bulk. Meanwhile, a plurality of experimental results all further confirm the different thermodynamics and kinetics of morphology evolution processed either by TA treatment or SVA treatment. Importantly, it was found that the SVA-treated film showed the increased photo-degradation in devices as compared to the TA-treated layer, resulting from obvious bulk morphology changes under illumination over 500 hours. The aim is to provide comprehensive insight into the influence of TA and SVA on time morphological evolution and degradation in OSCs. © 2017 The Royal Society of Chemistry.
Keywords: Annealing Butyric acid Heterojunctions Molecules Morphology Organic solar cells Solar power generation Thermodynamics X ray scattering

(Gd,Lu)AlO3:Dy3+ and (Gd,Lu)(3)Al5O12:Dy3+ as high-temperature thermographic phosphors - Hertle, Ellen Elisabeth; Chepyga, Liudmyla; Osvet, Andres; Brabec, Christoph; Batentschuk, Miroslaw; Will, Stefan; Zigan, Lars (Measurement Science & Technology, 2019)
A comparative investigation of the thermographic properties of Dy3+-doped gadolinium aluminum perovskite GdAlO3 (GAP) and gadolinium aluminum garnet Gd3Al5O12 (GAG) was performed with special regard to the suitability of these materials for surface thermometry in harsh measurement environments. The phosphors were synthesized by conventional high-temperature solid-state method using lithium fluoride (LiF) as a flux. The effects of substituting Gd3+ by Lu3+ ions on the stability of the garnet structure and the luminescence properties of the phosphors were investigated. An efficient energy transfer from Gd3+ to Dy3+ resulted in significantly stronger Dy3+ emission obtained through Gd3+ excitation at 275 nm compared to direct excitation of Dy3+ at 352 nm. The luminescence intensity of GAP:Dy3+ with Lu3+ substitution was three times higher at room temperature compared to GAP:Dy3+. Due to this intensity enhancement, the range of temperature measurements by the intensity ratio and decay time methods was extended from 900 K to 1100 K. The luminescence intensity of (Gd,Lu)AG:Dy3+ was doubled at room temperature compared to (Gd,Lu)AP:Dy3+ and the limit for reliable temperature measurements by the above mentioned methods was increased up to 1600 K.
CRIS-Team WoS Importer:2019-02-21
Keywords: phosphor thermometry; GAP; GAG; laser diagnostics; high temperature

Georeferencing of photovoltaic modules from aerial infrared videos using structure-from-motion - Bommes, Lukas; Buerhop-Lutz, Claudia; Pickel, Tobias; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (Progress in Photovoltaics, 2022)
To identify abnormal photovoltaic (PV) modules in large-scale PV plants economically, drone-mounted infrared (IR) cameras and automated video processing algorithms are frequently used. While most related works focus on the detection of abnormal modules, little has been done to automatically localize those modules within the plant. In this work, we use incremental structure-from-motion to automatically obtain geocoordinates of all PV modules in a plant based on visual cues and the measured GPS trajectory of the drone. In addition, we extract multiple IR images of each PV module. Using our method, we successfully map 99.3% of the 35,084 modules in four large-scale and one rooftop plant and extract over 2.2 million module images. As compared to our previous work, extraction misses 18 times less modules (one in 140 modules as compared to one in eight). Furthermore, two or three plant rows can be processed simultaneously, increasing module throughput and reducing flight duration by a factor of 2.1 and 3.7, respectively. Comparison with an accurate orthophoto of one of the large-scale plants yields a root mean square error of the estimated module geocoordinates of 5.87 m and a relative error within each plant row of 0.22 m to 0.82 m. Finally, we use the module geocoordinates and extracted IR images to visualize distributions of module temperatures and anomaly predictions of a deep learning classifier on a map. While the temperature distribution helps to identify disconnected strings, we also find that its detection accuracy for module anomalies reaches, or even exceeds, that of a deep learning classifier for seven out of ten common anomaly types. The software is published at https://github.com/LukasBommes/PV-Hawk.
CRIS-Team Scopus Importer:2022-04-29
Keywords: deep learning; defect detection; drone; georeferencing; mapping; PV plant inspection; structure-from-motion; thermography

Giant Rashba Splitting in CH3NH3PbBr3 Organic-Inorganic Perovskite - Niesner, Daniel; Wilhelm, Max; Levchuk, Ievgen; Osvet, Andres; Shrestha, Shreetu; Batentschuk, Miroslaw; Brabec, Christoph; Fauster, Thomas (Physical Review Letters, 2016)
As they combine decent mobilities with extremely long carrier lifetimes, organic-inorganic perovskites open a whole new field in optoelectronics. Measurements of their underlying electronic structure, however, are still lacking. Using angle-resolved photoelectron spectroscopy, we measure the valence band dispersion of single-crystal CH3NH3PbBr3. The dispersion of the highest energy band is extracted applying a modified leading edge method, which accounts for the particular density of states of organic-inorganic perovskites. The surface Brillouin zone is consistent with bulk-terminated surfaces both in the low-temperature orthorhombic and the high-temperature cubic phase. In the low-temperature phase, we find a ring-shaped valence band maximum with a radius of 0.043 Å-1, centered around a 0.16 eV deep local minimum in the dispersion of the valence band at the high-symmetry point. Intense circular dichroism is observed. This dispersion is the result of strong spin-orbit coupling. Spin-orbit coupling is also present in the room-temperature phase. The coupling strength is one of the largest ones reported so far.

Graded 2D/3D Perovskite Heterostructure for Efficient and Operationally Stable MA-Free Perovskite Solar Cells - Yao, Qin; Xue, Qifan; Li, Zhenchao; Zhang, Kaicheng; Zhang, Teng; Li, Ning; Yang, Shihe; Brabec, Christoph; Yip, Hin-Lap; Cao, Yong (Advanced Materials, 2020)
Almost all highly efficient perovskite solar cells (PVSCs) with power conversion efficiencies (PCEs) of greater than 22% currently contain the thermally unstable methylammonium (MA) molecule. MA-free perovskites are an intrinsically more stable optoelectronic material for use in solar cells but compromise the performance of PVSCs with relatively large energy loss. Here, the open-circuit voltage (V-oc) deficit is circumvented by the incorporation of beta-guanidinopropionic acid (beta-GUA) molecules into an MA-free bulk perovskite, which facilitates the formation of quasi-2D structure with face-on orientation. The 2D/3D hybrid perovskites embed at the grain boundaries of the 3D bulk perovskites and are distributed through half the thickness of the film, which effectively passivates defects and minimizes energy loss of the PVSCs through reduced charge recombination rates and enhanced charge extraction efficiencies. A PCE of 22.2% (certified efficiency of 21.5%) is achieved and the operational stability of the MA-free PVSCs is improved.
CRIS-Team WoS Importer:2020-06-05

Grain structure of thin-film silicon by zone melting recrystallization on SiC base layer - Kunz, T.; Hessmann, M. T.; Auer, R.; Bochmann, A.; Christiansen, S.; Brabec, Christoph (Journal of Crystal Growth, 2012)
The grain structure of thin-film silicon layers obtained by chemical vapor deposition and zone melting recrystallization (ZMR) on SiC barrier layers, as developed for thin-film solar cells, have been investigated by electron backscatter diffraction (EBSD). The occurrence of subgrain boundaries was checked by defect etching. Twin boundaries form 1 to 100 μm wide stripes, which are nearly parallel to the scan direction of ZMR. We find that stripe structure and the dominant grain orientations differ significantly from previously published ZMR layers grown on SiO surface. In a comprehensive model it is shown how the twinning structure and the dominant grain orientation can be related to the growth kinetics. The electronic activity of the defects was measured by electron beam induced current (EBiC). Contrary to other defects, the twin boundaries show no enhanced recombination. Therefore the found growth regime has potential advantages with respect of electronic properties of the layers. © 2012 Elsevier B.V. All rights reserved.
Keywords: A1. Defects; A1. Electron backscattering diffraction; A1. Twin boundaries; A3. Zone melting recrystallization; B1. Solar cells; B2. Semiconducting silicon

Graphene Oxide Thin Films: Synthesis and Optical Characterization - Prías Barragán, J. J.; Gross, K.; Darío Perea, José; Killilea, Niall Andrew; Heiß, Wolfgang; Brabec, Christoph; Calderón, H. Ariza; Prieto, Pedro (ChemistrySelect, 2020)
The oxidized derivative of graphene named Graphene oxide (GO) are attractive materials as optoelectronic devices due to their optical response in the mid-infrared wavelength spectral range; however, very large-scaled synthesis methods and optical characterization are required. Here, GO thin films are fabricated on quartz by implementing simple two-step pyrolysis processes by using renewable bamboo as source material. The effect of carbonization temperature (TCA) on the compositional, vibrational, and optoelectronic properties of the system are investigated. It was found that as TCA increases, graphite conversion rises, oxygen coverage reduces from 17 % to 4 %, and the band-gap energy monotonically decreases from 0.30 to 0.11 eV. Theoretical predictions of the energy band-gap variations with the oxide coverage obtained via density functional theory (DFT) computational simulations agree well with the experimental results, providing evidence of oxygen-mediated charge-transport scattering. Interestingly, in the optical response, increased TCA results in a blue-shift of the absorption and the absorbance spectrum can be correlated with the large size distribution of the graphitic nano-crystals of the samples. These results suggest that graphene oxide-bamboo pyroligneous acid (GO) thin films exhibit optoelectronic response useful in developing photodetectors and emitter devices in the mid-infrared (MIR) spectral range.
CRIS-Team Scopus Importer:2020-10-23
Keywords: band-gap energy; COSMO-RS; DFT computational simulations; graphene oxide; HR-TEM images; oxygen coverage; Photoluminescence; UV-Vis

"Green" synthesis of highly luminescent lead-free Cs2AgxNa1-xBiyIn1-yCl6 perovskites - Stroyuk, Oleksandr; Raievska, Oleksandra; Barabash, Anastasiia; Batentschuk, Miroslaw; Osvet, Andres; Fiedler, Saskia; Resch-Genger, Ute; Hauch, Jens; Brabec, Christoph (Journal of Materials Chemistry C, 2022)
A new "green" and mild synthesis of highly stable microcrystalline Cs2AgxNa1-xBiyIn1-yCl6 (CANBIC) perovskites under ambient conditions was developed that is scalable to the multi-gram production. Under UV illumination, the CANBIC perovskites emit intense broadband photoluminescence (PL) with a quantum yield (QY) of 92% observed for x = 0.35 and y = 0.01-0.02. The combination of strong UV absorbance and broadband visible emission, high PL QY, and long PL lifetimes of up to 1.4 mu s, along with an outstanding stability makes these CANBICs a promising material class for many optical applications.
CRIS-Team WoS Importer:2022-06-24

Guest editorial: Special section on organic photovoltaics - Brabec, Christoph; Brabec, Christoph J.; Lane, Paul; Kafafi, Zakya H. (Journal of Photonics for Energy, 2012)
Organic photovoltaics (OPVs) have a long history, stretching back three decades into the 1980s, when first studies were conducted on the photogeneration of charge carriers at interfaces in organic solids. Compared to inorganic photovoltaics, OPVs offer many advantages, such as low cost, high throughput production, flexible devices, lightweight products, as well as custom-designed colors. In the last decade, research activities have intensified to increase the power conversion efficiencies and lifetimes of OPVs and make them more competitive with their inorganic counterparts. Scientists and engineers worldwide have worked hard to exploit the inherent advantages of organic materials. A series of breakthroughs in materials, processing, and characterization have been reported in the last couple of years, leading to dramatic gains in the performance of organic solar cells. The most recent certified power conversion efficiencies meet or exceed the 10% level for a solution-processable single-junction device, positioning OPVs as the next-generation solar cells. Companies such as Merck, BASF, Sumitomo, and Plextronics have started to commercialize organic semiconducting materials, while companies such as Konarka Technologies, Heliatek, Solarmer, and Mitsubishi have begun commercialization of organic solar modules. Further development is necessary in order to achieve OPVs with higher efficiencies and better lifetimes. There are demands for stable and low-band-gap semiconductors with excellent charge-carrier-transport properties; concepts to control the microstructure in bulk heterojunction composites are essential; the development of efficient and environmentally stable interface materials has to take place; and, finally, strategies for a cost-efficient and long-time stable packaging processes need to be developed. In addition, further fundamental understanding of the photophysical processes, including the different interfaces in organic solar cells, is essential to minimize energetic losses and combat device degradation. For the final product release, light propagation and light management need to become integrated in organic solar modules. In this special section of the Journal of Photonics for Energy, papers that address the above issues and challenges are presented. These papers are based partially on talks and posters given at the conference on Organic Photovoltaics XII at the SPIE Optics + Photonics meeting held in San Diego in August 2011. We believe that the readers will find the results of the studies discussed in these manuscripts interesting, educational, and stimulating, and we welcome any constructive feedback with regard to this special section.

Guideline for Efficiency Enhancement in Semi-Transparent Thin-Film Organic Photovoltaics with Dielectric Mirrors - Bronnbauer, Carina; Gasparini, Nicola; Brabec, Christoph; Forberich, Karen (Advanced Optical Materials, 2016)
Semi-transparent organic solar cells (ST-OSCs) show a unique potential to be integrated in windows due to their outstanding characteristics such as high transparency and color-adjustability. In order to achieve both, high transparency and high efficiency, the use of dielectric mirrors is an excellent concept. However, such a mirror will not only improve the photocurrent generated by a solar cell but also cause losses in transparency. In this work, a theoretical model is developed that predicts the effect of the dielectric mirror on the balance between photocurrent enhancement and transparency loss depending on the spectral shape of the ST-OSC absorption. Experimental investigations with three fully printed ST-OSCs showing different absorption characteristics underline the validity of these studies. It is concluded that ST-OSCs with broad absorption spectra ranging from the short wavelength region over the visible to at least 950 nm are most suitable for the implementation of a dielectric mirror. A narrower absorption spectrum or a shift of the spectrum toward longer wavelengths makes an increase in photoactive layer thickness more beneficial than the attachment of a dielectric mirror. Moreover, the dielectric mirror approach is an excellent strategy to obtain high photocurrents for materials which cannot be processed at high active layer thicknesses.
Keywords: bragg mirrors; dielectric mirrors; organic photovoltaics; printing; semi-transparent

Guidelines for Closing the Efficiency Gap between Hero Solar Cells and Roll-To-Roll Printed Modules - Lucera, Luca; Kubis, Peter; Fecher, Frank W.; Bronnbauer, Carina; Turbiez, Mathieu; Forberich, Karen; Ameri, Tayebeh; Egelhaaf, Hans-Joachim; Brabec, Christoph (Energy Technology, 2015)
One of the biggest challenges for the commercialization of polymer-based and other printed photovoltaic (PV) technologies is to establish reliable up-scaling processes that minimize the efficiency losses occurring during the transition from record laboratory cells to roll-to-roll (R2R) printed PV modules. This article reviews the latest advances in reducing the efficiency gap between record solar cells and large-area organic PV modules. The major loss sources are identified for the most popular cell architectures and categorized into optical, electrical, and processing-related contributions. Their relative shares in the overall efficiency drop are quantified through optical and electrical simulations. Further potential sources of efficiency loss, such as the replacement of halogenated by green solvents for active layer processing, are also addressed. Finally, the effect of reduced efficiency gaps on the production costs of R2R printed modules is discussed, demonstrating that values as low as €0.5Wp -1 (the nominal power of a solar module/cell) can be achieved. © 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Photovoltaics; Polymers; Printing; Roll-to-roll processing; Solar cells

Guidelines for Material Design in Semitransparent Organic Solar Cells - Forberich, Karen; Troisi, Alessandro; Liu, Chao; Wagner, Michael; Brabec, Christoph J.; Egelhaaf, Hans Joachim (Advanced Functional Materials, 2024)
Organic solar cells (OSCs) are uniquely suited for semitransparent applications due to their adjustable absorption spectrum. However, most high-performance semitransparent cells reported to date are based on materials that have shown high power conversion efficiency for opaque devices. A model is therefore presented to assess the optimum efficiency and transparency for a specific donor and acceptor bandgap. The absorption characteristics of both donor and acceptor are modeled with spectral data of typical absorber materials from the literature which are adjusted to achieve the desired bandgap value. The results show three distinct regions of high light utilization efficiency (LUE) if the photopic curve is employed as a weighting function (corresponding to window applications), and a broad maximum for the plant action spectrum as a weighting function (corresponding to greenhouse applications). When comparing these findings to reported experimental values, it is evident that the bandgaps of the materials used for the experimental studies do not correspond to the maxima identified by the simulation model. The analysis of the energy levels of molecules recorded in the literature confirms that all bandgaps and therefore all LUE maxima are chemically feasible so that the performance of semitransparent OSCs can be further improved by designing materials with optimized absorption spectra.
CRIS-Team Scopus Importer:2024-03-22
Keywords: absorption spectrum; modeling; organic solar cells; Scharber plot; semitransparent

High-efficiency and air-stable P3HT-based polymer solar cells with a new non-fullerene acceptor - Holliday, Sarah; Ashraf, Raja Shahid; Wadsworth, Andrew; Baran, Derya; Yousaf, Syeda Amber; Nielsen, Christian B.; Tan, Ching-Hong; Dimitrov, Stoichko D.; Shang, Zhengrong; Gasparini, Nicola; Alamoudi, Maha; Laquai, Frederic; et al. (Nature Communications, 2016)
Solution-processed organic photovoltaics (OPV) offer the attractive prospect of low-cost, light-weight and environmentally benign solar energy production. The highest efficiency OPV at present use low-bandgap donor polymers, many of which suffer from problems with stability and synthetic scalability. They also rely on fullerene-based acceptors, which themselves have issues with cost, stability and limited spectral absorption. Here we present a new non-fullerene acceptor that has been specifically designed to give improved performance alongside the wide bandgap donor poly(3-hexylthiophene), a polymer with significantly better prospects for commercial OPV due to its relative scalability and stability. Thanks to the well-matched optoelectronic and morphological properties of these materials, efficiencies of 6.4% are achieved which is the highest reported for fullerene-free P3HT devices. In addition, dramatically improved air stability is demonstrated relative to other high-efficiency OPV, showing the excellent potential of this new material combination for future technological applications.

High efficiency and stability small molecule solar cells developed by bulk microstructure fine-tuning - Min, Jie; Jiao, Xuechen; Sgobba, Vito; Kan, Bin; Heumüller, Thomas; Rechberger, Stefanie; Spiecker, Erdmann; Guldi, Dirk Michael; Wan, Xiangjian; Chen, Yongsheng; Ade, Harald; Brabec, Christoph (Nano Energy, 2016)
Morphological control over the bulk heterojunction (BHJ) microstructure of a high-efficiency small molecule photovoltaic system composed of a quinquethiophene based molecule (DRCN5T) as electron donor and [6,6]-phenyl-C71-butyric acid methyl ester (PC70BM) as electron acceptor is demonstrated using three different post-processing strategies, including thermal annealing (TA), solvent vapor annealing (SVA), and two-step annealing (TA-SVA) treatments. We systematically analyze the processing condition-microstructure-device property relationships, explore the corresponding morphology evolution and their effects on carrier transport and recombination dynamics in BI-Js as well as understand the nature of phase-separation process resulting in light-induced degradation mechanisms. Within the investigated results, the causative relations between annealing sequence, photovoltaic parameters, morphology evolution and charge carrier dynamics are for the first time delineated. In addition, the observed trade-offs in device efficiency and stability with respect to the well-defined morphologies are highlighted. The in-depth picture of the bulk microstructure formation and its kinetic evolution as a function of the specific post-processing approaches is a valuable asset for the design of new photovoltaic materials and thin film nanoscale architectures that are more efficient and better aid future commercialization efforts. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Blend microstructure; Morphological control; Annealing sequence; Phase-separation; Charge carrier dynamics; Degradation mechanisms

High fill factor polymer solar cells comprising a transparent, low temperature solution processed doped metal oxide/metal nanowire composite electrode - Stubhan, Tobias; Krantz, Johannes; Li, Ning; Guo, Fei; Litzov, Ivan; Steidl, Matthias; Richter, Moses; Matt, Gebhard; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2012)
In this paper we report on the replacement for the commonly used ITO electrode material by a low temperature solution processed silver nanowire/(doped) metal oxide composite. Devices employing silver nanowires (AgNWs)/buffer layer electrodes with a photoactive layer of poly(3- hexylthiophene) (P3HT) and [6,6]-phenyl-C butyric acid methyl ester (PCBM) are showing a comparable performance to the ITO reference cell with fill factors (FF) of over 62% and a power conversion efficiency of ∼2.7%. Zinc oxide (ZnO) and highly conductive Al doped ZnO (AZO) are used as buffer layer. AgNW devices without a buffer layer have a high open circuit voltage (V ) but the FF and the short circuit current density (j ) are substantially lower. Overall it is demonstrated that AgNWs and the low temperature solution process of the buffer layer are an attractive device concept towards an indium free organic solar cell. © 2012 Elsevier B.V. All rights reserved.
Keywords: Aluminum-doped zinc oxide; Metal nanowires; Organic solar cells; Solution processed; Transparent electrode; Zinc oxide

High fill factor polymer solar cells incorporating a low temperature solution processed WO3 hole extraction layer - Stubhan, Tobias; Li, Ning; Luechinger, Norman A.; Halim, Samuel C.; Matt, Gebhard; Brabec, Christoph (Advanced Energy Materials, 2012)
We demonstrate solution-processed tungsten trioxide (WO) incorporated as hole extraction layer (HEL) in polymer solar cells (PSCs) with active layers comprising either poly(3-hexylthiophene) (P3HT) or poly[(4,4′-bis(2-ethylhexyl)dithieno[3,2-b:2′,3′-d]silole)-2, 6-diyl-alt-(4,7-bis(2-thienyl)-2,1,3-benzothiadiazole)-5,50-diyl] (Si-PCPDTBT) mixed with a fullerene derivative. The WO layers are deposited from an alcohol-based, surfactant-free nanoparticle solution. A short, low-temperature (80 °C) annealing is sufficient to result in fully functional films without the need for an oxygen-plasma treatment. This allows the application of the WO buffer layer in normal as well as inverted architecture solar cells. Normal architecture devices based on WO HELs show comparable performance to the PEDOTPSS reference devices with slightly better fill factors and open circuit voltages. Very high shunt resistances (over 1 MO cm) and excellent diode rectification underline the charge selectivity of the solution-processed WO layers. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA.
Keywords: 1; 3-benzothiadiazole; Active Layer; Fill factor; Fullerene derivative; Functional films; High fills; Low temperature solutions; Low temperatures; Nanoparticle solutions; Oxygen-plasma treatment; PEDOT-PSS; Poly-3-hexylthiophene; Polymer Solar Cells; Reference devices; Shunt resistances; Solution-processed; Surfactant-free; Tungsten trioxide Engineering controlled terms: Open circuit voltage; Plasma applications; Solar cells; Tungsten Engineering main heading: Temperature

Highly Efficient Bilayer Polymer Solar Cells Using the Method of Sequential Processing with Additive Bilayer - Lee, Jihoon; Jang, Soyeong; Tamilavan, Vellaiappillai; Li, Ning; Wang, Rong; Lüer, Larry; Lee, Dalyong; Yoon, Jung Won; Lee, Bo Ram; Choi, Hyosung; Park, Sung Heum; Brabec, Christoph (Solar RRL, 2023)
Despite the research value of bilayer organic solar cells (OSCs) for commercialization in the future, the bulk-heterojunction (BHJ) structure dominates the fabrication of OSCs because of its higher power conversion efficiency (PCE) compared with bilayer OSCs. Herein, four different types of bilayer OSC structures using sequential processing (SP) with an additive bilayer are investigated and considerably enhanced device performance is demonstrated. The performance of our bilayer devices based on a wide bandgap (PBDT-DPPD-TPD; P2) polymer and [6,6]-phenyl C61-butyric acid methyl ester (PCBM) is improved from 2.88% for the conventional bilayer structure to 6.62%. More importantly, remarkable PCEs of 8.78% and 15.16% for PTB7-Th/PCBM and PM6/Y6 bilayer OSCs, respectively, using the SP with additive bilayer method are achieved and the inhomogeneity issues of the BHJ structure are successfully addressed. Herein, a novel way to overcome the low efficiency of bilayer OSCs is suggested and an unprecedented possibility of renovation, breaking the standardization of OSC research, is presented.
CRIS-Team Scopus Importer:2023-01-20
Keywords: bilayer structures; high efficiency; organic solar modules; polymer solar cells; processing additives

Highly efficient, large area, roll coated flexible and rigid OPV modules with geometric fill factors up to 98.5% processed with commercially available materials - Lucera, L.; Machui, F.; Kubis, P.; Schmidt, H. D.; Adams, J.; Strohm, S.; Ahmad, T.; Forberich, Karen; Egelhaaf, H. -J.; Brabec, Christoph (Energy and Environmental Science, 2016)
Highly efficient, large area OPV modules achieving full area efficiencies of up to 93% of the reference small area cells are reported. The way to a no-loss up-scaling process is highlighted: photoelectrical conversion efficiencies of 5.3% are achieved on rigid modules and of 4.2% on flexible, roll coated ones, employing a commercially available photoactive material. Exceptionally high geometric fill factors (98.5%), achieved via structuring by ultrashort laser pulses, with interconnection widths below 100 μm are demonstrated.
Keywords: Engineering controlled terms: Efficiency; Ultrashort pulses Area efficiency; Fill factor; Photoactive materials; Small area; Upscaling Engineering main heading: Coated materials

Highly efficient, large area, roll coated flexible and rigid solar modules: Design rules and realization - Lucera, Luca; Machui, Florian; Kubis, Peter; Egelhaaf, Hans Joachim; Brabec, Christoph (43rd IEEE Photovoltaic Specialists Conference, PVSC 2016, Category numberCFP16PSC-ART; Code 124913, 2016)
Large area, roll-to-roll printed solar modules are presented in literature with power conversion efficiencies (PCE) well below hero solar cells produced in the lab. Here we show how to design a proper layout to minimize the electrical losses and how to evaluate optical losses induced by the substitution of the sputtered/evaporated electrodes with solution processable ones. Highly efficient, large area, roll-produced solar modules are then shown, achieving PCEs above 4.2% on total area on flexible and of 5.3% on glass substrates. A record-breaking geometric fill factor of 98.5% is demonstrated, thanks to ultra-fast laser structurin
Keywords: large area modules; no losses; organic photovoltaics; printed photovoltaics; Simulation

Highly efficient, large area, roll coated flexible and rigid solar modules: Design rules and realization - Lucera, Luca; Machui, Florian; Kubis, Peter; Egelhaaf, Hans-J.; Brabec, Christoph (44th IEEE Photovoltaic Specialist Conference, PVSC 2017; Category numberCFP17PSC-ART; Code 136737, 2018)
Large area, roll-to-roll printed solar modules are presented in literature with power conversion efficiencies (PCE) well below hero solar cells produced in the lab. Here we show how to design a proper layout to minimize the electrical losses and how to evaluate optical losses induced by the substitution of the sputtered/evaporated electrodes with solution processable ones. Highly efficient, large area, roll-produced solar modules are then shown, achieving PCEs above 4.2% on total area on flexible and of 5.3% on glass substrates. A record-breaking geometric fill factor of 98.5% is demonstrated, thanks to ultra-fast laser structurin
Keywords: Large area modules; No losses; Organic photovoltaics; Printed photovoltaics; Simulation

Highly efficient organic tandem solar cells: A follow up review - Ameri, Tayebeh; Li, Ning; Brabec, Christoph (Energy and Environmental Science, 2013)
Multi-junction solar cell configurations, where two or further sub-cells with complementary absorption are stacked and connected in series or parallel, offer an exciting approach to tackle the single junction limitations of organic solar cells and further improve their power conversion efficiency. In this article we aim to follow up our previous work and review the most important and novel developments that have been recently reported on organic tandem solar cells. In addition, some brief theoretical considerations addressing the potential of single and tandem solar cells, the working principles of the intermediate layer, the importance and benefits of optical simulations and finally the intricacies of a precise performance measurement of bulk-heterojunction organic tandem solar cells based on complementary absorber materials are presented. © 2013 The Royal Society of Chemistry.
Keywords: Bulk heterojunction; Intermediate layers; Multi junction solar cells; Optical simulation; Organic solar cell; Performance measurements; Power conversion efficiencies; Tandem solar cells Engineering controlled terms: Heterojunctions Engineering main heading: Solar cells GEOBASE Subject Index: energy efficiency; optical method; performance assessment; solar power; solar radiation; theoretical study

Highly luminescent Ca3Sc2Si3O12:Ce3+ silicate garnet nano- and microparticles with 50-70% photoluminescence quantum yields as efficient phosphor converters for white LEDs - Levchuk, Ievgen; Schröppel, Felix; Römling, Lukas; Chepyga, Liudmyla; Osvet, Andres; Khaidukov, Nicholas; Zorenko, Yuriy; Van Deun, Rik; Brabec, Christoph; Batentschuk, Miroslaw (Advanced Materials - TechConnect Briefs 2017, 2017)
We present a novel synthesis method of Ca3Sc2Si3O12:Ce3+ nano- and microparticles with outstandingly bright photoluminescence. Nanoparticles were synthesized by the co-precipitation method, where a long-chain fatty acid salt was used as the precipitation agent for Ca, Sc and Ce water solutions in combination with SiO2 nanoparticles or TEOS as a silica source. Further calcination in reducing atmosphere results in brightly luminescent Ca3Sc2Si3O12:Ce3+ nanopowders with up to 50% photoluminescence quantum yield (PLQY). The modified conventional solid-state reaction was utilized for synthesizing microparticles. Pre-synthesis of metal and silicon oxide solid blends with subsequent high-temperature post-treatment enables to obtain Ca3Sc2Si3O12:Ce3+ microparticles with the record-high PLQY of about 70%. Additionally, both kinds of samples display significantly higher thermal stability of photoluminescence in comparison to a commercial YAG:Ce phosphor.
Keywords: Ca3Sc2Si3O12:Ce3+; Co-precipitation; Nanopowder; Phosphor converter; White LED

Highly Luminescent Transparent Cs2AgxNa1-xBiyIn1-yCl6 Perovskite Films Produced by Single-Source Vacuum Deposition - Stroyuk, Oleksandr; Raievska, Oleksandra; Sebastia-Luna, Paz; Huisman, Bas A.H.; Kupfer, Christian; Barabash, Anastasiia; Hauch, Jens; Bolink, Henk J.; Brabec, Christoph J. (ACS Materials Letters, 2023)
Thermal deposition of halide perovskites as a universal and scalable route to transparent thin films becomes highly challenging in the case of lead-free double perovskites, requiring the evaporation dynamics of multiple metal halide sources to be balanced or a single-phase precursor preliminary synthesized to achieve a reliable control over the composition and the phase of the final films. In the present Letter, the feasibility of the single-source vacuum deposition of microcrystalline Cs2AgxNa1-xBiyIn1-yCl6 double perovskites into corresponding transparent nanocrystalline films while preserving the bulk spectral and structural properties is shown. The perovskite films produced from the most emissive powders with x = 0.40 and y = 0.01 revealed a photoluminescence quantum yield of 85%, highlighting thermal evaporation as a promising approach to functional perovskite-based optical materials.
CRIS-Team Scopus Importer:2023-02-03

Highly Reflective and Low Resistive Top Electrode for Organic Solar Cells and Modules by Low Temperature Silver Nanoparticle Ink - Tam, Kai Cheong; Saito, Hirotoshi; Maisch, Philipp; Forberich, Karen; Feroze, Sarmad; Hisaeda, Yutaka; Brabec, Christoph J.; Egelhaaf, Hans-Joachim (Solar RRL, 2021)
One of the issues that have caused a wide performance gap between commercially available organic photovoltaic (OPV) modules and the hero cells in literature lies in the lack of printable and roll-to-roll process compatible high-performance top electrodes. This work takes an unorthodox approach to this issue by developing a printable silver nanoparticle (AgNP) film top electrode that can achieve a similar performance as evaporated ones (EvapAg). It illustrates the developmental process from ink formulation to the critical processing conditions that are tailored for OPV devices procedurally. The resultant cells and modules with AgNP electrodes have achieved almost the same power conversion efficiencies (≈90%) as those with evaporated silver electrodes, as demonstrated for multiple material systems, printing methods, as well as layouts. Under low light condition, AgNP cells perform even significantly better than EvapAg ones, due to their lower leakage currents. More importantly, this work has demonstrated that fully printed OPV modules can achieve similar performance as small scale OPV cells with evaporated electrodes when both the electrical and optical performance of their top electrodes are comparable. With the latest generation of materials, this approach offers an attractive alternative for manufacturing of highly efficient OPV modules at large scale.
CRIS-Team Scopus Importer:2021-12-17
Keywords: inkjet printing; organic photovoltaics; organic solar modules; printed photovoltaics; silver nanoparticles; upscaling

Highly Stable Lasing from Solution-Epitaxially Grown Formamidinium-Lead-Bromide Micro-Resonators - Afify, Hany A.; Sytnyk, Mykhailo; Rehm, Viktor; Barabash, Anastasiia; Mashkov, Oleksandr; Osvet, Andres; Volobuev, Valentine V.; Korczak, Jędrzej; Szczerbakow, Andrzej; Story, Tomasz; Götz, Klaus; Unruh, Tobias; et al. (Advanced Optical Materials, 2022)
High-quality epitaxial growth of oriented microcrystallites on a semiconductor substrate is demonstrated here for formamidinium lead bromide perovskite, by drop casting of precursor solutions in air. The microcrystallites exhibit green photoluminescence at room temperature, as well as lasing with low thresholds. Lasing is observed even though the substrate is fully opaque at the lasing wavelengths, and even though it has a higher refractive index as the perovskite active material. Moreover, the lasing is stable for more than 109 excitation pulses, which is more than what is previously achieved for devices kept in the air. Such highly stable lasing under pulsed excitation represents an important step towards continuous mode operation or even electrical excitation in future perovskite-based devices.
CRIS-Team Scopus Importer:2022-04-14
Keywords: halide perovskites; lasing; microresonators; solution epitaxy

Highly Stable n–i–p Structured Formamidinium Tin Triiodide Solar Cells through the Stabilization of Surface Sn2+ Cations - Hu, Manman; Risqi, Andi Muhammad; Wu, Jianchang; Chen, Liang; Park, Jaewang; Lee, Seung Un; Yun, Hyun Sung; Park, Byung Wook; Brabec, Christoph; Seok, Sang Il (Advanced Functional Materials, 2023)
Improving the performance, reproducibility, and stability of Sn-based perovskite solar cells (PSCs) with n–i–p structures is an important challenge. Spiro-OMeTAD [2,2′,7,7′-tetrakis(N,N-di-p-methoxyphenyl-amine)9,9′-spirobifluorene], a hole transporting material (HTM) with n–i–p structure, requires the oxygen exposure after addition of Li-TFSI [Lithium bis(trifluoromethanesulfonyl)imide] as a dopant to increase the hole concentration. In Sn-based PSC, Sn2+ is easily oxidized to Sn4+ under such a condition, resulting in a sharp decrease in efficiency. Herein, a formamidinium tin triiodide (FASnI3)-based PSCs fabricated using DPI-TPFB [4-Isopropyl-4′-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate] instead of Li-TFSI are reported as a dopant in Spiro-OMeTAD. The DPI-TPFB enables the fabrication of PSCs with an efficiency of up to 10.9%, the highest among FASnI3-based PSCs with n–i–p structures. Moreover, ≈80% of the initial efficiency is maintained even after 1,597 h under maximum power point tracking conditions. In particular, the encapsulated device does not show any decrease in efficiency even after holding for 50 h in the 85 °C/85% RH condition. The high efficiency and excellent stability of PSCs prepared by doping with DPI-TPFB are attributed to not only increasing electrical conductivity by acting as a Lewis acid, but also stabilizing Sn2+ through coordination with Sn2+ on the surface of FASnI3.
CRIS-Team Scopus Importer:2023-04-21
Keywords: efficiency; new dopants; n–i–p structure; oxidation; pure tin perovskite; Spiro-OMeTAD; stability

Highly transmissive luminescent down-shifting layers filled with phosphor particles for photovoltaics - Solodovnyk, Anastasiia; Forberich, Karen; Stern, Edda; Krc, Janez; Topic, Marko; Batentschuk, Miroslaw; Lipovsek, Benjamin; Brabec, Christoph (Optical Materials Express, 2015)
We study the optical properties of polymer layers filled with phosphor particles in two aspects. First, we used two different polymer binders with refractive indices n = 1.46 and n = 1.61 (λ = 600 nm) to study the influence of Δn with the phosphor particles (n = 1.81). Second, we prepared two particle size distributions D = 12 μm and D = 19 μm. The particles were dispersed in both polymer binders in several volume concentrations and coated with thicknesses of 150-600 μm onto glass substrates. Experimental results and numerical simulations show that the layers of the higher refractive index binder with larger particles result in the highest optical transmittance in the visible light spectrum. Finally, we used numerical simulations to determine optimal layer composition for application in realistic photovoltaic devices.
Keywords: Engineering controlled terms: Binders; Bins; Light emission; Numerical models; Optical properties; Particle size; Phosphors; Polymers; Refractive index; Substrates Glass substrates; Layer composition; Phosphor particles; Photovoltaic devices; Photovoltaics; Polymer binders; Polymer layers; Volume concentration Engineering main heading: Filled polymers

Highly transmissive luminescent down-shifting layers filled with phosphor particles for photovoltaics: Publisher's note - Solodovnyk, Anastasiia; Forberich, Karen; Stern, Edda; Krc, Janez; Topic, Marko; Batentschuk, Miroslaw; Lipovsek, Benjamin; Brabec, Christoph (Optical Materials Express, 2015)
This publisher's note amends the author list and Acknowledgments of [Opt. Mater. Express 5, 1296 (2015)]. The author names were corrected online as of June 24, 2015: https://www.osapublishing.org/ome/abstract.cfm?uri=ome-5-6-1296.

High Performance All-Polymer Photodetector Comprising a Donor- Acceptor-Acceptor Structured Indacenodithiophene-Bithieno[3,4-c]Pyrroletetrone Copolymer - Murto, Petri; Genene, Zewdneh; Benavides, Cindy Montenegro; Xu, Xiaofeng; Sharma, Anirudh; Pan, Xun; Schmidt, Oliver; Brabec, Christoph; Andersson, Mats R.; Tedde, Sandro F.; Mammo, Wendimagegn; Wang, Ergang (ACS Macro Letters, 2018)
The synthesis of an acceptor polymer PIDT-2TPD, comprising indacenodithiophene (IDT) as the electron-rich unit and an interconnected bithieno[3,4-c]-pyrrole-4,4',6,6'-tetrone (2TPD) as the electron-deficient unit, and its application for all-polymer photodetectors is reported. The optical, electrochemical, charge transport, and device properties of a blend of poly(3-hexylthiophene) and PIDT-2TPD are studied. The blend shows strong complementary absorption and balanced electron and hole mobility, which are desired properties for a photoactive layer. The device exhibits dark current density in the order of 10(-5) mA/ cm(2), external quantum efficiency broadly above 30%, and nearly planar detectivity over the entire visible spectral range (maximum of 1.1 x 10(12) Jones at 610 nm) under -5 V bias. These results indicate that PIDT-2TPD is a highly functional new type of acceptor and further motivate the use of 2TPD as a building block for other n-type materials.

High-performance all-polymer solar cells with only 0.47 eV energy loss - Wu, Qiang; Wang, Wei; Wang, Tao; Sun, Rui; Guo, Jing; Wu, Yao; Jiao, Xuechen; Brabec, Christoph; Li, Yongfang; Min, Jie (Science China-Chemistry, 2020)
The field of all-polymer solar cells (all-PSCs) has experienced rapid development during the past few years, mainly driven by the development of efficient polymer acceptors. However, the power conversion efficiencies (PCEs) of the all-PSCs are still limited by insufficient light absorption of the donor/acceptor blend and large energy loss in devices. We herein designed a polymer acceptor PYT1 constructed n-type molecular acceptor Y5-C20 as the key building block and blended it with a polymer donor PM6 to obtain an all-polymer photoactive layer. The optimized PM6:PYT1 all-PSCs achieved a record higher PCE of 13.43% with a very low energy loss of 0.47 eV and a photoresponse of up to 900 nm compared with the Y5-C20 based device with a best PCE of 9.42%. Furthermore, the PCEs of the PM6:PYT1 all-PSCs are relatively insensitive to the 1-chloronaphthalene (CN) additive contents and active layer thickness. Our results also highlight the effect of CN additive on PM6:PYT1 morphology, i.e., charge generation, and transport find an optimized balance, and radiative and non-radiative loss is simultaneously reduced in the blend. This work promotes the development of high-performance polymer acceptors and heralds a brighter future of all-PSCs for commercial applications.
CRIS-Team Scopus Importer:2020-07-17
Keywords: absorption coefficient; all-polymer solar cells; energy loss; mechanical stability; polymer acceptor

High performance all-small-molecule solar cells: Engineering the nanomorphology: Via processing additives - Min, Jie; Kwon, Oh Kyu; Cui, Chaohua; Park, Jung-Hwa; Wu, Yue; Park, Soo Young; Li, Yongfang; Brabec, Christoph (Journal of Materials Chemistry A, 2016)
The use of small volumes of solvent additives (SAs) or little amounts of non-volatile additives is a processing approach that has been implemented in many high/record performing bulk heterojunction (BHJ) organic solar cells (OSCs). Here, the effects of six SA systems and a molecular additive di-2-thienyl-2,1,3-benzothiadiazole (DTBT) were studied with respect to the photovoltaic parameters of solution-processed all small molecule solar cells (all-SMSCs) based on the BDTT-S-TR:NIDCS-MO system. An effective strategy with binary additives has been employed in this all-SM system, where a small amount, 0.75 vol% 1,8-diiodooctane (DIO) and 2 wt% DTBT were added to the casting solution. This efficient SA approach yielded the highest power conversion efficiency (PCE) of 5.33%. The relevant additives facilitate phase separation in the nm domains and improve bulk transport as evidenced by photoluminescence (PL), atomic force microscopy (AFM), X-ray diffraction (XRD) and space charge limited current (SCLC) measurements.
Keywords: Engineering controlled terms: Additives; Atomic force microscopy; Cell engineering; Heterojunctions; Molecules; Organic solar cells; Phase separation; Photovoltaic effects; Solar power generation; X ray diffraction 1; 3-benzothiadiazole; Bulk heterojunction (BHJ); Molecular additives; Photovoltaic parameters; Power conversion efficiencies; Processing approach; Solution-processed; Space-charge-limited current Engineering main heading: Solar cells

High-performance direct conversion X-ray detectors based on sintered hybrid lead triiodide perovskite wafers - Shrestha, Shreetu; Fischer, Rene; Matt, Gebhard; Feldner, Patrick; Michel, Thilo; Osvet, Andres; Levchuk, Ievgen; Merle, Benoit; Golkar, Saeedeh; Chen, Haiwei; Tedde, Sandro F.; Schmidt, Oliver; et al. (Nature Photonics, 2017)
Lead halide perovskite semiconductors are in general known to have an inherently high X-ray absorption cross-section and a significantly higher carrier mobility than any other low-temperature solution-processed semiconductor. So far, the processing of several-hundred-micrometres-thick high-quality crystalline perovskite films over a large area has been unresolved for efficient X-ray detection. In this Article, we present a mechanical sintering process to fabricate polycrystalline methyl ammonium lead triiodide perovskite (MAPbI(3)) wafers with millimetre thickness and well-defined crystallinity. Benchmarking of the MAPbI(3) wafers against state-of-the-art CdTe detectors reveals competitive conversion efficiencies of 2,527 mu C Gy(air)(-1) cm(-2) under 70 kV(p) X-ray exposure. The high ambipolar mobility-lifetime product of 2 x 10(-4) cm(2) V-1 is suggested to be responsible for this exceptionally high sensitivity. Our findings inform a new generation of highly efficient and low-cost X-ray detectors based on perovskite wafer

High-Performance Organic Photodetectors from a High-Bandgap Indacenodithiophene-Based π-Conjugated Donor-Acceptor Polymer. - Benavides, Cindy Montenegro; Murto, Petri; Chochos, Christos L.; Gregoriou, Vasilis G.; Avgeropoulos, Apostolos; Xu, Xiaofeng; Bini, Kim; Sharma, Anirudh; Andersson, Mats R.; Schmidt, Oliver; Brabec, Christoph; Wang, Ergang; et al. (ACS Applied Materials and Interfaces, 2018)
A conjugated donor-acceptor polymer, poly[4,4,9,9-tetrakis (4-hexylpheny1)-4,9-dihydro-s-in dace no [1,2-b: 5,6-b']dithiophene 2,7 diyl alt-5 (2-ethylhexyl)-4H-thieno[3,4-c] pyrrole-4,6 (5H)-dione-1,3-diyl](PIDT-TPD), is blended with the fullerene derivative [6,6]phenyl-C61-butyric acid methyl ester (PC61BM) for the fabrication of thin and solution-processed organic photodetectors (OPDs). Systematic screening of the concentration ratio of the blend and the molecular weight of the polymer is performed to optimize the active layer morphology and the OPD performance. The device comprising a medium molecular weight polymer (27.0 kg/mol) in a PIDT-TPD:PC61BM 1:1 ratio exhibits an external quantum efficiency of 52% at 610 nm, a dark current density of 1 nA/cm(2), a detectivity of 1.44 x 10(13) Jones, and a maximum 3 dB cutoff frequency of 100 kHz at -5 V bias. These results are remarkable among the state-of-the-art red photodetectors based on conjugated polymers. As such, this work presents a functional organic active material for high-speed OPDs with a linear photoresponse at different light intensities.
Keywords: concentration ratio; dark current density; frequency response; high speed; molecular weight; red organic photodetectors

High-Performance Organic Solar Cells Based on a Small Molecule with Alkylthio-Thienyl-Conjugated Side Chains without Extra Treatments - Cui, Chaohua; Guo, Xia; Min, Jie; Guo, Bing; Cheng, Xiao; Zhang, Maojie; Brabec, Christoph; Li, Yongfang (Advanced Materials, 2015)
A new 2D-conjugated small molecule with alkylthio-thienyl-conjugated side chains (BDTT-S-TR) is synthesized for application as a donor material in organic solar cells (OSCs). The OSCs based on BDTT-S-TR/PCBM demonstrate a power conversion efficiency (PCE) of 9.20% without extra treatment. Moreover, an encouraging PCE of 6.68% is achieved from the device with active area of 144 mm.
Keywords: conjugated side chains; organic molecules; organic solar cells; solution processability

High-performance semitransparent perovskite solar cells with solution-processed silver nanowires as top electrodes - Guo, Fei; Azimi, Seyed Hamed; Hou, Yi; Przybilla, Thomas; Hu, Mengyao; Bronnbauer, Carina; Langner, Stefan; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (Nanoscale, 2015)
In this work, we report efficient semitransparent perovskite solar cells using solution-processed silver nanowires (AgNWs) as top electrodes. A thin layer of zinc oxide nanoparticles is introduced beneath the AgNWs, which fulfills two essential functionalities: it ensures ohmic contact between the PC60BM and the AgNWs and it serves as a physical foundation that enables the solution-deposition of AgNWs without causing damage to the underlying perovskite. The as-fabricated semitransparent perovskite cells show a high fill factor of 66.8%, V-oc = 0.964 V, J(sc) = 13.18 mA cm(-2), yielding an overall efficiency of 8.49% which corresponds to 80% of the reference devices with reflective opaque electrode

High performance tandem organic solar cells via a strongly infrared-absorbing narrow bandgap acceptor - Jia, Zhenrong; Qin, Shucheng; Meng, Lei; Ma, Qing; Angunawela, Indunil; Zhang, Jinyuan; Li, Xiaojun; He, Yakun; Lai, Wenbin; Li, Ning; Ade, Harald; Brabec, Christoph; et al. (Nature Communications, 2021)
Tandem organic solar cells are based on the device structure monolithically connecting two solar cells to broaden overall absorption spectrum and utilize the photon energy more efficiently. Herein, we demonstrate a simple strategy of inserting a double bond between the central core and end groups of the small molecule acceptor Y6 to extend its conjugation length and absorption range. As a result, a new narrow bandgap acceptor BTPV-4F was synthesized with an optical bandgap of 1.21 eV. The single-junction devices based on BTPV-4F as acceptor achieved a power conversion efficiency of over 13.4% with a high short-circuit current density of 28.9 mA cm−2. With adopting BTPV-4F as the rear cell acceptor material, the resulting tandem devices reached a high power conversion efficiency of over 16.4% with good photostability. The results indicate that BTPV-4F is an efficient infrared-absorbing narrow bandgap acceptor and has great potential to be applied into tandem organic solar cells.
CRIS-Team Scopus Importer:2021-01-15

High performance ternary organic solar cells with thick active layer exceeding 11% efficiency - Gasparini, Nicola; Lucera, Luca; Salvador, Michael Filipe; Prosa, Mario; Spyropoulos, Georgios; Kubis, Peter; Egelhaaf, Hans Joachim; Brabec, Christoph; Ameri, Tayebeh (Energy and Environmental Science, 2017)
We present a novel ternary organic solar cell with uncommonly thick active layer (>300 nm), featuring thickness invariant charge carrier recomb ination and delivering 11% power conversion efficiency (PCE). The ternary blend was used to demonstrate photovoltaic modules of high technological relevance both on gla ss and flexible substrates, yielding 8.2% and 6.8% PCE, respectively.

High Performance X-ray to Current Converters Fabricated Via Sintering or Melting of a Metal-halide Perovskite - Matt, Gebhard; Levchuk, Ievgen; Knüttel, Judith; Shrestha, Shreetu; Dallmann, Johannes; Hock, Rainer; Heiß, Wolfgang; Brabec, Christoph (nanoGe Fall Meeting 2019, 2019)
The search for an ideal X-ray sensitive photo-conductor is an ongoing task since the most semiconductors do not absorb high energy radiation effectively. However, the latter is an intrinsic property of the lead-halide perovskites semiconductors due to high radiation attenuation by the lead and halide ions combined with there good charge transport properties. In this presentation we will review our latest efforts utilizing organic-inorganic (MAPbI3) as well as a pure inorganic metal-halide perovkite (CsPbBr3) for X-ray to current converters. We demonstrate a sintering as well as a melting process which leads to the formation of several hundred µm thick and crystalline samples. Most notable for these samples are the good charge transport properties and unusual high mobility- lifetime products ( 1E-3 cm^2/V). The achieved X-ray to current conversation rate up to 2500 µC/Gycm2 is on par to the current state-of-the-art Cd(Zn)Te detector technology and our findings inform on a low-cost scaleable technology for the next generation of high energy detector technology.

High precision processing of flexible P3HT/PCBM modules with geometric fill factor over 95% - Kubis, Peter; Lucera, Luca; Machui, Florian; Spyropoulos, Georgios; Cordero, Johann; Frey, Alfred; Kaschta, Joachim; Voigt, Monika; Matt, Gebhard; Zeira, Eitan; Brabec, Christoph (Organic Electronics, 2014)
Flexible OPV modules, based on P3HT:PCBM as absorber layer, were manufactured with a power conversion efficiency over 3% and for a total area of 3500 mm(2) consisting of 14 in series interconnected cells. The modules utilize the excellent mechanical and the outstanding optical properties of sputtered transparent ITO-Metal-ITO (IMI) electrodes deposited on the PET foil on the one hand, and the combination of large area slot-die coating with high resolution ultrafast laser patterning on the other hand. The manufacturing of modules with outstanding performance was found to be reproducible. The right combination of innovative electrodes and smart roll-to-roll compatible processing technologies demonstrates a viable path towards high efficient industrial module technology. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Flexible transparent electrode; Flexible OPV module; Slot-die coating; Ultra-fast laser patterning; High geometric fill factor

High Q femtoREGEN™ UC laser systems for industrial microprocessing applications - Matylitsky, V. V.; Kubis, Peter; Brabec, Christoph; Au, J. Aus Der (Frontiers in Ultrafast Optics: Biomedical, Scientific, and Industrial Applications XII, 2012)
High average power, high repetition rate femtosecond lasers with μJ pulse energies are increasingly used for bio-medical and material processing applications. With the introduction of femtosecond laser systems such as the High Q femtoREGEN™ UC platform, micro-processing of solid targets with femtosecond laser pulses have obtained new perspectives for industrial applications. The unique advantage of material processing with sub-picosecond lasers is efficient, fast and localized energy deposition, which leads to high ablation efficiency and accuracy in nearly all kinds of solid materials. In this paper, we will show aspects of the design and performance of the femtoREGEN™ UC industrial laser system and give an overview of actual applications. © 2012 SPI
Keywords: Ablation; Femtosecond laser pulse; Micro-processing; Ultrafast laser

High-Resolution spectroScopic mapping of the chemical contrast from nanometer domains in P3HT:PCBM organic blend films for Solar-Cell applications by - Wang, Xiao; Zhang, Dai; Braun, Kai; Egelhaaf, Hans-Joachim; Brabec, Christoph; Meixner, Alfred J. (Advanced Functional Materials, 2010)
A high-resolution near-field spectroscopic mapping technique is successfully applied to investigate the influence of thermal annealing on the morphology of a poly(3-hexylthiophene) and [6,6]-penyl-C butyric acid methyl ester (P3HT:PCBM) blend film. Based on the simultaneously recorded morphological and spectroscopic information, the interplay among the blend film morphology, the local P3HT:PCBM molecular distribution, and the P3HT photoluminescence (PL) quenching efficiency are systematically discussed. The PL and Raman signals of the electron donor (P3HT) and acceptor (PCBM) are probed at an optical resolution of approximately 10 nm, which allows the chemical nature of the different domains to be identified directly. In addition, the local PL quenching efficiency, which is related to the electron transfer from P3HT to PCBM, is quantitatively revealed. From these experimental results, it is proposed that high-resolution near-field spectroscopic imaging is capable of mapping the local chemical composition and photophysics of the P3HT:PCB M blends on a scale of a few nanometers. © 2010 WlLEY-VCH Verlag GmbH & Co. KGaA,.

High shunt resistance in polymer solar cells comprising a MoO3 hole extraction layer processed from nanoparticle suspension - Stubhan, Tobias; Ameri, Tayebeh; Salinas Batallas, Michael; Krantz, Johannes; Machui, Florian; Halik, Marcus; Brabec, Christoph (Applied Physics Letters, 2011)
In this report, we present solution processed molybdenum trioxide (MoO3) layers incorporated as hole extraction layer (HEL) in polymer solar cells (PSCs) and demonstrate the replacement of the commonly employed poly(3,4-ethylene dioxythiophene):(polystyrene sulfonic acid) (PEDOT:PSS). MoO3 is known to have excellent electronic properties and to yield more stable devices compared to PEDOT:PSS. We demonstrate fully functional solar cells with up to 65 nm thick MoO3 HEL deposited from a nanoparticle suspension at low temperatures. The PSCs with an active layer comprising a blend of poly(3-hexylthiophene) and [6,6]-phenyl-C61 butyric acid methyl ester and a MoO3 HEL show comparable performance to reference devices with a PEDOT:PSS HEL. The best cells with MoO3 reach a fill factor of 66.7% and power conversion efficiency of 2.92%. Moreover, MoO3 containing solar cells exhibit an excellent shunt behavior with a parallel resistance of above 100 kΩ cm2.

High-speed sequential deposition of photoactive layers for organic solar cell manufacturing - Sun, Rui; Wang, Tao; Yang, Xinrong; Wu, Yao; Wang, Yang; Wu, Qiang; Zhang, Maojie; Brabec, Christoph; Li, Yongfang; Min, Jie (Nature Energy, 2022)
Despite the great success of organic photovoltaics in terms of device efficiency and stability at the laboratory scale, pressing demand for high-throughput and cost-effective solutions remains unresolved and rarely reported. Here we propose that a sequential-deposition, blade-coating approach using donor and acceptor materials can facilitate high-speed fabrication of photoactive layers while maintaining device performance. The sequential-deposition-processed blend and thickness of its designed PM6:T8 system can be optimized by the fine-tuning of the solution concentrations and coating speeds. We show that this strategy can be applied to a non-halogenated solvent and under high-humidity conditions. This high-speed approach is applicable to other non-fullerene photovoltaic systems and the slot-die coating technique. Techno-economic analysis suggests that this strategy can decrease the minimum sustainable price of module manufacturing. Overall, this work represents a step towards the scalable, cost-effective manufacturing of organic photovoltaics with both high performance and high throughput.
CRIS-Team Scopus Importer:2022-11-04

High-temperature thermographic phosphor mixture YAP/YAG:Dy3+ and its photoluminescence properties - Chepyga, Liudmyla M.; Osvet, Andres; Brabec, Christoph; Batentschuk, Miroslaw (Journal of Luminescence, 2017)
In this work we report on the investigation of high-temperature thermographic phosphors Dy3+-doped yttrium aluminum garnet and the mixture of yttrium aluminum perovskite / yttrium aluminum garnet (YAP/YAG). The phosphors were synthesized by conventional high temperature solid-state method using lithium fluoride (LiF) as a flux. The latter serves also as a source of co-doping Li+ and F- ions affecting the luminescent properties. The photoluminescence intensity of YAP/YAG:Dy (75/25%) mixture was doubled at room temperature compared to YAG:Dy and the intensity ratio of the lines in the regions 450–460 and 480–500 nm was increased from 0.45 to 0.63 at 1293 K, favoring temperature measurements. Therefore, the mixture of YAlO3/Y3Al5O12:Dy is promising material for high temperature phosphor thermometry. © 2017 Elsevier B.V.
Keywords: Aluminum; Dysprosium; Garnets; Light emission; Luminescence; Mixtures; Photoluminescence; Temperature measurement; Thermometers; Yttrium; High temperature solid state methods; Lithium fluoride; Luminescent property; Phosphor thermometry; Photoluminescence intensities; Photoluminescence properties; Thermographic phosphors; Yttrium aluminum garnet; Phosphors

High-Throughput Optical Screening for Efficient Semitransparent Organic Solar Cells - Xia, Ruoxi; Brabec, Christoph; Yip, Hin Lap; Cao, Yong (Joule, 2019)
Power-generating windows for buildings and automobiles bring great photovoltaic market opportunities. Ideal semitransparent photovoltaics should let required visible light pass and convert as much as near-infrared light energy into electric power. However, the current commercial, inorganic, semitransparent photovoltaics cannot fully meet such complex requirements, as their optical properties are intrinsically difficult to tune. Herein, by combining the advantages of organic photovoltaics with highly tunable optical properties and photonic structures with flexible optical regulation, a high-performance device with nearly 11% power conversion efficiency and 30% visible light transmittance was demonstrated. The advanced optical properties of the device were achieved by screening over tens of millions of device configurations through a high-throughput optical model, which had wide potential applications, especially as related to designs including multi-objective and multi-layer thickness optimizations.
CRIS-Team Scopus Importer:2019-09-17
Keywords: computational screening; high-throughput optical model; one-dimensional photonic crystals; semitransparent organic solar cells

High-throughput, outdoor characterization of photovoltaic modules by moving electroluminescence measurements - Doll, Bernd; Pickel, Tobias; Schreer, Oliver; Zetzmann, Cornelia; Hepp, Johannes; Teubner, Janine; Buerhop, Claudia; Hauch, Jens; Camus, Christian; Brabec, Christoph (Optical Engineering, 2019)
Fast and nondestructive quality control tools are important to assess the reliability of photovoltaic plants. On-site inspection is essential to minimize the risk of further damage and electrical yield losses. The most effective way of achieving this is with highly sensitive imaging techniques such as luminescence or infrared thermography imaging. Nowadays, electroluminescence (EL) is used at nighttime to detect defects such as local cell changes, series resistances, and shunts. However, the drawback of this method is low measurement throughput. To increase the throughput, indium gallium arsenide detectors with a resolution of 640 × 512 pixels are used, for which short integration times are possible to acquire EL images. For such short integration times, even moving image acquisition and movie recording are feasible to detect the mentioned defects. An outdoor EL setup is presented for mobile handheld recording, which can even be used under low-light conditions, below 100 W / m2, at daytime. Experiments show that 5 ms integration time is a good compromise between low contrasts for lower integration times and motion blur for higher integration times. The camera prototype has an onboard computer to avoid image transmission losses and an external lithium polymer battery power supply for improved mobility.
CRIS-Team Scopus Importer:2019-09-27
Keywords: defect detection; electroluminescence; high throughput; indium gallium arsenide camera; on-site inspection; photovoltaic module

High throughput, outdoor characterization of silicon photovoltaic modules by moving electroluminescence measurements - Doll, Bernd; Pickel, Tobias; Schreer, Oliver; Zetzmann, Cornelia; Teubner, Janine; Buerhop-Lutz, Claudia; Hauch, Jens; Camus, Christian; Brabec, Christoph (Vol. 10766, 2018)
Fast and non-destructive quality control tools are important to assess the reliability of photovoltaic plants. On-site inspection is essential to minimize the risk of module damage and electrical yield losses. This may only be achieved by using highly sensitive imaging techniques such as luminescence or infrared thermography imaging. Nowadays, electroluminescence is used to detect defects such as local cell changes, series resistances and shunts in solar cells and modules which can cause electrical losses. However, the drawback of this method is the relatively low measurement throughput. To increase the throughput InGaAs cameras with a resolution of 640 x 512 pixels are used, for which low integration times are possible to acquire electroluminescence images. For such low integration times even moving image acquisition and movie recording are feasible to detect the mentioned defects. In this paper, an outdoor electroluminescence setup is presented for mobile handheld recording. Experiments showed that 5 ms integration time is a good compromise between low contrasts for lower integration times and motion blurring for higher integration times. The camera prototype has an onboard computer to avoid image transmission losses. It was controlled and visualized over Wi-Fi and remote desktop connection. The energy supply was provided from LiPo-batteries for improved mobility. In comparison to conventional electroluminescence measurements we can decrease the measurement time of a 20 module string from 5 min to 20 s.<br
Keywords: defect detection; electroluminescence; high throughput; InGaAs camera; on-site inspection; photovoltaic module; InGaAs camera.

High-Throughput Robotic Synthesis and Photoluminescence Characterization of Aqueous Multinary Copper–Silver Indium Chalcogenide Quantum Dots - Stroyuk, Oleksandr; Raievska, Oleksandra; Langner, Stefan; Kupfer, Christian; Barabash, Anastasiia; Solonenko, Dmytro; Azhniuk, Yuriy; Hauch, Jens; Osvet, Andres; Batentschuk, Miroslaw; Zahn, Dietrich R. T.; Brabec, Christoph (Particle & Particle Systems Characterization, 2021)
The feasibility of a high-throughput robot-assisted synthesis of complex Cu1-xAgxInSySe1-x (CAISSe) quantum dots (QDs) by spontaneous alloying of aqueous glutathione-capped Ag–In–S, Cu–In–S, Ag–In–Se, and Cu–In–Se QDs is demonstrated. Both colloidal and thin-film core CAISSe and core/shell CAISSe/ZnS QDs are produced and studied by high-throughput semiautomated photoluminescence (PL) spectroscopy. The silver-copper-mixed QDs reveal clear evidence of a band bowing effect in the PL spectra and higher average PL lifetimes compared to the counterparts containing silver or copper only. The photophysical analysis of CAISSe and CAISSe/ZnS QDs indicates a composition-dependent character of the nonradiative recombination in QDs. The rate of this process is found to be lower for mixed copper-silver-based QDs compared to Cu- or Ag-only QDs. The combination of the band bowing effect and the suppressed nonradiative recombination of CAISSe QDs is beneficial for their applications in photovoltaics and photochemistry. The synergy of high-throughput robotic synthesis and a high-throughput characterization in this study is expected to grow into a self-learning synthetic platform for the production of metal chalcogenide QDs for light-harvesting, light-sensing, and light-emitting applications.
CRIS-Team Scopus Importer:2021-09-10
Keywords: combinatorial synthesis; semiconductor nanocrystals; spontaneous alloying; ternary chalcogenides; time-resolved photoluminescence

High-Throughput Time-Resolved Photoluminescence Study of Composition- And Size-Selected Aqueous Ag-In-S Quantum Dots - Stroyuk, Oleksandr; Raievska, Oleksandra; Kupfer, Christian; Solonenko, Dmytro; Osvet, Andres; Batentschuk, Miroslaw; Brabec, Christoph; Zahn, Dietrich R.T. (Journal of Physical Chemistry C, 2021)
Brightly luminescent, composition- and size-selected aqueous Ag-In-S (AIS) and Zn-diffused core/shell AIS/ZnS (ZAIS) quantum dots (QDs) were studied by high-throughput time-resolved photoluminescence (TRPL). Both QD size and QD composition effects on the photophysical properties of AIS (ZAIS) were probed independently by using an automated high-throughput TRPL setup. Linear relationships were found between the average PL lifetimes of AIS and ZAIS QDs and their respective bandgaps (Eg) indicating that the dynamics of the radiative recombination is governed mostly by the energy of the QD excited state irrespective of which factor is varied affecting the QD bandgap, i.e., their size or composition. The rate constants of radiative and nonradiative recombination were evaluated as a function of Eg forming continuous dependences for the entire AIS and ZAIS QD families. The rate of nonradiative recombination increases steeply for smaller QDs with Eg > 2.2 eV for both core AIS and core/shell ZAIS QDs, indicating that the interfacial electron transfer is the major contributor to the observed dependence. A strong decrease of the PL lifetime of AIS (and ZAIS) QDs in dense QD films or QDs incorporated into polyvinylpyrrolidone films was observed as compared to colloidal solutions. A reversible character of this effect upon polymer film dissolution shows that such behavior originates from energy (or electron) transfers among the QDs brought into close contact in the films. This phenomenon is expected to be of significance for the application of ternary QDs as a light-harvesting material.
CRIS-Team Scopus Importer:2021-07-02

Impact of 2D Ligands on Lattice Strain and Energy Losses in Narrow-Bandgap Lead–Tin Perovskite Solar Cells - Zhang, Kaicheng; Vincze, Andrej; Metwalli, Ezzeldin; Zhang, Jiyun; Liu, Chao; Meng, Wei; Zhang, Boxue; Tian, Jingjing; Heumüller, Thomas; Xie, Zhiqiang; Luo, Junsheng; Osvet, Andres; et al. (Advanced Functional Materials, 2023)
Mixed lead and tin (Pb/Sn) hybrid perovskites exhibit a great potential in fabricating all-perovskite tandem devices due to their easily tunable bandgaps. However, the energy deficit and instability in Pb/Sn perovskite solar cells (PSCs) constrain their practical applications, which renders defect passivation engineering indispensable to develop highly efficient and long-term stable PSCs. Herein, the mechanisms of strain tailoring and defect passivation in Pb/Sn PSCs by 2D ligands are investigated. The 2D ligands include electroneutral cations with long alkyl chain (LAC), iodates with relatively short alkyl chain (SAC) and their mixtures. This study reveals that LAC ligands facilitate the relaxation of tensile strain in perovskite films while SAC ligands cause strain buildup. By mixing LAC/SAC ligands, tensile strain in perovskite films can be balanced which improves solar cell performance. PSCs with admixed β-guanidinopropionic acid (GUA)/phenethylammonium iodide (PEAI) exhibit enhanced open circuit voltage and fill factor, which is attributed to reduced nonradiative recombination losses in the bulk and at the interfaces. Furthermore, the operational stability of PSCs is slightly improved by the mixed 2D ligands. This work reveals the mechanisms of 2D ligands in strain tailoring and defect passivation toward efficient and stable narrow-bandgap PSCs.
CRIS-Team Scopus Importer:2023-07-07
Keywords: 2D ligand passivation; energy losses; lead/tin perovskite solar cells; stability; strain tailoring

Impact of a large-scale market integration on the orientation of photovoltaic modules - Bogenrieder, Josef; Hosch, Patrick; Sölch, Christian; Brabec, Christoph (2016 13th International Conference on the European Energy Market (EEM), 2016)
To increase the amount of renewable energies, the Renewable Energies Act (REA) in Germany guarantees a fixed feed-in tariff for 20 years for every kilowatt-hour that is produced. Thus, photovoltaic modules were faced in the direction of the highest energy production. In this paper we investigate, if in a future energy system with a high share of renewable energy power and especially PV power, there is an incentive to face modules divergent because of an overproduction during noon. Hence, we modelled the PV generation for the states in Germany in detail as well as the spot market for the years 2014 and 2035 according to the Grid Development Plan of the German Transmission System Operators (TSO
Keywords: Engineering controlled terms: Electric power transmission; Photovoltaic cells; Power markets Development plans; Energy productions; Future energies; Market integration; Photovoltaic modules; Renewable energies; Renewable energy power; Transmission system operators Engineering controlled terms: Electric power transmission; Photovoltaic cells; Power markets Development plans; Energy productions; Future energies; Market integration; Photovoltaic modules; Renewable energies; Renewable energy power; Transmission system operators Engineering main heading: Commerce

Impact of PID on industrial rooftop PV-installations - Buerhop, Claudia; Fecher, Frank; Pickel, Tobias; Patel, Tirth; Zetzmann, Cornelia; Camus, Christian; Hauch, Jens; Brabec, Christoph (Proceedings Volume 10370,Reliability of Photovoltaic Cells, Modules, Components, and Systems X, 2017)
Potential induced degradation (PID) causes severe damage and financial losses even in modern PV-installations. In Germany, approximately 19% of PV-installations suffer from PID and resulting power loss. This paper focuses on the impact of PID in real installations and how different evaluated time intervals influence the performance ratio (PR) and the determined degradation rate. The analysis focuses exemplarily on a 300 kWp PV-system in the Atlantic coastal climate. IR-imaging is used for identifying PID without operation interruption. Historic electric performance data are available from a monitoring system for several years on system level, string level as well as punctually measured module string I-V-curves. The data sets are combined for understanding the PID behavior of this PV plant. The number of PID affected cells within a string varies strongly between 1 to 22% with the string position on the building complex. With increasing number of PID-affected cells the performance ratio decreases down to 60% for daily and monthly periods. Local differences in PID evolution rates are identified. An average PR-reduction of -3.65% per year is found for the PV-plant. On the string level the degradation rate varied up to 8.8% per year depending on the string position and the time period. The analysis reveals that PID generation and evolution in roof-top installations on industrial buildings with locally varying operation conditions can be fairly complex. The results yield that local operating conditions, e.g. ambient weather conditions as well as surrounding conditions on an industrial building, seem to have a dominating impact on the PID evolution rate.
Keywords: potential induced degradation (PID); IR-imaging; performance ratio; performance loss

Improved Air Processability of Organic Photovoltaics Using a Stabilizing Antioxidant to Prevent Thermal Oxidation - Steinberger, Marc; Distler, Andreas; Brabec, Christoph J.; Egelhaaf, Hans-Joachim (Journal of Physical Chemistry C, 2021)
During the production of organic solar cells, the exposure of constituting materials and resulting devices to light, heat, oxygen, and water is a potential source of degradation. We show that thermo-oxidation of the active materials occurs upon annealing the active layer or upon stirring the active materials solutions in air at elevated temperatures. By comparing various blends of donor polymers with fullerene or nonfullerene acceptors, fullerene is identified to be the most susceptible component to thermal oxidation in both film and solution, while the polymer remains unaffected. In both cases, the effect on the photovoltaic device performance consists predominantly in a decreased short-circuit current (J(SC)), suggesting that the underlying degradation mechanism is the same in the solid state and in solution. In addition, we find that thermo-oxidation of the active layer during annealing of the device can be decelerated by blending nickel(II) dibutyldithiocarbamate (Ni(dtc)(2)) as an antioxidant additive into the active layer. While small concentrations of additive stabilize JSC and therefore the power conversion efficiency, higher contents negatively affect device performance. On the other hand, thermo-oxidation of the active materials in solution during stirring in air at elevated temperatures can be avoided for several hours by adding as little as 0.5% Ni(dtc)(2). The observation that the antioxidant is consumed during stabilization of the active materials suggests a sacrificial protection mechanism.
CRIS-Team WoS Importer:2022-01-14

Improved Efficiency of Polymer Solar Cells by Modifying the Side Chain of Wide-Band Gap Conjugated Polymers Containing Pyrrolo[3,4- f]benzotriazole-5,7(6 H)-dione Moiety - Zhu, Peng; Fan, Baobing; Du, Xiaoyan; Tang, Xiaofeng; Li, Ning; Liu, Feng; Ying, Lei; Li, Zhenye; Zhong, Wenkai; Brabec, Christoph; Huang, Fei; Cao, Yong (ACS Applied Materials and Interfaces, 2018)
wo novel wide-band gap donor-acceptor-type conjugated copolymers, PTzBI-S and PTzBI-Ph, are designed and synthesized, based on alkylthio-thienyl- or alkylphenyl-substituted benzodithiophene (BDT) derivatives as the electron-donating unit and pyrrolo[3,4-f]benzotriazole-5,7(6H)-dione as the electron-withdrawing unit. The as-generated copolymers show the comparable optical and electrochemical properties. The alkylthio-thienyl-substituted BDT unit facilities a benign decrease of the highest occupied molecular orbital (HOMO) levels. This consequently enhances open-circuit voltages (VOC) over 0.9 V in relevant solar cells with the fullerene acceptor ([6, 6]-phenyl-C71-butyric acid methyl ester, PC71BM) or the nonfullerene acceptor (3,9-bis(2-methylene-(3-(1,1-dicyanomethylene)-indanone))-5,5,11,11-tetrakis(4-hexylphenyl)-dithieno[2,3-d:2′,3′-d′]-s-indaceno[1,2-b:5,6-b′]dithiophene, ITIC). The combination studies of Fourier transform photocurrent spectroscopy and electroluminescence further rationalize the VOC difference between solar cells with fullerene and nonfullerene acceptors. An impressively high power conversion efficiency of 10.19% is obtained for the device based on PTzBI-Ph:ITIC, outperforming the 8.84% achieved by the PC71BM-based device. Our results demonstrate that the modification of substituents of BDT units can effectively decrease the HOMO level and consequently improve VOC, ultimately allowing the attainment of high-efficiency polymer solar cel
Keywords: side-chain modification; wide-band gap copolymers; polymer solar cells; pyrrolo[3; 4- f]benzotriazole-5; 7(6 H)-dione

Improved High-Efficiency Perovskite Planar Heterojunction Solar Cells via Incorporation of a Polyelectrolyte Interlayer - Zhang, Hong; Azimi, Seyed Hamed; Hou, Yi; Ameri, Tayebeh; Przybilla, Thomas; Spiecker, Erdmann; Kraft, Mario; Scherf, Ullrich; Brabec, Christoph (Chemistry of Materials, 2014)
No abstract available for this article

Improved properties of phosphor-filled luminescent down-shifting layers: Reduced scattering, optical model, and optimization for PV application - Solodovnyk, Anastasiia; Lipovsek, Benjamin; Forberich, Karen; Stern, Edda; Krc, Janez; Batentschuk, Miroslaw; Topic, Marko; Brabec, Christoph (SPIE Micro+Nano Materials, Devices, and Applications Symposium, 2015)
We studied the optical properties of polymer layers filled with phosphor particles in two aspects. First, we used two different polymer binders with refractive indices n = 1.46 and n = 1.61 (λ = 600 nm) to decrease Δn with the phosphor particles (n = 1.81). Second, we prepared two particle size distributions D50 = 12 μm and D50 = 19 μm. The particles were dispersed in both polymer binders in several volume concentrations and coated onto glass with thicknesses of 150-600 μm. We present further a newly developed optical model for simulation and optimization of such luminescent down-shifting (LDS) layers. The model is developed within the ray tracing framework of the existing optical simulator CROWM (Combined Ray Optics/Wave Optics Model), which enables simulation of standalone LDS layers as well as complete solar cells (including thick and thin layers) enhanced by the LDS layers for an improved solar spectrum harvesting. Experimental results and numerical simulations show that the layers of the higher refractive index binder with larger particles result in the highest optical transmittance in the visible light spectrum. Finally we proved that scattering of the phosphor particles in the LDS layers may increase the overall light harvesting in the solar cell. We used numerical simulations to determine optimal layer composition for application in realistic thin-film photovoltaic devices. Surprisingly LDS layers with lower measured optical transmittance are more efficient when applied onto the solar cells due to graded refractive index and efficient light scattering. Therefore, our phosphor-filled LDS layers could possibly complement other light-coupling techniques in photovoltaics.
Keywords: absorptance; effective scattering approach; luminescent down-shifting (LDS); Mie scattering; organic solar cell; phosphor particles; ray-tracing; refractive index; transmittance; transparent binder

Improving spray coated organic photodetectors performance by using 1,8-diiodooctane as processing additive - Montenegro Benavides, Cindy; Rechberger, Stefanie; Spiecker, Erdmann; Berlinghof, Marvin; Unruh, Tobias; Biele, Markus; Schmidt, Oliver; Brabec, Christoph; Tedde, Sandro F. (Organic Electronics, 2018)
In this work, we present and support the positive influence of 1,8-diiodooctane (DIO) as processing additive for the fabrication of solution processed near infrared (NIR) organic photodiodes (OPDs) based on the spray-coated blend of [6,6]phenyl-C70-butyric acid methyl ester (PC70BM) and poly[(2,5-bis(2-hexyldecyl)-2,3,5,6-tetrahydro-3,6-diox-opyrrolo[3,4-c]pyrrole-1,4-diyl)-alt-([2,2’:5′,2″-terthiophene]-5,5″-diyl)] (PDPP3T). Transmission electron microscopy (TEM) analysis show that the use of DIO improves donor–acceptor interfaces in the bulk heterojunction (BHJ) layer. Besides the enhancement of electron/hole transport pathways that leads to higher efficiencies, it reduces significantly the roughness of spray coated layers. The External Quantum Efficiency (EQE) is increased up to 35% at 900 nm and the dark current is decreased one order of magnitude in comparison to the reference down to 20 nA/cm2 at -5 V. The OPD's detectivity is increased from 1.66×1011 Jones to 3.34×1012 Jones and the linearity response is improved. A comprehensive morphological and electro-optical characterization of the generated layers and devices is the main focus of this work.
Keywords: DIO additive; organic photodetectors; spray coating; BHJ morphology

Impurities and Their Influence on the Co-evaporation of Methylammonium Perovskite Thin-film Solar Cells - Borchert, Juliane; Levchuk, Ievgen; Snoek, Lavina C.; Rothmann, Mathias Uller; Snaith, Henry J.; Brabec, Christoph; Herz, Laura M.; Johnston, Michael B. (International Conference on Hybrid and Organic Photovoltaics, 2019)
In recent years power conversion efficiencies for lab-scale metal halide perovskite solar cells have risen rapidly to over 23.7% [1]. These perovskite semiconductors are advantageous due to their low Shockley-Read-Hall recombination rates, high absorption coefficients across much of the solar spectrum and high charge-carrier diffusion lengths and mobilities [2]. The planar heterojunction solar cell is a simple and popular design with the first efficient perovskite solar cell of this architecture fabricated by co-evaporation of lead iodide and methylammonium iodide (MAI) [3]. Co-evaporation of perovskite thin-films is carried out in a vacuum chamber in which two or more precursors are heated simultaneously until they evaporate. The vapours rise up and condense on the substrate which is mounted above on a rotating sample holder. Co-evaporation is a scalable process which is already used in a number of other industries and films grown via co-evaporation are uniform, have no pin-holes and are smooth over large areas [4]. This process is also solvent free which makes it fully additive and avoids the washing off of underlying layers. This is especially useful when complex layer stacks are being fabricated, for example in tandem solar cells. An important factor that will influence the commercial success of metal halide perovskite solar cells is the scalability of the deposition processes. To be able to scale a process, the reproducibility and yield of that process are both critical. In the past, several groups have encountered challenges with the evaporation of methylammonium iodide, including a variability of the chamber pressure and problems with the rate control of MAI deposition. The established method for the control of thermal evaporation processes, such as co-evaporation, is the use of quartz micro balances (QMBs). Unfortunately, it has frequently been reported, that these do not yield reliable results when used to monitor MAI evaporation. To resolve some of these challenges, we studied the role of impurities during the co-evaporation and their influence on the control of the evaporation process. To do this, we first characterised the precursor itself using nuclear magnetic resonance (NMR) and mass spectroscopy. We then evaporated perovskite films and monitored the evaporation process using quartz micro balances which are the established approach for rate control in thin-film deposition. Additionally we employed a residual gas analysis system to perform mass spectroscopy of the gas in the vacuum chamber during the evaporation. After the evaporation we characterised the deposited thin-films using a variety of methods, including scanning electron microscopy and X-ray diffraction. Finally we fabricated solar cells using MAI of different purity and measured their power conversion efficiency. Using this approach we are able to shed light on the influence of impurities in MAI on the co-evaporation of methylammonium lead iodide and the final solar cell performance. We are furthermore able to make suggestions on how to improve the control of the MAI evaporation and therefore the control over and reproducibility of the co-evaporation of methylammonium lead iodide thin-films.

Impurity Tracking Enables Enhanced Control and Reproducibility of Hybrid Perovskite Vapor Deposition. - Borchert, Juliane; Levchuk, Ievgen; Snoek, Lavina C.; Rothmann, Mathias Uller; Haver, Renee; Snaith, Henry J.; Brabec, Christoph; Herz, Laura M.; Johnston, Michael B. (ACS Applied Materials and Interfaces, 2019)
Metal halide perovskite semiconductors have the potential to enable low-cost, flexible, and efficient solar cells for a wide range of applications. Physical vapor deposition by co-evaporation of precursors is a method that results in very smooth and pinhole-free perovskite thin films and allows excellent control over film thickness and composition. However, for a deposition method to become industrially scalable, reproducible process control and high device yields are essential. Unfortunately, to date, the control and reproducibility of evaporating organic precursors such as methylammonium iodide (MAI) have proved extremely challenging. We show that the established method of controlling the evaporation rate of MAI with quartz microbalances (QMBs) is critically sensitive to the concentration of the impurities MAH2PO3 and MAH2PO2 that are usually present in MAI after synthesis. Therefore, controlling the deposition rate of MAI with QMBs is unreliable since the concentration of such impurities typically varies from one batch of MAI to another and even during the course of a deposition. However once reliable control of MAI deposition is achieved, we find that the presence of precursor impurities during perovskite deposition does not degrade the solar cell performance. Our results indicate that as long as precursor deposition rates are well controlled, physical vapor deposition will allow high solar cell device yields even if the purity of precursors changes from one run to another.
Keywords: solar cells; perovskites; hybrid metal-halide perovskites; co-evaporation; impurities; thermal evaporation; methylammonium iodide; residual gas analysis

Increased open-circuit voltage of organic solar cells by reduced donor-acceptor interface area - Vandewal, Koen; Widmer, Johannes; Heumüller, Thomas; Brabec, Christoph; Mcgehee, Michael D.; Leo, Karl; Riede, Moritz; Salleo, Alberto (Advanced Materials, 2014)
The charge carrier lifetime in small molecule: C photovoltaic devices is increased by reducing the physical interface area availabe for recombination. For donor contents below 10%, the gain in open-circuit voltage (V) depends logarithmically on the interface area while the energy of the interfacial charge-transfer state E remains invariant. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: bulk heterojunction; charge-transfer state; open-circuit voltage; organic solar cells

Increased thermal stabilization of polymer photovoltaic cells with oligomeric PCBM - Ramanitra, Hasina H.; Dowland, Simon A.; Bregadiolli, Bruna A.; Salvador, Michael; Silva, Hugo Santos; Begue, Didier; Graeff, Carlos F. O.; Peisert, Heiko; Chasse, Thomas; Rajoelson, Sambatra; Osvet, Andres; Brabec, Christoph; et al. (Journal of Materials Chemistry C, 2016)
The first oligomerisation of phenyl-C-butyric acid methyl ester (PCBM) using a facile atom transfer radical addition polymerization (ATRAP) and its exploitation for organic photovoltaic devices is described. Oligo(phenyl-C-butyric acid methyl ester)-alt-[1,4-bis(bromomethyl)-2,5-bis(octyloxy)benzene] (OPCBMMB) shows opto-electronic properties equivalent to those of PCBM but has a higher glass transition temperature. When mixed with various band gap semiconducting polymers, OPCBMMB delivers performances similar to PCBM but with an enhanced stabilization of the bulk heterojunction in photovoltaic devices on plastic substrates under thermal stress, regardless of the degree of crystallinity of the polymer and without changing opto-electronic propertie
Keywords: Engineering controlled terms: Atom transfer radical polymerization; Electronic properties; Energy gap; Esters; Free radical reactions; Glass transition; Heterojunctions; Oligomers; Photoelectrochemical cells; Photovoltaic cells; Semiconducting polymers; Stabilization; Substrates Atom transfer radical addition; Bulk heterojunction; Degree of crystallinity; Optoelectronic properties; Organic photovoltaic devices; Photovoltaic devices; Polymer photovoltaic cells; Thermal stabilization Engineering main heading: Butyric acid

Increasing the Fill Factor of Inverted P3HT:PCBM Solar Cells Through Surface Modification of Al-Doped ZnO via Phosphonic Acid-Anchored C60 SAMs - Stubhan, Tobias; Salinas Batallas, Michael; Ebel, Alexander; Krebs, Frederick C.; Hirsch, Andreas; Halik, Marcus; Brabec, Christoph (Advanced Energy Materials, 2012)
The influence of aluminum-doped zinc oxide (AZO) electron extraction layers modified with self-assembled monolayers (SAMs) on inverted polymer solar cells is investigated. It is found that AZO modification with phosphonic acid anchored Fullerene–SAMs leads to a reduction of the series resistance, while increasing the parallel resistance. This results in an increased efficiency from 2.9 to 3.3%.
Keywords: Al-doped ZnO; Aluminum-doped zinc oxide; Electron extraction; Fill factor; Inverted polymer solar cells; Parallel resistance; Phosphonic; Series resistances Engineering controlled terms: Electric resistance; Self assembled monolayers; Solar cells; Zinc oxide Engineering main heading: Organic acids

Indacenodithienothiophene-Based Ternary Organic Solar Cells - Gasparini, Nicola; García-Rodríguez, Amaranda; Prosa, Mario; Bayseç, Sebnem; Cando, Alex Palma; Katsouras, Athanasios; Avgeropoulos, Apostolos; Pagona, Georgia; Gregoriou, Vasilis G.; Chochos, Christos L.; Allard, Sybille; Scherf, Ullrich; et al. (Frontiers in Energy Research, 2017)
One of the key aspects to achieve high efficiency in ternary bulk-hetorojunction solar cells is the physical and chemical compatibility between the donor materials. Here, we report the synthesis of a novel conjugated polymer (P1) containing alternating pyridyl[2,1,3]thiadiazole between two different donor fragments, dithienosilole and indacenodithienothiophene (IDTT), used as a sensitizer in a host system of indacenodithieno[3,2-b]thiophene,2,3-bis(3-(octyloxy)phenyl)quinoxaline (PIDTTQ) and [6,6]-phenyl C70 butyric acid methyl ester (PC71BM). We found that the use of the same IDTT unit in the host and guest materials does not lead to significant changes in the morphology of the ternary blend compared to the host binary. With the complementary use of optoelectronic characterizations, we found that the ternary cells suffer from a lower mobility-lifetime (μτ) product, adversely impacting the fill factor. However, the significant light harvesting in the near infrared region improvement, compensating the transport losses, results in an overall power conversion efficiency enhancement of 7% for ternary blends as compared to the PIDTTQ:PC71BM devices.
Keywords: organic solar cells; ternary devices; OPV; IDTT; organic electronics

Industrially scalable and cost-effective Mn2+ doped ZnxCd1-xS/ZnS nanocrystals with 70% photoluminescence quantum yield, as efficient down-shifting materials in photovoltaics - Levchuk, Ievgen; Wuerth, C.; Krause, F.; Osvet, Andres; Batentschuk, Miroslaw; Resch-Genger, Ute; Kolbeck, Claudia; Herre, Patrick; Steinrück, Hans-Peter; Peukert, Wolfgang; Brabec, Christoph (Energy and Environmental Science, 2016)
We present colloidally stable and highly luminescent ZnxCd1-xS:Mn/ZnS core–shell nanocrystals (NCs) synthesized via a simple non-injection one-pot, two-step synthetic route, which can be easily upscaled. A systematic variation of the reaction component, parameters and thickness of the ZnS shell yielded doped nanocrystals with a very high photoluminescence quantum yield ( extgreekFpl) of 70%, which is the highest value yet reported for these Mn-doped sulfide-semiconductor NCs. These materials can be synthesized with high reproducibility in large quantities of the same high quality, i.e., the same extgreekFpl using accordingly optimized reaction conditions. The application of these zero-reabsorption high quality NCs in the light conversion layers, deposited on top of a commercial monocrystalline silicon (mono-Si) solar cell, led to a significant enhancement of the external quantum efficiency (EQE) of this device in the ultraviolet spectral region between 300 and 400 nm up to ca. 12%. EQE enhancement is reflected by an increase in the power conversion efficiency (PCE) by nearly 0.5 percentage points and approached the theoretical limit (0.6%) expected from down-shifting for this Si solar cell. The resulting PCE may result in a BoM (bill of materials) cost reduction of app. 3% for mono-Si photovoltaic modules. Such small but distinct improvements are expected to pave the road for an industrial application of doped semiconductor NCs as cost-effective light converters for silicon photovoltaic (PV) and other optoelectronic applications.
EAM Import::2019-03-14

Industrial viability of single-component organic solar cells - He, Yakun; Li, Ning; Heumüller, Thomas; Wortmann, Jonas; Hanisch, Benedict; Aubele, Anna; Lucas, Sebastian; Feng, Guitao; Jiang, Xudong; Li, Weiwei; Bäuerle, Peter; Brabec, Christoph (Joule, 2022)
Although the power conversion efficiencies (PCEs) of bulk heterojunction (BHJ) organic solar cells (OSCs) continue increasing toward the 20% milestone, important factors for industrial application are mostly neglected, such as photostability and cost potential. Single-component OSCs (SCOSCs) employing materials with chemically bonded donor and acceptor moieties successfully overcome the immiscibility between the donor and the acceptor as well as the resultant self-aggregation under external stress. To inspire a broader interest, the industrial figure of merit (i-FoM) of BHJ OSCs and the corresponding SCOSCs is calculated and analyzed, which includes PCE, photostability, and synthetic complexity (SC) index. Despite having a slightly more complex synthesis, all SCOSCs exhibit increased i-FoM values compared with the corresponding BHJ OSCs, and with the increase in efficiency, SCOSCs possess further potential for a higher i-FoM value. With the excellent photostability of nearly all investigated single-component semiconductors, SCOSCs are coming into the focus of attention for industrial utilization.
CRIS-Team Scopus Importer:2022-07-01
Keywords: i-FoM; industrial figure of merit; PCE; photostability; power conversion efficiency; SC index; SCOSCs; single-component organic solar cells; synthetic complexity index

Influence of a shunt on the electrical behavior in thin film photovoltaic modules - A 2D finite element simulation study - Fecher, Frank; Romero, Alexander Perez; Brabec, Christoph; Buerhop-Lutz, Claudia (Solar Energy, 2014)
Despite significant efficiency improvements of thin film photovoltaic modules over the last years, this technology struggles with the same problem - shunts that lower the output power dramatically. In this work, we studied the influence of a single shunt on the module performance by electrical 2D finite element simulations. By varying parameters such as irradiance, shunt resistance, shunt position and shunt size a profound understanding of the shunt's impact on the module performance was achieved. Most remarkable is the dependence of the module's output performance on the local shunt position, which can make up to 25% of the losses. Such high losses are caused by "circular" lateral currents in the electrode layers that spread in the shunted as well as into the neighboring cells. We show that the shunt's position inside the cell determines the geometry of the lateral currents and, consequently, the shunt's influence region.The finite element model presented here was developed on the basis of CIGS thin film modules, but the results are qualitatively valid for other monolithically series connected thin film module technologies like CdTe or a-Si:H. © 2014 Elsevier Ltd.
Keywords: 2D finite element simulation; Electrical performance; Shunt defect; Thin film photovoltaic module

Influence of a ternary donor material on the morphology of a P3HT:PCBM blend for organic photovoltaic devices - Machui, Florian; Rathgeber, Silke; Li, Ning; Ameri, Tayebeh; Brabec, Christoph (Journal of Materials Chemistry, 2012)
A comparison of grazing incidence wide-angle X-ray scattering (GiWAXS) and differential scanning calorimetric measurements (DSC) was used to identify the influence of a dominantly amorphous small band gap polymer material poly[2,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b′]dithiophene) -alt-4,7(2,1,3-benzothiadiazole)] (PCPDTBT) on the crystallinity of a semi-crystalline polymer/fullerene composite. In binary blends the low band gap polymer does not influence the crystalline part of P3HT, but does influence the crystallinity of the fullerene. In ternary blends, a significant drop of the PCBM crystallinity is observed with increasing PCPDTBT content. Adding more than 20 wt% PCPDTBT to a P3HT:PCBM blend leads to a dramatic reduction of device efficiency, mainly due to short circuit current density and fill factor losses. This deterioration is attributed to the fact that addition of more than 20 wt% PCPDTBT to the host system strongly reduces crystallinity of the fullerene phase and electron transport in the ternary system. © 2012 The Royal Society of Chemistry.
Keywords: 2; 1; 3-Benzothiadiazole; Binary blends; Crystallinities; Device efficiency; Differential scanning calorimetric measurements; Electron transport; Fill factor; Grazing incidence; Low bandgap polymers; Organic photovoltaic devices; Semi-crystalline polymer; Small band gap polymer; Ternary blends; Wide angle X-ray scattering Engineering controlled terms: Crystalline materials; Energy gap; Fullerenes; Polymer blends Engineering main heading: Polymers

Influence of blend microstructure on bulk heterojunction organic photovoltaic performance - Brabec, Christoph; Heeney, Martin; Mcculloch, Iain; Nelson, Jenny (Chemical Society Reviews, 2011)
The performance of organic photovoltaic devices based upon bulk heterojunction blends of donor and acceptor materials has been shown to be highly dependent on the thin film microstructure. In this tutorial review, we discuss the factors responsible for influencing blend microstructure and how these affect device performance. In particular we discuss how various molecular design approaches can affect the thin film morphology of both the donor and acceptor components, as well as their blend microstructure. We further examine the influence of polymer molecular weight and blend composition upon device performance, and discuss how a variety of processing techniques can be used to control the blend microstructure, leading to improvements in solar cell efficiencies. © 2011 The Royal Society of Chemistry.

Influence of pre-existing damages on the degradation behavior of crystalline silicon photovoltaic modules - Camus, Christian; Adegbenro, Ayodeji; Ermer, Jakob; Suryaprakash, Vignesh; Brabec, Christoph; Hauch, Jens (Journal of Renewable and Sustainable Energy, 2018)
In this paper, the influence of pre-existing crystalline damage, such as cracked or broken cells or soldering failures, as they are frequently observed in operating photovoltaic (PV) plants, on the degradation behavior of mono- and polycrystalline silicon PV modules is investigated. In particular, it is analyzed if and to what extent predamage introduced prior to lamination propagates upon stress exposure. Therefore, the pre-damaged modules are exposed to various accelerated aging conditions in order to analyze the impact of the pre-damage on the degradation behavior under the respective aging scenario. In order to separate the influence of the pre-damage from composition-induced influences, the choice of materials used in the modules is varied. These investigations reveal that none of the accelerated aging tests causes any change in the pre-existing damage. In fact, the degradation behavior and rate rather depended on the choice of the module components than on the nature of the predamage. Finally, these results are compared with indoor and outdoor results obtained from other studies<br

Influence of the bridging atom on the performance of a low-bandgap bulk heterojunction solar cell - Scharber, Markus C.; Koppe, Markus; Gao, Jia; Cordella, Fabrizio; Loi, Maria A.; Denk, Patrick; Morana, Mauro; Egelhaaf, Hans-Joachim; Forberich, Karen; Dennler, Gilles; Gaudiana, Russ; Waller, Dave; et al. (Advanced Materials, 2010)
X=C or Si(Chemical equation presented)Replacing a carbon atom with silicon (see figure) on the main chain of a conjugated polythiophene gives a polysilole with higher crystallinity, improved charge transport, reduced bimolecular recombination, and reduced formation of charge-transfer complexes when blended with a fullerene derivative. Optimized bulk heterojunction solar cells using this blend give certified efficiencies of 5.2% under AMI.5 illumination. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA.

Influence of the Hole Transporting Layer on the Thermal Stability of Inverted Organic Photovoltaics Using Accelerated-Heat Lifetime Protocols - Hermerschmidt, Felix; Savva, Achilleas; Georgiou, Efthymios; Tuladhar, Sachetan M.; Durrant, James R.; Mcculloch, Iain; Bradley, Donal D. C.; Brabec, Christoph; Nelson, Jenny; Choulis, Stelios A. (ACS Applied Materials and Interfaces, 2017)
High power conversion efficiency (PCE) inverted organic photovoltaics (OPVs) usually use thermally evaporated MoO3 as a hole transporting layer (HTL). Despite the high PCE values reported, stability investigations are still limited and the exact degradation mechanisms of inverted OPVs using thermally evaporated MoO3 HTL remain unclear under different environmental stress factors. In this study, we monitor the accelerated lifetime performance under the ISOS-D-2 protocol (heat conditions 65 °C) of nonencapsulated inverted OPVs based on the thiophene-based active layer materials poly(3-hexylthiophene) (P3HT), poly[[4,8-bis[(2-ethylhexyl)oxy]benzo[1,2-b:4,5-b′]dithiophene-2,6-diyl][3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3,4-b]thiophenediyl]] (PTB7), and thieno[3,2-b]thiophene-diketopyrrolopyrrole (DPPTTT) blended with [6,6]-phenyl C71-butyric acid methyl ester (PC[70]BM). The presented investigation of degradation mechanisms focus on optimized P3HT:PC[70]BM-based inverted OPVs. Specifically, we present a systematic study on the thermal stability of inverted P3HT:PC[70]BM OPVs using solution-processed poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) and evaporated MoO3 HTL. Using a series of measurements and reverse engineering methods, we report that the P3HT:PC[70]BM/MoO3 interface is the main origin of failure of the P3HT:PC[70]BM-based inverted OPVs under intense heat conditions, a trend that is also observed for the other two thiophene-based polymers used in this study. © 2017 American Chemical Society.
Keywords: Butyric acid; Conducting polymers; Degradation; Hole mobility; Molybdenum oxide; Reverse engineering; Stability; Thiophene; Degradation mechanism; Hole transporting layers; Inverted structure; lifetime; Organic photovoltaics; Thermodynamic stability

Influence of the Irradiance on the Detection and Performance of PID-Affected PV-Modules - Buerhop-Lutz, Claudia; Pickel, Tobias; Wenz, F.; Zetzmann, Cornelia; Hauch, Jens; Camus, Christian; Brabec, Christoph (35th European Photovoltaic Solar Energy Conference and Exhibition, 2018)
Potential induced degradation (PID) is still a severe problem in many PV-installations and a huge financial risk for investors and plant-owners if not detected early. In previous investigations it was shown that thermography, conducted with handheld or drone mounted IR-cameras, is a fast and reliable tool to detect PID affected PV-modules on site and estimate their remaining electrical power during normal plant operation. In this work we show how to improve the sensitivity of IR- and various other imaging techniques by using the characteristic behavior of PID affected cells regarding the different excitation forces, i.e. solar irradiance for IR- and electric current for DLIT- and EL-measurements. Furthermore, we address the implications of this specific behavior by simulating the energy yield of several PID affected PV-strings based on real monitoring data for two inspected sites and suggest carrying out the measurements on site- and under failure- relevant conditions rather than standard test conditio
Keywords: Performance; Energy Yield; Thermography; Potential Induced Degradation; EL Imaging

Influence of the Module Temperature on the Performance and EL-Image of Precracked PV-Modules - Buerhop-Lutz, Claudia; Krause, M.; Winkler, T.; Hauch, Jens; Camus, Christian; Brabec, Christoph (35th European Photovoltaic Solar Energy Conference and Exhibition, 2018)
EL-imaging is a valuable tool to analyze PV-modules for the presence of cracked cells. Normally, these inspections are done in air-conditioned labs or at cool nights outdoors. However, the PV-modules are supposed to generate energy outdoors in the field. Therefore, they operate at significantly elevated temperatures which are much higher than the temperatures at the inspection time. In order to investigate the temperature influence on the performance of precracked PV-modules, EL-images and IV-curves were recorded of warm and mechanically loaded modules. The study illustrates that the performance of cracked cells changes with temperature and pressure. There is the tendency that modules at elevated temperatures perform better than those at low temperatures under the same loading situatio
Keywords: Performance; Temperature; Mechanical Load; Cracks; Electro-Luminescence (EL)

Influence of Thiazole-Modified Carbon Nitride Nanosheets with Feasible Electronic Properties on Inverted Perovskite Solar Cells. - Cruz, Daniel; García Cerrillo, José; Kumru, Baris; Li, Ning; Perea, Jose Dario; Schmidt, Bernhard V. K. J.; Lauermann, Iver; Brabec, Christoph; Antonietti, Markus (Journal of the American Chemical Society, 2019)
Effective, solution-processable designs of interfacial electron-transporting layers (ETLs) or hole-blocking layers are promising tools in modern electronic devices, e.g., to improve the performance, cost, and stability of perovskite-based solar cells. Herein, we introduce a facile synthetic route of thiazole-modified carbon nitride with 1.5 nm thick nanosheets which can be processed to a homogeneous, metal-free ETL for inverted perovskite solar cells. We show that thiazole-modified carbon nitride enables electronic interface enhancement via suppression of charge recombination, achieving 1.09 V in Voc and a rise to 20.17 mA/cm2 in Jsc. Hence, this report presents the successful implementation of a carbon-nitride-based structure to boost charge extraction from the perovskite absorber toward the electron transport layer in p-i-n devices

Influence of tin oxide decoration on the junction conductivity of silver nanowires - Vogl, Lilian; Kalancha, Violetta; Schweizer, Peter; Denninger, Peter; Wu, Mingjian; Brabec, Christoph; Forberich, Karen; Spiecker, Erdmann (Nanotechnology, 2023)
Flexible electrodes using nanowires (NWs) suffer from challenges of long-term stability and high junction resistance which limit their fields of applications. Welding via thermal annealing is a common strategy to enhance the conductivity of percolated NW networks, however, it affects the structural and mechanical integrity of the NWs. In this study we show that the decoration of NWs with an ultrathin metal oxide is a potential alternative procedure which not only enhances the thermal and chemical stability but, moreover, provides a totally different mechanism to reduce the junction resistance upon heat treatment. Here, we analyze the effect of SnO x decoration on the conductance of silver NWs and NW junctions by using a four-probe measurement setup inside a scanning electron microscope. Dedicated transmission electron microscopy analysis in plan-view and cross-section geometry are carried out to characterize the nanowires and the microstructure of the junctions. Upon heat treatment the junction resistance of both plain silver NWs and SnO x -decorated NWs is reduced by around 80%. While plain silver NWs show characteristic junction welding during annealing, the SnO x -decoration reduces junction resistance by a solder-like process which does not affect the mechanical integrity of the NW junction and is therefore expected to be superior for applications.
CRIS-Team Scopus Importer:2023-02-24
Keywords: electrical measurements; electron microscopy; junctions; nanowires

Infrared Absorption Imaging of Water Ingress Into the Encapsulation of (Opto-)Electronic Devices - Hepp, Johannes; Vetter, Andreas; Langner, Stefan; Woiton, Michael; Jovicic, Gordana; Burlafinger, Klaus; Hauch, Jens; Camus, Christian; Egelhaaf, Hans-Joachim; Brabec, Christoph (IEEE Journal of Photovoltaics, 2019)
Water ingress into the encapsulation of electronic devices is a serious issue, especially for organic and perovskite-based electronics. In order to guide the development of suitable barrier materials and design, a reliable, fast, and non-destructive analysis tool is required. In this work, an imaging setup is presented, which is based on selective infrared (IR) radiation sources and a mid-IR sensitive camera that uses the absorption hand of water around 1920 nm and a reference band. This system enables us to monitor the distribution of water concentration inside the packaging of devices and its change over time. Our measurement is capable of detecting the local presence of water down to the mg/m(2) concentration range in a wide variety of encapsulation materials. The new tool allows identifying the pathways of moisture ingress into the encapsulation along with the corresponding diffusion coefficient. Thus, it provides fast and reliable analysis of humidity related failure mechanisms, and consequently helps to improve the design of encapsulation materials and processes.
Keywords: Degradation; diffusion processes; optical signal detection; organic photovoltaics (PVs); packaging

In(iii)-dictated formation of double Cs2AgxNa1−xFeyIn1−yCl6 perovskites - Stroyuk, Oleksandr; Raievska, Oleksandra; Barabash, Anastasiia; Hauch, Jens; Brabec, Christoph (Journal of Materials Chemistry C, 2023)
Stable double Cs2AgxNa1−xFeyIn1−yCl6 (CANFIC) microcrystalline perovskites were produced in air-open conditions. In(iii) was found to steer the precursor interaction exclusively towards single-phase solid-solution CANFIC perovskite microcrystals with well-controlled composition, even when present at a small amount (1%). CANFICs revealed sensitivity in the visible range with the lowest bandgap of 1.95 eV found for y = 0.99. Due to a combination of open-environment synthesis conditions, reliable compositional control, the abundant and relatively non-toxic character of constituents, stability, and absorbance in the visible spectral range, CANFIC perovskites show high promises for photovoltaic and photochemical applications.
CRIS-Team Scopus Importer:2023-06-23

Inkjet printed organic and perovskite photovoltaics—review and perspectives - Maisch, Philipp; Tam, Kai Cheong; Jang, DongJu; Steinberger, Marc; Yang, Fu; Brabec, Christoph; Egelhaaf, Hans-Joachim (Organic Flexible Electronics, 2021)
This chapter provides a review on digital printing of organic solar cells (OSCs) and perovskite solar cells (PSCs). It starts with a brief introduction to the fundamentals of both solar technologies. Highlighting the specific demands of many novel solar applications, the necessity to fabricate devices using cheap and most versatile techniques, such as drop-on-demand inkjet, is outlined. A short discussion on the fundamentals of inkjet technology provides the background for a literature overview on digitally printed OSCs and PSCs. The main part of this chapter describes the most significant achievements in the field and remaining challenges for inkjet fabrication of active layers, electron- as well as hole-transport layers and electrodes. An outlook on the perspectives that the combination of printed photovoltaics and inkjet has to offer concludes the chapter.<br
Keywords: Inkjet; organic photovoltaics; OPV; OSC; perovskite photovoltaics; PSC; printed solar cell; solar module; flexible electrode

Inkjet-printed polymer-based scattering layers for enhanced light outcoupling from top-emitting organic light-emitting diodes - Heinrichsdobler, Armin; Engelmayer, Manuel; Riedel, Daniel; Brabec, Christoph; Wehlus, Thomas (Proceedings Volume 10362, Organic Light Emitting Materials and Devices XXI; 103622B (2017), 2017)
High refractive index polymer-based scattering layers used as internal light extraction layers are a promising low-cost approach to enhance the luminous efficacy of organic light-emitting diodes (OLEDs). In order to avoid damaging of the OLED layers a structured and contactless deposition method for the polymer-based scattering layers is required. For enhanced lifetime of the devices the water diffusion through the scattering layer has to be eliminated by a structured patterning technique. Inkjet printing offers both a contactless and structured deposition. In this study we evaluate inkjet printing of nanocomposite polymer-based scattering layers for OLEDs. A detailed view on the material and process development is given. This involves an optimization of ink formulation, printing parameters as well as layer formation. The resulting haze values of the scattering layers at 550 nm vary between 40% and 90% for different layer thicknesses. The gain in external quantum efficacy of top-emitting OLEDs induced by light scattering compared to reference devices peaks at a factor of 2.3. The obtained results are discussed and verified by an optical volume scattering simulation model which will be presented in full detail. Also a parameter variation study and its impact on extraction efficiency will be shown.

Inkjet printed silver nanowire percolation networks as electrodes for highly efficient semitransparent organic solar cells - Maisch, Philipp; Tam, Kai Cheong; Lucera, Luca; Egelhaaf, Hans-Joachim; Scheiber, Horst; Maier, Eugen; Brabec, Christoph (Organic Electronics, 2016)
In this work, we demonstrate inkjet printing of silver nanowires (AgNW) with an average length of 10's of μm using industrial printheads with nozzle diameters in the same size range. The printed silver nanowire mesh reveals uniform distribution and a good balance between conductivity and transmittance, which is comparable to layers fabricated by conventional methods like slot-die or spray coating. Employing a novel AgNW ink formulation based on a high boiling alcohol allows printing directly on PEDOT:PSS and prevents nozzle clogging. Using silver nanowire meshes as bottom and top electrodes, a fully inkjet printed semitransparent organic solar cell with a power conversion efficiency of 4.3% for 1 cm area is demonstrated, which is the highest value reported so far for fully inkjet printed organic photovoltaic cells.
Keywords: Inkjet; Nanowire; Organic photovoltaics; Semitransparent electrode

Inkjet printing of highly conductive nanoparticle dispersions for organic electronics - Maisch, Philipp; Tam, Kai Cheong; Fecher, Frank W.; Egelhaaf, Hans Joachim; Brabec, Christoph; Scheiber, Horst; Maier, Eugen (12th International Congress on Molded Interconnect Devices, MID 2016, 2016)
Inkjet printing of conductive nanoparticle dispersions and their use in organic electronic devices for multiple purposes like contact pads and electrodes is demonstrated. In this context, we show the printing of semitransparent silver grid/Poly(3,4-ethylene-dioxythiophene) :poly(styrenesulfonate) (PEDOT:PSS) electrodes and their application in organic photovoltaics (OPV). The cell performance was optimized using finite element simulations accounting for electrical and optical layer properties as well as resolution restrictions given by the inkjet. Furthermore, we demonstrate inkjet printing of silver nanowires (AgNW) and their use as percolation electrode. Characterization reveals low sheet resistance of less than 20 Ω/□ together with a high specular transmittance of more than 90 %, indicating the excellent quality of the inkjet printed layers. Applying them as cathode and anode, fully inkjet printed semitransparent solar cells with power conversion efficiencies (PCE) of up to 4.3 % on an active area of > 1 cm are demonstrated.
Keywords: inkjet; organic photovoltaics; PEDOT:PSS; semitransparent electrode; silver grid; silver nanowires

Inkjet printing of multiple layers for large-scale, cadmium-free quantum dot light-emitting diodes - Hübner, Tobias; Brabec, Christoph; Göötz, Britta; Von Malm, Norwin (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
Quantum Dot Light Emitting Diodes (QDLEDs) are a promising alternative to the already established organic LEDs (OLEDs) in applications like automotive rear-lights. QDLEDs can exhibit higher luminance characteristics and superior operational stability. In order to be able to transfer the QDLEDs from their research state into market products, the oftenused Cadmium-containing QDs must be replaced by less toxic alternatives. Furthermore, the processing costs for the QDLEDs have to be minimized. We overcome both challenges by utilizing Indium Phosphide based QDs in the devices and applying inkjet-printing as a low-material consumption deposition technique. Inkjet-printing three layers of the stack design on top of each other proofs to be challenging concerning the layers homogeneity both macroscopically as well as microscopically. We present viable approaches for the ink formulation process, substrate-pretreatment steps and printing strategies to overcome wetting, dewetting and coffee-staining issues. The printed layers are investigated via topological and fluorescent tools and the successfully fabricated devices are examined via electrooptical measurements.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Area light source; Indium phosphide quantum dots; Inkjet-printing multiple layers; Quantum dot LEDs

Inkjet printing of semitransparent electrodes for photovoltaic applications - Maisch, Philipp; Tam, Kai C.; Lucera, Luca; Fecher, Frank W.; Egelhaaf, Hans-Joachim; Scheiber, Horst; Maier, Eugen; Brabec, Christoph (7th Conference on Organic Photovoltaic Devices, 2016)
In this work we compare two different semitransparent inkjet printed electrodes for organic photovoltaic (OPV) applications. We highlight the processing as well as layer properties of the most commonly used silver grid/PEDOT:PSS electrodes and a newly developed inkjet printed silver nanowire (AgNW) mesh. Application of the different electrode types in fully inkjet printed organic solar cells reveals the superior performance of the AgNWs. Using them as bottom and top electrode, semitransparent solar cells with power conversion efficiencies (PCE) of up to 4.3 % are demonstrated. Comparable devices with silver grid electrodes reach a maximum PCE of 3.6 %. We identify shading of the opaque silver grids, which cover ∼10 % of the device area, and thermal stress introduced by the curing of the silver grid top electrodes as main factors for the losses. Furthermore, the silver grids do not only lower the short circuit current of the solar cell, but are also visually obstructive. The newly developed inkjet printed AgNW percolation network electrodes show high transparency of over 90 % at a sheet resistance of less than 20 ω/□ and a very low haze of less than 3 %. This enables a clear view through semitransparent devices like organic light emitting diodes (OLEDS) or solar cells in which they can be use
Keywords: Inkjet; Organic photovoltaics; PEDOT:PSS; Semitransparent electrode; Silver grid; Silver nanowires

Innovative architecture design for high performance organic and hybrid multi-junction solar cells - Li, Ning; Spyropoulos, George D.; Brabec, Christoph (Proceedings Volume 10363,Organic, Hybrid, and Perovskite Photovoltaics XVIII, 2017)
The multi-junction concept is especially attractive for the photovoltaic (PV) research community owing to its potential to overcome the Schockley-Queisser limit of single-junction solar cells. Tremendous research interests are now focused on the development of high-performance absorbers and novel device architectures for emerging PV technologies, such as organic and perovskite PVs. It has been predicted that the multi-junction concept is able to boost the organic and perovskite PV technologies approaching the 20% and 30% benchmarks, respectively, showing a bright future of commercialization of the emerging PV technologies. In this contribution, we will demonstrate innovative architecture design for solution-processed, highly functional organic and hybrid multi-junction solar cells. A simple but elegant approach to fabricating organic and hybrid multi-junction solar cells will be introduced. By laminating single organic/hybrid solar cells together through an intermediate layer, the manufacturing cost and complexity of large-scale multi-junction solar cells can be significantly reduced. This smart approach to balancing the photocurrents as well as open circuit voltages in multi-junction solar cells will be demonstrated and discussed in detai

Inorganic Halide Perovskite Solar Cells: Progress and Challenges - Tian, Jingjing; Xue, Qifan; Yao, Qin; Li, Ning; Brabec, Christoph; Yip, Hin-Lap (Advanced Energy Materials, 2020)
All-inorganic perovskite semiconductors have recently drawn increasing attention owing to their outstanding thermal stability. Although all-inorganic perovskite solar cells (PSCs) have achieved significant progress in recent years, they still fall behind their prototype organic–inorganic counterparts owing to severe energy losses. Therefore, there is considerable interest in further improving the performance of all-inorganic PSCs by synergic optimization of perovskite films and device interfaces. This review article provides an overview of recent progress in inorganic PSCs in terms of lead-based and lead-free composition. The physical properties of all-inorganic perovskite semiconductors as well as the hole/electron transporting materials are discussed to unveil the important role of composition engineering and interface modification. Finally, a discussion of the prospects and challenges for all-inorganic PSCs in the near future is presented.
CRIS-Team Scopus Importer:2020-05-12
Keywords: inorganic perovskite; lead-based; lead-free perovskites; perovskite solar cells; perovskites

In Situ and Ex Situ Energy-Filtered Transmission Electron Microscopy Studies on the Nanomorpholgy Evolution of Organic Bulk Heterojunction Solar Cells - Harreiß, Christina; Langner, Stefan; Berlinghof, Marvin; Rechberger, Stefanie; Will, Johannes; Unruh, Tobias; Brabec, Christoph; Spiecker, Erdmann (Microscopy and Microanalysis, 2019)

In situ characterization methods for evaluating microstructure formation and drying kinetics of solution-processed organic bulk-heterojunction films - Güldal, Nusret Sena; Kassar, Thaer; Berlinghof, Marvin; Unruh, Tobias; Brabec, Christoph (Journal of Materials Research, 2017)
Recently, in situ characterization methods have attracted increasing attention, especially in organic photovoltaics (OPV) field, since they provide greater insight into the mechanism of film formation, thus help to identify optimized processing conditions used to process the most efficient organic bulk-heterojunction thin films. In combination with various powerful X-ray-based characterization methods, several studies observed the morphological changes under the influence of different processing conditions. In this review, we summarize the fundamentals and implementation of X-ray-based and optical characterization methods, utilized in in situ mode and introduce the reader a better overview of the information acquired from a given technique in terms of microstructure formation in OPV. While we give a chronological development of in situ characterization methods in the field of OPV, we discuss the interplay between thermodynamics of solutions and drying kinetics of different types of organic blends. © 2017 Materials Research Society.
Keywords: Characterization; Drying; Heterojunctions; Microstructure; Thermodynamics; Thin films; Characterization methods; In-situ characterization; Microstructure formation; Optical characterization; Organic bulk heterojunctions; Organic photovoltaics; Photovoltaic; Thermodynamics of solutions; In situ processing

In Situ Probing the Crystallization Kinetics in Gas-Quenching-Assisted Coating of Perovskite Films - Qiu, Shudi; Majewski, Martin; Dong, Lirong; Jang, DongJu; Le Corre, Vincent Marc; García Cerrillo, José; Ronsin, Olivier J.J.; Yang, Fu; Guo, Fei; Zhang, Kaicheng; Lüer, Larry; Harting, Jens; et al. (Advanced Energy Materials, 2024)
The pursuit of commercializing perovskite photovoltaics is driving the development of various scalable perovskite crystallization techniques. Among them, gas quenching is a promising crystallization approach for high-throughput deposition of perovskite films. However, the perovskite films prepared by gas-quenching assisted blade coating are susceptible to the formation of pinholes and frequently show inferior crystallinity if the interplay between film coating, film drying, and crystallization kinetics is not fully optimized. That arguably requires a thorough understanding of how single processing steps influence the crystallization kinetics of printed perovskite films. Here, in situ optical spectroscopies are integrated into a doctor-blading setup that allows to real-time monitor film formation during the gas-quenching process. It is found that the essential role of gas quenching treatment is in achieving a smooth and compact perovskite film by controlling the nucleation rate. Moreover, with the assistance of phase-field simulations, the role of excessive methylammonium iodide is revealed to increase grain size by accelerating the crystal growth rate. These results show a tailored control of crystal growth rate is critical to achieving optimal film quality, leading to fully printed solar cells with a champion power conversion efficiency of 19.50% and mini solar modules with 15.28% efficiency are achieved.
CRIS-Team Scopus Importer:2024-01-12
Keywords: blade coating; fully printed perovskite photovoltaics; gas quenching; in situ techniques; phase-field simulations

In-situ X-ray diffraction analysis of the recrystallization process in Cu2ZnSnS4nanoparticles synthesised by hot-injection - Brandl, Marco; Ahmad, Rameez; Distaso, Monica; Azimi, Seyed Hamed; Hou, Yi; Peukert, Wolfgang; Brabec, Christoph; Hock, Rainer (Thin Solid Films, 2015)
Kesterite CuZnSnS(CZTS) is a promising material for thin film solar cell applications. The biggest advantages of this compound lie in the abundance and non-toxicity of the contained elements. Low temperature hot injection synthesis can provide an economic way to produce CZTS nanoparticles for application in solution processed solar cells. Powder X-ray diffraction (PXRD) measurements on the as-synthesised particles suggest that the crystal structure is cubic and can be best described as sphalerite-like. This means that the cations in the CZTS are statistically distributed on the cation sites of the crystal lattice rather than well-ordered like in the tetragonal kesterite structure. An in-situ PXRD measurement while annealing the particles up to 550 °C revealed a recrystallization process that transforms the structure from cubic to tetragonal meaning an ordering of the cations.
Keywords: Copper zinc tin sulphide; Cubic phase; Hot-injection synthesis; In-situ; Phase transition; Tetragonal phase; X-ray diffraction

In-Situ X-ray Diffraction Analysis of the Recrystallization Process in Cu2ZnSnS4 Nano Particles Synthesized by Hot-Injection - Brandl, Marco; Ahmad, Rameez; Distaso, Monica; Azimi, Hamed; Hou, Yi; Peukert, Wolfgang; Brabec, Christoph; Hock, Rainer (Thin Solid Films, 2015)
Kesterite Cu2ZnSnS4 (CZTS) is a promisingmaterial for thin film solar cell applications. The biggest advantages of this compound lie in the abundance and non-toxicity of the contained elements. Low temperature hot injection synthesis can provide an economic way to produce CZTS nanoparticles for application in solution processed solar cells. Powder X-ray diffraction (PXRD) measurements on the as-synthesised particles suggest that the crystal structure is cubic and can be best described as sphalerite-like. This means that the cations in the CZTS are statistically distributed on the cation sites of the crystal lattice rather than well-ordered like in the tetragonal kesterite structure. An in-situ PXRD measurement while annealing the particles up to 550 °C revealed a recrystallization process that transforms the structure from cubic to tetragonal meaning an ordering of the cations.
EAM Import::2019-03-13

Instantaneous charge separation in non-fullerene acceptor bulk-heterojunction of highly efficient solar cells - Franco, V. A. Camargo; Gasparini, Nicola; Nagahara, Tetsuhiko; Lueer, Larry; Cerullo, Giulio; Brabec, Christoph (205, 2019)
Using broadband transient absorption in a high efficiency (>11%) photovoltaic blend with a non-fullerene acceptor, we observe instantaneous (sub-30 fs) charge separation, demonstrating close to ideal donor-acceptor level matching and nanomorphology in this ble

Integrated molecular, morphological and interfacial engineering towards highly efficient and stable solution-processed small molecule solar cells - Min, Jie; Luponosov, Yuriy N.; Gasparini, Nicola; Xue, Lingwei; Drozdov, Fedor V.; Peregudova, Svetlana M.; Dmitryakov, Petr V.; Gerasimov, Kirill L.; Anokhin, Denis V.; Zhang, Zhi-Guo; Ameri, Tayebeh; Chvalun, Sergei N.; et al. (Journal of Materials Chemistry A, 2015)
The synthesis of a series of A-π-D-π-A oligomers bearing coplanar electron-donating dithieno[3,2-b:2′,3′-d]silole (DTS) unit linked through bithiophene π-bridges with the electron-withdrawing alkyldicyanovinyl (alkyl-DCV) groups is described. This study demonstrates a systematic investigation of structure-property relationships in this type of oligomer and shows obvious benefits of alkyl-DCV groups as compared to the commonly used DCV ones, in terms of elaboration of high performance organic solar cells (OSCs). Considerable efforts have been made to improve the power conversion efficiency (PCE) of oligomer-based OSCs by diverse strategies including fine-tuning of the oligomer properties via variation of their terminal and central alkyl chains, blend morphology control via solvent vapor annealing (SVA) treatment, and surface modification via interfacial engineering. These efforts allowed achieving PCEs of up to 6.4% for DTS(Oct)-(2T-DCV-Me) blended with PCBM. Further morphological investigations demonstrated that the usage of SVA treatment indeed effectively results in increased absorption and ordering of the BHJ composite, with the only exception for the most soluble oligomer DTS(Oct)-(2T-DCV-Hex). Besides, a detailed study analyzed the charge transport properties and recombination loss mechanisms for these oligomers. This study not only revealed the importance of integrated alkyl chain engineering on gaining morphological control for high performance OSCs, but also exhibited a clear correlation between molecular ordering and charge carrier mobility respective to carrier dynamics. These results outline a detailed strategy towards a rather complete characterization and optimization methodology for organic photovoltaic devices, thereby paving the way for researchers to easily find the performance parameters adapted for widespread applications.
Keywords: Engineering controlled terms: Cell engineering; Oligomers; Surface treatment; Varactors Electronwithdrawing; Morphological control; Optimization methodology; Organic photovoltaic devices; Performance parameters; Power conversion efficiencies; Solvent-vapor annealing; Structure property relationships Engineering main heading: Solar cells

Integrated System Built for Small-Molecule Semiconductors via High-Throughput Approaches - Wu, Jianchang; Zhang, Jiyun; Hu, Manman; Reiser, Patrick; Torresi, Luca; Friederich, Pascal; Lahn, Leopold; Kasian, Olga; Guldi, Dirk Michael; Perez-Ojeda Rodriguez, Maria Eugenia; Barabash, Anastasiia; Rocha Ortiz, Juan Sebastian; et al. (Journal of the American Chemical Society, 2023)
High-throughput synthesis of solution-processable structurally variable small-molecule semiconductors is both an opportunity and a challenge. A large number of diverse molecules provide a possibility for quick material discovery and machine learning based on experimental data. However, the diversity of the molecular structure leads to the complexity of molecular properties, such as solubility, polarity, and crystallinity, which poses great challenges to solution processing and purification. Here, we first report an integrated system for the high-throughput synthesis, purification, and characterization of molecules with a large variety. Based on the principle “Like dissolves like,” we combine theoretical calculations and a robotic platform to accelerate the purification of those molecules. With this platform, a material library containing 125 molecules and their optical-electronic properties was built within a timeframe of weeks. More importantly, the high repeatability of recrystallization we design is a reliable approach to further upgrading and industrial production.<br

Intercalating-Organic-Cation-Induced Stability Bowing in Quasi-2D Metal-Halide Perovskites - Zhang, Jiyun; Langner, Stefan; Wu, Jianchang; Kupfer, Christian; Lüer, Larry; Meng, Wei; Zhao, Baolin; Liu, Chao; Daum, Manuel; Osvet, Andres; Li, Ning; Halik, Marcus; et al. (ACS Energy Letters, 2022)
Quasi-2D metal-halide perovskites with Ruddlesden-Popper structures have shown promising stability due to the protective effects of the intercalating organic cations. However, a systematic study of the effect of intercalating organic cations on stability has rarely been reported. Here we use a high-throughput-robot platform to fabricate over 300 perovskite films and study the effect of cations and their concentrations on the thermal stability of perovskite films. We find that approximately 20-25 mol % of intercalating organic cations into MAPbI3 (nominal n = 4/5) can maximize the film stability, while higher/lower concentrations lead to inferior stability, which is termed stability bowing in analogy to band-gap bowing. A model with two competitive effects of the intercalating organic cation (better protection vs more defects) is proposed to rationalize this behavior. We anticipate this work to provide new insights into the stability of quasi-2D perovskites.
CRIS-Team Scopus Importer:2022-02-11

Interface Design to Improve the Performance and Stability of Solution-Processed Small-Molecule Conventional Solar Cells - Min, Jie; Luponosov, Yuriy N.; Zhang, Zhi-Guo; Ponomarenko, Sergei A.; Ameri, Tayebeh; Li, Yongfang; Brabec, Christoph (Advanced Energy Materials, 2014)
A systematic study on the effect of various cathode buffer layers on the performance and stability of solution-processed small-molecule organic solar cells (SMOSCs) based on tris[4-[5-(1,1-dicyanobut-1-en-2-yl)-2,2-bithiophen-5-yl]phenyl]amine (N(Ph-2T-DCN-Et)3):6,6-phenyl-C71-butyric acid methyl ester (N(Ph-2T-DCN-Et)3:PC70BM) is presented. The power conversion efficiency (PCE) in these systems can be significantly improved from approximately 4% to 5.16% by inserting a metal oxide (ZnO) layer between the active layer and the Al cathode instead of an air-sensitive Ba or Ca layer. However, the low work-function Al cathode is susceptible to chemical oxidation in the atmosphere. Here, an amine group functionalized fullerene complex (DMAPA-C60) is inserted as a cathode buffer layer to successfully modify the interface towards ZnO/Ag and active layer/Ag functionality. For devices with ZnO/DMAPA-C60/Ag and DMAPA-C60/Ag cathodes the PCEs are improved from 2.75% to 4.31% and to 5.40%, respectively, compared to a ZnO/Ag device. Recombination mechanisms and stability aspects of devices with various cathodes are also investigated. The significant improvement in device performance and stability and the simplicity of fabrication by solution processing suggest this DMAPA-C60-based interface as a promising and practical pathway for developing efficient, stable, and roll-to-roll processable SMOSCs.
Keywords: Engineering controlled terms: Buffer layers; Butyric acid; Convergence of numerical methods; Conversion efficiency; Electrodes; Fullerenes; Molecules; Optical waveguides; Silver; Solar cells; Stability; Zinc oxide Cathode buffer layers; Conventional structures; Fullerene complexes; Power conversion efficiencies; Recombination mechanisms; Small-molecule organic solar cells; Solution-processing; Stability of solutions Engineering main heading: Cathodes

Interface Engineering of Perovskite Hybrid Solar Cells with Solution-Processed Perylene–Diimide Heterojunctions toward High Performance - Min, Jie; Zhang, Zhi-Guo; Hou, Yi; Ramírez Quiroz, César Omar; Przybilla, Thomas; Bronnbauer, Carina; Guo, Fei; Forberich, Karen; Azimi, Seyed Hamed; Ameri, Tayebeh; Spiecker, Erdmann; Li, Yongfang; et al. (Chemistry of Materials, 2015)
Perovskite hybrid solar cells (pero-HSCs) were demonstrated to be among the most promising candidates within the emerging photovoltaic materials with respect to their power conversion efficiency (PCE) and inexpensive fabrication. Further PCE enhancement mainly relies on minimizing the interface losses via interface engineering and the quality of the perovskite film. Here, we demonstrate that the PCEs of pero-HSCs are significantly increased to 14.0% by incorporation of a solution-processed perylene–diimide (PDINO) as cathode interface layer between the [6,6]-phenyl-C61 butyric acid methyl ester (PCBM) layer and the top Ag electrode. Notably, for PDINO-based devices, prominent PCEs over 13% are achieved within a wide range of the PDINO thicknesses (5–24 nm). Without the PDINO layer, the best PCE of the reference PCBM/Ag device was only 10.0%. The PCBM/PDINO/Ag devices also outperformed the PCBM/ZnO/Ag devices (11.3%) with the well-established zinc oxide (ZnO) cathode interface layer. This enhanced performance is due to the formation of a highly qualitative contact between PDINO and the top Ag electrode, leading to reduced series resistance (Rs) and enhanced shunt resistance (Rsh) values. This study opens the door for the integration of a new class of easily-accessible, solution-processed high-performance interfacial materials for pero-HSCs.

Interface materials for organic solar cells - Steim, Roland; Kogler, F. Rene; Brabec, Christoph (Journal of Materials Chemistry, 2010)
The progress in the development and understanding of interfacial materials for organic photovoltaics (OPV) is reviewed. The proper choice of interface materials is a must for highly efficient and stable OPV devices and has become a significant part of the OPV research today. Interface materials are either non-conducting, semiconducting or conducting layers which not only provide selective contacts for carriers of one sort, but can also determine the polarity of OPV devices, affect the open-circuit voltage, and act as optical spacers or protective layers. In this review both inorganic and organic interface materials are discussed with respect to their function in the OPV device. © 2010 The Royal Society of Chemistry.

Interface Molecular Engineering for Laminated Monolithic Perovskite/Silicon Tandem Solar Cells with 80.4% Fill Factor - Ramírez Quiroz, César Omar; Spyropoulos, Georgios; Salvador, Michael; Roch, Loïc M.; Berlinghof, Marvin; Darío Perea, José; Forberich, Karen; Dion-Bertrand, Laura Isabelle; Schrenker, Nadine J.; Classen, Andrej; Gasparini, Nicola; Chistiakova, Ganna; et al. (Advanced Functional Materials, 2019)
A multipurpose interconnection layer based on poly(3,4-ethylenedioxythiophene) doped with poly(styrene sulfonate) (PEDOT:PSS), and d-sorbitol for monolithic perovskite/silicon tandem solar cells is introduced. The interconnection of independently processed silicon and perovskite subcells is a simple add-on lamination step, alleviating common fabrication complexities of tandem devices. It is demonstrated experimentally and theoretically that PEDOT:PSS is an ideal building block for manipulating the mechanical and electrical functionality of the charge recombination layer by controlling the microstructure on the nano- and mesoscale. It is elucidated that the optimal functionality of the recombination layer relies on a gradient in the d-sorbitol dopant distribution that modulates the orientation of PEDOT across the PEDOT:PSS film. Using this modified PEDOT:PSS composite, a monolithic two-terminal perovskite/silicon tandem solar cell with a steady-state efficiency of 21.0%, a fill factor of 80.4%, and negligible open circuit voltage losses compared to single-junction devices is shown. The versatility of this approach is further validated by presenting a laminated two-terminal monolithic perovskite/organic tandem solar cell with 11.7% power conversion efficiency. It is envisioned that this lamination concept can be applied for the pairing of multiple photovoltaic and other thin film technologies, creating a universal platform that facilitates mass production of tandem devices with high efficiency.
Keywords: density functional theory; lamination; molecular dynamics; monolithic tandem; perovskite/silicon; transparent-conductive-adhesive

Introducing a New Potential Figure of Merit for Evaluating Microstructure Stability in Photovoltaic Polymer-Fullerene Blends - Perea, Jose Dario; Langner, Stefan; Salvador, Michael Filipe; Sanchez-Lengeling, Benjamin; Li, Ning; Zhang, Chaohong; Jarvas, Gabor; Kontos, Janos; Dallos, Andras; Aspuru-Guzik, Alan; Brabec, Christoph (Journal of Physical Chemistry C, 2017)
A theoretical understanding of the microstructure of organic semiconducting polymers and blends is vital to further advance the optoelectronic device performance of organic electronics. We outline the theoretical framework of a combined numerical approach based on polymeric solution theory to study the microstructure of polymer:small molecule blends. We feed the results of ab initio density functional theory quantum chemistry calculations into an artificial neural network for the determination of solubility parameters. These solubility parameters are used to calculate Flory-Huggings intermolecular parameters. We further show that the theoretical values are in line with experimentally determined data. On the basis of the Flory-Huggings parameters, we establish a figure of merit as a relative metric for assessing the phase diagrams of organic semiconducting blends in thin films. This is demonstrated for polymer:fullerene blend films on the basis of the prototypical polymers poly(3-hexylthiophene-2,5-diyl) (P3HT) and poly[(5,6-difluoro-2,1,3-benzothiadiazol-4,7-diyl)-alt-(3,3-di(2-octyldodecyl)-2,2,5,2;5,2-quaterthiophen-5,5-diyl)] (PffBT4T-2OD). After confirming the applicability of our model with a broader range of materials and differences in molecular weight, we suggest that this combined model should be able to inform design criteria and processing guidelines for existing and new high performance semiconducting blends for organic electronics applications with ideal and stable solid state morphology. (Graph Presented). © 2017 American Chemical Society.
Keywords: BlendingCalculationsDensity functional theoryFullerenesMicrostructureNeural networksOptoelectronic devicesOrganic polymersPolymer filmsPolymersQuantum chemistrySemiconducting filmsSemiconducting polymersSolubility

Introducing a new triazoloquinoxaline-based fluorene copolymer for organic photovoltaics: Synthesis, characterization, and photovoltaic properties - Baran, Derya; Pasker, Felix M.; Le Blanc, Stephan; Schnakenburg, Gregor; Ameri, Tayebeh; Hoeger, Sigurd; Brabec, Christoph (Journal of Polymer Science Part A-Polymer Chemistry, 2013)
A new donor-acceptor copolymer consisting of triazoloquinoxaline and 9,9-dialkylfluorene units on the main chain has been synthesized, characterized and evaluated as donor material in bulk heterojunction solar cells using PC BM as an acceptor. The resulting polymer PTQF showed good thermal stability and solubility in common organic solvents. Cyclic Voltammetry measurements showed that the PTQF has HOMO-LUMO energy levels of -5.13 and -3.62 eV, respectively. DFT calculations revealed that the HOMO is delocalized all over the thiophene and fluorene units and the LUMO is localized mainly on the triazole and pyrazine units. PTQF absorbs broadly in the visible region and exhibits a bandgap of 1.4 eV. Photovoltaic devices exhibited 1.7% efficiency for 1:2 PTQF:PCBM blend ratio using Ca/Ag electrodes. © 2012 Wiley Periodicals, Inc.
Keywords: benzotriazole; conducting polymers; conjugated polymers; electrochemistry; fluorene copolymer; organic photovoltaics; Suzuki coupling; triazoloquinoxaline

Introduction - Kafafi, Zakya H.; Brabec, Christoph; Lane, Paul A. (Proceedings of SPIE - The International Society for Optical Engineering, 2012)

Inverted, Environmentally Stable Perovskite Solar Cell with a Novel Low-Cost and Water-Free PEDOT Hole-Extraction Layer - Hou, Yi; Zhang, Hong; Chen, Wei; Chen, Shi; Ramírez Quiroz, César Omar; Azimi, Seyed Hamed; Osvet, Andres; Matt, Gebhard; Zeira, Eitan; Seuring, Jan; Kausch-Busies, Nina; Loevenich, Wilfried; et al. (Advanced Energy Materials, 2015)
A power conversion efficiency of 11.8% is demonstrated for planar perovskite solar cell based on acid water-free poly(3,4-ethylenedioxythiophene) (PEDOT) as the hole-transporting layer. This efficiency is further improved to 14.2% using a pH neutralized PEDOT, which reduces the sub-gap defects at the surface of perovskite. All the active layers reported are solution-processed at temperatures below 140 °C making it compatible with roll-to-roll production.
Keywords: low-temperature processing; perovskite solar cells; stabilities; water-free poly(3; 4-ethylenedioxythiophene)

Inverted organic solar cells using a solution processed aluminum-doped zinc oxide buffer layer - Stubhan, Tobias; Oh, Hyunchul; Pinna, Luigi; Krantz, Johannes; Litzov, Ivan; Brabec, Christoph (Organic Electronics, 2011)
In this article, we demonstrate a route to solve one of the big challenges in the large scale printing process of organic solar cells, which is the reliable deposition of very thin layers. Especially materials for electron (EIL) and hole injection layers (HIL) (except poly(3,4-ethylene dioxythiophene): (polystyrene sulfonic acid) (PEDOT:PSS)) have a low conductivity and therefore require thin films with only a few tens of nanometers thickness to keep the serial resistance under control. To overcome this limitation, we investigated inverted polymer solar cells with an active layer comprising a blend of poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl-C-butyric acid methyl ester (PCBM) with solution processed aluminum-doped zinc oxide (AZO) EIL. Devices with AZO and intrinsic zinc oxide (i-ZnO) EIL show comparable efficiency at low layer thicknesses of around 30 nm. The conductivity of the doped zinc oxide is found to be three orders of magnitude higher than for the i-ZnO reference. Therefore the buffer layer thickness can be enhanced significantly to more than 100 nm without hampering the solar cell performance, while devices with 100 nm i-ZnO films already suffer from increased series resistance and reduced efficiency. © 2011 Elsevier B.V. All rights reserved.
Keywords: Al doped ZnO; Electron injection layer; Inverted structure; Polymer solar cell; Solution processing; Zinc oxide nanoparticles

Inverted structure organic photovoltaic devices employing a low temperature solution processed WO 3 anode buffer layer - Li, Ning; Stubhan, Tobias; Luechinger, Norman A.; Halim, Samuel C.; Matt, Gebhard; Ameri, Tayebeh; Brabec, Christoph (Organic Electronics, 2012)
Solution processing is a convenient method and also the guarantee for low cost and large-scale organic photovoltaic (OPV) production. It was recently suggested that the absorption of OPV devices can be spectrally extended by introducing ternary semiconductor blends, where a second donor with a complementary absorption spectrum is added into the active layer. In this manuscript we demonstrate the successful replacement of poly(3,4- ethylenedioxythiophene) poly(styrenesulfonate) (PEDOT:PSS) by low temperature solution processed tungsten trioxide (WO ) nanoparticles for inverted OPV devices based on either poly(3-hexylthiophene) (P3HT): phenyl-C61-butyric acid methyl ester (PCBM) or P3HT: poly[2,1,3-benzothiadiazole-4,7-diyl[4,4- bis(2-ethylhexyl)-4H-cyclopenta[2,1-b:3,4-b′]dithiophene-2,6-diyl]] (Si-PCPDTBT):PCBM active layers. These WO nanoparticles can serve as fully functional anode buffer layers in inverted OPV devices without further treatment, while showing comparable functionality as PEDOT:PSS layers. © 2012 Elsevier B.V. All rights reserved.
Keywords: Anode buffer layer; Inverted structure; Organic photovoltaic; Solution processing; WO 3 nanoparticles

Ionic Dipolar Switching Hinders Charge Collection in Perovskite Solar Cells with Normal and Inverted Hysteresis - Almora Rodriguez, Osbel; Lopez-varo, Pilar; Cho, Kyung Taek; Aghazada, Sadig; Meng, Wei; Hou, Yi; Echeverria-Arrondo, Carlos; Zimmermann, Iwan; Matt, Gebhard; Jiménez-Tejada, Juan A.; Brabec, Christoph; Nazeeruddin, Mohammad Khaja; et al. (Solar Energy Materials and Solar Cells, 2019)
Drift-diffusion modeling of the ionic dipole switching from the measurement of fast scanned and long pre-biased electrical response is proposed as a novel protocol for evaluation of limit hysteretic effects in perovskite solar cells. Up to eight systems were measured including CH3NH3PbI3, Cs0.1FA0.74MA0.13PbI2.48Br0.39 and FA0.83MA0.17Pb1.1Br0.22I2.98 3D perovskite absorbers, as well as 2D capping layers towards the selective contacts. We show systematic hysteretic patterns, even among typical hysteresis-free devices, including normal and inverted hysteresis as general dissimilar trend between CH3NH3PbI3 and mixed perovskite cells, respectively. Particularly, strong changes in the short-circuit current density (Jsc) were identified, in addition to different trends affecting the fill factor (FF) and the open-circuit voltage (Voc). The changes in Jsc were analyzed with state-of-the-art numerical drift-diffusion simulations concluding in an important reduction in the charge collection due to ionic distribution switching depending on the pre-biasing protocol and the type of absorbing perovskite. It is shown that mixed perovskites inhibit ionic dipolar switching. In addition, our calculi signal on the required conditions for the occurrence of inverted hysteresis and changes in the Voc. Regarding the FF and Voc patterns a new empirical approach is introduced and corresponding interpretations are proposed. <br
Keywords: Perovskite solar cells; Ionic polarization; Hysteresis; Photocurrent

Ion-mediated hopping electrode polarization model for impedance spectra of CH3NH3PbI3 - Almora Rodriguez, Osbel; González-Lezcano, Alfredo; Guerrero, Antonio; Brabec, Christoph J.; Garcia-Belmonte, Germa (Journal of Applied Physics, 2020)
Methylammonium lead iodide (CH3NH3PbI3) is one of the most attractive materials for optoelectronic applications, and it is the most typical absorber in perovskite solar cells, which are unprecedentedly successful devices in terms of power conversion efficiency. In this work, the conductivity and capacitance spectra of symmetrically contacted Au/CH3NH3PbI3/Au thick pellets are measured via impedance spectroscopy at different temperatures in dark equilibrium. The experimental conductivity spectra are parameterized and showed to follow the formalism of hopping DC conductivity in the CH3NH3PbI3 bulk. The presence of several regimes for the general Jonscher's “universal” conductivity–frequency response is highlighted and associated with the ionic–electronic overlapping conductivities. For the capacitance spectra, the general features of electrode polarization capacitance at the CH3NH3PbI3/Au interfaces are identified but yet are found to be in disagreement with some trends of classical ionic conductivity models, unable to separate different contributions. Accordingly, an analytical model is proposed accounting for hopping processes where the low frequency activation energy is split into ionic and electronic components. Our parameterizations and analytical model discern between the bulk/interface and ionic/electronic phenomena and estimate the multiple activation energies in this hybrid halide perovskite.<br
Keywords: Electrodes; Photovoltaics; Perovskites; Dielectric properties; Optoelectronic applications; Electrochemical impedance spectroscopy; Ionic conductivity

IR-images of PV-modules with potential induced degradation (PID) correlated to monitored string power output - Buerhop, Claudia; Pickel, Tobias; Blumberg, Tiberius; Adams, Jens; Wrana, Simon; Dalsass, Manuel; Zetzmann, Cornelia; Camus, Christian; Hauch, Jens; Brabec, Christoph (Reliability of Photovoltaic Cells, Modules, Components, and Systems IX, 2016)
Many PV-plants suffer from potential induced degradation (PID) which causes severe power reduction of installed PVmodules. Fast and reliable methods to detect PID and evaluate the impact on the module performance are gaining importance. Drone-Assisted IR-inspection is a suitable method. PID affected modules are detected by their characteristic IR-fingerprint, modules with differing number of slightly heated cells occur more frequently at the negative string end. These modules show a degraded IV-curve, lowered Voc and Isc, and electroluminescence (EL)-images with suspicious, dark cells. Also, the measured string power is reduced. For a first quantitative data evaluation the suspicious cell are counted in the IR-images and correlated with the module power. A linear decrease of the module power with increasing number of suspicious cells results. A correlation function for estimating the module power was deduced, which has a mean deviation of less than 7%. This correlation function allows an acceptable approximation of the string power.
Keywords: Degradation; Electroluminescence; IR-imaging; IR-inspection; PID; Potential Induced Degradation; PV-modules; PV-plants; Reliability

IR-imaging and non-destructive loss analysis on thin film solar modules and cells - Adams, Jens; Fecher, Frank W.; Hoga, Felix; Vetter, Andreas; Buerhop, Claudia; Brabec, Christoph (Proceedings of SPIE - The International Society for Optical Engineering, 2014)
CIGS thin film solar modules, despite their high efficiency, may contain three different kinds of macroscopic defects referred to as bulk defects, interface defects and interconnect defects. These occur due to the film's sensitivity to inhomogeneities during the manufacturing process and decreasing the electrical power output from a cell or module. In this study, we present infrared (IR) imaging and contactless loss analyses of defects contained in commercially manufactured thin film solar modules. We investigated different relations between the emitted IR-signal (using illuminated lock-in thermography ILIT) and the respective open circuit cell voltage (Voc) as well as the maximum power point (Pmpp). A simulation study, using the 2D finite element method (FEM), provides a deeper understanding as to the impact on electrical performance when defects are present on the cell or module.
Keywords: 2D finite element method; CIGS thin film technology; Contactless; Defects; ILIT; Lock in thermography; Open circuit voltage

IR sensitization of an indene-C60 bisadduct (ICBA) in ternary organic solar cells - Ameri, Tayebeh; Heumüller, Thomas; Min, Jie; Li, Ning; Matt, Gebhard; Scherf, Ullrich; Brabec, Christoph (Energy and Environmental Science, 2013)
This article presents a smart strategy to successfully tackle two main limitations of organic solar cells (OSCs) in one step: the narrow absorption window of polymers as well as the V limitation related to the mono-PCBM. We demonstrate the high OSC performance of >5% in the combination of a fullerene multiadduct, i.e. indene-C60 bisadduct (ICBA) with a low bandgap polymer employing the concept of ternary OSCs. Solar cells achieving a fill factor (FF) of >60% along with high quantum efficiency in the near IR region are demonstrated for ternary composites consisting of P3HT, the fullerene-bisindene adduct of ICBA and a low bandgap copolymer sensitizer. Using P3HT as an efficient transport matrix with non-Langevin recombination dynamics allowed us to limit and overcome the otherwise dominant recombination losses of the indene-C60 bisadduct-low bandgap copolymer blends. The success of this strategy resulted in a relative efficiency improvement of over 25%. © 2013 The Royal Society of Chemistry.

ITO-Free and Fully Solution-Processed Semitransparent Organic Solar Cells with High Fill Factors - Guo, Fei; Zhu, Xiangdong; Forberich, Karen; Krantz, Johannes; Stubhan, Tobias; Salinas Batallas, Michael; Halik, Marcus; Spallek, Stefanie; Butz, Benjamin; Spiecker, Erdmann; Ameri, Tayebeh; Li, Ning; et al. (Advanced Energy Materials, 2013)
Organic photovoltaic (OPV) solar cells that can be simply processed from solution are in the focus of the academic and industrial community because of their enormous potential to reduce cost. One big challenge in developing a fully solution-processed OPV technology is the design of a well-performing electrode system, allowing the replacement of ITO. Several solution-processed electrode systems were already discussed, but none of them could match the performance of ITO. Here, we report efficient ITO-free and fully solution-processed semitransparent inverted organic solar cells based on silver nanowire (AgNW) electrodes. To demonstrate the potential of these AgNW electrodes, they were employed as both the bottom and top electrodes. Record devices achieved fill factors as high as 63.0%, which is comparable to ITO based reference devices. These results provide important progress for fully printed organic solar cells and indicate that ITO-free, transparent as well as non-transparent organic solar cells can indeed be fully solution-processed without losses. Indium tin oxide (ITO)-free and fully solution-processed organic solar cells are demonstrated by employing AgNW as both the bottom and top electrodes, in conjunction with Al-ZnO and poly(3,4-ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS) as charge extraction layers. Devices with electrical fill factor (FF) up to 63.0% and fully retained open circuit voltage (V) are achieved, indicating that superior optoelectronic and film quality properties of the two interlayers are perfectly compatible to AgNW electrodes. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Joint Super-Resolution and Rectification for Solar Cell Inspection - Hoffmann, Mathis; Köhler, Thomas; Doll, Bernd; Schebesch, Frank; Talkenberg, Florian; Peters, Ian Marius; Brabec, Christoph; Maier, Andreas; Christlein, Vincent (IEEE Journal of Photovoltaics, 2021)
Visual inspection of solar modules is an important monitoring facility in photovoltaic power plants. Since a single measurement of fast CMOS sensors is limited in spatial resolution and often not sufficient to reliably detect small defects, we apply multi-frame super-resolution (MFSR) to a sequence of low resolution measurements. In addition, the rectification and removal of lens distortion simplifies subsequent analysis. Therefore, we propose to fuse this pre-processing with standard MFSR algorithms. This is advantageous, because we omit a separate processing step, the motion estimation becomes more stable and the spacing of high-resolution (HR) pixels on the rectified module image becomes uniform w.r.t. the module plane, regardless of perspective distortion. We present a comprehensive user study showing that MFSR is beneficial for defect recognition by human experts and that the proposed method performs better than the state of the art. Furthermore, we apply automated crack segmentation and show that the proposed method performs 3x better than bicubic upsampling and 2x better than the state of the art for automated inspection.

Key parameters of efficient phosphor-filled luminescent down-shifting layers for photovoltaics - Solodovnyk, Anastasiia; Lipovsek, Benjamin; Riedel, Daniel; Forberich, Karen; Stern, Edda; Batentschuk, Miroslaw; Krc, Janez; Topic, Marko; Brabec, Christoph (Journal of Optics A-Pure and Applied Optics, 2017)
Spectral management is one of the promising ways to increase the efficiency of modern photovoltaic devices. We study the performance of phosphor-filled luminescent down-shifting (LDS) layers. We focus on four powder phosphors with refractive indices in the range of 1.66-1.84 and similar particle size distributions. Using experimental characterization as well as 3D optical simulations, we identify key parameters of the phosphor particles and LDS layers that primarily affect the optical transmittance, absorptance, and photoluminescence quantum yield of the layers. We investigate the influence of the medium located beneath the LDS layer and reveal a strong increase in the performance when the layer is applied directly onto the solar cell. Finally, the optimal combination of the particle, binder and layer parameters that render the highest performance of the LDS layers are also indicated and discussed. © 2017 IOP Publishing Ltd.
Keywords: absorptance; phosphors; photoluminescence quantum yield; photovoltaics; transmittance

Large-area organic photovoltaic modules with 14.5% certified world record efficiency - Basu, Robin; Gumpert, Fabian; Lohbreier, Jan; Morin, Pierre Olivier; Vohra, Varun; Liu, Yang; Zhou, Yinhua; Brabec, Christoph; Egelhaaf, Hans-Joachim; Distler, Andreas (Joule, 2024)
Organic photovoltaics (OPVs) have experienced a significant increase in power conversion efficiency (PCE) recently, now approaching 20% on small-cell level. Since the efficiencies on the module level are still substantially lower, focused upscaling research is necessary to reduce the gap between cells and modules. In this work, we present the upscaling of PM6:Y6-C12:PC61BM-based devices, processed in ambient air from non-halogenated solvents, from small-area cells to large-area modules with barely any performance loss. Supported by computational fluid dynamics simulations, an accelerated blade coating process that enables homogeneous coatings with <5% thickness deviation over 200 cm² is developed. Additional finite element method simulations are used to optimize the module layout and minimize the inevitable losses caused by electrode resistances and inactive interconnect areas to 1.9% and 3.5%, respectively. Finally, a 204-cm² OPV module with a certified PCE of 14.5% (15.0% on active area) is fabricated, which constitutes the new world record.
CRIS-Team Scopus Importer:2024-04-05
Keywords: certified world record efficiency; FEM simulations; laser patterning; OPVs; organic photovoltaics; process optimization; solar modules; solution-processed in ambient air

Large area slot-die coated organic solar cells on flexible substrates with non-halogenated solution formulations - Machui, Florian; Lucera, Luca; Spyropoulos, Georgios; Cordero, Johann; Ali, Abid Shaukat; Kubis, Peter; Ameri, Tayebeh; Voigt, Monika; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2014)
The transfer from lab scale to industrial application is one of the challenges for organic photovoltaics. For this, non halogenated formulations are a decisive need for the upscaling process, as are roll-to-toll (R2R) compatible methods. Devices processed with o-xylene using slot-die coating as a sheet-to-sheet technique show a reduced efficiency on a larger scale compared to lab scale solar cells. By using a mixture of high and low volatile solvents which selectively dissolve one component, the film homogeneity and the efficiency is dramatically improved. The slot-die coated active layers for solar cells processed from non-halogenated solvents show device efficiencies above 3% on flexible substrates.
Keywords: Film homogeneity; Flexible substrates; Ink formulation; Organic photovoltaics; Slot-die coating; Solvent

Laser process for extended silicon thin film solar cells - Hessmann, M. T.; Kunz, T.; Burkert, I.; Gawehns, N.; Schaefer, L.; Frick, T.; Schmidt, Michael; Meidel, B.; Auer, R.; Brabec, Christoph (Thin Solid Films, 2011)
We present a large area thin film base substrate for the epitaxy of crystalline silicon. The concept of epitaxial growth of silicon on large area thin film substrates overcomes the area restrictions of an ingot based monocrystalline silicon process. Further it opens the possibility for a roll to roll process for crystalline silicon production. This concept suggests a technical pathway to overcome the limitations of silicon ingot production in terms of costs, throughput and completely prevents any sawing losses. The core idea behind these thin film substrates is a laser welding process of individual, thin silicon wafers. In this manuscript we investigate the properties of laser welded monocrystalline silicon foils (100) by micro-Raman mapping and spectroscopy. It is shown that the laser beam changes the crystalline structure of float zone grown silicon along the welding seam. This is illustrated by Raman mapping which visualizes compressive stress as well as tensile stress in a range of - 147.5 to 32.5 MPa along the welding area. © 2011 Elsevier B.
Keywords: Crystalline silicon; Laser beam welding; Raman spectroscopy; Thin films

Laser structuring of crystalline silicon thin-film solar cells on opaque foreign substrates - Kunz, T.; Gazuz, V.; Hessmann, M. T.; Gawehns, N.; Burkert, I.; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2011)
Crystalline silicon thin-film solar cells were fabricated on graphite substrates. A laser ablation process was developed for edge isolation of the thin-film cells. The shunt resistance was comparable to otherwise identical cells isolated by plasma etching, while the reproducibility of the laser isolation process was higher. The solar cells were characterized by currentvoltage and light beam induced current measurements (LBiC). No interference was detected along the ablated edges. Spatial variations of the minority carrier lifetime are attributed to the grain structure of the seeding layer obtained by the zone melting recrystallization (ZMR). © 2011 Elsevier B.V.
Keywords: Crystalline thin-film silicon; Edge isolation; Graphite substrate; Laser processing

Last Generation Solar Cells in Outer Space: A STEM Outreach Project with Middle and High School Students in Colombia - Perea, Jose Dario; Gasca, Diana Carolina; Echeverry-Prieto, Ghisliane; Quiroga-Fonseca, Valentina; Orozco-Donneys, Carolina; Díaz-Montealegre, Leidy Catherine; Ortiz, Alejandro; Molina, Giovanny; Cruz, Daniel; Persad, Aaron; Redd-Kantareddy, Sai Nithin; Wachsmuth, Josua; et al. (European Journal of STEM Education, 2021)
As part of an unprecedented collaborative outreach effort, we implemented an innovative STEM outreach project, where more than 80 middle and high school students from different traditionally underrepresented school districts in Colombia-with no previous knowledge on material science or photovoltaics-created Last Generation Solar Cells (LGSCs) that were part of several suborbital spaceflight missions. As a result, the students were able to contrast visual and instrumental data obtained from the solar cells and modules that were launched to space with similar samples that remained on earth to measure the degradation that occurs during spaceflight conditions. At the same time, the students that participated were able to cultivate their curiosity, strengthen their scientific skills and increase their interest in pursuing careers in STEM fields. These experiences were possible thanks to an extraordinary collaborative network between public and private entities and the use of project-based education as a powerful driver of development, especially for low-to-middle-income countries, such as Colombia. Here, we share our methodology for constructing photovoltaic devices in rural settings, and we show the progression and impact of this novel scientific outreach project.
CRIS-Team Scopus Importer:2023-03-07
Keywords: last generation solar cells; organic solar cells; science outreach; STEM education

Layer-by-layer processed binary all-polymer solar cells with efficiency over 16% enabled by finely optimized morphology - Zhang, Yue; Wu, Baoqi; He, Yakun; Deng, Wanyuan; Li, Jingwen; Li, Junyu; Qiao, Nan; Xing, Yifan; Yuan, Xiyue; Li, Ning; Brabec, Christoph; Wu, Hongbin; et al. (Nano Energy, 2022)
Optimal active layer morphology is a prerequisite for high-efficiency all-polymer solar cells (all-PSCs). Herein, we report that the vertical phase separation as well as microstructures of the polymer donor and acceptor can be finely optimized in layer-by-layer (LbL) processed all-PSCs. By using 1-chloronaphthalene as the solvent additive during the deposition of the polymer acceptor in the top layer and applying thermal annealing on the entire active layer, bulk-heterojunction like morphology with favorable vertical composition distribution, improved lamellar ordering of the polymer donor (PBDB-T), and the formation of polymer fibrils of the polymer acceptor (PYT) have been realized simultaneously. This favorable morphology led to greatly enhanced exciton splitting efficiency, reduced trap density, improved charge transport, and suppressed charge recombination loss. As a result, the LbL processed all-PSCs of PBDB-T/PYT afforded a power conversion efficiency (PCE) of 16.05%, which is one of the highest PCEs for binary all-PSCs. Moreover, a fill factor (FF) of 0.77 has been obtained, which is the highest value for all-PSCs based on polymerized small molecule acceptors up to date. This work demonstrates an effective strategy for morphology optimization of LbL processed all-PSCs, which will greatly contribute to efficiency breakthrough.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Active layer morphology; All-polymer solar cells; High-efficiency; Layer-by-layer processing; Vertical composition distribution

Lifetime and Degradation of Pre-damaged PV-Modules - Field study and lab testing - Buerhop, Claudia; Wirsching, Sven; Gehre, Simon; Pickel, Tobias; Winkler, Thilo; Bemm, Andreas; Mergheim, Julia; Camus, Christian; Brabec, Christoph; Hauch, Jens (Conference record of the IEEE Photovoltaic Specialists Conference, 2017)
The presence of pre-cracked PV-modules in modern PV-plants is well-known. The evolution and actual impact of the cracks on electrical yield under real operation conditions is not yet understood but of great relevance. Established standards cannot reveal the relevant effects. Therefore, a unique threefold analysis is applied: 1) field exposure, 2) using a new accelerated loading test, and 3) Finite Elements (FEM) simulations. For the first time, we present comparative Electroluminescence (EL-) images recorded in the field and during load testing. Crack growth is studied in terms of the monitored weather conditions and the applied load simulating static snow and wind loads.

Lifetime and Degradation of Pre-damaged PV-Modules – Field study and lab testing - Buerhop, Claudia; Wirsching, Sven; Gehre, Simon; Pickel, Tobias; Winkler, Thilo; Bemm, Andreas; Mergheim, Julia; Camus, Christian; Hauch, Jens; Brabec, Christoph (44th IEEE Photovoltaic Specialists Conference, 2017)
The presence of pre-cracked PV-modules in modern PV-plants is well-known. The evolution and actual impact of the cracks on electrical yield under real operation conditions is not yet understood but of great relevance. Established standards cannot reveal the relevant effects. Therefore, a unique threefold analysis is applied: 1) field exposure, 2) using a new accelerated loading test, and 3) Finite Elements (FEM) simulations. For the first time, we present comparative Electroluminescence (EL-) images recorded in the field and during load testing. Crack growth is studied in terms of the monitored weather conditions and the applied load simulating static snow and wind loads.

Ligand-assisted thickness tailoring of highly luminescent colloidal CH3NH3PbX3 (X = Br and I) perovskite nanoplatelets - Levchuk, Ievgen; Herre, Patrick; Brandl, Marco; Osvet, Andres; Hock, Rainer; Peukert, Wolfgang; Schweizer, Peter; Spiecker, Erdmann; Batentschuk, Miroslaw; Brabec, Christoph (Chemical Communications, 2017)
Quantum size-confined CHNHPbX (X = Br and I) perovskite nanoplatelets with remarkably high photoluminescence quantum yield (up to 90%) were synthesized by ligand-assisted re-precipitation. Thickness-tunability was realized by varying the oleylamine and oleic acid ligand ratio. This method allows tailoring the nanoplatelet thickness by adjusting the number of unit cell monolayers. Broadly tunable emission wavelengths (450-730 nm) are achieved via the pronounced quantum size effect without anion-halide mixing.

Ligand Tuning of Localized Surface Plasmon Resonances in Antimony-Doped Tin Oxide Nanocrystals - Balitskii, Olexiy; Mashkov, Oleksandr; Barabash, Anastasiia; Rehm, Viktor; Afify, Hany A.; Li, Ning; Hammer, Maria; Brabec, Christoph; Eigen, Andreas; Halik, Marcus; Yarema, Olesya; Yarema, Maksym; et al. (Nanomaterials, 2022)
Aliovalent-doped metal oxide nanocrystals exhibiting localized surface plasmons (LSPRs) are applied in systems that require reflection/scattering/absorption in infrared and optical transparency in visible. Indium tin oxide (ITO) is currently leading the field, but indium resources are known to be very restricted. Antimony-doped tin oxide (ATO) is a cheap candidate to substitute the ITO, but it exhibits less advantageous electronic properties and limited control of the LSPRs. To date, LSPR tuning in ATO NCs has been achieved electrochemically and by aliovalent doping, with a significant decrease in doping efficiency with an increasing doping level. Here, we synthesize plasmonic ATO nanocrystals (NCs) via a solvothermal route and demonstrate ligand exchange to tune the LSPR energies. Attachment of ligands acting as Lewis acids and bases results in LSPR peak shifts with a doping efficiency overcoming those by aliovalent doping. Thus, this strategy is of potential interest for plasmon implementations, which are of potential interest for infrared upconversion, smart glazing, heat absorbers, or thermal barriers.
CRIS-Team WoS Importer:2022-10-28

Light harvesting enhancement upon incorporating alloy structured CdSeXTe1−X quantum dots in DPP:PC61BM bulk heterojunction solar cells - Soltani, Rezvan; Katbab, Ali Asghar; Schaumberger, Kerstin; Gasparini, Nicola; Brabec, Christoph; Rechberger, Stefanie; Spiecker, Erdmann; Alabau, Antoni Gimeno; Ruland, Andres; Saha, Avishek; Guldi, Dirk Michael; Sgobba, Vito; et al. (Journal of Materials Chemistry C, 2017)
Hybrid solar cells based on the pDPP5T-2 electron donating polymer, [6,6]-phenyl-C-butyric acid methyl ester (PCBM) and cadmium selenide telluride (CdSeTe) quantum dots (QDs) are fabricated and their photovoltaic performance and optoelectronic properties are investigated as a function of QD loading. The power conversion efficiency (PCE) of hybrid solar cells is improved up to 5.11% for the device containing 4 wt% of QDs which is mainly due to the enhancement in short circuit current density (J) resulting from increased light harvesting. A full-fledged study is performed on the microstructure, charge transfer/transport and recombination mechanisms of our ternary hybrid solar cells by employing various advanced techniques. The transmission electron microscopy (TEM) results reveal the non-agglomerated and uniform distribution of the CdSeTe QDs within the pDPP5T-2:PCBM host matrix at low QD concentrations. Transient absorption spectroscopy (TAS) showed a slower charge carrier recombination rate due to the introduction of QDs into the photoactive layer. It can be attributed to the more efficient exciton dissociation in ternary systems. These findings are consistent with the photovoltaic properties of the device.
Keywords: Engineering controlled terms: Absorption spectroscopy; Butyric acid; Cadmium compounds; Cadmium telluride; Charge transfer; Heterojunctions; High resolution transmission electron microscopy; Nanocrystals; Polymer solar cells; Semiconductor quantum dots; Solar power generation; Transmission electron microscopy Bulk heterojunction solar cells; Charge carrier recombination; Light harvesting enhancement; Optoelectronic properties; Photovoltaic performance; Power conversion efficiencies; Recombination mechanisms; Transient absorption spectroscopies Engineering main heading: Solar cells

Light intensity modulated impedance spectroscopy (LIMIS) in all-solid-state solar cells at open-circuit - Almora, Osbel; Zhao, Yicheng; Du, Xiaoyan; Heumüller, Thomas; Matt, Gebhard; Garcia-Belmonte, Germà; Brabec, Christoph (Nano Energy, 2020)
Potentiostatic impedance spectroscopy (IS) is a well-established characterization technique for elucidating the electric resistivity and capacitive features of materials and devices. For solar cells, by applying a small voltage perturbation the current signal is recorded and the recombination processes and defect distributions can be accessed. In this work, a photo-impedance approach, named “light intensity modulated impedance spectroscopy” (LIMIS), is first time tested in all-solid-state photovoltaics by individually recording photocurrent (IMPS) and photovoltage (IMVS) responsivity signals due to a small light perturbation at open-circuit (OC), and combining them: LIMIS = IMVS/IMPS. The experimental LIMIS spectra from silicon, organic, and perovskite solar cells are presented and compared with IS. Our theoretical analyses, including equivalent circuit models, show a correction to the lifetimes values by obtaining the total differential resistances and capacitances combining IS and LIMIS. This correction addresses some discrepancies among different techniques, as also shown with photo-induced transient photovoltage. The experimental differences between IS and LIMIS proves the unsuitability of the superposition principle and suggest a bias-dependent photo-current correction to the empirical Shockley equation of the steady-state current at different illumination intensities around OC. In addition, new features are reported for the low-frequency capacitance of perovskite solar cells.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Charge carrier generation rate; Impedance spectroscopy; Light intensity modulation; Perovskites; Photocurrent; Solar cells

Light management and light manipulation technologies for thin film photovoltaics applications - Brabec, Christoph; Batentschuk, Miroslaw; Forberich, Karen (European Quantum Electronics Conference, EQEC 2015, 2015)

Light propagation in phosphor-filled matrices for photovoltaic PL down-shifting - Solodovnyk, Anastasiia; Lipovsek, Benjamin; Forberich, Karen; Stern, Edda; Batentschuk, Miroslaw; Topic, Marko; Brabec, Christoph (Reflection, Scattering, and Diffraction from Surfaces IV, 2014)
Efficient transparent light converters have received lately a growing interest from optical device industries (LEDs, PV, etc.). While organic luminescent dyes were tested in PV light-converting application, such restrictions as small Stokes shifts, short lifetimes, and relatively high costs must yet be overcome. Alternatively, use of phosphors in transparent matrix materials would mean a major breakthrough for this technology, as phosphors exhibit long-term stability and are widely available. For the fabrication of phosphor-filled layers tailored specifically for the desired application, it is of great importance to gain deep understanding of light propagation through the layers, including the detailed optical interplay between the phosphor particles and the matrix material. Our measurements show that absorption and luminescent behavior of the phosphors and especially the scattering of light by the phosphor particles play an important role. In this contribution we have investigated refractive index difference between transparent binder and phosphors. Commercially available highly luminescent UV and near-UV absorbing μm-sized powder is chosen for the fabrication of phosphor-filled layers with varied refractive index of transparent polymer matrix, and well-defined particle size distributions. Solution-processed thick layers on glass substrates are optically analyzed and compared with simulation results acquired from CROWM, a combined wave optics/ray optics home-built software. The results demonstrate the inter-dependence of the layer parameters, prove the importance of careful optimization steps required for fabrication of efficient light converting layers, and, thus, show a path into the future of this promising approach.
Keywords: Light absorption; Matrix; Mie scattering; Phosphor particles; Ray-tracing; Refractive index; Solution processed layers

Local Observation of Phase Segregation in Mixed-Halide Perovskite. - Tang, Xiaofeng; van den Berg, Marius; Gu, Ening; Horneber, Anke; Matt, Gebhard; Osvet, Andres; Meixner, Alfred J.; Zhang, Dai; Brabec, Christoph (Nano Letters, 2018)
Mixed-halide perovskites have emerged as promising materials for optoelectronics due to their tunable bandgap in the entire visible region. A challenge remains however in the photo-induced phase-segregation, narrowing the bandgap of mixedhalide perovskites under illumination thus restricting applications. Here we use a combination of spatially-resolved and bulk measurements to give an in-depth insight into this important yet unclear phenomenon. We demonstrate that photo-induced phase-segregation in mixed-halide perovskites selectively occurs at the grain boundaries rather than within the grain centers by using shear-force scanning probe microscopy in combination with confocal optical spectroscopy. Such difference is further evidenced by light-biased bulk Fourier-transform photocurrent spectroscopy, which shows the iodine-rich domain as a minority phase coexisting with the homogenously mixed phase during illumination. By mapping the surface potential of mixed-halide perovskites, we evidence the higher concentration of positive space charge near grain boundary possibly provides the initial driving force for phasesegregation, while entropic mixing dominates the reverse process. Our work offers detailed insight into the microscopic processes occurring at the boundary of crystalline perovskite grains and will support the development of better passivation strategies, ultimately allowing to process environmentally more stable perovskite films.
Keywords: Perovskite; Photovoltaic; Photoluminescence; Phase-segregation; Scanning probe microscopy; Optical spectroscopy

Lock-in thermography as a tool for quality control of photovoltaic modules - Vetter, Andreas; Fecher, Frank; Adams, Jens; Schaeffler, Raymund; Theisen, Jean-Patrick; Brabec, Christoph; Buerhop, Claudia (Energy Science and Engineering, 2013)
In this short communication, we present a method which utilizes contactless ILIT (illuminated lock-in thermography) measurement of a photovoltaic (PV) module and image postprocessing in order to calculate the peak power Pmpp of the module and to study the influence of local defects on the module performance. In total, 103 Copper-Indium-Gallium-Diselenide (CIGS) modules were investigated and the results showed a good correlation (mean error less than 6%) between the calculated IR-signal and the measured Pmpp. We performed our study on CIGS modules but the presented approach is not restricted to CIGS modules. The method provides a valuable tool for PV quality control. We present a method which utilizes contactless ILIT (illuminated lock-in thermography) measurement of PV modules and image postprocessing in order to calculate the peak power of the modules. The method provides a valuable tool for PV quality control. © 2013 Society of Chemical Industry and John Wiley & Sons, Ltd.
Keywords: Engineering controlled terms: Image processingInfrared imagingLocks (fasteners)Photovoltaic cellsQuality assuranceQuality controlSelenium compoundsSolar energySolar power generationThermography (temperature measurement) Compendex keywords Copper indium gallium diselenideGood correlationsIlluminated lock-in thermographiesLocal defectsLockin thermographyModule performancePhotovoltaic modulesPhotovoltaics Engineering main heading: Thermography (imaging)

Long Lived OPV – what are the lifetime limitations of organic solar cells - Brabec, Christoph; Heumüller, Thomas (2022)

Long-term power degradation analysis of crystalline silicon PV modules using indoor and outdoor measurement techniques - Carigiet, Fabian; Brabec, Christoph; Baumgartner, Franz P. (Renewable and Sustainable Energy Reviews, 2021)
Annual degradation rates of PV modules are important in the yield prediction. For a high-quality PV module, these rates are lower than the measurement uncertainty of a nominal power measurement performed in todays most advanced certified photovoltaic reference laboratory. Therefore, the analysis requires a well thought out methodology that can compare the data relative to each other or relative to an unused module stored in the dark on an annual base. Over the past 10 years, several multi c-Si and HIT modules have been accurately monitored in a string and single module setup by an outdoor performance measurement system. Additionally, all modules have been dismantled and measured using an indoor flasher measurement system once every year. With this unique measurement setup, the annual degradation rates of multi c-Si modules and HIT modules are quantified based on three different analysis methodologies. The multi c-Si modules showed an average annual degradation rate of 0.18% ± 0.06% and 0.29% ± 0.06% measured by the outdoor and indoor system, respectively. The indoor analysis of the HIT modules yielded an average annual degradation of 0.26% ± 0.05%. That corresponds to half of the degradation observed by the outdoor analysis method. Further evaluations of the performance ratio PR confirmed the results gained by the indoor methodology. The comparison of the standard PR with a temperature-corrected PR’STC for both technologies showed that the benefit of the lower temperature coefficient of the HIT technology is eliminated by its worse low light behaviour.
CRIS-Team Scopus Importer:2021-04-09
Keywords: c-Si solar cell; Degradation rate; Outdoor performance monitoring; Outdoor test field; Performance ratio; Solar simulator measurement

Looking beyond the Surface: The Band Gap of Bulk Methylammonium Lead Iodide - Schuster, Oskar; Wientjes, Peter; Shrestha, Shreetu; Levchuk, Ievgen; Sytnyk, Mykhailo; Matt, Gebhard; Osvet, Andres; Batentschuk, Miroslaw; Heiß, Wolfgang; Brabec, Christoph; Fauster, Thomas; Niesner, Daniel (Nano Letters, 2020)
Despite the intense research on photovoltaic lead halide perovskites, reported optical properties as basic as the absorption onset and the optical band gap vary significantly. To unambiguously answer the question whether the discrepancies are a result of differences between bulk and "near-surface" material, we perform two nonlinear spectroscopies with drastically different information depths on single crystals of the prototypical (CH3NH3)PbI3 methylammonium lead iodide. Two-photon absorption, detected via the resulting generation of carriers and photocurrents (2PI-PC), probes the interband transitions with an information depth in the millimeter range relevant for bulk (single-crystal) material. In contrast, the transient magneto-optical Kerr effect (trMOKE) measured in a reflection geometry determines the excitonic transition energies in the region near (hundreds of nm) the surface which also determine the optical properties in typical thin films. To identify differences between structural phases, we sweep the sample temperature across the orthorhombic-tetragonal phase transition temperature. In the application-relevant room-temperature tetragonal phase (at 170 K), we find a bulk band gap of 1.55 ± 0.01 eV, whereas in the near-surface region excitonic transitions occur at 1.59 ± 0.01 eV. The latter value is consistent with previous reflectance measurements by other groups and considerably higher than the bulk band gap. The small band gap of the bulk material explains the extended infrared absorption of crystalline perovskite solar cells, the low-energy bands which carry optically driven spin-polarized currents, and the narrow bandwidth of crystalline perovskite photodetectors making use of the spectral filtering at the surface.
CRIS-Team Scopus Importer:2020-05-22
Keywords: band gap; CH3NH3PbI3; lead halide perovskite; magneto-optical Kerr effect; nonlinear absorption

Loss analysis on CIGS-modules by using contactless, imaging illuminated lock-in thermography and 2D electrical simulations - Fecher, Frank; Adams, Jens; Vetter, Andreas; Buerhop-Lutz, Claudia; Brabec, Christoph (40th IEEE Photovoltaic Specialist Conference, 2014)
Loss analysis on CIGS-modules are demonstrated by using contactless, imaging illuminated lock-in thermography (ILIT). Power dissipating defects, like shunts, were visualized in commercially manufactured test modules (30 × 30 cm). The evaluations of the ILIT-measurements displayed a correlations with the loss in maximum output power and in open circuit voltage. 2D finite element simulations of the shunts confirmed the correlations. A further simulative parameter study gives a deep understanding of the influence of a shunt on the electrical performance in thin film modules. As ILIT is a contactless and fast method, it has the potential to become a powerful tool for in-line characterization. Furthermore, we consider this technique to be applicable also to other thin film module technologies, like CdTe, a-Si:H or organic photovoltaics.
Keywords: lock-in thermography; module performance; photovoltaic; Pmpp; shunt; Voc

Low-cost copper complexes as p-dopants in solution processable hole transport layers - Kellermann, Renate; Taroata, Dan; Maltenberger, Anna; Hartmann, David; Brabec, Christoph; Schmid, Guenter (Applied Physics Letters, 2015)
We demonstrate the usage of the Lewis-acidic copper(II)hexafluoroacetylacetonate (Cu(hfac)2) and copper(II)trifluoroacetylacetonate (Cu(tfac)2) as low-cost p-dopants for conductivity enhancement of solution processable hole transport layers based on small molecules in organic light emitting diodes (OLEDs). The materials were clearly soluble in mixtures of environmentally friendly anisole and xylene and spin-coated under ambient atmosphere. Enhancements of two and four orders of magnitude, reaching 4.0×10-11 S/cm with a dopant concentration of only 2mol% Cu(hfac)2 and 1.5×10-9 S/cm with 5mol% Cu(tfac)2 in 2,2′,7,7′-tetra(N,N-ditolyl)amino-9,9-spiro-bifluorene (spiro-TTB), respectively, were achieved. Red light emitting diodes were fabricated with reduced driving voltages and enhanced current and power efficiencies (8.6lm/W with Cu(hfac)2 and 5.6lm/W with Cu(tfac)2) compared to the OLED with undoped spiro-TTB (3.9lm/W). The OLED with Cu(hfac)2 doped spiro-TTB showed an over 8 times improved LT50 lifetime of 70h at a starting luminance of 5000cd/m2. The LT50 lifetime of the reference OLED with PEDOT:PSS was only 8h. Both non-optimized OLEDs were operated at similar driving voltage and power efficiency.
Keywords: Engineering controlled terms: Coated materials; Conducting polymers; Copper; Doping (additives); Hole mobility; Light emitting diodes; Organic light emitting diodes (OLED) Ambient atmosphere; Conductivity enhancement; Dopant concentrations; Hole transport layers; Orders of magnitude; Organic light emitting diodes(OLEDs); Reduced driving voltage; Solution processable Engineering main heading: Copper compounds

Low-temperature and hysteresis-free electron-transporting layers for efficient, regular, and planar structure perovskite solar cells - Hou, Yi; Ramírez Quiroz, César Omar; Scheiner, Simon; Chen, Wei; Stubhan, Tobias; Hirsch, Andreas; Halik, Marcus; Brabec, Christoph (Advanced Energy Materials, 2015)
With the aim of fully utilizing the low processing temperatures of perovskite solar cells, significant progress in replacing high temperature processed TiO by various low-temperature solution processed electron transporting layers (LT-ETLs) was recently reported. Here, recent progress in the development of LT-ETLs for regular planar structure perovskite solar cells, which is essential for achieving high efficiency in parallel to avoiding hysteresis, is reviewed. In addition, the application of a novel hysteresis-free LT-ETLs for regular planar perovskite solar cells in our laboratory is briefly discussed. By incorporating a low temperature processed WOnanoparticular layer in combination with a mixed fullerene functionalized self-assembled monolayers (SAMs), a regular, planar structure, and hysteresis-free perovskite solar cell with a maximum efficiency of almost 15% can be fabricated. Recent progress in the development of low temperature processed electron-transporting layers for regular planar structure perovskite solar cells is reviewed. Moreover, the application of a novel mixed self-assembled monolayers in hysteresis-free perovskite solar cells is briefly discussed. The as-fabricated perovskite solar cells show a maximum efficiency of almost 15%.
Keywords: electron-transporting layers; hysteresis-free solar cells; low-temperature solution processed; perovskite solar cells

Low Temperature Processed Fully Printed Efficient Planar Structure Carbon Electrode Perovskite Solar Cells and Modules - Yang, Fu; Dong, Lirong; Jang, DongJu; Saparov, Begench; Tam, Kai Cheong; Zhang, Kaicheng; Li, Ning; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Energy Materials, 2021)
Scalable deposition processes at low temperature are urgently needed for the commercialization of perovskite solar cells (PSCs) as they can decrease the energy payback time of PSCs technology. In this work, a processing protocol is presented for highly efficient and stable planar n–i–p structure PSCs with carbon as the top electrode (carbon-PSCs) fully printed at fairly low temperature by using cheap materials under ambient conditions, thus meeting the requirements for scalable production on an industrial level. High-quality perovskite layers are achieved by using a combinatorial engineering concept, including solvent engineering, additive engineering, and processing engineering. The optimized carbon-PSCs with all layers including electron transport layer, perovskite, hole transport layer, and carbon electrode which are printed under ambient conditions show efficiencies exceeding 18% with enhanced stability, retaining 100% of their initial efficiency after 5000 h in a humid atmosphere. Finally, large-area perovskite modules are successfully obtained and outstanding performance is shown with an efficiency of 15.3% by optimizing the femtosecond laser parameters for the P2 line patterning. These results represent important progress toward fully printed planar carbon electrode perovskite devices as a promising approach for the scaling up and worldwide application of PSCs.
CRIS-Team Scopus Importer:2021-06-18
Keywords: carbon electrodes; doctor blades; fully printed devices; long-term stability; perovskite solar cells

Low-Temperature Solution-Processed Kesterite Solar Cell Based on in Situ Deposition of Ultrathin Absorber Layer - Hou, Yi; Azimi, Seyed Hamed; Gasparini, Nicola; Savador, Michael; Chen, Wei; Khanzada, Laraib Sarfraz; Brandl, Marco; Hock, Rainer; Brabec, Christoph (ACS Applied Materials and Interfaces, 2015)
The production of high-performance, solution-processed kesterite Cu2ZnSn(Sx,Se1-x)4 (CZTSSe) solar cells typically relies on high-temperature crystallization processes in chalcogen-containing atmosphere and often on the use of environmentally harmful solvents, which could hinder the widespread adoption of this technology. We report a method for processing selenium free Cu2ZnSnS4 (CZTS) solar cells based on a short annealing step at temperatures as low as 350 °C using a molecular based precursor, fully avoiding highly toxic solvents and high-temperature sulfurization. We show that a simple device structure consisting of ITO/CZTS/CdS/Al and comprising an extremely thin absorber layer (∼110 nm) achieves a current density of 8.6 mA/cm2. Over the course of 400 days under ambient conditions encapsulated devices retain close to 100% of their original efficiency. Using impedance spectroscopy and photoinduced charge carrier extraction by linearly increasing voltage (photo-CELIV), we demonstrate that reduced charge carrier mobility is one limiting parameter of low-temperature CZTS photovoltaics. These results may inform less energy demanding strategies for the production of CZTS optoelectronic layers compatible with large-scale processing techniques.
Keywords: CZTS; device stability; kesterite solar cells; low-temperature processing; molecular based precursor

Low temperature, solution processed metal oxide buffer layers fulfilling large area production requirements - Stubhan, Tobias; Litzov, Ivan; Li, Ning; Wang, Hao; Krantz, Johannes; Machui, Florian; Steidl, M.; Oh, H.; Matt, Gebhard; Brabec, Christoph (Proceedings of SPIE, 2012)
This paper is a review of our previous work on the field of low temperature, solution processed metal oxide buffer layers published in various journals. Our work focuses on zinc oxide (ZnO) and aluminum-doped zinc oxide (AZO) as n-type and molybdenum oxide (MoO3) as p-type solution processed buffer layer. In addition to that, we investigate the surface modification of AZO using phosphonic acid-anchored aliphatic and fullerene self assembled monolayers (SAMs
Keywords: Aluminum-doped zinc oxide; Low temperatures; Metal oxides; P-type; Phosphonic; Production requirements; Solution-processed; Zinc oxide (ZnO) Engineering controlled terms: Aluminum; Metallic compounds; Molybdenum oxide; Optical waveguides; Organic acids; Self assembled monolayers; Temperature; Zinc oxide Engineering main heading: Buffer layers

Luminescence Analysis of PV-Module Soiling in Germany - Doll, Bernd; Forberich, Karen; Hepp, Johannes; Langner, Stefan; Buerhop-Lutz, Claudia; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (IEEE Journal of Photovoltaics, 2021)
Energy losses of photovoltaic (PV) plants because of soiling are a problem in all regions, including Germany. Soft soiling, caused by a uniform dust film, is shading a PV module and is reducing yield depending on the thickness of the debris layer. Hard soiling, caused by agglomerations of dust or dirt, only covers parts of a PV module, and it causes local shading. A spot check of modules from different PV power plants in Germany revealed a power reduction because of soft- and hard soiling of up to 6%. Determination of soiling type and amount is a prerequisite for decisions about cleaning and for optimizing yield. In this article, we show that luminescence imaging can be used to detect and characterize soiling and quantify losses. For this purpose, we compare luminescence images before and after cleaning and we show that soiling becomes detectable and power losses quantifiable from difference images. We also show that the impact of hard soiling can be quantified from a single photoluminescence (PL) image. This technique may enable a fully automated quantification of power losses because of hard soiling in PV- modules and strings in the future.
CRIS-Team WoS Importer:2021-12-31

Luminescence properties and energy transfer processes in YAG:Yb,Er single crystalline films - Zorenko, Yu; Gorbenko, V.; Savchyn, V.; Batentschuk, Miroslaw; Osvet, Andres; Brabec, Christoph (Radiation Measurements, 2013)
The paper is dedicated to the study of the optical properties of YAG:Yb,Er single-crystalline films (SCF) grown by liquid phase epitaxy. The absorption, cathodoluminescence and time-resolved photoluminescence spectra and photoluminescence decay curves were measured for the SCFs with different doping levels of Er (from 0.6 to 4.2 at.%) and Yb (from 0.1 to 0.6 at.%). The spectra, excited by synchrotron radiation in the fundamental absorption range of the YAG and in the intraionic absorption bands of both dopants, reveal energy transfer from the YAG host to the Er and Yb ions and between these ions. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Er 3+ and Yb3+ dopants; Liquid phase epitaxy; Luminescence; Single crystalline films; YAG

Luminescent down-shifting layers with Eu2+ and Eu3+ doped strontium compound particles for photovoltaics - Solodovnyk, Anastasiia; Hollmann, Andre; Osvet, Andres; Forberich, Karen; Stern, Edda; Batentschuk, Miroslaw; Klupp Taylor, Robin; Brabec, Christoph (Next Generation Technologies for Solar Energy Conversion V, 2014)
In this contribution we discuss luminescent down-shifting (LDS) systems consisting of a polymer matrix filled with phosphor particles. It is an elegant approach to make a use of potentially destructive or otherwise wasted high energy photons and diminish charge carrier losses caused by thermalization in photovoltaics. Sub-micron and micron sized particles of strontium aluminate doped with Eu2+ and strontium carbonate doped with Eu3+ ions are chosen for the application due to their suitable absorption in UV spectral region. These particles exhibit strong luminescence in the visible range between 520 and 650 nm. The systems are carefully designed to meet critical optical requirements such as high transparency in the visible spectrum as well as sufficient absorption of UV light. They are coated on quartz glass substrates (20 x 20 x 1 mm) and can be easily laminated to different kinds of solar cells without any modification to well-established device fabrication processes. Optical characterization further confirms that particles of a few microns in size generate strong light scattering in layers due to the sizes slightly larger than visible light wavelengths. Dried thick layers of 20 to 100 μm are tested with CIGS and organic cells. The concept of light conversion is experimentally proven. However, optical losses cause a reduction in the overall performance of the tested devices. Possible ways to bring down the amount of light scattering and, thus, to increase optical transmission for the studied system are also addressed, and are a subject of future research.
Keywords: Light absorption; Light scattering; Luminescent down-shifting; Phosphor particles; Polymer matrix; Solar cell; Solution processed layers

Luminescent properties and energy transfer processes in YAG:Er single crystalline films - Zorenko, Yu.; Gorbenko, V.; Zorenko, T.; Savchyn, V.; Batentschuk, Miroslaw; Osvet, Andres; Brabec, Christoph (Journal of Luminescence, 2014)
The paper is dedicated to studying the optical properties of YAG:Er single crystalline films (SCF) grown by liquid phase epitaxy. The absorption, cathodoluminescence and photoluminescence spectra were measured for the YAG:Er SCFs with different doping levels of Er from 0.735 to 6.6 at%. The luminescence spectra and luminescence excitation spectra under synchrotron radiation excitation in the fundamental absorption range of the YAG and in the intrinsic f-d absorption bands of Er ions reveal the peculiarities of energy transfer from the YAG host to the Er ions. © 2014 Elsevier B.V.
Keywords: Liquid phase epitaxy; Luminescence; Single crystalline films; YAG

Luminescent properties of LuAG:Yb and YAG:Yb single crystalline films grown by Liquid Phase Epitaxy method - Zorenko, Yu; Zorenko, T.; Gorbenko, V.; Voznyak, T.; Popielarski, P.; Batentschuk, Miroslaw; Osvet, Andres; Brabec, Christoph; Kolobanov, V.; Spasky, D.; Fedorov, A. (Elsevier, 2016)
In this work, investigation of the spectroscopic parameters of the luminescence of Yb3+ ions in single crystalline films of Lu3Al5O12 and Y3Al5O12 garnets was performed using the synchrotron radiation excitation with the energy in the range of Yb3+ charge transitions (CT), exciton range and the onset of interband transitions of these garnets. The basic spectroscopic parameters of the Yb3+ CT luminescence in LuAG and YAG hosts were determined and summarized with taking into account the differences in the band gap structure of these garnets. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Luminescence; Liquid phase epitaxy; Single crystalline film; YAG and LuAG garnets; Yb dopant

Machine Learning for Ultra High Throughput Screening of Organic Solar Cells: Solving the Needle in the Haystack Problem - Hußner, Markus; Pacalaj, Richard Adam; Olaf Müller-Dieckert, Gerhard; Liu, Chao; Zhou, Zhisheng; Majeed, Nahdia; Greedy, Steve; Ramirez, Ivan; Li, Ning; Hosseini, Seyed Mehrdad; Uhrich, Christian; Brabec, Christoph; et al. (Advanced Energy Materials, 2024)
Over the last two decades the organic solar cell community has synthesized tens of thousands of novel polymers and small molecules in the search for an optimum light harvesting material. These materials are often crudely evaluated simply by measuring the current–voltage (JV) curves in the light to obtain power conversion efficiencies (PCEs). Materials with low PCEs are quickly disregarded in the search for higher efficiencies. More complex measurements such as frequency/time domain characterization that could explain why the material performed as it is often not performed as they are too time consuming/complex. This limited feedback forced the field to advance using a more or less random walk of material development and has significantly slowed progress. Herein, a simple technique based on machine learning that can quickly and accurately extract recombination time constants and charge carrier mobilities as a function of light intensity simply from light/dark JV curves alone. This technique reduces the time to fully analyze a working cell from weeks to seconds and opens up the possibility of not only fully characterizing new devices as they are fabricated, but also data mining historical data sets for promising materials the community has overlooked.
CRIS-Team Scopus Importer:2024-01-26
Keywords: drift diffusion; machine learning; organic photovoltaic; solar

Managing Phase Orientation and Crystallinity of Printed Dion-Jacobson 2D Perovskite Layers via Controlling Crystallization Kinetics - Chen, Yijun; Hu, Jinlong; Xu, Zhenhua; Jiang, Zhengyan; Chen, Shi; Xu, Baomin; Xiao, Xiudi; Liu, Xianhu; Forberich, Karen; Brabec, Christoph; Mai, Yaohua; Guo, Fei (Advanced Functional Materials, 2022)
Two-dimensional perovskites have attracted substantial attention for solar cell applications because of their higher stability as compared to their 3D analogs. To achieve efficient charge transport in thin-film devices, obtaining high crystalline perovskite crystals perpendicularly aligned to the substrate is of great importance. This article reports the scalable printing of high-quality Dion-Jacobson (DJ) perovskite thin films via tailoring crystallization kinetics. Introducing a small amount of 1-methyl-2-pyrrolidinone to the conventional N,N-dimethylformamide:dimethyl sulfoxide-based precursor, the strong coordination with ammonium spacers enables a notably retarded crystallization, which results in perovskite films with distinctly enhanced crystallinity, highly vertical orientation, and graded phase distribution. Accordingly, efficient charge generation and ultrafast interphase charge transfer are realized. The champion DJ perovskite device delivers a high current density of 17.10 mA cm(-2), an impressive open-circuit voltage of 1.21 V, leading to a stabilized efficiency of 16.19%. In addition, the devices processed from the ternary solvent exhibit remarkably improved stability under stimuli with light, heat, and humidity, benefiting from their superb phase stability. This work demonstrates an important advancement in scalable deposition of DJ perovskite thin films for efficient and stable photovoltaic devices.
CRIS-Team WoS Importer:2022-02-18

Material Properties of Laser-Welded Thin Silicon Foils - Hessmann, M. T.; Kunz, T.; Voigt, M.; Cvecek, K.; Schmidt, Michael; Bochmann, A.; Christiansen, S.; Auer, R.; Brabec, Christoph (International Journal of Photoenergy, 2013)
An extended monocrystalline silicon base foil offers a great opportunity to combine low-cost production with high efficiency silicon solar cells on a large scale. By overcoming the area restriction of ingot-based monocrystalline silicon wafer production, costs could be decreased to thin film solar cell range. The extended monocrystalline silicon base foil consists of several individual thin silicon wafers which are welded together. A comparison of three different approaches to weld 50 mu m thin silicon foils is investigated here: (1) laser spot welding with low constant feed speed, (2) laser line welding, and (3) keyhole welding. Cross-sections are prepared and analyzed by electron backscatter diffraction (EBSD) to reveal changes in the crystal structure at the welding side after laser irradiation. The treatment leads to the appearance of new grains and boundaries. The induced internal stress, using the three different laser welding processes, was investigated by micro-Raman analysis. We conclude that the keyhole welding process is the most favorable to produce thin silicon foil

Material Strategies to Accelerate OPV Technology Toward a GW Technology - Brabec, Christoph; Distler, Andreas; Du, Xiaoyan; Egelhaaf, Hans-Joachim; Hauch, Jens; Heumüller, Thomas; Li, Ning (Advanced Energy Materials, 2020)
With the rise of the solar power century, photovoltaic applications and installations will go beyond the traditional green field power plants and enter any aspect of daily life. Organic photovoltaics (OPVs) demonstrate certified cell efficiencies of over 17% and are expected to contribute to versatile applications powered by solar energy, for instance, applications rely on flexibility, transparency, color management, or integrability. In this work, the progress of OPV technology is briefly reviewed and the material strategies to accelerate OPV technology toward a GW era are analyzed. In addition to the exciting efficiency values achieved for small area devices, there are many important criteria deciding the success of OPV technology. By taking into consideration the synthetic complexity of OPV materials and the operational stability of OPV devices, the industrial figure of merit (i-FoM) is proposed as a fast and reliable method to verify the true potential of a novel material. Furthermore, “soft” key performance indicators are introduced, such as toxicity, flexibility, transparency, processing, which require different development strategies to reflect the potential of OPV technology for specific applications.
CRIS-Team Scopus Importer:2020-10-09
Keywords: device operational stability; organic photovoltaics; organic solar modules; synthetic complexity

Maximizing concentrated solar power (CSP) plant overall efficiencies by using spectral selective absorbers at optimal operation temperatures - Burlafinger, Klaus; Vetter, Andreas; Brabec, Christoph (Solar Energy, 2015)
Selective absorbers for CSP plants to suppress thermal losses and to increase the efficiency is a promising topic and strong scientific efforts have been spent on how to design and realize such materials. However, there has been no comprehensive optimization analysis of the overall efficiency of CSP plants with selective absorbers.We performed a comprehensive computational parameter study of operation temperature and optical properties of the absorber and investigated their effect on the overall plant efficiency in dependence of sun light concentration up to C=2000 suns. Optimal operation temperatures were shown not to exceed 1383. K. By using selective absorbers instead of a black body or currently used materials, our assessment yields a potential electrical power output gain of up to around 35%. Our investigations also provide the optical parameters of an ideal (perfect selective) absorber. Its optimal cut off wavelength λcut lies around 2.4. μm for concentration factors below 120 and above 600 suns. For C in the range of 120-600 suns the value of the cut off wavelength is 1.79. μm. Simulating non-ideal (realistic) absorption properties, it was found that the strongest influence is caused by high absorption at low wavelengths. Low emittance at longer wavelengths plays a less important role. Also the sharpness of the transition from high absorption to low emittance plays a minor role regarding overall plant efficiency. As a rule of thumb, the cut-off wavelength should be at around 2.4. μm when assuming realistic (non-ideal) spectral selectivity. Finally, the theoretical maximum overall efficiency of a CSP plant achievable by an ideal selective absorber was calculated to up to 73% at 2000 suns and even up to 65% for a selective absorber with realistic optical properties.
Keywords: Absorber; CSP; Optimal operation temperature; Overall efficiency; Selective; Spectral

Maximizing Performance and Stability of Organic Solar Cells at Low Driving Force for Charge Separation - Lüer, Larry; Wang, Rong; Liu, Chao; Dube, Henry; Heumüller, Thomas; Hauch, Jens; Brabec, Christoph (Advanced Science, 2023)
Thanks to the development of novel electron acceptor materials, the power conversion efficiencies (PCE) of organic photovoltaic (OPV) devices are now approaching 20%. Further improvement of PCE is complicated by the need for a driving force to split strongly bound excitons into free charges, causing voltage losses. This review discusses recent approaches to finding efficient OPV systems with minimal driving force, combining near unity quantum efficiency (maximum short circuit currents) with optimal energy efficiency (maximum open circuit voltages). The authors discuss apparently contradicting results on the amount of exciton binding in recent literature, and approaches to harmonize the findings. A comprehensive view is then presented on motifs providing a driving force for charge separation, namely hybridization at the donor:acceptor interface and polarization effects in the bulk, of which quadrupole moments (electrostatics) play a leading role. Apart from controlling the energies of the involved states, these motifs also control the dynamics of recombination processes, which are essential to avoid voltage and fill factor losses. Importantly, all motifs are shown to depend on both molecular structure and process conditions. The resulting high dimensional search space advocates for high throughput (HT) workflows. The final part of the review presents recent HT studies finding consolidated structure–property relationships in OPV films and devices from various deposition methods, from research to industrial upscaling.
CRIS-Team Scopus Importer:2023-12-15
Keywords: electrostatics; exciton binding energy; high throughput methods; hybridization; open circuit voltage losses; organic photovoltaics

Mechanical and Electrical Failure of Silver Nanowire Electrodes: A Scale Bridging In Situ Electron Microscopy Study - Schrenker, Nadine; Schweizer, Peter; Moninger, Marco; Karpstein, Nicolas; Mackovic, Mirza; Spyropoulos, Georgios; Göbelt, Manuela; Christiansen, Silke; Brabec, Christoph; Spiecker, Erdmann (Microscopy and Microanalysis, 2019)

Mechanical Failure of Transparent Flexible Silver Nanowire Networks for Solar Cells using 3D X-Ray Nano Tomography and Electron Microscopy - Englisch, Silvan; Wirth, Janis; Schrenker, Nadine; Tam, Kai Cheong; Egelhaaf, Hans-Joachim; Brabec, Christoph; Spiecker, Erdmann (Microscopy and Microanalysis, 2018)

Mechanochemical Synthesis of Cesium Titanium Halide Perovskites Cs2TiBr6-xIx (x=0, 2, 4, 6) - Kupfer, Christian; Elia, Jack; Kato, Masashi; Osvet, Andres; Brabec, Christoph (Crystal Research and Technology, 2022)
Perovskite materials have a great variety of applications, such as X-ray detection, lasing and piezoelectric, or solar energy harvesting. While achieving record efficiencies, perovskite solar cells suffer from the presence of toxic lead in their crystal structure. One possibility to circumvent this issue is via the family of vacancy-ordered double-perovskites, where lead atoms are replaced alternatingly by a tetravalent atom and a vacant lattice site. From this material family, Cs2TiBr6 has recently emerged as a promising candidate due to its favorable reported properties for photovoltaic applications specifically. This paper presents a novel and facile synthesis route to obtain phase-pure Cs2TiBr6 and its lesser-studied iodine-based relatives Cs2TiBr4I2, Cs2TiBr2I4, and Cs2TiI6 via high-energy mechanochemical ball milling. The materials are characterized with structural, microscopic, and photophysical techniques to reveal indirect bandgaps with values of 1.88, 1.13, 1.04, and 1.02 eV but also a distinct lack of any significant photoluminescence (PL) and a high instability under ambient conditions. These findings enable us to clarify the previously controversial properties of Cs2TiBr6 and establish its role in the vast landscape of perovskite photovoltaics.
CRIS-Team WoS Importer:2022-11-25
Keywords: ball milling; cesium titanium halides; lead-free; stability

Melting and Crystallization Features of CsPbBr3 Perovskite - Kanak, Andrii; Kopach, Oleg; Kanak, Liliia; Levchuk, Ievgen; Isaiev, Mykola; Brabec, Christoph; Fochuk, Petro; Khalavka, Yuriy (Crystal Growth and Design, 2022)
The all-inorganic perovskite cesium lead bromide (CsPbBr3) has attracted considerable attention as a promising material for optoelectronics and high-energy radiation detectors. In order to obtain a bulk single crystal from a melt, it is crucial to understand the peculiarities of melting and crystallization processes. Here, the solid-liquid and liquid-solid phase transitions were studied by differential thermal analysis at different heating/cooling rates (0.1, 1, 3, 5, and 10 degrees C/min). A two-stage melting mechanism of CsPbBr3 perovskite was proposed. The critical maximal sample temperature (Tcritical) was determined for each heating rate. If the sample was heated to a temperature below Tcritical, the crystallization occurred at a temperature higher than the melting point. Contrarily, if the sample was heated to a temperature higher than this critical value, the melt crystallization occurred with supercooling. We believe that such crystallization features are closely related to the melt structure, which changes during the sample heating. The activation energies of melting and crystallization processes of CsPbBr3 were determined to be 1846 and 1940 kJ/mol, respectively. For the first time, this study demonstrates the impact of heating and cooling conditions on the melting and crystallization processes of the bulk CsPbBr3. It is significant for gaining a fundamental understanding of the crystal growth and fabrication of high-quality monocrystalline materials.
CRIS-Team WoS Importer:2022-07-08

Micropowder Ca2YMgScSi3O12:Ce Silicate Garnet as an Efficient Light Converter for White LEDs - Shakhno, Anna; Markovskyi, Anton; Zorenko, Tetiana; Witkiewicz-Lukaszek, Sandra; Vlasyuk, Yevheniya; Osvet, Andres; Elia, Jack; Brabec, Christoph; Batentschuk, Miroslaw; Zorenko, Yuriy (Materials, 2022)
This work is dedicated to the crystallization and luminescent properties of a prospective Ca2YMgScSi3O12:Ce (CYMSSG:Ce) micropowder (MP) phosphor converter (pc) for a white light-emitting LED (WLED). The set of MP samples was obtained by conventional solid-phase synthesis using different amounts of B2O3 flux in the 1-5 mole percentage range. The luminescent properties of the CYMSSG:Ce MPs were investigated at different Ce3+ concentrations in the 1-5 atomic percentage range. The formation of several Ce3+ multicenters in the CYMSSG:Ce MPs was detected in the emission and excitation spectra as well as the decay kinetics of the Ce3+ luminescence. The creation of the Ce3+ multicenters in CYMSSG:Ce garnet results from: (i) the substitution by the Ce3+ ions of the heterovalent Ca2+ and Y3+ cations in the dodecahedral position of the garnet host; (ii) the inhomogeneous local environment of the Ce3+ ions when the octahedral positions of the garnet are replaced by heterovalent Mg2+ and Sc3+ cations and the tetrahedral positions are replaced by Si4+ cations. The presence of Ce3+ multicenters significantly enhances the Ce3+ emission band in the red range in comparison with conventional YAG:Ce phosphor. Prototypes of the WLEDs were also created in this work by using CYMSSG:Ce MP films as phosphor converters. Furthermore, the dependence of the photoconversion properties on the layer thickness of the CYMSSG:Ce MP was studied as well. The changes in the MP layer thickness enable the tuning of the white light thons from cold white/daylight to neutral white. The obtained results are encouraging and can be useful for the development of a novel generation of pcs for WLEDs.
CRIS-Team WoS Importer:2022-06-24
Keywords: WLED; phosphor converters; Ca2+-Mg2+-Si4+-based garnets; micropowder; luminescence; Ce3+ multicenters

Micro-powder Ca3Sc2Si3O12:Ce silicate garnets as efficient light converters for WLEDs - Levchuk, Ievgen; Osvet, Andres; Brabec, Christoph; Batentschuk, Miroslaw; Shakhno, Anna; Zorenko, Tetiana; Zorenko, Yuriy (Optical Materials, 2020)
A novel synthesis method of Ca3Sc2Si3O12:Ce micropowder with very bright photo-luminescence (PL) has been developed. The conventional solid-state reaction has been modified for Ca3Sc2Si3O12:Ce microparticle crystallization. Pre-synthesis of metal and silicon oxide blends with subsequent high-temperature treatment in reducing (H2/N2) atmosphere enables obtaining Ca3Sc2Si3O12:Ce micropowder with a high PL quantum yield of about 60–70% at Ce3+ content in the 2.5–5 at.% range, which is highly attractive for LED technology. Additionally, the Ca3Sc2Si3O12:Ce phosphors with Ce concentration in the 0.5–2.5% range display higher thermal stability of photoluminescence in comparison with a commercial YAG:Ce phosphor.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Ca–Si based Garnets; Converters; Luminescence; Micropowder; WLED

Micro-Raman mapping on layers for crystalline silicon thin-film solar cells - Kunz, T.; Hessmann, M. T.; Meidel, B.; Brabec, Christoph (Journal of Crystal Growth, 2011)
Micro-Raman mappings have been used for characterization of our layers system developed for thin-film silicon solar cells. For the cubic SiC barrier layer a preferential orientation of the grains in 〈1 1 1〉 direction normal to the substrate was revealed. A high density of stacking faults resulted in the splitting of transversal optical (TO)-phonon modes, usually only observed in several non-cubic SiC polytypes. Within the silicon layers, which were obtained by zone melting recrystallization (ZMR) and subsequent epitaxial growth, a high residual stress of about 625 MPa was measured near the boundary towards the SiC layer. Outside of this boundary no residual stress could be detected, in spite of commonly found twin boundaries. Thus the main origin of residual stress in the silicon layers is due to the different expansion coefficients of the respective layers, while grain boundaries have no dominant effect. © 2010 Elsevier B.V. All rights reserved.
Keywords: A1. Micro-Raman; A1. Recrystallization; A3. Chemical vapor deposition processes; B2. Semiconducting silicon; B3. Solar cells

Microscopic Deformation Modes and Impact of Network Anisotropy on the Mechanical and Electrical Performance of Five-fold Twinned Silver Nanowire Electrodes - Schrenker, Nadine; Xie, Zhuocheng; Schweizer, Peter; Moninger, Marco; Werner, Felix; Karpstein, Nicolas; Mackovic, Mirza; Spyropoulos, Georgios; Göbelt, Manuela; Christiansen, Silke H.; Brabec, Christoph; Bitzek, Erik; et al. (ACS nano, 2020)
Silver nanowire (AgNW) networks show excellent optical, electrical, and mechanical properties, which make them ideal candidates for transparent electrodes in flexible and stretchable devices. Various coating strategies and testing setups have been developed to further improve their stretchability and to evaluate their performance. Still, a comprehensive microscopic understanding of the relationship between mechanical and electrical failure is missing. In this work, the fundamental deformation modes of five-fold twinned AgNWs in anisotropic networks are studied by large-scale SEM straining tests that are directly correlated with corresponding changes in the resistance. A pronounced effect of the network anisotropy on the electrical performance is observed, which manifests itself in a one order of magnitude lower increase in resistance for networks strained perpendicular to the preferred wire orientation. Using a scale-bridging microscopy approach spanning from NW networks to single NWs to atomic-scale defects, we were able to identify three fundamental deformation modes of NWs, which together can explain this behavior: (i) correlated tensile fracture of NWs, (ii) kink formation due to compression of NWs in transverse direction, and (iii) NW bending caused by the interaction of NWs in the strained network. A key observation is the extreme deformability of AgNWs in compression. Considering HRTEM and MD simulations, this behavior can be attributed to specific defect processes in the five-fold twinned NW structure leading to the formation of NW kinks with grain boundaries combined with V-shaped surface reconstructions, both counteracting NW fracture. The detailed insights from this microscopic study can further improve fabrication and design strategies for transparent NW network electrodes.<br
Keywords: silver nanowire; five-fold twinning; transparent electrode; buckling; kinks; transmission electron microscopy; molecular dynamics

Microstructure instabilities in solution-processed organic bulk-heterojunction solar cells - Li, Ning; Zhang, Chaohong; Brabec, Christoph (7th IEEE World Conference on Photovoltaic Energy Conversion, WCPEC 2018, 2018)
The performance of organic solar cells (OSCs) is determined by the delicate, meticulously optimized bulkheterojunction microstructure, which consists of finely mixed and relatively separated donor/acceptor regions. In this work we examine the reliability and stability of bulk-heterojunction (BHJ) microstructures of a highly-efficiency OSC based on PCE11 as the donor and PCBM as the acceptor. The so called burn-in degradation is identified as a spinodal de-mixing due to the low miscibility of donor and acceptor, which is turned out to be a major challenge for the development of stable and efficient OSCs. Even though the microstructure can be kinetically tuned for achieving high-performance, the inherently low miscibility of donor and acceptor leads to spontaneous phase separation in the solid state, even at room temperature and in the dark. The construction of the spinodal phase diagrams highlight molecular incompatibilities between the donor and acceptor as a dominant mechanism for burn-in degradation, which is to date the major short-time loss reducing the performance and stability of organic solar cells<br
Keywords: donor-acceptor demixing; bulk-heterojunction; miscibility; microstructure stability; organic photovoltaic cells

Mitigation of carrier trapping effects on carrier lifetime measurements with continuous-wave laser illumination for Pb-based metal halide perovskite materials - Lobo, Ntumba; Matt, Gebhard; Osvet, Andres; Shrestha, Shreetu; Kanak, Andrii; Fochuk, Petro; Brabec, Christoph; Kato, Masashi (Journal of Applied Physics, 2024)
We investigated the impact of carrier trapping on the carrier lifetime of metal halide perovskite materials, which are key to solar cell production. We examined NH3CH3PbI3 (MAPbI3), NH3CH3PbBr3 (MAPbBr3), and CsPbBr3 using continuous-wave (CW) laser illumination during microwave photoconductivity decay (μ-PCD) measurements. Traditional pulsed light excitation falls short of mirroring solar cell operating conditions, owing to carrier trapping. Implementing CW laser illumination provides a more accurate estimation of the carrier lifetimes under operational conditions. With an increased photon flux from the CW laser, the μ-PCD decay curves changed, indicating reduced recombination via traps. The experiments revealed extended carrier lifetimes under continuous light for the MAPbI3 polycrystal. This suggests that CW lasers can mitigate trapping effects on carrier lifetime measurements. For the other samples, carrier trapping had a negligible effect on the measured carrier lifetimes. We believe that these findings will aid in the design of perovskite-based devices.
CRIS-Team Scopus Importer:2024-05-03

Module-Power Prediction from PL Measurements using Deep Learning - Hoffmann, Mathis; Hepp, Johannes; Doll, Bernd; Buerhop-Lutz, Claudia; Peters, Ian Marius; Brabec, Christoph; Maier, Andreas; Christlein, Vincent (IEEE Photovoltaic Specialists Conference, 2021)
The individual causes for power loss of photovoltaic modules are investigated for quite some time. Recently, it has been shown that the power loss of a module is, for example, related to the fraction of inactive areas. While these areas can be easily identified from electroluminescense (EL) images, this is much harder for photoluminescence (PL) images. With this work, we close the gap between power regression from EL and PL images. We apply a deep convolutional neural network to predict the module power from PL images with a mean absolute error (MAE) of 4.4% or 11.7WP. Furthermore, we depict that regression maps computed from the embeddings of the trained network can be used to compute the localized power loss. Finally, we show that these regression maps can be used to identify inactive regions in PL images as wel
Keywords: photoluminescence; power; regression; deep learning; weakly supervised

Molecular Donor–Acceptor Dyads for Efficient Single-Material Organic Solar Cells - Lucas, Sebastian; Kammerer, Jochen; Pfannmoeller, Martin; Schroeder, Rasmus R.; He, Yakun; Li, Ning; Brabec, Christoph; Leydecker, Tim; Samori, Paolo; Marszalek, Tomasz; Pisula, Wojchiech; Mena-Osteritz, Elena; et al. (Solar RRL, 2020)
Single-material organic solar cells (SMOSCs) promise several advantages with respect to prospective applications in printed large-area solar foils. Only one photoactive material has to be processed and the impressive thermal and photochemical long-term stability of the devices is achieved. Herein, a novel structural design of oligomeric donor–acceptor (D–A) dyads 1–3 is established, in which an oligothiophene donor and fullerene acceptor are covalently linked by a flexible spacer of variable length. Favorable optoelectronic, charge transport, and self-organization properties of the D–A dyads are the basis for reaching power conversion efficiencies up to 4.26% in SMOSCs. The dependence of photovoltaic and charge transport parameters in these ambipolar semiconductors on the specific molecular structure is investigated before and after post-treatment by solvent vapor annealing. The inner nanomorphology of the photoactive films of the dyads is analyzed with transmission electron microscopy (TEM) and grazing-incidence wide-angle X-ray scattering (GIWAXS). Combined theoretical calculations result in a lamellar supramolecular order of the dyads with a D–A phase separation smaller than 2 nm. The molecular design and the precise distance between donor and acceptor moieties ensure the fundamental physical processes operative in organic solar cells and provide stabilization of D–A interfaces.
CRIS-Team Scopus Importer:2020-12-04
Keywords: ambipolar charge transport; donor–acceptor dyads; fullerenes; oligothiophenes; single-material organic solar cells

Molecular Doping of a Hole-Transporting Material for Efficient and Stable Perovskite Solar Cells - Luo, Junsheng; Zhu, Jinqing; Lin, Fangyan; Xia, Jianxing; Yang, Hua; JinyuYang, None; Wang, Ruilin; Yuan, Junyu; Wan, Zhongquan; Li, Ning; Brabec, Christoph; Jia, Chunyang (Chemistry of Materials, 2022)
The bis(trifluoromethane)sulfonimide lithium salt (Li-TFSI) is commonly used as an effective dopant to improve the conductivity and hole mobility of Spiro-OMeTAD in state-of-the-art n-i-p perovskite solar cells (PSCs). However, such doping severely induces device instability because of the ultrahygroscopic and migratory nature of Li+ ions. Here, we demonstrate a fluorinated Fe(F20TPP)Cl with a hydrophobic property and a high migration barrier as a potential alternative to replace the Li-TFSI in doped Spiro-OMeTAD. The optimized PSCs show a champion power conversion efficiency as high as 21.53% with a stabilized efficiency exceeding 21%. In addition, long-term stability of PSCs is significantly improved, and the device retains 84% of its initial efficiency after 900 h under continuous 100 mW cm-2 white light-emitting diode illumination and 89% of its initial efficiency after even 50 days in an ambient environment without encapsulation. We believe that this work addresses the fundamental question of intrinsic and extrinsic instability in Li-TFSI-based PSCs by combining simulation and experimental studies. The novel dopant Fe(F20TPP)Cl developed for Spiro-OMeTAD in this work can effectively meet the demands of future photovoltaic applications with promising efficiency and device stability.
CRIS-Team Scopus Importer:2022-04-01

Molecular Oligothiophene–Fullerene Dyad Reaching Over 5% Efficiency in Single-Material Organic Solar Cells - Aubele, Anna; He, Yakun; Kraus, Teresa; Li, Ning; Mena-Osteritz, Elena; Weitz, Paul; Heumüller, Thomas; Zhang, Kaicheng; Brabec, Christoph; Bäuerle, Peter (Advanced Materials, 2021)
A novel donor–acceptor dyad, 4, in which the conjugated oligothiophene donor is covalently connected to fullerene PC71BM by a flexible alkyl ester linker, is synthesized and applied as photoactive layer in solution-processed single-material organic solar cells (SMOSCs). Excellent photovoltaic performance, including a high short-circuit current density (JSC) of 13.56 mA cm−2, is achieved, leading to a power conversion efficiency of 5.34% in an inverted cell architecture, which is substantially increased compared to other molecular single materials. Furthermore, dyad 4-based SMOSCs display excellent stability maintaining 96% of the initial performance after 750 h (one month) of continuous illumination and operation under simulated AM 1.5G irradiation. These results will strengthen the rational molecular design to further develop SMOSCs for potential industrial application.
CRIS-Team Scopus Importer:2021-09-10
Keywords: charge transport; device performance; donor–acceptor dyads; long-term stability; single-material organic solar cells

Monitoring and assessment of PV generation based on a combination of smart metering and thermographic measurement - Stegner, C.; Dalsass, M.; Luchscheider, P.; Brabec, Christoph (Solar Energy, 2018)
Electrical solar power generation has a very decentral character which is posing significant challenges to monitoring and assessment due to the high number of considered systems. At the same time, with the advent of smart metering, huge amounts of data are becoming available and demand for automated approaches that are robust enough to deal with measuring gaps and noise. We propose and introduce a combined method consisting of a fitting algorithm, which works with the high temporal resolution of the smart meter data used (15 s), and an infrared thermography measurement. The results are region-specific irradiance characteristics, precise description of individual skylines for single systems derived from calculations, indication of abnormalities that should be compared with the abnormalities identified in thermal images and identification of reasons for underperformance.
Keywords: Aerial infrared thermography; Module defects; PV simulation; Smart metering

Morphological and electrical control of fullerene dimerization determines organic photovoltaic stability - Heumüller, Thomas; Mateker, William R.; Distler, Andreas; Fritze, Urs F.; Cheacharoen, Rongrong; Nguyen, William H.; Biele, Markus; Salvador, Michael Filipe; von Delius, Max; Egelhaaf, Hans-Joachim; Mcgehee, Michael D.; Brabec, Christoph (Energy and Environmental Science, 2016)
Fullerene dimerization has been linked to short circuit current (J) losses in organic solar cells comprised of certain polymer-fullerene systems. We investigate several polymer-fullerene systems, which present J loss to varying degrees, in order to determine under which conditions dimerization occurs. By reintroducing dimers into fresh devices, we confirm that the photo-induced dimers are indeed the origin of the J loss. We find that both film morphology and electrical bias affect the photodimerization process and thus the associated loss of J. In plain fullerene films, a higher degree of crystallinity can inhibit the dimerization reaction, as observed by high performance liquid chromatography (HPLC) measurements. In blend films, the amount of dimerization depends on the degree of mixing between polymer and fullerene. For highly mixed systems with very amorphous polymers, no dimerization is observed. In solar cells with pure polymer and fullerene domains, we tune the fullerene morphology from amorphous to crystalline by thermal annealing. Similar to neat fullerene films, we observe improved light stability for devices with crystalline fullerene domains. Changing the operating conditions of the investigated solar cells from V to J also significantly reduces the amount of dimerization-related J loss; HPLC analysis of the active layer shows that more dimers are formed if the cell is held at V instead of J. The effect of bias on dimerization, as well as a clear correlation between PL quenching and reduced dimerization upon addition of small amounts of an amorphous polymer into PC60BM films, suggests a reaction mechanism via excitons.
Keywords: Engineering controlled terms: Amorphous films; Crystalline materials; Dimerization; Dimers; Fullerenes; High performance liquid chromatography; Liquid chromatography; Organic polymers; Polymer films; Polymers Amorphous polymers; Crystalline fullerene; Degree of crystallinity; Dimerization reactions; Electrical control; Operating condition; Organic photovoltaics; Polymer-fullerene system Engineering main heading: Solar cells

Morphology analysis of near IR sensitized polymer/fullerene organic solar cells by implementing low bandgap heteroanalogue C-/Si-PCPDTBT - Ameri, Tayebeh; Khoram, Parisa; Heumüller, Thomas; Baran, Derya; Machui, Florian; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Halik, Marcus; Rathgeber, Silke; Scherf, Ullrich; Brabec, Christoph (Journal of Materials Chemistry A, 2014)
In the current work, we have investigated the morphological aspects of the ternary solar cells based on host matrices of P3HT:PCBM and P3HT:ICBA, using the low bandgap polymer analogues of C- and Si-bridged PCPDTBT as near IR sensitizers, which show noticeably different performance. A direct comparison of these well-functional and poorly functional ternary blend systems provides insights into the bottlenecks of device performance and enables us to set up an initial set of design rules for ternary organic solar cells. Our study reveals the importance of surface energy as a driving force controlling sensitizer location and morphology formation of ternary blends. The interfacial surface energy results indicate that Si-PCPDTBT locates at amorphous interfaces and P3HT crystallites, while C-PCPDTBT tends to accumulate at amorphous interfaces and semi-crystalline (or agglomerated) domains of the fullerene derivatives. GIWAXS and SCLC results support this prediction where adding high content of C-PCPDTBT influences mainly the semi-crystallinity (aggregation) of the fullerene and reduces the electron mobility, but Si-PCPDTBT impacts mainly the P3HT ordering and, in turn, deteriorates the hole mobility. These findings show that the disruption of the fullerene semi-crystalline domains is more detrimental to the device performance than the disruption of the polymer domains.

Morphology Optimization via Side Chain Engineering Enables All Polymer Solar Cells with Excellent Fill Factor and Stability - Liu, Xi; Zhang, Chaohong; Duan, Chunhui; Li, Mengmeng; Hu, Zhicheng; Wang, Jing; Liu, Feng; Li, Ning; Brabec, Christoph; Janssen, Rene A. J.; Bazan, Guillermo C.; Huang, Fei; et al. (Journal of the American Chemical Society, 2018)
All-polymer solar cells (all-PSCs) composed of conjugated polymers as both donor and acceptor components in bulk heterojunction photoactive layers have attracted increasing attention. However, it is a big challenge to achieve optimal morphology in polymer:polymer blends. In response, we report herein a new strategy to adjust the nanoscale organization for all-PSCs. Specifically, side chain engineering of the well-known naphthalene diimide (NDI)-based polymer N2200 is modulated by introducing a fraction of linear oligoethylene oxide (OE) side chains to replace branched alkyl chains on the NDI units and by synthesizing a series of NDI-based polymer acceptors NOEx, where x is the percentage of OE chain substituted NDI units relative to total NDI units. Compared to the reference polymer NOE0, OE-chain-containing polymer NOE10 offers a much higher power conversion efficiency (PCE) of 8.1% with a record high fill factor (FF) of 0.75 in all-PSCs. Moreover, the NOE10-based all-PSC exhibits excellent long-term and thermal stabilities with >97% of the initial PCE being maintained after 300 h of aging at 65 degrees C. This work demonstrates an effective morphology optimization strategy to achieve highly efficient and stable all-PSCs and shows the excellent potential of NOE10 as an alternative to commercially available acceptor polymers N2200.
Keywords: Cell engineering; Conjugated polymers; Heterojunctions; Morphology; Naphthalene; Nondestructive examination; Polymer blends; Solar cells

Morphology related photodegradation of low-band-gap polymer blends - Wang, Xiao; Egelhaaf, Hans-Joachim; Mack, Hans-Georg; Azimi, Seyed Hamed; Brabec, Christoph; Meixner, Alfred J.; Zhang, Dai (Advanced Energy Materials, 2014)
The morphology related photodegradation of low band-gap polymer blends is investigated using optical microscopy and scanning probe microscopy. Poly[2,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b′]dithiophene)-alt-4,7(2,1,3-benzothiadiazole)] (C-PCPDTBT):[6,6]-phenyl C61-butyric acid methyl ester (PCBM) blend films without and with ODT, as well as poly[(4,40-bis(2-ethylhexyl)dithieno[3,2-b:20,30-d]silole)-2,6-diylalt-(2,1,3-benzothiadiazole)-4,7-diyl] (Si-PCPDTBT):PCBM blend films exposed to a focused 632.8 nm laser under ambient condition with and without inert gas protection are studied. The photodegradation of the polymer starts in the vicinity of the PCBM molecules (first sphere degradation), which effectively blocks the electron transfer processes. Stern-Volmer type kinetics are observed in the C-PCPDTBT:PCBM blend with ODT, which indicates that only a small number of photo-oxidized monomer units act as quenchers of the C-PCPDTBT polymer luminescence. Furthermore, in addition to the permanent damage of the polymer molecules, as witnessed from their Raman intensity decrease, the polymer photoluminescence demonstrates partial reversible recovery when inert gas protection is resumed, indicating the involvement of temporary polymer/O-charge transfer complexes in the photodegradation process.
Keywords: Nanoscale morphology; Phase separation; Photodegradation; Polymer blend films

Nanocrystal V2O5 thin film as hole-extraction layer in normal architecture organic solar cells - Wang, Hao; Li, Ning; Güldal, Nusret Sena; Brabec, Christoph (Organic Electronics, 2012)
Nanocrystal VO dispersion processed thin films are introduced as efficient hole extraction interlayer in normal architecture P3HT:PCBM solar cells. Both thin and rather thick interlayers are studied and demonstrated to work properly in organic photovoltaic. Nanocrystal V OVO layers effectively block electrons and effectively extract holes at the ITO anode. Very constant and high V (above 0.56 V) are easily achieved. Comparable J and PCE are demonstrated for nanocrystal dispersion-processed devices when compared with amorphous sol-gel processed devices. The excellent functionality of nanocrystal VO interlayers in Si-PCPDTBT:PCBM devices further demonstrates the broad application potential of this material class for photovoltaic applications. © 2012 Elsevier B.V. All rights reserved.
Keywords: Electrode buffer layer; Nanocrystals; Organic solar cell; Vanadium oxide

Nanomorphology and charge generation in bulk heterojunctions based on low-bandgap dithiophene polymers with different bridging atoms - Morana, Mauro; Azimi, Hamed; Dennler, Gilles; Egelhaaf, Hans-Joachim; Scharber, Markus; Forberich, Karen; Hauch, Jens; Gaudiana, Russell; Waller, David; Zhu, Zenghuo; Hingerl, Kurt; Van Bavel, Svetlana S.; et al. (Advanced Functional Materials, 2010)
Carbon bridged (C-PCPDTBT) and silicon-bridged (Si-PCPDTBT) dithiophene donor-acceptor copolymers belong to a promising class of low bandgap materials. Their higher field-effect mobility, as high as 10cm V s in pristine films, and their more balanced charge transport in blends with fullerenes make silicon-bridged materials better candidates for use in photovoltaic devices. Striking morphological changes are observed in polymer:fullerene bulk heterojunctions upon the substitution of the bridging atom. XRD investigation indicates increased π-π stacking in Si-PCPDTBT compared to the carbon-bridged analogue. The fluorescence of this polymer and that of its counterpart C-PCPDTBT indicates that the higher photogeneration achieved in Si-PCPDTBT:fullerene films (with either [C60]PCBM or [C70]PCBM) can be correlated to the inactivation of a charge-transfer complex and to a favorable length of the donor-acceptor phase separation. TEM studies of Si-PCPDTBT:fullerene blended films suggest the formation of an interpenetrating network whose phase distribution is comparable to the one achieved in C-PCPDTBT:fullerene using 1,8-octanedithiol as an additive. In order to achieve a balanced hole and electron transport, Si-PCPDTBT requires a lower fullerene content (between 50 to 60 wt%) than C-PCPDTBT (more than 70 wt%). The Si-PCPDTBT:[C70]PCBM OBH) solar cells deliver power conversion efficiencies of over 5%. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA.

Nano-morphology characterization of organic bulk heterojunctions based on mono and bis-adduct fullerenes - Azimi, Hamed; Fournier, Darcy; Wirix, Maarten; Dobrocka, Edmund; Ameri, Tayebeh; Machui, Florian; Rodman, Sheila; Dennler, Gilles; Scharber, Markus C.; Hingerl, Kurt; Loos, Joachim; Brabec, Christoph; et al. (Organic Electronics, 2012)
We have studied organic bulk heterojunction photovoltaic devices based on a bridged-bithiophene donor-acceptor type low-band gap polymer blended with PCBM and bis-PCBM. The impact of the molecular arrangement is discussed in terms of the correlation between the solar-cell performance and the degree of crystallization. Differential scanning calorimetry (DSC) and grazing-incidence X-ray diffraction (GIXRD) prove that films with bis-PCBM typically result in more amorphous blends than comparable films with PCBM. Electron tomography (ET) is used to visualize the three dimensional morphology of photoactive layers, confirming the presence of nanofibers, formed in different scales through the thickness in the blended films with mono and bis-fullerenes. © 2012 Elsevier B.V. All rights reserved.
Keywords: Bis-PCBM; Crystallinity; Morphology; Organic photovoltaic; PCBM

Nanoscale Morphology of Doctor Bladed versus Spin-Coated Organic Photovoltaic Films - Pokuri, Balaji Sesha Sarath; Sit, Joseph; Wodo, Olga; Baran, Derya; Ameri, Tayebeh; Brabec, Christoph; Moule, Adam J.; Ganapathysubramanian, Baskar (Advanced Energy Materials, 2017)
Recent advances in efficiency of organic photovoltaics are driven by judicious selection of processing conditions that result in a “desired” morphology. An important theme of morphology research is quantifying the effect of processing conditions on morphology and relating it to device efficiency. State-of-the-art morphology quantification methods provide film-averaged or 2D-projected features that only indirectly correlate with performance, making causal reasoning nontrivial. Accessing the 3D distribution of material, however, provides a means of directly mapping processing to performance. In this paper, two recently developed techniques are integrated—reconstruction of 3D morphology and subsequent conversion into intuitive morphology descriptors —to comprehensively image and quantify morphology. These techniques are applied on films generated by doctor blading and spin coating, additionally investigating the effect of thermal annealing. It is found that morphology of all samples exhibits very high connectivity to electrodes. Not surprisingly, thermal annealing consistently increases the average domain size in the samples, aiding exciton generation. Furthermore, annealing also improves the balance of interfaces, enhancing exciton dissociation. A comparison of morphology descriptors impacting each stage of photophysics (exciton generation, dissociation, and charge transport) reveals that spin-annealed sample exhibits superior morphology-based performance indicators. This suggests substantial room for improvement of blade-based methods (process optimization) for morphology tuning to enhance performance of large area devices.
Keywords: blade spin as-cast anneal; internal morphology analysis; organic photovoltaic cells; reconstruction; tortuosity connectivity fraction

Nanoscale Morphology of PTB7 Based Organic Photovoltaics as a Function of Fullerene Size - Roehling, John D.; Baran, Derya; Sit, Joseph; Kassar, Thaer; Ameri, Tayebeh; Unruh, Tobias; Brabec, Christoph; Moule, Adam J. (Scientific Reports, 2016)
High efficiency polymer:fullerene photovoltaic device layers self-assemble with hierarchical features from ångströms to 100's of nanometers. The feature size, shape, composition, orientation, and order all contribute to device efficiency and are simultaneously difficult to study due to poor contrast between carbon based materials. This study seeks to increase device efficiency and simplify morphology measurements by replacing the typical fullerene acceptor with endohedral fullerene LuN@PC BEH. The metal atoms give excellent scattering contrast for electron beam and X-ray experiments. Additionally, LuN@PC BEH has a lower electron affinity than standard fullerenes, which can raise the open circuit voltage of photovoltaic devices. Electron microscopy techniques are used to produce a detailed account of morphology evolution in mixtures of Lu 3 N@PC 80 BEH with the record breaking donor polymer, PTB7 and coated using solvent mixtures. We demonstrate that common solvent additives like 1,8-diiodooctane or chloronapthalene do not improve the morphology of endohedral fullerene devices as expected. The poor device performance is attributed to the lack of mutual miscibility between this particular polymer:fullerene combination and to co-crystallization of Lu 3 N@PC 80 BEH with 1,8-diiodooctane. This negative result explains why solvent additives mixtures are not necessarily a morphology cure-all.

Nanostructured organosilicon luminophores in highly efficient luminescent down-shifting layers for thin film photovoltaics - Uekert, Taylor; Solodovnyk, Anastasiia; Ponomarenko, Sergei; Osvet, Andres; Levchuk, Ievgen; Gast, Jessica; Batentschuk, Miroslaw; Forberich, Karen; Stern, Edda; Egelhaaf, Hans-Joachim; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2016)
We use a new type of solution processed luminescent molecules - nanostructured organosilicon luminophores (NOLs) - in printed luminescent down-shifting layers for photovoltaic light harvesting. We show that NOLs exhibit a high luminescent efficiency of 82-90% when added into two chemically different polymer matrices that are commonly used for photovoltaic encapsulation: polyvinyl butyral and ethylene-vinyl acetate. The coated layers are optimized to maximize both UV absorbance and visible light emission and transmittance. Attaching the luminescent layers onto a CIGS solar cell significantly improves the external quantum efficiency in the UV region: from 1% to 55% at 360 nm. As a result, the short circuit current density and power conversion efficiency increase by up to 3.2-4.3%. After experimental verification of our optical simulation model, we employ it to determine the ideal molecular structure of NOLs for luminescent down-shifting applied to CIGS.
Keywords: Absorbance; CIGS; Luminescence quantum yield; Luminescent down-shifting; Organic emitter; Organosilicon nanostructure; Photovoltaics

Nanowire Interconnects for Printed Large-Area Semitransparent Organic Photovoltaic Modules - Guo, Fei; Kubis, Peter; Przybilla, Thomas; Spiecker, Erdmann; Hollmann, Andre; Langner, Stefan; Forberich, Karen; Brabec, Christoph (Advanced Energy Materials, 2015)
Semitransparent organic photovoltaic (OPV) cells promise applications in various transparent architectures where their opaque counterparts cannot contribute. Realizing practical applications of this technology requires the manufacturing of large-area modules without significant performance loss compared to the lab-scale devices. In this work, efficient semitransparent OPV modules based on ultrafast laser patterning on both glass and flexible substrates are reported. Solution-processed metallic silver nanowires (AgNWs) are used as transparent top electrodes. The efficient low-ohmic contact of the interconnects between the top AgNWs and the bottom electrode in combination with high-precision laser beam positioning system allow to fabricate semitransparent modules with high electrical fill factor of approximate to 63% and a remarkable geometric fill factor exceeding 95%, respectively. These results represent an important progress toward upscaling of high-performance OPV modules with reduced production costs.

Near-infrared sensitization of polymer/fullerene solar cells: Controlling the morphology and transport in ternary blends - Ameri, Tayebeh; Foerster, Michael D.; Scherf, Ullrich; Brabec, Christoph (Springer New York LLC, 2017)
The concept of near-infrared (NIR) sensitization can be used as an alternative strategy to extend the spectral sensitivity of wide-bandgap polymers in polymer/fullerene solar cells. In ternary systems consisting of a conjugated polymer donor, a fullerene acceptor, and a sensitizer, the fullerene needs to act as an electron acceptor as well as an electron-transport matrix, the polymeric donor should provide a sufficiently high hole mobility, and the sensitizers should sensitize the bulk heterojunction solar cell in the red/NIR region. So far we have used various optoelectrical and structural techniques to investigate the possible mechanisms of the charge transfer and charge transport among the three components and microstructure of the ternary blends. In this review-like chapter, we present our recent achievements on developing the concept of NIR sensitization for polymer/fullerene solar cells by mainly addressing the important aspect of the relationship between morphology and transport.
Keywords: Cascade alignment; Differential scanning calorimetry; Fullerene multiadducts; GIWAXS; Hansen solubility parameters; Morphology agent; Near-IR sensitization; OPV; Phase diagram; SCLC; Surface energy; Ternary solar cell; Time-resolved pump-probe spectroscopy; Transport

Near IR sensitization of organic bulk heterojunction solar cells: Towards optimization of the spectral response of organic solar cells - Koppe, Markus; Egelhaaf, Hans-Joachim; Dennler, Gilles; Scharber, Markus C.; Brabec, Christoph; Schilinsky, Pavel; Hoth, Claudia N. (Advanced Functional Materials, 2010)
The spectroscopic response of a poly(3-hexylthiophene)/[6,6]-phenyl-C -butyric acid methyl ester (P3HT/PCBM)-based bulk heterojunction solar cell is extended into the near infrared region (NIR) of the spectrum by adding the low bandgap polymer polyp,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta[2,1 -b, 3, 4-b]-dithiophene)-alt-4, 7-(2, l, 3-benzothiadiazole)] [PCPDTBTJ to the blend. The dominant mechanism behind the enhanced photosensitivity of the ternary blend is found to be a two-step process: first, an ultrafast and efficient photoinduced charge transfer generates positive charges on P3HT and PCPDTBT and a negative charge on PCBM. In a second step, the positive charge on PCPDTBT is transferred to P3HT. Thus, P3HT serves two purposes. On the one hand it is involved in the generation of charge carriers by the photoinduced electron transfer to PCBM, and, on the other hand, it forms the charge transport matrix for the positive carriers transferred from PCPDTBT. Other mechanisms, such as energy transfer or photoinduced charge transfer directly between the two polymers, are found to be absent or negligible. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA.

Near IR sensitization of polymer/fullerene solar cells - Ameri, Tayebeh; Min, Jie; Li, Ning; Machui, Florian; Brabec, Christoph; Forster, Michael; Schottler, Kristina; Dolfen, Daniel; Allard, Sybille; Scherf, Ullrich (Organic Photovoltaics XIII, 2012)
In this work we discuss an elegant, alternative strategy to extend the spectral sensitivity of wide bandgap polymers in the near IR region. We discuss the microstructure of different functional ternary systems and compare them from different perspectives. © 2012 SPIE.
Keywords: IR sensitization; Organic solar cells; Small bandgap polymers; Ternary blends

NEW PV SYSTEM CONCEPT –INDUCTIVE POWER TRANSFER FOR PV MODULES - Carigiet, Fabian; Knecht, Raphael; Baumann, Thomas; Brabec, Christoph; Baumgartner, Franz (35th European Photovoltaic Solar Energy Conference and Exhibition (35th EUPVSEC), 2018)
The proposed new PV system concept is based on several AC modules that are connected in series using inductive power transfer. These modules include a cell matrix thatis connected to a module integrated DC/AC inverter. The high frequency AC current flows through the primary side planar coil generating a magnetic flux. Outside of the PV module, there is a clamp including ferromagnetic material for the magnetic circuit that caries the magnetic flux to the secondary winding. The magnetic flux induces an AC current in the secondary winding,which is formed by the common cable.An AC/AC converter is placed at the end of the PV module strings to generate the 50Hz and to connect the PV power plant to the electricity grid. This new PV system concept is a fundamentally new approach of the electricity transmission in the field of PVsystem technology. It is not restricted to the replacement or optimisation of an individual system component, but it requires the continuing development of the PV module construction and the contactless connection technology to the common cable. The proposed inductive power transfer per each PV module opens up a complete new field for the PV system technolo
Keywords: PV system; inductive power transfer; AC modules; module integration

New silicate based thermographic phosphors Ca3Sc2Si3O12:Dy, Ca3Sc2Si3O12:Dy,Ce and their photoluminescence properties - Chepyga, Liudmyla M.; Osvet, Andres; Levchuk, Ievgen; Ali, Amjad; Zorenko, Yuriy; Gorbenko, Vitalii; Zorenko, Tetiana; Fedorov, Alexander; Brabec, Christoph; Batentschuk, Miroslaw (Journal of Luminescence, 2018)
We report on the investigation of Dy3+-doped calcium scandium silicate garnet (Ca3Sc2Si3O12 abbreviated CSSG) as a high-temperature thermographic phosphor. The Ca3Sc2Si3O12:Dy and Ca3Sc2Si3O12:Dy,Ce phosphors were synthesized: (1) as single crystalline films by liquid phase epitaxy on Gd3Ga3Al2O12 (GAGG) substrates using PbO-B2O3 flux; (2) via fatty acid-assisted co-precipitation method with subsequent annealing. The resulting silicate based phosphors CSSG:Dy, CSSG:Dy,Ce were characterized by XRD, SEM, photoluminescence excitation and emission spectroscopy. Temperature dependence of the emission spectra was studied at temperatures between 293 K and 1500 K. The emission in two spectral regions corresponding to the transitions in Dy3+ ions at 458 nm and 484 nm shows different temperature sensitivity allowing for thermometry based on the intensity ratio method. The intensity ratio and the sensitivity of single crystalline films are higher than those of co-precipitated materials at temperatures up to 1200 K. It is concluded that the CSSG:Dy is a promising phosphor for high temperature measurements, with its temperature sensitivity comparable to YAG:
Keywords: Cerium; Phosphor thermometry; Silicate garnet; Dysprosium; Luminescence

Nondestructive characterization of polymeric components of silicon solar modules by near-infrared absorption spectroscopy (NIRA) - Stroyuk, Oleksandr; Buerhop-Lutz, Claudia; Vetter, Andreas; Hauch, Jens; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2020)
Degradation of the encapsulation of solar modules is a crucial problem and, accordingly, tools for assessing and understanding the according degradation is an important research topic. Here, we suggest near-infrared absorption spectroscopy (NIRA) as a tool that has a strong potential to determine non-invasively the composition of encapsulant and backsheet in typical commercial solar modules. Correct polymer identification by NIRA was supported by Raman spectral microscopy of the backsheet air sides and cross sections, with a hundred solar modules of different manufacturers analyzed by both spectroscopic methods. Furthermore, a specific NIRA measurement regime of the ethylene vinyl acetate encapsulant is presented, which potentially allows to probe the composition of the encapsulant non-destructively under lab conditions but also on silicon solar modules in the field installed outdoors. The present report shows NIRA to be a powerful method for non-destructive analysis of backsheets and encapsulants of photovoltaic silicon modules.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Backsheet; Encapsulant; Near infrared spectroscopy; Photovoltaics; Raman spectroscopy; Silicon solar modules

Non-destructive imaging of defects in Ag-sinter die attach layers – A comparative study including X-ray, Scanning Acoustic Microscopy and Thermography - Dreher, P.; Schmidt, R.; Vetter, Andreas; Hepp, Johannes; Karl, André; Brabec, Christoph (Microelectronics Reliability, 2018)
In typical power electronic modules several semiconductor dies such as MOSFET or IGBT are soldered to a DBC substrate. During module production the quality of the solder layers can be monitored by the use of X-ray inspection and the void rate can be determined. Recently, the more robust Ag-sinter technology is deployed for attaching the power dies to the substrate, especially for high reliability or high temperature requirements. Besides voiding also adhesion problems can occur during sintering due to multiple reasons (e.g. contamination). In contrast to volume defects, pure adhesion problems cannot be detected by means of X-rays. Accordingly, other methods have to be applied for process monitoring. The present investigation compares the advantages and disadvantages of different non-destructive imaging techniques towards the detection of defects in sinter layers. Besides X-ray, Scanning Acoustic Microscopy (SAM) and Lock-in Thermography methods (DLIT+ILIT) were studied and evaluated in terms of suitability for detecting different defect types, resolution (minimum defect sizes), inspection time and possible integration into the assembly process.<br
Keywords: Lock-in thermography; Scanning acoustic microscopy; Silver-sintering technology; Non-destructive imaging; Power electronics; X-ray

Non-fullerene acceptors end-capped with an extended conjugation group for efficient polymer solar cells - Li, Renlong; Liu, Gongchu; Fan, Baobing; Du, Xiaoyan; Tang, Xiaofeng; Li, Ning; Ying, Lei; Brabec, Christoph; Huang, Fei; Cao, Yong (Organic Electronics, 2018)
We report two novel small-molecule non-fullerene acceptors, IF-TN and IDT-TN, with indenofluorene (IF) and indacenodithiophene (IDT) as their respective central electron-rich cores and naphthyl-fused indanone (N) as the electron-withdrawing end-groups. By pairing these non-fullerene acceptors with a widely used polymer PBDB-T, the fabricated polymer solar cells based on PBDB-T:IDT-TN obtain a power conversion efficiency up to 5.89%, associated with a relatively high open-circuit voltage of 0.97 V and a remarkably low non-radiative open-circuit voltage loss of 0.23 V. These findings provide an effective approach for the rational molecular design of small-molecule acceptors with low non-radiative open-circuit voltage los
Keywords: Open-circuit voltage loss; Small molecules; Electron acceptors; Non-fullerene polymer solar cells

Non-Stationary Outdoor EL-Measurements with a Fast and Highly Sensitive InGaAs Camera - Adams, Jens; Doll, Bernd; Buerhop-Lutz, Claudia; Pickel, Tobias; Teubner, Janine; Camus, Christian; Brabec, Christoph (32nd European Photovoltaic Solar Energy Conference and Exhibition, 2016)
A fast and non-destructive failure inspection is essential to ensure the reliability of PV plants. This might only be achieved by using highly sensitive imaging techniques which can detect local electrical losses in solar modules. Here, EL imaging used for outdoor PV inspection gained large interest, since it can be used to characterize local cell damages, series resistances, and shunts in solar modules. However, currently available EL-cameras base on Si-CCD-detectors. Besides high spatial resolutions they exhibit long image integration times (IIT) of about 1 s for obtaining evaluable EL-images. To overcome this limitation we present, for the first time, an InGaAs camera which enables a complete EL-characterization of field-installed PV-modules with IITs between 1 ms and 20 ms. The short IITs result in frame rates of about 100 Hz which even offer the opportunity of recording dynamic EL-movies and daylight Electroluminescence Lock-In (ELLI) measurements. To test the outdoor applicability we compared ELmovies of the InGaAs camera with EL-images of a Si-CCD camera and show that all relevant power reducing cell failures (e. g. cracks) can be detected and characterized.
Keywords: Performance and Reliability measurement; Electroluminescence of PV Modules; Energy rating; Degradation; Ageing; Lifetime Characterization of PV Cells and Modules

Non-Uniformity Measurements of a Steady State Solar Simulator Using the Hishikawa-Hashimoto Method and Subsequent Improvement - Doll, Bernd; Hoyer, Ulrich; Hofer, Markus; Pickel, Tobias; Buerhop-Lutz, Claudia; Camus, Christian; Hauch, Jens; Brabec, Christoph (32nd European Photovoltaic Solar Energy Conference and Exhibition, 2016)
A steady state solar simulator has been set up at the ZAE Bayern. The system is meant to be used for the characterization of photovoltaic (PV) of various technologies. In particular, it can be used for pre-conditioning of thin film modules in order to enable reliable power and I-V measurements. Furthermore, it allows for determining the temperature coefficient of PV modules of various technologies. The latter application will also be discussed in this work. Here, the optimization of the steady state solar simulator based on a method originally introduced by Hishikawa et al. for pulsed solar simulators is described and the results of this optimization are presented.
Keywords: Characterization; Experimental Methods; Light-Soaking; Qualification and Testing

Novel fatty-acid assisted co-precipitation method for the synthesis of SrAl2O4: Eu2+, Sm3+ storage phosphor nanoparticles - Romling, Lukas; Levchuk, Ievgen; Steimle, Max; Osvet, Andres; Batentschuk, Miroslaw; Winnacker, Albrecht; Brabec, Christoph (Advanced Materials - TechConnect Briefs 2017, 2017)
In this work SrAl2O4 doped with Eu2+ and Sm3+ were successfully synthesized using a novel fatty acid assisted co-precipitation method. The main focus was laid on (1) finding a suitable synthesis procedure to reproducibly obtain nanosized SrAl2OM4 doped with Europium and Samarium of high purity (2) optimizing the Eu2+ concentration for nano scaled Strontium Aluminate and finally (3) optimizing the co-doping amount of Sm3+ to obtain a high intensity photostimulated luminesence (PSL). As a last step the dependence of the PSL signal to the writein and read-out wavelengths of the stimulating light was determined.
Keywords: Co-precipitation; Phosphor; Photostimulated luminescence; SrAl2O4

Novel two-dimensional phosphor thermography by decay-time method using a low frame-rate CMOS camera - Ali, Amjad; Chepyga, Liudmyla; Khanzada, Laraib Sarfraz; Osvet, Andres; Brabec, Christoph; Batentschuk, Miroslaw (Optics and Lasers in Engineering, 2020)

Numerical Simulation of light propagation in silver nanowire films using time-harmonic inverse iterative method - Yan, Shuai; Krantz, Johannes; Forberich, Karen; Pflaum, Christoph; Brabec, Christoph (Journal of Applied Physics, 2013)
The interaction between light and silver nanowires (Ag NWs) in a thin film is simulated by solving Maxwells equations numerically. Time-harmonic inverse iterative method is implemented to overcome the problem of negative permittivity of silver, which makes the classical finite-difference time-domain iteration unstable. The method is validated by showing the correspondence between the plasmonic resonance of an Ag NW from a two dimensional simulation and the analytical solution. In agreement with previous experimental studies, the simulation results show that the transmissivity of the Ag NW films is higher than expected from the geometric aperture. The cause of this phenomenon is studied using TE/TM modes analysis for Ag NW films with different surface coverage of parallel-aligned Ag NWs. Furthermore, 3D simulation of Ag NW films with randomly arranged Ag NWs is performed by parallel computation on high performance computers. A binder layer is taken into account for a preliminary comparison between the simulation and experimental results. The agreements and disagreements between the simulated and measured spectra are discussed. © 2013 AIP Publishing LLC.
UnivIS-Import:2015-03-09:Pub.2013.tech.IMMD.c3sim.numeri
Keywords: Finite difference time domains; High performance computers; Negative permittivity; Parallel Computation; Plasmonic resonances; Silver nanowires; Surface coverages; Two-dimensional simulations Engineering controlled terms: Computer simulation; Electric resistance measurement; Finite difference time domain method; Inverse problems; Iterative methods Engineering main heading: Silver

Numerical study of plasmonic absorption enhancement in semiconductor absorbers by metallic nanoparticles - Hornich, Julian; Pflaum, Christoph; Brabec, Christoph; Forberich, Karen (Journal of Applied Physics, 2016)
We are studying the influence of spherical silver nanoparticles (AgNP) in absorbing media by numerically solving the Maxwell's equations. Our simulations show that the near-field absorption enhancement introduced by a single AgNP in the surrounding medium is increasing with the growing particle diameter. However, we observe that the relative absorption per particle volume is on a similar level for different particle sizes; hence, different numbers of particles with the same total volume yield the same near-field absorption enhancement. We also investigate the effect of non-absorbing shells around the AgNP with the conclusion that even very thin shells suppress the beneficial effects of the particles noticeably. Additionally, we include AgNP in an organic solar cell at different vertical positions with different particle spacings and observe the beneficial effects for small AgNP and the scattering dependent performance for larger particles.

Observation of reversible light degradation in organic photovoltaics induced by long-persistent radicals - Zhang, Difei; Liu, Chao; Zhang, Kaicheng; Jia, Yanhua; Zhong, Wenkai; Qiu, Weidong; Li, Yuanfeng; Heumüller, Thomas; Forberich, Karen; Le Corre, Vincent Marc; Lüer, Larry; Li, Ning; et al. (Energy and Environmental Science, 2023)
With the rapid development of organic photovoltaics, device stability has become a crucial obstacle hindering their transition from laboratory-scale to industrial applications. However, it still remains unclear how light differs from heat in driving trap formation and device degradation. On the basis of the PTzBI-dF:Y6-BO system, it is observed that the post-thermal annealing on these high-performance organic solar cells can partially recover the light-induced burn-in losses. The recovery process is found to be correlated with a reversible charge extraction ability, reversible trap density of state, local charge carrier density and charge accumulation. Herein, we propose an innovative mechanism for light degradation in organic photovoltaic devices, which is triggered by the presence of light-induced long-persistent radicals. The findings offer deep insights into light degradation of organic photovoltaics and a new perspective for improving device stability under long-term operation.
CRIS-Team Scopus Importer:2023-12-01

Oligomer-Assisted Photoactive Layers Enable >18 % Efficiency of Organic Solar Cells - Cheng, Yujun; Huang, Bin; Huang, Xuexiang; Zhang, Lifu; Kim, Seoyoung; Xie, Qian; Liu, Chao; Heumüller, Thomas; Liu, Zuoji; Zhang, Youhui; Wu, Feiyan; Yang, Changduk; et al. (Angewandte Chemie International Edition, 2022)
Although ternary organic solar cells (OSCs) have unique advantages in improving device performance, the morphology assembly in the ternary-phase would be more uncertain or complex than that in the binary-phase. Here, we propose a new concept of oligomer-assisted photoactive layers for high-performance OSCs. The formed alloy-like phase of the oligomer : host polymer blend enabled the oligomer-assisted OSCs to fuse the advantages of both binary and ternary devices, exhibiting substantially enhanced performance and stability compared to the control devices. With the addition of oligomers, outstanding efficiencies of 17.33 % for a PM6 : Y6 device, 18.32 % for a PM6 : BTP-eC9 device, and 17.13 % for a PM6/Y6 pseudo-bilayer device were achieved, all of which are one of the highest values in their corresponding fields. The improved performance originated from the downshift energy levels, enhanced light absorption, optimized blend morphology, favorable charge dynamics, and reduced non-radiative energy loss.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Organic Solar Cells; Performance; Stability

Optical model for simulation and optimization of luminescent down-shifting layers filled with phosphor particles for photovoltaics - Lipovsek, Benjamin; Solodovnyk, Anastasiia; Forberich, Karen; Stern, Edda; Krc, Janez; Brabec, Christoph; Topic, Marko (Optics Express, 2015)
We developed an optical model for simulation and optimization of luminescent down-shifting (LDS) layers for photovoltaics. These layers consist of micron-sized phosphor particles embedded in a polymer binder. The model is based on ray tracing and employs an effective approach to scattering and photoluminescence modelling. Experimental verification of the model shows that the model accurately takes all the structural parameters and material properties of the LDS layers into account, including the layer thickness, phosphor particle volume concentration, and phosphor particle size distribution. Finally, using the verified model, complete organic solar cells on glass substrate covered with the LDS layers are simulated. Simulations reveal that an optimized LDS layer can result in more than 6% larger short-circuit current of the solar cell.
CRIS-Team Scopus Importer:2023-03-07

Optical Model for Simulation and Optimization of Luminescent down-shifting Layers in Photovoltaics - Lipovsek, Benjamin; Solodovnyk, Anastasiia; Forberich, Karen; Stern, Edda; Brabec, Christoph; Krc, Janez; Topic, Marko (E-MRS Spring Meeting 2015 Symposium C - Advanced inorganic materials and structures for photovoltaics, 2015, 2015)
We present an optical model that was developed for the purpose of simulation and optimization of luminescent down-shifting layers based on phosphor particles. The model combines three-dimensional ray tracing with a novel effective scattering approach based on the Mie scattering theory. Verification of the model with experimental results shows that the model accurately takes various layer parameters into account, such as the layer thickness, the phosphor volume concentration, and the phosphor particle size distribution. Finally, using the verified model, we investigate the concept of luminescent down-shifting in organic solar cells and discuss the optimal layer parameters. Preliminary simulation results show that in the case of the studied solar cell, an improvement in the short-circuit current density of more than 6% can be obtained.
Keywords: Fluorescent and luminescent materials; Optical modelling and simulation; Solar energy; Wavelength conversion devices

Optimization of Solution-Processed Luminescent Down-Shifting Layers for Photovoltaics by Customizing Organic Dye Based Thick Films - Solodovnyk, Anastasiia; Kick, Christopher; Osvet, Andres; Egelhaaf, Hans Joachim; Stern, Edda; Batentschuk, Miroslaw; Forberich, Karen; Brabec, Christoph (Energy Technology, 2016)
We theoretically and experimentally determined the optimized film properties of luminescent down-shifting (LDS) layers for thin film solar cells. Based on the predictions from an adapted optical model, we coated thick (300–500 mm) and efficient luminescent down-shifting layers from environmentally friendly solvents and industrially scalable inks. LDS layers consisted of polyvinyl butyral (PVB) as binder and organic luminescent dyes as UV-converters. The luminescence quantum yields of the dyes were studied in solution (benzyl alcohol) and for solid thick films. Our data shows that the studied dyes retain luminescent efficiencies of approximately 90% in the solid state when processed from solution. We further apply the produced layers onto copper indium gallium diselenide (CIGS) solar cells to verify the theoretical predictions for enhancing the external quantum efficiency (EQE) in the UV region. For the best converters a remarkable enhancement of the EQE from 9% to 52% was recorded at 380 nm. These findings underline that printed LDS layers indeed have the potential to enhance the efficiency and the light harvesting capabilities of industrially relevant photovoltaic modules.

Optimization of synthesis and compositional parameters of magnesium germanate and fluoro-germanate thermographic phosphors - Ali, Amjad; Khanzada, Laraib Sarfraz; Hashemi, Amir; Polzer, Carsten; Osvet, Andres; Brabec, Christoph; Batentschuk, Miroslaw (Journal of Alloys and Compounds, 2018)
Various documented formulations of magnesium germanate and flouro-germanate were synthesized by conventional solid state method at various temperatures to find out optimal synthesis conditions for maximum luminescence intensity. Relative efficiency of luminescence intensity and thermal stability of luminescence of these formulations is then discussed with respect to the commercially available phosphor. Mg28Ge7.5O38F10:Mn4+ was found to be the most efficient when synthesized at 1150 °C in air and has a comparable efficiency with respect to commercial sample. Photoluminescence intensity with increasing temperature was measured till 500 °C; the samples showed persistent emission till 300 °C. Relatively, samples with MgF2 give stronger emission at high temperatures if added in proper ratio.
Keywords: Mn4+ Red luminescence Magnesium fluoro-germanate Magnesium germanat Temperature dependent photoluminescence

Optimizing Perovskite Thin-Film Parameter Spaces with Machine Learning-Guided Robotic Platform for High-Performance Perovskite Solar Cells - Zhang, Jiyun; Liu, Bowen; Liu, Ziyi; Wu, Jianchang; Arnold, Simon; Shi, Hongyang; Osterrieder, Tobias; Hauch, Jens; Wu, Zhenni; Luo, Junsheng; Wagner, Jerrit; Berger, Christian; et al. (Advanced Energy Materials, 2023)
Simultaneously optimizing the processing parameters of functional thin films remains a challenge. The design and utilization of a fully automated platform called SPINBOT is presented for the engineering of solution-processed functional thin films. The SPINBOT is capable of performing experiments with high sampling variability through the unsupervised processing of hundreds of substrates with exceptional experimental control. Through the iterative optimization process enabled by the Bayesian optimization (BO) algorithm, the SPINBOT explores an intricate parameter space, continuously improving the quality and reproducibility of the produced thin films. This machine learning (ML)-guided reliable SPINBOT platform enables the acceleration of the optimization process of perovskite solar cells via a simple photoluminescence characterization of films. As a result, this study arrives at an optimal film that, when processed into a solar cell in an ambient atmosphere, immediately yields a champion power conversion efficiency (PCE) of 21.6% with satisfactory performance reproducibility. The unsealed devices retain 90% of their initial efficiency after 1100 h of continuous operation at 60–65 °C under metal-halide lamps. It is anticipated that the integration of robotic platforms with the intelligent algorithm will facilitate the widespread adoption of effective autonomous experimentation to address the evolving needs and constraints within the materials science research community.
CRIS-Team Scopus Importer:2023-11-10
Keywords: closed-loop optimization; efficient and stable devices; machine learning; manufacturing optimization; perovskite thin films; PL characterization; robotic platform

Opto-electronics of PbS quantum dot and narrow bandgap polymer blends - Kahmann, Simon; Mura, Andrea; Protesescu, Loredana; Kovalenko, Maksym V.; Brabec, Christoph; Loi, Maria A. (Journal of Materials Chemistry C, 2015)
Here we report on the interaction between the narrow bandgap polymer [2,6-(4,4-bis(2-ethylhexyl)-4H-cyclopenta-[2,1-b;3,4-b]dithiophene)-alt-4,7-(2,1,3-benzothiadiazole)] (PCPDTBT) and lead sulphide (PbS) colloidal quantum dots (CQDs) upon photoexcitation. We show that the presence of both materials in a blend leads to a significant reduction of photoluminescence (PL) lifetime of the polymer. This observation is attributed, supported by transient absorption (TA) data, to an efficient electron transfer towards the QDs for excitons generated on the polymer. Furthermore, the ligand capping the QD surface exhibits a great impact on the dynamics of the PL, with the long-chain oleic acid (OA) largely suppressing any kind of interaction. By means of external quantum efficiency (EQE) measurements we find evidence that both components give rise to a contribution to the photocurrent, making this an interesting blend for future applications in hybrid organic-inorganic solar cells.
Keywords: Engineering controlled terms: Copolymers; Energy gap; Polymer blends; Semiconductor quantum dots; Semiconductor quantum wells 2; 1; 3-Benzothiadiazole; Colloidal quantum dots; Electron transfer; External quantum efficiency; Future applications; Hybrid organic-inorganic; Narrow bandgap polymers; Transient absorption Engineering main heading: Quantum efficiency

Organic and perovskite solar modules innovated by adhesive top electrode and depth-resolved laser patterning - Spyropoulos, George D.; Quiroz, Cesar Omar Ramirez; Salvador, Michael Filipe; Hou, Yi; Gasparini, Nicola; Schweizer, Peter; Adams, Jens; Kubis, Peter; Li, Ning; Spiecker, Erdmann; Ameri, Tayebeh; Egelhaaf, Hans-Joachim; et al. (Energy and Environmental Science, 2016)
We demonstrate an innovative solution-processing fabrication route for organic and perovskite solar modules via depth-selective laser patterning of an adhesive top electrode. This yields unprecedented power conversion efficiencies of up to 5.3% and 9.8%, respectively. We employ a PEDOT:PSS-Ag nanowire composite electrode and depth-resolved post-patterning through beforehand laminated devices using ultra-fast laser scribing. This process affords low-loss interconnects of consecutive solar cells while overcoming typical alignment constraints. Our strategy informs a highly simplified and universal approach for solar module fabrication that could be extended to other thin-film photovoltaic technologies.
Keywords: Indexed keywords Engineering controlled terms: Conducting polymers; Electrodes; Laminated composites; Organic lasers; Perovskite; Solar cells; Solar power generation Depth-resolved; Fabrication routes; Innovative solutions; Laser patterning; Photovoltaic technology; Power conversion efficiencies; Solar module; Universal approach Engineering main heading: Solar cell arrays GEOBASE Subject Index: efficiency measurement; electrode; film; innovation; laser method; perovskite; photovoltaic system

Organic photovoltaic modules with new world record efficiencies - Distler, Andreas; Brabec, Christoph; Egelhaaf, Hans-Joachim (Progress in Photovoltaics, 2020)
During the last years, the development of new active materials has led to constant improvement in the power conversion efficiency (PCE) of solution-processed organic photovoltaics (OPV) to nowadays record values above 17% on small lab cells. In this work, we show the developments and results of a successful upscaling of such highly efficient OPV systems to the module level on large areas, which yielded two new certified world record efficiencies, namely, 12.6% on a module area of 26 cm2 and 11.7% on a module area of 204 cm2. The decisive developments leading to this achievement include the optimization of the module layout as well as the high-resolution short-pulse (nanosecond) laser structuring processes involved in the manufacturing of such modules. By minimizing the inactive areas within the total module area that are used for interconnecting the individual solar cells of the module in series, geometric fill factors of over 95% have been achieved. A production yield of 100% working modules during the manufacturing of these modules and an extremely narrow distribution of the final PCE values underline the excellent process control and reproducibility of the results. The new developments and their implementation into the production process of the record OPV modules are described in detail, along with the challenges that arose during this development. Finally, dark lock-in thermography (DLIT), electroluminescence (EL), and photoluminescence (PL) measurements of the record module are presented.
CRIS-Team Scopus Importer:2020-09-25
Keywords: certified power conversion efficiency (PCE); laser patterning; organic photovoltaics (OPV); solar modules; world record

Organic photovoltaics for low light applications - Steim, Roland; Ameri, Tayebeh; Schilinsky, Pavel; Waldauf, Christoph; Dennler, Gilles; Scharber, Markus; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2011)
Here we report on organic photovoltaics (OPV) suitable for low light applications. In this paper, we illustrate the impact of R and R for indoor and outdoor applications. In addition, we propose a simple physics approach to predict the behavior of organic solar cells under various illumination intensities through electrical modeling. The combination of simulation and modeling allows to define a set of design rules for OPVs under low light illumination. The performance of various organic solar cells under low light intensity is compared with our predictions and excellent correlation is found. OPV shows high performance under low light conditions. © 2011 Elsevier B.V. All rights reserved.
Keywords: Indoor; Low light; OPV; Organic photovoltaics; Shunt resistance; Simulation

Organic Photovoltaics: Materials, Device Physics, and Manufacturing Technologies: Second Edition - Brabec, Christoph; Scherf, Ullrich; Dyakonov, Vladimir V. (Wiley Blackwell, 2014)
The versatility of organic photovoltaics is already well known and this completely revised, updated, and enlarged edition of a classic provides an up-to-date overview of this hot topic. The proven structure of the successful first edition, divided into the three key aspects of successful device design: materials, device physics, and manufacturing technologies, has been retained. Important aspects such as printing technologies, substrates, and electrode systems are covered. The result is a balanced, comprehensive text on the fundamentals as well as the latest results in the area that will set R&D trends for years to come. With its combination of both academic and commercial technological views, this is an optimal source of information for scientists, engineers, and graduate students already actively working in this field, and looking for comprehensive summaries on specific topics.

Organic solar cells using oligomer acceptors for improved stability and efficiency - Liang, Youcai; Zhang, Difei; Wu, Zerun; Jia, Tao; Lüer, Larry; Tang, Haoran; Hong, Ling; Zhang, Jiabin; Zhang, Kai; Brabec, Christoph; Li, Ning; Huang, Fei (Nature Energy, 2022)
The power conversion efficiencies of organic solar cells (OSCs) have reached over 19%. However, the combination of high efficiency and long-term stability is still a major conundrum of commercialization. Here a Y6-analogue and a 2,2′-bithiophene unit are utilized to construct a series of oligomer acceptors to investigate the effect of molecular size and packing properties on photovoltaic performance. By altering the molecular chain length, we modify the thermal properties, crystallization behaviours and molecular packing and achieve an optimal microstructure and a more stable morphology in blend films. A combination of efficiencies over 15% and an extrapolated T80 lifetime over 25,000 h, which equates to an average lifetime exceeding 16 years in Guangzhou, is achieved for binary OSCs based on an oligomer acceptor. This work emphasizes the importance of oligomeric strategy in tuning molecular packing behaviours and blend morphology, leading to development of novel non-fullerene acceptors for stable and efficient OSCs.
CRIS-Team Scopus Importer:2022-11-25

Organic Tandem Solar Cells - Dennler, Gilles; Sariciftci, Niyazi Serdar; Brabec, Christoph; Annamalai, V.E. (Reference Module in Materials Science and Materials Engineering 2016, 2016)
The article traces the developments in the area of organic tandem solar cells. By piling several solar devices one over the other, a tandem cell is obtained. The light which is not absorbed in the lower cell can be absorbed in the upper cell. The thermalization losses are lowered due to the usage of materials having different bandgaps. By finding the appropriate dopants for both the p and the n region the efficiency of the stacked device can be boosted to 3.8%, which is 80% larger than that of a single device. It is postulated that efficiencies as high as 15% can be achieve
Keywords: Band gap Dopant Organic solar cell Polymeric solar cell Power conversion efficiency Single junction solar cell Solar device Solar tandem cell

Organic tandem solar cells - Li, Ning; Ameri, Tayebeh; Brabec, Christoph (CRC Press, 2015)

Organic ternary solar cells: A review - Ameri, Tayebeh; Khoram, Parisa; Min, Jie; Brabec, Christoph (Advanced Materials, 2013)
Recently, researchers have paid a great deal of attention to the research and development of organic solar cells, leading to a breakthrough of over 10% power conversion efficiency. Though impressive, further development is required to ensure a bright industrial future for organic photovoltaics. Relatively narrow spectral overlap of organic polymer absorption bands within the solar spectrum is one of the major limitations of organic solar cells. Among different strategies that are in progress to tackle this restriction, the novel concept of ternary organic solar cells is a promising candidate to extend the absorption spectra of large bandgap polymers to the near IR region and to enhance light harvesting in single bulk-heterojunction solar cells. In this contribution, we review the recent developments in organic ternary solar cell research based on various types of sensitizers. In addition, the aspects of miscibility, morphology complexity, charge transfer dynamics as well as carrier transport in ternary organic composites are addressed. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: dyes; IR sensitization; low bandgap polymers; organic solar cells; small molecules; ternary blends

Organometallic perovskites for optoelectronic applications (Conference Presentation) - Levchuk, Ievgen; Högl, Florian; Brandl, Marco; Osvet, Andres; Herre, Patrick; Hock, Rainer; Schweizer, Peter; Spiecker, Erdmann; Batentschuk, Miroslaw; Brabec, Christoph; Peukert, Wolfgang (SPIE Nanoscience + Engineering, 2016, 2016)
Organometallic halide perovskites CH3NH3BX3 (B= Pb, Sn, Ge; X = I, Br, Cl) have become one of the most promising semiconductors for solar cell applications, reaching power conversion efficiencies beyond 20%. Improving our ability to harness the full potential of organometal halide perovskites requires the development of more reliable synthesis routines of well defined, reproducible and defect free reference systems allowing to study the fundamental photo-physical processes. In this study we present size and band gap engineering for organo-lead perovskites crystallites with various shapes and sizes ranging from the 5 nm regime all the way to 1 cm. Colloidal nano-crystals, micro-crystlline particles as well as single crystals are demonstrated with excellent purity and control in shape and size are demonstrated. The structural, optical and photo-physical properties of these reference materials are investigated and analyzed as function of their size and shape.
Keywords: particle; crystal; organometal; optoelectronics

Outdoor photoluminescence of large area photovoltaic modules - Doll, Bernd; Hepp, Johannes; Hoffmann, Mathis; Talkenberg, Florian; Schüler, Renè; Baier, Manuel; Buerhop-Lutz, Claudia; Tegtmeyer, Dirk; Peters, Ian Marius; Hauch, Jens; Brabec, Christoph (Proceedings Volume 11809, Organic, Hybrid, and Perovskite Photovoltaics XXII, 2021)
Cost-effective, fast, and non-destructive, on-site photovoltaic (PV) characterization methods are of interest to PV operators to determine countermeasures against defects causing power loss or against safety problems. Combining the advantages of both methods electroluminescence (EL) and thermography is photoluminescence (PL). With our PL setup, we achieved high resolution luminescence images of large area PV modules without any physical and electrical contact. Defects are recognizable with a high rate compared to indoor EL images at controlled conditions. We analyzed inactive areas, cracks, potential induced degradation, snail trails, EVA degradation, and interconnection failures and compared the PL images with different characterization methods.
Keywords: Luminescene; Solar cells; Electroluminescence; Photovoltaics; Image resolution; Light sources; Safety; Sensors; Silicon; Thermography

Overcoming efficiency and stability limits in water-processing nanoparticular organic photovoltaics by minimizing microstructure defects - Xie, Chen; Heumüller, Thomas; Gruber, Wolfgang; Tang, Xiaofeng; Classen, Andrej; Schuldes, Isabel; Bidwell, Matthew; Späth, Andreas; Fink, Rainer; Unruh, Tobias; Mcculloch, Iain; Li, Ning; et al. (Nature Communications, 2018)
There is a strong market driven need for processing organic photovoltaics from eco-friendly solvents. Water-dispersed organic semiconducting nanoparticles (NPs) satisfy these premises convincingly. However, the necessity of surfactants, which are inevitable for stabilizing NPs, is a major obstacle towards realizing competitive power conversion efficiencies for water-processed devices. Here, we report on a concept for minimizing the adverse impact of surfactants on solar cell performance. A poloxamer facilitates the purification of organic semiconducting NPs through stripping excess surfactants from aqueous dispersion. The use of surfactant-stripped NPs based on poly(3-hexylthiophene) / non-fullerene acceptor leads to a device efficiency and stability comparable to the one from devices processed by halogenated solvents. A record efficiency of 7.5% is achieved for NP devices based on a low-band gap polymer system. This elegant approach opens an avenue that future organic photovoltaics processing may be indeed based on non-toxic water-based nanoparticle inks.
Keywords: microstructure-recombination correlation; organic photovoltaics; polymer-fullerene nanoparticles; water processed

Overcoming Electrode-Induced Losses in Organic Solar Cells by Tailoring a Quasi-Ohmic Contact to Fullerenes via Solution-Processed Alkali Hydroxide Layers - Zhang, Hong; Shallcross, R. Clayton; Li, Ning; Stubhan, Tobias; Hou, Yi; Chen, Wei; Ameri, Tayebeh; Turbiez, Mathieu; Armstrong, Neal R.; Brabec, Christoph (Advanced Energy Materials, 2016)
It is shown that the performance of inverted organic solar cells can be significantly improved by facilitating the formation of a quasi-ohmic contact via solution-processed alkali hydroxide (AOH) interlayers on top of n-type metal oxide (aluminum zinc oxide, AZO, and zinc oxide, ZnO) layers. AOHs significantly reduce the work function of metal oxides, and are further proven to effectively passivate defect states in these metal oxides. The interfacial energetics of these electron collecting contacts with a prototypical electron acceptor (C) are investigated to reveal the presence of a large interface dipole and a new interface state between the Fermi energy and the C highest occupied molecular orbital for AOH-modified AZO contacts. These novel interfacial gap states are a result of ground-state electron transfer from the metal hydroxide-functionalized AZO contact to the adsorbed molecules, which are hypothesized to be electronically hybridized with the contact. These interface states tail all the way to the Fermi energy, providing for a highly n-doped (metal-like) interfacial molecular layer. Furthermore, the strong "light-soaking" effect is no longer observed in devices with a AOH interface. Solution-processed alkali hydroxides significantly reduce the work function of metal oxides, such as zinc oxide or aluminum zinc oxide (AZO), and are further proven to effectively passivate defect states in these metal oxides. The interface states with alkali hydroxide-modified AZO contacts tail all the way to the Fermi energy, providing for a highly n-doped (metal-like) interfacial molecular layer.
Keywords: alkali hydroxide; interfacial layers; organic solar cells; solution processing

Overcoming interface losses in organic solar cells by applying low temperature, solution processed aluminum-doped zinc oxide electron extraction layers - Stubhan, Tobias; Litzov, Ivan; Li, Ning; Salinas Batallas, Michael; Steidl, Matthias; Sauer, Gerhard; Forberich, Karen; Matt, Gebhard; Halik, Marcus; Brabec, Christoph (Journal of Materials Chemistry A, 2013)
Intrinsic zinc oxide (ZnO) is widely used as an electron extraction layer (EEL) for inverted polymer solar cells. Despite the excellent device performance, a major drawback for large area production is its low conductivity. Using microscopic simulations, we derived a technically reasonable threshold value of 10−3 S cm−1 for the conductivity required to overcome transport limitations. For conductivity values typical for ZnO we observed the interface layer thickness restriction at only a few tens of nanometers, either as a fill factor drop due to serial resistance, eventually accompanied by a second diode behavior, or by the need for light soaking. Higher conductive aluminum-doped zinc oxide (AZO), which was introduced earlier, meets the desired conductivity threshold, however, at the cost of high temperature processing. High annealing temperatures (>150 °C) significantly improve the electrical properties of ZnO, but prohibit processing on plastic substrates or organic active layers. Here we report on AZO layers from a sol–gel precursor, which has been already reported to give sufficiently high conductivities at lower processing temperatures (<150 °C). We investigate the influence of different precursor compositions on the electrical properties of the thin films and their performance in inverted poly(3-hexylthiophene):[6,6]-phenyl-C61-butyric acid methyl ester (P3HT:PCBM) solar cells. Low temperature AZO layers with thicknesses up to 680 nm maintained comparable performance to devices with thin AZO layers.
Keywords: Aluminum-doped zinc oxide; Annealing temperatures; High-temperature processing; Inverted polymer solar cells; Microscopic simulation; Organic active layers; Poly (3-hexylthiophene); Processing temperature Engineering controlled terms: Aluminum; Electric properties; Extraction; Processing; Sol-gels; Solar cells; Temperature Engineering main heading: Zinc oxide

Overcoming Interfacial Losses in Solution-Processed Organic Multi-Junction Solar Cells - Du, Xiaoyan; Lytken, Ole; Killian, Manuela; Cao, Jiamin; Stubhan, Tobias; Turbiez, Mathieu; Schmuki, Patrik; Steinrück, Hans-Peter; Ding, Liming; Fink, Rainer; Li, Ning; Brabec, Christoph (Advanced Energy Materials, 2016)
Organic solar cells are promising in terms of full-solution-processing which enables low-cost and large-scale fabrication. While single-junction solar cells have seen a boost in power conversion efficiency (PCE), multi-junction solar cells are promising to further enhance the PCE. In all-solution-processed multi-junction solar cells, interfacial losses are often encountered between hole-transporting layer (HTL) and the active layers and therefore greatly limit the application of newly developed high-performance donor and acceptor materials in multi-junction solar cells. Here, the authors report on a systematic study of interface losses in both single-junction and multi-junction solar cells based on representative polymer donors and HTLs using electron spectroscopy and time-of-flight secondary ion mass spectrometry. It is found that a facile mixed HTL containing poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) and MoO nanoparticles successfully overcomes the interfacial losses in both single- and multi-junction solar cells based on various active layers by reducing interface protonation, promoting better energy-level alignment, and forming a dense and smooth layer. Solution-processed single-junction solar cells are demonstrated to reach the same performance as with evaporated MoO (over 7%). Multi-junction solar cells with polymers containing nitrogen atoms as the first layer and the mixed PEDOT:PSS and MoO nanoparticles as hole extraction layer reach fill factor (FF) of over 60%, and PCE of over 8%, while the identical stack with pristine PEDOT:PSS or MoO nanoparticles show FF smaller than 50% and PCE less than 5%.
Keywords: Interfacial losses; Organic multi-junction solar cells; Organic photovoltaics; Recombination layer; Solution-processing

Overcoming Microstructural Limitations in Water Processed Organic Solar Cells by Engineering Customized Nanoparticulate Inks - Xie, Chen; Classen, Andrej; Späth, Andreas; Tang, Xiaofeng; Min, Jie; Meyer, Markus; Zhang, Chaohong; Li, Ning; Osvet, Andres; Fink, Rainer; Brabec, Christoph (Advanced Energy Materials, 2018)
The application of conjugated polymer and fullerene water-based nanoparticles (NP) as ecofriendly inks for organic photovoltaics (OPVs) is reported. A low bandgap polymer diketopyrrolopyrrole–quinquethiophene (PDPP5T-2) and the methanofullerene PC71BM are processed into three types of nanoparticles: pristine fullerene NPs, pristine polymer NPs, and mixed polymer:fullerene NPs, allowing the formation of bulk heterojunction (BHJ) composites with different domain sizes. Mild thermal annealing is required to melt the nanospheres and enable the formation of interconnected pathways within mixed phases. This BHJ is accompanied by a shrinkage of film, whereas the more compact layers show enhanced mobility. Consistently reduced recombination and better performance are found for mixed NP, containing both, the polymer and the fullerene within a single NP. The optimized solar cell processed by ultrasmall NPs delivers a power conversion efficiency of about 3.4%. This is among the highest values reported for aqueous processed OPVs but still lacks performance compared to those being processed from halogenated solvents. Incomplete crystallization is identified as the main root for reduced efficiency. It is nevertheless believed that postprocessing does not cut attraction from printing aqueous organic NP inks as a trendsetting strategy for the reliable and ecofriendly production of organic solar cells.
Keywords: Microstructure-recombination correlation; Organic photovoltaics; Polymer-fullerene nanoparticles; Water processed

Overcoming Moisture-Induced Degradation in Organic Solar Cells - Wachsmuth, Josua; Distler, Andreas; Deribew, Dargie; Salvador, Michael Filipe; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Engineering Materials, 2023)
Unencapsulated organic solar cells are prone to severe performance losses in the presence of moisture. Accelerated damp heat (85 °C/85% RH) studies are presented and it is shown that the hygroscopic hole-transporting PEDOT:PSS layer is the origin of device failure in the case of prototypical inverted solar cells. Complementary measurements unveil that under these conditions a decreased PEDOT:PSS work function along with areas of reduced electrical contact between active layer and hole-transport layer are the main factors for device degradation rather than a chemical reaction of water with the active layer. Replacements for PEDOT:PSS are explored and it is found that tungsten oxide (WO3) or phosphomolybdic acid (PMA)—materials that can be processed from benign solvents at room temperature—yields comparable performance as PEDOT:PSS and enhances the resilience of solar cells under damp heat. The stability trend follows the order PEDOT:PSS << WO3 < PMA, with PEDOT:PSS-based devices failing after few minutes, while PMA-based devices remain nearly pristine over several hours. PMA is thus proposed as a robust, solution-processable hole extraction layer that can act as a one to one replacement of PEDOT:PSS to achieve organic solar cells with significantly improved longevity.
CRIS-Team Scopus Importer:2023-06-02
Keywords: degradation and stability; humidity; organic photovoltaics; phosphomolybdic acid; solution processed

Overcoming photovoltage deficitvianatural amino acid passivation for efficient perovskite solar cells and modules - Hu, Jinlong; Xu, Xin; Chen, Yijun; Wu, Shaohang; Wang, Zhen; Wang, Yousheng; Jiang, Xiaofang; Cai, Boyuan; Shi, Tingting; Brabec, Christoph; Mai, Yaohua; Guo, Fei (Journal of Materials Chemistry A, 2021)
Electronic defects at grain boundaries and surfaces of perovskite crystals impair the photovoltaic performance and stability of solar devices. In this work, we report the compensation of photovoltage losses in blade-coated methylammonium lead triiodide (MAPbI3) devicesviapassivation with natural amino acid (NAA) molecules. We found that the optoelectronic properties of NAA-passivated perovskite films and the corresponding device performances are closely correlated with the molecular interaction strength. A side-by-side comparative study of four typical NAAs reveals that arginine (Arg) functionalized with a guanidine end group exhibits optimum passivation effects owing to the strongest coordinative bonding with the uncoordinated Pb2+, which markedly suppresses the detrimental antisite PbIdeep level defects. As a result, nonradiative charge recombination is significantly reduced, resulting in a substantially increased open-circuit voltage (VOC) of 1.17 V and a high efficiency of 20.49%. A solar module with an active area of 10.08 cm2is also fabricated, yielding an efficiency of 15.65% with negligibleVOClosses. In parallel, the Arg-passivated solar devices exhibit enhanced operational stability due to the formation of a hydrophilic Arg protective layer which encapsulates the perovskite crystals.
CRIS-Team Scopus Importer:2021-03-19

Overcoming Temperature-Induced Degradation of Silver Nanowire Electrodes by an Ag@SnOx Core-Shell Approach - Kalancha, Violetta; These, Albert; Vogl, Lilian; Levchuk, Ievgen; Zhou, Xin; Barr, Maissa; Bruns, Mark; Bachmann, Julien; Virtanen, Sannakaisa; Spiecker, Erdmann; Osvet, Andres; Brabec, Christoph; et al. (Advanced Electronic Materials, 2022)
Transparent electrodes consisting of silver nanowires (Ag NWs) are a solution-processed alternative to commonly used indium tin oxide electrodes. Here, Ag NW electrodes protected by a tin oxide (SnOx) are explored and unprecedented thermal stability is found. While unprotected Ag NW electrodes fail at 250 degrees C, the SnOx Ag NW electrodes remain stable for 40 h at 250 degrees C and withstand high temperatures up to 500 degrees C for short times. First, an optimized method of synthesis that provides uniform Ag NWs with high reproducibility is used. Afterward, a SnOx shell is formed in a wet chemical reaction. Fabrication of highly conductive electrodes requires thermal annealing at 300 degrees C for 5 min under ambient atmosphere. Electrodes with a sheet resistance as low as 20 ohm sq(-1) and visible transmittance of 84% are demonstrated. It is shown that a approximate to 2 nm thick SnOx shell effectively protects the Ag NWs in a temperature range between 200 and 500 degrees C, whereas unprotected Ag NWs suddenly fail at temperatures beyond 200 degrees C. It is strongly anticipated that these improvements in the stability of Ag NWs open a large field of further investigations and applications.
CRIS-Team WoS Importer:2022-02-11

Overcoming the Interface Losses in Planar Heterojunction Perovskite-Based Solar Cells - Hou, Yi; Chen, Wei; Baran, Derya; Stubhan, Tobias; Luechinger, Norman A.; Hartmeier, Benjamin; Richter, Moses; Min, Jie; Chen, Shi; Ramírez Quiroz, César Omar; Li, Ning; Zhang, Hong; et al. (Advanced Materials, 2016)
An experiment was conducted to demonstrate that low-temperature processed NiO-based nanocrystal ink (LT-NiO) has the potential to form an almost loss-free hole selective interface for flat heterojunction perovskite-based solar cells. First, The patterned ITO substrates were ultrasonic cleaned with acetone and isopropanol for 10 min each. On cleaned ITO substrate, a dense and smooth layer of LT-NiO was deposited by spin coating and followed by annealing at 70?230°C for 10 min in air to remove organic components. The as-prepared perovskite precursor solution was filtered using 0.45 μm PTFE syringe filter and coated onto the ITO/LT-NiO substrate at a speed of 4000 r.p.m. for 35 s. J-V characteristics of all the devices were measured using a source measurement unit from BoTest. FTPS:FTPS-EQE measurements were carried out using a Vertex 70 from Brucker optics, equipped with QTH lamp, quartz beam splitter and external detector option. A major improvement in open circuit voltage is found by replacing PEDOT:PSS with LT-NiO. A detailed analysis reveals that LT-NiO significantly reduces non-radiative recombination at the PEDOT:PSS/perovskite interface and further enhances the radiative LED efficiency towards unity which brings open circuit voltage closer to the radiative limit.
Keywords: low temperature processing; nickel oxide; non-radiative voltage loss; perovskite solar cells

Overcoming the Thermal Instability of Efficient Polymer Solar Cells by Employing Novel Fullerene-Based Acceptors - Zhang, Chaohong; Mumyatov, Alexander; Langner, Stefan; Perea Ospina, Jose Dario; Kassar, Thaer; Min, Jie; Ke, Lili; Chen, Haiwei; Gerasimov, Kirill L.; Anokhin, Denis V.; Ivanov, Dimitri A.; Ameri, Tayebeh; et al. (Advanced Energy Materials, 2017)
Solution-processed organic solar cells with promising photovoltaic performance and extraordinary high thermal stability are achieved by employing novel fullerene-based acceptors in combination with two state-of-the-art polymer donors. The findings demonstrated in this work underline the necessity and importance of novel acceptor design rules for highly efficient organic solar cells with excellent device stability.
Keywords: Miscibility; Morphological analysis; Novel fullerene-based acceptors; Organic photovoltaics; Thermal stability

P3HT: Non-fullerene acceptor based large area, semi-transparent PV modules with power conversion efficiencies of 5%, processed by industrially scalable methods - Strohm, S.; Machui, F.; Langner, Stefan; Kubis, P.; Gasparini, Nicola; Salvador, Michael Filipe; Mcculloch, I.; Egelhaaf, H. -J.; Brabec, Christoph (Energy and Environmental Science, 2018)

Panchromatic ternary/quaternary polymer/fullerene BHJ solar cells based on novel silicon naphthalocyanine and silicon phthalocyanine dye sensitizers - Ke, Lili; Gasparini, Nicola; Min, Jie; Zhang, Hong; Adam, Matthias; Rechberger, Stefanie; Forberich, Karen; Zhang, Chaohong; Spiecker, Erdmann; Tykwinski, Rik; Brabec, Christoph; Ameri, Tayebeh (Journal of Materials Chemistry A, 2017)
More efficient light harvesting throughout the whole solar spectrum by introducing third and fourth components offers a new pathway towards the development of high efficiency organic solar cells based on polymer/fullerene blends. Recently, dye molecules have been utilized as promising light harvesting photosensitizers in the near-IR region. Herein, we report the design, synthesis and application of a novel silicon naphthalocyanine (SiNC-1) as an efficient photosensitizer in single dye ternary devices as well as in multi-colored co-sensitized quaternary devices, incorporating a silicon phthalocyanine (SiPC-0 or SiPC-1) as the fourth component to complement the spectral absorption of the SiNC-1. The dominant complex charge transfer/transport mechanism behind the enhanced photosensitivity of the ternary blend has been investigated by means of electrical, optical, and advanced characterization techniques. External quantum efficiency (EQE) measurements on multi-colored dye sensitized devices covering the UV-vis as well as near-IR regions from 350 up to 900 nm outline apparent signal characteristics of each single dye, corroborating the effective contribution of both SiPC and SiNC dyes to enhancing the short-circuit current density (J). Our results further illustrate the potential of the multi-colored dye sensitization concept as a powerful approach to mitigate the non-ideal optical absorption normally encountered in organic-based optoelectronic devices.
Keywords: Engineering controlled terms: Charge transfer; Dye-sensitized solar cells; Efficiency; Electromagnetic wave absorption; Light absorption; Nitrogen compounds; Optoelectronic devices; Organic solar cells; Photosensitizers; Polymer blends; Polymer solar cells; Silicon; Solar cells Characterization techniques; Dye sensitization; External quantum efficiency; Light-harvesting; Naphthalocyanines; Phthalocyanine dyes; Signal characteristic; Spectral absorptions Engineering main heading: Silicon solar cells

Parasitic emission in inkjet-printed InP-based quantum dot light-emitting diodes - Hübner, Tobias; Richter, Alexander F.; Feldmann, Jochen; Brabec, Christoph; von Malm, Norwin (Organic Electronics, 2021)
Indium phosphide-based colloidal quantum dot (QD) light-emitting diodes represent a promising technology for various lighting applications. To promote this innovative technology closer to an industrialized production environment, the fabrication methods should be adapted. Hence it is necessary to replace the common spin-coating process under an inert atmosphere, by a more cost-efficient inkjet-printing process at ambient conditions. However, in our case, this transfer results in devices with limited performance and parasitic emission channels besides the desired QD emission. In this paper, we identify the physical origin of these parasitic emission channels for three different device layouts depending on the QD material as well as the number of inkjet-printed layers. For the first type of devices, a recombination process on the dopant of the electron transporting layer (ETL) as well as an exciplex formation at the interface between QDs and ETL was identified. For the next device layout, the introduction of a hole-conducting matrix embedding the QDs leads to a shift of the parasitic emission with contributions from the matrix material. Finally, the integration of a hole injection layer leads to a reduction of the undesired emission processes. For all three kinds of devices, the spacial separation of the dopant in the ETL from the QDs is a critical factor, since it directly influences the parasitic emission channels.
CRIS-Team Scopus Importer:2021-04-23
Keywords: Charge carrier balance; Colloidal quantum dot LED; Indium phosphide; Inkjet-printing; Parasitic emission

Passive cooling of large-area organic light-emitting diodes - Schwamb, Philipp; Reusch, Thilo C. G.; Brabec, Christoph (Organic Electronics, 2013)
The authors investigated passive cooling of large-area organic light-emitting diodes (OLEDs) with special focus on convective cooling. Electro-optical and thermal behaviour of large-area OLED devices are therefore modelled using finite element method (FEM) and computational fluid dynamics (CFD) simulations. Resulting temperature and luminance distributions are compared with measurement data at different driving conditions and test setups. The investigation yields that including laterally resolved convection coefficients from CFD simulations greatly improves model accuracy compared to simpler convection estimations. These findings are important for OLED and their heat spreader design especially for features like flexible, transparent, high-power and or large-area due to their specific limitations for heat spreading and or their high heat spreading requirements. © 2013 Elsevier B.V. All rights reserved.
Keywords: Computational fluid dynamics; Heat distribution; Natural convection; Organic light-emitting diode; Passive cooling; Thermal modeling

Patterning of OPV modules by ultra-fast laser - Kubis, Peter; Lucera, Luca; Guo, Fei; Spyropoulos, Georgios; Voigt, Monika; Brabec, Christoph (Laser Processing and Fabrication for Solar, Displays, and Optoelectronic Devices III, 2014)
A novel production process combining slot-die coating, transparent exible IMI (ITO-Metal-ITO) electrodes and ultra-fast laser ablation can be used for the realization of P3HT:PCBM based thin film exible OPV modules. The fast and precise laser ablation allows an overall efficiency over 3 % and a device geometric fill factor (GFF) over 95 %. Three functional layers can be ablated using the same wavelength only with varying the laser uence and overlap. Different OPV device architectures with multilayers utilizing various materials are challenging for ablation but can be structured by using a systematical approach.
Keywords: Exible OPV module; Laser ablation; Semitransparent OPV module; Slot-die coating; Ultra-fast laser

Patterning of organic photovoltaic modules by ultrafast laser - Kubis, Peter; Li, Ning; Stubhan, Tobias; Machui, Florian; Matt, Gebhard; Voigt, Monika; Brabec, Christoph (Progress in Photovoltaics: Research and Applications, 2015)
In this paper, we demonstrate that laser patterning of organic solar cells by ultrafast laser systems (pulse length <350 fs) is an attractive process to produce photovoltaic modules with outstanding high geometric fill factors. Moreover, in terms of precision, registration, and debris generation and in terms of keeping the damage to the underneath layers at a minimum, ultrafast laser patterning with a pulse length of few hundreds of femtoseconds turns out to yield superior results. Ablation of all three different solar cell layers (electrodes (P1 and P3) and interfaces and semiconductor (P2)) is achieved with a single wavelength simply by a precise adjustment of the laser fluence and the patterning overlap. Camera positioning allows a precise registration between the various processing steps and a reduction of the width of the overall interconnection regime to the hundreds of micrometers dimension, resulting in high geometrical fill factors of over 90% for monolithically interconnected organic solar cell modules.
Keywords: Femtosecond pulses; Laser patterning; Organic solar cells; PV module

PEDOT:PSS-Free Polymer Non-Fullerene Polymer Solar Cells with Efficiency up to 18.60% Employing a Binary-Solvent-Chlorinated ITO Anode - Sun, Rui; Wang, Tao; Wu, Yao; Zhang, Meng; Ma, Yunlong; Xiao, Zuo; Lu, Guanghao; Ding, Liming; Zheng, Qingdong; Brabec, Christoph; Li, Yongfang; Min, Jie (Advanced Functional Materials, 2021)
Despite the tremendous development of different high-performing photovoltaic systems in non-fullerene polymer solar cells (PSCs), improving their performance is still highly demanding. Herein, an effective and compatible strategy, i.e., binary-solvent-chlorinated indium tin oxide (ITO) anode, is presented to improve the device performance of the state-of-the-art photoactive systems. Although both ODCB (1,2-dichlorobenzene) solvent- and ODCB:H2O2 (hydrogen peroxide) co-solvent-chlorinated ITO (ITO-Cl-ODCB and ITO-Cl-ODCB:H2O2) show similar optical transmittance, electrical conductivities, and work function values, ITO-Cl-ODCB:H2O2 exhibits higher Cl surface coverage and more suitable surface free energy close to the poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS)-buffered ITO anode (ITO/PEDOT:PSS). As a direct consequence, the performance of ITO-Cl-ODCB-based PBDB-T-2F:BTP-eC9:PC71BM PSCs is comparable as the bare ITO-based devices. In contrast, the performance of ITO-Cl-ODCB:H2O2-based devices with both small and the scaled-up areas significantly surpass the ITO/PEDOT:PSS-based devices. Furthermore, detailed experimental studies are conducted linking optical property, blend morphology, and physical dynamics to find the reasons for the performance difference. By applying the ITO-Cl-ODCB:H2O2 anode to six other photovoltaic systems, the device efficiencies are enhanced by 3.6–6.2% relative to those of the ITO/PEDOT:PSS-based control devices, which validates its great application potential of co-solvent-modified ITO anode employed into PEDOT:PSS-free PSCs.
CRIS-Team Scopus Importer:2021-09-24
Keywords: blend morphology; non-fullerene acceptors; optical transmittance; polymer solar cells; surface chlorination

Perfluoroalkylsulfonyl ammonium for humidity- resistant printing high-performance phase-pure FAPbI3 perovskite solar cells and modules - Chen, Xining; Yang, Fu; Yuan, Linhao; Huang, Shihao; Gu, Hao; Wu, Xiaoxiao; Shen, Yunxiu; Chen, Yujin; Li, Ning; Egelhaaf, Hans-Joachim; Brabec, Christoph; Zhang, Rui; et al. (Joule, 2024)
High-quality phase-pure formamidinium lead triiodide (FAPbI3) perovskite film needs to be fabricated under strict control of the surrounding atmosphere, which becomes more rigorous when large-area FAPbI3 film is involved, leading to high-performance FAPbI3 perovskite solar cells and modules predominantly carried out in an inert gas-filled atmosphere. In this work, we propose a scalable printing strategy for the large-area high-quality phase-pure FAPbI3 film under a high-humidity atmosphere (up to 75% ± 5% relative humidity) by regulating the perovskite precursor ink with a functional perfluoroalkylsulfonyl quaternary ammonium iodide. This approach decreases the energy barriers of cubic phase formation and heterogeneous nucleation, thereby regulating the FAPbI3 crystallization. The printed photovoltaic small-area cells and large-area modules achieved remarkable power conversion efficiencies of 24.37% and 22.00%, respectively. Specifically, the unencapsulated device exhibits superior operational stability with T90 > 1,060 h, ambient stability with T90 > 2,020 h, and thermal stability with T90 > 2,350 h.
CRIS-Team Scopus Importer:2024-07-19
Keywords: blade coating; film formation; humid atmosphere; perovskite crystallization; perovskite solar cells; scalable printing; solar module; stable perovskite

Performance Analysis of Pre-Cracked PV-Modules at Realistic Loading Conditions - Buerhop, Claudia; Winkler, Thilo; Fecher, Frank W.; Hauch, Jens; Bemm, Andreas; Camus, Christian; Brabec, Christoph (33rd European Photovoltaic Solar Energy Conference and Exhibition, 2017)
Damaged modules, especially with existing cell cracks, are observed quite often in PV-installations. Little knowledge exists about the stability of such pre-cracked modules under real operating conditions. Previous investigations and existing standards focus on the degradation of new, defect-free modules. This work highlights a twofold approach for performance study of pre-cracked modules: 1) artificial stressing of 20 representative pre-cracked modules with a novel load test set-up simulating snow and wind loads, 2) simulating IV-curves of cracked cells. The experimental results are discussed with respect to field exposure data. EL-images of stressed PV-modules indicate that new cracks are only initiated once a certain threshold is exceeded. Below this threshold formerly unseen cracks open, as can be seen by small changes in the EL-intensity. Power measurements yield a strong power reduction at the loaded state. Due to the solar cell being under tension the cracks open and the separated areas lose their electrical contact. Considering a break resistance in the IVcurve, simulations lead to good agreement with the observed experimental results. It is highlighted that the electric contact after unloading for the previously unloaded module recovers visibly in the ELimage as well as in the power output. Simulating real weather (operating) conditions by moderate static loading tests reveals no measurable changes in the EL-images affecting the power output.
Keywords: Degradation; Performance; Module; Cracks; EL Imaging

Performance enhancement of the p3ht/pcbm solar cells through nir sensitization using a small-bandgap polymer - Ameri, Tayebeh; Min, Jie; Li, Ning; Machui, Florian; Baran, Derya; Forster, Michael; Schottler, Kristina J.; Dolfen, Daniel; Scherf, Ullrich; Brabec, Christoph (Advanced Energy Materials, 2012)

Performance Evaluation of Semitransparent Perovskite Solar Cells for Application in Four-Terminal Tandem Cells - Kirchartz, Thomas; Korgitzsch, Sophie; Hüpkes, Jürgen; Ramírez Quiroz, César Omar; Brabec, Christoph (ACS Energy Letters, 2018)
The efficiency of perovskite-based tandem solar cells and the respective efficiency gain over the single-junction operation of the bottom cell strongly depend on the performance of the component cells. Thus, a fair comparison of reported top cells is difficult. We therefore compute the tandem cell efficiency for the combination of several semitransparent perovskite top solar cells and crystalline silicon or chalcopyrite bottom cells from the literature. We focus on four-terminal configurations but also estimate and discuss the differences between four- and two-terminal configurations. For each top cell, we thereby determine the tandem cell performance as a function of the bottom cell efficiency, which results in a linear relationship. From these data, we extract two parameters to quantify the suitability of the top cell: (i) the slope of the tandem vs. bottom cell efficiency, which is the effective transparency of the top cell, and (ii) the tandem cell efficiency for a targeted bottom cell. These two figures of merit were calculated for a representative set of bottom cells and may serve for comparison of semitransparent perovskite top cells in the future. Copyright © 2018 American Chemical Societ
Keywords: Copper compounds; Efficiency; Perovskite; Perovskite solar cells

Performance of a Module and Defect Detection Algorithm for Aerial Infrared Images as a Function of the Flying Altitude - Dalsaß, Manuel; Deitsch, Sergiu; Luchscheider, Philipp; Gallwitz, Florian; Brabec, Christoph (32nd European Photovoltaic Solar Energy Conference and Exhibition, 2016)
n recent years, remote-controlled unmanned air vehicles (UAV) have been used increasingly to attain aerial infrared (aIR) recordings of large photovoltaic (PV) power plants with which thermally suspicious PV modules can be identified and localized. But so far, aIR recordings are still analyzed mostly manually – a process which can be extremely time-consuming and error-prone. In this context, the performance of a module and defect detection algorithm for aIR images is evaluated as a function of the flying altitude. For this purpose, aIR recordings of a PV power plant are generated from six flying altitudes from 5 m to 30 m above ground level by means of a drone measurement system and used as data input for the image processing tool. The results indicate optimal flying altitudes for both module and defect detection. However, the most suitable flying altitude may be a compromise with further conditions. The findings of this work will advance future automatic monitoring and early detection systems.<br
Keywords: Monitoring; Aerial Thermography; PV Module Defects; Automatic Detection

Perovskite solar cells fabricated using dicarboxylic fullerene derivatives - Erten-Ela, Sule; Chen, Haiwei; Kratzer, Andreas; Hirsch, Andreas; Brabec, Christoph (New Journal of Chemistry, 2016)
Perovskite solar cells were first fabricated in dye sensitized solar cells. But also, perovskite hybrid solar cells were demonstrated to be among the most promising candidates within the emerging photovoltaic materials with their high power conversion efficiencies and low-cost fabrication. In this work, we design and synthesize a novel benzoic acid fullerene bis adduct material (BAFB) for use in perovskite hybrid organic-inorganic solar cells. The obtained maximum efficiency is reported to be 9.63% using a novel benzoic acid fullerene bis adduct (BAFB) for perovskite heterojunction solar cells.

Perspectives of solution epitaxially grown defect tolerant lead-halide-perovskites and lead-chalcogenides - Afify, Hany A.; Sytnyk, Mykhailo; Zhou, Shuyu; Osvet, Andres; Brabec, Christoph; Korczak, Jedrzej; Szczerbakow, Andrzej; Story, Tomasz; Heiß, Wolfgang (Applied Physics Letters, 2021)
Lead-chalcogenides and lead-halide-perovskites exhibit similar physical properties, which can be summarized as defect tolerant behavior. While the lead-chalcogenides have been pioneering materials in vapor phase epitaxy, metal-halide-perovskites offer the possibility for epitaxial growth from solutions by techniques such as spin or drop casting. The obtained microstructures show promising optical properties, and in a showcase example of formamidinium-lead-tribromide on lead sulfide, we show first lasing results. These results open up several perspectives for solution epitaxial structures, including electrically pumped quantum devices, demanded not only for lighting but also for quantum information technology, which would be another milestone achievement for metal-halide semiconductors.
CRIS-Team WoS Importer:2021-12-17

Phase diagram and stability of mixed-cation lead iodide perovskites: A theory and experiment combined study - Xu, Zhengwei; Zhao, Yicheng; Zhang, Jiyun; Chen, Keqiu; Brabec, Christoph; Feng, Yexin (Physical Review Materials, 2020)
Alloying structurally similar perovskites to form mixed-cation lead iodide perovskites, e.g., Cs(x)FA((1-x))PbI(3), MA(x)FA((1-x))PbI(3), and Cs(x)MA(y)FA((1-x-y)) PbI3, could improve the performance of perovskite-based solar cells and light-emitting diodes. However, a phase diagram of them and a clear understanding of the underlying atomic-scale mechanism are still lacking. Using ab initio calculations combined with high-throughput experimentation, we demonstrate the phase diagram of mixed-cation lead iodide perovskites. Only a small proportion of monovalent cations (Cs+/Rb+/MA(+)) could be incorporated into the FAPbI(3)/MAPbI(3) matrix; otherwise it will be separated into delta-CsPbI3, delta-RbPbI3, MAI, etc. The smaller the radius of doping cations, the harder it is to incorporate them into a perovskite lattice and the easier it is to stabilize the perovskite phase. In FAPbI(3)-based multication perovskites, moreover, over 10 mol % alloying is needed to convert delta phase to alpha phase at room temperature. The combined upper and lower limits for doping concentration restrict the appropriate alloying ratio to a narrow window. We further plot the relative energy diagram for triple-cation perovskite Cs(x)MA(y)FA((1-x-y))PbI(3), which reveals the ideal doping ratio for uniform stable alloying. This theory-experiment-combined study provides a clear microscopic picture of phase stability and segregation for mixed-cation perovskite solids.
CRIS-Team WoS Importer:2020-10-09

Phase-Field Simulation of Liquid-Vapor Equilibrium and Evaporation of Fluid Mixtures - Ronsin, Olivier; Jang, Dong Ju; Egelhaaf, Hans-Joachim; Brabec, Christoph; Harting, Jens (ACS Applied Materials and Interfaces, 2021)
In solution processing of thin films, the material layer is deposited from a solution composed of several solutes and solvents. The final morphology and hence the properties of the film often depend on the time needed for the evaporation of the solvents. This is typically the case for organic photoactive or electronic layers. Therefore, it is important to be able to predict the evaporation kinetics of such mixtures. We propose here a new phase-field model for the simulation of evaporating fluid mixtures and simulate their evaporation kinetics. Similar to the Hertz-Knudsen theory, the local liquid-vapor (LV) equilibrium is assumed to be reached at the film surface and evaporation is driven by diffusion away from this gas layer. In the situation where the evaporation is purely driven by the LV equilibrium, the simulations match the behavior expected theoretically from the free energy: for evaporation of pure solvents, the evaporation rate is constant and proportional to the vapor pressure. For mixtures, the evaporation rate is in general strongly time-dependent because of the changing composition of the film. Nevertheless, for highly nonideal mixtures, such as poorly compatible fluids or polymer solutions, the evaporation rate becomes almost constant in the limit of low Biot numbers. The results of the simulation have been successfully compared to experiments on a polystyrene-toluene mixture. The model allows to take into account deformations of the liquid-vapor interface and, therefore, to simulate film roughness or dewetting.
CRIS-Team Scopus Importer:2021-12-24
Keywords: evaporation; film drying; liquid-vapor equilibrium; phase-field

Phosphor Particles for Luminescent Down-Shifting in Photovoltaics: Determination of Complex Refractive Indices - Lipovsek, Benjamin; Solodovnyk, Anastasiia; Riedel, Daniel; Osvet, Andres; Gast, Jessica; Stern, Edda; Forberich, Karen; Batentschuk, Miroslaw; Brabec, Christoph; Krč, Janez; Topič, Marko (33rd European Photovoltaic Solar Energy Conference and Exhibition, 2017)
We demonstrate a novel two-step method for accurate determination of the complex refractive indices of phosphor materials in particulate form. The real part of the refractive index is first measured at a number of selected wavelengths using the Becke Line method; the results are interpolated over a broader wavelength range using Sellmeier's equations. The imaginary part of the refractive index is extracted from measured optical characteristics of polymer layers embedded with phosphor particles; a specialized numerical simulation tool is employed for this purpose. Finally, using the determined complex refractive indices, we numerically investigate the potential of luminescent down-shifting applied to thin-film solution-processed solar cells. We study the influence of the main properties of luminescent down-shifting layers filled with phosphor particles, and indicate the gains in the solar cell performance that can be obtained using this approach.
Keywords: Organic Solar Cell; Photoluminescence; Photovoltaic (PV); Modelling / Modeling; Optical Properties

Photocurrent generation and charge transport mechanism study in solution-processed CZTS thin films - Khanzada, Laraib S.; Makhdoom, Muhammad Atif; Lin, Xianzhong; Azimi, Hamed; Brabec, Christoph (Optik, 2023)
Clean, benign and economical energy harvesting is envisioned to mitigate the global climate change – originated from the burning of fossil fuels – addressing both the energy crises and environmental issues. In this work, charge transport mechanism and the dynamics of photocurrent generation in thin films of CZTS nanocrystals is studied. A liquid phase processing route – owing to low temperature – has been adopted using a molecular based precursor solution for the in-situ development of CZTS crystals during film deposition. Results shows that charge carriers follow band conduction and nearest-neighbor hopping (NNH) mechanisms at elevated temperatures while Mott variable-range hopping (VRH) is the dominating phenomenon at low temperatures which are analogues to expensive vacuum-deposited kieserite thin films behavior.
CRIS-Team Scopus Importer:2023-01-06
Keywords: Conductivity; CZTS; Kesterite; Persistent photoconductivity; Solar Cell; Thin Film

Photodegradation of Si-PCPDTBT:PCBM active layer for organic solar cells applications: A surface and bulk investigation - Tournebize, Aurelien; Seck, Mamadou; Vincze, Andrej; Distler, Andreas; Egelhaaf, Hans-Joachim; Brabec, Christoph; Rivaton, Agnes; Peisert, Heiko; Chasse, Thomas (Solar Energy Materials and Solar Cells, 2016)
The photooxidation of a polymer blend film used in efficient solar cells based on poly[(4,40-bis(2-ethylhexyl)dithieno[3,2-b:20,30- d]silole)-2,6-diylalt-(2,1,3-benzothiadiazole)-4,7-diyl], (Si-PCPDTBT) and [6,6]-phenyl-C71-butyric acid methyl (PC70BM) has been investigated. A set of experiments from complementary techniques was developed to monitor the modifications during ageing that occur not only in the bulk but also at the surface. The surface analyses were performed by X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM), and the bulk analyses by UV–visible spectroscopy and infrared (IR) spectroscopy. The results reveal that the silicon bridge atom is the first target of degradation. We have identified the existence of a photooxidation profile within the 300 nm thick film. Such a heterogeneous degradation was confirmed by time-of-flight secondary ion mass spectrometry (TOF-SIMS) depth profiling.
Keywords: Active layer; Degradation; Organic solar cell; Photooxidation profile

Photoinduced degradation of methylammonium lead triiodide perovskite semiconductors - Tang, Xiaofeng; Brandl, Marco; May, Benjamin; Levchuk, Ievgen; Hou, Yi; Richter, Moses; Chen, Haiwei; Chen, Shi; Kahmann, Simon; Osvet, Andres; Maier, Florian; Steinrück, Hans-Peter; et al. (Journal of Materials Chemistry A, 2016)
Photoinduced degradation is a critical obstacle for the real application of novel semiconductors for photovoltaic applications. In this paper, the photoinduced degradation of CHNHPbI in a vacuum and air (relative humidity 40%) is analyzed by ex situ and advanced in situ technologies. Without light illumination, CHNHPbI films slowly degrade under vacuum and air within 24 hours. However, we find that CHNHPbI converts to metallic lead (Pb) when exposed to vacuum and light illumination. Further, a series of lead salts (e.g. PbO, Pb(OH) and PbCO) are formed when CHNHPbI is degraded under environmental conditions, i.e. under the combination of light, oxygen and moisture. Photoinduced degradation is found to be determined by the environmental atmosphere as CHNHPbI films remain very stable under nitrogen conditions. The results from vacuum conditions underpin that the high volatility of the organic component (CHNHI) is in conflict with reaching excellent intrinsic stability due to its role in creating ion vacancies. The degradation in air suggests that both oxygen and water contribute to the fast photodecomposition of CHNHPbI into lead salts rather than water alone. Given these basic yet fundamental understandings, the design of hydrophobic capping layers becomes one prerequisite towards long-term stable perovskite-based devices.
Keywords: Engineering controlled terms: Lead; Perovskite; Salts; Slow light Environmental conditions; Intrinsic stability; Light illumination; Organic components; Photo-decomposition; Photoinduced degradation; Photovoltaic applications; Real applications Engineering main heading: Photodegradation

Photoluminescence for Defect Detection on Full-Sized Photovoltaic Modules - Doll, Bernd; Hepp, Johannes; Hoffmann, Mathis; Schuler, Rene; Buerhop-Lutz, Claudia; Peters, Ian Marius; Hauch, Jens; Maier, Andreas; Brabec, Christoph (IEEE Journal of Photovoltaics, 2021)
Cost-effective, fast, and nondestructive on-site characterization of photovoltaic plants is required to determine countermeasures against power loss, defects, or safety problems. Methods with small impact on the operation and a high throughput, such as infrared thermography (IR), or methods with high resolution for detailed defect information, such as electroluminescence (EL) imaging, are expedient. To combine high resolution and high throughput, we propose to use photoluminescence (PL) as an outdoor characterization method for full-sized module imaging. With PL imaging as with IR imaging, no electrical contact is necessary, yet image resolution is on par with EL images. Our outdoor PL setup features an excitation source with 18 broadband, white, high power, chip on board LEDs coupled with low-cost short pass filters. This setup is suitable for indium gallium arsenide and silicon detectors. Here, we compare the visibility of common defects, including short-circuited bypass diodes, cracks, potential induced degradation, snail trails, ethylene-vinyl acetate degradation, and interconnection failures, in PL images to that in state-of-the-art imaging techniques IR, EL, and ultraviolet fluorescence. We find that out of these seven defects, five can be detected well, cell cracks under certain conditions, and interconnection failures not at all. We discuss how different techniques are complementary to enable better defect detection.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Cameras; Defect detection; Detectors; fluorescence; Image resolution; Imaging; luminescence; photoluminescence; photovoltaic (PV) systems; Silicon; silicon (Si); Throughput; Tools

Photoluminescence properties of thermographic phosphors YAG:Dy and YAG:Dy, Er doped with boron and nitrogen - Chepyga, Liudmyla M.; Jovicic, Gordana; Vetter, Andreas; Osvet, Andres; Osvet, Andres; Brabec, Christoph; Batentschuk, Miroslaw (Applied Physics B-Lasers and Optics, 2016)
This paper investigates Dy-doped and Dy, Er-co-doped yttrium aluminum garnets (YAG) with the admixture of boron nitride with the aim of using them as efficient thermographic phosphors at high temperatures. The phosphors were synthesized using a conventional high-temperature solid-state method. The influence of two fluxes, BO and LiF/NHF, and the effect of activator and coactivator concentrations were investigated. Additionally, the effect of B and N substituting for Al and O ions, respectively, in the YAG:Dy co-doped with Er was studied for the first time. The changes in the host lattice led to a much stronger photoluminescence compared with the samples without B and N substitution. The admixture of BN also improves the thermal sensitivity of the YAG:Dy and YAG:Dy, Er thermographic phosphor
Keywords: Engineering controlled terms: Erbium; Light emission; Photoluminescence Coactivators; High temperature; High temperature solid state methods; Host lattice; Photoluminescence properties; Thermal sensitivity; Thermographic phosphors; Yttrium aluminum garnet Engineering main heading: Phosphors

Photoluminescent and storage properties of photostimulable core/shell type silicate nanoparticles - Osvet, Andres; Batentschuk, Miroslaw; Milde, Moritz; Lundt, Nils; Gellermann, Carsten; Dembski, Sofia; Winnacker, Albrecht; Brabec, Christoph (Physica Status Solidi (C) Current Topics in Solid State Physics, 2013)
We have prepared hybrid luminescent nanoparticles with amorphous SiO cores and crystalline ZnSiO:Mnshells by sol-gel technology. Under UV excitation the shells of the particles emit green Mn-related luminescence at 525 nm. In addition, under the UV excitation at least two kinds of traps are filled with electrons, contributing to a long afterglow and photostimulated luminescence. The paper presents the details of the charging and stimulation characteristics of the photostimulated luminescence. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Luminescent core/shell nanoparticles; Nanophosphors; Photostimulated luminescence; Zn2SiO4:Mn2+

Photophysics of Molecular-Weight-Induced Losses in Indacenodithienothiophene-Based Solar Cells - Gasparini, Nicola; Katsouras, Athanasios; Prodromidis, Mamantos I.; Avgeropoulos, Apostolos; Baran, Derya; Salvador, Michael Filipe; Fladischer, Stefanie; Spiecker, Erdmann; Chochos, Christos L.; Ameri, Tayebeh; Brabec, Christoph (Advanced Functional Materials, 2015)
The photovoltaic performance and optoelectronic properties of a donor-acceptor copolymer are reported based on indacenodithienothiophene (IDTT) and 2,3-bis(3-(octyloxy)phenyl)quinoxaline moieties (PIDTTQ) as a function of the number-average molecular weight (Mn). Current-voltage measurements and photoinduced charge carrier extraction by linear increasing voltage (photo-CELIV) reveal improved charge generation and charge transport properties in these high band gap systems with increasing Mn, while polymers with low molecular weight suffer from diminished charge carrier extraction because of low mobility-lifetime (μτ) product. By combining Fourier-transform photocurrent spectroscopy (FTPS) with electroluminscence spectroscopy, it is demonstrate that increasing Mn reduces the nonradiative recombination losses. Solar cells based on PIDTTQ with Mn = 58 kD feature a power conversion efficiency of 6.0% and a charge carrier mobility of 2.1 × 10-4 cm2 V-1 s-1 when doctor bladed in air, without the need for thermal treatment. This study exhibits the strong correlations between polymer fractionation and its optoelectronics characteristics, which informs the polymer design rules toward highly efficient organic solar cells.
Keywords: charge transport; energetic losses; indacenodithienothiophene; molecular weight; organic solar cells

Photostimulable fluorescent nanoparticles for biological imaging - Osvet, Andres; Milde, Moritz; Dembski, Sofia; Rupp, Sabine; Gellermann, Carsten; Batentschuk, Miroslaw; Brabec, Christoph; Winnacker, Albrecht (2011 MRS Spring Meeting, 2012)
Spherical monodisperse core/shell-type nanoparticles, comprising an amorphous SiO core coated with a luminescent phosphor layer were synthesized by the modified Pechini processes. The sol-gel method allows covering the 50-500 nm core particles with different inorganic phosphor layers of about 10 nm thickness, doped with rare-earth or transition metal ions which determine the luminescent properties. Particles comprising a Zn SiO shell, doped with Mn ions, are not only fluorescent under UV irradiation (260 nm), but store the activation energy by trapping electrons/holes at lattice defects. This energy is released as phosphorescence in the time scale of seconds and minutes, or as photostimulated luminescence under the excitation of red light (650 nm). Traps related to these processes are different, and their concentration is affected by the preparation conditions of the particles. © 2011 Materials Research Society.
Keywords: Biological imaging; Core particles; Fluorescent nanoparticles; Luminescent property; Monodisperse; Pechini process; Phosphor layers; Photo stimulated luminescence; Preparation conditions; Red light; Time-scales; Trapping electrons; UV irradiation Engineering controlled terms: Activation energy; Biological materials; Coated materials; Fluorescence; Light emission; Manganese; Manganese compounds; Metal ions; Nanoparticles; Phosphors; Silicon compounds; Sol-gel process; Transition metals Engineering main heading: Amorphous materials

Photovoltaic limitations of BODIPY:fullerene based bulk heterojunction solar cells - Baran, Derya; Tuladhar, Sachetan; Economopoulos, Solon P.; Neophytou, Marios; Savva, Achilleas; Itskos, Grigorios; Othonos, Andreas; Bradley, Donal D C; Brabec, Christoph; Nelson, Jenny; Choulis, Stelios A. (Synthetic Metals, 2017)
The photovoltaic performance of blends of a series of 4,4′-Difluoro-4-bora-3a,4a-diaza-s-indacenes)-based (BODIPY) conjugated polymers donors with fullerene electron acceptors is investigated. Despite the high Voc values observed, solar cell device yields relatively low power conversion efficiencies. Our study takes into account the materials’ structure-property relationship, light harvesting capabilities, charge transport, collection properties and morphological characteristics to elucidate factors affecting the photovoltaic performance in this class of polymers. We show that elimination of low molecular weight species and suitable electrodes for hole collection can be used to overcome some of the observed limitations on photovoltaic performance.
Keywords: BODIPY polymer donors; Charge transport; Collection; Fractionation process; Morphology; Organic solar cells

Photovoltaic loss analysis of inkjet-printed polymer solar cells using pristine solvent formulations - Hoth, C. N.; Schilinsky, P.; Choulis, S. A.; Brabec, Christoph (Macromolecular Symposia, 2010)
We have recently reported inkjet-printed organic solar cells with a record power conversion efficiency of 3.5%. In this contribution, we present our first trials to process a functional active layer of a polymer:fullerene bulk-hetero junction solar cell by inkjet printing using tetralene as a solvent. Solar cells with the inkjet-printed active layer based on pristine tetralene show calibrated AM1.5 power conversion efficiency (PCE) of around 1.3% over comparable doctor bladed cells with PCE of 3.3%. Analysis in terms of one-diode equivalent circuit combined with current-voltage characteristics of the devices as a function of light intensity and voltage were performed to reveal the dominant loss mechanisms of the inkjet printed solar cells using tetralene solvent formulation. The loss analysis described in this paper helps us to identify the device performance limitations and to design methods to improve the performance of inkjet printed organic solar cells. Copyright © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Device loss analysis; Fullerene; Inkjet printing; Morphology; Organic photovoltaics; Polymer; Polymer solar cells; Solvent formulations

Photovoltaic properties of benzotriazole containing alternating donor-acceptor copolymers: Effect of alkyl chain length - Baran, Derya; Balan, Abidin; Stubhan, Tobias; Ameri, Tayebeh; Toppare, Levent; Brabec, Christoph (Synthetic Metals, 2012)
A series of variable alkyl chain length substituted donor-acceptor (D-A) conjugated polymers with thiophene ring as the donor and benzotriazole moiety as the acceptor has been investigated in bulk heterojunction solar cells. The optical and electrochemical properties showed that the absorption onsets and the energy levels of the copolymers were not affected by alkyl substitution revealing 1.9 eV of optical band gap. The morphologies of the blend film can be fine-tuned by increasing the chain length attached to the benzotriazole unit. Photovoltaic devices were fabricated using (6,6)-phenyl-C-butyric acid methyl ester (PCBM) and (6,6)-phenyl-C-butyric acid methyl ester (PCBM) as the acceptors. The maximum performance was achieved with a V of 0.75 V, J of 3.70 mA/cm , FF of 45% and a PCE of 1.23% for the PTBT-DA10:PCBM device using 1:4 w/w ratio in chlorobenzene (CB). © 2012 Elsevier B.V. All rights reserved.
Keywords: Benzotriazole; Donor-acceptor polymers; Effect of chain length; Organic photovoltaics; Solar cell

Physics-guided characterization and optimization of solar cells using surrogate machine learning model - Ren, Zekun; Oviedo, Felipe; Xue, Hansong; Thway, Muang; Zhang, Kaicheng; Li, Ning; Perea, Jose Dario; Layurova, Mariya; Wang, Yue; Tian, Siyu I. P.; Heumüller, Thomas; Birgersson, Erik; et al. (2019 IEEE 46th Photovoltaic Specialists Conference (PVSC), 2019)
Characterization, material parameter extraction and subsequent optimization of solar cell devices is a highly time‑consuming and complex procedure. In this work, we propose a method for quick extraction of limiting material parameters in solar cell devices using a surrogate, physics-embedded, neural network model. This surrogate model, implemented by an autoencoder architecture trained with a physical numerical model, allows to quickly extract the device parameters of interest at a certain process condition by using only a small number of illumination dependent current-voltage (JV) measurements. Our surrogate model adequately links material parameters at a certain process condition to final device efficiency. The model provides physical insights about the location of the best performing and robust processing conditions in solar cell devices. We test our approach with GaAs and CH3NH3PbI3 (MAPbI) perovskite solar cells. The model allows to find a set of processing conditions that maximize the performance of both GaAs and MAPbI solar cells, and analogous processing conditions that minimize solar cell variabili

Pinhole-Free Inkjet Printing Strategies for Organic Electronics - Heinrichsdobler, Armin; Roigk, Julia Christina; Schirmeier, Frank; Brabec, Christoph; Wehlus, Thomas (Advanced Materials Technologies, 2017)
Inkjet printing is a widely used technique in the field of printed electronics. Yet its reliability is limited because absent droplets induced by defective, e.g., clogged, nozzles can lead to pinholes in the printed layers causing a reduction of the quality of printed films or a breakdown of the functionality in microelectronic devices. Therefore, pinholes in inkjet-printed layers need to be avoided. In this study the origins for pinholes in inkjet-printed films are examined. It is found that single missing droplets cannot lead to pinholes but certain formations can. This paper presents the corresponding responsible combinations of defective nozzles necessary to create a pinhole. To enable a statistical approach the pinhole occurrence probabilities are computed depending on the number of broken nozzles as well as quality factors and step sizes with a Monte Carlo simulation. The model shows that by choosing the right print strategy the pinhole probability can be reduced by three orders of magnitude. Finally, a novel print strategy is suggested, which is not yet supported by default printer settings but can reduce the pinhole probability even further by a factor of over 2000 in total. This represents the smallest pinhole occurrence probability ever achieved.
Keywords: inkjet printing; Monte Carlo simulation; pinholes; printed electronics

PMMA as an effective protection layer against the oxidation of P3HT and MDMO-PPV by ozone - Früh, Andreas; Egelhaaf, Hans Joachim; Hintz, Holger; Quinones, Dustin; Brabec, Christoph; Peisert, Heiko; Chassé, Thomas (Journal of Materials Research, 2018)
The protective effect of poly(methylmethacrylate) (PMMA) cover layers against the degradation of π-conjugated polymers by ozone and photo-oxidation, respectively, has been investigated by UV/Vis spectroscopy. The PMMA films were cast from solution at thicknesses between 20 and 100 nm on top of films of poly(3-hexylthiophene) and poly[2-methoxy-5-(3′,7′-dimethyloctyloxy)-1,4-phenylenevinylene]. PMMA layers of more than 65 nm in thickness reduce the oxidation rate of the π-conjugated polymers under 15 ppm of ozone in the dark by more than three orders of magnitude, whereas photo-oxidation rates under dry and humid air remain unaffected. The PMMA cover layers are hardly affected by ambient ozone over thousands of hours. Calculations of ozone and oxygen fluxes through the PMMA films reveal that ozonation rates are limited by the diffusion of ozone, whereas photo-oxidation rates are not limited by the diffusion of oxygen, due to the much larger pressure gradient of the latte
Keywords: optoelectronic; organic; oxidation

Polarons in Narrow Band Gap Polymers Probed over the Entire Infrared Range: A Joint Experimental and Theoretical Investigation - Kahmann, Simon; Fazzi, Daniele; Matt, Gebhard; Thiel, Walter; Loi, Maria A.; Brabec, Christoph (Journal of Physical Chemistry Letters, 2016)
We investigate the photoinduced absorption (PIA) spectra of the prototypical donor-acceptor polymer [2,6-(4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b′]dithiophene)-alt-4,7-(2,1,3-benzothiadiazole)] (C-PCPDTBT) and its silicon bridged variant Si-PCPDTBT over a spectral range from 0.07 to 1.5 eV. Comparison between time-dependent density functional theory simulations of the electronic and vibrational transitions of singlet excitons, triplet excitons, polarons, and bipolarons with the experimental results proves that the observed features are due to positive polarons delocalized on the polymer chains. We find that the more crystalline Si-bridged variant gives rise to a red-shift in the transition energies, especially in the mid-infrared (MIR) spectral range and furthermore observe that the pristine polymers' responses depend on the excitation energy. Blending with PCBM, on the other hand, leads to excitation-independent PIA spectra. By computing the response properties of molecular aggregates, we show that polarons are delocalized in not only the intra- but also the interchain direction, leading to intermolecular transitions which correspond well to experimental absorption features at the lowest energies.
Keywords: Engineering controlled terms: Blending; Computation theory; Density functional theory; Energy gap; Excitons; Polarons 2; 1; 3-Benzothiadiazole; Donor-acceptor polymers; Interchain direction; Narrow band gap polymers; Photoinduced absorption; Theoretical investigations; Time dependent density functional theory; Vibrational transitions Engineering main heading: Polymers

Polymer-acid-metal quasi-ohmic contact for stable perovskite solar cells beyond a 20,000-hour extrapolated lifetime - Luo, Junsheng; Liu, Bowen; Yin, Haomiao; Zhou, Xin; Wu, Mingjian; Shi, Hongyang; Zhang, Jiyun; Elia, Jack; Zhang, Kaicheng; Wu, Jianchang; Xie, Zhiqiang; Liu, Chao; et al. (Nature Communications, 2024)
The development of a robust quasi-ohmic contact with minimal resistance, good stability and cost-effectiveness is crucial for perovskite solar cells. We introduce a generic approach featuring a Lewis-acid layer sandwiched between dopant-free semicrystalline polymer and metal electrode in perovskite solar cells, resulting in an ideal quasi-ohmic contact even at elevated temperature up to 85 °C. The solubility of Lewis acid in alcohol facilitates nondestructive solution processing on top of polymer, which boosts hole injection from polymer into metal by two orders of magnitude. By integrating the polymer-acid-metal structure into solar cells, devices exhibit remarkable resilience, retaining 96% ± 3%, 96% ± 2% and 75% ± 7% of their initial efficiencies after continuous operation in nitrogen at 35 °C for 2212 h, 55 °C for 1650 h and 85 °C for 937 h, respectively. Leveraging the Arrhenius relation, we project an impressive T80 lifetime of 26,126 h at 30 °C.
CRIS-Team Scopus Importer:2024-03-15

Polymer-based scattering layers for internal light extraction from organic light emitting diodes - Riedel, Daniel; Wehlus, Thomas; Reusch, Thilo C. G.; Brabec, Christoph (Organic Electronics, 2016)
Efficient light extraction for organic light emitting diodes (OLED) using scalable processes and low-cost materials are important prerequisites for the future commercialization of OLED lighting devices. The light-extraction technology exhibited in this paper uses polymer-based high-refractive index scattering layers processed from solution. The scatter matrix formulation incorporates two types of nanoparticles for refractive index tuning and scattering, respectively. Planarization by the same material in order to reduce surface defects was critical for achieving highly increased device yield. Highly efficient and defect-free large-area (1.8 cm) white OLED devices were fabricated on top of the scattering layer in a bottom emitter configuration. Light extraction enhancement leads to an overall efficiency gain of up to 81% for luminances of 5000 cd m.
Keywords: Internal light extraction; OLED; Organic light-emitting diodes; Planarization; Scattering layers

Polymer-fullerene bulk-heterojunction solar cells - Brabec, Christoph; Gowrisanker, Srinivas; Halls, Jonathan J. M.; Laird, Darin; Jia, Shijun; Williams, Shawn P. (Advanced Materials, 2010)
Solution-processed bulk heterojunction organic photovoltaic (OPV) devices have gained serious attention during the last few years and are established as one of the leading next generation photovoltaic technologies for low cost power production. This article reviews the OPV development highlights of the last two decades, and summarizes the key milestones that have brought the technology to today's efficiency performance of over 7%. An outlook is presented on what will be required to drive this young photovoltaic technology towards the next major milestone, a 10% power conversion efficiency, considered by many to represent the efficiency at which OPV can be adopted in wide-spread applications. With first products already entering the market, sufficient lifetime for the intended application becomes more and more critical, and the status of OPV stability as well as the current understanding of degradation mechanisms will be reviewed in the second part of this article. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Polymer: Nonfullerene Bulk Heterojunction Solar Cells with Exceptionally Low Recombination Rates - Gasparini, Nicola; Salvador, Michael Filipe; Heumüller, Thomas; Richter, Moses; Classen, Andrej; Shrestha, Shreetu; Matt, Gebhard; Holliday, Sarah; Strohm, Sebastian; Egelhaaf, Hans Joachim; Wadsworth, Andrew; Baran, Derya; et al. (Advanced Energy Materials, 2017)
Organic semiconductors are in general known to have an inherently lower charge carrier mobility compared to their inorganic counterparts. Bimolecular recombination of holes and electrons is an important loss mechanism and can often be described by the Langevin recombination model. Here, the device physics of bulk heterojunction solar cells based on a nonfullerene acceptor (IDTBR) in combination with poly(3-hexylthiophene) (P3HT) are elucidated, showing an unprecedentedly low bimolecular recombination rate. The high fill factor observed (above 65%) is attributed to non-Langevin behavior with a Langevin prefactor (β/βL) of 1.9 × 10-4. The absence of parasitic recombination and high charge carrier lifetimes in P3HT:IDTBR solar cells inform an almost ideal bimolecular recombination behavior. This exceptional recombination behavior is explored to fabricate devices with layer thicknesses up to 450 nm without significant performance losses. The determination of the photoexcited carrier mobility by time-of-flight measurements reveals a long-lived and nonthermalized carrier transport as the origin for the exceptional transport physics. The crystalline microstructure arrangement of both components is suggested to be decisive for this slow recombination dynamics. Further, the thickness-independent power conversion efficiency is of utmost technological relevance for upscaling production and reiterates the importance of understanding material design in the context of low bimolecular recombination. © 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Charge recombination; Charge transport; Langevin; Nonfullerene acceptor; Organic photovoltaic devices

Power-Law Density of States in Organic Solar Cells Revealed by the Open-Circuit Voltage Dependence of the Ideality Factor - Saladina, Maria; Wöpke, Christopher; Göhler, Clemens; Ramirez, Ivan; Gerdes, Olga; Liu, Chao; Li, Ning; Heumüller, Thomas; Brabec, Christoph; Walzer, Karsten; Pfeiffer, Martin; Deibel, Carsten (Physical Review Letters, 2023)
The density of states (DOS) is fundamentally important for understanding physical processes in organic disordered semiconductors, yet hard to determine experimentally. We evaluated the DOS by considering recombination via tail states and using the temperature and open-circuit voltage (V_oc) dependence of the ideality factor. By performing Suns-V_oc measurements, we find that the energetic disorder increases deeper into the band gap, which is not expected for a Gaussian or exponential DOS. The linear dependence of the disorder on energy reveals the power-law DOS in organic solar cells.
CRIS-Team Scopus Importer:2023-07-07

Precursor-Engineered Volatile Inks Enable Reliable Blade-Coating of Cesium–Formamidinium Perovskites Toward Fully Printed Solar Modules - Du, Tian; Rehm, Viktor; Qiu, Shudi; Pal, Subhajit; Jang, DongJu; Peng, Zijian; Zhang, Jiyun; Yuan, Haozhen; Briscoe, Joe; Heiß, Wolfgang; Brabec, Christoph J.; Egelhaaf, Hans Joachim (Advanced Science, 2024)
Reliable fabrication of large-area perovskite films with antisolvent-free printing techniques requires high-volatility solvents, such as 2-methoxyethanol (2ME), to formulate precursor inks. However, the fabrication of high-quality cesium–formamidinium (Cs–FA) perovskites has been hampered using volatile solvents due to their poor coordination with the perovskite precursors. Here, this issue is resolved by re-formulating a 2ME-based Cs0.05FA0.95PbI3 ink using pre-synthesized single crystals as the precursor instead of the conventional mixture of raw powders. The key to obtaining high-quality Cs–FA films lies in the removal of colloidal particles from the ink and hence the suppression of colloid-induced heterogeneous nucleation, which kinetically facilitates the growth of as-formed crystals toward larger grains and improved film crystallinity. Employing the precursor-engineered volatile ink in the vacuum-free, fully printing processing of solar cells (with carbon electrode), a power conversion efficiency (PCE) of 19.3%, a T80 (80% of initial PCE) of 1000 h in ISOS-L-2I (85 °C/1 Sun) aging test and a substantially reduced bill of materials are obtained. The reliable coating methodology ultimately enables the fabrication of carbon-electrode mini solar modules with a stabilized PCE of 16.2% (average 15.6%) representing the record value among the fully printed counterparts and a key milestone toward meeting the objectives for a scalable photovoltaic technology.
CRIS-Team Scopus Importer:2024-05-24
Keywords: cesium formamidinium perovskite; reliable blade coating; single crystals; solar module; volatile ink

Predicting layer thicknesses by numerical simulation for meniscus-guided coating of organic photovoltaics - Gumpert, Fabian; Janßen, Annika; Brabec, Christoph; Egelhaaf, Hans-Joachim; Lohbreier, Jan; Distler, Andreas (Engineering Applications of Computational Fluid Mechanics, 2023)
To achieve maximum efficiency in organic photovoltaics (OPV), functional layers with uniform and exactly predefined thickness are required. An in-depth understanding of the coating process is therefore crucial for an accurate process control. In this paper, the meniscus-guided blade coating process, which is the most commonly used process for the manufacturing of organic electronics, is investigated by experimental and numerical methods. A computational fluid dynamics (CFD) model is created to simulate the coating behaviour of P3HT:O IDTBR, an industrial state-of-the-art active material system used in OPV, and its results' independence of numerical parameters is ensured. In particular, the influence of the coating velocity and the initially injected fluid volume on the resulting wet film thickness is studied. The developed CFD analysis is able to reproduce the experimental results with very high accuracy. It is found that the film thickness follows a power law dependence on the velocity (˜v 2/3) and a linear dependence on the ink volume (˜V). Accordingly, an analytical expression based on our theoretical considerations is presented, which predicts the wet film thickness as a function of the coating velocity and the ink volume only based on easily accessible ink properties. Consequently, this CFD model can effectively substitute time-consuming and expensive experiments, which currently have to be performed manually in the laboratory for a multitude of novel material systems, and thus supports highly accelerated material research. Moreover, the results of this work can be used to achieve homogeneous large-area coatings by utilising accelerated blade coating.
CRIS-Team Scopus Importer:2023-08-18
Keywords: coating techniques; COMSOL multiphysics; Numerical simulation; organic photovoltaics; renewable energy; thin films

Preface - Sablon, Kimberly A.; Heier, Jakob; Tatavarti, Sudersena Rao; Olson, Dana C.; Kippelen, Bernard; Fu, Lan; Brabec, Christoph; Wang, Zhiming; Nüesch, Frank A. (Materials Research Society Symposium Proceedings, 2013)

Preface to the Special Issue of ChemSusChem on Advanced Organic Solar Cells - Brabec, Christoph; Heeney, Martin; Kim, Youngkyoo; Luscombe, Christine K. (Chemsuschem, 2021)
Organic solar cells have garnered much interest as an Earth-abundant and low-energy-production renewable energy source. In their Editorial to the Special Issue on Advanced Organic Solar Cells, Guest Editors Christoph Brabec, Martin Heeney, Youngkyoo Kim, and Christine Luscombe introduce this exciting field and discuss some of the Special Issue's contents.
CRIS-Team Scopus Importer:2021-08-27
Keywords: donor-acceptor systems; nonfullerene acceptors; polymers; renewable energy; solar cells

Printable Dielectric Mirrors with Easily Adjustable and Well-Defined Reflection Maxima for Semitransparent Organic Solar Cells - Bronnbauer, Carina; Hornich, Julian; Gasparini, Nicola; Guo, Fei; Hartmeier, Benjamin; Luechinger, Norman A.; Pflaum, Christoph; Brabec, Christoph; Forberich, Karen (Advanced Optical Materials, 2015)
Building integrated semitransparent thin-film solar cells is a strategy for future eco-friendly power generation. Organic photovoltaics in combination with dielectric mirrors (DMs) are a potential candidate as they promise high efficiencies in parallel to the possibility to adjust the color and thus the transparency of the whole device. A fully solution processed and printable DM with an easily adjustable reflection maximum is presented that can be facilely attached to solar cells. The DM is optimized via optical simulations to the particular needs of the device with regard to photocurrent enhancement. The excellent agreement between experimental and theoretical results confirms the high optical quality of the printed layers with respect to homogeneity and surface roughness. The used inks are organic-inorganic nanocomposites with a large refractive index contrast of ≈0.7. The short-circuit current is enhanced by up to ≈24% for a semitransparent polymer solar cell.
Keywords: Dielectric mirrors; Organic photovoltaics; Printing; Refractive indices; Semitransparent

Printed Organic Solar Cells - Hoth, Claudia N.; Seemann, Andrea; Steim, Roland; Ameri, Tayebeh; Azimi, Hamed; Brabec, Christoph J. (Wiley Blackwell, 2014)
This chapter contains sections titled: This chapter reviews a few of the essential technologies around the organic photovoltaic (OPV) science that are relevant for the realisation of solution-processed bulk-heterojunction solar cells. It begins with a discussion on the various aspects of morphology formation in organic bulk-heterojunction solar cells. Then, the chapter provides a review of the progress in selected interface materials, which are decisive not only for the solar cell performance but also for the long-time stability of the solar cells. Next, the chapter presents and reviews the concept of multilayer solar cells or tandem solar cells for OPV. Following this, a section explains the relevant design criteria for electrodes suitable for OPV. Finally, the chapter is concluded by a review of the overall production process, especially the printing processes for the semiconductor layer.
Keywords: Organic photovoltaic (OPV); Organic photovoltaic (OPV) electrode requirements; Organic photovoltaic (OPV) morphology; Printed organic solar cells; Tandem technology

Printed semi-transparent large area organic photovoltaic modules with power conversion efficiencies of close to 5 % - Lucera, L.; Machui, F.; Schmidt, H. D.; Ahmad, T.; Kubis, P.; Strohm, S.; Hepp, J.; Vetter, Andreas; Egelhaaf, H. -J.; Brabec, Christoph (Organic Electronics, 2017)
Currently, certified lab scale organic photovoltaic (OPV) cells reach efficiencies of more than 12% and life times of 10 years. For commercialization, it is necessary to understand which performance can be reached in fully printed large scale products. Our investigations show that large area, semi-transparent organic photovoltaic modules based on industrially available materials can achieve power conversion efficiencies of more than 4.8% on rigid substrates and 4.3% on flexible ones. The modules processed with a combination of large area coating and laser patterning with an active area of 68.76 cmfor flexible modules and a total area of 197.4 cmfor glass modules offer exceptionally high geometric fill factors of more than 94% and a transparency of more than 10%. The processing recipe and the layout of the modules are based on indications of optical and electrical simulations which allow to produce devices with only negligible losses in comparison to small single cell devices. Losses due to imperfect coating or patterning are identified by thermal imaging.
Keywords: Large area processing; Module; Organic photovoltaics; Renewable energy; Semi-transparent; Slot-die coating

Printed Smart Photovoltaic Window Integrated with an Energy-Saving Thermochromic Layer - Guo, Fei; Chen, Shi; Chen, Zhang; Luo, Hongjie; Gao, Yanfeng; Przybilla, Thomas; Spiecker, Erdmann; Osvet, Andres; Forberich, Karen; Brabec, Christoph (Advanced Optical Materials, 2015)
A smart photovoltaic window is designed and constructed by solution-processing a layer of thermochromic VO2 nanoparticles on top of a semitransparent organic solar cell. The prepared smart window not only produces electricity using the visible part of the solar spectrum but also saves energy via intelligently modulating the amount of NIR radiation passing through the device in response to ambient temperature.

Printing high performance reflective electrodes for organic solar cells - Krantz, Johannes; Forberich, Karen; Kubis, Peter; Machui, Florian; Min, Jie; Stubhan, Tobias; Brabec, Christoph (Organic Electronics, 2015)
In this paper we solve a long term material problem of thin film organic electronics, namely the solution processing of an opaque electrode. Solution processing of opaque metallic top electrodes typically leads to severe shunting problems. We solve this issue by reversing the electrode sequence and print a highly conductive but opaque bottom electrode from metallic precursors. Devices based on these printed bottom electrodes are compared to reference stacks based on evaporated silver. The transparent top electrode is solution processed from silver nanowire inks, which results in highly transparent electrodes with excellent conductivity. The optical, mainly reflective properties of the opaque silver electrode are investigated in comparison to screen-printed silver pastes. The outstanding smoothness of the printed Ag electrode results in high reflectivity and poly(3-hexylthiophene-2,5-diyl):[6,6]-phenyl-C61-butyric acid methyl ester (P3HT:PCBM) based solar cells with η >. 2.5% and high fill factors performing on par with reference devices on evaporated silver electrode layers.
Keywords: Highly reflective electrode; Printed silver precursor ink; Solution processable electrode; Substrate architecture; Superstrate architecture

Printing of Large-Scale, Flexible, Long-Term Stable Dielectric Mirrors with Suppressed Side Interferences - Bronnbauer, Carina; Riecke, Arne; Adler, Marius; Hornich, Julian; Schunk, Gerhard; Brabec, Christoph; Forberich, Karen (Advanced Optical Materials, 2017)
Dielectric mirrors are wavelength-selective mirrors which are based on thin film interference effects. Their optical band can precisely be adjusted in width, position, and reflectance by the refractive index of the applied materials, the layers’ thicknesses, and the amount of deposited layers. Nowadays, they are a well-known light management tool for efficiency enhancement in, for example, semitransparent organic solar cells (OSCs) and light guiding in organic light-emitting diodes (OLEDs). However, most of the dielectric mirrors are still fabricated by lab-scale techniques such as spin-coating or physical vapor deposition under vacuum. Large-scale, fully printed (maximum 20 × 20 cm2) dielectric mirrors with adjustable reflectance characteristics are fabricated, using temperatures of maximum 50 °C and alcohol-based inks. According to the moderate processing conditions they can be easily deposited not only on rigid glass substrates but also on flexible foils. They show high stability against humidity, light irradiation, and temperature, positioning themselves as good candidates for applications in OLEDs and OSCs. Eventually, by simulations and experiments it is verified that a moderate degree of variations in layer thickness and surface roughness can suppress side interference fringes, while not impacting the main transmittance minimum or the main reflection maximum, respectively.
Keywords: Bragg reflectors; Dielectric mirrors; Fully printed; Large scale; Lifetime

Profitability and LCOE of Small Solar Battery Systemsthe German Case. (Smart Grid Solar - A Bavarian Smart Energy Project) - Stegner, Christoph; Luchscheider, Philipp; Bogenrieder, Josef; German, Reinhard; Brabec, Christoph (Proceedings of the 31st European Photovoltaic Solar Energy Conference (EU PVSEC 2015), 2015)
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.IMMD7.profit

Progress in Poly (3-Hexylthiophene) Organic Solar Cells and the Influence of Its Molecular Weight on Device Performance - Wadsworth, Andrew; Hamid, Zeinab; Bidwell, Matthew; Ashraf, Raja S.; Khan, Jafar I.; Anjum, Dalaver H.; Cendra, Camila; Yan, Jun; Rezasoltani, Elham; Guilbert, Anne A. Y.; Azzouzi, Mohammed; Gasparini, Nicola; et al. (Advanced Energy Materials, 2018)
Poly (3-hexylthiophene) (P3HT) was an early frontrunner in the development of donor polymers to be used in organic photovoltaics. A relatively straightforward and inexpensive synthesis suggests that it may be the most viable donor polymer to use in large-scale commercial organic solar cells. Replacing fullerenes with new electron acceptors has led to significant improvements in device performance and stability, with devices now able to exceed an efficiency of 7%. Past studies have reported a dependence of device performance on the molecular weight of the polymer in fullerene-containing blends, however, with nonfullerene acceptors now showing promise a similar study was needed. P3HT blends, with two nonfullerene acceptors (O-IDTBR and EH-IDTBR), were probed using a number of polymer batches with varying molecular weights. O-IDTBR was shown to exhibit a dependence on the polymer molecular weight, with optimal performance achieved with a 34 kDa polymer, while EH-IDTBR displayed an independence in performance with varying polymer molecular weight. Probing the thermal and morphological behavior of the P3HT:O-IDTBR blends suggests that an optimal morphology with pronounced donor and acceptor domains was only achieved with the 34 kDa polymer, and a greater degree of mixing was exhibited in the other blends, likely leading to poorer device performance.
Keywords: IDTBR; molecular weight; nonfullerene; organic photovoltaics; poly (3-hexylthiophene)

Pushing efficiency limits for semitransparent perovskite solar cells - Ramírez Quiroz, César Omar; Levchuk, Ievgen; Bronnbauer, Carina; Salvador, Michael Filipe; Forberich, Karen; Heumüller, Thomas; Hou, Yi; Schweizer, Peter; Spiecker, Erdmann; Brabec, Christoph (Journal of Materials Chemistry A, 2015)
While perovskite-based semitransparent solar cells deliver competitive levels of transparency and efficiency to be envisioned for urban infrastructures, the complexity and sensitivity of their processing conditions remain challenging. Here, we introduce two robust protocols for the processing of sub-100 nm perovskite films, allowing fine-tuning of the active layer without compromising the crystallinity and quality of the semiconductor. Specifically, we demonstrate that a method based on solvent-induced crystallization with a rapid drying step affords perovskite solar cells with 37% average visible transmittance (AVT) and 7.8% PCE. This process enhances crystallization with a preferential phase orientation presumably at the interface, yielding a high fill factor of 72.3%. The second method is based on a solvent-solvent extraction protocol, enabling active layer films as thin as 40 nm and featuring room-temperature crystallization in an ambient environment on a few second time span. As a result, we demonstrate a maximum AVT of 46% with an efficiency of 3.6%, which is the highest combination of efficiency and transparency for a full device stack to date. By combining the two methods presented here we cover a broad range of thicknesses vs. transparency values and confirm that solvent-induced crystallization represents a powerful processing strategy toward high-efficiency semitransparent solar cells. Optical simulations support our experimental findings and provide a global perspective of the opportunities and limitations of semitransparent perovskite photovoltaic devices.

PV module power prediction by deep learning on electroluminescence images - Assessing the physics learned by a convolutional neural network - Lüer, Larry; Forberich, Karen; Hepp, Johannes; Buerhop-Lutz, Claudia; Winkler, Thilo; Rodrigues, Sandy; Hoffmann, Mathis; Doll, Bernd; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (Solar Energy Materials and Solar Cells, 2024)
Fast and reliable performance monitoring of photovoltaic modules is essential for economic forecasting in large-scale installations. Deep Learning methods, such as convolutional neural networks, have the potential to predict module power directly from electroluminescence images in an automated workflow. However, neural networks must be trained using large numbers of electroluminescence images of defective modules. Due to budgetary or technical limitations, these training images will always be biased, limiting generalization. Here, we demonstrate a transparent method to discriminate the information learned by a convolutional neural network into generally valid physics and bias. Learning of physics is assessed by providing an artificial, unbiased feature list, which is converted into synthetic electroluminescence images. Using these images, we compare the predictions of the neural network trained on the biased dataset to those of a physics-based equivalent. Bias is assessed by a closer look at the deviations between the predictions from the equivalent circuit model and the trained neural network. The assessment of physics knowledge incorporated by a Deep Learning method gives insight into how the method achieves its predictive capacity.
CRIS-Team Scopus Importer:2023-11-24

Qualitative analysis of bulk-heterojunction solar cells without device fabrication: An elegant and contactless method - Baran, Derya; Li, Ning; Breton, Anne-Catherine; Osvet, Andres; Ameri, Tayebeh; Leclerc, Mario; Brabec, Christoph (Journal of the American Chemical Society, 2014)
The enormous synthetic efforts on novel solar cell materials require a reliable and fast technique for the rapid screening of novel donor/acceptor combinations in order to quickly and reliably estimate their optimized parameters. Here, we report the applicability of such a versatile and fast evaluation technique for bulk heterojunction (BHJ) organic photovoltaics (OPV) by utilizing a steady-state photoluminescence (PL) method confirmed by electroluminescence (EL) measurements. A strong relation has been observed between the residual singlet emission and the charge transfer state emission in the blend. Using this relation, a figure of merit (FOM) is defined from photoluminescence and also electroluminescence measurements for qualitative analysis and shown to precisely anticipate the optimized blend parameters of bulk heterojunction films. Photoluminescence allows contactless evaluation of the photoactive layer and can be used to predict the optimized conditions for the best polymer-fullerene combination. Most interestingly, the contactless, PL-based FOM method has the potential to be integrated as a fast and reliable inline tool for quality control and material optimization. © 2014 American Chemical Society.
Keywords: Engineering controlled terms: ElectroluminescencePhotoluminescenceSolar cells Compendex keywords Bulk heterojunction (BHJ)Bulk-heterojunction solar cellsCharge transfer stateFigure of merit (FOM)Material optimizationOptimized conditionsOrganic photovoltaicsSolar cell materials Engineering main heading: Heterojunctions

Qualitative und quantitative Auswertung regelmäßig durchgeführter aIR-Inspektionen von PV-Anlagen mit typischem PID-Muster - Fecher, Frank W.; Buerhop-Lutz, Claudia; Pickel, Tobias; Hundhausen, Martin; Zetzmann, Cornelia; Camus, Christian; Hauch, Jens; Brabec, Christoph (32. Symposium Photovoltaische Solarenergie, 2017)
Potential induzierte Degradation (PID) von Photovoltaik (PV)-Anlagen wird immer öfter an PV-Anlagen diagnostiziert und kann den Ertrag innerhalb weniger Jahre nach der Installation drastisch reduzieren. Als Ursachen werden lange Modulstrings mit hoher Systemspannung von ca. 800 V oder mehr sowie Temperatur und Feuchte im Wechselspiel mit der Verkapselung genannt [1]. Neuste Untersuchungen gehen davon aus, dass grob geschätzt 19 % der PV-Anlagen in Deutschland PID-Probleme haben [2]. Da PID zu einer zeitlich fortscheitenden Verschlechterung der Anlagen führt, ist es wichtig, möglichst frühzeitig PID und dessen Schadensgrad festzustellen, um erfolgreich Gegenmaßnahmen zu ergreifen. Zur Verifikation von PID wird vielfach Elektrolumineszenz (EL) aber auch Infrarot (IR)-Thermographie herangezogen [3, 4]. Da IR-Inspektionen schnell, zuverlässig und kosteneffizient Hinweise auf PID in Solaranlagen ohne Betriebsunterbrechung geben, ist es unser Ziel, eine Methode zur schnellen Diagnose von PID vorzustellen, die gleichzeitig eine quantitative Bestimmung des Schädigungsgrads und regelmäßige Nachmessungen erlaubt. In diesem Artikel stellen wir typische PID-Muster anhand von Infrarotluftaufnahmen (aIR) vor. Die Auswertung dieser zeigte auch erste Zusammenhänge zum Leistungsverlust der PV-Anlage. Des Weiteren wurde das Fortschreiten der PID in den Anlagen regelmäßig sowie der Einsatz von PID-Regenerationsboxen untersucht.

Quality control of polymer solar modules by lock-in thermography - Hoppe, Harald; Bachmann, Jonas; Muhsin, Burhan; Druee, Karl-Heinz; Riedel, Ingo; Gobsch, Gerhard; Buerhop-Lutz, Claudia; Brabec, Christoph; Dyakonov, Vladimir (Journal of Applied Physics, 2010)
We have characterized lateral imperfections of photovoltaic modules based on solution processed polymer-fullerene semiconductor blends by means of lock-in thermography (LIT). The active layer of the solar cell modules is based on the heterogeneous organic semiconductor system poly(3-hexylthiophene):phenyl-C -butyric acid methyl ester and the power conversion efficiency of the modules reached nearly 2% under irradiation of an AM 1.5 solar simulator. Applying highly sensitive LIT allowed us to detect several kinds of laterally distributed defects originating from imperfections in the respective functional layers as well as in the quality of encapsulation. We show that LIT is a powerful method for the quality control of large area polymer solar cells and modules, enabling fast feedback for optimization of production parameters. © 2010 American Institute of Physics.

Quantifying the Absorption Onset in the Quantum Efficiency of Emerging Photovoltaic Devices - Almora, Osbel; Cabrera, Carlos I.; García Cerrillo, José; Kirchartz, Thomas; Rau, Uwe; Brabec, Christoph (Advanced Energy Materials, 2021)
The external quantum efficiency (EQE), also known as incident-photon-to-collected-electron spectra are typically used to access the energy dependent photocurrent losses for photovoltaic devices. The integral over the EQE spectrum results in the theoretical short-circuit current under a given incident illumination spectrum. Additionally, one can also estimate the photovoltaic bandgap energy (Eg) from the inflection point in the absorption threshold region. The latter has recently been implemented in the “Emerging PV reports,” where the highest power conversion efficiencies are listed for different application categories, as a function of Eg. Furthermore, the device performance is put into perspective thereby relating it to the corresponding theoretical limit in the Shockley–Queisser (SQ) model. Here, the evaluation of the EQE spectrum through the sigmoid function is discussed and proven to effectively report the Eg value and the sigmoid wavelength range λs, which quantifies the steepness of the absorption onset. It is also shown how EQE spectra with large λs indicate significant photovoltage losses and present the corresponding implications on the photocurrent SQ model. Similarly, the difference between the photovoltaic and optical bandgap is analyzed in terms of λs.
CRIS-Team Scopus Importer:2021-03-19
Keywords: bandgap energy; emerging photovoltaics; external quantum efficiency; solar cells

Quantifying the Energy Losses in CsPbI2Br Perovskite Solar Cells with an Open-Circuit Voltage of up to 1.45 v - Tian, Jingjing; Zhang, Kaicheng; Xie, Zhiqiang; Peng, Zijian; Zhang, Jiyun; Osvet, Andres; Lüer, Larry; Kirchartz, Thomas; Rau, Uwe; Li, Ning; Brabec, Christoph (ACS Energy Letters, 2022)
CsPbI2Br perovskite solar cells (PSCs) have attracted much interest because of their thermodynamic stability, relatively stable cubic perovskite phase, and their potential as a top cell for tandem applications. However, the open-circuit voltage (VOC) reported to date is in most cases well below the detailed balance (DB) limit for single-junction PSCs. Here, we demonstrate that adding lead acetate to the CsPbI2Br precursor allows us to substantially reduce losses due to nonradiative recombination. Corresponding champion devices reach a power conversion efficiency (-) of 16.7% and a highest VOC value of 1.45 V, which represents 90% of the DB limit for single-junction PSCs at a bandgap of 1.89 eV. In order to disentangle the nonradiative recombination loss mechanisms, we quantify the origin of energy losses by calculating the radiative limit of the open-circuit voltage (VOCrad) and the quasi-Fermi level splitting (QFLS) of perovskite films with and without other functional layers. We further analyze the strategies to reduce the residual losses in order to push the efficiency beyond the 90% theoretical limit.
CRIS-Team Scopus Importer:2022-11-18

Quantifying the extent of contact doping at the interface between high work function electrical contacts and poly(3-hexylthiophene) (P3HT) - Shallcross, R. Clayton; Stubhan, Tobias; Ratcliff, Erin L.; Kahn, Antoine; Brabec, Christoph; Armstrong, Neal R. (Journal of Physical Chemistry Letters, 2015)
We demonstrate new approaches to the characterization of oxidized regioregular poly(3-hexylthiophene-2,5-diyl) (P3HT) that results from electronic equilibration with device-relevant high work function electrical contacts using high-resolution X-ray (XPS) and ultraviolet (UPS) photoelectron spectroscopy (PES). Careful interpretation of photoemission signals from thiophene sulfur atoms in thin (ca. 20 nm or less) P3HT films provides the ability to uniquely elucidate the products of charge transfer between the polymer and the electrical contact, which is a result of Fermi-level equilibration between the two materials. By comparing high-resolution S 2p core-level spectra to electrochemically oxidized P3HT standards, the extent of the contact doping reaction is quantified, where one in every six thiophene units (ca. 20%) in the first monolayer is oxidized. Finally, angle-resolved XPS of both pure P3HT and its blends with phenyl-C61-butyric acid methyl ester (PCBM) confirms that oxidized P3HT species exist near contacts with work functions greater than ca. 4 eV, providing a means to characterize the interface and "bulk" region of the organic semiconductor in a single film.
Keywords: band bending; contact doping; electrochemistry; P3HT; photoelectron spectroscopy

Quantitative Analysis of Charge Dissociation by Selectively Characterizing Exciton Splitting Efficiencies in Single Component Materials - He, Yakun; Hanisch, Benedict; Osvet, Andres; Lüer, Larry; Aubele, Anna; Bäuerle, Peter; Li, Weiwei; Li, Ning; Brabec, Christoph (Israel Journal of Chemistry, 2021)
Exciton dissociation between donor and acceptor is the decisive process to determine the photovoltaic performance of organic solar cells (OSCs). The rather fast dynamics of photo-induced charge generation in well-optimized bulk heterojunction (BHJ) composites complicate the quantitative analysis of the charge generation efficiency for donor and acceptor units. Herein, we report time-resolved photoluminescence (TRPL) investigations and demonstrate their potential as a quantitative and contactless characterization technique allowing to separately determine the exciton splitting efficiency of donor and acceptor moieties in selected single component materials. We demonstrate that the exciton splitting efficiency for donor or acceptor moieties can be separately adjusted in these materials by post-treatment, while the corresponding BHJ composites undergo excessive phase separation upon external stress. By relating the separate exciton splitting efficiencies to their photovoltaic performance, the limiting factor in corresponding OSCs, either charge generation or recombination, is identified.
CRIS-Team Scopus Importer:2021-10-22
Keywords: charge dissociation; charge transfer; exciton splitting efficiency; organic solar cells; single component materials; transient photoluminescence

Quantitative Analysis of the Separate Influences of Material Composition and Local Defects on the Voc of PV Devices: An Exemplary Study on CIGS - Hepp, Johannes; Vetter, Andreas; Hofbeck, Bernhard; Sultan, Umair; Hauch, Jens; Camus, Christian; Brabec, Christoph (IEEE Journal of Photovoltaics, 2020)
A lot of effort is required in order to close the efficiency gap between laboratory record Cu(In,Ga)Se 2 (CIGS) solar cells and commercially produced modules. An obstacle easily overlooked is the fact that reduced module performance may have multiple root causes. Here, we show how to isolate two main factors that influence the open circuit voltage (Voc) of photovoltaic devices, the material composition and the local defects, here shunts in particular, i.e., regions of significantly lowered resistivity. In order to characterize the material composition, we used electroluminescence spectroscopy. Additionally, we investigated the effect of local defects on the Voc, by the use of thermography. Which of both factors dominates the resulting Voc depends on the insolation intensity under which the device is operated. We established a model in order to estimate the Voc as a function of the luminescence peak wavelength, the quantification of the thermal hot spots caused by local defects, and the insolation intensity. Subsequently, we investigated how these factors affect the electrical conversion efficiency of the device. The combination of these two measurement techniques results in a more conclusive evaluation of the electrical parameters, thereby enabling an improved quality assessment to allow a successive process optimization. This approach is also applicable to other thin film PV technologies such as perovskite and organic solar cells.<br
Keywords: Cu(In; Ga)Se2 (CIGS); infrared (IR) imaging; luminescence; photovoltaic cells; quality management

Quantitative Assessment of the Influence of Camera and Parameter Choice for Outdoor Electroluminescence Investigations of Silicon Photovoltaic Panels - Doll, Bernd; Del Rivero, E. Calderón; Hepp, Johannes; Pickel, Tobias; Buerhop, Claudia; Knecht, R.; Camus, C.; Hauch, Jens; Parisi, J.; Brabec, Christoph (Zeitschrift für Naturforschung Section A - A Journal of Physical Sciences, 2019)
With the spread of photovoltaics (PV) and increasing diversity in PV panel technology, quantitative comparison of the modules is highly desirable for consistent on-site quality assessment. Electroluminescence imaging reveals many defects, such as macroscopic crystal or electrical contact defects, but quantitative comparison outside the laboratory without controlled environment is still difficult, especially for different detector technologies. Here, we show how this problem can be addressed by adding reference spots in the module area: One passive dark spot and an active bright spot composed of a high-power back-contacted silicon PV cell. Those reference spots are used to evaluate the module's electroluminescence signal under different environmental conditions and to establish comparable results. Additionally, the comparison of images acquired with different camera technology detectors, such as silicon and InGaAs, is realised for signal levels.
CRIS-Team Scopus Importer:2019-07-12
Keywords: Defect Detection; Electroluminescence; Outdoor; Photovoltaic; Quantitative Comparison

Quantitative assessment of the power loss of silicon PV modules by IR thermography and its dependence on data-filtering criteria - Teubner, Janine; Buerhop, Claudia; Pickel, Tobias; Hauch, Jens; Camus, Christian; Brabec, Christoph (Progress in Photovoltaics, 2019)
Reliability and quality control of photovoltaic (PV) plants increases in importance as the relevance of PV for the worldwide renewable energy production grows. In this study, a new method is presented which allows for a quantitative assessment of silicon PV module performance solely by relying on the cell temperatures measured via thermography (IR). A module temperature and power key figure are formulated and found to correlate very well with a linear relationship. The dependence of the deduced correlation's precision on measurement conditions is calculated and discussed. It facilitates decision-making because optimal measurement conditions usually occur only very rarely, such that a compromise between data quality and measurement frequency has to be found. The power loss correlation presented in this paper may be used as part of a maintenance routine in order to ensure the best possible long-term performance of the PV plant over its lifetime. The practical application in the field is outlined and explained.
CRIS-Team Scopus Importer:2019-08-23
Keywords: empirical power correlation; infrared measurement; PV; silicon modules; UAV

Quantitative imaging of shunts in organic photovoltaic modules using lock-in thermography - Besold, S.; Hoyer, U.; Bachmann, J.; Swonke, Th.; Schilinsky, P.; Steim, R.; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2014)
Thermographic methods are widely established to detect shunts in photovoltaic technologies. In all methods the cell has to be directly accessible to determine quantitative shunt values. In this manuscript a precise method is presented to determine shunt values in solar modules consisting of series connected bulk-heterojunction organic solar cells without the need to access the single cells separately. It will be shown that, although parallel resistances in organic solar cells show a strong dependence on the illumination intensity, the shunts that are detected using illuminated lock-in-thermography are strongly ohmic and therefore can be assigned a distinct ohm value. (c) 2014 Elsevier B.V. All rights reserved.
Keywords: Organic photovoltaics; Thermography; Simulation; Defect imaging; Parallel resistance

Quantitative Study of Potential Induced Degradation of a Roof-Top PV-Installation with IR-Imaging - Buerhop-Lutz, Claudia; Pickel, Tobias; Fecher, Frank W.; Zetzmann, Cornelia; Hauch, Jens; Camus, Christian; Brabec, Christoph (33rd European Photovoltaic Solar Energy Conference and Exhibition, 2017)
Potential induced degradation (PID) causes severe damage and financial losses even in modern PVinstallations. In Germany, approximately 19% of PV-installations suffer from PID and resulting power loss. This paper focuses on the impact of PID in real installations. The analysis focuses exemplarily on a 314 kWp PV-system in the Atlantic coastal climate. Infrared (IR)-imaging is used for identifying PID without operation interruption. Historic electric performance monitoring data for several years are analyzed on system and string level. Additionally, punctually measured module string current-voltage (I-V)-curves are considered. The data sets are combined for understanding the PID behavior of this PV plant. The number of PID affected cells within a string varies strongly between 1 to 22% with the string position on the building complex. A PID-resistance which correlates to the defined PID-defect-ration is presented. Finally, indicators for the reliable determination of PID is given.
Keywords: potential induced degradation (PID); IR-imaging; PID criteria; power loss; PID-resistance

Rare-Earth Ion-Based Photon Up-Conversion for Transmission-Loss Reduction in Solar Cells - Wang, Hai-Qiao; Osvet, Andres; Batentschuk, Miroslaw; Brabec, Christoph (Rare-Earth Ion-Based Photon Up-Conversion for Transmission-Loss Reduction in Solar Cells, 2021)
Photon up-conversion (UC) describes an anti-Stokes emission process, in which a luminophor emits one higher energy photon after being excited by multiple low-energy photons, among which rare-earth (RE) ion-doped materials present promising UC properties due to unique electron configuration. RE UC materials have been widely studied in solar cells with the purpose to reduce transmission losses, i.e., achieve wide/full solar spectral harvesting and high-power conversion efficiency, by converting unutilized sub-bandgap photons into sensitive resonant photons. This chapter exclusively focuses on RE-doped UC materials and their applications in solar cells. The RE-based UC photophysics, UC enhancement, and applications in solar cells will be reviewed and briefly discussed.<br

Rare-earth ion doped up-conversion materials for photovoltaic applications - Wang, Hao; Batentschuk, Miroslaw; Osvet, Andres; Pinna, Luigi; Brabec, Christoph (Advanced Materials, 2011)
With the aim of utilizing the infrared region of solar radiation to improve solar cell performance, significant progress, including theoretical analysis and experimental achievement, has been made in the field of up-conversion for photovoltaic applications. This Research News article reviews recent progress in the development of rear-earth (RE) ion doped up-conversion materials for solar cell applications. In addition, new trends for RE-ion-doped phosphors are briefly discussed, among them trivalent RE-ion-doped up-conversion materials for organic solar cell applications. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: nonlinear optical materials; phosphors; photovoltaic devices; rare earth ions

Rational Design of High-Performance Wide-Bandgap (≈2 eV) Polymer Semiconductors as Electron Donors in Organic Photovoltaics Exhibiting High Open Circuit Voltages (≈1 V) - Chochos, Christos L.; Katsouras, Athanasios; Gasparini, Nicola; Koulogiannis, Chrysanthos; Ameri, Tayebeh; Brabec, Christoph; Avgeropoulos, Apostolos (Macromolecular Rapid Communications, 2016)
Systematic optimization of the chemical structure of wide-bandgap (≈2.0 eV) "donor-acceptor" copolymers consisting of indacenodithiophene or indacenodithieno[3,2-b]thiophene as the electron-rich unit and thieno[3,4-c]pyrrole-4,6-dione as the electron-deficient moiety in terms of alkyl side chain engineering and distance of the electron-rich and electron-deficient monomers within the repeat unit of the polymer chain results in high-performance electron donor materials for organic photovoltaics. Specifically, preliminary results demonstrate extremely high open circuit voltages (V s) of ≈1.0 V, reasonable short circuit current density (J ) of around 11 mA cm, and moderate fill factors resulting in efficiencies close to 6%. All the devices are fabricated in an inverted architecture with the photoactive layer processed by doctor blade equipment, showing the compatibility with roll-to-roll large-scale manufacturing processes. From the correlation of the chemical structure-optoelectronic properties-photovoltaic performance, a rational guide toward further optimization of the chemical structure in this family of copolymers, has been achieved.
Keywords: High open circuit voltage; Indacenodithiophene; Organic photovoltaics; Ternary solar cells; Wide-bandgap conjugated polymers

Rationale for highly efficient and outdoor-stable terpolymer solar cells - Tang, Hua; Liao, Zhihui; Karuthedath, Safakath; Chen, Si; Liu, Heng; Khan, Jafar I. I.; Babics, Maxime; Yang, Wenchao; Alqurashi, Maryam; He, Yakun; Gorenflot, Julien; Huang, Jiaming; et al. (Energy and Environmental Science, 2023)
Random terpolymerization is an effective approach to achieving highly efficient and outdoor-stable terpolymer photovoltaics. However, the working principle behind this remains unclear. Herein, we report spectroscopic, morphological, and computational results and conclude the previous work on terpolymer research to unveil their structure-property relations and elucidate key rules for high-efficiency and outdoor-stable terpolymer photovoltaics. More specifically, introducing a strong electron-deficient or electron-rich third moiety is suggested to enable broadened absorption with minimized non-radiative voltage losses. Besides, the third component should manipulate the D/A miscibility towards a thermodynamically more stable morphology. However, the content of the third component should be small to maintain molecular orientation and exciton diffusion length in conjunction with optimized phase-separation and crystallinity, in turn reducing bimolecular carrier recombination. Obeying these rules, terpolymer solar cells based on the parent donors D18 and PM6 with enhanced power conversion efficiency (PCE) and excellent outdoor stability are demonstrated. Our findings provide a rationale for explaining and achieving high-performance and outdoor-stable terpolymer photovoltaics, paving the path to commercialization.
CRIS-Team WoS Importer:2023-04-07

Rational Interface Design and Morphology Control for Blade-Coating Efficient Flexible Perovskite Solar Cells with a Record Fill Factor of 81% - Wang, Zhen; Zeng, Linxiang; Zhang, Cuiling; Lu, Yuanlin; Qiu, Shudi; Wang, Chuan; Liu, Chong; Pan, Lijun; Wu, Shaohang; Hu, Jinlong; Liang, Guangxing; Fan, Ping; et al. (Advanced Functional Materials, 2020)
Halide perovskites are one of the ideal photovoltaic materials for constructing flexible solar devices due to relatively high efficiencies for low-temperature solution-processed devices. However, the overwhelming majority of flexible perovskite solar cells are produced using spin coating, which represents a major hurdle for upscaling. Here, a scalable approach is reported to fabricate efficient and robust flexible perovskite solar cells on a polymer substrate. Thiourea is introduced into perovskite precursor solution to modulate the crystal growth, resulting in dense and uniform perovskite thin films on rough surfaces. As a decisive step, a cascade energy alignment is realized for the hole extraction layer by rationally designing a bilayer interface comprised of PEDOT:PSS/PTAA with a distinct offset in the highest occupied molecular orbital levels, enabling markedly enhanced charge extraction and spectral response. An efficiency as high as 19.41% and a record fill factor up to 81% are achieved for flexible perovskite devices processed by a scalable printing method. Equally important, the bilayer interface reinforces the bendability of the indium tin oxide substrate, leading to enhanced mechanical robustness of the flexible devices. These results underpin the importance of morphology control and interface design in constructing high-performance flexible perovskite solar cells.
CRIS-Team Scopus Importer:2020-07-10
Keywords: bilayer interface; blade coating; cascade energy alignment; flexible solar cells; perovskite

Real-time evaluation of thin film drying kinetics using an advanced, multi-probe optical setup - Güldal, Nusret Sena; Kassar, Thaer; Berlinghof, Marvin; Ameri, Tayebeh; Osvet, Andres; Pacios, Roberto; Li Destri, Giovanni; Unruh, Tobias; Brabec, Christoph (Journal of Materials Chemistry C, 2016)
Solution-processed organic photovoltaic devices are advantageous due to their low-cost large area manufacturing techniques, such as slot-die coating, gravure printing and roll-to-roll coating. The final microstructure of a polymer:fullerene bulk-heterojunction (BHJ) film is a fine interplay between solution thermodynamics (e.g. solubility, miscibility...) and kinetics (e.g. solvent evaporation, polymer ordering, phase separation...) during the drying process. In order to design better performing organic photovoltaic devices, gaining knowledge over the drying properties of polymer:fullerene thin films is essential. A novel in situ thin film drying characterization chamber, equipped with white-light reflectometry, laser light scattering and photoluminescence, is presented in combination with grazing-incidence X-ray diffraction on two different polymer:fullerene bulk heterojunctions based on poly-(3-hexylthiophene-2,5-diyl) (P3HT) and polythieno[3,2b]thiophene-diketopyrrolopyrrole-co-thiophene (DPP-TT-T) polymers. With photoluminescence applied for the first time as an in situ method for such drying studies, these single-chamber measurements track the fine interplay between thermodynamics and kinetics of thin film drying and provide invaluable information on solution behavior and microstructure formation.
Keywords: Engineering controlled terms: Coatings; Drying; Fullerenes; Heterojunctions; Kinetics; Light scattering; Microstructure; Phase separation; Photoluminescence; Plastic coatings; Polymer films; Polymers; Rolls (machine components); Solubility; Thermodynamics; Thiophene; X ray diffraction Bulk heterojunction (BHJ); Grazing incidence X-ray diffraction; Manufacturing techniques; Microstructure formation; Organic photovoltaic devices; Poly(3-hexylthiophene-2; 5-diyl); Solution thermodynamics; Thermodynamics and kinetics Engineering main heading: Thin films

Real-time in-situ observation of morphological changes in organic bulk-heterojunction solar cells by means of capacitance measurements - Lungenschmied, Christoph; Bauer, Siegfried; Schwoediauer, Reinhard; Rodman, Sheila; Fournier, Darcy; Dennler, Gilles; Brabec, Christoph (Journal of Applied Physics, 2011)
We present a method to directly study temperature induced structural and morphological changes in the active layer of organic solar cells by capacitance determination. At sufficiently high frequencies the change in device capacitance with temperature is dominated by the expansion of the organic layer. Variations in the expansion coefficient or the permittivity are visible in the capacitive response. We have studied thin film devices based on poly(3- hexyl)thiophene (P3HT) as well as organic solar cells made from blends of P3HT with a fullerene derivative. Temperature induced transitions are correlated to structural changes in the polymer (e.g., glass transition) as well as morphological changes of the blend; the morphology transition driven by phase separation sets in around 120 C. The advantage of our capacitance method is substantiated as we have demonstrated that confinement due to the substrate and the top electrode alters the effect of temperature on thin films as compared to the bulk material. © 2011 American Institute of Physics.
Keywords: Active Layer; Bulk materials; Capacitance method; Capacitive response; Device capacitance; Effect of temperature; Expansion coefficients; Fullerene derivative; High frequency; In-situ observations; Morphological changes; Morphology transitions; Organic bulk-heterojunction solar cells; Organic layers; Organic solar cell; Structural change; Temperature-induced Engineering controlled terms: Capacitance; Capacitance measurement; Glass transition; Heterojunctions; Morphology; Phase separation; Polymer films; Thin film devices; Thin films; Thiophene Engineering main heading: Solar cells

Real-Time Investigation of Intercalation and Structure Evolution in Printed Polymer:Fullerene Bulk Heterojunction Thin Films - Kassar, Thaer; Güldal, Nusret Sena; Berlinghof, Marvin; Ameri, Tayebeh; Kratzer, Andreas; Schroeder, Bob C.; Li Destri, Giovanni; Hirsch, Andreas; Heeney, Martin; Mcculloch, Iain; Brabec, Christoph; Unruh, Tobias (Advanced Energy Materials, 2016)
The complex intermixing morphology is critical for the performance of the nanostructured polymer:fullerene bulk heterojunction (BHJ) solar cells. Here, time resolved in situ grazing incidence X-ray diffraction and grazing incidence small angle X-ray scattering are used to track the structure formation of BHJ thin films formed from the donor polymer poly(2,5-bis(3-hexadecylthiophen-2-yl)thieno[3,2-b]thiophene) with different fullerene derivative acceptors. The formation of stable bimolecular crystals through the intercalation of fullerene molecules between the side chains of polymer crystallites is investigated. Such systems exhibit more efficient exciton dissociation but lower photo-conductance and faster decay of charges. On the basis of the experimental observations, intercalation obviously takes place before or with the formation of the crystalline polymer domains. It results in more stable structures whose volume remains constant upon further drying. Three distinct periods of drying are observed and the formation of unidimensional fullerene channels along the π-stacking direction of polymer crystallites is confirmed.
Keywords: fullerenes; grazing incidence diffraction; intercalation dynamics; organic solar cells; thin films

Real-Time Study on Structure Formation and the Intercalation Process of Polymer: Fullerene Bulk Heterojunction Thin Films - Kassar, Thaer; Berlinghof, Marvin; Güldal, Nusret Sena; Schmutzler, Tilo; Zontone, Federico; Brandl, Marco; Metwalli, Ezzeldin; Will, Johannes; Li, Ning; Ameri, Tayebeh; Brabec, Christoph; Unruh, Tobias (Solar RRL, 2020)
Fullerene intercalation between the side chains of conjugated polymers has a detrimental impact on both charge separation and charge transport processes in bulk heterojunction (BHJ) organic photovoltaic cells (OPVs). In situ grazing incidence X-ray scattering experiments allow to characterize the structure formation, drying kinetics, and intercalation in blends of phenyl-c61-butyric acid methyl ester (PC60BM) and poly(2,5-bis(3-tetradecylthiophen-2-yl)thieno[3,2-b]thiophene) named (pBTTT-C14) from their 1,2-orthodichlorobenzene (oDCB) solutions with different volume fractions of dodecanoic acid methyl ester (Me12) as a solvent additive. The structure formation process during evaporation of the solvent:additive mixture can be described by five periods, which are correlated to a multistep contraction of the lamellar stacking of the bimolecular crystals. The onset of crystallization is delayed by increasing the additive volume fraction in the coating solution leading to a promoted crystallinity. A conclusive picture of fullerene intercalation and additive-tuned structural evolution during the drying of thin films of the polymer:fullerene BHJ blends will be presented.
CRIS-Team WoS Importer:2020-02-04

Recent advances in semi-transparent polymer and perovskite solar cells for power generating window applications - Xue, Qifan; Xia, Ruoxi; Brabec, Christoph; Yip, Hin-Lap (Energy and Environmental Science, 2018)
Semi-transparent photovoltaic (ST-PV) technologies can be applied to replace facades and roofs in conventional buildings and coatings on vehicles to produce energy from sunlight. Current ST-PV technology is Si-based, but although Si achieves adequate efficiencies, it compromises on aesthetic appeal; its color is intrinsically difficult to tune. However, this presents an opportunity for semi-transparent polymer and perovskite-based PVs, the optical properties of which can be modulated easily by tuning their material compositions. In this review article, we summarize recent progress made in the material selection, optical engineering and device architecture design for high-performance, semi-transparent polymer and perovskite solar cells and discuss challenges for the commercialization of these semi-transparent solar cells for power-generating applications in windows.
Keywords: Cell engineering; Optical properties; Perovskite; Perovskite solar cells; Photovoltaic cells; Polymer solar cells; Polymers; Silicon solar cells

Recent progress in thick‐film organic photovoltaic devices: Materials, devices, and processing - Zhang, Difei; Fan, Baobing; Ying, Lei; Li, Ning; Brabec, Christoph; Huang, Fei; Cao, Yonghai (SusMat, 2021)
A successful transfer of organic photovoltaic technologies from lab to fab has to overcome a range of critical challenges such as developing high-mobility light-harvesting materials, minimizing the upscaling losses, designing advanced solar modules, controlling film quality, decreasing overall cost, and extending long-operation lifetime. To realize large-area devices toward practical applications, much effort has been devoted to understanding the fundamental mechanism of how molecular structures, device architectures, interfacial engineering, and light management and carrier dynamics affect photovoltaic performance. Such studies addressed various fundamental issues of charge carrier behavior in organic heterojunctions primarily in terms of exciton generation dependence upon light incidence, charge transportation dependence on built-in electric field, and charge extraction versus recombination. In consideration of high-throughput roll-to-roll process for large-scale fabrication of organic photovoltaic devices, it is highly appreciable to realize high power conversion efficiencies that are highly tolerable to the film thickness. Herein we summarize the recent progress in developing thick-film organic photovoltaic devices from the perspective of efficiency-loss mechanisms, material design, and device optimization strategies, proposing guidelines for designing high-efficiency thickness-insensitive devices toward mass production.

Recombination dynamics as a key determinant of open circuit voltage in organic bulk heterojunction solar cells: A comparison of four different donor polymers - Maurano, Andrea; Hamilton, Rick; Shuttle, Chris G.; Ballantyne, Amy M.; Nelson, Jenny; O'Regan, Brian; Zhang, Weimin; Mcculloch, Iain; Azimi, Hamed; Morana, Mauro; Brabec, Christoph; Durrant, James R. (Advanced Materials, 2010)
Transient photovoltage and charge extraction analyses are employed to analyzes charge carrier densities and bimolecular recombination dynamics in organic polymer: fullerene solar cells under open circuit operating conditions, employing four different donor polymers. An equation is derived which allows us to calculate the device V from these kinetic measurements. This equation allows us to calculate voltage output of devices within ± 25 meV of directly measured values. This analysis thus allows us to relate device open circuit voltage directly to the kinetics of bimolecular recombination, and thereby the influence of nanomorphology upon device voltage output. Copyright © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: bimolecular recombination; charge dynamics; open circuit voltage; organic solar cell; power conversion efficiency

Recrystallized thin-film silicon solar cell on graphite substrate with laser single side contact and hydrogen passivation - Li, Da; Wittmann, Stephan; Kunz, Thomas; Ahmad, Taimoor; Gawehns, Nidia; Hessmann, Maik T.; Ebser, Jan; Terheiden, Barbara; Auer, Richard; Brabec, Christoph J. (EPJ Photovoltaics, 2015)
Laser single side contact formation (LSSC) and the hydrogen passivation process are studied and developed for crystalline silicon thin film (CSiTF) solar cells on graphite substrates. The results demonstrate that these two methods can improve cell performance by increasing the open circuit voltage and fill factor. In comparison with our previous work, we have achieved an increase of 3.4% absolute cell efficiency for a 40 μm thick 4 cm 2 aperture area silicon thin film solar cell on graphite substrate. Current density-voltage (J-V) measurement, quantum efficiency (QE) and light beam induced current (LBiC) are used as characterization methods.
CRIS-Team Scopus Importer:2023-03-07

Red-emitting Ca 1-xSr xS:Eu 2+ phosphors as light converters for plant-growth applications - Xia, Qi; Batentschuk, Miroslaw; Osvet, Andres; Richter, Peter; Häder, Donat-Peter; Schneider, Jürgen; Wondraczek, Lothar; Winnacker, Albrecht; Brabec, Christoph (2011 MRS Spring Meeting, 2012)
A series of Ca Sr S:Eu phosphors were synthesized with solid state reactions and with various Ca/Sr ratio and Eu doping concentrations. The influences of the lattice composition and the Eu doping level on photoluminescent properties were analyzed. With doping concentrations between 0.1 to 3 mol%, concentration quenching takes place leading to the decrease of luminance; the emission maxima are also red-shifted. Further, this work reports enhanced photosynthetic activities of intact spinach leaves due to spectral modification of simulated solar irradiation by one synthesized phosphor (Ca Sr S:Eu ). The CO assimilation rates of intact spinach leaves were monitored with an effective homemade photosynthesis measurement system with controlled light conditions. The phosphor could efficiently convert the photosynthetically less active green part of the solar spectrum into the red, with a broad-band red emission centered at 650 nm and a halfband-width of 68 nm, giving an excellent match with the absorption spectrum of spinach chloroplasts. By careful referencing the photon flux, we found an enhanced photosynthetic activities by about 30% due to the emission of the phosphor. © 2011 Materials Research Society.
Keywords: Assimilation rate; Broad bands; Concentration quenching; Doping concentration; Doping levels; Emission maxima; Light conditions; Measurement system; Photo-luminescent properties; Photon flux; Photosynthetic activity; Red emissions; Red-shifted; Solar irradiation; Solar spectrum; Spectral modifications; Spinach leaves Engineering controlled terms: Calcium; Carbon dioxide; Light emission; Phosphors; Solar radiation; Solid state reactions Engineering main heading: Europium

Reduced voltage losses yield 10% efficient fullerene free organic solar cells with >1 V open circuit voltages - Baran, D.; Kirchartz, T.; Wheeler, S.; Dimitrov, S.; Abdelsamie, M.; Gorman, J.; Ashraf, R. S.; Holliday, S.; Wadsworth, A.; Gasparini, Nicola; Kaienburg, P.; Yan, H.; et al. (Energy and Environmental Science, 2016)
Optimization of the energy levels at the donor-acceptor interface of organic solar cells has driven their efficiencies to above 10%. However, further improvements towards efficiencies comparable with inorganic solar cells remain challenging because of high recombination losses, which empirically limit the open-circuit voltage (V) to typically less than 1 V. Here we show that this empirical limit can be overcome using non-fullerene acceptors blended with the low band gap polymer PffBT4T-2DT leading to efficiencies approaching 10% (9.95%). We achieve V up to 1.12 V, which corresponds to a loss of only E/q - V = 0.5 ± 0.01 V between the optical bandgap E of the polymer and V. This high V is shown to be associated with the achievement of remarkably low non-geminate and non-radiative recombination losses in these devices. Suppression of non-radiative recombination implies high external electroluminescence quantum efficiencies which are orders of magnitude higher than those of equivalent devices employing fullerene acceptors. Using the balance between reduced recombination losses and good photocurrent generation efficiencies achieved experimentally as a baseline for simulations of the efficiency potential of organic solar cells, we estimate that efficiencies of up to 20% are achievable if band gaps and fill factors are further optimized.
Keywords: Engineering controlled terms: Energy gap; Fullerenes; Open circuit voltage; Organic solar cells; Polymer solar cells; Timing circuits Donor-acceptor interfaces; Fullerene free; Inorganic solar cells; Low bandgap polymers; Non-radiative recombinations; Orders of magnitude; Photocurrent generations; Recombination loss Engineering main heading: Solar cells

Reducing burn-in voltage loss in polymer solar cells by increasing the polymer crystallinity - Heumueller, Thomas; Mateker, William R.; Sachs-Quintana, I. T.; Vandewal, Koen; Bartelt, Jonathan A.; Burke, Timothy M.; Ameri, Tayebeh; Brabec, Christoph; Mcgehee, Michael D. (Energy and Environmental Science, 2014)
In order to commercialize polymer solar cells, the fast initial performance losses present in many high efficiency materials will have to be managed. This burn-in degradation is caused by light-induced traps and its characteristics depend on which polymer is used. We show that the light-induced traps are in the bulk of the active layer and we find a direct correlation between their presence and the open-circuit voltage loss in devices made with amorphous polymers. Solar cells made with crystalline polymers do not show characteristic open circuit voltage losses, even though light-induced traps are also present in these devices. This indicates that crystalline materials are more resistant against the influence of traps on device performance. Recent work on crystalline materials has shown there is an energetic driving force for charge carriers to leave amorphous, mixed regions of bulk heterojunctions, and charges are dominantly transported in pure, ordered phases. This energetic landscape allows efficient charge generation as well as extraction and also may benefit the stability against light-induced traps. This journal is © the Partner Organisations 2014.
Keywords: Engineering controlled terms: Crystalline materials; Heterojunctions; Open circuit voltage; Solar cells Amorphous polymers; Bulk heterojunction; Charge generation; Crystalline polymers; Device performance; Open circuit voltage loss; Polymer crystallinity; Polymer Solar Cells Engineering main heading: Polymers GEOBASE Subject Index: crystallinity; energy efficiency; photovoltaic system; polymer; solar power

Reducing energy barrier of δ-to-α phase transition for printed formamidinium lead iodide photovoltaic devices - Xu, Zhenhua; Zeng, Linxiang; Hu, Jinlong; Wang, Zhen; Zhang, Putao; Brabec, Christoph; Forberich, Karen; Mai, Yaohua; Guo, Fei (Nano Energy, 2022)
Recent progress in perovskite photovoltaics has witnessed a growing interest in formamidinium lead iodide (FAPbI3), primarily due to its high efficiency potential and excellent stability. However, the high energy barrier of δ-to-α phase transition presents a major hurdle to fabricate phase-pure α-FAPbI3 layers. Here, we report a two-step phase transition process to deposit high-quality photovoltaic α-FAPbI3 films by printing method. This is realized by judicious selection of a Lewis base N-methyl-2-pyrrolidone (NMP) and its counter Lewis acid, which enables the regulation of intermediary phase to reduce the energy barrier. With fine tuning the phase transition pathway, phase-pure and stable α-FAPbI3 perovskite films are obtained, which yield solar devices with a champion efficiency of 21.35%. The printed mini-modules with active areas of 12.32 cm2 and 55.44 cm2 are also fabricated, giving efficiencies of 17.07% and 14.17%, respectively. This work provides new insights of α-FAPbI3 crystallization for constructing efficient and stable printed photovoltaic devices.
CRIS-Team Scopus Importer:2021-11-12
Keywords: Energy barrier tuning; Mini-modules; Printed α-FAPbI; Two-step crystallization

Reducing Open-Circuit Voltage Losses in All-Inorganic Perovskite Cells by Dedoping - Peng, Zijian; Tian, Jingjing; Zhang, Kaicheng; These, Albert; Xie, Zhiqiang; Zhao, Yicheng; Osvet, Andres; Guo, Fei; Lüer, Larry; Li, Ning; Brabec, Christoph (ACS Energy Letters, 2023)
CsPbI2Br is an attractive photovoltaic material due to its promising optoelectronic properties. However, the corresponding perovskite solar cells (PSCs) with p-i-n configuration suffer from low open-circuit voltage (VOC) and fill factor (FF), limiting their application in tandem solar cells. Here, we propose using the fullerene ICBA as the electron charge transporting layer (ETL), forming a better interfacial contact and enhancing the internal quasi-Fermi level splitting (QFLS). A further reduction of VOC losses of around 0.1 V was achieved by an ultrathin phenethylammonium chloride (PEACl) layer between the perovskite and the ETL. We precisely study the VOC improvement and find that passivation of surface recombination contributes only 20 mV, while more importantly, a major increase of 80 mV is achieved by dedoping the perovskite surface, which removes a non-negligible electron extraction barrier. Our results give helpful direction regarding how to further improve VOC in p-i-n perovskite cells.
CRIS-Team Scopus Importer:2023-04-21

Reducing the efficiency–stability–cost gap of organic photovoltaics with highly efficient and stable small molecule acceptor ternary solar cells - Baran, Derya; Ashraf, Raja Shahid; Hanifi, David A.; Abdelsamie, Maged; Gasparini, Nicola; Röhr, Jason A.; Holliday, Sarah; Wadsworth, Andrew; Lockett, Sarah; Neophytou, Marios; Emmott, Christopher J M; Nelson, Jenny; et al. (Nature Materials, 2016)
Technological deployment of organic photovoltaic modules requires improvements in device light-conversion efficiency and stability while keeping material costs low. Here we demonstrate highly efficient and stable solar cells using a ternary approach, wherein two non-fullerene acceptors are combined with both a scalable and affordable donor polymer, poly(3-hexylthiophene) (P3HT), and a high-efficiency, low-bandgap polymer in a single-layer bulk-heterojunction device. The addition of a strongly absorbing small molecule acceptor into a P3HT-based non-fullerene blend increases the device efficiency up to 7.7 ± 0.1% without any solvent additives. The improvement is assigned to changes in microstructure that reduce charge recombination and increase the photovoltage, and to improved light harvesting across the visible region. The stability of P3HT-based devices in ambient conditions is also significantly improved relative to polymer:fullerene devices. Combined with a low-bandgap donor polymer (PBDTTT-EFT, also known as PCE10), the two mixed acceptors also lead to solar cells with 11.0 ± 0.4% efficiency and a high open-circuit voltage of 1.03 ± 0.01 V.
Keywords: Engineering controlled terms: Efficiency; Energy gap; Fullerenes; Heterojunctions; Molecules; Open circuit voltage; Photovoltaic cells; Polymer solar cells; Polymers; Solar power generation Ambient conditions; Bulk-heterojunction devices; Charge recombinations; Device efficiency; Low bandgap polymers; Organic photovoltaics; Poly-3-hexylthiophene; Solvent additives Engineering main heading: Solar cells

Reducing Voltage Losses in Organic Photovoltaics Requires Interfacial Disorder Management - Wang, Rong; Han, Leng; Li, Ning; Chochos, Christos L.; Gregoriou, Vasilis G.; Lüer, Larry; Brabec, Christoph (Advanced Energy Materials, 2024)
Thanks to the introduction of non-fullerene acceptors, efficiencies of organic photovoltaics are now approaching 20%. Closing the gap with inorganic photovoltaics requires minimizing voltage losses without penalizing charge extraction, for which microstructure control is crucial. However, the complex interplay between microstructure and charge generation, recombination, and extraction has so far not been unraveled. Here, a systematic study linking device performance to distinct microstructural features via machine learning is presented. Building bi-layer devices allows to separately study the influence of aggregation and disorder on the energies and lifetimes of bulk and interfacial states. Unambiguous assignments of specific structural motifs to the device photophysics are thus possible. It is found that the control of aggregation-caused quenching is decisive for the exciton splitting efficiency and thus the carrier generation. Furthermore, the static disorder at the donor–acceptor interface controls the nonradiative recombination by shifting the excited state population from the bulk toward the interface. Finally, the amount of disorder in the bulk is found decisive for charge extraction. The finding that charge generation, recombination, and extraction are controlled by distinct structural features, is the key to optimizing these motifs independently, which will pave the way for organic photovoltaics toward the detailed balance limit.
CRIS-Team Scopus Importer:2024-05-03
Keywords: interfacial energy states; machine learning; microstructure; organic solar cells; voltage loss

Relation of Nanostructure and Recombination Dynamics in a Low-Temperature Solution-Processed CuInS2 Nanocrystalline Solar Cell - Azimi, Seyed Hamed; Heumüller, Thomas; Gerl, Andreas; Matt, Gebhard; Kubis, Peter; Distaso, Monica; Ahmad, Rameez; Akdas, Tugce; Richter, Moses; Peukert, Wolfgang; Brabec, Christoph (Advanced Energy Materials, 2013)
The understanding and control of nanostructures with regard to transport and recombination mechanisms is of key importance in the optimization of the power conversion efficiency (PCE) of solar cells based on inorganic nanocrystals. Here, the transport properties of solution-processed solar cells are investigated using photo-CELIV (photogenerated charge carrier extraction by linearly increasing voltage) and transient photovoltage techniques; the solar cells are prepared by an in-situ formation of CuInS2 nanocrystals (CIS NCs) at the low temperature of 270 °C. Structural and morphological analyses reveal the presence of a metastable CuIn5S8 phase and a disordered morphology in the CuInS2 nanocrytalline films consisting of polycrystalline grains at the nanoscale range. Consistent with the disordered morphology of the CIS NC thin films, the CIS NC devices are characterized by a low carrier mobility. The carrier density dynamic indicates that the recombination kinetics in these devices follows the dispersive bimolecular recombination model and does not fully behave in a diffusion-controlled manner, as expected by Langevin-type recombination. The mobility–lifetime product of the charge carriers properly explains the performance of the thin (200 nm) CIS NC solar cell with a high fill-factor of 64% and a PCE of over 3.5\
Keywords: nanostructures; power; conversion; nanocrystal

Reliability of IR-imaging of PV-plants under operating conditions - Buerhop, Cl; Schlegel, D.; Niess, M.; Vodermayer, C.; Weigmann, R.; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2012)
The quality check of PV-plants under certain operating conditions by employing infrared-imaging has acquired significance during the last years. In order to prove the reliability of these techniques in terms of power loss, life time, critical temperatures and failure mechanisms, fifteen PV-plants were investigated in detail. In total, about 260 dismantled modules were analyzed by power measurements as well as electroluminescence and IR-thermography. Apart from revealing the reliability of this technique, the evaluated data manifest various failure mechanisms, like cell fracture, deficient solder joints, short-circuited cells and bypassed substrings. The impact of these frequently detected defects on the resulting temperature, the IV-curve and the power output is discussed. Finally, differing defects can be diagnosed by characteristic temperature differences. In conclusion, the reliability and usefulness of infrared-mapping of PV-plants were proved with the result, that all modules having cells with increased temperature show remarkably reduced power output. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: IR-imaging; Outdoor testing; Reliability; Operating conditions; Electroluminescence

Reliable comparison of perovskite solar cell performance using maximum power point tracking - Rakocevic, Lucija; Ernst, Felix; Gehlhaar, Robert; Aernouts, Tom; Brabec, Christoph; Poortmans, Jef (International Conference on Hybrid and Organic Photovoltaics, 2019)
Organometallic halide based thin film PV has achieved research device efficiencies of 23.7 %, surpassing other thin film PV technologies in less than a decade of research. However, hysteretic behavior caused by ion movement in perovskite semiconductor affecting charge carrier extraction can inhibit a reliable performance measurement. This behavior, reflected in transient current variations following voltage alteration, can be dependent on preconditioning of the sample, scan rate, temperature and the composition of the perovskite solar cell stack itself. Therefore, a reliable performance comparison of perovskite solar cells is non-trivial. We examine the robustness of maximum power point tracking (MPPT) using three measurement algorithms to compare the performance of three n-i-p planar perovskite stacks. Moreover, we extract the relevant measurement parameters for a reliable MPPT. Figure shows how the measurement delay affects the measured performance of a solar cell for each of the studied algorithms. As the result of the study, we propose a measurement protocol to determine the device PCE applicable in everyday laboratory testing of perovskite solar cells. Finally, we draw attention to the importance of defining a robust and universal measurement procedure for comparison of various perovskite based thin film PV devices researched in the community<br

Reliable Performance Comparison of Perovskite Solar Cells Using Optimized Maximum Power Point Tracking - Rakocevic, Lucija; Ernst, Felix; Yimga, Nadine T.; Vashishtha, Saumye; Aernouts, Tom; Heumüller, Thomas; Brabec, Christoph; Gehlhaar, Robert; Poortmans, Jef (Solar RRL, 2019)
Performance comparison of perovskite solar cells with different architectures is nontrivial. J-V sweeps can be unreliable due to stack-dependent output variations affected by sample preconditioning, scan rate, scan direction, and temperature. Maximum power point tracking is regarded as a more reliable performance measurement. In this study, a two-step measuring procedure is proposed for quick and unbiased comparison of perovskite-based solar cells. In the proposed procedure, the transient current density characterization step is used to determine optimal parameters for maximum power point tracking performance characterization. Moreover, factors affecting time limited maximum power point tracking by comparing performance and output of three different maximum power point tracking algorithms applied to devices, from three planar n-i-p perovskite stacks, are analyzed and identified. Numerical simulation is used to model differences and define limitations of the algorithms. As a result, it is shown that measurement delay and voltage step can have a crucial effect on maximum power point tracking output, regardless of the chosen algorithm.
CRIS-Team WoS Importer:2019-03-08

Renewed Prospects for Organic Photovoltaics - Zhang, Guichuan; Lin, Francis R.; Qi, Feng; Heumüller, Thomas; Distler, Andreas; Egelhaaf, Hans-Joachim; Li, Ning; Chow, Philip C. Y.; Brabec, Christoph; Jen, Alex K. -Y.; Yip, Hin-Lap (Chemical Reviews, 2022)
Organic photovoltaics (OPVs) have progressed steadily through three stages of photoactive materials development: (i) use of poly(3-hexylthiophene) and fullerene-based acceptors (FAs) for optimizing bulk heterojunctions; (ii) development of new donors to better match with FAs; (iii) development of non-fullerene acceptors (NFAs). The development and application of NFAs with an A-D-A configuration (where A = acceptor and D = donor) has enabled devices to have efficient charge generation and small energy losses (Eloss < 0.6 eV), resulting in substantially higher power conversion efficiencies (PCEs) than FA-based devices. The discovery of Y6-type acceptors (Y6 = 2,2'-((2Z,2'Z)-((12,13-bis (2-ethylhexyl)-3,9-diundecyl-12,13-dihydro-[1,2,5]-thiadiazolo [3,4-e]-thieno- [2 ",3 ":4',5']thieno-[2',3':4,5]pyrrolo-[3,2-g]thieno-[2',3':4,5]thieno-[3,2-b]indole-2,10- diyl)bis(methanylylidene))bis(5,6-difluoro-3-oxo-2,3-dihydro-1H-indene-2,1-diylidene))-dimalononitrile) with an A-DA' D-A configuration has further propelled the PCEs to go beyond 15% due to smaller Eloss values (& SIM;0.5 eV) and higher external quantum efficiencies. Subsequently, the PCEs of Y6-series single-junction devices have increased to > 19% and may soon approach 20%. This review provides an update of recent progress of OPV in the following aspects: developments of novel NFAs and donors, understanding of the structure-property relationships and underlying mechanisms of state-of-the-art OPVs, and tasks underpinning the commercialization of OPVs, such as device stability, module development, potential applications, and high-throughput manufacturing. Finally, an outlook and prospects section summarizes the remaining challenges for the further development of OPV technology.
CRIS-Team WoS Importer:2022-08-26

Resolving a Critical Instability in Perovskite Solar Cells by Designing a Scalable and Printable Carbon Based Electrode-Interface Architecture - Mashhoun, Sara; Hou, Yi; Chen, Haiwei; Tajabadi, Fariba; Taghavinia, Nima; Egelhaaf, Hans-Joachim; Brabec, Christoph (Advanced Energy Materials, 2018)
Thin-film solar cells based on hybrid organo-halide lead perovskites achieve over 22% power conversion efficiency (PCE). A photovoltaic technology at such high performance is no longer limited by efficiency. Instead, lifetime and reliability become the decisive criteria for commercialization. This requires a standardized and scalable architecture which does fulfill all requirements for larger area solution processing. One of the most highly demanded technologies is a low temperature and printable conductive ink to substitute evaporated metal electrodes for the top contact. Importantly, that electrode technology must have higher environmental stability than, for instance, an evaporated silver (Ag) electrode. Herein, planar and entirely low-temperature-processed perovskite devices with a printed carbon top electrode are demonstrated. The carbon electrode shows superior photostability compared to reference devices with an evaporated Ag top electrode. As hole transport material, poly (3′hexyl thiophene) (P3HT) and copper(I) thiocyanate (CuSCN), two cost-effective and commercially available p-type semiconductors are identified to effectively replace the costlier 2,2′,7,7′-Tetrakis-(N,N-di-4-methoxyphenylamino)- 9,9′-spirobifluorene (spiro-MeOTAD). While methylammonium lead iodide (MAPbI3)-based perovskite solar cells (PSCs) with an evaporated Ag electrode degrade within 100 h under simulated sunlight (AM 1.5), fully solution-processed PSCs with printed carbon electrodes preserve more than 80% of their initial PCE after 1000 h of constant illumination.<br
Keywords: carbon electrodes; hole transporting material; stability; perovskite solar cells; photovoltaic devices

Revealing Hidden UV Instabilities in Organic Solar Cells by Correlating Device and Material Stability - Classen, Andrej; Heumüller, Thomas; Wabra, Isabell; Gerner, Johannes; He, Yakun; Einsiedler, Lukas; Li, Ning; Matt, Gebhard; Osvet, Andres; Du, Xiaoyan; Hirsch, Andreas; Brabec, Christoph (Advanced Energy Materials, 2019)
With state-of-the-art organic solar cells (OSCs) surpassing 16% efficiency, stability becomes critical for commercialization. In this work, the power of using photoluminescence (PL) measurements on plain films is demonstrated, as well as high-performance liquid chromatography analysis to reveal the origin of UV instabilities in OSCs based on the most commonly used acceptors PC70BM ([6,6]-phenyl-C71-butyric acid methyl ester), ITIC (3,9-bis(2-methylene-(3-(1,1-dicyanomethylene)-indanone))-5,5,11,11-tetrakis(4-hexylphenyl)-dithieno[2,3-d:2′,3′-d′]-s-indaceno[1,2-b:5,6-b′]dithiophene), and o-IDTBR (indacenodithiophene-based non-fullerene acceptor). The UV dependent stability tests reveal instabilities in solar cells based on PC70BM and ITIC while devices based on o-IDTBR are highly stable even under UV illumination. The analysis of solar cell devices based on charge extraction and sub-bandgap external quantum efficiency only shows the UV-dependent emergence of traps, while PL spectra of plain films on glass allows the disentanglement and identification of individual instabilities in multi-component bulk-heterojunction devices. In particular, the PL analysis demonstrates UV instabilities of PC70BM and ITIC toward the processing additive 1,8 diiodooctane (DIO). The chemical analysis reveals the in-depth mechanism, by providing direct proof of photochemical reactions of PC70BM and ITIC with UV-induced radicals of DIO. Based on this scientific understanding, it is shown how to stabilize PBQ-QF:PC70BM devices.
CRIS-Team Scopus Importer:2019-09-17
Keywords: degradation; diiodooctane; organic solar cells; stability; UV

Revealing Minor Electrical Losses in the Interconnecting Layers of Organic Tandem Solar Cells - Prosa, Mario; Li, Ning; Gasparini, Nicola; Bolognesi, Margherita; Seri, Mirko; Muccini, Michele; Brabec, Christoph (Advanced Materials Interfaces, 2017)
The interconnection layer (ICL) of organic multijunction solar cells represents one of the most delicate parts to ensure an efficient device operation. In view of pushing the efficiencies toward the theoretical limit, the individuation of minor losses affecting the ICL operation is of crucial importance. However, the difficulties arising from its position within the complex device structure typically hamper an accurate and selective investigation of the ICL. Here, a method based on the analysis of the photo-generated current density-voltage (Jph-V) response of solar cells, in the region of bias over the open-circuit voltage, is proved to individuate minor electrical losses within the ICL. Interestingly, the proposed method is demonstrated to effectively operate on tandem substructures, where different ICLs are investigated through the combination of materials having diverse characteristics. Furthermore, the use of a complementary investigation technique based on electroluminescence (EL) analysis allows to distinguish the specific nature of the electrical losses. The combination of Jph-V and EL analyses represents an elegant and advanced approach to shed light on the quality of ICLs in tandem substructures by avoiding the fabrication of the more complex tandem architecture. © 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Electrical losses; Electroluminescence; Interconnecting layers; Organic tandem solar cells; Photo-generated current

Revealing Photodegradation Pathways of Organic Solar Cells by Spectrally Resolved Accelerated Lifetime Analysis - Weitz, Paul; Le Corre, Vincent Marc; Du, Xiaoyan; Forberich, Karen; Deibel, Carsten; Brabec, Christoph; Heumüller, Thomas (Advanced Energy Materials, 2022)
A method for organic solar cell (OSC) stability testing is presented that aims to provide more unique insight into the causes of degradation patterns of OSCs. The method involves using monochromatic light at high irradiation doses to accelerate isolated degradation mechanisms while monitoring the device with a series of in-situ steady-state and transient electrical measurements. The experimental results are accompanied by drift-diffusion simulations to localize degradation pathways. PM6:Y6-based OSCs are tested, which are known to show a rather broad range of lifetimes as a function of device architecture, material batches, or degradation conditions. The experiments reveal a degradation mechanism that causes an increased trap-state density inside the PM6:Y6 layer. The transient simulations suggest that these states are formed at or around the interface between the PM6:Y6 and the electron transport layer. Furthermore, the surprisingly dominant impact of the illuminating wavelength on the degradation pattern is evidenced. Lastly, the degradation rate of the devices scales linearly with light intensity, making high intensity and spectrally selective degradation the most promising way to accelerate stability testing for the faster development of stable OSCs.
CRIS-Team Scopus Importer:2022-12-09
Keywords: acceleration; drift-diffusion; organic solar cells; photodegradation; transient; wavelength-dependence

Revealing processing stability landscape of organic solar cells with automated research platforms and machine learning - Du, Xiaoyan; Lüer, Larry; Heumueller, Thomas; Classen, Andrej; Liu, Chao; Berger, Christian; Wagner, Jerrit; Le Corre, Vincent M.; Cao, Jiamin; Xiao, Zuo; Ding, Liming; Forberich, Karen; et al. (InfoMat, 2024)
We use an automated research platform combined with machine learning to assess and understand the resilience against air and light during production of organic photovoltaic (OPV) devices from over 40 donor and acceptor combinations. The standardized protocol and high reproducibility of the platform results in a dataset of high variety and veracity to deploy machine learning models to encounter links between stability and chemical, energetic, and morphological structure. We find that the strongest predictor for air/light resilience during production is the effective gap Eg,eff which points to singlet oxygen rather than the superoxide anion being the dominant agent in degradation under processing conditions. A similarly good prediction of air/light resilience can also be achieved by considering only features from chemical structure, that is, information which is available prior to any experimentation.
CRIS-Team Scopus Importer:2024-06-28
Keywords: air stability; automated screening; donor/acceptor combinations; machine learning; organic solar cells

Revealing the Crystallization and Thermal-Induced Phase Evolution in Aromatic-Based Quasi-2D Perovskites Using a Robot-Based Platform - Zhang, Jiyun; Wu, Jianchang; Zhao, Yicheng; Zou, Yuqin; Barabash, Anastasiia; Wu, Zhenni; Zhang, Kaicheng; Deng, Can; Elia, Jack; Li, Chaohui; Rocha Ortiz, Juan Sebastian; Liu, Chao; et al. (ACS Energy Letters, 2023)
Introducing large organic cations to form reduced-dimensional (quasi-2D) perovskites has proven to be effective in stabilizing three-dimensional perovskites. In this study, we synthesized 28 Ruddlesden-Popper-type quasi-2D perovskites using four aromatic-based cations (phenylmethylammonium (PMA), phenethylammonium (PEA), phenylpropylammonium (PPA), and phenylbutanammonium (PBA)) and systematically investigated their optoelectronic and structural properties and thermal stability. A counterintuitive finding that longer-chain PPA-based films exhibited relatively poorer stability compared to films with shorter-chain cations has been found. This instability in PPA-based samples is attributed to significant lattice distortion and a mismatched phase between face-sharing trimers, causing intense configurational strain. On the other hand, PBA-containing films maintained robust structural stability due to distinctive crystallization kinetics and a gradual phase-transformation process (from larger-n to lower-n phases) induced by a stronger steric-hindrance effect. Our study sheds light on the complex impact of aromatic-based cations on optoelectronic properties and stability of perovskites, providing guidelines for the rational compositional design engineering of highly stable perovskite material

Revealing the Morphology of Organic Bulk Heterojunction Solar Cells Using EFTEM and Low‐Energy STEM - Fladischer, Stefanie; Schweizer, Peter; Ameri, Tayebeh; Brabec, Christoph; Spiecker, Erdmann (European Microscopy Congress 2016, 2016)
The morphology of organic bulk heterojunction (BHJ) solar cells decisively influences the device performance and efficiency and therefore is an important factor that needs to be investigated to gain a better understanding and improvement of the devices. Especially the nanoscale morphology of the active layer plays an important role as it determines the charge separation at the interfaces and the percolation pathways to the electrodes. This nanoscale morphology depends not only on the involved materials but also on their molecular weight and their treatment like thermal annealing and solvent vapor annealing.<br
Keywords: organic solar cells; morphology; EFTEM; low-energy STEM

Revealing the strain-associated physical mechanisms impacting the performance and stability of perovskite solar cells - Meng, Wei; Zhang, Kaicheng; Osvet, Andres; Zhang, Jiyun; Gruber, Wolfgang; Forberich, Karen; Meyer, Bernd; Heiß, Wolfgang; Unruh, Tobias; Li, Ning; Brabec, Christoph (Joule, 2022)
Identification and investigation of strain at buried interfaces in halide perovskite photovoltaics are crucial for directing research on the performance and stability of perovskite solar cells. In this work, we find a gradual shift in the band gap of up to 60 meV over a perovskite layer thickness of 300 nm caused by interfacial strain. This graded band gap is desired insofar as it relates to the aspect of device engineering. However, in parallel, the increased defect density causes charge recombination at the buried interface. These two effects compensate for each other, resulting in an overall performance improvement under standard 1 sun illumination. Nevertheless, the disadvantage of enhanced defect density is clearly observed at low-light intensities, where the device performance becomes dominated by charge recombination and ion migration. Moreover, the strained interfaces are proven to induce enhanced defect densities, causing significantly accelerated device degradation under illumination as well as in the dark.
CRIS-Team Scopus Importer:2022-03-18
Keywords: device stability; graded band gap; interface engineering; low-light PV applications; perovskite solar cells; strain engineering

Revealing Trap States in Lead Sulphide Colloidal Quantum Dots by Photoinduced Absorption Spectroscopy - Kahmann, Simon; Sytnyk, Mykhailo; Schrenker, Nadine; Matt, Gebhard; Spiecker, Erdmann; Heiß, Wolfgang; Brabec, Christoph; Loi, Maria A. (Advanced Electronic Materials, 2017)
Due to their large surface to volume ratio, colloidal quantum dots (CQDs) are often considered to exhibit a significant amount of surface defects. Such defects are one possible source for the formation of in-gap states (IGS), which can enhance the recombination of excited carriers, i.e., work as electrical traps. These traps are investigated for lead sulphide CQDs of different size, covered with different ligands using a mid-infrared photoinduced absorption (PIA) technique. The obtained PIA spectra reveal two distinct absorption bands, whose position depends on the particle size, i.e., the electronic confinement in the CQDs. Smaller particles exhibit deeper traps. The chemical nature of the capping ligand does not affect the resulting position other than due to its change in confinement, but better passivating species lead to smaller signals. Furthermore, ligand specific narrow lines observed are superimposed on the broad electronic background of the PIA spectra, which is attributed to Fano resonances caused by the interplay of the narrow molecular vibrations and the continuum of trap states. Mid-infrared photoinduced absorption represents a valuable tool to unravel distributions of IGS in CQDs and allows for an assessment of the quality of ligand exchanged films. These findings have implications for understanding the performances of CQD-based (opto-) electronic devices, such as solar cells, transistors, or quantum dot light emitting diodes, which are limited by frequent carrier trapping events.
Keywords: Colloidal quantum dots; Mid infrared spectroscopy; Molecular vibrations; Pump-probe spectroscopy; Trap states

Reversible Growth of Halide Perovskites via Lead Oxide Hydroxide Nitrates Anchored Zeolitic Imidazolate Frameworks for Information Encryption and Decryption - Zeng, Linxiang; Huang, Xiongjian; Le, Yakun; Zhou, Xinming; Zheng, Wenyan; Brabec, Christoph; Qiao, Xvsheng; Guo, Fei; Fan, Xianping; Dong, Guoping (ACS nano, 2023)
The low formation energies of metal halide perovskites endow them with potential luminescent materials for applications in information encryption and decryption. However, reversible encryption and decryption are greatly hindered by the difficulty in robustly integrating perovskite ingredients into carrier materials. Here, we report an effective strategy to realize information encryption and decryption by reversible synthesis of halide perovskites, on the lead oxide hydroxide nitrates (Pb13O8(OH)6(NO3)4) anchored zeolitic imidazolate framework composites. Benefiting from the superior stability of ZIF-8 in combination with the strong bond between Pb and N evidenced by X-ray absorption spectroscopy and X-ray photoelectron spectroscopy, the as-prepared Pb13O8(OH)6(NO3)4-ZIF-8 nanocomposites (Pb-ZIF-8) can withstand common polar solvent attack. Taking advantage of blade-coating and laser etching, the Pb-ZIF-8 confidential films can be readily encrypted and subsequently decrypted through reaction with halide ammonium salt. Consequently, multiple cycles of encryption and decryption are realized by quenching and recovery of the luminescent MAPbBr3-ZIF-8 films with polar solvents vapor and MABr reaction, respectively. These results provide a viable approach to integrate the state-of-the-art materials perovskites and ZIF for applications in information encryption and decryption films with large scale (up to 6 × 6 cm2), flexibility, and high resolution (approximate 5 μm line width).
CRIS-Team Scopus Importer:2023-03-24
Keywords: blade coating; femtosecond laser etching; lead oxide hydroxide nitrate; perovskite; ZIF-8

Robot-Based High-Throughput Engineering of Alcoholic Polymer: Fullerene Nanoparticle Inks for an Eco-Friendly Processing of Organic Solar Cells - Xie, Chen; Tang, Xiaofeng; Berlinghof, Marvin; Langner, Stefan; Chen, Shi; Späth, Andreas; Li, Ning; Fink, Rainer; Unruh, Tobias; Brabec, Christoph (ACS Applied Materials and Interfaces, 2018)
Development of high-quality organic nanoparticle inks is a significant scientific challenge for the industrial production of solution processed organic photovoltaics (OPVs) with eco-friendly processing methods. In this work, we demonstrate a novel, robot-based, high throughput procedure performing automatic poly(3-hexylthio-phene-2,5-diyl) and indene-C-60 bisadduct nanoparticle ink synthesis in nontoxic alcohols. A novel methodology to prepare particle dispersions for fully functional OPVs by manipulating the particle size and solvent system was studied in detail. The ethanol dispersion with a particle diameter of around 80-100 nm exhibits reduced degradation, yielding a power conversion efficiency of 4.52%, which is the highest performance reported so far for water/alcohol-processed OPV devices. By successfully deploying the high-throughput robot-based approach for an organic nanoparticle ink preparation, we believe that the findings demonstrated in this work will trigger more research interest and effort on eco-friendly industrial production of OPVs.
Keywords: organic photovoltaics; eco-friendly industrial production; robot-based systems; high-throughput organic nanoparticle synthesis; stable organic nanoparticle inks; organic nanoparticle size control

Robot-Based High-Throughput Screening of Antisolvents for Lead Halide Perovskites - Gu, Ening; Tang, Xiaofeng; Langner, Stefan; Duchstein, Patrick; Zhao, Yicheng; Levchuk, Ievgen; Kalancha, Violetta; Stubhan, Tobias; Hauch, Jens; Egelhaaf, Hans-Joachim; Zahn, Dirk; Osvet, Andres; et al. (Joule, 2020)
Solution-based processing of photovoltaic materials has important advantages, including lower overall costs and easier upscaling of fabrication, where the solvents play an essential role. Antisolvent crystallization technique is often applied to achieve high-quality perovskite materials. However, the basic chemistry of the solvent-antisolvent crystallization is still not well understood. Besides, common antisolvents are toxic, and their number is limited. In this work, a novel robot-based method was used to screen the efficient antisolvents for different solvent-perovskite systems. 336 combinations of perovskite-solvent-antisolvent could be prepared and characterized by the integrated robotic platform in 2 days. In addition, we provided a detailed working mechanism of the solvent-antisolvent crystallization approach. Furthermore, hundreds of potential antisolvents were proposed based on high-throughput screening and simulation. Verification tests match well with theory, and all reported antisolvents used for photovoltaic device optimizations are within our predicted range of the Hansen space, indicating that the predictions are reliable. In terms of solution-processed lead halide perovskite optoelectrical materials, suitable antisolvent is essential for the crystallization and properties of final products. Conventional experiments of antisolvent selections are based on the manual time-consuming trial-error methods, which cannot meet today's increasing demands. In this work, a robot-based method was used to screen the antisolvents for different solvent-perovskite systems in a high-throughput manner to study the influence of interactions among the solvent molecules, cations, metal-halides, and antisolvents, to build an informative database, and to reveal the working mechanism and selection criteria of antisolvents. Besides, simulations based on the screening results provide hundreds of potential antisolvents. Corresponding verification tests evidenced that our predictions are reliable and vital for designing future efficient mixed solvent systems for the fabrication of perovskite optoelectrical materials. A robotic platform is adopted to conduct a comprehensive solvent engineering for making lead halide perovskites in a high-throughput manner. Deeper insights into the working mechanisms and selection criteria of antisolvents are investigated and summarized. In addition, a reliable antisolvent database is established, and verification tests match well with the theory. Furthermore, our work provides significant guidance for designing functional and environment-friendly mixed solvent systems to fabricate high-quality perovskite materials or devices.
CRIS-Team Scopus Importer:2020-08-21
Keywords: antisolvents; automated research; high-throughput method; lead halide complexes; lead halide perovskite; solvent engineering

Robust nonfullerene solar cells approaching unity external quantum efficiency enabled by suppression of geminate recombination - Baran, Derya; Gasparini, Nicola; Wadsworth, Andrew; Tan, Ching Hong; Wehbe, Nimer; Song, Xin; Hamid, Zeinab; Zhang, Weimin; Neophytou, Marios; Kirchartz, Thomas; Brabec, Christoph; Durrant, James R.; et al. (Nature Communications, 2018)
Nonfullerene solar cells have increased their efficiencies up to 13%, yet quantum efficiencies are still limited to 80%. Here we report efficient nonfullerene solar cells with quantum efficiencies approaching unity. This is achieved with overlapping absorption bands of donor and acceptor that increases the photon absorption strength in the range from about 570 to 700 nm, thus, almost all incident photons are absorbed in the active layer. The charges generated are found to dissociate with negligible geminate recombination losses resulting in a short-circuit current density of 20 mA cm(-2) along with open-circuit voltages >1 V, which is remarkable for a 1.6 eV bandgap system. Most importantly, the unique nano-morphology of the donor:acceptor blend results in a substantially improved stability under illumination. Understanding the efficient charge separation in nonfullerene acceptors can pave the way to robust and recombination-free organic solar cells.

Role of Polymer Fractionation in Energetic Losses and Charge Carrier Lifetimes of Polymer: Fullerene Solar Cells - Baran, Derya; Vezie, Michelle S.; Gasparini, Nicola; Deledalle, Florent; Yao, Jizhong; Schroeder, Bob C.; Bronstein, Hugo; Ameri, Tayebeh; Kirchartz, Thomas; Mcculloch, Iain; Nelson, Jenny; Brabec, Christoph (Journal of Physical Chemistry C, 2015)
Nonradiative recombination reduces the open-circuit voltage relative to its theoretical limit and leads to reduced luminescence emission at a given excitation. Therefore, it is possible to correlate changes in luminescence emission with changes in open-circuit voltage and in the charge carrier lifetime. Here we use luminescence studies combined with transient photovoltage and differential charging analyses to study the effect of polymer fractionation in indacenoedithiophene-co-benzothiadiazole (IDTBT):fullerene solar cells. In this system, polymer fractionation increases electroluminescence emission at the same injection current and reduces nonradiative recombination. High-molecular-weight and fractionated IDTBT polymers exhibit higher carrier lifetime-mobility product compared to that of their nonfractionated analogues, resulting in improved solar cell performance. (Graph Presented).
Keywords: Engineering controlled terms: Carrier lifetime; Charge carriers; Fullerenes; Light; Luminescence; Open circuit voltage; Polymers Differential charging; Electroluminescence emission; High molecular weight; Luminescence emission; Non-radiative recombinations; Polymer fractionation; Solar cell performance; Transient photovoltage Engineering main heading: Solar cells

Roll to roll compatible fabrication of inverted organic solar cells with a self-organized charge selective cathode interfacial layer - Zhang, Hong; Tan, Wan-Yi; Fladischer, Stefanie; Ke, Lili; Ameri, Tayebeh; Li, Ning; Turbiez, Mathieu; Spiecker, Erdmann; Zhu, Xu-Hui; Cao, Yong; Brabec, Christoph (Journal of Materials Chemistry A, 2016)
We successfully demonstrate a simple approach to printing efficient, inverted organic solar cells (OSCs) with a self-organized charge selective cathode interface layer based on the small-molecule Phen-NaDPO. Different from previous studies, Phen-NaDPO molecules were blended into a polymer/fullerene blend, comprising a low bandgap diketopyrrolopyrrole-quinquethiophene alternating copolymer pDPP5T-2 and phenyl-C-butyric acid methyl ester (PCBM), and processed by doctor blading in air. We observed a spontaneous, surface energy driven migration of Phen-NaDPO towards the ZnO interface and a subsequent formation of electron selective and barrier free extraction contacts. In the presence of 0.5 wt% Phen-NaDPO, a PCE of 5.4% was achieved for the inverted device based on an ITO/ZnO cathode. Notably, the photovoltaic performances remained at the same level with increasing the Phen-NaDPO concentration in the active layer from 0.25 to 1 wt%. Furthermore, this approach could be proven to effectively work with other cathodes such as bare ITO and ITO/AZO. The self-organization of Phen-NaDPO through spontaneous vertical phase separation is mainly attributed to its high surface energy and strong interaction with the cathode material. The present results highlight that a self-organized cathode interfacial material processed from a "ternary" active layer is fully compatible with the requirements for roll-to-roll fabrication of inverted organic solar cells.
Keywords: Engineering controlled terms: Butyric acid; Cathodes; Electrodes; Interfacial energy; Molecules; Organic solar cells; Phase separation Alternating copolymer; Cathode interfacial layers; Diketopyrrolopyrroles; High surface energy; Inverted organic solar cells; Photovoltaic performance; Roll-to-roll fabrication; Vertical phase separations Engineering main heading: Solar cells

Round-Robin studies as a method for testing and validating high-effi ciency ito-free polymer solar cells based on roll-to-roll-coated highly conductive and transparent flexible substrates - Larsen-Olsen, Thue T.; Machui, Florian; Lechene, Balthazar; Berny, Stephane; Angmo, Dechan; Sondergaard, Roar; Blouin, Nicolas; Mitchell, William; Tierney, Steven; Cull, Tobias; Tiwana, Priti; Meyer, Frank; et al. (Advanced Energy Materials, 2012)
Photovoltaic cells based on organic and polymer materials (OPVs) are celebrated as being a possible solution to the energy needs of the future, [ 1b ] and, with record effi ciencies having breached the 10% milestone accompanied by emerging involvement from the materials industry, expectations are rapidly approaching reality. [ 1c ] However, in order to move OPVs beyond the individual laboratory and into a generally applied setting, scientists need to limit the gap between carefully prepared hero devices and the large-scale manufacture of thousands of devices. We propose that this is done by urgently attending to the challenges of scalability and reproducibility. In this communication, we demonstrate an approach using round-robin testing as a method to validate effi ciency measurements of OPVs based on semitransparent electrodes on fl exible substrates, with and without indium tin oxide (ITO). ITO-free substrates were rollto- roll coated under ambient conditions and were truly scalable. Our results demonstrate inherent uncertainties in the device-effi ciency data, with variations in the carefully measured effi ciency data for the same device between highly qualifi ed laboratories as high as 25%, depending on the substrate and its active area. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Round-Robin Studies on Roll-Processed ITO-free Organic Tandem Solar Cells Combined with Inter-Laboratory Stability Studies - Livi, Francesco; Sondergaard, Roar R.; Andersen, Thomas R.; Roth, Berenger; Gevorgyan, Suren; Dam, Henrik F.; Carle, Jon E.; Helgesen, Martin; Spyropoulos, Georgios; Adams, Jens; Ameri, Tayebeh; Brabec, Christoph; et al. (Energy Technology, 2015)
Roll-processed, indium tin oxide (ITO)-free, flexible, organic tandem solar cells and modules have been realized and used in round-robin studies as well as in parallel inter-laboratory stability studies. The tandem cells/modules show no significant difference in comparison to their single-junction counterparts and the use of round-robin studies as a consensus tool for evaluation of organic solar cell parameters is judged just as viable for the tandem solar cells as for single-junction devices. The inter-laboratory stability studies were conducted according to testing protocols ISOS-D-2, ISOS-D-3, and ISOS-L-2, and in spite of a much more complicated architecture the organic tandem solar cells show no significant difference in stability in comparison to their single-junction counterparts. © 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: ITO-free; Photovoltaics; Roll processing; Stability; Tandem solar cells

Sb2Se3Thin-Film Growth by Solution Atomic Layer Deposition - Koch, Vanessa; Charvot, Jaroslav; Cao, Yuanyuan; Hartmann, Claudia; Wilks, Regan G.; Kundrata, Ivan; Minguez Bacho, Ignacio; Gheshlaghi, Negar; Hoga, Felix; Stubhan, Tobias; Alex, Wiebke; Pokorný, Daniel; et al. (Chemistry of Materials, 2022)
We establish solution atomic layer deposition (sALD) for the controlled growth of pure Sb2Se3 thin films under mild conditions, namely, room temperature and atmospheric pressure. Upscaling this process yields Sb2Se3 thin films with high homogeneity over large-area (4″) substrates. Annealing of the initially amorphous material leads to highly crystalline and smooth Sb2Se3 thin films. Removing the constraints of thermal stability and sufficient volatility in sALD compared to traditional gas-phase ALD opens up a broad choice of precursors and allows us to examine a wide range of Se2- precursors, of which some exhibit facile synthetic routes and allow us to tune their reactivity for optimal experimental ease of use. Moreover, we demonstrate that the solvent used in sALD represents an additional, attractive tool to influence and tailor the reactivity at the liquid-solid interface between the precursors and the surface.
Created from Fastlane, Scopus look-up

Scalable, ambient atmosphere roll-to-roll manufacture of encapsulated large area, flexible organic tandem solar cell modules - Andersen, Thomas R.; Dam, Henrik F.; Hosel, Markus; Helgesen, Martin; Carle, Jon E.; Larsen-Olsen, Thue T.; Gevorgyan, Suren A.; Andreasen, Jens W.; Adams, Jens; Li, Ning; Machui, Florian; Spyropoulos, Georgios; et al. (Energy and Environmental Science, 2014)
Inline printing and coating methods have been demonstrated to enable a high technical yield of fully roll-to-roll processed polymer tandem solar cell modules. We demonstrate generality by employing different material sets and also describe how the ink systems must be carefully co-developed in order to reach the ambitious objective of a fully printed and coated 14-layer flexible tandem solar cell stack. The roll-to-roll methodologies involved are flexographic printing, rotary screen printing, slot-die coating, X-ray scattering, electrical testing and UV-lamination. Their combination enables the manufacture of completely functional devices in exceptionally high yields. Critical to the ink and process development is a carefully chosen technology transfer to industry method where first a roll coater is employed enabling contactless stack build up, followed by a small roll-to-roll coater fitted to an X-ray machine enabling in situ studies of wet ink deposition and drying mechanisms, ultimately elucidating how a robust inline processed recombination layer is key to a high technical yield. Finally, the transfer to full roll-to-roll processing is demonstrated. This journal is © the Partner Organisations 2014.
Keywords: Engineering controlled terms: Coatings; Manufacture; Technology transfer; Testing Ambient atmosphere; Flexographic printing; Functional devices; Polymer tandem solar cells; Process development; Recombination layers; Roll-to-roll processing; Rotary screen printing Engineering main heading: Solar cells GEOBASE Subject Index: coating; photovoltaic system; polymer; solar power; technological development

Scintillators based on CdWO 4 and CdWO 4: Bi single crystalline films - Zorenko, Yuriy; Gorbenko, Vitaliy; Voznyak, Taras; Konstankevych, Ivan; Savchyn, Volodymyr; Batentschuk, Miroslaw; Winnacker, Albrecht; Brabec, Christoph (IEEE Transactions on Nuclear Science, 2012)
This research is directed on creating by liquid phase epitaxy the single crystalline film scintillators based on undoped and Bi doped CdWO compounds as well as the phoswich detector based on CdWO : Bi or CdWO films CdWO or CdWO : Bi crystals epitaxial structures. The luminescent and scintillation properties of the undoped and Bi doped (in a concentration range of 0.04-0.25 at. %) CdWO films, grown by LPE method from Na WO flux, were compared with the properties of CdWO bulk crystal analogs, grown from melts by the Czochralski method. Using the traditional luminescence spectroscopy and the luminescence spectroscopy under excitation by pulsed synchrotron radiation with energy in the fundamental absorption range of CdWO host, we have also examined the nature of different emission centers and studied energy transfer processes from tungstate hosts to Bi ions and defect centers in CdWO and CdWO : Bi films and their crystal analogs. © 2012 IEEE.
Keywords: Bi dopant; liquid phase epitaxy; luminescence; scintillators; single crystals and single crystalline films

Self-assembled microstructured polymeric and ceramic surfaces - Woiton, Michael; Heyder, Madeleine; Laskowsky, Alexandra; Stern, Edda; Scheffler, Michael; Brabec, Christoph (Journal of the European Ceramic Society, 2011)
Self-assembled microstructures were manufactured by dip coating of substrates with unfilled and filler-loaded preceramic polymer mixtures in the presence of a solvent and a non-solvent. The nature of the polymers was characterized by their solubility parameters. Variation of the polymer/polymer ratio and the volume fraction of the solvent and/or non-solvent led to different surface structures. Studies of the structure formation mechanism indicate that demixing processes of the polymers are responsible for self-assembly in filler-free mixtures. In filler-loaded mixtures the structure formation process, however, is more complex. The micro-structured polymeric coatings obtained from filler loaded systems were converted into polymer derived ceramic coatings under shape retention. High specific surface areas were measured after thermal conversion. © 2011 Elsevier Ltd.
Keywords: Films; Porosity; Precursors-organic; Self-assembly; SiC; Surfaces

Self-assembly of colloidal single-layer carbon nitride - Stroyuk, Oleksandr; Raievska, Oleksandra; Brabec, Christoph; Dzhagan, Volodymyr; Havryliuk, Yevhenii; Zahn, Dietrich R. T. (Nanoscale, 2022)
We introduce a new concept of a "bottom-to-top" design of intercalate carbon nitride compounds based on the effects of self-assembly of colloidal single-layer carbon nitride (SLCN) sheets stabilized by tetraethylammonium hydroxide NEt4OH upon ambient drying of the water solvent. These effects include (i) formation of stage-1 intercalates of NEt4OH during the ambient drying of SLCN colloids on glass substrates and (ii) the spontaneous formation of layered hexagonally-shaped networks of SLCN sheets on freshly-cleaved mica surfaces. The dynamics of the intercalate formation was followed by in situ X-ray diffraction allowing different stages to be identified, including the deposition of a primary "wet" intercalate of hydrated NEt4OH and the gradual elimination of excessive water during its ambient drying. The intercalated NEt4+ cations show a specific "flattened" conformation allowing the dynamics of formation and structure of the intercalate to be probed by vibrational spectroscopies. The two-dimensional self-assembly on mica is assumed to be driven both by the internal hexagonal symmetry of heptazine units and by a templating effect of the mica surface.
CRIS-Team WoS Importer:2022-08-26

Self-Healing Cs3Bi2Br3I6 Perovskite Wafers for X-Ray Detection - Daum, Manuel; Deumel, Sarah; Sytnyk, Mykhailo; Afify, Hany A.; Hock, Rainer; Eigen, Andreas; Zhao, Baolin; Halik, Marcus; These, Albert; Matt, Gebhard; Brabec, Christoph; Tedde, Sandro F.; et al. (Advanced Functional Materials, 2021)
Self-healing of defects imposed by external stimuli such as high energy radiation is a possibility to sustain the operational lifetime of electronic devices such as radiation detectors. Cs3Bi2Br3I6 polycrystalline wafers are introduced here as novel X-ray detector material, which not only guarantees a high X-ray stopping power due to its composition with elements with high atomic numbers, but also outperforms other Bi-based semiconductors in respect to detector parameters such as detection limit, transient behavior, or dark current. The polycrystalline wafers represent a size scalable technology suitable for future integration in imager devices for medical applications. Most astonishingly, aging of these wafer-based devices results in an overall improvement of the detector performance—dark currents are reduced, photocurrents are increased, and one of the most problematic properties of X-ray detectors, the base line drift is reduced by orders of magnitude. These aging induced improvements indicate self-healing effects which are shown to result from recrystallization. Optimized synthetic conditions also improve the as prepared X-ray detectors; however, the aged device outperforms all others. Thus, self-healing acts in Cs3Bi2Br3I6 as an optimization tool, which is certainly not restricted to this single compound, it is expected to be beneficial also for many further polycrystalline ionic semiconductors.
CRIS-Team Scopus Importer:2021-08-27
Keywords: bismuth halides; lead-free perovskites; photoconductors; self-healing; X-ray detection

Semitransparent Organic Light Emitting Diodes with Bidirectionally Controlled Emission - Bronnbauer, Carina; Osvet, Andres; Brabec, Christoph; Forberich, Karen (ACS Photonics, 2016)
Semitransparent OLEDs are a candidate for large-area eco-friendly light sources that can be integrated into building facades, suggesting colorful windows that become luminescent if the OLED is switched on. However, since the light is emitted in two directions, smart light engineering has to be implemented to direct the light into a preferred direction and to prevent for instance huge energetic losses to the outside of a building. We introduce an unprecedented device architecture, composed of a dielectric mirror attached to a semitransparent OLED. Such a system features a dual functionality that depends on the viewing direction: changing the color perception and/or enhancing the light directionality while still preserving a high overall device transparency. First, we motivate the potential of this concept with a theoretical study, showing that broad modifications in the color range can be realized via device optimization and that the maximum possible emission enhancement of the OLED is limited only by the transparency of the interfacial layers and the electrodes. Then, experimental investigations with a semitransparent yellow OLED (transparency = 58.2%) in combination with six different dielectric mirrors validate the theoretical results. Retaining the same color perception, up to 80% of the total emitted light can be directed toward one side while the color is modified at the other side of the device stack. Here, modifications from yellow to purple to dark or light blue can be realized.
Keywords: color modification; dielectric mirror; fully printed; light management; OLED; semitransparent

Semitransparent organic photovoltaic modules with Ag nanowire top electrodes - Guo, Fei; Kubis, Peter; Przybilla, Thomas; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (International Society for Optical Engineering; 1999, 2014)
Semitransparent organic photovoltaic (OPV) cells are promising for applications in transparent architectures where their opaque counterparts are not suitable. Manufacturing of large-area modules without performance losses compared to their lab-scale devices is a key step towards practical applications of this PV technology. In this paper, we report the use of solution-processed silver nanowires as top electrodes and fabricate semitransparent OPV modules based on ultra-fast laser scribing. Through a rational choice of device architecture in combination with high-precision laser patterning, we demonstrate efficient semitransparent modules with comparable performance as compared to the reference devices.
Keywords: semitransparent organic solar cells; organic photovoltaic modules; silver nanowires; laser patterning

Semitransparent polymer solar cells - Guo, Fei; Ameri, Tayebeh; Forberich, Karen; Brabec, Christoph (Polymer International, 2013)
This perspective discusses the choice of semiconducting photoactive polymers toward high efficiencies of semitransparent polymer solar cells and stresses several promising alternative transparent electrodes to ITO and their processing methods. Bulk heterojunction based polymer:fullerene solar cells have attracted intensive research interest both in academic and industrial communities in the last two decades, mainly related to their potential low-cost production process. A power conversion efficiency of over 10% has been reported recently, making the commercialization of this clean and cheap solar energy convertor a realistic prospect for the near future. The intrinsic features of semitransparency and color tunability of the thin polymeric photoactive films are the greatest asset for polymer solar cells. Recently, aesthetic semitransparent polymer solar cells (ST-PSCs) that can be integrated into transparent windows, roofs, glass and other semitransparent architectural elements have received much attention. In this perspective paper, we present the progress in achieving high performance ST-PSCs, discuss the requirements for transparent electrodes, focusing on alternatives to tin-doped indium oxide, and address the challenges ahead to make ST-PSC viable for real applications. © 2013 Society of Chemical Industry.
Keywords: Bulk heterojunction; OPV; Polymer solar cells; Semitransparent; Silver nanowire

Sensitive Direct Converting X-Ray Detectors Utilizing Crystalline CsPbBr3 Perovskite Films Fabricated via Scalable Melt Processing - Matt, Gebhard; Levchuk, Ievgen; Knüttel, Judith; Dallmann, Johannes; Osvet, Andres; Sytnyk, Mykhailo; Tang, Xiaofeng; Elia, Jack; Hock, Rainer; Heiß, Wolfgang; Brabec, Christoph (Advanced Materials Interfaces, 2020)
Here the fabrication of an inorganic metal-halide perovskite CsPbBr3 based X-ray detector is reported utilizing a simple, scalable, and cost-sensitive melt processing directly on substrate of any size. X-ray diffraction analysis on the several 100 mm thick melt processed films confirms crystalline domains in the cm(2) range. The CsPbBr3 film features a resistance of 8.5 G omega cm and a hole mobility of 18 cm(2) V-1 s(-1). An X-ray to current conversion rate of 1450 mC Gy(air)(-1) cm(-2) at an electric field of 1.2 x 10(4) V cm(-1) and a detection limit in the sub mu Gy(air) s(-1) regime is demonstrated. The high crystallinity and chemical purity of the melt processed CsPbBr3 films are suggested to be responsible for a performance which is on par to current state-of-the-art Cd(Zn)Te based X-ray detector technology.
Keywords: X-ray detection; metal-halide perovskites; photophysics

Separating the Influence of Material Composition and Local Defects on the Voc of CIGS Solar Modules - Hepp, Johannes; Vetter, Andreas; Hofbeck, Bernhard; Camus, Christian; Hauch, Jens; Brabec, Christoph (33rd European Photovoltaic Solar Energy Conference and Exhibition, 2017)
In spite of the steadily improved quality of co-evaporated Cu(In,Ga)Se2 absorber layers, the existence of local defects affecting the module performance in large area production can still be an issue. Generally, both, lateral composition gradients and point defects can be found in those layers. We show the necessity to separate these two influences and propose two measurement techniques in order to asses the effect of the material and the defects individually. In oder to quantify the theoretical defect-free open circuit voltage (Voc), given by the material composition, we used luminescence spectroscopy. The additional effect on the Voc originating from local defects was determined using dark lock-in thermography. The combination of both these methods enables a local prediction of a module’s Voc. In the following, we conduct an indepth analysis of the determination of the material composition and its impact on the resulting Voc.
Keywords: Defects; Monitoring; Spectroscopy; Electroluminescence; CIGS

Sequential Deposition of High-Quality Photovoltaic Perovskite Layers via Scalable Printing Methods - Guo, Fei; He, Wenxin; Qiu, Shudi; Wang, Chuan; Liu, Xianhu; Forberich, Karen; Brabec, Christoph; Mai, Yaohua (Advanced Functional Materials, 2019)
Sequential deposition is demonstrated as an effective technology for preparation of high-performance perovskite solar cells based on lab-scale spin coating. However, devices fabricated by scalable methods are lagging far behind their state-of-the-art spin-coated counterparts, largely due to the difficulty in obtaining high-quality thin films of perovskites crystallized from printed precursors. Here, a generic strategy that allows sequential deposition of dense and uniform perovskite films via two-step blade coating is reported. The rational selection of solvent combined with a mild vacuum extraction process enables us to produce uniform lead iodide (PbI2) films over large areas. Significantly, the resulting PbI2 films possess a mesoporous structure that is highly beneficial for the insertion reaction with methylammonium iodide (MAI). It is further identified that the deposition temperature of MAI plays an important role in determining the morphology and crystallinity of the perovskite films. Solar cells using these sequentially bladed perovskite layers yield efficiencies over 16% with high fill factors up to 78%. These results represent important progress toward the largescale deposition of perovskite thin films for practical applications<br
Keywords: perovskite; scalable printing; sequential deposition; solar cells

Series vs parallel connected organic tandem solar cells: Cell performance and impact on the design and operation of functional modules - Etxebarria, Ikerne; Furlan, Alice; Ajuria, Jon; Fecher, Frank W.; Voigt, Monika; Brabec, Christoph; Wienk, Martijn M.; Slooff, Lenneke; Veenstra, Sjoerd; Gilot, Jan; Pacios, Roberto (Solar Energy Materials and Solar Cells, 2014)
Tandem solar cells are the best approach to maximize the light harvesting and adjust the overall absorption of the cell to the solar irradiance spectrum. Usually, the front and back subcells are connected in series in two-terminal device (2T) designs which require a current matching between both subcells in order to avoid potential losses. Alternatively, they can also be connected in parallel giving rise to a three terminal connection (3T). In principle, both designs have their assets and drawbacks in terms of device performance, design and materials' characterization. In this letter, we theoretically and experimentally confront both designs with each other (2T and 3T). Theoretical estimations show a maximum PCE of 15% for 2T and about 13% for 3T structures with ideal bandgaps for the front and back cell. However, 3T tandem devices can yield higher efficiencies than 2T for some specific material combinations whose theoretical values are between 10% and 12%. Therefore, other aspects related to the fabrication feasibility are studied in order to analyze the most convenient approach for module development. The need of a conducting interlayer restricts the width of the cell and causes a 3% reduction in the geometrical fill factor of the module in comparison to the 2T approach. The R2R processing of modules with 3T cells would also require an additional laser step. Finally, a couple of existing material combinations have been experimentally implemented into 2T and 3T tandem devices. The limitation imposed by their specific and non-ideal bandgaps restricts the efficiency to around 7%, considerably below the ideal case. © 2014 Elsevier B.V.
Keywords: R2R module processing; Tandem organic solar cells; Three-terminal parallel connection; Two-terminal series connection

Shape-Controlled Solution-Epitaxial Perovskite Micro-Crystal Lasers Rivaling Vapor Deposited Ones - Afify, Hany A.; Rehm, Viktor; Barabash, Anastasiia; These, Albert; Zhang, Jiyun; Osvet, Andres; Schüßlbauer, Christoph; Thiel, Dominik; Ullrich, Tobias; Dierner, Martin; Przybilla, Thomas; Will, Johannes; et al. (Advanced Functional Materials, 2022)
Epitaxial growth methods usually need dedicated equipment, high energy consumption to maintain pure vacuum conditions and evaporation of source materials, and elevated substrate temperatures. Solution epitaxial growth requires nothing of that but is rarely used because the achieved microstructures are of low quality, not homogeneous, and finally exhibit worse performances in devices. Here, an antisolvent-vapor-assisted-crystallization of metal-halide-perovskites as a method overcoming these disadvantages is demonstrated. The methylammonium lead tribromide exhibits van-der-Waals type of epitaxial growth on mica substrates, resulting in micro-crystallites whose shape can be controlled to be either triangular micro-prism or micro-cuboid. These micro-crystallites act as optical resonators supporting various optical modes and lasing is achieved under optical excitation with low thresholds and record high environmental stability. Selecting suitable resonators from a large variety of sizes allows control of mode spacing and finally mono-mode operation, considered to be an important feature of semiconductor laser devices. The achieved results are essentially competitive to those obtained by vapor phase epitaxial microstructures, highlighting that epitaxy of high-quality optoelectronic device structures is feasible by minimum technological efforts and energy consumption, which are of increasing importance considering issues such as global warming and the current energy crisis.
Created from Fastlane, WoS look-up

Shy Organic Photovoltaics: Digitally Printed Organic Solar Modules With Hidden Interconnects - Maisch, Philipp; Tam, Kai Cheong; Schilinsky, Pavel; Egelhaaf, Hans-Joachim; Brabec, Christoph (Solar RRL, 2018)
One of the biggest attractions of the organic photovoltaics (OPV) technology is the easiness with which it can be integrated. However, despite its semitransparency and wide variety of colors, a major unresolved challenge is to fabricate optically inconspicuous organic photovoltaic modules (OPV-M) that can be integrated into visually demanding products. This is dominantly due to the visual obstruction from Z-interconnection lines inherent to module processing with classical patterning methods. We now present for the first time a solution to this problem, which utilizes a visually seamless interconnection method to elegantly minimize the conspicuity of the interconnection regime. We realize such invisible interconnects by inkjet printing highly conductive silver lines, which penetrate the solar cell stack and form an electrical connection between adjacent cells. A combined characterization approach utilizing in-depth electrical characterization and finite element (FEM) simulation rationalizes the excellent electrical cell-to-cell contact established with this interconnection technology. We combine this technology with a variable-geometry module design into an innovative digital inkjet printing platform for the production of state-of-the art but visually attractive solar modules. The full potential of this concept is demonstrated by a fully inkjet printed arbitrarily shaped OPV-M portrait<br
Keywords: inkjet printing; organic photovoltaics; printed electronics; shy photovoltaics; upscaling

Side-Chain Engineering for Enhancing the Properties of Small Molecule Solar Cells: A Trade-off Beyond Efficiency - Min, Jie; Cui, Chaohua; Heumüller, Thomas; Fladischer, Stefanie; Cheng, Xiao; Spiecker, Erdmann; Li, Yongfang; Brabec, Christoph (Advanced Energy Materials, 2016)
Three small molecules with different substituents on bithienyl-benzo[1,2-b:4,5-b′]dithiophene (BDTT) units, BDTT-TR (meta-alkyl side chain), BDTT-O-TR (meta-alkoxy), and BDTT-S-TR (meta-alkylthio), are designed and synthesized for systematically elucidating their structure–property relationship in solution-processed bulk heterojunction organic solar cells. Although all three molecules show similar molecular structures, thermal properties and optical band gaps, the introduction of meta-alkylthio-BDTT as the central unit in the molecular backbone substantially results in a higher absorption coefficient, slightly lower highest occupied molecular orbital level and significantly more efficient and balanced charge transport property. The bridging atom in the meta-position to the side chain is found to impact the microstructure formation which is a subtle but decisive way: carrier recombination is suppressed due to a more balanced carrier mobility and BDTT based devices with the meta-alkylthio side chain (BDTT-S-TR) show a higher power conversion efficiency (PCE of 9.20%) as compared to the meta-alkoxy (PCE of 7.44% for BDTT-TR) and meta-alkyl spacer (PCE of 6.50% for BDTT-O-TR). Density functional density calculations suggest only small variations in the torsion angle of the side chains, but the nature of the side chain linkage is further found to impact the thermal as well as the photostability of corresponding devices. The aim is to provide comprehensive insight into fine-tuning the structure–property interrelationship of the BDTT material class as a function of side chain engineering.
Keywords: absorption coefficient; microstructure formation; photostability; side chain engineering; structure-property relationships

Silicon nitride and intrinsic amorphous silicon double antireflection coatings for thin-film solar cells on foreign substrates - Li, Da; Kunz, Thomas; Wolf, Nadine; Liebig, Jan Philipp; Wittmann, Stephan; Ahmad, Taimoor; Hessmann, Maik T.; Auer, Richard; Göken, Mathias; Brabec, Christoph (Thin Solid Films, 2015)
Hydrogenated intrinsic amorphous silicon (a-Si:H) was investigated as a surface passivationmethod for crystalline silicon thin film solar cells on graphite substrates. The results of the experiments, including quantumefficiency and current density-voltage measurements, show improvements in cell performance. This improvement is due to surface passivation by an a-Si:H(i) layer, which increases the open circuit voltage and the fill factor. In comparison with our previous work, we have achieved an increase of 0.6% absolute cell efficiency for a 40 μm thick 4 cm2 aperture area on the graphite substrate. The optical properties of the SiNx/a-Si:H(i) stack were studied using spectroscopic ellipsometer techniques. Scanning transmission electron microscopy inside a scanning electron microscope was applied to characterize the cross section of the SiNx/a-Si:H(i) stack using focus ion beam preparatio
Keywords: Amorphous silicon; Crystalline silicon thin film; Double layer antireflection coating; Focus ion beam; Graphite substrate; Scanning transmission electron microscopy; Surface passivation

Silicon/organic hybrid heterojunction infrared photodetector operating in the telecom regime - Bednorz, Mateusz; Matt, Gebhard; Glowacki, Eric D.; Fromherz, Thomas; Brabec, Christoph; Scharber, Markus C.; Sitter, Helmut; Sariciftci, N. Serdar (Organic Electronics, 2013)
The authors report on the fabrication of a silicon/organic heterojunction based IR photodetector. It is demonstrated that an Al/p-Si/perylene-derivative/ Al heterostructure exhibits a photovoltaic effect up to 2.7 μm (0.46 eV), a value significantly lower than the bandgap of either material. Although the devices are not optimized, at room temperature a rise time of 300 ns, a responsivity of ≈0.2 mA/W with a specific detectivity of D ≈ 7 × 10 Jones at 1.55 μm is found. The achieved responsivity is two orders of magnitude higher compared to our previous efforts [1,2]. It will be outlined that the photocurrent originates from an absorption mechanism involving excitation of an electron from the Si valence band into the extended LUMO state in the perylene-derivative, with possible participation of intermediate localized surface state in the organic material. The non-invasive deposition of the organic interlayer onto the Si results in compatibility with the CMOS process, making the presented approach a potential alternative to all inorganic device concepts.© 2013 Elsevier B.V. All rights reserved.
Keywords: Hybrid system; Infrared spectroscopy; Organic electronics; Photo-detector

Simulation of optical Properties of percolation type electrode for thin film solar cells with silver nanowires - Yan, Shuai; Krantz, Johannes; Pflaum, Christoph; Brabec, Christoph (Photonics for Solar Energy Systems IV, 2012)
Silver nanowire films are a newly introduced choice for transparent electrodes in thin film solar cells. Simulation is an adequate and economic method to analyse and predict the optical properties of these films. We simulate the optical behavior of such films by solving Maxwell equations. The simulation technique is a finite integration technique (FIT) combined with a time harmonic inverse iteration method (THIIM) to handle the negative permittivity of silver. Parallel computation on high performance computers(HPC) is used to meet the large computational requirement of the problem. In agreement to preliminary experimental results, the simulation results show that transmission of light is larger than expected by a simple ray-tracing model. © 2012 SPIE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.lsinfs.simula_8
Keywords: Ag NW films; Maxwell equations; Optical simulation; Parallel computation; Transparent electrodes

Single-Component Organic Solar Cells with Competitive Performance - He, Yakun; Li, Ning; Brabec, Christoph (Organic Materials, 2021)
Organic semiconductors with chemically linked donor and acceptor units can realize charge carrier generation, dissociation and transport within one molecular architecture. These covalently bonded chemical structures enable single-component organic solar cells (SCOSCs) most recently to start showing specific advantages over binary or multi-component bulk heterojunction concepts due to simplified device fabrication and a dramatically improved microstructure stability. The organic semiconductors used in SCOSCs can be divided into polymeric materials, that is, double-cable polymers, di-block copolymers as well as donor–acceptor small molecules. The nature of donor and acceptor segments, the length and flexibility of the connecting linker and the resultant nanophase separation morphology are the levers which allow optimizing the photovoltaic performance of SCOSCs. While remaining at 1–2% for over a decade, efficiencies of SCOSCs have recently witnessed significant improvement to over 6% for several materials systems and to a record efficiency of 8.4%. In this mini-review, we summarize the recent progress in developing SCOSCs towards high efficiency and stability, and analyze the potential directions for pushing SCOSCs to the next efficiency milestone.
Keywords: double-cable polymers; di-block copolymers; donor–acceptor small molecules; single-component organic solar cells; photovoltaic performance; device stability

Single-Layer Carbon Nitride as an Efficient Metal-Free Organic Electron-Transport Material with a Tunable Work Function - Saboor, Abdus; Stroyuk, Oleksandr; Raievska, Oleksandra; Liu, Chao; Hauch, Jens; Brabec, Christoph (Advanced Functional Materials, 2024)
Single-layer carbon nitride (SLCN) is introduced as a metal-free organic electron transport material (ETL) for organic solar cells, delivering a performance comparable to that of the benchmark nanocrystalline ZnO. SLCN is produced in the form of stable aqueous inks and can serve as an efficient electron transport layer for three different types of active layers, showing high stability to photodegradation. A lower conductivity of SLCN films as compared to ZnO is counter-balanced by their higher transparency and lower light scattering losses. The SLCN ETL provides a unique opportunity to tune the work function from ca. −4.1 to −4.6 eV by varying the annealing temperature due to partial thermal oxidation of the SLCN film. The PL band position follows the oxidation-induced changes of the work function allowing PL properties of SLCN to be used to predict the PV efficiency. The 2D structure of SLCN coupled with unique structural and compositional variability, and tunability of the work function show a high promise for emerging organic PV devices.
CRIS-Team Scopus Importer:2024-03-15
Keywords: 2D materials; charge transport materials; organic solar cells; polyheptazine

Single molecular precursor ink for AgBiS2 thin films: synthesis and characterization - Gu, Ening; Lin, Xianzhong; Tang, Xiaofeng; Matt, Gebhard; Osvet, Andres; Hou, Yi; Jäger, Sebastian; Xie, Chen; Karl, André; Hock, Rainer; Brabec, Christoph (Journal of Materials Chemistry C, 2018)
Recently, AgBiS2 has been demonstrated to be a promising non-toxic, earth-abundant absorber material for solar energy application. In this work, a novel route to deposit AgBiS2 thin films from single molecular precursor ink is presented. It is found that the amount of thiourea has a crucial impact on the formulation of a stable molecular ink. Understanding the coordination chemistry of the molecular precursor ink is important for getting better control over the thin film processing. With the assistance of Raman spectroscopy, possible complexation mechanisms and general coordination states within the molecular ink are studied. In addition, the influence of ink composition as well as the annealing temperature on the structure and morphology of resulting AgBiS2 films is systematically investigated. It is found that the crystallinity and particle size increase with higher annealing temperature. The obtained AgBiS2 thin films show a cubic structure with a preferred orientation in [111] direction. Optical and electrical measurements demonstrate that the obtained AgBiS2 is an indirect band gap material, which features two transition mechanisms with an indirect band gap of around 0.87 eV and a direct one of around 1.21 eV. The high absorption coefficient, low Urbach energy and fast transient photoconductivity confirm its potential as an absorber for photovoltaic applications.

Site-specific assessment of mechanical loads on photovoltaic modules from meteorological reanalysis data - Camus, Christian; Offermann, Pascal; Weissmann, Martin; Buerhop, Claudia; Hauch, Jens; Brabec, Christoph (Solar Energy, 2019)
This work demonstrates the capability of meteorological reanalysis data for estimating mechanical stresses due to wind gusts on photovoltaic modules. Besides the immediate power loss caused by the inactive solar cell areas within the module, the influence of cracks induced by such mechanical loads on the ageing and degradation behavior of PV modules is in the focus of current PV reliability research. To choose and/or design the optimum module for a given deployment site at the most economical cost, the mechanical loads the module will be exposed to during its service life need to be estimated. Hence, this paper introduces a new methodology for assessing and deducing site-specific mechanical load scenarios which are expected to be imposed on photovoltaic modules by wind gusts for a given location. The approach presented here is based on the linear calibration of meteorological reanalysis data with publicly available and standardized high-quality surface weather station data of local weather services. In this fashion, site-specific mechanical load scenarios can be deduced for virtually any site covered by the respective reanalysis data set. These scenarios can be used for developing site-specific module qualification tests, thereby providing a methodology enabling climate-specific module designs or specifications. This methodology can also be transferred to virtually any location and other climate and weather parameters such as snow loads, UV dose, etc. Hence a complete assessment of all weather-related degradation scenarios could be deduced eventually.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Degradation; Forecast; Mechanical load; Photovoltaics; Reanalysis; Wind gusts

Six metal cations in one double perovskite: exploring complexity of chloride elpasolites by high-throughput experimentation - Stroyuk, Oleksandr; Raievska, Oleksandra; Daum, Manuel; Hauch, Jens; Brabec, Christoph (Journal of Materials Chemistry C, 2024)
A high-throughput screening of lead-free double chloride perovskites Cs2MIMIIICl6 is performed combining combinatorial robot-assisted synthesis with accelerated structural and spectral characterizations. The screening encompasses about 350 elpasolite compounds with broad variations of the MIII site, including combinations of two (Bi + In, Bi + Sb, and In + Sb) and three cations (In + Bi + Sb and Fe + Bi + In). The robot-assisted open-environment synthesis protocol allows the double perovskites with these MIII combinations and Ag+/Na+-occupied MI site to be produced using a general routine in the form of single-phase microcrystalline solid solutions with reliably controlled composition. The high-throughput screening revealed a series of non-additive effects arising from the combination of multiple cations on the MIII site, including a “volcano”-shaped dependence of the photoluminescence quantum yield of Cs2(Ag,Na)(Bi,In)Cl6 elpasolites on Ag/Na and Bi/In ratio and band-bowing effects in the compositional dependences of the bandgaps of perovskites with Bi + Sb, In + Bi + Sb, and Fe + Bi + In combinations. In the latter case, the accelerated screening resulted in the double chloride perovskites with an unusually low indirect bandgap of 1.64 eV.
CRIS-Team Scopus Importer:2024-06-14

Solar cell fabricated on welded thin flexible silicon - Hessmann, Maik Thomas; Kunz, Thomas; Ahmad, Taimoor; Li, Da; Wittmann, Stephan; Riecke, Arne; Ebser, Jan; Terheiden, Barbara; Cvecek, Kristian; Schmidt, Michael; Auer, Richard; Brabec, Christoph (EPJ Photovoltaics, 2015)
We present a thin-film crystalline silicon solar cell with an AM1.5 efficiency of 11.5% fabricated on welded 50 μm thin silicon foils. The aperture area of the cell is 1.00 cm 2 . The cell has an open-circuit voltage of 570 mV, a short-circuit current density of 29.9 mA cm − 2 and a fill factor of 67.6%. These are the first results ever presented for solar cells on welded silicon foils. The foils were welded together in order to create the first thin flexible monocrystalline band substrate. A flexible band substrate offers the possibility to overcome the area restriction of ingot-based monocrystalline silicon wafers and the feasibility of a roll-to-roll manufacturing. In combination with an epitaxial and layer transfer process a decrease in production costs can be achieved.
Created from Fastlane, Scopus look-up

Solar spectral conversion for improving the photosynthetic activity in algae reactors - Wondraczek, Lothar; Batentschuk, Miroslaw; Schmidt, Markus A.; Borchardt, Rudolf; Scheiner, Simon; Seemann, Benjamin; Schweizer, Peter; Brabec, Christoph (Nature Communications, 2013)
Sustainable biomass production is expected to be one of the major supporting pillars for future energy supply, as well as for renewable material provision. Algal beds represent an exciting resource for biomass/biofuel, fine chemicals and CO storage. Similar to other solar energy harvesting techniques, the efficiency of algal photosynthesis depends on the spectral overlap between solar irradiation and chloroplast absorption. Here we demonstrate that spectral conversion can be employed to significantly improve biomass growth and oxygen production rate in closed-cycle algae reactors. For this purpose, we adapt a photoluminescent phosphor of the type Ca SrEuS, which enables efficient conversion of the green part of the incoming spectrum into red light to better match the Q peak of chlorophyll b. Integration of a Ca SrEuS backlight converter into a flat panel algae reactor filled with Haematococcus pluvialis as a model species results in significantly increased photosynthetic activity and algae reproduction rate. © 2013 Macmillan Publishers Limited. All rights reserved.

Solubility and miscibility for diluted polymers and their extension to organic semiconductors - Perea Ospina, Jose Dario; Langner, Stefan; Ameri, Tayebeh; Brabec, Christoph (Encyclopedia of Physical Organic Chemistry, 6 Volume Set, Band 1, 2017)

Solubility Based Identification of Green Solvents for Small Molecule Organic Solar Cells - Burgues-Ceballos, Ignasi; Machui, Florian; Min, Jie; Ameri, Tayebeh; Voigt, Monika M.; Luponosov, Yuriy N.; Ponomarenko, Sergei A.; Lacharmoise, Paul D.; Campoy-Quiles, Mariano; Brabec, Christoph (Advanced Functional Materials, 2014)
Replacing halogenated solvents in the processing of organic solar cells by green solvents is a required step before the commercialization of this technology. With this purpose, some attempts have been made, although a general method is yet to be developed. Here, the potential of the Hansen solubility parameters (HSP) analysis for the design of green ink formulations for solution-processed active layer in bulk heterojunction photovoltaic devices based on small molecules is demonstrated. The motivation of moving towards organic small molecules stems from their lower molecular weight and more definite structure which makes them more likely to be dissolved in a wider variety of organic solvents. In the first step, the HSP of selected active materials are determined, namely, the star-shaped D-π-A tris[4-[5′′-(1,1-dicyanobut-1-en-2-yl)-2,2′-bithiophen-5-yl]pheny]amine N(Ph-2T-DCN-Et)3 small molecule and fullerene derivative [6,6]-phenyl-C71-butyric acid methyl ester (PC70BM). Secondly, computer simulations based on HSP allow the prediction of suitable green solvents for this specific material system. The most promising green solvents, according to the simulations, are then used to fabricate solar cell devices using pristine solvents and two solvents mixtures. These devices show power conversion efficiencies around 3.6%, which are comparable to those obtained with halogenated solvents. This good performance is a result of the sufficient solubility achieved after a successful prediction of good (green) solvents.
Keywords: Hansen solubility parameters; ink formulations; non-halogenated solvents; organic photovoltaics; small molecule

Solubility, Miscibility, and the Impact on Solid-State Morphology - Brabec, Christoph; Machui, Florian (Wiley-VCH, 2013)
Keywords: Glass transition temperature; Miscibility; Organic semiconductors; Phase diagram; Solar cells; Solubility

Solution-coated barriers for organic electronics - Channa, Iftikhar Ahmed; Distler, Andreas; Brabec, Christoph; Egelhaaf, Hans-Joachim (Organic Flexible Electronics, 2021)
This chapter provides a review on solution processed barriers for flexible organic electronics. After elaborating on the necessity for encapsulation of organic devices by describing the degradation mechanisms caused by oxygen and water, the state of the art of vacuum-deposited barriers is briefly addressed as it presently defines the benchmark of barrier technology. Subsequently, the fundamentals of permeation of gases through barriers and the characterization methods for barrier performance are described. The main part of the chapter gives an overview of the material systems used for manufacturing solution-processed barriers. We start with the methods relying on reducing diffusion and solubility coefficients of oxygen and water in barrier films. Subsequently, barriers based on tortuosity and barriers based on covering substrates with layers of zero or very low permeability are described. Finally, the role of getters is elucidated. The chapter is concluded with highlighting some of the present challenges in the field of solution processed flexible barriers.<br
Keywords: Flexible barriers; flexible electronics; flexible packaging; organic photovoltaics; organic light emitting diodes; OLED; OPV; OFET; device lifetime; accelerated ageing

Solution-Growth Liquid-Phase Epitaxy of CsPbBr3 on NaCl by Optimizing the Substrate Dissolution - Elia, Jack; Levchuk, Ievgen; Hou, Yi; Matt, Gebhard; These, Albert; Zhao, Yicheng; Zhang, Jiyun; Forberich, Karen; Osvet, Andres; Götz, Klaus; Prihoda, Annemarie; Wu, Mingjian; et al. (Journal of Physical Chemistry C, 2023)
Since the earliest days of liquid-phase epitaxy (LPE) research, substrate stability has been a prerequisite for investigating nucleation and epitaxial growth. For flux- and melt-growth LPE, soluble substrates have always been viewed as problematic and difficult. However, solution-growth LPE transforms this disadvantage into a benefit by facilitating the creation of graded interfaces. In this study, we investigated the nucleation and growth of solution-grown LPE in the evaporation mode of soluble CsPbBr3 on freshly cleaved NaCl single-crystal substrates. Only two of the four main types of CsPbBr3 crystallization observed are epitaxial. The microscopic observation of composition gradients at the interface of CsPbBr3 grains and substrates reveals a promising opportunity to manipulate the lattice constant at the interface by simply controlling the temperature and concentration.
CRIS-Team Scopus Importer:2023-12-08

Solution-Processed Metallic Nanowire Electrodes as Indium Tin Oxide Replacement for Thin-Film Solar Cells - Krantz, Johannes; Richter, Moses; Spallek, Stefanie; Spiecker, Erdmann; Brabec, Christoph (Advanced Functional Materials, 2011)
Solution processed silver nanowire (Ag NW) films are introduced as transparent electrodes for thin-film solar cells. Ag NW electrodes were processed by doctor blade-coating on glass substrates at moderate temperatures (less than 100 degrees C). The morphological, optical, and electrical characteristics of these electrodes were investigated as a function of processing parameters. For solar-cell application, Ag NW electrodes with an average transparency of 90% between 450 and 800 nm and a sheet resistivity of 10 O per square were chosen. The performance of poly(3-hexylthiophen-2,5-diyl):[6,6]-phenyl-C61-butyric acid methyl ester (P3HT:PCBM) solar cells on Ag NW electrodes was found to match the performance of otherwise identical cells on indium tin oxide. Overall, P3HT:PCBM solar cells with an efficiency of 2.5% on transparent Ag NW electrodes have been realized.
Keywords: silver nanowires; electrodes; organic electronics; indium tin oxide replacement; solar cells

Solution processed oxygen and moisture barrier based on glass flakes for encapsulation of organic (opto-) electronic devices - Channa, Iftikhar Ahmed; Distler, Andreas; Scharfe, Benedikt; Feroze, Sarmad; Forberich, Karen; Lipovsek, Benjamin; Brabec, Christoph; Egelhaaf, Hans-Joachim (Flexible and Printed Electronics, 2021)
The concept of transparent barriers against oxygen and water based on polymer films filled with glass flakes is presented. Barriers are prepared by casting polyvinyl butyral (PVB) films containing glass flakes of different aspect ratios (ARs) at different loadings to systematically study the effect of these parameters on barrier quality and optical transmission. It is found that the glass flakes are distributed homogeneously in the PVB film, with an almost perfect orientation of the long axes of the platelets parallel to the film surface. For glass flakes having an AR of 2000, barrier films with optical transmittance exceeding 85% and water vapor transmission rates of 0.14 g m(-2) d(-1) are obtained at a glass loading of 25 vol%. The haze of the glass flake filled PVB films, which is mainly due to surface roughness of the films according to optical simulations, is reduced by coating a smoothing layer on top. The barrier properties persist even after 20 000 cycles of bending at a radius of 3 cm. The lifetime of organic solar cells increases to beyond 1000 h under damp heat conditions as well as under constant illumination, when the devices are encapsulated with the PVB/glass flake composite films.
CRIS-Team WoS Importer:2021-06-25
Keywords: optical simulations; organic solar cell encapsulation; flexible barriers; glass flakes; polyvinyl butyral

Solution-Processed Parallel Tandem Polymer Solar Cells Using Silver Nanowires as Intermediate Electrode - Guo, Fei; Kubis, Peter; Li, Ning; Przybilla, Thomas; Matt, Gebhard; Stubhan, Tobias; Ameri, Tayebeh; Butz, Benjamin; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (Acs Nano, 2014)
Tandem architecture is the most relevant concept to overcome the efficiency limit of single-junction photovoltaic solar cells. Series-connected tandem polymer solar cells (PSCs) have advanced rapidly during the past decade. In contrast, the development of parallel-connected tandem cells is lagging far behind due to the big challenge in establishing an efficient interlayer with high transparency and high in-plane conductivity. Here, we report all-solution fabrication of parallel tandem PSCs using silver nanowires as intermediate charge collecting electrode. Through a rational interface design, a robust interlayer is established, enabling the efficient extraction and transport of electrons from subcells. The resulting parallel tandem cells exhibit high fill factors of similar to 60% and enhanced current densities which are identical to the sum of the current densities of the subcells. These results suggest that solution-processed parallel tandem configuration provides an alternative avenue toward high performance photovoltaic devices.
Keywords: parallel-tandem; polymer solar cells; solution-processed; silver nanowires

Solvent engineering of scalable deposited wide-bandgap perovskites for efficient monolithic perovskite-organic tandem solar cells - Tang, Yun; Zhang, Yuchao; Zhou, Xinming; Huang, Ting; Shen, Kai; Zhang, Kang Ning; Du, Xiaoyan; Shi, Tingting; Xiao, Xiudi; Li, Ning; Brabec, Christoph; Mai, Yaohua; et al. (Nano Energy, 2023)
High-quality wide-bandgap perovskite films are a key component in constructing efficient tandem solar cells. Although the efficiency of perovskite tandem devices advances rapidly in recent years, the majority of wide-bandgap perovskite films are deposited by laboratory spin-coating, which greatly hinders their commercial viability. Here, we first show that the widely-used binary solvents (DMF:DMSO) in spin-coating are incapable of producing qualified wide-bandgap perovskite films by scalable methods. It is identified that dense and uniform wide-bandgap thin films can be deposited from single-solvent NMP by blade-coating, which is mainly related to the well-controlled crystallization kinetics enabled by the formation of stable intermediate adduct. Along with a rational passivation by constructing a 2D/3D layered heterojunction, inverted perovskite devices with a bandgap of 1.8 eV deliver a champion efficiency of 18.92 %. On this basis, monolithic perovskite-organic tandem solar cells with an efficient and robust interconnection layer of “SnO2/Au/PEDOT:PSS” are fabricated, yielding a high efficiency of 22.25 % along with an impressive open-circuit voltage of 2.1 V. These results demonstrate an important step toward scalable fabrication of monolithic perovskite-organic tandem solar devices.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Blade coating; Perovskite-organic; Solvent engineering; Tandem solar cells; Wide-bandgap

Special section guest editorial: Solution-processable organic solar cells - Brabec, Christoph; Ameri, Tayebeh (Journal of Photonics for Energy, 2015)

Spontaneous alloying of ultrasmall non-stoichiometric Ag-In-S and Cu-In-S quantum dots in aqueous colloidal solutions - Stroyuk, Oleksandr; Raievska, Oleksandra; Solonenko, Dmytro; Kupfer, Christian; Osvet, Andres; Batentschuk, Miroslaw; Brabec, Christoph; Zahn, Dietrich R. T. (RSC Advances, 2021)
The effect of spontaneous alloying of non-stoichiometric aqueous Ag-In-S (AIS) and Cu-In-S (CIS) quantum dots (QDs) stabilized by surface glutathione (GSH) complexes was observed spectroscopically due to the phenomenon of band bowing typical for the solid-solution Cu(Ag)-In-S (CAIS) QDs. The alloying was found to occur even at room temperature and can be accelerated by a thermal treatment of colloidal mixtures at around 90 °C with no appreciable differences in the average size observed between alloyed and original individual QDs. An equilibrium between QDs and molecular and clustered metal-GSH complexes, which can serve as “building material” for the new mixed CAIS QDs, during the spontaneous alloying is assumed to be responsible for this behavior of GSH-capped ternary QDs. The alloying effect is expected to be of a general character for different In-based ternary chalcogenides.
CRIS-Team Scopus Importer:2021-07-23

Spontaneously Self-Assembly of a 2D/3D Heterostructure Enhances the Efficiency and Stability in Printed Perovskite Solar Cells - Hu, Jinlong; Wang, Chuan; Qiu, Shudi; Zhao, Yicheng; Gu, Ening; Zeng, Linxiang; Yang, Yuzhao; Li, Chaohui; Liu, Xianhu; Forberich, Karen; Brabec, Christoph; Nazeeruddin, Mohammad Khaja; et al. (Advanced Energy Materials, 2020)
As perovskite solar cells (PSCs) are highly efficient, demonstration of high-performance printed devices becomes important. 2D/3D heterostructures have recently emerged as an attractive way to relieving the film inhomogeneity and instability in perovskite devices. In this work, a 2D/3D ensemble with 2D perovskites self-assembled atop 3D methylammonium lead triiodide (MAPbI3) via a one-step printing process is shown. A clean and flat interface is observed in the 2D/3D bilayer heterostructure for the first time. The 2D perovskite capping layer significantly suppresses nonradiative charge recombination, resulting in a marked increase in open-circuit voltage (VOC) of the devices by up to 100 mV. An ultrahigh VOC of 1.20 V is achieved for MAPbI3 PSCs, corresponding to 91% of the Shockley–Queisser limit. Moreover, notable enhancement in light, thermal, and moisture stability is obtained as a result of the protective barrier of the 2D perovskites. These results suggest a viable approach for scalable fabrication of highly efficient perovskite solar cells with enhanced environmental stability.
CRIS-Team Scopus Importer:2020-03-27
Keywords: 2D/3D heterojunctions; high efficiency; perovskite solar cells; self-assembly; stability

Spray-Coated Organic Photodetectors and Image Sensors with Silicon-Like Performance - Biele, Markus; Montenegro Benavides, Cindy; Hürdler, Judith; Tedde, Sandro F.; Brabec, Christoph; Schmidt, Oliver (Advanced Materials Technologies, 2018)
Solution-processed bulk heterojunction based organic photodiodes are ideal candidates for large-area light sensing. Here, spray-coated large-area organic photodiodes based on a novel polymer (Lisicon PV-D4650) with dark current densities down to 34 pA cm−2 and a maximum responsivity of ≈0.44 A W−1@660 nm under reverse bias conditions of −5 V are reported. These values are comparable to commercially available state-of-the-art solid-state photodetectors. Furthermore, cutoff frequencies of 50 kHz and a linear dynamic range exceeding eight orders of magnitude or ≥160 dB are achieved. The usage of 1,8-diiodooctane as processing additive for spray coating vastly reduces the surface roughness of spray-coated organic photodiodes which facilitates the preparation of large-area light sensors and image sensors. © 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinhe
Keywords: surface roughness; responsivity; spray coating; OPD; imaging

Spray-Coated Silver Nanowires as Top Electrode Layer in Semitransparent P3HT:PCBM-Based Organic Solar Cell Devices - Krantz, Johannes; Stubhan, Tobias; Richter, Moses; Spallek, Stefanie; Litzov, Ivan; Matt, Gebhard; Spiecker, Erdmann; Brabec, Christoph (Advanced Functional Materials, 2013)
Silver nanowire (Ag NW) thin films are investigated as top electrodes in semitransparent inverted organic solar cells. The performance of semitransparent poly(3-hexylthiophene-2,5-diyl):[6,6]-phenyl-C61-butyric acid methyl ester (P3HT:PCBM) organic solar cells with Ag NW top electrode layers is found to match very closely the performance of reference devices based on thermally evaporated, highly reflective metal silver top electrodes. The optical losses of the semitransparent electrodes are investigated in detail and analyzed in terms of transmission, scattering, and reflection losses. The impact on an external back reflector is shown to increase the light harvesting efficiency of optically thin devices. Further analysis of transparent devices under illumination from the indium tin oxide (ITO) backside and through the Ag NW front electrode open the possibility to gain deep insight into the vertical microstructure related devices performance. Overall, Ag NW top electrodes are established as a serious alternative to TCO based electrodes. Semitransparent devices with efficiencies of over = 2.0% are realized.
Keywords: silver nanowires; electrodes; semitransparent photovoltaic devices; organic electronics; spray deposition

Squeezing the Threshold of Metal-Halide Perovskite Micro-Crystal Lasers Grown by Solution Epitaxy - Zhou, Shuyu; Rehm, Viktor; Afify, Hany A.; Feng, Yufei; Korczak, Jędrzej; Szczerbakow, Andrzej; Story, Tomasz; Peng, Zijian; These, Albert; Barabash, Anastasiia; Osvet, Andres; Brabec, Christoph; et al. (Advanced Functional Materials, 2024)
Metal halide perovskite semiconductors have demonstrated remarkable progress not only in photovoltaics and X-ray detection but also in laser technologies. Particularly appealing is the simplicity with which micro-crystallites can be epitaxially grown, thereby forming micro-resonators suitable for lasing. Here, the laser threshold is optimized by selecting excitation laser parameters and by improving material quality. The latter process is conducted for formamidinium lead tribromide, emitting in the green spectral range. Depending on the growth method and parameters, the sizes of the micro-resonators can be tuned between ≈3 and 23 micrometers. Under laser excitation systematically lower thresholds are observed for micro-resonators in the 4–7 micrometer size range, than for larger ones, irrespective of growth method. Among three optimized growth methods, epitaxial growth via antisolvent vapor-assisted crystallization exhibits the smallest threshold powers, indicating the highest material quality. This conclusion is supported by hyperspectral microscopic luminescence imaging and by transient photoluminescence. The best laser structures exhibit record threshold powers for epitaxially grown perovskites, indicating that the selected antisolvent vapor epitaxial growth holds great promises also for other perovskite materials.
CRIS-Team Scopus Importer:2024-05-10
Keywords: FAPbBr; lasing; micro-resonators; perovskites; solution epitaxy

Stabilization of aluminum doped zinc oxide nanoparticle suspensions and their application in organic solar cells - Wolf, N.; Stubhan, Tobias; Manara, J.; Dyakonov, Vladimir; Brabec, Christoph (Thin Solid Films, 2014)
Aluminum doped zinc oxide (AZO) nanoparticles were redispersed in isopropyl alcohol and stabilized with different stabilizers and mixtures of stabilizers that allow for electronically functional particles. The size of the redispersed nanoparticles was small enough to use these suspensions to build interfacial layers in inverted polymer-fullerene solar cells. The performance of these devices was found to depend on the stabilizer used in the nanoparticle suspension. The best performance was obtained with an AZO interfacial layer built with a 3,6,9-trioxadecanoic acid and polyvinylpyrrolidone stabilized nanoparticle suspension. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Aluminum doped zinc oxide; Nanoparticle suspensions; Interfacial layers; Inverted polymer-fullerene solar cells

Standardization as an Instrument to Accelerate the Development of Stable Emerging Photovoltaic Technologies—The IEC TS 62876-2-1:2018—Technical Specification for the Stability Testing of Photovoltaic Devices Enabled by Nanomaterials - Hauch, Jens; Brabec, Christoph; Fabricius, Norbert; Bergholz, Werner (Energy Technology, 2020)
For new photovoltaic (PV) technologies the improvement and quantification of stability is a significant challenge. Accelerated aging tests are usually applied to shorten development times. While many of these tests exist, there is no standard that can serve as a guideline for choosing relevant tests and applying them correctly to achieve comparability between results. With the IEC TS 62876-2-1:2018 for the first time, a standard has been developed which defines the most significant testing protocols for stability. This standard is designed especially for third-generation PV technologies that utilize nanomaterials but may be applied to any other new PV technologies as well. The standard defines the relevant stresses, recommends values for testing, defines seven standard tests, and provides reporting requirements for documentation. As a stability criterion the time t80, the time it takes for a measured efficiency of a device to reach 80% of the initial efficiency during the testing, is applied. A wide adoption of the tests outlined in the IEC TS 62876 significantly shortens development times and decreases the time to market for emerging PV technologies.
CRIS-Team Scopus Importer:2020-08-14
Keywords: nano-enabled photovoltaic devices; photovoltaics; stabilities; standards; technical specifications

Star-shaped D-π-A oligothiophenes with a tris(2-methoxyphenyl)amine core and alkyldicyanovinyl groups: synthesis and physical and photovoltaic properties - Luponosov, Yuriy N.; Min, Jie; Solodukhin, Alexander N.; Bakirov, Artem V.; Dmitryakov, Petr V.; Shcherbina, Maxim A.; Peregudova, Svetlana M.; Cherkaev, Georgiy V.; Chvalun, Sergei N.; Brabec, Christoph; Ponomarenko, Sergei A. (Journal of Materials Chemistry C, 2016)
Synthesis of a series of star-shaped oligomers having a novel electron donating tris(2-methoxyphenyl)amine (m-TPA) core, which is linked through a bithiophene or terthiophene extgreekp-bridge with electron-deficient alkyldicyanovinyl (alkyl-DCV) groups, is described. A comprehensive study of the oligomers revealed significant dependence of their physical properties, including absorption, molecular frontier energy levels, crystal packing, and melting and glass transition temperatures, upon the chemical structure. A comparison of their photophysical properties to the nearest analog having the common dicyanovinyl (DCV) groups demonstrated a number of benefits to use alkyl-DCV units for the design of donor–acceptor small molecules: higher solubility, increased electrochemical stability, better photovoltaic performance, and possibility to control the relative physical and photovoltaic properties by a simple adjustment of alkyl and extgreekp-bridge lengths. Modification of the well-known triphenylamine (TPA) core in the star-shaped oligomers by methoxy groups increases not only solubility, but also crystallinity of the oligomers, whereas their photovoltaic performance stays on a similar level as their analogs with a TPA core. The study demonstrates that these design strategies represent interesting and simple tools for the effective modulation of properties of star-shaped molecules.
EAM Import::2019-03-13
Keywords: Engineering controlled terms: Crystal structure; Glass transition; Molecules; Oligomers; Solubility Design strategies; Electrochemical stabilities; Electron-deficient; Electron-donating; Photophysical properties; Photovoltaic performance; Photovoltaic property; Star-shaped molecules Engineering main heading: Stars

Statistical Analysis of Infrared-Inspections of PV-Plants - Buerhop, Claudia; Pickel, Tobias; Scheuerpflug, Hans; Hauch, Jens; Camus, Christian; Brabec, Christoph (33rd European Photovoltaic Solar Energy Conference and Exhibition, 2017)
First statistical evaluation of IR-inspections of PV-plants reveals that 81% of the installed PV-plants show IR-abnormalities. More than 140 PV-plants with more than 200,000 PV-modules were inspected and evaluated statistically. Main IR-abnormalities or failures in modules and string installations are analyzed, respectively. The average failure rate for PV-modules is about 6% and for module strings approximately 1%. The differentiation based on the installation type reveals that small residential installations relatively seen show more defective modules than large field installations. A first estimation of the missed income by not detecting and maintaining major module and plant failures yield a missed income of about 100 Mio. EUR considering the PV-systems installed in Germany. IR-imaging is a valuable method to give fast and reliable information about the actual quality and failure rate in inspected PV-installations.
Keywords: Performance; IR Imaging; Statistics; Failure

Statistical overview of findings by IR-inspections of PV-plants - Buerhop, Claudia; Pickel, Tobias; Scheuerpflug, Hans; Camus, Christian; Hauch, Jens; Brabec, Christoph (Proceedings of SPIE - The International Society for Optical Engineering, 2016)
First statistical evaluation of IR-inspections of PV-plants reveals that 86% of the installed PV-plants show IR-Abnormalities. More than 120 PV-plants with more than 160,000 PV-modules were inspected and evaluated statistically. Main IR-Abnormalities or failures in modules and string installations are analyzed, respectively. The average failure rate for PV-modules is about 8% and for module strings approximately 4%. The differentiation between the installation locations reveals that small residential installation show relatively more defective modules than large field installations.-Therefore, IR-imaging is a valuable method to give fast and reliable information about the actual quality and failure rate in inspected PV-installations.
Keywords: Defects; Failure; IR-images; PV-modules; Statistics; Substrings

Steric Engineering Enables Efficient and Photostable Wide-Bandgap Perovskites for All-Perovskite Tandem Solar Cells - Wen, Jin; Zhao, Yicheng; Liu, Zhou; Gao, Han; Lin, Renxing; Wan, Sushu; Ji, Chenglong; Xiao, Ke; Gao, Yuan; Tian, Yuxi; Xie, Jin; Brabec, Christoph; et al. (Advanced Materials, 2022)
Wide-bandgap (WBG, ≈1.8 eV) perovskite is a crucial component to pair with narrow-bandgap perovskite in low-cost monolithic all-perovskite tandem solar cells. However, the stability and efficiency of WBG perovskite solar cells (PSCs) are constrained by the light-induced halide segregation and by the large photovoltage deficit. Here, a steric engineering to obtain high-quality and photostable WBG perovskites (≈1.8 eV) suitable for all-perovskite tandems is reported. By alloying dimethylammonium and chloride into the mixed-cation mixed-halide perovskites, wide bandgaps are obtained with much lower bromide contents while the lattice strain and trap densities are simultaneously minimized. The WBG PSCs exhibit considerably improved performance and photostability, retaining >90% of their initial efficiencies after 1000 h of operation at maximum power point. With the triple-cation/triple-halide WBG perovskites enabled by steric engineering, a stabilized power conversion efficiency of 26.0% in all-perovskite tandem solar cells is further obtained. The strategy provides an avenue to fabricate efficient and stable WBG subcells for multijunction photovoltaic devices.
CRIS-Team Scopus Importer:2022-06-03
Keywords: all-perovskite tandem solar cells; lattice strain; light-induced halide segregation; steric engineering; wide-bandgap perovskite solar cells

Strain-activated light-induced halide segregation in mixed-halide perovskite solids - Zhao, Yicheng; Miao, Peng; Elia, Jack; Hu, Huiying; Wang, Xiaoxia; Heumüller, Thomas; Hou, Yi; Matt, Gebhard; Osvet, Andres; Chen, Yu-Ting; Tarragó, Mariona; de Ligny, Dominique; et al. (Nature Communications, 2020)
Light-induced halide segregation limits the bandgap tunability of mixed-halide perovskites for tandem photovoltaics. Here we report that light-induced halide segregation is strain-activated in MAPb(I1−xBrx)3 with Br concentration below approximately 50%, while it is intrinsic for Br concentration over approximately 50%. Free-standing single crystals of CH3NH3Pb(I0.65Br0.35)3 (35%Br) do not show halide segregation until uniaxial pressure is applied. Besides, 35%Br single crystals grown on lattice-mismatched substrates (e.g. single-crystal CaF2) show inhomogeneous segregation due to heterogenous strain distribution. Through scanning probe microscopy, the above findings are successfully translated to polycrystalline thin films. For 35%Br thin films, halide segregation selectively occurs at grain boundaries due to localized strain at the boundaries; yet for 65%Br films, halide segregation occurs in the whole layer. We close by demonstrating that only the strain-activated halide segregation (35%Br/45%Br thin films) could be suppressed if the strain is properly released via additives (e.g. KI) or ideal substrates (e.g. SiO2).<br

Structural fluctuations cause spin-split states in tetragonal (CH₃NH₃)PbI₃ as evidenced by the circular photogalvanic effect - Niesner, Daniel; Hauck, Martin; Shrestha, Shreetu; Levchuk, Ievgen; Matt, Gebhard; Osvet, Andres; Batentschuk, Miroslaw; Brabec, Christoph; Weber, Heiko B.; Fauster, Thomas (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Lead halide perovskites are used in thin-film solar cells, which owe their high efficiency to the long lifetimes of photocarriers. Various calculations find that a dynamical Rashba effect could significantly contribute to these long lifetimes. This effect is predicted to cause a spin splitting of the electronic bands of inversion-symmetric crystalline materials at finite temperatures, resulting in a slightly indirect band gap. Direct experimental evidence of the existence or the strength of the spin splitting is lacking. Here, we resonantly excite photocurrents in single crystalline (CH3NH3)PbI3 with circularly polarized light to clarify the existence of spin splittings in the band structure. We observe a circular photogalvanic effect, i.e., the photocurrent depends on the light helicity, in both orthorhombic and tetragonal (CH3NH3)PbI3. At room temperature, the effect peaks for excitation photon energies ΔE=110 meV below the direct optical band gap. Temperature-dependent measurements reveal a sign change of the effect at the orthorhombic extendashtetragonal phase transition, indicating different microscopic origins in the two phases. Within the tetragonal phase, both ΔE and the amplitude of the circular photogalvanic effect increase with temperature. Our findings support a dynamical Rashba effect in this phase, i.e., a spin splitting caused by thermally induced structural fluctuations which break inversion symmetr
Keywords: organic–inorganic perovskite; lead halide perovskite; circular photogalvanic effect; dynamical Rashba; Rashba effect

Structure and linkage assessment of T-shaped Pyrrolidine[60]Fullerene- and Isoxazoline[60]Fullerene-BODIPY-triarylamine hybrids - Rocha-Ortiz, Juan S.; Montalvo-Acosta, Joel José; He, Yakun; Insuasty, Alberto; Hirsch, Andreas; Brabec, Christoph; Ortiz, Alejandro (Dyes and Pigments, 2023)
Eight novel C60-BODIPY-Triarylamine electroactive triads have been synthesized and characterized. Using pyrrolidine (PIR and BDPF series) and isoxazoline (ISO series) as linkers between the fullerene and the BODIPY-Triarylamine (-TAA) system, the effect of these linkers along with different functionalization on the TAA on the electronic properties were studied. Moreover, their photophysical and electrochemical properties were investigated by comparing them to the reference substances BDP, 10a, 10b, and C60. All C60-BODIPY-TAA derivatives absorb visible light strongly in a range between 535 and 563 nm, and photoexcitation of the BODIPY unit causes photo-induced electron transfer, producing the corresponding charge-separated species, which was confirmed by solvatochromic effects on fluorescence measurements. The direction of charge transfer was also revealed by their redox potentials. A better electron affinity was observed for the ISO series when compared with PIR and BDPF. Thermogravimetric analysis showed that the pyrrolidine derivatives are more stable than their isoxazoline analogs and the insertion of alkoxy units in the triads triggers a better thermal endurance in the studied compounds.
CRIS-Team Scopus Importer:2023-06-30
Keywords: BODIPY dyes; Electron transfer; Isoxazoline[60]Fullerene; Pyrrolidine[60]Fullerene; Triarylamines

Sub-bandgap photon harvesting for organic solar cells via integrating up-conversion nanophosphors - Chen, Wei; Hou, Yi; Osvet, Andres; Guo, Fei; Kubis, Peter; Batentschuk, Miroslaw; Winter, Benjamin; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (Organic Electronics, 2015)
Lanthanide-doped up-conversion nanophosphors were employed as up-conversion converters (UC-converters) combined with organic solar cells (OSCs). The optical properties of the external up-conversion layers were investigated, and the optimized layers were laminated with OSCs. Strong photocurrents were observed when OSCs with an UC converter were illuminated by a NIR laser. An improvement of photocurrent and efficiency were also observed under AM 1.5 G sun irradiation. Our investigations show a proof-of-concept that organic solar cells could utilize sub-bandgap photons via integrating up-conversion nanophosphors, which provide us a promising approach to exceed the efficiency limit of single junction organic solar cells.
Keywords: IR light harvesting; Nanophosphors; Organic photovoltaics; Up-conversion

Suppressing Nonradiative Losses in Wide-Band-Gap Perovskites Affords Efficient and Printable All-Perovskite Tandem Solar Cells with a Metal-Free Charge Recombination Layer - Zhou, Xinming; Lai, Hongwei; Huang, Ting; Chen, Chaoran; Xu, Zhenhua; Yang, Yuzhao; Wu, Shaohang; Xiao, Xiudi; Chen, Lang; Brabec, Christoph; Mai, Yaohua; Guo, Fei (ACS Energy Letters, 2023)
Although the efficiencies of all-perovskite tandem solar cells have surpassed 26%, further advancement of device performance is constrained by the large photovoltage deficit in wide-band-gap perovskite subcells. Meanwhile, state-of-the-art charge recombination layers incorporate an additional thin metal film (Au or Ag), which not only complexes device fabrication but induces parasitic optical losses. Here, we first fabricate efficient wide-band-gap perovskite solar cells (PSCs) with by suppressing nonradiative losses both in bulk material and at interface. The prepared PSCs with a band gap of 1.71 eV yield an impressive open-circuit voltage (VOC) of 1.27 V, giving a small VOC deficit of 0.44 V and an efficiency of 20.8%. We then fabricate monolithic all-printed perovskite tandem devices by constructing a metal-free recombination layer, which yields an efficiency of 23.65% and a high VOC of 2.05 V. This work offers a simple yet effective charge recombination architecture for advancing the performance of all-perovskite tandem devices.
CRIS-Team Scopus Importer:2023-02-03

Suppressing Nonradiative Recombination in Lead-Tin Perovskite Solar Cells through Bulk and Surface Passivation to Reduce Open Circuit Voltage Losses - Zhang, Kaicheng; Späth, Andreas; Almora, Osbel; Le Corre, Vincent Marc; Wortmann, Jonas; Zhang, Jiyun; Xie, Zhiqiang; Barabash, Anastasiia; Hammer, Maria; Heumüller, Thomas; Min, Jie; Fink, Rainer; et al. (ACS Energy Letters, 2022)
Lead-Tin perovskite solar cells (Pb/Sn PSCs) are limited by the intrinsic instability of Sn(II), which tends to oxidize forming Sn vacancies in perovskite films. Herein, a Lewis base β-guanidinopropionic acid (GUA) and hydrazinium iodide (HAI) are introduced to effectively passivate the perovskite bulk and surface, respectively. The synergistic approach leads to Pb/Sn PSCs with a promising power conversion efficiency of 20.5% owing to the significantly reduced nonradiative recombination and voltage losses. As a result, the VOC × FF product of PSCs is significantly improved, which is among the highest values documented in the literature, being favorable for perovskite-based tandem applications. Additionally, the strategy demonstrated in this work could also improve the stability of PSCs by enhancing the chemical robustness of the perovskite layer. These results emphasize the significance of bulk and surface passivation in the development of efficient and stable PSCs based on Pb/Sn perovskites.
CRIS-Team Scopus Importer:2022-09-30

Suppressing photooxidation of conjugated polymers and their blends with fullerenes through nickel chelates - Salvador, Michael; Gasparini, Nicola; Perea, Jose Dario; Paleti, Harish; Distler, Andreas; Inasaridze, Liana N.; Troshin, Pavel A.; Luer, Larry; Egelhaaf, Hans-Joachim; Brabec, Christoph (Energy and Environmental Science, 2017)
Conjugated polymer semiconductors offer unique advantages over conventional semiconductors but tend to suffer from electro-optic performance roll-off, mainly due to reduced photofastness. Here, we demonstrate that the commodity nickel chelate nickel(ii) dibutyldithiocarbamate, Ni(dtc)2, effectively inhibits photooxidation across a wide range of prototypical π-conjugated polymer semiconductors and blends. The addition of 2-10 wt% of Ni(dtc)2 increases the resilience of otherwise quickly photobleaching semiconducting thin films, even in the presence of detrimental, radical forming processing additives. Using electron spin resonance spectroscopy and sensitive oxygen probes, we found that Ni(dtc)2 acts as a broadband stabilizer that inhibits both the formation of reactive radicals and singlet oxygen. The mechanism of stabilization is of sacrificial nature, but contains non-sacrificial contributions in polymers where singlet oxygen is a key driver of photooxidation. Ultrafast pump-probe spectroscopy reveals quenching of triplet excited states as the central mechanism of non-sacrificial stabilization. When introduced into the active layer of organic photovoltaic devices, Ni(dtc)2 retards the short circuit current loss in air without affecting the sensitive morphology of bulk heterojunctions and without major sacrifices in semiconductor properties. Antioxidants based on nickel complexes thus constitute functional stabilizers for elucidating degradation mechanisms in organic semiconductors and represent a cost-effective route toward organic electronic appliances with extended longevity. © 2017 The Royal Society of Chemistry.
Keywords: Engineering controlled terms: ChelationCost effectivenessDegradationElectron spin resonance spectroscopyHeterojunctionsMagnetic momentsNickelOxygenPhotobleachingPhotooxidationPolymer blendsProbesSemiconducting filmsSemiconductor devicesSpectroscopyStabilization Compendex keywords Degradation mechanismElectro-optic performanceOrganic electronicsOrganic photovoltaic devicesPolymer semiconductorsSemiconducting thin filmsSemiconductor propertiesUltrafast pump-probe spectroscopy Engineering main heading: Conjugated polymers

Suppressing photo-oxidation of non-fullerene acceptors and their blends in organic solar cells by exploring material design and employing friendly stabilizers - Guo, Jing; Wu, Yao; Sun, Rui; Wang, Wei; Guo, Jie; Wu, Qiang; Tang, Xiaofeng; Sun, Chenkai; Luo, Zhenghui; Chang, Kai; Zhang, Zhuohan; Yuan, Jun; et al. (Journal of Materials Chemistry A, 2019)
In addition to a high power conversion efficiency, ambient stability is another impact factor for the successful commercialization of organic solar cells (OSCs). Understanding the role of photovoltaic materials is the key to address this challenge, but no such studies have been systematically performed on non-fullerene acceptors (NFAs). In this work, we firstly investigate the role of NFA photo-oxidation in device degradation. Relevant investigation of physical dynamics underlines the effects on the device performance for NFA photo-oxidation acting as trap states in exposed blends. In addition, taking ITIC as an example, we shed some light on the possible mechanisms of NFA photo-oxidation, which cannot be eliminated by relevant strategies and principles of material design. These results drive us to further investigate the photobleaching rates of thirty-three NFAs, including fused-ring electron acceptors and perylene diimide acceptor derivatives. Surprisingly, most of them show a higher optical density loss as compared to their fullerene-based counterparts. In view of relevant comparative analysis in the Discussion section, we further propose some design strategies to improve the photo-oxidation stability of NFAs. More importantly, we also find a stabilizer (namely nickel chelate S6) that can effectively suppress the photo-oxidation of NFAs and their blends and thus improve the ambient stability of OSCs.
CRIS-Team Scopus Importer:2019-11-19

Suppressing the Surface Recombination and Tuning the Open-Circuit Voltage of Polymer/Fullerene Solar Cells by Implementing an Aggregative Ternary Compound - Galli, Diana; Gasparini, Nicola; Forster, Michael; Eckert, Anika; Widling, Christian; Killian, Manuela; Avgeropoulos, Apostolos; Gregoriou, Vasilis G.; Scherf, Ullrich; Chochos, Christos L.; Brabec, Christoph; Ameri, Tayebeh (ACS Applied Materials and Interfaces, 2018)
In this work, we present a novel small molecule based on dithienylthienothiadiazole units (named SM1) acting as an efficient component in ternary blend organic solar cells to modify the hole extraction at the interface. Our findings show that the SM1 suppresses the surface recombination and enhances the open-circuit voltage (Voc). By introducing SM1 in a host system composed of poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl-C61-butyric acid methyl ester (PCBM), we obtained Voc values of up to 0.75 V and fill factors larger than 70% for the ternary blends. As a consequence, the power conversion efficiency is improved by about 30% compared to P3HT:PCBM binary devices. Interestingly, external quantum efficiency and absorption spectra in the near-infrared region do not show any contribution of SM1 in dried films. Instead, the addition of the small molecule improves the Voc by reducing the surface recombination losses. To shed light on the recombination processes, we carried out Fourier-transform photocurrent spectroscopy and impedance spectroscopy measurements. This work shows that the ternary concept can also have functionalities other than photosensitization and can even act as a morphology-directing agent or an interface modifie
Keywords: open-circuit voltages; recombination losses; ternary organic solar cells; sensitizers; small molecules

Suppression of Hysteresis Effects in Organohalide Perovskite Solar Cells - Hou, Yi; Scheiner, Simon; Tang, Xiaofeng; Gasparini, Nicola; Richter, Moses; Li, Ning; Schweizer, Peter; Chen, Shi; Chen, Haiwei; Ramírez Quiroz, César Omar; Du, Xiaoyan; Matt, Gebhard; et al. (Advanced Materials Interfaces, 2017)
Thin-film solar cell based on hybrid perovskites shows excellent light-to-power conversion efficiencies exceeding 22%. However, the mixed ionic-electronic semiconductor hybrid perovskite exhibits many unusual properties such as slow photocurrent instabilities, hysteresis behavior, and low-frequency giant capacitance, which still question us so far. This study presents a direct surface functionalization of transparent conductive oxide electrode with an ultrathin ≈2 nm thick phosphonic acid based mixed C60/organic self-assembled monolayer (SAM) that significantly reduces hysteresis. Moreover, due to the strong phosphonates bonds with indium tin oxide (ITO) substrates, the SAM/ITO substrates also exhibit an excellent recyclability merit from the perspective of cost effectiveness. Impedance studies find the fingerprint of an ion-based diffusion process in the millisecond to second regime for TiO2-based devices, which, however, is not observed for SAM-based devices at these low frequencies. It is experimentally demonstrated that ion migration can be considerably suppressed by carefully engineering SAM interfaces, which allows effectively suppressing hysteresis and unstable diode behavior in the frequency regime between ≈1 and 100 Hz. It is suggested that a reduced density of ionic defects in combination with the absence of charge carrier accumulation at the interface is the main physical origin for the reduced hysteresis.

Suppression of phase segregation in wide-bandgap perovskites with thiocyanate ions for perovskite/organic tandems with 25.06% efficiency - Zhang, Zhichao; Chen, Weijie; Jiang, Xingxing; Cao, Jianlei; Yang, Haidi; Chen, Haiyang; Yang, Fu; Shen, Yunxiu; Yang, Heyi; Cheng, Qinrong; Chen, Xining; Tang, Xiaohua; et al. (Nature Energy, 2024)
Mixed halide wide-bandgap perovskites are suitable for integration in tandem photovoltaics such as perovskite/organic tandem solar cells. However, halide phase segregation originating from halogen vacancy-assisted ion migration in wide-bandgap perovskites limits the device efficiency and lifetime. Here we incorporate pseudo-halogen thiocyanate (SCN) ions in iodide/bromide mixed halide perovskites and show that they enhance crystallization and reduce grain boundaries. Trace amount of SCN ions in the bulk enter the perovskite lattice, forming an I/Br/SCN alloy, and occupy iodine vacancies, blocking halide ion migration via steric hindrance. Taken together, these effects retard halide phase segregation under operation and reduce energy loss in the wide-bandgap perovskite cells. The resulting perovskite/organic tandem solar cell achieves a power conversion efficiency of 25.82% (certified 25.06%) and an operational stability of 1,000 h.
CRIS-Team Scopus Importer:2024-04-05

Suppression of Thermally Induced Fullerene Aggregation in Polyfullerene-Based Multiacceptor Organic Solar Cells - Dowland, Simon A.; Salvador, Michael Filipe; Perea Ospina, Jose Dario; Gasparini, Nicola; Langner, Stefan; Rajoelson, Sambatra; Ramanitra, Hasina H.; Lindner, Benjamin; Osvet, Andres; Brabec, Christoph; Hiorns, Roger C.; Egelhaaf, Hans-Joachim (ACS Applied Materials and Interfaces, 2017)
A novel main-chain polyfullerene, poly[fullerene-alt-2,5-bis(octyloxy)terephthalaldehyde] (PPC4), is investigated for its hypothesized superior morphological stability as an electron-accepting material in organic photovoltaics relative to the widely used fullerene phenyl-C61-butyric acid methyl ester (PCBM). When mixed with poly(3-hexylthiophene-2,5-diyl) (P3HT), PPC4 affords low-charge-generation yields because of poor intermixing within the blend. The adoption of a multiacceptor system, by introducing PCBM into the P3HT:polyfullerene blend, was found to lead to a 3-fold enhancement in charge generation, affording power conversion efficiencies very close to that of the prototypical P3HT:PCBM binary control. Upon thermal stressing and in contrast to the P3HT:PCBM binary, photovoltaic devices based on the multiacceptor system demonstrated significantly improved stability, outperforming the control because of suppression of the PCBM migration and aggregation processes responsible for rapid device failure. We rationalize the influence of the fullerene miscibility and its implications on the device performance in terms of a thermodynamic model based on Flory-Huggins solution theory. Finally, the potential universal applicability of this approach for thermal stabilization of organic solar cells is demonstrated, utilizing an alternative low-band-gap polymer-donor system.
Keywords: fullerene aggregation; main-chain polyfullerenes; multi acceptor composite blend; organic photovoltaics; thermal stability

Surface thermography using dual channel imaging based on the blue and red emission of Ba3MgSi2O8:Eu2+, Mn2+ - Hashemi, Amir; Gast, Jessica; Ali, Amjad; Osvet, Andres; Batentschuk, Miroslaw; Brabec, Christoph (Measurement Science and Technology, 2017)
In this investigation, we present a surface temperature determination method, based on the luminescence characteristics of Ba3MgSi2O8:Eu+2,Mn+2. Simple optics utilizing only one RGB scientific CMOS camera makes this measurement technique easily applicable. Four different imaging methods were developed and are presented together with the corresponding calibration curves. We successfully utilized the methods to take surface temperature gradient images of glass plates with a point heat source between them.
Keywords: Phosphor spectroscopy; Dual channel lock in method; Phase sensitive averaging detection method; Imaging; Temperature measurement; Photoluminescence decay; Intensity ratio

Surface versus Bulk Currents and Ionic Space-Charge Effects in CsPbBr3 Single Crystals - Almora Rodriguez, Osbel; Matt, Gebhard; These, Albert; Kanak, Andrii; Levchuk, Ievgen; Shrestha, Shreetu; Osvet, Andres; Brabec, Christoph; Garcia-Belmonte, Germa (Journal of Physical Chemistry Letters, 2022)
CsPbBr3 single crystals have potential for application in ionizing-radiation detection devices due to their optimal optoelectronic properties. Yet, their mixed ionic-electronic conductivity produces instability and hysteretic artifacts hindering the long-term device operation. Herein, we report an electrical characterization of CsPbBr3 single crystals operating up to the time scale of hours. Our fast time-of-flight measurements reveal bulk mobilities of 13-26 cm(2) V-1 s(-1) with a negative voltage bias dependency. By means of a guard ring (GR) configuration, we separate bulk and surface mobilities showing significant qualitative and quantitative transport differences. Our experiments of current transients and impedance spectroscopy indicate the formation of several regimes of space-charge-limited current (SCLC) associated with mechanisms similar to the Poole-Frenkel ionized-trap-assisted transport. We show that the ionic-SCLC seems to be an operational mode in this lead halide perovskite, despite the fact that experiments can be designed where the contribution of mobile ions to transport is negligible.
CRIS-Team WoS Importer:2022-06-10

Surpassing the 10% efficiency milestone for 1-cm2 all-polymer solar cells - Fan, Baobing; Zhong, Wenkai; Ying, Lei; Zhang, Difei; Li, Meijing; Lin, Yanrui; Xia, Ruoxi; Liu, Feng; Yip, Hin Lap; Li, Ning; Ma, Yuguang; Brabec, Christoph; et al. (Nature Communications, 2019)
Naphthalenediimide-based n-type polymeric semiconductors are extensively used for constructing high-performance all-polymer solar cells (all-PSCs). For such all-polymer systems, charge recombination can be reduced by using thinner active layers, yet suffering insufficient near-infrared light harvesting from the polymeric acceptor. Conversely, increasing the layer thickness overcomes the light harvesting issue, but at the cost of severe charge recombination effects. Here we demonstrate that to manage light propagation within all-PSCs, a thick bulk-heterojunction film of approximately 350 nm is needed to effectively enhance photo-harvesting in the near-infrared region. To overcome the severe charge recombination in such a thick film, a non-halogenic additive is used to induce a well-ordered micro-structure that inherently suppresses recombination loss. The combined strategies of light management and delicate morphology optimization lead to a promising efficiency over 10% for thick-film all-PSCs with active area of 1 cm2, showing great promise for future large-scale production and application of all-PSCs.
CRIS-Team Scopus Importer:2019-09-17

Sustainability considerations for organic electronic products - McCulloch, Iain; Chabinyc, Michael; Brabec, Christoph J.; Nielsen, Christian Bech; Watkins, Scott Edward (Nature Materials, 2023)
The development of organic electronic applications has reached a critical point. While markets, including the Internet of Things, transparent solar and flexible displays, gain momentum, organic light-emitting diode displays lead the way, with a current market size of over 25 billion, helping to create the infrastructure and ecosystem for other applications to follow. It is imperative to design built-in sustainability into the materials selection, processing and device architectures of all of these emerging applications, and to close the loop for a circular approach. In this Perspective, we evaluate the status of embedded carbon in organic electronics, as well as options for more sustainable materials and manufacturing, including engineered recycling solutions that can be applied within the product architecture and at the end of life. This emerging industry has a responsibility to ensure a ‘cradle-to-cradle’ approach. We highlight that ease of dismantling and recycling needs to closely relate to the product lifetime, and that regeneration should be facilitated in product design. Materials choices should consider the environmental effects of synthesis, processing and end-product recycling as well as performance.
CRIS-Team Scopus Importer:2023-06-30

Switching Off Hysteresis in Perovskite Solar Cells by Fine-Tuning Energy Levels of Extraction Layers - Guerrero, Antonio; Bou, Agustín; Matt, Gebhard; Almora, Osbel; Heumüller, Thomas; Garcia-Belmonte, Germà; Bisquert, Juan; Hou, Yi; Brabec, Christoph (Advanced Energy Materials, 2018)
Lead halide perovskites often suffer from a strong hysteretic behavior on their j–V response in photovoltaic devices that has been correlated with slow ion migration. The electron extraction layer has frequently been pointed to as the main culprit for the observed hysteretic behavior. In this work three hole transport layers are studied with well‐defined highest occupied molecular orbital (HOMO) levels and interestingly the hysteretic behavior is markedly different. Here it is shown that an adequate energy level alignment between the HOMO level of the extraction layer and the valence band of the perovskite, not only suppresses the hysteresis, avoiding charge accumulation at the interfaces, but also degradation of the hole transport layer is reduced. Numerical simulation suggests that formation of an injection barrier at the organic/perovskite heterointerface could be one mechanism causing hysteresis. The suppression of such barriers may require novel design rules for interface materials. Overall, this work highlights that both external contacts need to be carefully optimized in order to obtain hysteresis‐free perovskite devices.
Keywords: Charge accumulation; Hysteresis; Perovskites; Energy barrier; Hole extraction layer

Synthesis and photoluminescent properties of the Dy3+ doped YSO as a high-temperature thermographic phosphor - Chepyga, Liudmyla; Hertle, Ellen Elisabeth; Ali, Amjad; Zigan, Lars; Osvet, Andres; Brabec, Christoph; Batentschuk, Miroslaw (Journal of Luminescence, 2018)
Dy3+-doped yttrium orthosilicate (Y2SiO5, abbreviated YSO) phosphors were synthesized: (1) by conventional high temperature solid-state method using two types of fluxes: lithium fluoride (LiF) and boron oxide (B2O3); (2) by metal alkoxide sol-gel method using isopropoxide assisted co-precipitation with subsequent annealing to explore its possible application in high-temperature thermometry. It was experimentally observed that the use of LiF flux affects the luminescent properties due to improvement of the crystal quality of crystallites and co-doping Li+ and F- ions. Herein, a strategy involving the use of different fluxes and concentration of Dy3+ ions has been developed to achieve high photoluminescence (PL) intensity and high intensity ratio of different PL peaks. The case of incorporated LiF in the host crystal lattices revealed strong enhancement of luminescence intensity of YSO:Dy (more than three times higher at 293 K) compared to the luminescence intensity of the phosphors synthesized with B2O3. Based on the results of high temperature measurements, it can be stated that YSO:Dy is a favorable phosphor for high temperature measurement, with a temperature sensitivity range comparable to YAG:Dy but with a lower PL decay time which is reduced by about 60%. For temperatures up to 1250 K the intensity ratio approach offers better measurement capabilities while the temperature sensitivity above 1250 K is superior for the decay time approach.
Keywords: Dysprosium; Luminescence; Phosphor thermometry; YSO

Synthesis and photovoltaic effect in red/near-infrared absorbing A-D-A-D-A-type oligothiophenes containing benzothiadiazole and thienothiadiazole central units - Luponosov, Yuriy N.; Min, Jie; Khanin, Dmitry A.; Baran, Derya; Pisarev, Sergey A.; Peregudova, Svetlana M.; Dmitryakov, Petr V.; Chvalun, Sergei N.; Cherkaev, Georgiy V.; Svidchenko, Evgeniya A.; Ameri, Tayebeh; Brabec, Christoph; et al. (Journal of Photonics for Energy, 2015)
Two π-conjugated acceptor-donor-acceptor-donor-acceptor-type (A-D-A-D-A) oligothiophenes, TT-(2T-DCV-Hex) and BT-(2T-DCV-Hex) were designed and synthesized with thienothiadiazole (TT) or benzothiadiazole (BT) as the core and dicyanovinyl (DCV) as the terminal acceptor groups for comprehensively investigating and understanding structure-property relationships. The resulting oligomers were first characterized by thermal analysis, UV-Vis spectroscopy, and cyclic voltammetry. By simply changing the BT to TT core in these two oligothiophenes, the highest occupied molecular orbital levels were varied from-5.55 eV for BT-(2T-DCV-Hex) to-5.11 eV for TT-(2T-DCV-Hex), and the optical band gaps were varied from 1.72 eV for BT-(2T-DCV-Hex) to 1.25 eV for TT-(2T-DCV-Hex), ascribed to the stronger electron accepting character of the TT core. However, the power conversion efficiency of bulk heterojunction organic solar cells (OSCs) with TT-(2T-DCV-Hex) as donor and [6,6]-phenyl C70-butyric acid methyl ester (PC71BM) as acceptor was measured to be 0.04% only, which is much lower than that of BT-(2T-DCV-Hex):PC71BM (1.54%). Compared to the TT-(2T-DCV-Hex) system, the BT-(2T-DCV-Hex) based device shows smoother film surface morphology, and superior charge generation and charge carrier mobilities. Therefore, the results clearly demonstrate that in addition to modifying the alkyl side chains and p-bridge lengths, the design of new small molecules for high-performance OSCs should also aim to choose suitable acceptor units.
Keywords: benzothiadiazole; charge carrier mobility; charge generation; dicyanovinyl group; Donor-acceptor oligomer; organic solar cell; thienothiadiazole

Synthesis, characterization and optoelectronic properties of a new perylene diimide-benzimidazole type solar light harvesting dye - Dincalp, Haluk; Cimen, Oguzhan; Ameri, Tayebeh; Brabec, Christoph; Icli, Siddik (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2014)
A perylene diimide type small molecule (BI-PDI) has been synthesized through Suzuki coupling reaction between N,N′-bis(2,6-diisopropylphenyl)- 1,7-dibromoperylene-3,4,9,10-tetracarboxylic diimide and 2-(2-hydroxyphenyl)-7- phenyl-1H-benzimidazole-4-boronic acid. BI-PDI small molecule has showed an absorption band between 350 and 750 nm on thin films. HOMO and LUMO energy levels of BI-PDI dye have been calculated to be about -5.92 eV and -3.82 eV, respectively. Solution-processed bulk heterojunction (BHJ) solar cells have been constructed using BI-PDI as donor and [6,6]-phenyl-C-butyric acid methyl ester (PCBM) as acceptor or poly(3-hexylthiophene) (P3HT) as donor and BI-PDI as acceptor. The external quantum efficiencies (EQE) of the devices cover the most of the visible region between 400 and 700 nm for both configurations. Photovoltaic performances of BI-PDI-based organic solar cells are limited by the aggregation tendency of PDI structure and poor hole/electron mobilities of the active layer. © 2014 Elsevier B.V. All rights reserved.
Keywords: Benzimidazole; Charge transfer; Light harvesting; Perylene diimide; Photoluminescence; Photovoltaics

Systematic Analysis of Polymer Molecular Weight Influence on the Organic Photovoltaic Performance - Katsouras, Athanasios; Gasparini, Nicola; Koulogiannis, Chrysanthos; Spanos, Michael; Ameri, Tayebeh; Brabec, Christoph; Chochos, Christos L.; Avgeropoulos, Apostolos (Macromolecular Rapid Communications, 2015)
The molecular weight of an electron donor-conjugated polymer is as essential as other well-known parameters in the chemical structure of the polymer, such as length and the nature of any side groups (alkyl chains) positioned on the polymeric backbone, as well as their placement, relative strength, the ratio of the donor and acceptor moieties in the backbone of donor-acceptor (D-A)-conjugated polymers, and the arrangement of their energy levels for organic photovoltaic performance. Finding the "optimal" molecular weight for a specific conjugated polymer is an important aspect for the development of novel photovoltaic polymers. Therefore, it is evident that the chemistry of functional conjugated polymers faces major challenges and materials have to adopt a broad range of specifications in order to be established for high photovoltaic performance. In this review, the approaches followed for enhancing the molecular weight of electron-donor polymers are presented in detail, as well as how this influences the optoelectronic properties, charge transport properties, structural conformation, morphology, and the photovoltaic performance of the active layer. Approaches followed for enhancing the molecular weight of the electron donor polymers and how this influences their optoelectronic properties, charge transport properties, structural conformation, morphology, and the photovoltaic performance of the active layer are analyzed and presented in detail.
Keywords: donor-acceptor; molecular weight; organic photovoltaics; polymers

Tailoring doped organic nanoparticles as selective hole transporters for printed non-fullerene organic solar cells - Xu, Junyi; Späth, Andreas; Gruber, Wolfgang; Barabash, Anastasiia; Stadler, Philipp; Gubanov, Kirill; Wu, Mingjian; Forberich, Karen; Spiecker, Erdmann; Fink, Rainer H.; Unruh, Tobias; McCulloch, Iain; et al. (Nano Energy, 2023)
Keywords: Inverted structure; Organic nanoparticle; Doping; Organic solar cell; Solution-processed hole transporting layer

Tailoring green formulation: Printing and upscaling of inverted organic solar cells - Voigt, Monika; Machui, Florian; Lucera, Luca; Spyropoulos, Georgios; Cordero, Johann; Kubis, Peter; Ali, Abid Shaukat; Shalan, Ahmed E.; Brabec, Christoph (39th IEEE Photovoltaic Specialists Conference, PVSC 2013, 2013)
By tailoring the solvents of active organic solar cell layers regarding their solubility (Hansen parameters), non-halogenated solvents and solvent mixtures can be used to print the active layers of organic solar cells. Similar efficiencies to other typical laboratory methods as spin-coating can be reached. Furthermore, using sheet-to-sheet printing or coating techniques compatible to mass-manufacturing and structuring by laser ablation, we can upscale to 10×20 cm and manufacture modules on plastic substrates. This is a breakthrough for organic solar cells and the next important step on the way to utilize organic solar cells for industrial manufacturing. © 2013 IEEE.
Keywords: Green solvents; P3HT:PCBM; Photovoltaic cells; Printing; Simulation; Solubility

Tailoring the Dimensionality of 2D/3D Heterojunctions for Inverted Perovskite Solar Cells - Li, Chaohui; Zhang, Kaicheng; Maiti, Santanu; Peng, Zijian; Tian, Jingjing; Park, Hyoungwon; Byun, Jiwon; Xie, Zhiqiang; Dong, Lirong; Qiu, Shudi; Bornschlegl, Andreas; Liu, Chao; et al. (ACS Energy Letters, 2024)
Interface engineering is crucial to achieving stable perovskite photovoltaic devices. A versatile approach is developed to tailor interface properties via integrating co-assembled monolayers (co-SAMs) at the p-type buried interface and by capping a two-dimensional (2D) perovskite layer at the n-type upper interface with vacuum quenching. Optimized co-SAMs promote the coverage of the hole transport layer, significantly reducing the incidence of leakage currents. Based on this foundation, we develop damp-heat-stable perovskite solar cells by precisely tailoring the fragments of 2D perovskite layers through vacuum annealing with phenethylammonium iodide. An impressive open-circuit voltage of 1.216 V is achieved, corresponding to 92% of the value determined by the detailed-balance limit, along with a power conversion efficiency of 23.68%. Ultimately, integrating co-SAMs and the vacuum-assisted annealing fabricated devices maintain 96% and 80% of initial efficiencies after 1200 and 500 h of tracking at a maximum power point under 55 and 85 °C, respectively.
CRIS-Team Scopus Importer:2024-02-23

Tailoring the Nature of Interface States in Efficient and Stable Bilayer Organic Solar Cells by a Transfer-Printing Technique - Wang, Rong; Jiang, Youyu; Gruber, Wolfgang; He, Yakun; Wu, Mingjian; Weitz, Paul; Zhang, Kaicheng; Lüer, Larry; Forberich, Karen; Unruh, Tobias; Spiecker, Erdmann; Deibel, Carsten; et al. (Advanced Materials Interfaces, 2022)
Bulk heterojunction organic solar cells (BHJ-OSCs) are designed to overcome inefficient charge generation and limited exciton diffusion of organic semiconductors. However, there are some disadvantages involving inherent voltage losses, microstructure control, and operational instability. Bilayer solar cells (BL-OSCs) without mixed regions are free from these problems and offer a platform to explore the photophysical processes at the donor-acceptor interface. Here, a breakthrough for n-i-p BL-OSCs in charge generation efficiency is reported. A gradual adjustment of the molecular interface orientation of the polymer donor (PM6) is accompanied by the evolution of charge-transfer states and Forster energy transfer. Besides, less recombination losses and superior morphological stability of BL-OSCs are achieved at a PCE comparable to that of BHJ-OSCs with similar layer thickness. This investigation confirms the feasibility of manufacturing BL-OSCs by a transfer printing method and provides a versatile architecture to study fundamental interface phenomena in OSCs independent from microstructure disorder.
CRIS-Team WoS Importer:2022-04-29

Targeted Adjusting Molecular Arrangement in Organic Solar Cells via a Universal Solid Additive - Zhang, Difei; Li, Yuanfeng; Li, Meijing; Zhong, Wenkai; Heumüller, Thomas; Li, Ning; Ying, Lei; Brabec, Christoph; Huang, Fei (Advanced Functional Materials, 2022)
The incorporation of solid additive has been considered as an effective strategy for developing organic photovoltaics with multi-components, which is independent of dynamics, playing unique roles in morphology adjustment. However, their complex working mechanisms involving specific chemical structures are selective to material systems, hence limiting their university and flexibility in application. Herein, an inert small-molecular compound naphtho[1,2-c:5,6-c′]bis[1,2,5]thiadiazole (NT) is introduced into the bulk-heterojunction blend as the solid additive, which can function with various material systems and solvents, depending on its simple π-conjugated structure and S⋯N interaction for adjusting molecular alignment. It is interesting to note that the introduced NT can not only improve device performance, but also simplify complicated pre- or post-processing methods, reduce impact from batch-to-batch differences, construct sufficient energy transfer channel as well as improve device stability. The resulting devices based on PTzBI-dF:Y6-BO system show an impressive power conversion efficiency of 17.4% with obviously enhanced T80 lifetime of >1200 h. These findings provide useful guidelines for exploring potential universal solid additives benefitting toward commercial application.
CRIS-Team Scopus Importer:2022-07-22
Keywords: device stability; morphology evolution; non-fullerene acceptors; organic solar cells; solid additives

Technology-dependent analysis of the snow melting and sliding behavior on photovoltaic modules - Bogenrieder, Josef; Camus, Christian; Huettner, Maximilian; Offermann, Pascal; Brabec, Christoph; Hauch, Jens (Journal of Renewable and Sustainable Energy, 2018)
In this study, the snow melting behavior of several photovoltaic technologies, all installed at the same location under identical conditions, is analyzed based on the time-dependent changes of the snow cover, which is extracted from images of a monitoring webcam, for various temperature and irradiation conditions. From this study, conclusions can be drawn for the optimum module technology for a given location with respect to snow-dependent yield losses. In particular, the melting behavior is analyzed regarding its dependence on the ambient temperature and the irradiation level. Finally, the relevance of snow cover-related losses is discussed. The study shows that comparably large frameless modules exhibit the highest snow shedding rates. Hence, they are snow-free for longer periods, thereby increasing their potential for electricity generation in snowy regions. In summary, this paper reveals the beneficial snow removal properties of large frameless modules for snowy areas by applying a novel image processing technique for the determination of the snow-covered area fraction of the modules. Published by AIP Publishing.

Technology-specific yield analysis of various photovoltaic module technologies under specific real weather conditions - Bogenrieder, Josef; Hüttner, M.; Luchscheider, Philipp; Hauch, Jens; Camus, Christian; Brabec, Christoph (Progress in Photovoltaics: Research and Applications, 2017)
In the presented paper, we introduce an approach to rate the performance of modules under specific real weather conditions, since solar modules are rated according to standard test conditions which do not give evidence of the performance under real outdoor conditions. Therefore,we categorize the daily weather at a photovoltaic test site into 7 different climatic-day classifications and multiple cloud scenarios. Two different approaches to evaluate the cloud conditions were investigated. Furthermore, we use the developed approach to rate the performance of 8 different commercially available photovoltaic modules that have been installed and measured in Germany. The evaluation shows that module properties (eg, temperature coefficient, spectral response, and mechanical construction) have a major influence on the performance of photovoltaic modules under different weather conditions.
Keywords: climate; outdoor; performance; photovoltaics; weather; yield analysis

Temperature-dependent optical spectra of single-crystal (CH3NH3)PbBr3 cleaved in ultrahigh vacuum - Niesner, Daniel; Schuster, Oskar; Wilhelm, Max; Levchuk, Ievgen; Osvet, Andres; Shrestha, Shreetu; Batentschuk, Miroslaw; Brabec, Christoph; Fauster, Thomas (Physical Review B - Condensed Matter and Materials Physics, 2017)
We measure temperature-dependent one-photon and two-photon induced photoluminescence from (CH3NH3)PbBr3 single crystals cleaved in ultrahigh vacuum. An approach is presented to extract absorption spectra from a comparison of both measurements. Cleaved crystals exhibit broad photoluminescence spectra. We identify the direct optical band gap of 2.31 eV. Below 200 K, the band gap increases with temperature, and it decreases at elevated temperature, as described by the Bose-Einstein model. An excitonic transition is found 22 meV below the band gap at temperatures <200 K. Defect emission occurs at photon energies <2.16 eV. In addition, we observe a transition at 2.25 eV (2.22 eV) in the orthorhombic (tetragonal and cubic) phase. Below 200 K, the associated exciton binding energy is also 22 meV, and the transition redshifts at higher temperature. The binding energy of the exciton related to the direct band gap, in contrast, decreases in the cubic phase. High-energy emission from free carriers is observed with higher intensity than reported in earlier studies. It disappears after exposing the crystals to ai

Temperature measurements using YAG : Dy and YAG : Sm under diode laser excitation (405 nm) - Hashemi, Amir; Vetter, Andreas; Jovicic, Gordana; Batentschuk, Miroslaw; Brabec, Christoph (Measurement Science & Technology, 2015)
Temperature-sensitive phosphors offer an option of accurate contactless temperature measurement. The method can be applied to a wide temperature range and up to more than 1500 K. In the current paper, phosphor thermometry based on four rare earths doped in YAG was studied. The standard excitation of thermographic phosphors is carried out with a Nd : YAG laser often at 355 or 266 nm. We examined the temperature dependent luminescence at an excitation wavelength of 405 nm. The excitation with visible blue light offers two main advantages: the excitation sources are rather cheap and they involve less safety issues. Accordingly, a variety of new application of such remote-thermometry would be possible. The results show that YAG : Dy and YAG : Sm may be well utilized for phosphor thermometry excited by a 405 nm diode laser.
Keywords: phosphor thermometry; temperature; luminescence; phosphorescence; diode laser

Ternary All-Polymer Solar Cells With 8.5% Power Conversion Efficiency and Excellent Thermal Stability - Liu, Xi; Zhang, Chaohong; Pang, Shuting; Li, Ning; Brabec, Christoph; Duan, Chunhui; Huang, Fei; Cao, Yong (Frontiers in Chemistry, 2020)
All-polymer solar cells (all-PSCs) composed of polymer donors and acceptors have attracted widespread attention in recent years. However, the broad and efficient photon utilization of polymer:polymer blend films remains challenging. In our previous work, we developed NOE10, a linear oligoethylene oxide (OE) side-chain modified naphthalene diimide (NDI)-based polymer acceptor which exhibited a power conversion efficiency (PCE) of 8.1% when blended with a wide-bandgap polymer donor PBDT-TAZ. Herein, we report a ternary all-PSC strategy of incorporating a state-of-the-art narrow bandgap polymer (PTB7-Th) into the PBDT-TAZ:NOE10 binary system, which enables 8.5% PCEs within a broad ternary polymer ratio. We further demonstrate that, compared to the binary system, the improved photovoltaic performance of ternary all-PSCs benefits from the combined effect of enhanced photon absorption, more efficient charge generation, and balanced charge transport. Meanwhile, similar to the binary system, the ternary all-PSC also shows excellent thermal stability, maintaining 98% initial PCE after aging for 300 h at 65°C. This work demonstrates that the introduction of a narrow-bandgap polymer as a third photoactive component into ternary all-PSCs is an effective strategy to realize highly efficient and stable all-PSCs.
CRIS-Team Scopus Importer:2020-05-15
Keywords: all-polymer solar cells; Förster resonant energy transfer; power conversion efficiency; ternary solar cells; thermal stability

The 2021 flexible and printed electronics roadmap - Bonnassieux, Yvan; Brabec, Christoph; Cao, Yong; Carmichael, Tricia Breen; Chabinyc, Michael L.; Cheng, Kwang Ting; Cho, Gyoujin; Chung, Anjung; Cobb, Corie L.; Distler, Andreas; Egelhaaf, Hans-Joachim; Grau, Gerd; et al. (Flexible and Printed Electronics, 2021)
This roadmap includes the perspectives and visions of leading researchers in the key areas of flexible and printable electronics. The covered topics are broadly organized by the device technologies (sections 1–9), fabrication techniques (sections 10–12), and design and modeling approaches (sections 13 and 14) essential to the future development of new applications leveraging flexible electronics (FE). The interdisciplinary nature of this field involves everything from fundamental scientific discoveries to engineering challenges; from design and synthesis of new materials via novel device design to modelling and digital manufacturing of integrated systems. As such, this roadmap aims to serve as a resource on the current status and future challenges in the areas covered by the roadmap and to highlight the breadth and wide-ranging opportunities made available by FE technologies.
CRIS-Team Scopus Importer:2021-06-25
Keywords: E-textiles; Flexible and printed electronics; Organic light emitting diodes; Organic photovoltaics; Roll-to-roll printing; Sensors; Thin film transistors

The effect of organic and metal oxide interfacial layers on the performance of inverted organic photovoltaics - Savva, Achilleas; Petraki, Foteini; Elefteriou, Polyvios; Sygellou, Lambrini; Voigt, Monika; Giannouli, Myrsini; Kennou, Stella; Nelson, Jenny; Bradley, Donal D. C.; Brabec, Christoph; Choulis, Stelios A. (Advanced Energy Materials, 2013)
We study the origin of the improvement of the power conversion effi ciency (PCE) of inverted organic solar cells when an interfacial insulating organic layer of polyoxyethylene tridecyl ether (PTE) is introduced between the indium tin oxide (ITO) bottom electrode and the TiOx interfacial layer. XPS and UPS measurements are used to investigate the energy level alignment at the interfaces within the ITO/TiOx and ITO/PTE/TiOx structures and to identify any effects due to chemical interaction and interfacial dipoles. Scanning electron microscopy studies show that the surface structure of the TiOx layer is affected, when it is coated on top of the PTE layer. Surface contact angle measurements show that the incorporated interfacial layer of PTE is more hydrophilic than ITO and thus PTE modifi ed TiO x becomes more hydrophilic. This, in combination with the surface gaps of the PTE interfacial layer, is likely to lead to changed wetting and hydrolysis properties of TiOx when coated on ITO/PTE than on ITO alone. The different TiOx layer quality is refl ected in improved electron selectivity, leading to enhanced fi ll factor, reduced parasitic resistance effects and higher power conversion effi ciency for inverted solar cells with a PTE interfacial layer between ITO and TiOx. © 2013 WILEY-VCH Verlag GmbH and Co. © 2013 WILEY-VCH Verlag GmbH & Co.
CRIS-Team Scopus Importer:2023-03-07

The effect of oxygen induced degradation on charge carrier dynamics in P3HT:PCBM and Si-PCPDTBT:PCBM thin films and solar cells - Karuthedath, Safakath; Sauermann, Tobias; Egelhaaf, Hans-Joachim; Wannemacher, Reinhold; Brabec, Christoph; Lueer, Larry (Journal of Materials Chemistry A, 2015)
Due to their light weight, transparency and flexibility, organic photovoltaic (OPV) devices are ideal for building integration. As this application requires solar cell life times of more than twenty years and oxygen ingress cannot be avoided at competitive cost on this time scale, OPV modules must be intrinsically stabilized against photo-oxidation. To this end, the mechanism of rapid performance loss of OSCs due to oxygen-induced degradation must be understood. Here, we combine transient absorption experiments with electrical studies in P3HT:PCBM and Si-PCPDTBT:PCBM thin films and solar cells after controlled photo-oxidation, studying charge carrier dynamics on the femtosecond to millisecond time scale. We find that oxygen-induced degradation does not significantly influence charge generation, while its influence on charge recombination is strong in both materials. A dramatic retardation of charge recombination already at low levels of oxygen-induced degradation is attributed to a substantial reduction of charge mobilities. We also observe a significant increase of the background concentration of charge carriers with the level of degradation, which leads to a crossover from second order towards pseudo-first order recombination behaviour. Extraction is shown to be retarded even more strongly than recombination, possibly by a reduction of the extraction field by the background carriers. Overall, the recombination yield is increased with degradation, explaining the strong performance loss already at low degradation levels.
Keywords: Engineering controlled terms: Charge carriers; Extraction; Oxygen; Silicon; Thin films Background concentration; Building integration; Charge carrier dynamics; Charge recombinations; Induced degradation; Organic photovoltaic devices; Substantial reduction; Transient absorption Engineering main heading: Solar cells

The evolution of Materials Acceleration Platforms: toward the laboratory of the future with AMANDA - Wagner, Jerrit; Berger, Christian; Du, Xiaoyan; Stubhan, Tobias; Hauch, Jens; Brabec, Christoph (Journal of Materials Science, 2021)
The development of complex functional materials poses a multi-objective optimization problem in a large multi-dimensional parameter space. Solving it requires reproducible, user-independent laboratory work and intelligent preselection of experiments. However, experimental materials science is a field where manual routines are still predominant, although other domains like pharmacy or chemistry have long used robotics and automation. As the number of publications on Materials Acceleration Platforms (MAPs) increases steadily, we review selected systems and fit them into the stages of a general material development process to examine the evolution of MAPs. Subsequently, we present our approach to laboratory automation in materials science. We introduce AMANDA (Autonomous Materials and Device Application Platform - www.amanda-platform.com), a generic platform for distributed materials research comprising a self-developed software backbone and several MAPs. One of them, LineOne (L1), is specifically designed to produce and characterize solution-processed thin-film devices like organic solar cells (OSC). It is designed to perform precise closed-loop screenings of up to 272 device variations per day yet allows further upscaling. Each individual solar cell is fully characterized, and all process steps are comprehensively documented. We want to demonstrate the capabilities of AMANDA L1 with OSCs based on PM6:Y6 with 13.7% efficiency when processed in air. Further, we discuss challenges and opportunities of highly automated research platforms and elaborate on the future integration of additional techniques, methods and algorithms in order to advance to fully autonomous self-optimizing systems—a paradigm shift in functional materials development leading to the laboratory of the future.
CRIS-Team Scopus Importer:2021-08-06

The fabrication of color-tunable organic light-emitting diode displays via solution processing - Guo, Fei; Karl, André; Xue, Qifan; Tam, Kai C.; Forberich, Karen; Brabec, Christoph (Light: Science & Applications, 2017)
Electroluminescent devices based on organic semiconductors have attracted significant attention owing to their promising applications in flat-panel displays. The conventional display pixel consisting of side-by-side arrayed red, green and blue subpixels represents the mature technology but bears an intrinsic deficiency of a low pixel density. Constructing an individual color-tunable pixel that comprises vertically stacked subpixels is considered an advanced technology. Although color-tunable organic light-emitting diodes (OLEDs) have been fabricated using the vacuum deposition of small molecules, the solution processing of conjugated polymers would enable a much simpler and inexpensive manufacturing process. Here we present the all-solution processing of color-tunable OLEDs comprising two vertically stacked polymer emitters. A thin layer of highly conducting and transparent silver nanowires is introduced as the intermediate charge injection contact, which allows the emission spectrum and intensity of the tandem devices to be seamlessly manipulated. To demonstrate a viable application of this technology, a 4-by-4 pixelated matrix color-tunable display was fabricated.
Keywords: color tunable; oLED display; organic light-emitting diode; silver nanowires; solution processing; tandem

The Impact of COVID-19-Related Measures on the Solar Resource in Areas with High Levels of Air Pollution - Peters, Ian Marius; Brabec, Christoph; Buonassisi, Tonio; Hauch, Jens; Nobre, André M. (Joule, 2020)
Restrictions enacted to reduce the spreading of COVID-19 have resulted in notably clearer skies around the world. In this study, we confirm that reduced levels of air pollution correlate with unusually high levels of clear-sky insolation in Delhi, India. Restrictions here were announced on March 19th, with the nation going into lockdown on March 24th. Comparing insolation data before and after these dates with insolation from previous years (2017 to 2019), we observe an 8.3% ± 1.7% higher irradiance than usual in late March and a 5.9% ± 1.6% higher one in April, while we find no significant differences in values from previous years in February or early March. Using results from a previous study, we calculated the expected increase in insolation based on measured PM2.5 concentration levels. Measurements and calculations agree within confidence intervals, suggesting that reduced pollution levels are a major cause for the observed increase in insolation. A broadly noticed consequence of the restrictions enacted to counter the spreading of COVID-19 was unusually clear skies in many regions of the world. Better air quality has an impact on solar power generation, as fewer pollution particles in the air means that more sunlight will reach solar panels on the ground. In this study, we explore how air pollution in Delhi has developed following the lockdown on March 24th and how this reduction has affected how much sunlight the city received. First, we looked at measured particle concentration levels and noticed that after lockdown, levels dropped to about half of where they had been in previous years. Then, we looked at how much sunlight was received by solar panels. Before lockdown, insolation was similar to previous years. Yet, after lockdown, there was a clear and significant increase. In late March, insolation was up by 8.3% compared with levels in previous years. This is comparable to moving a solar panel from Toronto to Houston. Following restrictions to counter the spread of COVID-19, reports about unusually clear skies appeared in many regions of the world. In this study, we explore how air pollution in Delhi has developed following the lockdown on March 24th and how this reduction has affected how much sunlight the city received. Until early April, pollution levels had dropped to half of their usual levels. The cleaner air allowed more sunlight to pass, increasing insolation by more than 8%.
CRIS-Team Scopus Importer:2020-07-24
Keywords: air pollution; COVID-19; solar energy

The influence of CPC reflectors on the electrical incidence angle modifier of c-Si cells in a PVT hybrid collector - Proell, M.; Karrer, H.; Brabec, Christoph; Hauer, A. (Solar Energy, 2016)
PVT collectors aim for the co-generation of pv electricity and heat. The following concept intents to raise the thermal efficiency by concentrating sunlight with CPC reflectors, in order to access a higher number of solar thermal applications.The work presented here, focuses on the influence of the CPC reflectors on the pv efficiency. Parabolic concentrators in general, and CPC reflectors in particular, cause a non-uniform illumination of the pv cells, which decreases the pv efficiency. Ray tracing calculations of one particular CPC geometry result in a characteristic, angular dependent solar flux distribution in the cell plane.The effect of this flux distribution was measured on a real scale experimental collector on a outdoor solar test stand. The incidence angle modifier (IAM) of the pv efficiency was measured for three different concentrations, as well as for an improved CPC geometry, aiming to homogenize the flux distribution in the cell plane.The experiments showed, that the pv efficiency drops from 15% at STC to between 9% and 11%, depending on the solar concentration factor, which influences the efficiency negatively. The predicted efficiency boost of the improved CPC geometry could not be validated experimentally, as the additional optical losses of the more complex setup were high compared to its improvement effect.In order to understand these results, a theoretical model was built, combining ray tracing, electrical and thermal modeling of the CPC PVT collector. This model enabled to calculate the temperature distribution, as well as the pv efficiency simultaneously, by dividing the pvt absorber into finite elements.
Keywords: Concentrating; CPC; Fluid; Flux distribution; Hybrid; PVT

The influence of defects on the cellular open circuit voltage in CuInGaSe2 thin film solar modules-An illuminated lock-in thermography study - Adams, J.; Vetter, A.; Hoga, F.; Fecher, F.; Theisen, J. P.; Brabec, Christoph; Buerhop-Lutz, C. (Solar Energy Materials and Solar Cells, 2014)
CuInGaSe2 (CIGS) thin film solar modules, despite their high efficiency, may contain three different kinds of macroscopic defects referred to as bulk defects, interface defects and interconnect defects. This occurs due to film's sensitivity to inhomogeneities during the manufacturing process. The result is a decrease of electrical power output from a cell or module. In this paper, we present the influence of macroscopic defects on the electrical behavior of CIGS thin film solar cells. To accomplish this, we investigated the relation between the IR-signal emitted of a defect in a cell (measured using illuminated lock-in thermography ILIT) and the respective open circuit cell voltage (V-oc,V-cell) under low light conditions ( < 100 W/m(2)). Furthermore, we developed a modified masking method of measuring V-oc,V-cell of a single cell within a thin film solar module. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: ILIT; Cell voltage; Open circuit; V-oc; Defect; Lock-in thermography

The influence of polymer purification on photovoltaic device performance of a series of indacenodithiophene donor polymers - Ashraf, Raja Shahid; Schroeder, Bob C.; Bronstein, Hugo A.; Huang, Zhenggang; Thomas, Stuart; Kline, R. Joseph; Brabec, Christoph; Rannou, Patrice; Anthopoulos, Thomas D.; Durrant, James R.; Mcculloch, Iain (Advanced Materials, 2013)
A series of low bandgap indacenodithiophene polymers is purified by recycling SEC in order to isolate narrow polydispersity fractions. This additional purification step is found to have a significant beneficial influence on the solar cell performance and the reasons for this performance increase are investigated. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: fractionation; indacenodithiophene; organic photovoltaics; purification

The Interplay of Contact Layers: How the Electron Transport Layer Influences Interfacial Recombination and Hole Extraction in Perovskite Solar Cells. - Hermes, Ilka M.; Hou, Yi; Bergmann, Victor W.; Brabec, Christoph; Weber, Stefan A.L. (Journal of Physical Chemistry Letters, 2018)
Charge selective contact layers in perovskite solar cells influence the current density-voltage hysteresis, an effect related to ion migration in the perovskite. As such, fullerene-based electron transport layers (ETL) suppress hysteresis by reducing the mobile ion concentration. However, the impact of different ETL on the electronic properties of other constituent device layers remains unclear. In this Kelvin probe force microscopy study, we compared potential distributions of methylammonium lead iodide-based solar cells with two ETL (planar TiO2 and C60-functionalized self-assembled monolayer) with different hysteretic behavior. We found significant changes in the potential distribution of the organic hole transport layer spiroMeOTAD, suggesting the formation of a neutral spiroMeOTAD-iodide interface due to a reaction between iodide with p-doped spiroMeOTAD in the TiO2 cell. Our results show that the ETL affects not only the mobile ion concentration and the recombination at the perovskite/ETL interface but also the resistance and capacitance of the spiroMeOTAD.

The path to ubiquitous organic electronics hinges on its stability - Brabec, Christoph; Egelhaaf, Hans-Joachim; Salvador, Michael (Journal of Materials Research, 2018)

The Physics of Small Molecule Acceptors for Efficient and Stable Bulk Heterojunction Solar Cells - Gasparini, Nicola; Wadsworth, Andrew; Moser, Maximilian; Baran, Derya; Mcculloch, Iain; Brabec, Christoph (Advanced Energy Materials, 2018)
Organic bulk heterojunction solar cells based on small molecule acceptors have recently seen a rapid rise in the power conversion efficiency with values exceeding 13%. This impressive achievement has been obtained by simultaneous reduction of voltage and charge recombination losses within this class of materials as compared to fullerene-based solar cells. In this contribution, the authors review the current understanding of the relevant photophysical processes in highly efficient nonfullerene acceptor (NFA) small molecules. Charge generation, recombination, and charge transport is discussed in comparison to fullerene-based composites. Finally, the authors review the superior light and thermal stability of nonfullerene small molecule acceptor based solar cells, and highlight the importance of NFA-based composites that enable devices without early performance loss, thus resembling so-called burn-in free devices.
Keywords: charge recombination; nonfullerene acceptors; organic solar cells; photophysics; stability

The Relevance of Solubility and Miscibility for the Performance of Organic Solar Cells - Langner, Stefan; Perea Ospina, Jose Dario; Zhang, Chaohong; Li, Ning; Brabec, Christoph (CRC Press, 2019)
This chapter introduces the approach to ab initio calculate the values based on computational methods, and a Figure of Merit to predict the microstructure stability of bulk heterojunction (BHJ) composites. It focuses on solute-liquid miscibility and solute-solute miscibility and explains the degradation mechanisms related to microstructure. The chapter provides a detailed insight into the theoretical, computational and experimental principles of mixing of organic semiconductors. The microstructure of a BHJ film is determined by the competition between thermodynamics and kinetics during the drying process. The chapter describes the M. L. Hansen solubility parameters (HSPs) can be visualized in a three dimensional coordinates system with the solubility parameters as axes. The mixing compatibility of a polymer and a fullerene is graphically represented by the values of thermodynamic variables when the equilibrium is established among the phases of a system.
CRIS-Team Scopus Importer:2023-03-07

The Relevance of Solubility and Miscibility for the Performance of Organic Solar Cells - Langner, Stefan; Perea Ospina, Jose Dario; Zhang, Chaohong; Li, Ning; Brabec, Christoph (Conjugated Polymers. Properties, Processing, and Applications, 2019)
This chapter introduces the approach to ab initio calculate the values based on computational methods, and a Figure of Merit to predict the microstructure stability of bulk heterojunction (BHJ) composites. It focuses on solute–liquid miscibility and solute–solute miscibility and explains the degradation mechanisms related to microstructure. The chapter provides a detailed insight into the theoretical, computational and experimental principles of mixing of organic semiconductors. The microstructure of a BHJ film is determined by the competition between thermodynamics and kinetics during the drying process. The chapter describes the M. L. Hansen solubility parameters (HSPs) can be visualized in a three dimensional coordinates system with the solubility parameters as axes. The mixing compatibility of a polymer and a fullerene is graphically represented by the values of thermodynamic variables when the equilibrium is established among the phases of a syst
CRIS-Team WoS Importer:2021-10-18

Thermal-Driven Phase Separation of Double-Cable Polymers Enables Efficient Single-Component Organic Solar Cells - Feng, Guitao; Li, Junyu; He, Yakun; Zheng, Wenyu; Wang, Jing; Li, Cheng; Tang, Zheng; Osvet, Andres; Li, Ning; Brabec, Christoph; Yi, Yuanping; Yan, He; et al. (Joule, 2019)
Conventional organic solar cells (OSCs) need two components that function as donor and acceptor, respectively. Although there has been wishful thinking about constructing OSCs based on a single component, it is generally believed to be highly challenging to achieve efficient single-component OSCs (SCOSCs). In this work, we design a new double-cable conjugated polymer containing a strongly crystalline backbone as donor and aromatic side units as acceptor. With a high annealing temperature (230°C), both the backbones and perylene bisimide side units could self-organize into ordered nanostructures. This enables efficient charge transport and low charge recombination, resulting in a record efficiency of 6.3% in SCOSCs. The cells also exhibit excellent stability, with >90% efficiency retention over 300 h of continuous one-sun illumination. These results suggest that the concept of SCOSCs is highly promising, especially to overcome the limitations of conventional OSCs toward industrial application.
CRIS-Team Scopus Importer:2019-07-19
Keywords: conjugated polymers; double cable; nanophase separation; single-component organic solar cells; thermal driven

The role of chemical structure in indacenodithienothiophene-alt-benzothiadiazole copolymers for high performance organic solar cells with improved photo-stability through minimization of burn-in loss - Chochos, Christos L.; Leclerc, Nicolas; Gasparini, Nicola; Zimmerman, Nicolas; Tatsi, Elisavet; Katsouras, Athanasios; Moschovas, Dimitrios; Serpetzoglou, Efthymis; Konidakis, Ioannis; Fall, Sadiara; Leveque, Patrick; Heiser, Thomas; et al. (Journal of Materials Chemistry A, 2017)
It is of upmost importance to gain an in-depth understanding of the role of the polymer chemical structure in the performance of the corresponding organic solar cell (OSC) and its degradation behavior, which is currently insufficiently explored. Achieving these correlations will set new design rules towards further optimization of polymer chemical structures for OSCs exhibiting high performances and long stability. In this study, our efforts have been focused on identifying how the nature of aryl substituents and the number of fluorine atoms anchored in the backbone of indacenodithieno[3,2-b]thiophene (IDTT) based polymers influence their optoelectronic properties, the OSC performances and their degradation mechanisms. The most important outcome of this study is the demonstration that standard initial burn-in loss is primary attributed to microstructure instabilities. Furthermore, the initial burn-in loss could be substantially reduced through the rational design of the polymeric semiconductor's chemical structure, leading to improved lifetimes and low (20%) initial power conversion efficiency loss. In particular, we identify the beneficial effect of the presence of the two fluorine atoms on the benzo[c][1,2,5]thiadiazole (BTD), as compared to the non-fluorinated and mono-fluorinated analogues, in decreasing the burn-in by reducing the microstructure instabilities regardless of the aryl substituent that is present in the polymer backbone. © The Royal Society of Chemistry.
Keywords: Engineering controlled terms: Chemical stabilityDegradationFluorineImage enhancementMicrostructureOrganic solar cellsPolymer solar cellsPolymersSolar cellsStructure (composition)Substitution reactions Compendex keywords Beneficial effectsBenzothiadiazolesDegradation behaviorDegradation mechanismIn-depth understandingOptoelectronic propertiesPolymeric semiconductorsPower conversion efficiencies Engineering main heading: Structural design

The role of connectivity in significant bandgap narrowing for fused-pyrene based non-fullerene acceptors toward high-efficiency organic solar cells - Liu, Shungang; Su, Wenyan; Zou, Xianshao; Du, Xiaoyan; Cao, Jiamin; Wang, Nong; Shen, Xingxing; Geng, Xinjian; Tang, Zilong; Yartsev, Arkady; Zhang, Maojie; Gruber, Wolfgang; et al. (Journal of Materials Chemistry A, 2020)

The role of exciton lifetime for charge generation in organic solar cells at negligible energy-level offsets - Classen, Andrej; Chochos, Christos L.; Lüer, Larry; Gregoriou, Vasilis G.; Wortmann, Jonas; Osvet, Andres; Forberich, Karen; McCulloch, Iain; Heumüller, Thomas; Brabec, Christoph (Nature Energy, 2020)
Organic solar cells utilize an energy-level offset to generate free charge carriers. Although a very small energy-level offset increases the open-circuit voltage, it remains unclear how exactly charge generation is affected. Here we investigate organic solar cell blends with highest occupied molecular orbital energy-level offsets (∆EHOMO) between the donor and acceptor that range from 0 to 300 meV. We demonstrate that exciton quenching at a negligible ∆EHOMO takes place on timescales that approach the exciton lifetime of the pristine materials, which drastically limits the external quantum efficiency. We quantitatively describe this finding via the Boltzmann stationary-state equilibrium between charge-transfer states and excitons and further reveal a long exciton lifetime to be decisive in maintaining an efficient charge generation at a negligible ∆EHOMO. Moreover, the Boltzmann equilibrium quantitatively describes the major reduction in non-radiative voltage losses at a very small ∆EHOMO. Ultimately, highly luminescent near-infrared emitters with very long exciton lifetimes are suggested to enable highly efficient organic solar cells.
CRIS-Team Scopus Importer:2020-09-11

The role of innovation for economy and sustainability of photovoltaic modules - Peters, Ian Marius; Hauch, Jens; Brabec, Christoph (iScience, 2022)
The role of innovation for the success of photovoltaics cannot be overstated. Photovoltaics have enjoyed the most substantial price learning of any energy technology. Innovation affects photovoltaic performance in more ways, though. Here, we explore the role of innovation for economics and greenhouse gas savings of photovoltaic modules using replacement scenarios. We find that the greenhouse gas displacement potential of photovoltaic modules has improved substantially over the last 20 years—4-fold for the presented example. We show that the economically ideal time for repowering is after around 20 years, but that repowering may reduce greenhouse gas savings. Expanding photovoltaic installations is generally preferable, economically and sustainably, to repowering. We argue that i) we should maximize the greenhouse gas saving potential of each module, which requires a global strategy, ii) tandem solar cells should aim for stability, and iii) efforts to continue and accelerate innovation in photovoltaic technology are needed.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Energy management; Engineering

The Voltage-Ear – An Anomaly in photovoltaic systems with undersized inverters - Wittmann, Ernst; Buerhop-Lutz, Claudia; Christlein, Vincent; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (IEEE Photonics Journal, 2024)
This study presents a phenomenon in photovoltaic field installations we call voltage ear. PV installations exhibit the voltage ear under specific conditions where modules generate more power than the inverter can handle. When inverters exceed their power limit it results in inverter clipping, and the solar modules are regulated to operate at a voltage above that at maximum power. This kind of voltage rise leads to a specific pattern in the monitoring data – the voltage ear. In the present study, data from a solar park in France was analyzed. This park featured a high rate of inverter malfunctions, including overheating and fires, resulting in an estimated 5% failure rate and, ultimately, in a complete replacement of inverters. An automated analysis of the monitoring data revealed 32.000 occurrences of excess voltage in 1.65 million data points (2%). Instances of the phenomena were detected and segmented using a K-means sorting algorithm, which yielded a perfect recall value. Analysis of the identified voltage ear conditions showed, that it occurs predominantly during seasons of high irradiance and cool temperatures. Excess voltages of up to 161 V in single strings were observed, increasing the probability for PID and inverter damage. The direct yield loss due to deviation from maximum power point was between 0.02% in January and 0.9% in June. We assume, that the voltage ear is a symptom of system design issues that can result in malfunctioning of inverters and hope that it will be useful as an indicator for identifying design and operation issues.<br
Keywords: Inverters; Ear; Voltage measurement; Monitoring; Voltage control; Temperature measurement; Current measurement; PV field inspection; monitoring data; voltage ear; K-means clustering; inverter failure

Thin-Film Electrostatic Discharge Protection for Highly Segmented OLEDs in Automotive Applications - Bechert, Hermann; Almora, Osbel; Regau, Kilian; Matt, Gebhard; Brabec, Christoph; Wehlus, Thomas (Advanced Materials Technologies, 2019)
Future autonomous driving requires new lighting solutions. Communication in between other cars and pedestrians, which fulfills the requirements of the automotive lighting industry, is needed. A very promising lighting solution for this application are highly segmented organic light-emitting diodes (OLEDs). Unfortunately, small area OLEDs are very sensitive to electrostatic discharge due to the small capacitance of the OLED segments. This study presents a solution for highly segmented OLEDs to fulfill automotive requirements regarding electrostatic discharge (ESD) without cost driving external components but through the improvement of the OLED itself. This solution is designed to be cheap and simple in fabrication, derived from standard photolithography to ensure no impact on existing supply chains and flexible OLED fabrication. After introducing the improved device concept for highly segmented OLEDs and its boundary conditions, a detailed view on the corresponding fabrication steps is given. The capacitive response of the protected OLED segments with respect to OLEDs without the introduced protection layer is characterized via impedance spectroscopy. The results exhibit the functionality of the ESD protection layer and prove with automotive ESD stability requirements complianc
Keywords: OLED; segmentation; ESD protection; impedance spectroscopy; capacitance; automotive rear-light

Thin Film Encapsulation of Organic Solar Cells by Direct Deposition of Polysilazanes from Solution - Channa, Iftikhar Ahmed; Distler, Andreas; Zaiser, Michael; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Energy Materials, 2019)
Organic electronic devices (OEDs), e.g., organic solar cells, degrade quickly in the presence of ambient gases, such as water vapor and oxygen. Thus, in order to extend the lifetime of flexible OEDs, they have to be protected by encapsulation. A solution-based encapsulation method is developed, which allows the direct deposition of the diffusion barrier on top of OEDs, thus avoiding lamination of barrier films. The method is based on the deposition of a perhydropolysilazane (PHPS) ink and its subsequent conversion into a silica layer by deep UV irradiation. The resulting barrier films show water vapor transmission rates (WVTRs) of <10(-2) g m(-2) d(-1) (40 degrees C/85% relative humidity (RH)) and oxygen transmission rates (OTRs) of <10(-2) cm(3) m(-2) d(-1) bar(-1) at ambient conditions. Flexibility of the resulting barrier films is improved by coating a barrier stack of several thin PHPS layers alternating with organic polymer interlayers. These stacks show an increase of WVTR values by less than 10% after 3000 bending cycles. Direct coating of the PHPS films on top of organic solar cells enhances the device lifetime in damp heat conditions from a few hours to beyond 300 h.
CRIS-Team WoS Importer:2019-08-09

Time-dependent morphology evolution of solution-processed small molecule solar cells during solvent vapor annealing - Min, Jie; Jiao, Xuechen; Ata, Ibrahim; Osvet, Andres; Ameri, Tayebeh; Baeuerle, Peter; Ade, Harald; Brabec, Christoph (Advanced Energy Materials, 2016)
Morphological modification using solvent vapor annealing (SVA) provides a simple and widely used fabrication option for improving the power conversion efficiencies of solution-processed bulk heterojunction (BHJ) small molecule solar cells. Previous reports on SVA have shown that this strategy influences the degree of donor/acceptor phase separation and also improves molecular donor ordering. A blend composed of a dithienopyrrole containing oligothiophene as donor (named UU07) and [6,6]-phenyl-C61-butyric acid methyl ester as acceptor is investigated with respect to SVA treatment to explore the dynamics of the BHJ evolution as a function of annealing time. A systematic study of the time dependence of morphology evolution clarifies the fundamental mechanisms behind SVA and builds the structure-property relation to the related device performance. The following two-stage mechanism is identified: Initially, as SVA time increases, donor crystallinity is improved, along with enhanced domain purity resulting in improved charge transport properties and reduced recombination losses. However, further extending SVA time results in domains that are too large and a few large donor crystallites, depleting donor component in the mixed domain. Moreover, the larger domain microstructure suffers from enhanced recombination and overall lower bulk mobility. This not only reveals the importance of precisely controlling SVA time on gaining morphological control, but also provides a path toward rational optimization of device performance. Time-dependent morphology evolution of solution-processed small molecule solar cells during solvent vapor annealing is systematically and methodically investigated. This not only reveals the importance of precisely controlling SVA time on gaining morphological control, but also provides a path toward the rational optimization of device performance.
Keywords: bulk mobility; device performance; morphology evolution; solar cells; solvent vapor annealing

Time-Resolved Analysis of Dielectric Mirrors for Vapor Sensing - Gao, Shuai; Tang, Xiaofeng; Langner, Stefan; Osvet, Andres; Harreiß, Christina; Barr, Maissa; Spiecker, Erdmann; Bachmann, Julien; Brabec, Christoph; Forberich, Karen (ACS Applied Materials and Interfaces, 2018)
Dielectric mirrors based on bilayers of polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene (SEBS) and poly(vinyl alcohol) (PVA)-zirconium dioxide (ZrO2) nanocomposites are fabricated for vapor sensing. When exposed to specific solvent vapor, the layers of dielectric mirrors can gradually swell and cause a red-shift of the reflection band. Because PVA solely responds to water and SEBS is sensitive to several different types of organic solvents, the mirrors can respond to a large variety of solvents. The dual-functional hydrophilic ZrO2 nanoparticles are introduced to not only enlarge the refractive index contrast but also increase the permeability. Time-resolved measurements show that mirrors with nanoparticles have a significantly faster response than those without nanoparticles. Moreover, the dependence on relative humidity is studied for representative solvents, and several types of solvents are selected to show the dependence on the solvent-polymer interaction parameters at typical relative humidity, which allows one to predict the responsivity and selectivity of the sensors. © 2018 American Chemical Societ
Keywords: dielectric mirrors; distributed Bragg reflectors; vapor sensing; fully printed; time-resolved analysis

TIPS Pentacene as a Beneficial Interlayer for Organic Photodetectors in Imaging Applications - Montenegro Benavides, Cindy; Biele, Markus; Schmidt, O.; Brabec, Christoph; Tedde, S. F. (IEEE Transactions on Electron Devices, 2018)
The small molecule 6,13-bis (triisopropylsilylethynyl) (TIPS) pentacene has been used as an interlayer for the reduction of dark currents in organic photodetectors (OPDs) based on a bulk heterojunction of poly-3-hexyl-thiophene(P3HT) and [6, 6]-phenyl C61 butyric acid methyl ester. We report OPDs with dark currents of ∼0.9 nA/cm2 at −5 V and external quantum efficiencies close to 80% at 530 nm. Compared to the reference, P3HT interlayer, TIPS pentacene shows a significant increase of the OPD’s detectivity from 3.29 × 1012 to 1.63 × 1013 Jones. Also, the OPD’s dynamic range is improved reducing the limit of signal detection from 132 to 6.3 nW/cm2 under green light irradiation. Singular hysteresis in the I–V characteristic curve has been observed and impedance spectroscopy measurements were carried out to analyze its origin and generate a replacement electrical model for the device at reverse bias. Finally, OPDs with TIPS pentacene interlayer have been integrated on top of amorphous silicon thin-film transistor backplanes to obtain the first OPD-based image sensor using this interlayer.
Keywords: Capacitance; Dark current; Electrodes; Frequency measurement; image sensor; Image sensors; Indium tin oxide; low dark current; organic photodetectors (OPDs); Pentacene; Photodetectors; triisopropylsilylethynyl (TIPS) pentacene interlayer

Towards 15% energy conversion efficiency: A systematic study of the solution-processed organic tandem solar cells based on commercially available materials - Li, Ning; Baran, Derya; Forberich, Karen; Machui, Florian; Ameri, Tayebeh; Turbiez, Mathieu; Carrasco-Orozco, Miguel; Drees, Martin; Facchetti, Antonio; Krebs, Frederik C.; Brabec, Christoph (Energy and Environmental Science, 2013)
Owing to the lack of scalable high performance donor materials, studies on mass-produced organic photovoltaic (OPV) devices lag far behind that on lab-scale devices. In this work, we choose 6 already commercially available conjugated polymers and systematically investigate their potential in organic tandem solar cells. All the devices are processed under environmental conditions using doctor-blading, which is highly compatible with mass-production coating technologies. Power conversion efficiencies (PCE) of 6-7% are obtained for OPV devices based on different active layers. Optical simulations based on experimental data are performed for all realized tandem solar cells. An efficiency potential of ∼10% is estimated for these compounds in combination with phenyl-C-butyric acid methyl ester (PCBM) as an acceptor. In addition, we assume a hypothetical, optimized acceptor to understand the limitation of donors. It is suggested that a PCE of >14% is realistic for tandem solar cells based on these commercially available donor materials. Along with the demonstration of novel intermediate layers we believe that this systematic study provides valuable insight for those attempting to realize the high efficiency potential of tandem architectures. © 2013 The Royal Society of Chemistry.
Keywords: Coating technologies; Environmental conditions; Novel intermediates; Optical simulation; Organic photovoltaic devices; Power conversion efficiencies; Solution-processed; Tandem solar cells Engineering controlled terms: Conversion efficiency Engineering main heading: Solar cells GEOBASE Subject Index: coating; energy efficiency; numerical model; optimization; photovoltaic system

Towards a full understanding of regioisomer effects of indene-C60 bisadduct acceptors in bulk heterojunction polymer solar cells - Cao, Tiantian; Chen, Ning; Liu, Guangxin; Wan, Yingbo; Perea, Jose Dario; Xia, Yijun; Wang, Zhaowei; Song, Bo; Li, Ning; Li, Xiaohong; Zhou, Yi; Brabec, Christoph; et al. (Journal of Materials Chemistry A, 2017)
Indene-C60 bisadduct (IC60BA), which can offer a significantly higher open-circuit voltage (Voc) than monoadducts, has become the research focus as electron acceptor materials in polymer solar cells (PSCs) in recent years. However, despite its popularity, IC60BA have always been applied in PSCs as mixture of several regioisomers and the nature of this mixture has never been fully investigated and understood. Herein, for the first time, 12 major regioisomers of IC60BA were isolated and a full investigation was carried out with respect to their structure, abundance, solubility and their corresponding photovoltaic performance. The results show that the PSCs based on these regioisomeric structures present very diverse PCE and their photovoltaic performance was dramatically affected not only by the relative indene positions but also by the steric orientation of the two indene groups. Electrochemical studies further revealed that the effect of energetic disorder inside the IC60BA regioisomers on their photovoltaic performance is insignificant when applied in PSCs. However, the steric structures and solubility of the regioisomers were found to have significant impact on the morphology and bulk properties of the active layer of PSCs, which give rise to very different PCE of devices based on IC60BA regioisomers with different structures. © 2017 The Royal Society of Chemistry.
Keywords: Heterojunctions; Mixtures; Open circuit voltage; Photovoltaic effects; Polycyclic aromatic hydrocarbons; Polymer solar cells; Solubility; Bulk heterojunction; Bulk properties; Different structure; Electrochemical studies; Electron acceptor materials; Photovoltaic performance; Polymer solar cell (PSCs); Steric structure; Solar cells

Toward Self-Driven Autonomous Material and Device Acceleration Platforms (AMADAP) for Emerging Photovoltaics Technologies - Zhang, Jiyun; Hauch, Jens A.; Brabec, Christoph J. (Accounts of Chemical Research, 2024)
Conspectus In the ever-increasing renewable-energy demand scenario, developing new photovoltaic technologies is important, even in the presence of established terawatt-scale silicon technology. Emerging photovoltaic technologies play a crucial role in diversifying material flows while expanding the photovoltaic product portfolio, thus enhancing security and competitiveness within the solar industry. They also serve as a valuable backup for silicon photovoltaic, providing resilience to the overall energy infrastructure. However, the development of functional solar materials poses intricate multiobjective optimization challenges in a large multidimensional composition and parameter space, in some cases with millions of potential candidates to be explored. Solving it necessitates reproducible, user-independent laboratory work and intelligent preselection of innovative experimental methods. Materials acceleration platforms (MAPs) seamlessly integrate robotic materials synthesis and characterization with AI-driven data analysis and experimental design, positioning them as enabling technologies for the discovery and exploration of new materials. They are proposed to revolutionize materials development away from the Edisonian trial-and-error approaches to ultrashort cycles of experiments with exceptional precision, generating a reliable and highly qualitative data situation that allows training machine learning algorithms with predictive power. MAPs are designed to assist the researcher in multidimensional aspects of materials discovery, such as material synthesis, precursor preparation, sample processing and characterization, and data analysis, and are drawing escalating attention in the field of energy materials. Device acceleration platforms (DAPs), however, are designed to optimize functional films and layer stacks. Unlike MAPs, which focus on material discovery, a central aspect of DAPs is the identification and refinement of ideal processing conditions for a predetermined set of materials. Such platforms prove especially invaluable when dealing with “disordered semiconductors,” which depend heavily on the processing parameters that ultimately define the functional properties and functionality of thin film layers. By facilitating the fine-tuning of processing conditions, DAPs contribute significantly to the advancement and optimization of disordered semiconductor devices, such as emerging photovoltaics. In this Account, we review the recent advancements made by our group in automated and autonomous laboratories for advanced material discovery and device optimization with a strong focus on emerging photovoltaics, such as solution-processing perovskite solar cells and organic photovoltaics. We first introduce two MAPs and two DAPs developed in-house: a microwave-assisted high-throughput synthesis platform for the discovery of organic interface materials, a multipurpose robot-based pipetting platform for the synthesis of new semiconductors and the characterization of thin film semiconductor composites, the SPINBOT system, which is a spin-coating DAP with the potential to optimize complex device architectures, and finally, AMANDA, a fully integrated and autonomously operating DAP. Notably, we underscore the utilization of a robot-based high-throughput experimentation technique to address the common optimization challenges encountered in extensive multidimensional composition and parameter spaces pertaining to organic and perovskite photovoltaics materials. Finally, we briefly propose a holistic concept and technology, a self-driven autonomous material and device acceleration platform (AMADAP) laboratory, for autonomous functional solar materials discovery and development. We hope to discover how AMADAP can be further strengthened and universalized with advancing development of hardware and software infrastructures in the future.
CRIS-Team Scopus Importer:2024-05-10

Towards large-scale production of solution-processed organic tandem modules based on ternary composites: Design of the intermediate layer, device optimization and laser based module processing - Li, Ning; Kubis, Peter; Forberich, Karen; Ameri, Tayebeh; Krebs, Frederik C.; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2014)
We report on a novel approach including: 1. the design of an efficient intermediate layer, which facilitates the use of most high performance active materials in tandem structure and the compatibility of the tandem concept with large-scale production; 2. the concept of ternary composites based on commercially available materials, which enhances the absorption of poly(3-hexylthiophene) (P3HT) and as a result increase the PCE of the P3HT-based large-scale OPV devices; 3. laser-based module processing, which provides an excellent processing resolution and as a result can bring the power conversion efficiency (PCE) of mass-produced organic photovoltaic (OPV) devices close to the highest PCE values achieved for lab-scale solar cells through a significant increase in the geometrical fill factor. We believe that the combination of the above mentioned concepts provides a clear roadmap to push OPV towards large-scale production and commercial applications. © 2013 Elsevier B.V.
Keywords: Intermediate layer; Laser-based module processing; Optical-simulation; Organic tandem solar cells; Solution processing; Ternary composites

Towards low-cost, environmentally friendly printed chalcopyrite and kesterite solar cells - Azimi, Seyed Hamed; Hou, Yi; Brabec, Christoph (Energy and Environmental Science, 2014)
Solution-processed organic and inorganic semiconductors offer a promising path towards low-cost mass production of solar cells. Among the various material systems, solution processing of multicomponent inorganic semiconductors offers considerable promise due to their excellent electronic properties and superior photo- and thermal stability. This review surveys the recent developments of "all solution-processed" copper-indium (-gallium)-chalcogenide (CuInS, CuInSe and Cu(In, Ga)(Se, S)) chalcopyrites and copper-zinc-tin-chalcogenide (CuZnSnS and CuZnSnSe (CZTS(e))) kesterite solar cells. A brief overview further addresses some of the most critical material aspects and associated loss mechanisms in chalcopyrite and kesterite devices. Today's state-of-the-art performance as well as future challenges to achieve low-cost and environmentally friendly production is discussed. This journal is © the Partner Organisations 2014.
Keywords: Engineering controlled terms: Chalcogenides; Copper compounds; Costs; Electronic properties; Gallium Cu(In; Ga)(Se; S)2; Future challenges; Inorganic semiconductors; Mass production; Material systems; Solution-processed; Solution-processing; State-of-the-art performance Engineering main heading: Solar cells GEOBASE Subject Index: alternative energy; cost analysis; fuel cell; renewable resource; solar power

Towards true contactless outdoor luminescence of silicon photovoltaic modules with inhomogeneous small area excitation source - Doll, Bernd; Kornhas, Jakob; Hepp, Johannes; Buerhop, Claudia; Camus, Christian; Brabec, Christoph; Hauch, Jens (2018 IEEE 7th World Conference on Photovoltaic Energy Conversion, WCPEC 2018 - A Joint Conference of 45th IEEE PVSC, 28th PVSEC and 34th EU PVSEC, 2018)
A fast, non-destructive on-site defect detection tool can help to ensure reliable power production of photovoltaic (PV) plants. In particular, it can serve as a cost-effective means for assessing a PV plant's quality and value. Luminescence as a highly sensitive imaging technique can detect local cell damage, series resistance and shunts in solar cells. Typically, outdoor imaging techniques use some sort of modulation of the solar cells' emission. Generally, this requires a physical contact with the module or string. Here, first results obtained from a PL-setup, suitable for fast and fully contactless measurements are presented. The illumination is generated with a small area light source suitable for mobile application
Keywords: reliability; silicon.; photoluminescence; photovoltaic module; defect detection; outdoor characterization; electroluminescence

Transient absorption spectroscopy studies on polythiophene-fullerene bulk heterojunction organic blend films sensitized with a low-bandgap polymer - Löslein, Heiko; Ameri, Tayebeh; Matt, Gebhard; Koppe, Markus; Egelhaaf, Hans J.; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Brabec, Christoph (Macromolecular Rapid Communications, 2013)
Recently, the concept of near-infrared sensitization is successfully employed to increase the light harvesting in large-bandgap polymer-based solar cells. To gain deeper insights into the operation mechanism of ternary organic solar cells, a comprehensive understanding of charge transfer-charge transport in ternary blends is a necessity. Herein, P3HT:PCPDTBT:PCBM ternary blend films are investigated by transient absorption spectroscopy. Hole transfer from PCPDTBT-positive polarons to P3HT in the P3HT:PCPDTBT:PCBM 0.9:0.1:1 blend film can be visualized. This process evolves within 140 ps and is discussed with respect to the proposed charge-generation mechanisms. Polythiophene-fullerene bulk heterojunction ternary blend films are investigated by transient absorption spectroscopy. Hole transfer from PCPDTBT-positive polarons to P3HT in the blend film can be visualized. This process evolves within 140 ps and is discussed with respect to the proposed charge-generation mechanisms. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Transparent and Low-Loss Luminescent Solar Concentrators Based on Self-Trapped Exciton Emission in Lead-Free Double Perovskite Nanocrystals - Zdražil, Lukáš; Kalytchuk, Sergii; Langer, Michal; Ahmad, Razi; Pospíšil, Jan; Zmeškal, Oldřich; Altomare, Marco; Osvet, Andres; Zboril, Radek; Schmuki, Patrik; Brabec, Christoph; Otyepka, Michal; et al. (ACS Applied Energy Materials, 2021)
Luminescent solar concentrators (LSCs) are light-harvesting devices that redirect solar light to an edge-attached photovoltaic cell, and thus, they have high potential to be incorporated directly into buildings’ windows to allow for generating electricity. Perovskite nanocrystals (PNCs) are promising materials for LSCs because their enticing optical properties can be engineered to provide a high photoluminescence (PL) quantum yield (QY) and low overlap between absorption and emission spectra. Replacement of toxic, lead-containing perovskites in LSCs by lead-free PNCs, while retaining high optical efficiency of the device, remains the key challenge, which needs to be overcome to build environmentally friendly solar-harvesting platforms. In this work, we use nanocrystals of Bi-doped Cs2Ag0.4Na0.6InCl6 double perovskites with a self-trapped exciton emission to realize for the first time a transparent, low-reabsorption, lead-free perovskite-based LSC. Fabricated 100 cm2 LSCs show an internal optical quantum efficiency of 21.2% with the corresponding internal concentration factor of 2.7. Monte Carlo (MC) ray-tracing simulations identified the loss caused by nonunity PL QY to be the most significant contribution to the overall efficiency loss. The MC simulations also allowed us to estimate the efficiency of 39.4% for 2,500 cm2 LSCs with hypothetical unity PL. These results demonstrate a significant promise held by Bi-doped lead-free PNCs for LSCs.
Keywords: photovoltaics; lead-free perovskites; double perovskites; perovskite nanocrystals; luminescent solar concentrators; Monte Carlo simulations

Trapping effects and surface/interface recombination of carrier recombination in single- or poly-crystalline metal halide perovskites - Lobo, Ntumba; Kawane, Takuya; Matt, Gebhard; Osvet, Andres; Shrestha, Shreetu; Levchuk, Ievgen; Brabec, Christoph; Kanak, Andrii; Fochuk, Petro; Kato, Masashi (Japanese Journal of Applied Physics, 2022)
The lifetime of a carrier is a crucial parameter for solar cell materials, and metal halide perovskite materials are promising for solar cell applications. In this study, we observed carrier recombination using time-resolved photoluminescence (TR-PL) and microwave photoconductivity decay (mu-PCD) in metal halide perovskite materials: NH3CH3PbI3 (MAPbI(3)), NH3CH3PbBr3 (MAPbBr(3)), and CsPbBr3 with single- and poly-crystalline structures. By comparing the decay curves of TR-PL and mu-PCD, we found trap levels in the band gap for all the materials. We employed two excitation wavelengths for the mu-PCD measurements, and we observed faster mu-PCD signal decays for short wavelength excitation for MAPbBr(3) and CsPbBr3. Additionally, we established that the poly-crystals exhibited faster decay compared with the single crystals for MAPbBr(3) and CsPbBr3. Therefore, we concluded that there are significant contributions of the interface and surface recombination on carrier recombination for MAPbBr(3) and CsPbBr3, but not for MAPbI(3).
CRIS-Team WoS Importer:2022-12-16

Traps and transport resistance are the next frontiers for stable non-fullerene acceptor solar cells - Woepke, Christopher; Goehler, Clemens; Saladina, Maria; Du, Xiaoyan; Nian, Li; Greve, Christopher; Zhu, Chenhui; Yallum, Kaila M.; Hofstetter, Yvonne J.; Becker-Koch, David; Li, Ning; Heumüller, Thomas; et al. (Nature Communications, 2022)
Stability is one of the most important challenges facing material research for organic solar cells (OSC) on their path to further commercialization. In the high-performance material system PM6:Y6 studied here, we investigate degradation mechanisms of inverted photovoltaic devices. We have identified two distinct degradation pathways: one requires the presence of both illumination and oxygen and features a short-circuit current reduction, the other one is induced thermally and marked by severe losses of open-circuit voltage and fill factor. We focus our investigation on the thermally accelerated degradation. Our findings show that bulk material properties and interfaces remain remarkably stable, however, aging-induced defect state formation in the active layer remains the primary cause of thermal degradation. The increased trap density leads to higher non-radiative recombination, which limits the open-circuit voltage and lowers the charge carrier mobility in the photoactive layer. Furthermore, we find the trap-induced transport resistance to be the major reason for the drop in fill factor. Our results suggest that device lifetimes could be significantly increased by marginally suppressing trap formation, leading to a bright future for OSC.
CRIS-Team Scopus Importer:2022-07-15

Triphenylamine-Based Push-Pull Molecule for Photovoltaic Applications: From Synthesis to Ultrafast Device Photophysics - Kozlov, Oleg V.; Liu, Xiaomeng; Luponosov, Yuriy N.; Solodukhin, Alexander N.; Toropynina, Victoria Y.; Min, Jie; Buzin, Mikhail I.; Peregudova, Svetlana M.; Brabec, Christoph; Ponomarenko, Sergei A.; Pshenichnikov, Maxim S. (Journal of Physical Chemistry C, 2017)
Small push-pull molecules attract much attention as prospective donor materials for organic solar cells (OSCs). By chemical engineering, it is possible to combine a number of attractive properties such as broad absorption, efficient charge separation, and vacuum and solution processabilities in a single molecule. Here we report the synthesis and early time photophysics of such a molecule, TPA-2T-DCV-Me, based on the triphenylamine (TPA) donor core and dicyanovinyl (DCV) acceptor end group connected by a thiophene bridge. Using time-resolved photoinduced absorption and photoluminescence, we demonstrate that in blends with [70]PCBM the molecule works both as an electron donor and hole acceptor, thereby allowing for two independent channels of charge generation. The charge-generation process is followed by the recombination of interfacial charge transfer states that takes place on the subnanosecond time scale as revealed by time-resolved photoluminescence and nongeminate recombination as follows from the OSC performance. Our findings demonstrate the potential of TPA-DCV-based molecules as donor materials for both solution-processed and vacuum-deposited OSCs. (Figure Presented). © 2017 American Chemical Society.
Keywords: Charge transfer; Molecules; Organic solar cells; Photoluminescence; Solar cells; Vacuum applications; Charge separations; Independent channels; Interfacial charge transfer; Photoinduced absorption; Photovoltaic applications; Push-pull molecules; Subnanosecond time scale; Time-resolved photoluminescence; Synthesis (chemical)

Two similar near-infrared (IR) absorbing benzannulated AZA-bodipy dyes as near-ir sensitizers for ternary solar cells - Min, Jie; Ameri, Tayebeh; Gresser, Roland; Lorenz-Rothe, Melanie; Baran, Derya; Troeger, Anna; Sgobba, Vito; Leo, Karl; Riede, Moritz; Guldi, Dirk Michael; Brabec, Christoph (ACS Applied Materials and Interfaces, 2013)
Ternary composite inverted organic solar cells based on poly(3-hexylthiophen-2,5-diyl) (P3HT) and phenyl-C-butyric acid methyl ester (PCBM) blended with two different near-infrared absorbing benzannulated aza-BODIPY dyes, difluoro-bora-bis-(1-phenyl-indoyl)-azamethine (1) or difluoro-bora-bis-(1-(5-methylthiophen)-indoyl)-azamethine (2), were constructed and characterized. The amount of these two aza-BODIPY dyes, within the P3HT and PCBM matrix, was systematically varied, and the characteristics of the respective devices were recorded. Although the addition of both aza-BODIPY dyes enhanced the absorption of the blends, only the addition of 1 improved the overall power conversion efficiency (PCE) in the near-infrared (IR) region. The present work paves the way for the integration of near-infrared absorbing aza-BODIPY derivatives as sensitizers in ternary composite solar cells. © 2013 American Chemical Society.

Ultrafast screening method for assessing the photostability of thin-film solar cells - Vetter, Andreas; Burlafinger, Klaus; Brabec, Christoph (Electrical Engineering, 2016)
Commercial success of optoelectronical devices such as solar cells depend strongly on lifetime next to production costs and power conversion efficiency. While a steep decrease in production costs and significant increase in efficiency have been achieved, lifetime still plays often a limiting factor, in particular, in case of highly innovative new device types. Lifetime tests measuring the stability of devices without external influences (i. p. water) generally take very long time due to the required long lifetime of optoelectronical devices. We established a novel accelerated lifetime test (ALT) setup which may increase the test speed by a factor of several hundred. We verified the setup and the applicability of our ALT measurement routine with an experiment on a well-studied innovative thin-film solar cell type (P3HT:PCBM).
Keywords: ALT; Optoelectronics; Organic photovoltaics; PV; Solar cell; Thin film

Ultra low band gap α,β-unsubstituted BODIPY-based copolymer synthesized by palladium catalyzed cross-coupling polymerization for near infrared organic photovoltaics - Squeo, Benedetta M.; Gasparini, Nicola; Ameri, Tayebeh; Palma-Cando, Alex; Allard, Sybille; Gregoriou, Vasilis G.; Brabec, Christoph; Scherf, Ullrich; Chochos, Christos L. (Journal of Materials Chemistry A, 2015)
A new ultra low band gap (LBG) α,β-unsubstituted BODIPY-based conjugated polymer has been synthesized by conventional cross coupling polymerization techniques (Stille cross coupling) for the first time. The polymer exhibits a panchromatic absorption spectrum ranging from 300 nm to 1100 nm and an optical band gap (Eoptg) of 1.15 eV, suitable for near infrared (NIR) organic photovoltaic applications as electron donor. Preliminary power conversion efficiency (PCE) of 1.1% in polymer : [6,6]-phenyl-C71-butyric acid methyl ester (PC71BM) 1 : 3 weight ratio bulk heterojunction (BHJ) solar cells has been achieved, demonstrating very interesting and promising photovoltaic characteristics, such as good fill factor (FF) and open circuit voltage (Voc). These results showing that by the proper chemical design, new α,β-unsubstituted BODIPY-based NIR copolymers can be developed in the future with suitable energy levels matching those of PC71BM towards more efficient NIR organic photovoltaics (OPVs).

Ultrastable Single-component Material Devices: the Next Frontier for Organic Solar Cells - He, Yakun; Bäuerle, Peter; Li, Weiwei; Li, Ning; Brabec, Christoph (nanoGe, 2022)

Ultrastable single-component organic solar cells: the next frontier towards industrial viability - He, Yakun; Brabec, Christoph; Heumüller, Thomas; Wortmann, Jonas; Hanisch, Benedict; Aubele, Anna; Li, Ning; Feng, Guitao; Jiang, Xudong; Li, Weiwei; Bäuerle, Peter; Lucas, Sebastian (Proceedings of International Conference on Hybrid and Organic Photovoltaics (HOPV22), 2022)
Power conversion efficiencies (PCEs) of bulk heterojunction (BHJ) organic solar cells (OSCs) continue increasing towards the 20% milestone mainly due to the emerging non-fullerene acceptors (NFAs). While significant efforts have been devoted to efficiency analysis, important factors for industrial application are mostly neglected, such as photostability and the cost potential. Single-component organic solar cells (SCOSCs) employing materials with donor and acceptor moieties chemically bonded within one molecule or polymer, successfully overcome the immiscibility between donor and acceptor as well as the resultant self-aggregation under external stress [1]. To inspire a broader interest, in this work, the industrial figure of merit (i-FOM) of OSCs are calculated and analyzed, which includes PCE, photostability, and synthetic complexity (SC) index [2]. Based on the notable advantages of SCOSCs over the correspondent BHJ OSCs, especially the enhanced stability and simplified film processing, we systematically compare the i-FOM values of BHJ OSCs and the corresponding SCOSCs. SCMs exhibit overall much higher i-FOM values compared with the BHJ OSCs, and the highest value reaches 0.3, which is comparable with (or higher than) the ones of high-efficiency BHJ OSCs. With the increase of efficiency, SCOSCs possess the further potential to a higher i-FOM value. Among all factors, the synthetic complexity of SCOSCs is slightly higher than that of the corresponding BHJ OSCs due to the extra synthetic step for connecting donor and acceptor moieties. Nevertheless, the covalent bonding structure of SCMs helps overcome the immiscibility between D and A for proper nanophase separation and consequently a decent PCE, in comparison with the large-scale phase separation for the corresponding BHJ systems. More importantly, the higher i-FOM of SCOSCs is mostly ascribed to the substantially enhanced stability compared with BHJ [3]. SCOSCs based on dyad 1 exhibit surprisingly high photostability under concentrated light (7.5 suns and 30 suns), corresponding to an almost unchanged device stability up to ten thousand hours under 1-sun illumination. For realizing industrial application, SCOSCs have to give a high efficiency comparable to the current high-efficiency BHJ OSCs, while BHJ should be developed in the direction of less complicated synthesis. With joint efforts of researchers from multidiscipline, SCOSCs will see continuing progress in efficiency, reaching an i-FOM value enough for industrial application. <br

Ultra-stable single component organic solar cells under thermal and/or illumination pressure: the next superior organic photovoltaics? - He, Yakun; Baeuerle, Peter; Li, Weiwei; Heumüller, Thomas; Li, Ning; Brabec, Christoph (13th Conference on Hybrid and Organic Photovoltaics (HOPV21), 2021)
Stability issue is the core restriction for the application of organic solar cells (OSCs). However, state-of-the-art OSCs based on bulk-heterojunction concept suffer from stability problems caused by the severe morphological changes upon thermal or illumination stress [1]. Single-component concept, enabled by the covalently-bonded structure with donor and acceptor in one molecule, presents attractive advantages such as a simplification of device fabrication and a stabilization of microstructure [2]. Recently, with the rapid improvement of efficiency from 2-3% to 8.4% for single-component organic solar cells (SCOSCs), the reports on their stability however are scanty. In this work, we for the first time systematically investigated the stability under thermal and illumination stress of a series of SCOSCs based on polymeric (SCP3, PBDBPBI-Cl) and molecular (Dyad1, 2, 3, 4) materials. Under thermal pressure, double-cable polymer-based SCOSCs exhibited excellent thermal stability with no degradation at 90 oC for 3000 hours, partially attributed to the high temperatures (around 200 oC) for post-treating active layer during device fabrication. Such rather high annealing temperatures are plausible to create microstructure arrangements which are in thermodynamic equilibrium after cooling down. Furthermore, without precedent, we studied the thermal stability comparison among a series of SCOSCs based on D-A small molecules (Dyad1, 2 and 3) with the same donor and acceptor units but differently long alkyl space linkers. Since macroscopic diffusion of molecules is excluded in these dyads, the length of the spacer can only provide the necessary flexibility for sub-nm rearrangements caused by thermal stress. Interestingly, dyads showed a distinctly different behavior, Dyad1 with the shortest linker exhibiting the highest thermal stability, while Dyad3 with the longest linker showing the worst thermal stability [3]. This highlights the need for further in-depth studies on the dual importance of spacer length for performance and stability. Moreover, Dyad1-based SCOSCs exhibited extraordinary illumination stability, retaining 98% of the initial PCE under concentrated light equal to 7.5-suns for over 1000 hours, which could be among the highest illumination stability for solution-processed OSCs. Based on the outstanding stability, SCOSCs could be an ideal candidate to study the ultimate stability under extremely rugged accelerating conditions such as high temperature and concentrated light. Since the morphological evolution is excluded, SCOSCs could serve as a model system to selectively study interface degradation. In the near future, SCOSCs will see a prospective renaissance with 10% efficiency and 20 years lifetime for industrial applications.

Understanding and Controlling the Evolution of Nanomorphology and Crystallinity of Organic Bulk-Heterojunction Blends with Solvent Vapor Annealing - Harreiß, Christina; Langner, Stefan; Wu, Mingjian; Berlinghof, Marvin; Rechberger, Stefanie; Will, Johannes; Conroy, Michele; Bangert, Ursel; Unruh, Tobias; Brabec, Christoph; Spiecker, Erdmann (Solar RRL, 2022)
Solvent vapor annealing (SVA) has been shown to significantly improve the device performance of organic bulk-heterojunction solar cells, yet the mechanisms linking nanomorphology, crystallinity of the active layer, and performance are still largely missing. Here, the mechanisms are tackled by correlating the evolution of nanomorphology, crystallinity, and performance with advanced transmission electron microscopy methods systematically. Model system of DRCN5T:PC71BM blends are SVA treated with four solvents differing in their donor and acceptor solubilities. The choice of solvent drastically influences the rate at which the maximum device efficiency establishes, though similar values can be achieved for all solvents. The donor solubility is identified as a key parameter that controls the kinetics of diffusion and crystallization of the blend molecules, resulting in an inverse relationship between optimal annealing time and donor solubility. For the highest efficiency, optimum domain size and single-crystalline nature of DRCN5T fibers are found to be crucial. Moreover, the π–π stacking orientation of the crystallites is directly revealed and related to the nanomorphology, providing insight into the charge carrier transport pathways. Finally, a qualitative model relating morphology, crystallinity, and device efficiency evolution during SVA is presented, which may be transferred to other light-harvesting blends.
Created from Fastlane, Scopus look-up
Keywords: crystallinity; EF-ED; EFTEM; nanomorphology; organic BHJ solar cells; small molecules; SVA

Understanding Causalities in Organic Photovoltaics Device Degradation in a Machine-Learning-Driven High-Throughput Platform - Liu, Chao; Lüer, Larry; Le Corre, Vincent Marc; Forberich, Karen; Weitz, Paul; Heumüller, Thomas; Du, Xiaoyan; Wortmann, Jonas; Zhang, Jiyun; Wagner, Jerrit; Ying, Lei; Hauch, Jens; et al. (Advanced Materials, 2023)
Organic solar cells (OSCs) now approach power conversion efficiencies of 20%. However, in order to enter mass markets, problems in upscaling and operational lifetime have to be solved, both concerning the connection between processing conditions and active layer morphology. Morphological studies supporting the development of structure–process–property relations are time-consuming, complex, and expensive to undergo and for which statistics, needed to assess significance, are difficult to be collected. This work demonstrates that causal relationships between processing conditions, morphology, and stability can be obtained in a high-throughput method by combining low-cost automated experiments with data-driven analysis methods. An automatic spectral modeling feeds parametrized absorption data into a feature selection technique that is combined with Gaussian process regression to quantify deterministic relationships linking morphological features and processing conditions with device functionality. The effect of the active layer thickness and the morphological order is further modeled by drift–diffusion simulations and returns valuable insight into the underlying mechanisms for improving device stability by tuning the microstructure morphology with versatile approaches. Predicting microstructural features as a function of processing parameters is decisive know-how for the large-scale production of OSCs.
CRIS-Team Scopus Importer:2023-04-28
Keywords: device stability; Gaussian process regression (GPR) prediction; linear Pearson correlations; machine learning; organic solar cells

Understanding the correlation and balance between the miscibility and optoelectronic properties of polymer-fullerene solar cells - Zhang, Chaohong; Langner, Stefan; Mumyatov, Alexander V.; Anokhin, Denis V.; Min, Jie; Perea, Jose Dario; Gerasimov, Kirill L.; Osvet, Andres; Ivanov, Dimitri A.; Troshin, Pavel; Li, Ning; Brabec, Christoph (Journal of Materials Chemistry A, 2017)
Organic photovoltaics is one of the most promising technologies for sustainable green energy supply. Because of their high electron affinity and superior electron-transporting ability, fullerene-based materials are deemed as very strong electron-accepting components in organic solar cells. However, the most widely used fullerene-based acceptors, such as phenyl-C61-butyric acid methyl ester, exhibit limited microstructural stability and unsatisfactory thermal stability owing to their insufficient compatibility with organic donors. Here, we in-depth investigate the carrier dynamics along with structural evolution and analyze the acceptor loadings in optimized bulk-heterojunction (BHJ) solar cells as a function of the polymer-fullerene miscibility. The polymer-fullerene miscibility has more influential effects than the crystallinity of single components on the optimized acceptor:donor ratio in polymer-fullerene solar cells. The findings demonstrated in this work suggest that the balance between the miscibility of BHJ composites and their optoelectronic properties has to be carefully considered for future development and optimization of OPV solar cells based on BHJ composites. Miscibility is proposed in addition to crystallinity as a further design criterion for long lived and efficient solar cells. © 2017 The Royal Society of Chemistry.
Keywords: Engineering controlled terms: Butyric acidElectron affinityFullerenesHeterojunctionsOrganic solar cellsPolymer solar cellsPolymersSolubility Bulk heterojunction (BHJ)Electron transportingHigh electron affinitiesInfluential effectsMicrostructural stabilityOptoelectronic propertiesOrganic photovoltaicsStructural evolution Engineering main heading: Solar cells

Understanding the Limitations of Charge Transporting Layers in Mixed Lead–Tin Halide Perovskite Solar Cells - Zhang, Kaicheng; Forberich, Karen; Lüer, Larry; García Cerrillo, José; Meng, Wei; Du, Xiaoyan; Le Corre, Vincent Marc; Zhao, Yicheng; Niu, Tianqi; Xue, Qifan; Koster, L Jan Anton; Li, Ning; et al. (Advanced Energy and Sustainability Research, 2021)

Understanding the Microstructure Formation of Polymer Films by Spontaneous Solution Spreading Coating with a High-Throughput Engineering Platform - Wang, Rong; Lüer, Larry; Langner, Stefan; Heumüller, Thomas; Forberich, Karen; Zhang, Heyi; Hauch, Jens; Li, Ning; Brabec, Christoph (Chemsuschem, 2021)
An important step of the great achievement of organic solar cells in power conversion efficiency is the development of low-band gap polymer donors, PBDB−T derivatives, which present interesting aggregation effects dominating the device performance. The aggregation of polymers can be manipulated by a series of variables from a materials design and processing conditions perspective; however, optimization of film quality is a time- and energy-consuming work. Here, we introduce a robot-based high-throughput platform (HTP) that is offering automated film preparation and optical spectroscopy thin-film characterization in combination with an analysis algorithm. PM6 films are prepared by the so-called spontaneous film spreading (SFS) process, where a polymer solution is coated on a water surface. Automated acquisition of UV/Vis and photoluminescence (PL) spectra and automated extraction of morphological features is coupled to Gaussian Process Regression to exploit available experimental evidence for morphology optimization but also for hypothesis formulation and testing with respect to the underlying physical principles. The integrated spectral modeling workflow yields quantitative microstructure information by distinguishing amorphous from ordered phases and assesses the extension of amorphous versus the ordered domains. This research provides an easy to use methodology to analyze the exciton coherence length in conjugated semiconductors and will allow to optimize exciton splitting in thin film organic semiconductor layers as a function of processing.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Gaussian process regression; high-throughput engineering; microstructure morphology; organic photovoltaics; spontaneous film spreading

Unraveling Dual Operational Mechanisms in an Air-Stable All Inorganic Perovskite for Nonvolatile Memory and Neuromorphic Computing - Xie, Zhiqiang; Zhang, Difei; Cheng, Long; Li, Chaohui; Elia, Jack; Wu, Jianchang; Tian, Jingjing; Chen, Lijun; Loi, Maria Antonietta; Osvet, Andres; Brabec, Christoph (ACS Energy Letters, 2024)
Two-terminal drift memristors (nonvolatile) are widely employed to emulate biological synaptic functionalities in neuromorphic architectures. However, reliable emulations of synaptic dynamics can only be achieved through the integration of their counterparts, diffusive memristors. Moreover, the combination of drift and diffusive memristors represents a desirable approach to address the escalating demands posed by the increasing complexity of neuromorphic computing frameworks, which are still in their nascent stages. Accordingly, an air-stable inorganic perovskite memristor (RbPbI3) is demonstrated with adjustable drift and diffusive modes. By employing an electroforming process, the drift-type devices demonstrate bipolar resistive switching with a large ON/OFF ratio (102), stable endurance (2000 cycles), long retention (1.2 × 105 s), and robust air stability. In contrast, diffusive-type devices, without an electroforming process, effectively emulate synaptic behaviors, including paired-pulse facilitation, long-term potentiation/depression, and spike-timing-dependent plasticity. Additionally, experimental data are utilized to train neural networks constructed with perovskite artificial synapses on image classification tasks. The results demonstrate accuracies of 89.24% (MNIST) and 79.10% (Fashion-MNIST) under supervised learning, closely approximating their theoretical values.
CRIS-Team Scopus Importer:2024-03-01

Unraveling the Charge-Carrier Dynamics from the Femtosecond to the Microsecond Time Scale in Double-Cable Polymer-Based Single-Component Organic Solar Cells - He, Yakun; Wang, Bingzhe; Lüer, Larry; Feng, Guitao; Osvet, Andres; Heumüller, Thomas; Liu, Chao; Li, Weiwei; Guldi, Dirk Michael; Li, Ning; Brabec, Christoph (Advanced Energy Materials, 2021)
Single-component organic solar cells (SCOSCs) have witnessed great improvement during the last few years with the champion efficiency jumping from the previous 2-3% to currently 6-11% for the representative material classes. However, the photophysics in many of these materials has not been sufficiently investigated, lacking essential information regarding charge-carrier dynamics as a function of microstructure, which is highly demanded for a better understanding and potential guidance for further improvements. In this work, for the first time, the charge-carrier dynamics of a representative double-cable polymer, which achieves efficiencies of over 6% as an active layer in SCOSCs, is investigated across seven orders of magnitude in time scale, from fs-ps charge generation to ns-mu s charge recombination processes. Specific emphasis is placed on understanding the impact of thermal post-treatment on the charge dissociation and recombination dynamics. Annealing the photoactive layer at 230 degrees C results in the highest photovoltaic performance because of efficient charge generation in parallel to suppressed recombination. This work intends to present a complete picture of the charge-carrier dynamics in SCOSCs using the representative double-cable polymer PBDBPBI-Cl.
CRIS-Team WoS Importer:2021-12-31

Unraveling the Complex Nanomorphology of Ternary Organic Solar Cells with Multimodal Analytical Transmission Electron Microscopy - Rechberger, Stefanie; Gasparini, Nicola; Singh, Ranbir; Kim, Min; Chochos, Christos L.; Gregoriou, Vasilis G.; Cho, Kilwon; Brabec, Christoph; Ameri, Tayebeh; Spiecker, Erdmann (Solar RRL, 2020)
Elucidating the complex materials distribution in the active layers of ternary organic solar cells is one of the greatest challenges in the field of organic photovoltaics. Knowledge of the nanomorphology is key to understanding photophysical processes (e.g., charge separation, adjustment of the recombination mechanism, and suppression of the radiationless and energetic losses) and thus improving the device performance. Herein, for the first time, the successful discrimination and spatial mapping of the active layer components of a ternary organic solar cell are demonstrated using analytical transmission electron microscopy. The material distribution of all three organic components is successfully visualized by multimodal imaging using complementary electron energy loss signals. A complete picture of the morphological aspects can be gained by studying the lateral and cross-sectional morphology as well as the morphology evolution as a function of the mixing ratio of the polymers. Finally, a correlation between the morphology, photophysical processes, and device performance of the ternary and the reference binary system is achieved, explaining the differences of the power conversion efficiency between the two systems.
CRIS-Team Scopus Importer:2020-04-21
Keywords: device performance; energy-filtered transmission electron microscopy; morphology; ternary organic solar cells; transmission electron microscopy

Unraveling the influence of non-fullerene acceptor molecular packing on photovoltaic performance of organic solar cells - Ye, Linglong; Weng, Kangkang; Xu, Jinqiu; Du, Xiaoyan; Chandrabose, Sreelakshmi; Chen, Kai; Zhou, Jiadong; Han, Guangchao; Tan, Songting; Xie, Zengqi; Yi, Yuanping; Li, Ning; et al. (Nature Communications, 2020)
In non-fullerene organic solar cells, the long-range structure ordering induced by end-group π–π stacking of fused-ring non-fullerene acceptors is considered as the critical factor in realizing efficient charge transport and high power conversion efficiency. Here, we demonstrate that side-chain engineering of non-fullerene acceptors could drive the fused-ring backbone assembly from a π–π stacking mode to an intermixed packing mode, and to a non-stacking mode to refine its solid-state properties. Different from the above-mentioned understanding, we find that close atom contacts in a non-stacking mode can form efficient charge transport pathway through close side atom interactions. The intermixed solid-state packing motif in active layers could enable organic solar cells with superior efficiency and reduced non-radiative recombination loss compared with devices based on molecules with the classic end-group π–π stacking mode. Our observations open a new avenue in material design that endows better photovoltaic performance.
CRIS-Team Scopus Importer:2020-12-04

Unraveling the Microstructure-Related Device Stability for Polymer Solar Cells Based on Nonfullerene Small-Molecular Acceptors - Du, Xiaoyan; Heumüller, Thomas; Gruber, Wolfgang; Almora, Osbel; Classen, Andrej; Qu, Jianfei; He, Feng; Unruh, Tobias; Li, Ning; Brabec, Christoph (Advanced Materials, 2020)
As the power conversion efficiency (PCE) of organic solar cells (OSCs) has surpassed the 17% baseline, the long-term stability of highly efficient OSCs is essential for the practical application of this photovoltaic technology. Here, the photostability and possible degradation mechanisms of three state-of-the-art polymer donors with a commonly used nonfullerene acceptor (NFA), IT-4F, are investigated. The active-layer materials show excellent intrinsic photostability. The initial morphology, in particular the mixed region, causes degradation predominantly in the fill factor (FF) under illumination. Electron traps are formed due to the reorganization of polymers and diffusion-limited aggregation of NFAs to assemble small isolated acceptor domains under illumination. These electron traps lead to losses mainly in FF, which is in contradistinction to the degradation mechanisms observed for fullerene-based OSCs. Control of the composition of NFAs close to the thermodynamic equilibrium limit while keeping adequate electron percolation and improving the initial polymer and NFA ordering are of the essence to stabilize the FF in NFA-based solar cells, which may be the key tactics to develop next-generation OSCs with high efficiency as well as excellent stability.
CRIS-Team Scopus Importer:2020-03-10
Keywords: bulk-heterojunction microstructure; morphology stability; nonfullerene acceptors; organic solar cells; photostability

Unraveling the Role of Non-Fullerene Acceptor with High Dielectric Constant in Organic Solar Cells - Zhang, Yue; He, Yakun; Zeng, Liang; Lüer, Larry; Deng, Wanyuan; Chen, Yuting; Zhou, Jiadong; Wang, Zhiqiang; Brabec, Christoph; Wu, Hongbin; Xie, Zengqi; Duan, Chunhui (Small, 2023)
Increasing the relative dielectric constant is a constant pursuit of organic semiconductors, but it often leads to multiple changes in device characteristics, hindering the establishment of a reliable relationship between dielectric constant and photovoltaic performance. Herein, a new non-fullerene acceptor named BTP-OE is reported by replacing the branched alkyl chains on Y6-BO with branched oligoethylene oxide chains. This replacement successfully increases the relative dielectric constant from 3.28 to 4.62. To surprise, BTP-OE offers consistently lower device performance relative to Y6-BO in organic solar cells (16.27% vs 17.44%) due to the losses in open-circuit voltage and fill factor. Further investigations unravel that BTP-OE has resulted in reduced electron mobility, increased trap density, enhanced first order recombination, and enlarged energetic disorder. These results demonstrate the complex relationship between dielectric constant and device performance, which provide valuable implications for the development of organic semiconductors with high dielectric constant for photovoltaic application.
CRIS-Team Scopus Importer:2023-05-26
Keywords: dielectric constant; energetic disorder; first order recombination; non-fullerene acceptors; organic solar cells

Unravelling material properties of halide perovskites by combined microwave photoconductivity and time-resolved photoluminescence spectroscopy - Kupfer, Christian; Le Corre, Vincent Marc; Li, Chaohui; Lüer, Larry; Forberich, Karen; Kato, Masashi; Osvet, Andres; Brabec, Christoph (Journal of Materials Chemistry C, 2024)
To take advantage of the huge compositional space of metal halide perovskites, a reliable and fast characterization method is required. By combining time-resolved photoluminescence (trPL) with microwave photoconductivity measurements, we are able to rapidly extract fundamental material properties of promising perovskite materials from bare films. This is achieved by incorporating a rate-equation model into a fitting algorithm based on Bayesian optimization to globally fit the experimental results. Including microwave photoconductivity measurements into our analysis significantly enhances the accuracy of estimating recombination rate constants. Additionally, it grants us the ability to determine the ratio of electron and hole mobilities, a crucial charge transport property that cannot be obtained solely through time-resolved photoluminescence measurements. Furthermore, the high sensitivity of microwave photoconductivity measurements to long-lived trap states yields information about the trap-assisted recombination, which is a major source of efficiency loss for solar devices and is difficult to assess from pure trPL measurements. In this work, we introduce the fundamental principles of microwave photoconductivity, along with the employed rate-equation model and fitting techniques. We then outline the procedure for conducting measurements and extracting the recombination rate constants, trap density, and mobility ratio. Subsequently, we highlight the benefits of combining both methods through a comparison of results from fits using only trPL with those from fits incorporating combined signals on a simulated dataset. We also discuss the merits of conducting intensity-dependent measurements. Finally, we present the annealing-dependent results obtained from a highly relevant triple-cation, mixed-halide perovskite, FA0.82MA0.13Cs0.05Pb(I0.87Br0.13)3, as an application example, where we uncover the presence of long-lived traps beyond 10 μs.
Created from Fastlane, Scopus look-up

Unveiling the Role of BODIPY Dyes as Small-Molecule Hole Transport Material in Inverted Planar Perovskite Solar Cells - Seoneray, Isabel; Wu, Jianchang; Rocha-Ortiz, Juan S.; Bornschlegl, Andreas; Barabash, Anastasiia; Wang, Yunuo; Lüer, Larry; Hauch, Jens; García, Angélica; Zapata-Rivera, Jhon; Brabec, Christoph J.; Ortiz, Alejandro (Solar RRL, 2024)
Perovskite solar cells (PSCs) have become a research hotspot since their dramatic increase in power conversion efficiency (PCE), surpassing 26% due to advances in cell engineering and interfacial layers. Within the last factor, hole transporting materials play a crucial role in enhancing device performance and stability. Among several molecular building blocks, BODIPYs are attractive for the design of novel hole transporting material (HTMs) due to their outstanding photophysical and charge transport properties easily tuned by synthetic modifications. Herein, the synthesis of five new BODIPY-based HTMs PyBDP 1–5 are reported, functionalized at the meso- and α- positions with pyrenyl and arylamino units, respectively. The resulting compounds exhibit broad absorption in the visible region, remarkable thermal stability, narrow bandgaps, suitable energy levels, and good hole extraction capability, as subtracted from experimental and computational characterizations. The performance of the BODIPY derivatives as HTMs is evaluated in planar inverted (p-i-n) PSCs and compared to commonly used PTAA, resulting in highly efficient systems, reaching PCEs very close to that obtained with the reference polymer (21.51%). The incorporation of these BODIPY-based HTMs result in an outstanding PCE of 20.37% for devices including PyBDP-1 and 19.97% for devises containing PyBDP-3, thus demonstrating that BODIPY derivatives are a promising alternative to obtain simple and efficient organic HTMs.
CRIS-Team Scopus Importer:2024-05-31
Keywords: arylamine; BODIPY; hole-transporting material; perovskite solar cells; pyrene

Up-conversion semiconducting MoO 3:Yb/Er nanocomposites as buffer layer in organic solar cells - Wang, Hao; Stubhan, Tobias; Osvet, Andres; Litzov, Ivan; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2012)
The spectral sensitivity of organic solar cells can be sensitized in the near-IR and IR by incorporating Yb/Er-doped MoO up-conversion nanocomposites. Poly-3-hexyl thiophene (P3HT) and [6,6] phenyl C butyric acid methyl ester (PC BM) were chosen for the active layer. Yb/Er-doped MoO nanoparticles with dual functionality were solution processed as charge selective interface layer. On the one hand, the electrical functionality of MoO as hole extraction layer is demonstrated. On the other hand, up-conversion emission from Yb sensitized Er dopants in the MoO nanoparticles is observed. Since the photocurrent generated from up-conversion with 975 nm excitation was found to be in competition with photocurrent contributions from a charge transfer complex absorbing also in the near IR, up-conversion from a Yb/Er doped MoO layer within an organic solar cell is proven spectroscopically and demonstrated by analyzing the photocurrent response of the Yb/Er doped cell and the undoped cell to the excitation intensity. The concept to integrate up-conversion functionality into metal oxide (MOx) based charge extraction layer suggests a promising and practical pathway for improving the near IR and IR sensitivity of thin film solar cells. © 2012 Elsevier B.V.
Keywords: Interface layer; Organic solar cell; Solution-processable; Up-conversion semiconducting MoO 3

Upscaling Solution-Processed Perovskite Photovoltaics - Yang, Fu; Jang, DongJu; Dong, Lirong; Qiu, Shudi; Distler, Andreas; Li, Ning; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Energy Materials, 2021)
The performance of hybrid organic–inorganic perovskite solar cells has reached a certified efficiency of 25.5% over the past decade, which has attracted significant attention as a promising candidate for photovoltaic (PV) applications. However, the most efficient perovskite solar cells were produced by the technique of spin coating, which is extremely limited in terms of upscaling production for the commercialization of the technology. Furthermore, the efficiencies of large-area perovskite modules are still significantly lower than those of lab size solar cells. Thus, there are still some challenges that need to be overcome to bridge the efficiency gap between small-area perovskite solar cells and large-area perovskite devices. The first challenge lies in preparing high-quality perovskite layers by low-cost and scalable techniques with high reproducibility. Second, selecting and depositing charge extraction layers as well as bottom and top electrodes by scalable and low-cost techniques are essential tasks. In this review, recent progress and challenges of scalable technologies for solution-based coating and printing of perovskite PVs are summarized and analyzed. Based on the analysis, strategies and opportunities are proposed to promote the development of stable and efficient large-area perovskite PV toward commercialization.
CRIS-Team Scopus Importer:2021-10-22
Keywords: high-efficiency; long-term stability; perovskite photovoltaics; roll-to-roll production; scalable coating

Utilization of Inverter Operating Point Shifts as a Quality Assessment Tool for Photovoltaic Systems - Dalsaß, Manuel; Schmitt, Pascal; Buerhop, Claudia; Luchscheider, Philipp; Hauch, Jens; Brabec, Christoph; Camus, Christian (Ieee Photonics Journal, 2018)
This paper presents a novel approach for the automated identification of electrically impaired strings in photovoltaic (PV) systems, which is solely based on monitored inverter data. By shifting the inverter operating points of two or more strings to a common voltage level on the direct current side, the effect of defects such as bypassed substrings is actively amplified so that defects can be detected reliably. The presented Common Voltage Test is illustrated using an electrical simulation based on the extended two-diode model. The effectiveness of the proposed approach is demonstrated using real monitoring data of an inverter in a PV power plant in Bavaria, Germany. For validation, electrically defective PVmodules within the PV system are identified and located using aerial infrared thermography. Facilitating an automated reliable detection of faulty strings in PV systems, the approach is especially useful for large-scale PV power plants since only the faulty strings need to be examined in greater detail. Consequently, the maintenance becomes more efficient so that the maintenance costs may be reduced significantly.
Keywords: Fault detection; inverters; monitoring; photovoltaic (PV) systems.

Utilizing the unique charge extraction properties of antimony tin oxide nanoparticles for efficient and stable organic photovoltaics - Liu, Chao; Félix, Roberto; Forberich, Karen; Du, Xiaoyan; Heumüller, Thomas; Matt, Gebhard; Gu, Ening; Wortmann, Jonas; Zhao, Yicheng; Cao, Yuanyuan; He, Yakun; Ying, Lei; et al. (Nano Energy, 2021)
Simultaneously enhancing device performance and longevity, as well as balancing the requirements on cost, scalability, and simplification of processing, is the goal of interface engineering of organic solar cells (OSCs). In our work, we strategically introduce antimony (Sb3+) cations into an efficient and generic n-type SnO2 nanoparticles (NPs) host during the scalable flame spray pyrolysis synthesis. Accordingly, a significant switch of conduction property from an n-type character to a p-type character is observed, with a corresponding shift in the work function (WF) from 4.01 ± 0.02 eV for pristine SnO2 NPs to 5.28 ± 0.02 eV for SnO2 NPs with 20 mol. % Sb content (ATO). Both pristine SnO2 and ATO NPs with fine-tuned optoelectronic properties exhibit remarkable charge carrier extraction properties, excellent UV resistance and photo-stability being compatible with various state-of-the-art OSCs systems. The reliable and scalable pristine SnO2 and ATO NPs processed by doctor-blading in air demand no complex post-treatment. Our work offers a simple but unique approach to accelerate the development of advanced interfacial materials, which could circumvent the major existing interfacial problems in solution-processed OSCs.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Antimony doped tin oxide; Doping mechanism; Interface engineering; Metal oxide nanoparticles; Organic photovoltaics

UV emitting single crystalline film scintillators grown by LPE method: Current status and perspective - Zorenko, Yuriy; Gorbenko, Vitaliy; Savchyn, Volodymyr; Voznyak, Taras; Batentschuk, Miroslaw; Winnacker, Albrecht; Xia, Qi; Brabec, Christoph (Materials Research Society Symposium Proceedings, 2012)
This work is dedicated to the development of new type of UV phosphors based on single crystalline films (SCF) of aluminum garnet compounds grown by liquid phase epitaxy (LPE). The development of two types of UV emitting SCF scintillators is reported in this work: 1) Pr-doped SCF of Y-Lu-Al garnet having the intensive Pr f-d luminescence in the 300-400 run spectral ranges with a decay time of about 13-18 ns; 2) SCF of Y-Lu-Al-garnet doped with Sc isoelectronic impurity emitting in the 290-400 nm range due to the formation of the Sc and Sc centers with a luminescence decay time in the order of several hundred ns. © 2011 Materials Research Society.
Keywords: Current status; Decay time; Isoelectronic impurities; Luminescence decay time; Single-crystalline film; Spectral range; UV-Emitting Engineering controlled terms: Aluminum; Crystalline materials; Films; Garnets; Ionization; Luminescence; Scintillation; Scintillation counters Engineering main heading: Phosphors

Verifying Defective PV-Modules by IR-Imaging and Controlling with Module Optimizers - Buerhop, Claudia; Fecher, Frank W.; Pickel, Tobias; Häring, Adrian; Adamski, Tim; Camus, Christian; Hauch, Jens; Brabec, Christoph (33rd European Photovoltaic Solar Energy Conference and Exhibition, 2017)
Quality control and efficient operation of roof-top, residential PV-installations is an economic and technical challenge because these PV-systems often suffer from various roof orientations and inclinations as well as partial and temporal shading. Module optimizers, which track the operating point individually for each module group, are good solutions providing also additional electrical information. The purpose of this work is verifying the identification and localization of defective PVmodules with IR-imaging and with module optimizers as well as quantifying the impact on the performance. Several PV-plants were inspected and carefully analyzed. The findings using IR-imaging can clearly be classified to substring failures due to open circuit and short circuit, bypass-diode faults, cell defect, and some undefined optimizer problems. The electric data reveal that these findings are related to certain power loss and monthly or annual yield reduction. Interesting is the temporal behavior of particular defective sites, which show short-term recovery. In summary, there is a good agreement between the occasionally performed IR-findings and the continuously monitored electrical data.
Keywords: Defects; Monitoring; Yield; IR Imaging; Thermography; Module Optimization/Optimisation

Verifying defective PV-modules by IR-imaging and controlling with module optimizers - Buerhop, Claudia; Fecher, Frank W.; Pickel, Tobias; Häring, Adrian; Adamski, Tim; Camus, Christian; Hauch, Jens; Brabec, Christoph (Progress in Photovoltaics, 2018)
Quality control and efficient operation of roof‐top residential photovoltaic (PV)‐installations is an economic and technical challenge because these PV‐systems often suffer from various roof orientations and inclinations as well as partial and temporal shading. Module optimizers, which track the operating point individually for each module group, are good solutions providing also additional electrical information. The purpose of this work is verifying the identification and localization of defective PV‐modules with infrared (IR)–imaging and with module optimizers as well as quantifying the impact on the performance. Several PV‐plants were inspected and carefully analyzed. The findings using IR‐imaging can clearly be classified to substring failures due to open circuit and short circuit, bypass‐diode faults, cell defect, and some undefined optimizer problems. The electric data reveal that these findings are related to certain power loss and monthly or annual yield reduction. Interesting is the temporal behavior of particular defective sites, which show short‐term recovery. In summary, there is a good agreement between the occasionally performed IR‐findings and the continuously monitored electrical data.
Keywords: Defects; IR-imaging; Module optimizer; Monitoring; Thermography; Yield

Vertically Aligned 2D/3D Pb-Sn Perovskites with Enhanced Charge Extraction and Suppressed Phase Segregation for Efficient Printable Solar Cells - Li, Chaohui; Pan, Yamin; Hu, Jinlong; Qiu, Shudi; Zhang, Cuiling; Yang, Yuzhao; Chen, Shi; Liu, Xianhu; Brabec, Christoph; Nazeeruddin, Mohammad Khaja; Mai, Yaohua; Guo, Fei (ACS Energy Letters, 2020)
The concept of mixed 2D/3D heterostructures has emerged as an effective method for improving the stability of lead halide perovskite solar cells, which has been, however, rarely reported in lead-tin (Pb-Sn) mixed perovskite devices. Here, we report a scalable process for depositing mixed 2D/3D Pb-Sn perovskite solar cells that deliver remarkably enhanced efficiency and stability compared to their 3D counterparts. The incorporation of a small amount (3.75%) of an organic cation 2-(4-fluorophenyl)ethylammonium iodide induces the growth of highly oriented Pb-Sn perovskite crystals perpendicularly aligned with the substrate. Moreover, for the first time, phase segregation is observed in pristine 3D Pb-Sn perovskites, which is suppressed due to the presence of the 2D perovskites. Accordingly, a high current density of 28.42 mA cm(-2) is obtained due to the markedly enhanced spectral response and charge extraction. Eventually, mixed 2D/3D Pb-Sn perovskite devices with a band gap of 1.33 eV yield efficiencies as high as 17.51% and in parallel exhibit good stability.
Created from Fastlane, WoS look-up

Visible and Near-Infrared Imaging with Nonfullerene-Based Photodetectors - Gasparini, Nicola; Gregori, Alberto; Salvador, Michael; Biele, Markus; Wadsworth, Andrew; Tedde, Sandro; Baran, Derya; Mcculloch, Iain; Brabec, Christoph (Advanced Materials Technologies, 2018)
The solution-processed organic photodetectors underpin an emerging technology with inherent implications in the biological sensors and imaging displays. Conventional organic photodiodes, the core element of an organic photodetector, rely mainly on fullerene-based acceptors, which in combination with high and middle bandgap donors, limit the spectral photosensitivity to the visible range. Even in the case of low bandgap polymers the oscillator strength and thus the extinction coefficient are usually limited in the NIR due to the nature of molecular orbital hybridization. Instead, it is showed that pairing prototypical poly(3-hexylthiophene) (P3 HT) with rhodanine-benzothiadiazolecoupled indacenodithiophene (IDTBR), a nonfullerene electron acceptor absorbing beyond 750 nm, as the photoactive material of a simple photodiode results in a highly efficient organic photodetector with a record responsivity of 0.42 A W-1 and external quantum efficiency (EQE) of 69% in the NIR (755 nm) Nonfullerene-based photodiodes are processed on amorphous silicon active matrix backplanes to realize large area flat panel photodetector imagers able to detect objects under visible and NIR light conditions with an exceptional combination of responsivity, dynamic response and image crosstalk.
Keywords: imager; large area devices; near-infrared detection; nonfullerene acceptors; organic photodetectors

Visualizing and Suppressing Nonradiative Losses in High Open-Circuit Voltage n-i-p-Type CsPbI3 Perovskite Solar Cells - Meng, Wei; Hou, Yi; Karl, André; Gu, Ening; Tang, Xiaofeng; Osvet, Andres; Zhang, Kaicheng; Zhao, Yicheng; Du, Xiaoyan; García Cerrillo, José; Li, Ning; Brabec, Christoph (ACS Energy Letters, 2020)
Cesium lead iodide (CsPbI3) has attracted increasing attention for its photovoltaic applications, owing to its thermal stability and suitable band gap for tandem solar cells. However, the severe nonradiative recombination losses in CsPbI3-based perovskite solar cells generally restrict their open-circuit voltage (VOC) to the range of 0.9 to 1.1 V. This work uniquely reports a method to visualize all defect-assisted recombination pathways with photoluminescence (PL) techniques. Visible and valuable insight into the reduction of defect densities on a micrometer scale was obtained by the bottom surface and bulk passivation with barium hydroxide and trioctylphosphine oxide. The dual effects successfully improve the VOC of the solar cell from 0.87 to 1.17 V. These results highlight the potential of hyperspectral PL imaging as a powerful tool to give guidance to further suppress the nonradiative VOC losses in all-inorganic perovskites.
CRIS-Team Scopus Importer:2020-01-21

Visualizing the performance loss of solar cells by IR thermography - an evaluation study on CIGS with artificially induced defects - Vetter, Andreas; Babbe, Finn S.; Hofbeck, Bernhard; Kubis, Peter; Richter, Michael; Heise, Stephan J.; Ohland, Joerg; Riedel, Ingo; Brabec, Christoph (Progress in Photovoltaics: Research and Applications, 2016)
Local electric defects may result in considerable performance losses in solar cells. Infrared (IR) thermography is one important tool to detect these defects on photovoltaic modules. Qualitative interpretation of IR images has been carried out successfully, but quantitative interpretation has been hampered by the lack of “calibration” defects. The aims of this study are to (i) establish methods to induce well-defined electric defects in thin-film solar cells serving as “calibration” defects and to (ii) assess the accuracy of IR imaging methods by using these artificially induced defects. This approach paves the way for improving quality control methods based on imaging in photovoltaic. We created ohmic defects (“shunts”) by using a focused ion beam and weak diodes (“interface shunts”) by applying a femto-second laser at rather low power on copper indium gallium selenide cells. The defects can be induced precisely and reproducibly, and the severity of the defects on the electrical performance can be well adjusted by focused ion beam/laser parameters. The successive assessment of the IR measurement (ILIT-Voc) revealed that this method can predict the losses in P (maximal power extractable) with a mean error of below 10%. Copyright Â© 2016 John Wiley & Sons, Ltd.
Keywords: defects; imaging; perfomance; PV modules

Volatile Perovskite Precursor Ink Enables Window Printing of Phase-Pure FAPbI3 Perovskite Solar Cells and Modules in Ambient Atmosphere - Yuan, Linhao; Chen, Xining; Guo, Xianming; Huang, Shihao; Wu, Xiaoxiao; Shen, Yunxiu; Gu, Hao; Chen, Yujin; Zeng, Guixiang; Egelhaaf, Hans-Joachim; Brabec, Christoph; Yang, Fu; et al. (Angewandte Chemie International Edition, 2024)
Despite the great success of perovskite photovoltaics in terms of device efficiency and stability using laboratory-scale spin-coating methods, the demand for high-throughput and cost-effective solutions remains unresolved and rarely reported because of the complicated nature of perovskite crystallization. In this work, we propose a stable precursor ink design strategy to control the solvent volatilization and perovskite crystallization to enable the wide speed window printing (0.3 to 18.0 m/min) of phase-pure FAPbI3 perovskite solar cells (pero-SCs) in ambient atmosphere. The FAPbI3 perovskite precursor ink uses volatile acetonitrile (ACN) as the main solvent with DMF and DMSO as coordination additives is beneficial to improve the ink stability, inhibit the coffee rings, and the complicated intermediate FAPbI3 phases, delivering high-quality pin-hole free and phase-pure FAPbI3 perovskite films with large-scale uniformity. Ultimately, small-area FAPbI3 pero-SCs (0.062 cm2) and large-area modules (15.64 cm2) achieved remarkable efficiencies of 24.32 % and 21.90 %, respectively, whereas the PCE of the devices can be maintained at 23.76 % when the printing speed increases to 18.0 m/min. Specifically, the unencapsulated device exhibits superior operational stability with T90>1350 h. This work represents a step towards the scalable, cost-effective manufacturing of perovskite photovoltaics with both high performance and high throughput.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Large-Area Printing; Perovskite Solar Cells; Solar Module; Volatile Solvent; Wide Speed Window

Washing away barriers - Li, Ning; Brabec, Christoph (Nature Energy, 2017)
Light-weight and stretchable, organic photovoltaics offer unique integration prospects. Now, organic solar cells and modules can also be washed while maintaining good photoconversion efficiencies. © 2017 The Publisher

Water ingress in encapsulated inverted organic solar cells: Correlating infrared imaging and photovoltaic performance - Adams, Jens; Salvador, Michael Filipe; Lucera, Luca; Langner, Stefan; Spyropoulos, George D.; Fecher, Frank; Voigt, Monika; Dowland, Simon A.; Osvet, Andres; Egelhaaf, Hans-Joachim; Brabec, Christoph (Advanced Energy Materials, 2015)
Understanding the degradation and failure mechanisms of organic photovoltaic devices is a key requirement for this technology to mature toward a reliable product. Here, an investigation on accelerated temperature and moisture long-term stability testing (>20 000 h) of inverted and glass-encapsulated poly(3-hexylthiophene)/phenyl-C-butyric acid methyl ester solar cells is presented. The degradation kinetics is analyzed using the Arrhenius model and the resulting activation energy for the diffusion of water is measured to be ≈43 kJ mol. Through comparison of electroluminescence imaging, lock-in thermography, and photoluminescence mapping, the device performance is correlated with the loss of effective cell area and it is shown that the reaction of water at the hole extraction/active layer interface is likely to be the dominant cause for long-term device failure. The diffusion of water through the packaged solar cell is described using classical diffusion theory. Based on an analytical solution of a simple diffusion model, the diffusion coefficient is estimated to be 4 × 10 m s. A shelf life of 100 000 h is anticipated at 65 °C/85% RH using a 9.3 cm wide protective adhesive rim. The findings of this study may inform strategies for predicting lifetimes of organic solar cells and modules based on local in situ tracking of moisture-induced device performance loss using IR imaging. Lifetime limitations of current-generation inverted and encapsulated organic solar cells under damp heat conditions are identified by correlating photovoltaic device performance with lock-in IR imaging techniques. The combination of electroluminescence imaging and water diffusion modeling may inform strategies for predicting early performance losses in solar cells and modules.
Keywords: electroluminescence imaging; lock-in thermography; long-term stability; organic photovoltaics; water diffusion

Wirtschaftlichkeitsbetrachtung von Haushaltsspeichern und realdatengestützte Untersuchung des elektrischen Eigenverbrauchs von PV-Strom - Stegner, Christoph; Bogenrieder, Josef; Auer, Sebastian; Luchscheider, Philipp; German, Reinhard; Brabec, Christoph (Nachhaltige Energieversorgung und Integration von Speichern: Tagungsband zur NEIS 2015, 2015)
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.IMMD7.wirtsc

X-ray Diffraction, Micro-Raman and X-ray Photoemission Spectroscopic Investigations for Hydrothermally Obtained Hybrid Compounds of Delafossite CuGaO2 and Wurtzite ZnO - Choi, Minuk; Brabec, Christoph; Hayakawa, Tomokatsu (Ceramics, 2022)
P-type delafossite CuGaO2 is a wide-bandgap semiconductor for optoelectronic applications, and its lattice parameters are very similar to those of n-type semiconductor wurtzite ZnO. Accordingly, the investigation of crystalline heterostructures of CuGaO2 and ZnO has attracted significant attention. In this study, interfacial CuGaO2/ZnO hetero-compounds were examined through X-ray diffraction (XRD) analysis, confocal micro-Raman spectroscopy, and X-ray photo-electron spectroscopy (XPS). XRD and Raman analysis revealed that the hydrothermal deposition of ZnO on hexagonal platelet CuGaO2 base crystals was successful, and the subsequent reduction process could induce a unique, unprecedented reaction between CuGaO2 and ZnO, depending on the deposition parameters. XPS allowed the comparison of the binding energies (peak position and width) of the core level electrons of the constituents (Cu, Ga, Zn, and O) of the pristine CuGaO2 single crystallites and interfacial CuGaO2/ZnO hybrids. The presences of Cu2+ ions and strained GaO6 octahedra were the main characteristics of the CuGaO2/ZnO hybrid interface. The XPS and modified Auger parameter analysis gave an insight into a specific polarization of the interface, promising for further development of CuGaO2/ZnO hybrids.
CRIS-Team WoS Importer:2023-01-13

X-ray imaging: Perovskites target X-ray detection - Heiß, Wolfgang; Brabec, Christoph (Nature Photonics, 2016)
Single crystals of perovskites are currently of interest to help fathom fundamental physical parameters limiting the performance of perovskite-based polycrystalline solar cells. Now, such perovskites offer a technology platform for optoelectronic devices, such as cheap and sensitive X-ray detectors.
Keywords: Sensors and biosensors; X-rays

X-ray imaging with scintillator-sensitized hybrid organic photodetectors - Buechele, Patric; Richter, Moses; Tedde, Sandro F.; Matt, Gebhard; Ankah, Genesis N.; Fischer, Rene; Biele, Markus; Metzger, Wilhelm; Lilliu, Samuele; Bikondoa, Oier; Macdonald, J. Emyr; Brabec, Christoph; et al. (Nature Photonics, 2015)
Medical X-ray imaging requires cost-effective and high-resolution flat-panel detectors for the energy range between 20 and 120€...keV. Solution-processed photodetectors provide the opportunity to fabricate detectors with a large active area at low cost. Here, we present a disruptive approach that improves the resolution of such detectors by incorporating terbium-doped gadolinium oxysulfide scintillator particles into an organic photodetector matrix. The X-ray induced light emission from the scintillators is absorbed within hundreds of nanometres, which is negligible compared with the pixel size. Hence, optical crosstalk, a limiting factor in the resolution of scintillator-based X-ray detectors, is minimized. The concept is validated with a 256 × 256 pixel detector with a resolution of 4.75€...lp mm '1 at a MTF = 0.2, significantly better than previous stacked scintillator-based flat-panel detectors. We achieved a resolution that proves the feasibility of solution-based detectors in medical applications. Time-resolved electrical characterization showed enhanced charge carrier mobility with increased scintillator filling, which is explained by morphological changes.
Keywords: Engineering controlled terms: Cost effectiveness; Medical applications; Medical imaging; Photodetectors; Photons; Pixels; X ray analysis Electrical characterization; Flat panel detectors; Gadolinium oxysulfides; Medical X-ray imaging; Morphological changes; Optical cross-talk; Organic photodetector; Solution-processed Engineering main heading: Scintillation counters

Zellrisse - nur halb so schlimm? - Buerhop-Lutz, Claudia; Pickel, Tobias; Bemm, Andreas; Vodermayer, Christian; Glück, Bernhard; Huber, Alexander; Camus, Christian; Hauch, Jens; Brabec, Christoph (pv magazine Deutschland, 2017)
Das Wichtigste in Kürze Ein Autorenteam hat mit Zellrissen behaftete Module ein Jahr lang in einer Outdooranlage untersucht. Die Performance dieser Module war trotz Stürmen und Schnee nicht geringer als die einer Kontrollgruppe. Die Elektrolumineszenzaufnahmen zeigen, dass nach einem Jahr weder die Anzahl der Zellrisse erhöht war noch ihre Ausprägung zugenommen hatte. Die Autoren schließen daraus, dass vorhandene Zellrisse sich nicht notwendigerweise negativ auf das Degradationsverhalten auswirken und sie daher für den Betrieb weniger schlimm sind als landläufig angenommen. Ein signifikanter Einfluss auf die Stabilität der Module unter Realbedingungen konnte im Rahmen des Versuchs nicht festgestellt werden.